Associations of dietary protein and amino acid intakes with disability-adjusted life years for Alzheimer's disease in Japanese people. - Ishikawa-Takata, Kazuko; Fujiwara, Kazuki; Tanaka, Takayuki; Nakamura, Keiji; Kobayashi, Hisamine; Okada, Shinobu (J Alzheimers Dis, 2025)
BackgroundThe number of patients with dementia is increasing worldwide. In Japan, dementia is the most significant reason recognized for people requiring nursing care. Protein is one of the possible preventive nutrients for dementia; however, adequate intake levels can differ according to usual protein intakes and protein sources.ObjectiveThis study examined the relationships between disability-adjusted life years (DALYs) for Alzheimer's disease and protein or amino acid intakes.MethodsGlobal Burden of Disease Study data (DALYs for each sex and age group in each year) and de-identified individual records from the National Health and Nutrition Survey Japan (data from 46,831 subjects) from 2001 to 2019 were used. Multiple regression analyses were conducted to assess the relationships between DALYs and protein or amino acid intakes with lifestyle factors and sociodemographic index as confounding factors.ResultsHigher protein-to-energy ratios were correlated with lower DALYs in women in their 70 s (partial regression coefficient [Coeff.] = -349.488,  = 0.034), in men in their 60 s (Coeff. = -51.484), and in both sexes combined in their 60 s (Coeff. = -26.696,  = 0.015) even after adjusting for other possible nutrient intakes. Additionally, elevated isoleucine, lysine, tyrosine, histidine, arginine, alanine, asparagine, and glycine levels were correlated with lower DALYs in women in their 70 s (Coeff. = -2.752 to -0.141).ConclusionsAdequate protein and specific amino acid intakes may be associated with DALYs for Alzheimer's disease.

Brain-penetrant histone deacetylase inhibitor RG2833 improves spatial memory in females of an Alzheimer's disease rat model. - Ndukwe, Kelechi; Serrano, Peter A; Rockwell, Patricia; Xie, Lei; Figueiredo-Pereira, Maria E (J Alzheimers Dis, 2025)
BACKGROUND: Nearly two-thirds of Alzheimer's disease (AD) patients are women. Therapeutics for women are critical to lowering their elevated risk of developing this major cause of adult dementia. Moreover, targeting epigenetic processes such as histone acetylation that regulate multiple cellular pathways is advantageous given the multifactorial nature of AD. Histone acetylation takes part in memory consolidation, and its disruption is linked to AD. OBJECTIVE: Determine whether the investigational drug RG2833 has repurposing potential for AD. RG2833 is a histone deacetylase HDAC1/3 inhibitor that is orally bioavailable and permeates the blood-brain-barrier. METHODS: RG2833 effects were determined on cognition, transcriptome, and AD-like pathology in 11-month TgF344-AD female and male rats. Treatment started early in the course of pathology when therapeutic intervention is predicted to be most effective. RESULTS: RG2833-treatment of 11-month TgF344-AD rats: (1) Significantly improved hippocampal-dependent spatial memory in females but not males. (2) Upregulated expression of immediate early genes, such as Arc, Egr1 and c-Fos, and other genes involved in synaptic plasticity and memory consolidation in females. Remarkably, out of 17,168 genes analyzed for each sex, no significant changes in gene expression were detected in males at p < 0.05, false discovery rate <0.05, and fold-change equal or > 1.5. (3) Failed to improve amyloid beta accumulation and microgliosis in female and male TgF344-AD rats. CONCLUSIONS: Our study highlights the potential of histone-modifying therapeutics such as RG2833 to improve cognitive behavior and drive the expression of immediate early, synaptic plasticity and memory consolidation genes, especially in female AD patients.

Cost-effectiveness of diagnosing and treating patients with early Alzheimer's disease with anti-amyloid treatment in a clinical setting. - Wimo, Anders; Handels, Ron; Blennow, Kaj; Kirsebom, K Bjørn-Eivind; Selnes, Per; Bon, Jaka; Emersic, Andreja; Gonzalez-Ortiz, Fernando; Gregoric Kramberger, Milica; Sköldunger, Anders; Speh, Andreja; Timón-Reina, Santiago; et al. (J Alzheimers Dis, 2025)
BackgroundThe introduction of anti-amyloid treatments (AAT) for Alzheimer's disease (AD) has put the cost-effectiveness into focus.ObjectiveEstimate the potential cost-effectiveness of diagnostic pathways combined with AAT for early AD.MethodsDiagnostic accuracy of blood-based (BBM) and cerebrospinal fluid (CSF) biomarkers was obtained from Norwegian memory clinics using positron emission tomography (PET) as reference standard. In a health-economic model, the cost-effectiveness of three diagnostic strategies was estimated relying either on BBM (p-tau 217), CSF (Aβ ratio), and BBM with CSF confirmatory testing and compared with standard of care (SoC) and compared with CSF-AAT. The model consisted of a decision tree reflecting the diagnostic process and a subsequent Markov cohort model starting at mild cognitive impairment due to AD. All strategies except SoC were combined with AAT including costs of treatment (assumed €5000/year), infusions and monitoring.ResultsCompared with SoC all three strategies (CSF-AAT, BBM-AAT, and BBM-CSF-AAT) resulted in QALY gains at higher costs, with an incremental cost-effectiveness ratio (ICER) of 110k€, 141k€ and 110k€ respectively. Compared with CSF-AAT both BBM-AAT and BBM-CSF-AAT strategies resulted in QALYs lost at lower costs, with an ICER of 27k€ and 109k€ respectively. Results were particularly sensitive to the price of AAT and possible subcutaneous administration.ConclusionsCompared with SoC all three strategies are potentially not cost-effective as they exceeded the Swedish maximum willingness to pay threshold of €94,800 per QALY gained. BBM-CSF-AAT versus CSF-AAT is potentially cost-effective if willing to accept its QALY loss. Discussions on budget impact on different payers are needed after introducing AAT.

DNA methylation age acceleration is associated with incident cognitive impairment in the health and retirement study. - Blostein, Freida; Bakulski, Kelly M; Fu, Mingzhou; Wang, Herong; Zawistowski, Matthew; Ware, Erin B (J Alzheimers Dis, 2025)
BackgroundDNA methylation clocks have emerged as promising biomarkers for cognitive impairment and dementia. Longitudinal studies exploring the association between DNA methylation clocks and cognitive decline have been constrained by limited sample sizes and a lack of diversity.ObjectiveOur study aimed to investigate associations between DNA methylation clocks and incident cognitive impairment using a larger and US nationally-representative sample from the Health and Retirement Study.MethodsWe measured DNA methylation age acceleration in 2016 by regressing the DNA methylation clocks, including GrimAge, against chronological age. Cognitive change over time was determined by Langa-Weir cognition status from 2016 to 2018. Multivariable logistic regression evaluated the association between DNA methylation age acceleration and cognitive change, adjusting for cell-type proportions, demographic, and health factors. We also applied inverse probability weighting to address potential selection bias from varying loss-to-follow-up rates.ResultsThe analytic sample (N = 2713) was 54% female, 8.4% Black/African American, 86% White, 7.5% Hispanic, and 68 years old at baseline. During the two years of follow-up, 12% experienced cognitive change and had higher baseline GrimAge (mean = 1.2 years) acceleration compared to those maintaining normal cognition (mean = -0.8 years). A one-year increase in GrimAge acceleration was associated with 1.05 times higher adjusted and survey-weighted odds of cognitive change during follow-up (95% CI: 1.01-1.10). This association was consistent after accounting for loss-to-follow-up (OR = 1.07, 95% CI: 1.04-1.11).ConclusionsOur study offers insights into DNA methylation age acceleration associated with cognitive change over time, suggesting avenues for improved prevention, diagnosis, and treatment.

Down syndrome and Alzheimer's disease: Oxidative stress in the neurodegenerative process. - Cordeiro, Augusto Magno Tranquezi; Singulani, Monique Patricio; Talib, Leda Leme; Forlenza, Orestes Vicente (J Alzheimers Dis, 2025)
BACKGROUND: Individuals with Down syndrome (DS) generally show neuropathological features of Alzheimer disease (AD). The trisomy of chromosome 21 causes an imbalance of antioxidant systems, which can be linked to AD pathophysiology. OBJECTIVE: Verify the difference between the activity of antioxidant enzymes and products of the oxidation process in peripheral blood in non-trisomic (NT) and trisomic (DS) adults and elders and respective associations with cognitive impairment. METHODS: A total of 120 subjects were included in this study. Sociodemographic and clinical information were collected as per protocol for participants in DS and NT groups. The cognitive state of the DS participants was established according to the Brazilian version of the Cambridge Examination for Mental Disorders of Older People with Down's syndrome and Others with Intellectual Disabilities (CAMDEX-DS). The CAMDEX interview was used for this purpose for participants in the NT group. Plasma samples were collected to evaluate protein carbonyl content, superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT), malondialdehyde (MDA), and 4-hydroxy-2-nonenal (HNE). RESULTS: We found increased levels of SOD and CAT activity in the DS group. When the groups were stratified by cognitive decline, elevated levels of SOD and CAT activity were found both in DS groups with and without decline. The activity of GPx was similar between the groups, as well as MDA and HNE. CONCLUSION: The results suggest that alterations of the antioxidative processes can be implicated in the onset of neurodegeneration observed in individuals with DS.

Factors associated with a healthy diet and willingness to change dietary behavior in older adults at increased risk of dementia. - Blotenberg, Iris; Zülke, Andrea E; Luppa, Melanie; Wittmann, Felix; Fankhänel, Thomas; Weise, Solveig; Döhring, Juliane; Escales, Catharina; Kosilek, Robert P; Michel, Irina; Brettschneider, Christian; Oey, Anke; et al. (J Alzheimers Dis, 2025)
BackgroundHealthy dietary patterns have been linked to reduced risks for cardiovascular diseases and dementia, making nutrition an essential part of a comprehensive approach for dementia prevention. Knowledge about factors associated with a healthy diet in people with increased dementia risk is scarce.ObjectiveTo analyze dietary habits and associated factors in older adults with increased dementia risk in Germany.MethodsWe used baseline-data of the AgeWell.de-trial (n = 1001, %= 52.2, M= 69.0, SD = 4.9). Nutrition was assessed using a composite score, comprising 11 components covered by national recommendations for a healthy diet (range = 0-11 points). Linear regressions assessed associations of sociodemographic, social, health-related and psychological factors with consumption of a healthy diet. Further, we assessed stages of change based on the transtheoretical model of behavior change.ResultsConsumption of a healthy diet was moderate (Median = 4, IQR = 2). Female sex (b = 0.64, 95% CI: 0.41, 0.88), higher levels of motivation for healthy eating (b = 0.22, 95% CI: 0.10, 0.34) and higher self-efficacy (b = 0.33, 95% CI: 0.20, 0.46) were linked to a healthy diet. Regarding the stages of behavior change, the majority were in the maintenance stage (45.2%), followed by the contemplation (21.5%) and precontemplation (21.2%) stages.ConclusionsResults suggest room for improvement regarding a healthy diet in our sample. Lifestyle-based interventions in older adults should be tailored towards current levels of motivation and self-efficacy of participants. Including modules targeting motivation and self-efficacy might help maximize intervention effectiveness.

Iron chelation by oral deferoxamine treatment decreased brain iron and iron signaling proteins. - Thorwald, Max A; Sta Maria, Naomi S; Chakhoyan, Ararat; O'Day, Peggy A; Jacobs, Russell E; Zlokovic, Berislav; Finch, Caleb E (J Alzheimers Dis, 2025)
BACKGROUND: Deferoxamine (DFO) and other iron chelators are clinically used for cancer and stroke. They may also be useful for Alzheimer's disease (AD) to diminish iron from microbleeds. DFO may also stimulate antioxidant membrane repair which is impaired during AD. DFO and other chelators do enter the brain despite some contrary reports. OBJECTIVE: Low dose, oral DFO was given in lab chow to wildtype (WT) C57BL/6 mice to evaluate potential impact on iron levels, iron-signaling and storage proteins, and amyloid-β protein precursor (AβPP) and processing enzymes. Young WT mice do not have microbleeds or disrupted blood-brain barrier of AD mice. METHODS: Iron was measured by MRI and chemically after two weeks of dietary DFO. Cerebral cortex was examined for changes in iron metabolism, antioxidant signaling, and AβPP processing by western blot. RESULTS: DFO decreased brain iron 18% ( < 0.01) estimated by R2 MRI and decreased seven major proteins that mediate iron metabolism by at least 25%. The iron storage proteins ferritin light and heavy chain decreased by at least 30%. AβPP and secretase enzymes also decreased by 30%. CONCLUSIONS: WT mice respond to DFO with decreased AβPP, amyloid processing enzymes, and antioxidant repair. Potential DFO treatment for early-stage AD by DFO should consider the benefits of lowered AβPP and secretase enzymes.

Lifespan of male and female APP/PS1 and APP mouse models of Alzheimer's disease. - Roberts, Hannah; Fang, Yimin; Quinn, Kathleen; Hill, Tiarra; Peck, Mackenzie R; Bartke, Andrzej; Hascup, Kevin N; Hascup, Erin R (J Alzheimers Dis, 2025)
Alzheimer's disease (AD) disproportionately affects women, yet most preclinical research studies are male-centric. We performed lifespan analyses of male and female AD mouse models (APP/PS1 and APP) and their shared genetic background control (C57BL/6). Survival curves support significant sex differences between genotypes. Minimal longevity revealed increased age in male APP/PS1, and decreased age in male APP mice. Maximal longevity revealed an increased average age in males. Furthermore, median lifespan differed between sex and genotype. This study supports dimorphic survival in two mouse models of AD, emphasizing the need to examine mechanisms and treatments in both sexes.

Performance of a smell identification test versus the Mini-Mental Status Exam for the detection of dementia and cognitive impairment among persons with cognitive concerns in primary care. - Luchsinger, Jose A; Teresi, Jeanne A; Valdez, Lenfis; Rosario, Dahiana; de Miguel, Maria; Taylor, Delphine; Singer, Jessica; Chang, Nancy; Fuller, William S; Boquín, Cyrus; Silver, Stephanie; Eimicke, Joseph P; et al. (J Alzheimers Dis, 2025)
BackgroundOdor identification deficits predict Alzheimer's disease (AD) in epidemiological studies.ObjectiveTo compare the accuracy of a short odor identification test with a short cognitive screening test for the detection of dementia and cognitive impairment in elderly persons with cognitive concerns.MethodsThis was a cross-sectional study of 600 participants 65 years and older, without known mild cognitive impairment (MCI) or dementia, with cognitive concerns, attending primary care practices in New York City. The odor identification test was the Brief Smell Identification Test (BSIT). The comparator test was the Mini Mental Status Exam II (MMSE). Cognitive diagnoses were made using the National Alzheimer's Coordinating Center Uniform Data set (NACC-UDS) version 3 forms with slight modifications. Test performance was compared using Receiver Operating Characteristic analyses.ResultsThe mean age was 72.65 ± 6.31 years, 73.3% were female, 63.3% were Hispanic, 13.5% non-Hispanic Black, and 20.8% non-Hispanic White; 23.5% were classified as normal cognition, 27.7% as cognitive impairment-not mild cognitive impairment (MCI), 31.2% as amnestic MCI, 5.7% as non-amnestic MCI, and 12% as dementia. The MMSE was superior to the BSIT in detecting dementia and any cognitive impairment. Combining abnormal scores in the BSIT (≤8) to MMSE (≤24) improved the MMSE's specificity and positive predictive value (PPV) in detecting cognitive impairment.ConclusionsThe MMSE was superior to the BSIT in detecting dementia and cognitive impairment in primary care but using both tests improved specificity and PPV for identifying persons with subjective complaints needing further cognitive and biomarker evaluation.

Social isolation, loneliness, genetic risk, and incident dementia in people with type 2 diabetes mellitus: A population-based cohort study. - He, Zhixuan; Nie, Yu; Zhang, Weijie; Liu, Yue; Liu, Yaping; Xue, Huachen; Ai, Sizhi; Feng, Hongliang; Zhou, Yujing; Zhang, Jihui; Liang, Yan Yannis; Ning, Yuping (J Alzheimers Dis, 2025)
BackgroundSocial isolation and loneliness, two independent constructs of social disengagement, are becoming increasingly recognized factors for dementia risk.ObjectiveWe aimed to investigate whether these two constructs also associate with dementia risk in individuals with type 2 diabetes mellitus (T2DM), which is becoming more prevalent.MethodsThe longitudinal study included 24,986 participants (mean age: 60.0 ± 6.9 years, median follow-up: 12.0 years) with T2DM at baseline from the UK Biobank. Social isolation and loneliness were assessed using self-reported questionnaires. Genetic risk factors for dementia including polygenic risk score (PRS) and genotype were extracted. We identified incident dementia cases by linking hospital records and death registries.ResultsSocial isolation (most versus least: hazard ratio, HR: 1.46 [95% confidence intervals, CI: 1.22-1.75]) and loneliness (yes versus no: 1.56 [1.25-1.95]) were associated with an increased risk of incident dementia after adjusting for demographic factors; however, such associations attenuated when further adjusting for health behaviors, psychological factors, or diabetes-related characteristics. The social isolation-dementia association was predominantly attributable to health behaviors (48% for the most social isolation), while the loneliness-dementia association was largely explained by psychological factors (46%). Significant modification effects of dementia genetic risk were observed in these associations.ConclusionsSocial isolation and loneliness were associated with a greater risk for incident dementia among T2DM individuals, with differential explanatory factors. The genetic risk for dementia modified these associations. The findings underscore the importance of strengthening social connections to mitigate diabetes-related dementia risk.

Amyloid-β Pathology Is the Common Nominator Proteinopathy of the Primate Brain Aging. - Ferrer, Isidro (J Alzheimers Dis, 2024)
Senile plaques, mainly diffuse, and cerebral amyloid-β (Aβ) angiopathy are prevalent in the aging brain of non-human primates, from lemurs to non-human Hominidae. Aβ but not hyper-phosphorylated tau (HPtau) pathology is the common nominator proteinopathy of non-human primate brain aging. The abundance of Aβ in the aging primate brain is well tolerated, and the impact on cognitive functions is usually limited to particular tasks. In contrast, human brain aging is characterized by the early appearance of HPtau pathology, mainly forming neurofibrillary tangles, dystrophic neurites of neuritic plaques, and neuropil threads, preceding Aβ deposits by several decades and by its severity progressing from selected nuclei of the brain stem, entorhinal cortex, and hippocampus to the limbic system, neocortex, and other brain regions. Neurofibrillary tangles correlate with cognitive impairment and dementia in advanced cases. Aβ pathology is linked in humans to altered membrane protein and lipid composition, particularly involving lipid rafts. Although similar membrane alterations are unknown in non-human primates, membrane senescence is postulated to cause the activated β-amyloidogenic pathway, and Aβ pathology is the prevailing signature of non-human and human primate brain aging.
Keywords: Aging; Amyloid beta-Peptides; Animals; Brain; Humans; Neurofibrillary Tangles; Plaque, Amyloid; Primates; tau Proteins

The Association Between Neuropathological Lesions and Body Mass Index Is Independent of Cognitive Abilities. - Ururahy, Raul Dos Reis; do Val, Marina Scott; Ciciliati, Aline Maria Macagnan; Leite, Renata Elaine Paraizo; Paes, Vitor Ribeiro; Rodrigues, Roberta Diehl; Grinberg, Lea Tenenholz; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Suemoto, Claudia Kimie (J Alzheimers Dis, 2024)
BACKGROUND: The association of moderate and severe dementia with low body mass index (BMI) is well described, but weight decline seems to also occur in individuals with preclinical neuropathologies. Considering that up to one-fifth of individuals with normal cognition meet the criteria for a dementia-related neuropathological diagnosis, autopsy studies are key to detecting preclinical neurodegenerative and cerebrovascular diseases that could be underlying weight changes. OBJECTIVE: We investigated the association between dementia-related brain lesions and BMI and evaluated whether the cognitive function was a mediator of this association. METHODS: In 1,170 participants, sociodemographic data, clinical history, and cognitive post-mortem evaluation were assessed with an informant. Neuropathological evaluation was performed in all cases. Linear regression models were used to investigate the association between neuropathological lesions (exposure variable) and BMI (outcome) adjusted for demographic, clinical, and cognitive variables in the whole sample, and in only those with normal cognition. Corrections for multiple comparisons were performed. In addition, a mediation analysis was performed to investigate the direct and indirect effects of cognitive abilities on the association between neuropathology and BMI. RESULTS: Individuals with lower BMI had a higher burden of neuropathological lesions and poorer cognitive abilities. Only neurofibrillary tangles (NFT) and neuropathological comorbidity were associated with low BMI, while other neurodegenerative and cerebrovascular lesions were not. NFT were indirectly associated with BMI through cognitive abilities, and also directly, even in participants with normal cognition. CONCLUSIONS: Neurofibrillary tangles were directly associated with low BMI even in individuals with preclinical Alzheimer's disease.

Association of Statin Use with Dementia Risk Among Older Adults in Japan: A Nested Case-Control Study Using the LIFE Study. - Ge, Sanyu; Kitamura, Tetsuhisa; Zha, Ling; Komatsu, Masayo; Komukai, Sho; Murata, Fumiko; Maeda, Megumi; Gon, Yasufumi; Kimura, Yasuyoshi; Kiyohara, Kosuke; Sobue, Tomotaka; Fukuda, Haruhisa (J Alzheimers Dis, 2024)
BACKGROUND: Previous studies have shown a possible association between statin use and a decreased risk of dementia, but the association has not been sufficiently established, especially in the super-aging society of Japan. OBJECTIVE: This study aimed to determine the association between statin use and the risk of dementia among Japanese participants aged> =65 years old. METHODS: Data from the Longevity Improvement and Fair Evidence (LIFE) Study were utilized, including medical and long-term care (LTC) claim data from 17 municipalities between April 2014 and December 2020. A nested case-control study was conducted with one case matched to five controls based on age, sex, municipality, and year of cohort entry. We used a conditional logistic regression model to calculate the odds ratios (ORs) and 95% confidence intervals (95% CIs). RESULTS: This study included 57,302 cases and 283,525 controls, with 59.7% of the participants being woman. After adjusting for potential confounders, statin use was associated with a lower risk of dementia (OR, 0.70; 95% CI: 0.68-0.73) and Alzheimer's disease (OR: 0.66; 95% CI: 0.63-0.69). Compared with non-users, the ORs of dementia were as follows: 1.42 (1.34-1.50) for 1-30 total standardized daily dose (TSDD), 0.91 (0.85-0.98) for 31-90 TSDD, 0.63 (0.58-0.69) for 91-180 TSDD, and 0.33 (0.31-0.36) for >180 TSDD in dose-analysis. CONCLUSIONS: Statin use is associated with a reduced risk of dementia and Alzheimer's disease among older Japanese adults. A low cumulative statin dose is associated with an increased risk of dementia, whereas a high cumulative statin dose is a protective factor against dementia.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Dementia; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Japan; Male; Risk Factors

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

The Associations of Phosphorylated Tau 181 and Tau 231 Levels in Plasma and Cerebrospinal Fluid with Cognitive Function in Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Li, Zhirui; Fan, Zixuan; Zhang, Qian (J Alzheimers Dis, 2024)
BACKGROUND: Cerebrospinal fluid (CSF) or blood biomarkers like phosphorylated tau proteins (p-tau) are used to detect Alzheimer's disease (AD) early. Increasing studies on cognitive function and blood or CSF p-tau levels are controversial. OBJECTIVE: Our study examined the potential of p-tau as a biomarker of cognitive status in normal control (NC), mild cognitive impairment (MCI), and AD patients. METHODS: We searched PubMed, Cochrane, Embase, and Web of Science for relevant material through 12 January 2023. 5,017 participants from 20 studies-1,033 AD, 2,077 MCI, and 1,907 NC-were evaluated. Quantitative analysis provided continuous outcomes as SMDs with 95% CIs. Begg tested publication bias. RESULTS: MCI patients had lower CSF p-tau181 levels than AD patients (SMD =-0.60, 95% CI (-0.85, -0.36)) but higher than healthy controls (SMD = 0.67). AD/MCI patients had greater plasma p-tau181 levels than healthy people (SMD =-0.73, 95% CI (-1.04, -0.43)). MCI patients had significantly lower p-tau231 levels than AD patients in plasma and CSF (SMD =-0.90, 95% CI (-0.82, -0.45)). MCI patients showed greater CSF and plasma p-tau231 than healthy controls (SMD = 1.34, 95% CI (0.89, 1.79) and 0.43, (0.23, 0.64)). Plasma p-tau181/231 levels also distinguished the three categories. MCI patients had higher levels than healthy people, while AD patients had higher levels than MCI patients. CONCLUSIONS: CSF p-tau181 and p-tau231 biomarkers distinguished AD, MCI, and healthy populations. Plasma-based p-tau181 and p-tau231 biomarkers for AD and MCI need further study.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition; Cognitive Dysfunction; Humans; tau Proteins

Associations of Physical Activity Engagement with Cerebral Amyloid-β and Tau from Midlife. - Gonzales, Mitzi M; Kojis, Daniel; Spartano, Nicole L; Thibault, Emma G; DeCarli, Charles S; El Fakhri, Georges; Johnson, Keith A; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2024)
BACKGROUND: Higher midlife physical activity engagement has been associated with lower dementia risk in late life. However, the underlying mechanisms contributing to the protective effect remain unclear. OBJECTIVE: The goal of the current study was to evaluate the associations of physical activity with cerebral amyloid-β (Aβ) and tau in a predominately middle-aged community-based cohort, as well as to explore whether the associations differ by sex or age. METHODS: Participants from the Framingham Heart Study underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Total physical activity levels were evaluated by self-report using the Physical Activity Index (PAI). Cross-sectional associations between total PAI with regional Aβ and tau PET retention were evaluated using linear regression models adjusted for demographic and cardiovascular risk factors. Interactions with sex and age group were examined and stratified analyses were performed when significant. FDR-correction for multiple comparisons was applied. RESULTS: The sample included 354 participants (mean age 53±8 years, 51% female). Higher total PAI scores were associated with lower entorhinal cortex tau PET binding (β (SE) = -0.021(0.008), p = 0.049). There were significant interactions with sex. In men alone, total PAI inversely associated with entorhinal cortex (β (SE) = -0.035(0.009), p = 0.001), inferior temporal (β (SE) = -0.029(0.010), p = 0.012), and rhinal cortex tau(β (SE) = -0.033(0.010), p = 0.002). CONCLUSIONS: The results suggest that higher midlife physical activity engagement may confer resistance to tau pathology. However, the effects may vary based on sex, highlighting the importance of better understanding and tailoring lifestyle interventions to address sex disparities.

Bisecting N-Acetylglucosamine Correlates with Phospho-Tau181 in Subjective Cognitive Decline but not in Control Cases. - Egebäck Arulf, Sofia; Ziyue Zhou, Robin; Kirsebom, Bjørn-Eivind; Jejcic, Alenka; Fladby, Tormod; Winblad, Bengt; Tjernberg, Lars; Schedin-Weiss, Sophia (J Alzheimers Dis, 2024)
BACKGROUND: The N-glycan structure bisecting N-acetylglucosamine (bisecting GlcNAc) is present on several N-glycans that are elevated in Alzheimer's disease (AD), and previous studies have shown that bisecting GlcNAc levels correlate with total tau and phospho-tau181 in cerebrospinal fluid at early stages of AD. A recent population-based study showed that bisecting GlcNAc correlates with total tau also in blood and that this correlation could predict conversion to dementia. OBJECTIVE: In this study, we have further investigated how bisecting GlcNAc relates to total tau and phospho-tau 181 in cerebrospinal fluid samples from controls and cases with early cognitive deficits, stratified by amyloid/tau status and gender. METHODS: Relative levels of bisecting GlcNAc in cerebrospinal fluid were measured by an enzyme-linked lectin assay in individuals with subjective cognitive decline, mild cognitive impairment and controls from the Norwegian Dementia Disease Initiation cohort. RESULTS: As in our previous study, the correlation between bisecting GlcNAc and total tau or phospho-tau181 was particularly strong in the subjective cognitive decline group. The correlation was observed in amyloid negative and tau negative as well as amyloid positive and tau positive individuals, both in females and in males. Interestingly, among the amyloid negative and tau negative individuals, the correlation was observed in individuals with subjective cognitive decline but not in the controls. CONCLUSIONS: Thus, bisecting GlcNAc could be a biomarker for early cognitive decline.

On the Clinimetrics of the Montreal Cognitive Assessment: Cutoff Analysis in Patients with Mild Cognitive Impairment due to Alzheimer's Disease. - Ilardi, Ciro Rosario; Menichelli, Alina; Michelutti, Marco; Cattaruzza, Tatiana; Federico, Giovanni; Salvatore, Marco; Iavarone, Alessandro; Manganotti, Paolo (J Alzheimers Dis, 2024)
BACKGROUND: In the era of disease-modifying therapies, empowering the clinical neuropsychologist's toolkit for timely identification of mild cognitive impairment (MCI) is crucial. OBJECTIVE: Here we examine the clinimetric properties of the Montreal Cognitive Assessment (MoCA) for the early diagnosis of MCI due to Alzheimer's disease (MCI-AD). METHODS: Data from 48 patients with MCI-AD and 47 healthy controls were retrospectively analyzed. Raw MoCA scores were corrected according to the conventional Nasreddine's 1-point correction and demographic adjustments derived from three normative studies. Optimal cutoffs were determined while previously established cutoffs were diagnostically reevaluated. RESULTS: The original Nasreddine's cutoff of 26 and normative cutoffs (non-parametric outer tolerance limit on the 5th percentile of demographically-adjusted score distributions) were overly imbalanced in terms of Sensitivity (Se) and Specificity (Sp). The optimal cutoff for Nasreddine's adjustment showed adequate clinimetric properties (≤23.50, Se = 0.75, Sp = 0.70). However, the optimal cutoff for Santangelo's adjustment (≤22.85, Se = 0.65, Sp = 0.87) proved to be the most effective for both screening and diagnostic purposes according to Larner's metrics. The results of post-probability analyses revealed that an individual testing positive using Santangelo's adjustment combined with a cutoff of 22.85 would have 84% post-test probability of receiving a diagnosis of MCI-AD (LR+ = 5.06). CONCLUSIONS: We found a common (mal)practice of bypassing the applicability of normative cutoffs in diagnosis-oriented clinical practice. In this study, we identified optimal cutoffs for MoCA to be allocated in secondary care settings for supporting MCI-AD diagnosis. Methodological and psychometric issues are discussed.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Neuropsychological Tests; Retrospective Studies; Sensitivity and Specificity

Comparative accuracy of Mini-Linguistic State Examination, Addenbrooke's Cognitive Examination, and Depistage Cognitif de Quebec for the diagnosis of primary progressive aphasia. - Fernández-Romero, Lucía; Morello-García, Florentina; Laforce, Robert; Delgado-Alonso, Cristina; Delgado-Álvarez, Alfonso; Gil-Moreno, María José; Lavoie, Monica; Matías-Guiu, Jorge; Cuetos, Fernando; Matías-Guiu, Jordi A (J Alzheimers Dis, 2024)
BACKGROUND: Clinical diagnosis in primary progressive aphasia (PPA) is challenging. Recently, emphasis has been placed on the importance of screening evaluation. Three different screening tests that use different strategies based on the assessment of language (Mini-Linguistic State Examination, MLSE) or different cognitive domains (Addenbrooke's Cognitive Examination, ACE-III and Dépistage Cognitif de Québec, DCQ) have been proposed and independently validated. These tests aim to detect PPA and classify into the three main variants (non-fluent (nfvPPA), semantic (svPPA) and logopenic (lvPPA)). OBJECTIVE: This study aims to evaluate and compare the diagnostic capacity of these three instruments in PPA. METHODS: A cross-sectional study including 43 patients with PPA (nfvPPA ( = 19), svPPA ( = 8), and lvPPA ( = 16)) and 21 cognitively unimpaired controls was conducted. Clinical diagnoses were established based on an extensive multidisciplinary assessment including neuropsychological assessment, fluorodeoxyglucose-positron emission tomography, MRI, and cerebrospinal fluid biomarkers. Both PPA patients and controls completed the three tests (MLSE, ACE-III, and DCQ). RESULTS: Internal consistency was excellent for the three tests. The area under the curve for the diagnosis of PPA was 0.950 for MLSE, 0.953 for ACE-III, and 0.933 for DCQ. Correlations between the three tests were high. The MLSE, ACE-III, and DCQ tests obtained adequate levels of discrimination between the variants of PPA, with accuracies between 76-79%. CONCLUSIONS: This study confirms the validity of ACE-III, MLSE, and DCQ for the diagnosis of PPA and its variants. This suggests that detailed assessment of linguistic characteristics (MLSE) and non-linguistic features (DCQ, ACE-III) are relevant for the diagnosis and classification of PPA.
Keywords: Aged; Aphasia, Primary Progressive; Cross-Sectional Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Reproducibility of Results

Computational Evaluation of the Potential Pharmacological Activity of Salen-Type Ligands in Alzheimer's Disease. - Puentes-Díaz, Nicolás; Chaparro, Diego; Reyes-Marquez, Viviana; Morales-Morales, David; Flores-Gaspar, Areli; Alí-Torres, Jorge (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia representing from 60% to 70% of the cases globally. It is a multifactorial disease that, among its many pathological characteristics, has been found to provoke the metal ion dysregulation in the brain, along with an increase in the oxidative stress. There is proof that metallic complexes formed by the amyloid-β peptide (Aβ) and extraneuronal copper can catalyze the production of reactive oxygen species, leading to an increase in oxidative stress, promoting neuronal death. Due to this interaction, bioavailable copper has become an important redox active target to consider within the search protocols of multifunctional agents for AD's treatment. OBJECTIVE: In this study, we examined by using bioinformatics and electronic structure calculations the potential application of 44 salen-type copper chelating ligands and 12 further proposed molecules as possible multifunctional agents in the context of AD. METHODS: The candidates were evaluated by combining bioinformatic tools and electronic structure calculations, which allowed us to classify the molecules as potential antioxidants, redistributor-like compounds, and the newly proposed suppressor mechanism. RESULTS: This evaluation demonstrate that salen-type ligands exhibit properties suitable for interfering in the chain of copper-induced oxidative stress reactions present in AD and potential redistributor and suppressor activity for copper ions. Finally, a novel set of plausible candidates is proposed and evaluated. CONCLUSION: According to the evaluated criteria, a subset of 13 salen-type candidates was found to exhibit promissory pharmacological properties in the AD framework and were classified according to three plausible action mechanisms.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antioxidants; Chelating Agents; Computational Biology; Copper; Humans; Ligands; Oxidative Stress

Dementia in the Ancient Greco-Roman World Was Minimally Mentioned. - Finch, Caleb E; Burstein, Stanley M (J Alzheimers Dis, 2024)
BACKGROUND: The possibility that Alzheimer's disease and related dementias (ADRD) is a modern disease arises from the minimal mention of advanced cognitive decline by ancient Greeks and Romans, who were mainly concerned with the physical frailties of older ages. OBJECTIVE: Because standard medical histories of elderly health lacked mention of cognitive decline, we examined texts by Greek and Roman authors that mentioned memory loss and dementia. METHODS: Primary texts of Greco-Roman authors, 8th century BCE into the 3rd century CE, that mentioned cognitive decline were identified and critically evaluated. Secondary sources were excluded. RESULTS: No ancient account of cognitive loss is equivalent to modern clinical data. The term dementia was occasionally used in antiquity, but not invariably linked to old age. Ancient Greeks and Romans expected intellectual competence beyond age 60. While some memory loss was acknowledged, we found only four accounts of severe cognitive loss that might represent ADRD. The possibility of modest ADRD prevalence in ancient Greece and Rome is consistent with its low prevalence in the Tsimane of Bolivia. These contemporary Amerindians live under conditions of high mortality from frequent infections and minimal cardiovascular disease with physically demanding lives. Tsimane after age 60 had increased mild cognitive impairment; the few cases of dementia were not clinically consistent with AD. CONCLUSIONS: The modern 'epidemic level' of advanced dementias was not described among ancient Greco-Roman elderly. The possible emergence of advanced ADRD in the Roman era may be associated with environmental factors of air pollution and increased exposure to lead. Further historical analysis may formulate critical hypotheses about the modernity of high ADRD prevalence.
Keywords: Aged; Alzheimer Disease; Greek World; Humans; Memory Disorders; Roman World

Enhancing Rab7 Activity by Inhibiting TBC1D5 Expression Improves Mitophagy in Alzheimer's Disease Models. - Liang, Xiao; Wang, Yangyang; Li, Siyu; Fan, Jianing; Zhou, Fanlin; Li, Xiaoju; Li, Shijie; Li, Yu (J Alzheimers Dis, 2024)
BACKGROUND: Mitochondrial dysfunction exists in Alzheimer's disease (AD) brain, and damaged mitochondria need to be removed by mitophagy. Small GTPase Rab7 regulates the fusion of mitochondria and lysosome, while TBC1D5 inhibits Rab7 activation. However, it is not clear whether the regulation of Rab7 activity by TBC1D5 can improve mitophagy and inhibit AD progression. OBJECTIVE: To investigate the role of TBC1D5 in mitophagy and its regulatory mechanism for Rab7, and whether activation of mitophagy can inhibit the progression of AD. METHODS: Mitophagy was determined by western blot and immunofluorescence. The morphology and quantity of mitochondria were tracked by TEM. pCMV-Mito-AT1.03 was employed to detect the cellular ATP. Amyloid-β secreted by AD cells was detected by ELISA. Co-immunoprecipitation was used to investigate the binding partner of the target protein. Golgi-cox staining was applied to observe neuronal morphology of mice. The Morris water maze test and Y-maze were performed to assess spatial learning and memory, and the open field test was measured to evaluate motor function and anxiety-like phenotype of experimental animals. RESULTS: Mitochondrial morphology was impaired in AD models, and TBC1D5 was highly expressed. Knocking down TBC1D5 increased the expression of active Rab7, promoted the fusion of lysosome and autophagosome, thus improving mitophagy, and improved the morphology of hippocampal neurons and the impaired behavior in AD mice. CONCLUSIONS: Knocking down TBC1D5 increased Rab7 activity and promoted the fusion of autophagosome and lysosome. Our study provided insights into the mechanisms that bring new possibilities for AD therapy targeting mitophagy.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; GTPase-Activating Proteins; Humans; Male; Mice; Mice, Transgenic; Mitochondria; Mitophagy; Neurons; rab GTP-Binding Proteins; rab7 GTP-Binding Proteins

The funnel effect of reserves prompted by leisure activities across the Alzheimer's disease continuum. - Serra, Laura; Bonarota, Sabrina; Di Domenico, Carlotta; Caruso, Giulia; Giulietti, Giovanni; Rizzuti, Martina; Assogna, Martina; Rodini, Marta; Mencarelli, Lucia; Di Lorenzo, Francesco; Koch, Giacomo; Fadda, Lucia; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Reserves' mechanisms explain inconsistencies between accumulation of neuropathological damage and clinical manifestations. Leisure activities are believed to promote reserves. OBJECTIVE: This study evaluates whether cognitive, social, and physical leisure activities performed over life-span predict current cognitive functioning in normal aging and Alzheimer's disease (AD) continuum. METHODS: 35 AD, 24 amnestic-Mild Cognitive Impairment (a-MCI) patients, 21 individuals with subjective cognitive complaint (SCD), and 25 controls underwent a questionnaire developed to quantify leisure activities in different life periods, the Addenbrooke's Cognitive Examination-Revised (ACE-R), and T1-weighted 3T-MRI scans for brain volumetrics and cortical thickness quantification. Partial/total leisure activities' scores and demographic and brain variables were entered as predictors, while ACE-R scores as dependent variables in linear regression analyses. RESULTS: Current level of cognition was predicted by (i) social and physical activities performed in middle age and current cognitive activity in AD; (ii) cognitive and social activities performed in middle age, current age and cortical thickness in a-MCI; (iii) recreational activities the set of lifetime, current age, and brain features in SCD; (iv) education and the set of lifetime leisure activities over lifespan in controls. CONCLUSIONS: This study shows a funnel effect due to gradual reduction of stimulatory activities in the transition from healthy aging to AD. Reserve indices taking into account different types of stimulatory activities allow to capture even smallest residual effects of reserves accumulated over lifespan, until their complete depletion at advanced AD stages. These results may help target tailored interventions during normal and pathological aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Cognition; Cognitive Dysfunction; Cognitive Reserve; Female; Humans; Leisure Activities; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Interaction Between Arteriosclerosis and Amyloid-β on Cognitive Function. - Frentz, Ingeborg; van Arendonk, Joyce; Leeuwis, Anna E; Vernooij, Meike W; van der Flier, Wiesje M; Bos, Daniel; De Deyn, Peter Paul; Wolters, Frank J; Ikram, M Arfan (J Alzheimers Dis, 2024)
BACKGROUND: Dementia is a multifactorial disease, with Alzheimer's disease (AD) and vascular pathology often co-occurring in many individuals with dementia. Yet, the interplay between AD and vascular pathology in cognitive decline is largely undetermined. OBJECTIVE: The aim of the present study was to examine the joint effect of arteriosclerosis and AD pathology on cognition in the general population without dementia. METHODS: We determined the interaction between blood-based AD biomarkers and CT-defined arteriosclerosis on cognition in 2,229 dementia-free participants of the population-based Rotterdam Study (mean age: 68.9 years, 52% women) cross-sectionally. RESULTS: Amyloid-β (Aβ)42 and arterial calcification were associated with cognitive performance. After further adjustment for confounders in a model that combined all biomarkers, only arterial calcification remained independently associated with cognition. There was a significant interaction between arterial calcification and Aβ42 and between arterial calcification and the ratio of Aβ42/40. Yet, estimates attenuated, and interactions were no longer statistically significant after adjustment for cardio metabolic risk factors. CONCLUSIONS: Arteriosclerosis and AD display additive interaction-effects on cognition in the general population, that are due in part to cardio metabolic risk factors. These findings suggest that joint assessment of arteriosclerosis and AD pathology is important for understanding of disease etiology in individuals with cognitive impairment.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Arteriosclerosis; Biomarkers; Cognition; Cognitive Dysfunction; Female; Humans; Male; tau Proteins

Investigating the efficacy of ergothioneine to delay cognitive decline in mild cognitively impaired subjects: A pilot study. - Yau, Yu Fung; Cheah, Irwin K; Mahendran, Rathi; Tang, Richard My; Chua, Ru Yuan; Goh, Rachel E S; Feng, Lei; Li, Jialiang; Kua, Ee Heok; Chen, Christopher; Halliwell, Barry (J Alzheimers Dis, 2024)
BACKGROUND: Dementia, particularly Alzheimer's disease, is a major healthcare challenge in ageing societies. OBJECTIVE: This study aimed to investigate the efficacy and safety of a dietary compound, ergothioneine, in delaying cognitive decline in older individuals. METHODS: Nineteen subjects aged 60 or above with mild cognitive impairment were recruited for this double-blinded, randomized, and placebo-controlled study (ClinicalTrials.gov identifier: NCT03641404, registration date: 19/08/2018). Subjects received either ergothioneine (25 mg per capsule) or a placebo, taken 3 times a week for one year. The whole blood profile, markers of renal and liver functions, neurocognitive performance, plasma levels of ergothioneine and its metabolites, and plasma biomarkers related to neurodegeneration were measured across the study. RESULTS: Ergothioneine intake did not alter clinical safety markers (blood counts, kidney and liver function) throughout the study, further validating its safety for human consumption. Subjects receiving ergothioneine demonstrated improved performance in assessment of learning ability and stabilized plasma levels of neurofilament light chain, compared with the placebo group, which saw no improvement in cognitive assessments and a significant increase in neurofilament light chain levels. CONCLUSIONS: Prolonged intake of ergothioneine showed no toxicity in elderly people. Enhanced Rey Auditory Verbal Learning Test performance and stabilized neurofilament light chain levels suggest improvements in memory and learning abilities and a deceleration of neuronal damage, respectively. Our results add to existing data that ergothioneine is safe for extended consumption and may hold the potential to delay cognitive decline in elderly adults.

Long Non-Coding RNA Profile in Genetic Symptomatic and Presymptomatic Frontotemporal Dementia: A GENFI Study. - Serpente, Maria; Fenoglio, Chiara; Arcaro, Marina; Carandini, Tiziana; Sacchi, Luca; Pintus, Manuela; Rotondo, Emanuela; Borracci, Vittoria; Ghezzi, Laura; Bouzigues, Arabella; Russell, Lucy L; Foster, Phoebe H; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Long non-coding RNAs (lncRNAs) play crucial roles in gene regulation and are implicated in neurodegenerative diseases, including frontotemporal dementia (FTD). However, their expression patterns and potential as biomarkers in genetic FTD involving Chromosome 9 Open Reading Frame (C9ORF72), Microtubule Associated Protein Tau (MAPT), and Progranulin (GRN) genes are not well understood. OBJECTIVE: This study aimed to profile the expression levels of lncRNAs in peripheral blood mononuclear cells collected within the GENetic Frontotemporal dementia Initiative (GENFI). METHODS: Fifty-three lncRNAs were analyzed with the OpenArray Custom panel, in 131 patients with mutations in C9ORF72, MAPT, and GRN, including 68 symptomatic mutation carriers (SMC) and 63 presymptomatic mutation carriers (PMC), compared with 40 non-carrier controls (NC). RESULTS: Thirty-eight lncRNAs were detectable; the relative expression of NEAT1 and NORAD was significantly higher in C9ORF72 SMC as compared with NC. GAS5 expression was instead significantly lower in the GRN group versus NC. MAPT carriers showed no significant deregulations. No significant differences were observed in PMC. Disease duration did not correlate with lncRNA expression. CONCLUSIONS: NEAT1 and NORAD are upregulated in C9ORF72 SMC and GAS5 levels are downregulated in GRN SMC, underlining lncRNAs' relevance in FTD and their potential for biomarker development. Further validation and mechanistic studies are crucial for clinical implications.

Long-Term Safety of Gantenerumab in Participants with Alzheimer's Disease: A Phase III, Double-Blind, and Open-Label Extension Study (Marguerite RoAD). - Neve, Anuja; Das, Bibha; Wojtowicz, Jakub; Huang, Zhiyue; Bullain, Szofia; Watkin, Michelle; Lott, Dominik; Bittner, Tobias; Delmar, Paul; Klein, Gregory; Hofmann, Carsten; Kerchner, Geoffrey A; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Gantenerumab is an anti-amyloid-β immunoglobulin G1 monoclonal antibody for subcutaneous (SC) administration. The efficacy and safety of low-dose (105 mg or 225 mg) gantenerumab were investigated in Marguerite RoAD (MR; NCT02051608), a Phase III, double-blind (DB), placebo-controlled study in participants with mild Alzheimer's disease (AD) dementia. Following a preplanned futility analysis of the SCarlet RoAD study (NCT01224106), MR was converted into an open-label extension (OLE). OBJECTIVE: The DB study aimed to assess the efficacy of gantenerumab compared with placebo from baseline to Week 104 in participants with mild AD dementia. Following conversion to an OLE, this objective became exploratory, as the OLE assessed the long-term safety and tolerability of SC gantenerumab at doses of up to 1,200 mg every 4 weeks (Q4W) in OLE participants. METHODS: Eligible DB study participants were offered the opportunity to receive gantenerumab up-titrated to 1,200 mg Q4W. Safety and tolerability were assessed using magnetic resonance imaging (MRI), physical and neurologic examinations, and adverse event monitoring. RESULTS: Overall, 225 participants were rolled over from the DB part of MR and received ≥1 gantenerumab dose in the OLE. The median treatment duration was 123 weeks. Fifty-nine (26.2%) and 41 (18.2%) participants had amyloid-related imaging abnormality (ARIA)-edema and ARIA-hemorrhage MRI findings, respectively. ARIA findings were manageable with MRI monitoring and dose intervention; most were asymptomatic. There were no unexpected safety findings. CONCLUSIONS: SC gantenerumab at doses of up to 1,200 mg Q4W were well tolerated in participants with mild AD dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Double-Blind Method; Female; Humans; Male; Middle Aged; Treatment Outcome

Mayo Normative Studies: Amyloid and Neurodegeneration Negative Normative Data for the Auditory Verbal Learning Test and Sex-Specific Sensitivity to Mild Cognitive Impairment/Dementia. - Stricker, Nikki H; Christianson, Teresa J; Pudumjee, Shehroo B; Polsinelli, Angelina J; Lundt, Emily S; Frank, Ryan D; Kremers, Walter K; Machulda, Mary M; Fields, Julie A; Jack, Clifford R; Knopman, David S; Graff-Radford, Jonathan; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Conventional normative samples include individuals with undetected Alzheimer's disease neuropathology, lowering test sensitivity for cognitive impairment. OBJECTIVE: We developed Mayo Normative Studies (MNS) norms limited to individuals without elevated amyloid or neurodegeneration (A-N-) for Rey's Auditory Verbal Learning Test (AVLT). We compared these MNS A-N- norms in female, male, and total samples to conventional MNS norms with varying levels of demographic adjustments. METHODS: The A-N- sample included 1,059 Mayo Clinic Study of Aging cognitively unimpaired (CU) participants living in Olmsted County, MN, who are predominantly non-Hispanic White. Using a regression-based approach correcting for age, sex, and education, we derived fully-adjusted T-score formulas for AVLT variables. We validated these A-N- norms in two independent samples of CU (n = 261) and mild cognitive impairment (MCI)/dementia participants (n = 392) > 55 years of age. RESULTS: Variability associated with age decreased by almost half in the A-N- norm sample relative to the conventional norm sample. Fully-adjusted MNS A-N- norms showed approximately 7- 9% higher sensitivity to MCI/dementia compared to fully-adjusted MNS conventional norms for trials 1- 5 total and sum of trials. Among women, sensitivity to MCI/dementia increased with each normative data refinement. In contrast, age-adjusted conventional MNS norms showed greatest sensitivity to MCI/dementia in men. CONCLUSIONS: A-N- norms show some benefits over conventional normative approaches to MCI/dementia sensitivity, especially for women. We recommend using these MNS A-N- norms alongside MNS conventional norms. Future work is needed to determine if normative samples that are not well characterized clinically show greater benefit from biomarker-refined approaches.

Microglial TLR4/NLRP3 Inflammasome Signaling in Alzheimer's Disease. - Li, Yunfeng; Chen, Xiongjin; Zhou, Mulan; Feng, Sifan; Peng, Xiaoping; Wang, Yan (J Alzheimers Dis, 2024)
Alzheimer's disease is a pervasive neurodegenerative disease that is estimated to represent approximately 70% of dementia cases worldwide, and the molecular complexity that has been highlighted remains poorly understood. The accumulation of extracellular amyloid-β (Aβ), intracellular neurofibrillary tangles formed by tau hyperphosphorylation, and neuroinflammation are the major pathological features of Alzheimer's disease (AD). Over the years, there has been no apparent breakthrough in drug discovery based on the Aβ and tau hypotheses. Neuroinflammation has gradually become a hot spot in AD treatment research. As the primary cells of innate immunity in the central nervous system, microglia play a key role in neuroinflammation. Toll-like receptor 4 (TLR4) and nucleotide-binding oligomerization domain-like receptor 3 (NLRP3) inflammasomes are vital molecules in neuroinflammation. In the pathological context of AD, the complex interplay between TLR4 and the NLRP3 inflammasomes in microglia influences AD pathology via neuroinflammation. In this review, the effect of the activation and inhibition of TLR4 and NLRP3 in microglia on AD pathology, as well as the cross-talk between TLR4 and the NLRP3 inflammasome, and the influence of essential molecules in the relevant signaling pathway on AD pathology, were expounded. In addition, the feasibility of these factors in representing a potential treatment option for AD has been clarified.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Inflammasomes; Microglia; Neurodegenerative Diseases; Neuroinflammatory Diseases; NLR Family, Pyrin Domain-Containing 3 Protein; Signal Transduction; Toll-Like Receptor 4

Neural Computation-Based Methods for the Early Diagnosis and Prognosis of Alzheimer's Disease Not Using Neuroimaging Biomarkers: A Systematic Review. - Cabrera-León, Ylermi; Báez, Patricio García; Fernández-López, Pablo; Suárez-Araujo, Carmen Paz (J Alzheimers Dis, 2024)
BACKGROUND: The growing number of older adults in recent decades has led to more prevalent geriatric diseases, such as strokes and dementia. Therefore, Alzheimer's disease (AD), as the most common type of dementia, has become more frequent too. BACKGROUND: Objective: The goals of this work are to present state-of-the-art studies focused on the automatic diagnosis and prognosis of AD and its early stages, mainly mild cognitive impairment, and predicting how the research on this topic may change in the future. METHODS: Articles found in the existing literature needed to fulfill several selection criteria. Among others, their classification methods were based on artificial neural networks (ANNs), including deep learning, and data not from brain signals or neuroimaging techniques were used. Considering our selection criteria, 42 articles published in the last decade were finally selected. RESULTS: The most medically significant results are shown. Similar quantities of articles based on shallow and deep ANNs were found. Recurrent neural networks and transformers were common with speech or in longitudinal studies. Convolutional neural networks (CNNs) were popular with gait or combined with others in modular approaches. Above one third of the cross-sectional studies utilized multimodal data. Non-public datasets were frequently used in cross-sectional studies, whereas the opposite in longitudinal ones. The most popular databases were indicated, which will be helpful for future researchers in this field. CONCLUSIONS: The introduction of CNNs in the last decade and their superb results with neuroimaging data did not negatively affect the usage of other modalities. In fact, new ones emerged.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Deep Learning; Early Diagnosis; Humans; Neural Networks, Computer; Neuroimaging; Prognosis

Psychosis in Neurodegenerative Dementias: A Systematic Comparative Review. - Cressot, Coralie; Vrillon, Agathe; Lilamand, Matthieu; Francisque, Hélène; Méauzoone, Aurélie; Hourregue, Claire; Dumurgier, Julien; Marlinge, Emeline; Paquet, Claire; Cognat, Emmanuel (J Alzheimers Dis, 2024)
BACKGROUND: Psychosis, characterized by delusions and/or hallucinations, is frequently observed during the progression of Alzheimer's disease (AD) and other neurodegenerative dementias (ND) (i.e., dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD)) and cause diagnostic and management difficulties. OBJECTIVE: This review aims at presenting a concise and up-to-date overview of psychotic symptoms that occur in patients with ND with a comparative approach. METHODS: A systematic review was conducted following the PRISMA guidelines. 98 original studies investigating psychosis phenotypes in neurodegenerative dementias were identified (40 cohort studies, 57 case reports). RESULTS: Psychosis is a frequently observed phenomenon during the course of ND, with reported prevalence ranging from 22.5% to 54.1% in AD, 55.9% to 73.9% in DLB, and 18% to 42% in FTD. Throughout all stages of these diseases, noticeable patterns emerge depending on their underlying causes. Misidentification delusions (16.6-78.3%) and visual hallucinations (50-69.6%) are frequently observed in DLB, while paranoid ideas and somatic preoccupations seem to be particularly common in AD and FTD, (respectively 9.1-60.3% and 3.10-41.5%). Limited data were found regarding psychosis in the early stages of these disorders. CONCLUSIONS: Literature data suggest that different ND are associated with noticeable variations in psychotic phenotypes, reflecting disease-specific tendencies. Further studies focusing on the early stages of these disorders are necessary to enhance our understanding of early psychotic manifestations associated with ND and help in differential diagnosis issues.
Keywords: Alzheimer Disease; Delusions; Dementia; Frontotemporal Dementia; Humans; Lewy Body Disease; Neurodegenerative Diseases; Psychotic Disorders

Regional differences in glucose metabolic decline and tau deposition in the Alzheimer's continuum brain. - Ishii, Kazunari; Yamada, Takahiro; Hanaoka, Kohei; Kaida, Hayato; Kojita, Yasuyuki; Kono, Atsushi; Hanada, Kazushi; Saigoh, Kazumasa; Sakuta, Shizuka; Hashimoto, Mamoru; Kato, Takashi; Nakamura, Akinori (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β and tau proteins, leading to neurofibrillary tangles. A biomarker-based diagnostic method called the ATN system categorizes AD pathology into amyloid-β (A), tau (T), and neurodegeneration (N). The relationship between regional tau deposition and reduced glucose metabolism in the preclinical AD stage is not well understood. OBJECTIVE: We presented voxel-by-voxel metabolic/tau deposition ratio (MTR) images to investigate the effects of tau deposition on metabolism in AD brains on a stage-by-stage basis. METHODS: We selected 174 subjects who underwent 3D-MRI, FDG-PET, amyloid PET, and tau PET scans. MTR images were created by normalizing FDG-PET toMK6240 PET images. Voxel-wise comparisons among 63 cognitively normal amyloid-negative (CNA) subjects, 49 subjects with AD dementia (ADD), 23 subjects with mild cognitive impairment due to AD (MCA), and 39 preclinical AD (PRC) subjects were conducted. RESULTS: There was reduced glucose metabolism in ADD and MCA groups compared to CNA, predominantly in parietotemporal areas. Tau deposition was observed in wider areas in ADD and restricted to the medial temporal lobes in MCA. MTR exhibited significant reductions in broader regions in ADD and MCA, indicating simultaneous glucose metabolism decrease and tau deposition. At the MCA and PRC stages, glucose metabolism impairment and tau deposition were shown in separate regions by FDG PET and tau PET, respectively, while MTR images showed impairment in both regions. CONCLUSIONS: Our findings suggest that MTR imaging provides insights into AD pathophysiology by simultaneously assessing glucose metabolism and tau deposition. In the early stage of the AD continuum (MCA and PRC), metabolic decline and tau deposition occur independently in different brain regions.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Glucose; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; tau Proteins

Research Participants' Perspectives on Precision Diagnostics for Alzheimer's Disease. - Smith, Hadley Stevens; Robinson, Jill O; Levchenko, Ariel; Pereira, Stacey; Pascual, Belen; Bradbury, Kathleen; Arbones, Victoria; Fong, Jamie; Shulman, Joshua M; McGuire, Amy L; Masdeu, Joseph (J Alzheimers Dis, 2024)
BACKGROUND: Understanding research participants' responses to learning Alzheimer's disease (AD) risk information is important to inform clinical implementation of precision diagnostics given rapid advances in disease modifying therapies. OBJECTIVE: We assessed participants' perspectives on the meaning of their amyloid positron emission tomography (PET) imaging results for their health, self-efficacy to understand their results, psychological impact of learning their results, experience receiving their results from the clinical team, and interest in genetic testing for AD risk. METHODS: We surveyed individuals who were being clinically evaluated for AD and received PET imaging six weeks after the return of results. We analyzed responses to close-ended survey items by PET result using Fisher's exact test and qualitatively coded open-ended responses. RESULTS: A total of 88 participants completed surveys, most of whom had mild cognitive impairment due to AD (38.6%), AD (28.4%), or were cognitively unimpaired (21.6%). Participants subjectively understood their results (25.3% strongly agreed, 41.8% agreed), which could help them plan (16.5% strongly agreed, 49.4% agreed). Participants with a negative PET result (n = 25) reported feelings of relief (Fisher's exact p < 0.001) and happiness (p < 0.001) more frequently than those with a positive result. Most participants felt that they were treated respectfully and were comfortable voicing concerns during the disclosure process. Genetic testing was anticipated to be useful for medical care decisions (48.2%) and to inform family members about AD risk (42.9%). CONCLUSIONS: Participants had high subjective understanding and self-efficacy around their PET results and did not experience negative psychological effects. Interest in genetic testing was high.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Cognitive Dysfunction; Emotions; Humans; Positron-Emission Tomography

Sleep Biomarkers for Predicting Cognitive Decline and Alzheimer's Disease: A Systematic Review of Longitudinal Studies. - Carpi, Matteo; Fernandes, Mariana; Mercuri, Nicola Biagio; Liguori, Claudio (J Alzheimers Dis, 2024)
BACKGROUND: Sleep disturbances are considered a hallmark of dementia, and strong evidence supports the association between alterations in sleep parameters and cognitive decline in patients with mild cognitive impairment and Alzheimer's disease (AD). OBJECTIVE: This systematic review aims to summarize the existing evidence on the longitudinal association between sleep parameters and cognitive decline, with the goal of identifying potential sleep biomarkers of AD-related neurodegeneration. METHODS: Literature search was conducted in PubMed, Web of Science, and Scopus databases from inception to 28 March 2023. Longitudinal studies investigating the association between baseline objectively-measured sleep parameters and cognitive decline were assessed for eligibility. RESULTS: Seventeen studies were included in the qualitative synthesis. Sleep fragmentation, reduced sleep efficiency, reduced REM sleep, increased light sleep, and sleep-disordered breathing were identified as predictors of cognitive decline. Sleep duration exhibited a U-shaped relation with subsequent neurodegeneration. Additionally, several sleep microstructural parameters were associated with cognitive decline, although inconsistencies were observed across studies. CONCLUSIONS: These findings suggest that sleep alterations hold promise as early biomarker of cognitive decline, but the current evidence is limited due to substantial methodological heterogeneity among studies. Further research is necessary to identify the most reliable sleep parameters for predicting cognitive impairment and AD, and to investigate interventions targeting sleep that can assist clinicians in the early recognition and treatment of cognitive decline. Standardized procedures for longitudinal studies evaluating sleep and cognition should be developed and the use of continuous sleep monitoring techniques, such as actigraphy or EEG headband, might be encouraged.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cognitive Dysfunction; Humans; Longitudinal Studies; Sleep

Symptomatic Clusters Related to Amyloid Positivity in Cognitively Unimpaired Individuals. - Sannemann, Lena; Bartels, Claudia; Brosseron, Frederic; Buerger, Katharina; Fliessbach, Klaus; Freiesleben, Silka Dawn; Frommann, Ingo; Glanz, Wenzel; Heneka, Michael T; Janowitz, Daniel; Kilimann, Ingo; Kleineidam, Luca; et al. (J Alzheimers Dis, 2024)
BACKGROUND: The NIA-AA Research Framework on Alzheimer's disease (AD) proposes a transitional stage (stage 2) characterized by subtle cognitive decline, subjective cognitive decline (SCD) and mild neurobehavioral symptoms (NPS). OBJECTIVE: To identify participant clusters based on stage 2 features and assess their association with amyloid positivity in cognitively unimpaired individuals. METHODS: We included baseline data of N = 338 cognitively unimpaired participants from the DELCODE cohort with data on cerebrospinal fluid biomarkers for AD. Classification into the AD continuum (i.e., amyloid positivity, A+) was based on Aβ42/40 status. Neuropsychological test data were used to assess subtle objective cognitive dysfunction (OBJ), the subjective cognitive decline interview (SCD-I) was used to detect SCD, and the Neuropsychiatric Inventory Questionnaire (NPI-Q) was used to assess NPS. A two-step cluster analysis was carried out and differences in AD biomarkers between clusters were analyzed. RESULTS: We identified three distinct participant clusters based on presented symptoms. The highest rate of A+ participants (47.6% ) was found in a cluster characterized by both OBJ and SCD. A cluster of participants that presented with SCD and NPS (A+:26.6% ) and a cluster of participants with overall few symptoms (A+:19.7% ) showed amyloid positivity in a range that was not higher than the expected A+ rate for the age group. Across the full sample, participants with a combination of SCD and OBJ in the memory domain showed a lower Aβ42/ptau181 ratio compared to those with neither SCD nor OBJ. CONCLUSIONS: The cluster characterized by participants with OBJ and concomitant SCD was enriched for amyloid pathology.

There are dementia patients in Gaza too. - Irfan, Bilal; Abu Shammala, Abdallah; Alshaer, Nour; Nasser, Elias; Wajahath, Muaaz; Hamawy, Adam; Tahir, Mohammed; Khawaja, Haseeb; Khan, Osaama; Fikry, Karim; Kaleem, Arshad; Nasser, Mosab; et al. (J Alzheimers Dis, 2024)
This editorial highlights the devastating impact of the ongoing Israeli military assault in Gaza on dementia patients, whose fragile care systems have collapsed, leaving them vulnerable and without essential medical support. Through harrowing stories of displacement, medication shortages, and tragic deaths, the piece underscores the profound moral failure in protecting Gaza's most vulnerable, calling for urgent global action to address the humanitarian crisis and ensure dignity and healthcare for all affected individuals.
Keywords: Dementia; Humans; Middle East

Visual Functions Are Associated with Biomarker Changes in Alzheimer's Disease. - Memon, Ashar; Moore, Jasmine A; Kang, Chris; Ismail, Zahinoor; Forkert, Nils D (J Alzheimers Dis, 2024)
BACKGROUND: While various biomarkers of Alzheimer's disease (AD) have been associated with general cognitive function, their association to visual-perceptive function across the AD spectrum warrant more attention due to its significant impact on quality of life. Thus, this study explores how AD biomarkers are associated with decline in this cognitive domain. OBJECTIVE: To explore associations between various fluid and imaging biomarkers and visual-based cognitive assessments in participants across the AD spectrum. METHODS: Data from participants (N = 1,460) in the Alzheimer's Disease Neuroimaging Initiative were analyzed, including fluid and imaging biomarkers. Along with the Mini-Mental State Examination (MMSE), three specific visual-based cognitive tests were investigated: Trail Making Test (TMT) A and TMT B, and the Boston Naming Test (BNT). Locally estimated scatterplot smoothing curves and Pearson correlation coefficients were used to examine associations. RESULTS: MMSE showed the strongest correlations with most biomarkers, followed by TMT-B. The p-tau181/Aβ1-42 ratio, along with the volume of the hippocampus and entorhinal cortex, had the strongest associations among the biomarkers. CONCLUSIONS: Several biomarkers are associated with visual processing across the disease spectrum, emphasizing their potential in assessing disease severity and contributing to progression models of visual function and cognition.

Accumulation of pTau231 at the Postsynaptic Density in Early Alzheimer's Disease. - Lilek, Jaclyn; Ajroud, Kaouther; Feldman, Alexander Z; Krishnamachari, Sesha; Ghourchian, Shadi; Gefen, Tamar; Spencer, Callen L; Kawles, Allegra; Mao, Qinwen; Tranovich, Jessica F; Jack, Clifford R; Mesulam, M-Marsel; et al. (J Alzheimers Dis, 2023)

Age-Related Association Between APOE ɛ4 and Cognitive Progression in de novo Parkinson's Disease. - Liu, Jia-Yao; Ma, Ling-Zhi; Wang, Jun; Cui, Xin-Jing; Sheng, Ze-Hu; Fu, Yan; Li, Meng; Ou, Ya-Nan; Yu, Jin-Tai; Tan, Lan; Lian, Yan (J Alzheimers Dis, 2023)
BACKGROUND: APOE ɛ4 genotype was correlated with exacerbation of pathology and higher risk of dementia in Parkinson's disease (PD). Meanwhile, the differential influence of APOE ɛ4 on cognition in young and old individuals interpreted as antagonistic pleiotropy. OBJECTIVE: To examine whether the effect of APOE ɛ4 on cognitive progression in de novo PD is age dependent. METHODS: In this study, 613 de novo PD patients were recruited from Parkinson's Progression Markers Initiative (PPMI). To examine the age-dependent relationship between APOE ɛ4 and cognitive changes, we added 3-way interaction of APOE ɛ4*baseline age*time to the linear mixed-effect (LME) models and evaluated the specific roles of APOE ɛ4 in the middle age group and elderly group separately. Cox regression was utilized to examine the progression of cognition in age-stratified PD participants. RESULTS: Age significantly modified relationship between APOE ɛ4 and cognitive changes in most cognitive domains (pinteraction <0.05). In the elderly group, APOE ɛ4 carriers showed steeper decline in global cognition (p = 0.001) as well as in most cognitive domains, and they had a greater risk of cognitive progression (adjusted HR 1.625, 95% CI 1.143-2.310, p = 0.007), compared with non-carriers. However, in the middle age group, no significant relationships between APOE ɛ4 and cognitive decline can be detected. CONCLUSION: Our results indicated that the APOE ɛ4 allele has an age-dependent effect on cognitive decline in PD patients. The underlying mechanisms need to be investigated in the future.
Keywords: Aged; Apolipoprotein E4; Cognition; Cognitive Dysfunction; Disease Progression; Genotype; Heterozygote; Humans; Parkinson Disease

Associations Between Ambient Air Pollution and Cognitive Abilities from Midlife to Early Old Age: Modification by APOE Genotype. - Franz, Carol E; Gustavson, Daniel E; Elman, Jeremy A; Fennema-Notestine, Christine; Hagler, Donald J; Baraff, Aaron; Tu, Xin M; Wu, Tsung-Chin; De Anda, Jaden; Beck, Asad; Kaufman, Joel D; Whitsel, Nathan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Fine particulate matter (PM2.5) and nitrogen dioxide (NO2) measures of ambient air pollution are associated with accelerated age-related cognitive impairment, and Alzheimer's disease and related dementias (ADRD). OBJECTIVE: We examined associations between air pollution, four cognitive factors, and the moderating role of apolipoprotein E (APOE) genotype in the understudied period of midlife. METHODS: Participants were ∼1,100 men in the Vietnam Era Twin Study of Aging. Baseline cognitive assessments were from 2003 to 2007. Measures included past (1993-1999) and recent (3 years prior to baseline assessment) PM2.5 and NO2 exposure, in-person assessment of episodic memory, executive function, verbal fluency, and processing speed, and APOE genotype. Average baseline age was 56 years with a 12-year follow-up. Analyses adjusted for health and lifestyle covariates. RESULTS: Performance in all cognitive domains declined from age 56 to 68. Higher PM2.5 exposures were associated with worse general verbal fluency. We found significant exposure-by-APOE genotype interactions for specific cognitive domains: PM2.5 with executive function and NO2 with episodic memory. Higher PM2.5 exposure was related to worse executive function in APOE ɛ4 carriers, but not in non-carriers. There were no associations with processing speed. CONCLUSION: These results indicate negative effects of ambient air pollution exposure on fluency alongside intriguing differential modifications of cognitive performance by APOE genotype. APOE ɛ4 carriers appeared more sensitive to environmental differences. The process by which air pollution and its interaction with genetic risk for ADRD affects risk for later life cognitive decline or progression to dementia may begin in midlife.

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

Can Traditional Board Games Prevent or Slow Down Cognitive Impairment? A Systematic Review and Meta-Analysis. - Pozzi, Federico Emanuele; Appollonio, Ildebrando; Ferrarese, Carlo; Tremolizzo, Lucio (J Alzheimers Dis, 2023)
BACKGROUND: Traditional board games can entail significant skills encompassing several cognitive functions across different domains. Therefore, they may potentially represent effective cognitive interventions in the aging population with or without Alzheimer's disease or other types of dementia. OBJECTIVE: We aimed at verifying the hypothesis that traditional board games can prevent or slow down cognitive decline, through a systematic review on traditional board games and dementia. METHODS: We searched five databases with tailored search strings. We included studies assessing the impact of board games on elderly subjects at risk of or suffering from cognitive impairment, or subjects with cognitive impairment irrespective of age. Studies where the effect of board games was not separated by cards or other games were excluded. A meta-analysis was performed for specific cognitive and non-cognitive outcomes. RESULTS: Board games improved mental function, as measured by Montreal Cognitive Assessment (p = 0.003) and Mini-Mental State Examination (p = 0.02). Ska and Go improved Trail Making Test -A, while Mahjong improved executive functions. There was no consistent effect across different games on Digit Span or Categorical Fluency. Chess improved quality of life measured with the WHO-QoL-OLD scale (p < 0.00001). Mahjong temporarily improved depressive symptoms. Go increased BDNF levels and left middle temporal gyrus and bilateral putamen metabolism. CONCLUSIONS: Traditional board games may slow global cognitive decline and improve the quality of life in elderly subjects. Different games have varying impacts on specific cognitive domains, possibly mediated by functional and biological factors.
Keywords: Aged; Alzheimer Disease; Cognition; Cognitive Dysfunction; Executive Function; Humans; Quality of Life

CERAD (Consortium to Establish a Registry for Alzheimer's Disease) Neuropsychology Assessment Battery: 35 Years and Counting. - Fillenbaum, Gerda G; Mohs, Richard (J Alzheimers Dis, 2023)
BACKGROUND: In 1986, the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) was mandated to develop a brief neuropsychological assessment battery (CERAD-NAB) for AD, for uniform neuropsychological assessment, and information aggregation. Initially used across the National Institutes of Aging-funded Alzheimer's Disease Research Centers, it has become widely adopted wherever information is desired on cognitive status and change therein, particularly in older populations. OBJECTIVE: Our purpose is to provide information on the multiple uses of the CERAD-NAB since its inception, and possible further developments. METHODS: Since searching on "CERAD neuropsychological assessment battery" or similar terms missed important information, "CERAD" alone was entered into PubMed and SCOPUS, and CERAD-NAB use identified from the resulting studies. Use was sorted into major categories, e.g., psychometric information, norms, dementia/differential dementia diagnosis, epidemiology, intervention evaluation, genetics, etc., also translations, country of use, and alternative data gathering approaches. RESULTS: CERAD-NAB is available in ∼20 languages. In addition to its initial purpose assessing AD severity, CERAD-NAB can identify mild cognitive impairment, facilitate differential dementia diagnosis, determine cognitive effects of naturally occurring and experimental interventions (e.g., air pollution, selenium in soil, exercise), has helped to clarify cognition/brain physiology-neuroanatomy, and assess cognitive status in dementia-risk conditions. Surveys of primary and tertiary care patients, and of population-based samples in multiple countries have provided information on prevalent and incident dementia, and cross-sectional and longitudinal norms for ages 35-100 years. CONCLUSION: CERAD-NAB has fulfilled its original mandate, while its uses have expanded, keeping up with advances in the area of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Humans; Neuropsychological Tests; Neuropsychology; Psychometrics; Registries

Cerebrospinal Fluid sTREM-2, GFAP, and β-S100 in Symptomatic Sporadic Alzheimer's Disease: Microglial, Astrocytic, and APOE Contributions Along the Alzheimer's Disease Continuum. - Bonomi, Chiara Giuseppina; Assogna, Martina; Di Donna, Martina Gaia; Bernocchi, Francesca; De Lucia, Vincenzo; Nuccetelli, Marzia; Fiorelli, Denise; Loizzo, Stefano; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro; Motta, Caterina (J Alzheimers Dis, 2023)
BACKGROUND: Many transversal mechanisms act synergistically at different time-points in the cascade of Alzheimer's disease (AD), since amyloid-β (Aβ) deposition, tau pathology, and neuroinflammation influence each other. OBJECTIVE: We explored the contributions of microglia and astrocytes in patients with symptomatic sporadic AD stratified according to AT(N) system and APOE genotype. METHODS: We compared the cerebrospinal fluid (CSF) levels of sTREM-2 and markers of astrocytic activation (GFAP; β-S100) from 71 patients with AD (23 A+T-,48 A+T+; 38 APOEɛ3, 33 APOEɛ4) and 30 healthy controls (HC). With multivariate analyses we investigated associations between glial biomarkers, Aβ42, and p-tau in all subgroups. RESULTS: CSF sTREM-2 was higher in A+T+ [1.437 (0.264)] and A+T- [1.355 (0.213)] than in HC [1.042 (0.198); both p < 0.001]; GFAP and β-S100 were comparable across groups. Considering all patients, sTREM-2 positively associated with Aβ42 (p = 0.04) and p-tau (=0.016), with the first being present only in the A+T- subgroup (p = 0.023). GFAP positively associated with Aβ42 in all patients (p = 0.020) and in the A+T+ subgroup (p = 0.04). Stratifying by APOE, a positive association of sTREM-2 and p-tau was confirmed selectively in carriers of ɛ4 (p = 0.018). Finally, sTREM-2 positively correlated with β-S100 in all subgroups, and with GFAP in A+T+ (p = 0.042). CONCLUSION: Our results confirm the increase of CSF sTREM-2 in AD, which associates with reduced amyloidopathy in A+T- patients. Moreover, microglial activation seems to increase CSF tau levels in carriers of APOEɛ4, is associated with astrocytic reactivity (GFAP) in A+T+, and likely leads the acquisition of a more neurotoxic astrocytic phenotype (β-S100).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Humans; Microglia; Peptide Fragments; tau Proteins

Characterizing Limbic-Predominant Age-Related TDP-43 Encephalopathy Without Alzheimer's Disease and Lewy Body Dementia in the Oldest Old: A Case Series. - Leiby, Anne-Marie C; Scambray, Kiana A; Nguyen, Hannah L; Basith, Farheen; Fakhraee, Shahrzad; Melikyan, Zarui A; Bukhari, Syed A; Montine, Thomas J; Corrada, Maria M; Kawas, Claudia H; Sajjadi, S Ahmad (J Alzheimers Dis, 2023)
BACKGROUND: Limbic-predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC) is a clinicopathological construct proposed to facilitate studying TDP-43 pathology in older individuals. OBJECTIVE: Our aim was to describe clinical and cognitive characteristics of LATE-NC without Alzheimer's disease neuropathologic change (ADNC) and Lewy body (LB) and to compare this with ADNC and primary age related tauopathy (PART). METHODS: In 364 autopsies of the oldest old of The 90+ Study, we identified those with LATE-NC without ADNC and LB. Control groups were participants with ADNC and PART. RESULTS: Of 31% of participants who had LATE-NC, only 5 (1.4%) had LATE-NC without ADNC and LB, all of whom had tau. These participants had a gradual and progressive cognitive decline. Four (80%) had dementia at death, a rate that was higher than ADNC (50%) and PART (21.7%). Mean duration of cognitive impairment was twice as long in LATE-NC without ADNC and LB (6.2 years) compared to ADNC (2.9 years) and PART (3 years). LATE-NC without ADNC and LB group had a higher prevalence of syncope, depression, and extrapyramidal signs than the ADNC and PART groups. CONCLUSIONS: Despite the high prevalence of LATE-NC, LATE-NC without ADNC and LB was rare in this large oldest-old cohort, highlighting the very high prevalence of multiple pathologic changes in the oldest old. Slowly progressive cognitive decline, ubiquitous memory impairment, history of syncope and depression, and extrapyramidal signs were prominent features among our LATE-NC without ADNC and LB group.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; DNA-Binding Proteins; Humans; Lewy Body Disease; Syncope; Tauopathies; TDP-43 Proteinopathies

Characterizing Performance Gaps of a Code-Based Dementia Algorithm in a Population-Based Cohort of Cognitive Aging. - Vassilaki, Maria; Fu, Sunyang; Christenson, Luke R; Garg, Muskan; Petersen, Ronald C; St Sauver, Jennifer; Sohn, Sunghwan (J Alzheimers Dis, 2023)
BACKGROUND: Multiple algorithms with variable performance have been developed to identify dementia using combinations of billing codes and medication data that are widely available from electronic health records (EHR). If the characteristics of misclassified patients are clearly identified, modifying existing algorithms to improve performance may be possible. OBJECTIVE: To examine the performance of a code-based algorithm to identify dementia cases in the population-based Mayo Clinic Study of Aging (MCSA) where dementia diagnosis (i.e., reference standard) is actively assessed through routine follow-up and describe the characteristics of persons incorrectly categorized. METHODS: There were 5,316 participants (age at baseline (mean (SD)): 73.3 (9.68) years; 50.7% male) without dementia at baseline and available EHR data. ICD-9/10 codes and prescription medications for dementia were extracted between baseline and one year after an MCSA dementia diagnosis or last follow-up. Fisher's exact or Kruskal-Wallis tests were used to compare characteristics between groups. RESULTS: Algorithm sensitivity and specificity were 0.70 (95% CI: 0.67, 0.74) and 0.95 (95% CI: 0.95, 0.96). False positives (i.e., participants falsely diagnosed with dementia by the algorithm) were older, with higher Charlson comorbidity index, more likely to have mild cognitive impairment (MCI), and longer follow-up (versus true negatives). False negatives (versus true positives) were older, more likely to have MCI, or have more functional limitations. CONCLUSIONS: We observed a moderate-high performance of the code-based diagnosis method against the population-based MCSA reference standard dementia diagnosis. Older participants and those with MCI at baseline were more likely to be misclassified.
Keywords: Alzheimer Disease; Cognitive Aging; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Male

Coexistence of Amyotrophic Lateral Sclerosis and Alzheimer's Disease: Case Report and Review of the Literature. - Verde, Federico; Aiello, Edoardo Nicolò; Adobbati, Laura; Poletti, Barbara; Solca, Federica; Tiloca, Cinzia; Sangalli, Davide; Maranzano, Alessio; Muscio, Cristina; Ratti, Antonia; Zago, Stefano; Ticozzi, Nicola; et al. (J Alzheimers Dis, 2023)
We describe a case of amyotrophic lateral sclerosis (ALS) associated with Alzheimer's disease (AD) and review the literature about the coexistence of the two entities, highlighting the following: mean age at onset is 63.8 years, with slight female predominance; ALS tends to manifest after cognitive impairment and often begins in the bulbar region; average disease duration is 3 years; cognitive phenotype is mostly amnestic; the pattern of brain involvement is, in most cases, consistent with AD. Our case and the reviewed ones suggest that patients with ALS and dementia lacking unequivocal features of FTD should undergo additional examinations in order to recognize AD.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Brain; Cognitive Dysfunction; Female; Frontotemporal Dementia; Humans; Male

Cognitive and Neuropsychological Profiles in Alzheimer's Disease and Primary Age-Related Tauopathy and the Influence of Comorbid Neuropathologies. - Walker, Jamie M; Gonzales, Mitzi M; Goette, William; Farrell, Kurt; White Iii, Charles L; Crary, John F; Richardson, Timothy E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease neuropathologic change (ADNC) is defined by the progression of both hyperphosphorylated-tau (p-tau) and amyloid-β (Aβ) and is the most common underlying cause of dementia worldwide. Primary age-related tauopathy (PART), an Aβ-negative tauopathy largely confined to the medial temporal lobe, is increasingly being recognized as an entity separate from ADNC with diverging clinical, genetic, neuroanatomic, and radiologic profiles. OBJECTIVE: The specific clinical correlates of PART are largely unknown; we aimed to identify cognitive and neuropsychological differences between PART, ADNC, and subjects with no tauopathy (NT). METHODS: We compared 2,884 subjects with autopsy-confirmed intermediate-high stage ADNC to 208 subjects with definite PART (Braak stage I-IV, Thal phase 0, CERAD NP score "absent") and 178 NT subjects from the National Alzheimer's Coordinating Center dataset. RESULTS: PART subjects were older than either ADNC or NT patients. The ADNC cohort had more frequent neuropathological comorbidities as well as APOE ɛ4 alleles than the PART or NT cohort, and less frequent APOE ɛ2 alleles than either group. Clinically, ADNC patients performed significantly worse than NT or PART subjects across cognitive measures, but PART subjects had selective deficits in measures of processing speed, executive function, and visuospatial function, although additional cognitive measures were further impaired in the presence of neuropathologic comorbidities. In isolated cases of PART with Braak stage III-IV, there are additional deficits in measures of language. CONCLUSION: Overall, these findings demonstrate underlying cognitive features specifically associated with PART, and reinforce the concept that PART is a distinct entity from ADNC.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Cognition; Executive Function; Humans; Tauopathies

Costs During the Last Five Years of Life for Patients with Clinical and Pathological Confirmed Diagnosis of Lewy Body Dementia and Alzheimer's Disease. - Zhu, Carolyn W; Gu, Yian; Kociolek, Anton J; Fernandez, Kayri K; Cosentino, Stephanie; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: Little is known regarding healthcare expenditures for patients with dementia with Lewy bodies (DLB) during the end of life. OBJECTIVE: This study estimated Medicare expenditures during the last 5 years of life in a decedent sample of patients who were clinically diagnosed with Alzheimer's disease (AD) or DLB and had autopsy confirmed diagnosis. METHODS: The study included 58 participants clinically diagnosed with mild dementia at study entry (AD: n = 44, DLB: n = 14) and also had autopsy-confirmed diagnoses of pure AD (n = 32), mixed AD+Lewy body (LB) (n = 5), or pure LB (n = 11). Total Medicare expenditures were compared by clinical and pathology confirmed diagnosis, adjusting for sex, age at death, and patient's cognition, function, comorbidities, and psychiatric and extrapyramidal symptoms. RESULTS: When pathology diagnoses were not considered, predicted annualized total Medicare expenditures during the last 5 years of life were similar between clinically diagnosed AD ($7,465±1,098) and DLB ($7,783±1,803). When clinical diagnoses were not considered, predicted expenditures were substantially higher in patients with pathology confirmed mixed AD+LB ($12,005±2,455) than either pure AD ($6,173±941) or pure LB ($4,629±1,968) cases. Considering clinical and pathology diagnosis together, expenditures for patients with clinical DLB and pathology mixed AD+LB ($23,592±3,679) dwarfed other groups. CONCLUSION: Medicare expenditures during the last 5 years of life were substantially higher in patients with mixed AD+LB pathology compared to those with pure-AD and pure-DLB pathologies, particularly in those clinically diagnosed with DLB. Results highlight the importance of having both clinical and pathology diagnoses in examining healthcare costs.

Different Trajectories of Apathy and Depression Among Subjective Cognitive Impairment Individuals with or without Conversion to Dementia: Results from the Memento Cohort in France. - Bogdan, Anamaria; Fabre, Roxane; Desmidt, Thomas; Golebiowski, Jérôme; Topin, Jérémie; Bethus, Ingrid; Hanon, Olivier; Boutoleau-Bretonnière, Claire; Wagemann, Nathalie; Annweiler, Cedric; Ousset, Pierre-Jean; Godefroy, Olivier; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Apathy and depression are two early behavioral symptoms in Alzheimer's disease (AD) and related disorders that often occur prior to the onset of cognitive decline and memory disturbances. Both have been associated with an increased risk of conversion to dementia, with a distinct neuropathology. OBJECTIVE: The assessment of the trajectories of apathy and depression and their independent impact on dementia conversion. METHODS: Apathy and Depression were measured using the Neuropsychiatric Inventory for caregiver (NPI) and clinician (NPI-C), among the nondemented individuals reporting subjective cognitive decline (SCD) at baseline. They were followed up over a 60-month period. Some converted to dementia, according to the methodology carried out by the French Memento Cohort. RESULTS: Among individuals with SCD (n = 2,323), the levels of apathy and depression were low and did not evolve significantly over the 60-month period, despite a trend in apathy increasing as of month 24. Regarding SCD individuals who converted to dementia within the 60-month period (n = 27), the prevalence of depression remained globally steady, while the levels of apathy increased over time. CONCLUSION: Apathy and depression have different trajectories among individuals with SCD and apathy alone is more likely-compared to depression-to be associated with conversion to dementia.

Disrupted excitation-inhibition balance in cognitively normal individuals at risk of Alzheimer's disease. - Fortel, Igor; Zhan, Liang; Ajilore, Olusola; Wu, Yichao; Mackin, Scott; Leow, Alex (bioRxiv, 2023)
BACKGROUND: Sex differences impact Alzheimer's disease (AD) neuropathology, but cell-to-network level dysfunctions in the prodromal phase are unclear. Alterations in hippocampal excitation-inhibition balance (EIB) have recently been linked to early AD pathology. OBJECTIVE: Examine how AD risk factors (age, APOE-ɛ4, amyloid-β) relate to hippocampal EIB in cognitively normal males and females using connectome-level measures. METHODS: Individuals from the OASIS-3 cohort (age 42-95) were studied (N = 437), with a subset aged 65+ undergoing neuropsychological testing (N = 231). RESULTS: In absence of AD risk factors (APOE-ɛ4/Aβ+), whole-brain EIB decreases with age more significantly in males than females (p = 0.021, β = -0.007). Regression modeling including APOE-ɛ4 allele carriers (Aβ-) yielded a significant positive AGE-by-APOE interaction in the right hippocampus for females only (p = 0.013, β = 0.014), persisting with inclusion of Aβ+ individuals (p = 0.012, β = 0.014). Partial correlation analyses of neuropsychological testing showed significant associations with EIB in females: positive correlations between right hippocampal EIB with categorical fluency and whole-brain EIB with the trail-making test (p < 0.05). CONCLUSION: Sex differences in EIB emerge during normal aging and progresses differently with AD risk. Results suggest APOE-ɛ4 disrupts hippocampal balance more than amyloid in females. Increased excitation correlates positively with neuropsychological performance in the female group, suggesting a duality in terms of potential beneficial effects prior to cognitive impairment. This underscores the translational relevance of APOE-ɛ4 related hyperexcitation in females, potentially informing therapeutic targets or early interventions to mitigate AD progression in this vulnerable population.

Early Diagnosis of Mild Cognitive Impairment due to Alzheimer's Disease Using a Composite of MemTrax and Blood Biomarkers. - Chen, Weineng; Lin, Cha; Su, Fengjuan; Fang, Yingying; Liu, Ganqiang; Chen, Yu-Chian; Zhou, Xianbo; Yao, Xiaoli; Ashford, Curtis B; Li, Feng; Ashford, J Wesson; Fu, Qingling; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Accessible measurements for the early detection of mild cognitive impairment (MCI) due to Alzheimer's disease (AD) are urgently needed to address the increasing prevalence of AD. OBJECTIVE: To determine the benefits of a composite MemTrax Memory Test and AD-related blood biomarker assessment for the early detection of MCI-AD in non-specialty clinics. METHODS: The MemTrax Memory Test and Montreal Cognitive Assessment were administered to 99 healthy seniors with normal cognitive function and 101 patients with MCI-AD; clinical manifestation and peripheral blood samples were collected. We evaluated correlations between the MemTrax Memory Test and blood biomarkers using Spearman's rank correlation analyses and then built discrimination models using various machine learning approaches that combined the MemTrax Memory Test and blood biomarker results. The models' performances were assessed according to the areas under the receiver operating characteristic curve. RESULTS: The MemTrax Memory Test and Montreal Cognitive Assessment areas under the curve for differentiating patients with MCI-AD from the healthy controls were similar. The MemTrax Memory Test strongly correlated with phosphorylated tau 181 and amyloid-β 42/40. The area under the curve for the best composite MemTrax Memory Test and blood biomarker model was 0.975 (95% confidence interval: 0.950-0.999). CONCLUSION: Combining MemTrax Memory Test and blood biomarker results is a promising new technique for the early detection of MCI-AD.

Effect of Metabolic Syndrome Risk Factors on Processing Speed and Executive Function in Three Racialized Groups. - Bouges, Shenikqua; Fischer, Barbara; Norton, Derek L; Wyman, Mary F; Lambrou, Nickolas; Zuelsdorff, Megan; Van Hulle, Carol A; Ennis, Gilda E; James, Taryn T; Johnson, Adrienne L; Chin, Nathaniel; Carlsson, Cynthia M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Metabolic syndrome (MetS) has been associated with increased risk for Alzheimer's disease and related dementias (ADRD). Understanding the association of MetS risk factors to processing speed and executive function in the pre-clinical stages of ADRD in under-represented groups would offer insight on potential mechanisms through which MetS associates with ADRD risk. OBJECTIVE: Examine association of MetS features and processing speed and executive function across three racial groups. METHODS: Cognitively unimpaired adults from the Wisconsin Alzheimer's Disease Research Center and the Wisconsin Registry for Alzheimer's Disease Prevention completed blood-draws and neuropsychological testing. Six cognitive outcomes were assessed in association to MetS risk factors: Trailmaking Tests A and B, Animal Fluency, Digit Symbol, and composite scores for Processing Speed and Executive Function. Linear mixed effect models were used to assess the relationship between MetS risk factor count and longitudinal cognitive performance across three racialized groups. RESULTS: Participant sample sizes varied by outcome analyzed (N = 714-1,088). African American and Native American groups exhibited higher rates of MetS than non-Hispanic Whites. MetS was associated with processing speed and executive function across all racialized groups. Three-way interaction by racialized group was limited to one cognitive outcome: Trailmaking Test A. CONCLUSION: Metabolic dysfunction incrementally affects cognitive trajectory, with generally similar associations across racial groups. Since racialized groups exhibit higher levels of both MetS and ADRD, MetS may represent a driving factor for increased ADRD risk experience by racialized group and an important and modifiable target through which to reduce risk of ADRD.

Effects of a Physical Activity Program that Incorporates Exercises Targeting Balance, Strength, and Proprioception on Cognitive Functions and Physical Performance in Old Adults with Mild Cognitive Impairment. - Boulares, Ayoub; Fabre, Claudine; Cherni, Ala; Jdidi, Hela; Gaied Chortane, Sabri; Trompetto, Carlo; Puce, Luca; Bragazzi, Nicola Luigi (J Alzheimers Dis, 2023)
BACKGROUND: Aging often leads to cognitive function decline, sensory structure deterioration, and musculoskeletal system weakening. This impacts postural control during static and dynamic activities like walking, increasing the fall risk among the elderly. Older adults with mild cognitive impairment (MCI) face an elevated fall risk and cognitive decline, magnifying the public health concern. OBJECTIVE: This study aimed to explore solutions by investigating the effects of a multi-component physical activity program on cognitive and motor functions in MCI patients. METHODS: Twenty-three participants were enrolled in the study and assigned into two groups: an intervention group (n = 13; age = 85.7±5.5 years) and a control group (n = 9; age = 85±6.7 years). The study spanned two months, with participants engaging in three 60-minute weekly physical exercise sessions. The intervention focused on improving proprioception, muscle strength, and balance. RESULTS: Results demonstrated significant enhancements in physical performance, fall risk reduction, and balance (p < 0.05). Various tests, including the timed up and go test, Unipedal Stance test, Tinetti test, Short Physical Performance Battery, and 6-minute walking test, indicated these improvements. Cognitive function was evaluated with the Mini-Mental State Examination, revealing non-significant progress (p > 0.05). Predictive models for outcomes were developed using linear regression analysis during the follow-up stage. CONCLUSIONS: This study underscores the effectiveness of a multi-component physical activity program encompassing balance, proprioception, and muscle-strengthening exercises as a non-pharmaceutical approach in improving balance skills and playing a key role in mitigating the risk of falls among old adults with MCI.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Exercise; Exercise Therapy; Humans; Physical Functional Performance; Postural Balance; Proprioception; Time and Motion Studies

The Efficacy and Safety of Physiotherapy in People with Dementia: A Systematic Review. - Saúde, Alexandra; Bouça-Machado, Raquel; Leitão, Mariana; Benedetti, Andrea; Ferreira, Joaquim J (J Alzheimers Dis, 2023)
BACKGROUND: Physiotherapy has become increasingly relevant as a new therapeutic intervention for dementia. However, it is unclear which interventions are the most suitable. OBJECTIVE: This study sought to summarize and critically appraise the evidence on physiotherapy interventions in dementia. METHODS: A systematic review conducted using CENTRAL, MEDLINE, and PEDro databases, from their inception to July 2022, identified all experimental studies of dementia that included physiotherapy interventions. RESULTS: Of 194 articles included, the most frequently used interventions were aerobic training (n = 82, 42%), strength training (n = 79, 41%), balance training (n = 48, 25%), and stretching (n = 22, 11%). These were associated with a positive effect on several motor and cognitive outcomes. A total number of 1,119 adverse events were reported. CONCLUSION: Physiotherapy has several motor and cognitive benefits in dementia. Future research should focus on establishing a physiotherapy prescription protocol for people with mild cognitive impairment and for each stage of dementia.
Keywords: Cognitive Dysfunction; Dementia; Humans; Physical Therapy Modalities; Resistance Training

Extracellular Tau Oligomers Damage the Axon Initial Segment. - Best, Merci N; Lim, Yunu; Ferenc, Nina N; Kim, Nayoung; Min, Lia; Wang, Dora Bigler; Sharifi, Kamyar; Wasserman, Anna E; McTavish, Sloane A; Siller, Karsten H; Jones, Marieke K; Jenkins, Paul M; et al. (J Alzheimers Dis, 2023)
BACKGROUND: In Alzheimer's disease (AD) brain, neuronal polarity and synaptic connectivity are compromised. A key structure for regulating polarity and functions of neurons is the axon initial segment (AIS), which segregates somatodendritic from axonal proteins and initiates action potentials. Toxic tau species, including extracellular oligomers (xcTauOs), spread tau pathology from neuron to neuron by a prion-like process, but few other cell biological effects of xcTauOs have been described. OBJECTIVE: Test the hypothesis that AIS structure is sensitive to xcTauOs. METHODS: Cultured wild type (WT) and tau knockout (KO) mouse cortical neurons were exposed to xcTauOs, and quantitative western blotting and immunofluorescence microscopy with anti-TRIM46 monitored effects on the AIS. The same methods were used to compare TRIM46 and two other resident AIS proteins in human hippocampal tissue obtained from AD and age-matched non-AD donors. RESULTS: Without affecting total TRIM46 levels, xcTauOs reduce the concentration of TRIM46 within the AIS and cause AIS shortening in cultured WT, but not TKO neurons. Lentiviral-driven tau expression in tau KO neurons rescues AIS length sensitivity to xcTauOs. In human AD hippocampus, the overall protein levels of multiple resident AIS proteins are unchanged compared to non-AD brain, but TRIM46 concentration within the AIS and AIS length are reduced in neurons containing neurofibrillary tangles. CONCLUSION: xcTauOs cause partial AIS damage in cultured neurons by a mechanism dependent on intracellular tau, thereby raising the possibility that the observed AIS reduction in AD neurons in vivo is caused by xcTauOs working in concert with endogenous neuronal tau.

High-Quality Sleep Mitigates ABCA7-Related Generalization Deficits in Healthy Older African Americans. - Sinha, Neha; Fausto, Bernadette A; Mander, Bryce; Gluck, Mark A (J Alzheimers Dis, 2023)
BACKGROUND: Both sleep deficiencies and Alzheimer's disease (AD) disproportionately affect older African Americans. Genetic susceptibility to AD further compounds risk for cognitive decline in this population. Aside from APOE ɛ4, ABCA7 rs115550680 is the strongest genetic locus associated with late-onset AD in African Americans. While sleep and ABCA7 rs115550680 independently influence late-life cognitive outcomes, we know too little about the interplay between these two factors on cognitive function. OBJECTIVE: We investigated the interaction between sleep and ABCA7 rs115550680 on hippocampal-dependent cognitive function in older African Americans. METHODS: One-hundred fourteen cognitively healthy older African Americans were genotyped for ABCA7 risk (n = 57 carriers of risk "G" allele; n = 57 non-carriers), responded to lifestyle questionnaires, and completed a cognitive battery. Sleep was assessed via a self-reported rating of sleep quality (poor, average, good). Covariates included age and years of education. RESULTS: Using ANCOVA, we found that carriers of the risk genotype who reported poor or average sleep quality demonstrated significantly poorer generalization of prior learning¾a cognitive marker of AD¾compared to their non-risk counterparts. Conversely, there was no genotype-related difference in generalization performance in individuals who reported good sleep quality. CONCLUSION: These results indicate that sleep quality may be neuroprotective against genetic risk for AD. Future studies employing more rigorous methodology should investigate the mechanistic role of sleep neurophysiology in the pathogenesis and progression of AD associated with ABCA7. There is also need for the continued development of non-invasive sleep interventions tailored to racial groups with specific AD genetic risk profiles.

Implication of Circulating Extracellular Vesicles-Bound Amyloid-β42 Oligomers in the Progression of Alzheimer's Disease. - M.R. BenKhedher; Haddad, Mohamed; Fülöp, Tamás; Laurin, Danielle; Ramassamy, Charles (J Alzheimers Dis, 2023)
BACKGROUND: The perplex interrelation between circulating extracellular vesicles (cEVs) and amyloid-β (Aβ) deposits in the context of Alzheimer's disease (AD) is poorly understood. OBJECTIVE: This study aims to 1) analyze the possible cross-linkage of the neurotoxic amyloid-β oligomers (oAβ) to the human cEVs, 2) identify cEVs corona proteins associated with oAβ binding, and 3) analyze the distribution and expression of targeted cEVs proteins in preclinical participants converted to AD 5 years later (Pre-AD). METHODS: cEVs were isolated from 15 Pre-AD participants and 15 healthy controls selected from the Canadian Study of Health and Aging. Biochemical, clinical, lipid, and inflammatory profiles were measured. oAβ and cEVs interaction was determined by nanoparticle tracking analysis and proteinase K digestion. cEVs bound proteins were determined by ELISA. RESULTS: oAβ were trapped by cEVs and were topologically bound to their external surface. We identified surface-exposed proteins functionally able to conjugate oAβ including apolipoprotein J (apoJ), apoE and RAGE, with apoJ being 30- to 130-fold higher than RAGE and apoE, respectively. The expression of cEVs apoJ was significantly lower in Pre-AD up to 5 years before AD onset. CONCLUSION: Our findings suggest that cEVs might participate in oAβ clearance and that early dysregulation of cEVs could increase the risk of conversion to AD.

Klotho Gene Expression Is Decreased in Peripheral Blood Mononuclear Cells in Patients with Alzheimer's Disease and Frontotemporal Dementia. - Sorrentino, Federica; Fenoglio, Chiara; Sacchi, Luca; Serpente, Maria; Arighi, Andrea; Carandini, Tiziana; Arosio, Beatrice; Ferri, Evelyn; Arcaro, Marina; Visconte, Caterina; Rotondo, Emanuela; Scarpini, Elio; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The longevity gene Klotho (KL) was recently associated with neurodegenerative diseases including Alzheimer's disease (AD). Its role in the brain has not been completely elucidated, although evidence suggests that KL-VS heterozygosity is associated with a reduced risk of AD in Apolipoprotein E ɛ4 carriers. Conversely, no data about genetic association with frontotemporal dementia (FTD) are available so far. OBJECTIVE: To investigate the involvement of KL in AD and FTD by the determination of the genetic frequency of KL-VS variant and the expression analysis of KL gene. METHODS: A population consisting of 438 patients and 240 age-matched controls was enrolled for the study. KL-VS and APOE genotypes were assessed by allelic discrimination through a QuantStudio 12K system. KL gene expression analysis was performed in a restricted cohort of patients consisting of 43 AD patients, 41 FTD patients and 19 controls. KL gene expression was assessed in peripheral blood mononuclear cells with specific TaqMan assay. Statistical analysis was performed using GraphPad 9 Prims software. RESULTS: KL-VS frequency was comparable to the ones found in literature and no differences were found in both allelic and genotypic frequencies between patients and controls were found. Conversely, KL expression levels were significantly lower in AD and FTD patients compared with controls (mean fold regulation - 4.286 and - 6.561 versus controls in AD and FTD, respectively, p = 0.0037). CONCLUSION: This is the first study investigating KL in FTD. We showed a decreased expression of the gene in AD and FTD, independent of the genotype, suggesting a role of Klotho in common steps during neurodegeneration.

Medial Temporal Lobe Atrophy in Predementia Alzheimer's Disease: A Longitudinal Multi-Site Study Comparing Staging and A/T/N in a Clinical Research Cohort. - Jarholm, Jonas Alexander; Bjørnerud, Atle; Dalaker, Turi Olene; Akhavi, Mehdi Sadat; Kirsebom, Bjørn Eivind; Pålhaugen, Lene; Nordengen, Kaja; Grøntvedt, Gøril Rolfseng; Nakling, Arne; Kalheim, Lisa F; Almdahl, Ina S; Tecelao, Sandra; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Atrophy of the medial temporal lobe (MTL) is a biological characteristic of Alzheimer's disease (AD) and can be measured by segmentation of magnetic resonance images (MRI). OBJECTIVE: To assess the clinical utility of automated volumetry in a cognitively well-defined and biomarker-classified multi-center longitudinal predementia cohort. METHODS: We used Automatic Segmentation of Hippocampal Subfields (ASHS) to determine MTL morphometry from MRI. We harmonized scanner effects using the recently developed longitudinal ComBat. Subjects were classified according to the A/T/N system, and as normal controls (NC), subjective cognitive decline (SCD), or mild cognitive impairment (MCI). Positive or negative values of A, T, and N were determined by cerebrospinal fluid measurements of the Aβ42/40 ratio, phosphorylated and total tau. From 406 included subjects, longitudinal data was available for 206 subjects by stage, and 212 subjects by A/T/N. RESULTS: Compared to A-/T-/N- at baseline, the entorhinal cortex, anterior and posterior hippocampus were smaller in A+/T+orN+. Compared to NC A- at baseline, these subregions were also smaller in MCI A+. Longitudinally, SCD A+ and MCI A+, and A+/T-/N- and A+/T+orN+, had significantly greater atrophy compared to controls in both anterior and posterior hippocampus. In the entorhinal and parahippocampal cortices, longitudinal atrophy was observed only in MCI A+ compared to NC A-, and in A+/T-/N- and A+/T+orN+ compared to A-/T-/N-. CONCLUSION: We found MTL neurodegeneration largely consistent with existing models, suggesting that harmonized MRI volumetry may be used under conditions that are common in clinical multi-center cohorts.
Keywords: Alzheimer Disease; Atrophy; Cognitive Dysfunction; Entorhinal Cortex; Hippocampus; Humans; Magnetic Resonance Imaging; Temporal Lobe

Midlife Neuropsychological Profiles and Associated Vascular Risk: The Bogalusa Heart Study. - De Anda-Duran, Ileana; Kolachalama, Vijaya B; Carmichael, Owen T; Hwang, Phillip H; Fernandez, Camilo; Au, Rhoda; Bazzano, Lydia A; Libon, David J (J Alzheimers Dis, 2023)
BACKGROUND: Individuals with Alzheimer's disease (AD) often present with coexisting vascular pathology that is expressed to different degrees and can lead to clinical heterogeneity. OBJECTIVE: To examine the utility of unsupervised statistical clustering approaches in identifying neuropsychological (NP) test performance subtypes that closely correlate with carotid intima-media thickness (cIMT) in midlife. METHODS: A hierarchical agglomerative and k-means clustering analysis based on NP scores (standardized for age, sex, and race) was conducted among 1,203 participants (age 48±5.3 years) from the Bogalusa Heart Study. Regression models assessed the association between cIMT ≥50th percentile and NP profiles, and global cognitive score (GCS) tertiles for sensitivity analysis. RESULTS: Three NP profiles were identified: Mixed-low performance [16%, n = 192], scores ≥1 SD below the mean on immediate, delayed free recall, recognition verbal memory, and information processing; Average [59%, n = 704]; and Optimal [26%, n = 307] NP performance. Participants with greater cIMT were more likely to have a Mixed-low profile [OR = 3.10, 95% CI (2.13, 4.53), p < 0.001] compared to Optimal. After adjusting for education and cardiovascular (CV) risks, results remained. The association with GCS tertiles was more attenuated [lowest (34%, n = 407) versus highest (33%, n = 403) tertile: adjusted OR = 1.66, 95% CI (1.07, 2.60), p = 0.024]. CONCLUSION: As early as midlife, individuals with higher subclinical atherosclerosis were more likely to be in the Mixed-low profile, underscoring the potential malignancy of CV risk as related to NP test performance, suggesting that classification approaches may aid in identifying those at risk for AD/vascular dementia spectrum illness.

Mild Cognitive Impairment is Associated with Poorer Everyday Decision Making. - Fenton, Laura; Han, S Duke; DiGuiseppi, Carolyn G; Fowler, Nicole R; Hill, Linda; Johnson, Rachel L; Peterson, Ryan A; Knoepke, Christopher E; Matlock, Daniel D; Moran, Ryan; Karlawish, Jason; Betz, Marian E (J Alzheimers Dis, 2023)
BACKGROUND: Older adults are faced with many unique and highly consequential decisions such as those related to finances, healthcare, and everyday functioning (e.g., driving cessation). Given the significant impact of these decisions on independence, wellbeing, and safety, an understanding of how cognitive impairment may impact decision making in older age is important. OBJECTIVE: To examine the impact of mild cognitive impairment (MCI) on responses to a modified version of the Short Portable Assessment of Capacity for Everyday Decision making (SPACED). METHODS: Participants were community-dwelling, actively driving older adults (N = 301; M age = 77.1 years, SD = 5.1; 69.4% with a college degree or higher; 51.2% female; 95.3% White) enrolled in the Advancing Understanding of Transportation Options (AUTO) study. A generalized linear model adjusted for age, education, sex, randomization group, cognitive assessment method, and study site was used to examine the relationship between MCI status and decision making. RESULTS: MCI status was associated with poorer decision making; participants with MCI missed an average of 2.17 times more points on the SPACED than those without MCI (adjusted mean ratio: 2.17, 95% CI: 1.02, 4.61, p = 0.044). CONCLUSION: This finding supports the idea that older adults with MCI exhibit poorer decision-making abilities than cognitively normal older adults. It also suggests that older adults with MCI may exhibit poorer decision making across a wide range of decision contexts.
Keywords: Aged; Cognitive Dysfunction; Decision Making; Delivery of Health Care; Educational Status; Female; Humans; Independent Living; Male

Mindfulness Prevents Depression and Psychopathology in Elderly People with Mild to Moderate Alzheimer's Disease: A Randomized Clinical Trial. - Quintana-Hernández, Domingo J; Rojas-Hernández, Jaime; Santana-Del Pino, Angelo; Céspedes Suárez, Carmen; Pellejero Silva, Mónica; Miró-Barrachina, María Teresa; Ibáñez Fernández, Ignacio; Estupiñán López, José Antonio; Borkel, Lucas F (J Alzheimers Dis, 2023)
BACKGROUND: This longitudinal study addressed whether mindfulness practice prevents psychological and behavioral symptoms, especially mood disorders, in Alzheimer's disease (AD). OBJECTIVE: To assess the incidence of depression in the course of AD and to determine which non-pharmacological treatment (NPT) is most effective in preventing psychopathological symptoms. METHODS: We conducted a longitudinal, non-inferiority and equivalence randomized clinical trial, repeated-measures design, with a control group and three experimental treatments: mindfulness, cognitive stimulation, and relaxation. Each experimental group performed three weekly sessions for two years. The pharmacological treatment of all participants was donepezil (10 mg). Participants were patients with probable AD without diagnosed depression from the public neurology services of the Canary Health Service, Spain. Psychological evaluation was performed using the Geriatric Depression Scale (GDS), Hamilton Depression Rating Scale (HDRS), and Neuropsychiatric Inventory (NPI-Q). The statistical analysis included only patients who attended at least 75% of the sessions. A nonparametric, repeated-measures analysis was performed with Kruskal-Wallis H test and between-group differences with Mann-Whitney U test with Bonferroni correction (p < 0.008). Effect size was calculated with partial eta-squared. RESULTS: The results showed significant differences with large effect sizes (η2p>0.14) between mindfulness and the rest of the experimental groups as well as the control in the GDS, HDRS, and NPI-Q scales. CONCLUSION: Compared to the other experimental groups, only mindfulness prevented the onset of depression and other psychopathologies in early-stage AD. Based on its effectiveness in maintaining cognitive functions and preventing psychopathology, we recommend mindfulness as the first-choice NPT for mild to moderate AD.
Keywords: Aged; Alzheimer Disease; Depression; Donepezil; Humans; Longitudinal Studies; Mindfulness

Montreal Cognitive Assessment in Mild Cognitive Impairment: Relationship with Cerebrospinal Fluid Biomarkers and Conversion to Dementia. - Bernardes, Catarina; Lima, Marisa; Duro, Diana; Silva-Spínola, Anuschka; Durães, João; Tábuas-Pereira, Miguel; Baldeiras, Ines; Freitas, Sandra; Santana, Isabel (J Alzheimers Dis, 2023)
BACKGROUND: Mild cognitive impairment (MCI) is considered a prodromal state of dementia. Abnormal values of cerebrospinal fluid Alzheimer's disease biomarkers (CSF-AD-b) have been associated with a higher risk of conversion to dementia (due to Alzheimer's disease), but studies evaluating the ability of Montreal Cognitive Assessment (MoCA) in this task are lacking. OBJECTIVE: This study aims to investigate the relationship between MoCA and CSF-AD-b, as well as the ability of those tools to predict conversion to dementia. METHODS: Taking advantage of our MCI cohort with biological characterization on longitudinal follow-up (180 patients followed for 62.6 months during which 41.3% converted), we computed MoCA and MMSE z-scores, using Portuguese normative data. The performance in MoCA z-score was correlated with CSF-AD-b and the relative time to conversion and risk according to baseline characteristics were analyzed using Kaplan-Meier analysis and Cox regression models. RESULTS: MoCA z-scores were correlated with Aβ42 (p = 0.026), t-tau (p = 0.033), and p-tau (p = 0.01). Impaired MMSE (p < 0.001) and MoCA z-scores (p = 0.019), decreased Aβ42 (p < 0.001) and increased t-tau (p < 0.001) and p-tau (p < 0.001) were associated with shorter estimated time of conversion. Aβ42 (p < 0.001) and MMSE z-scores (p = 0.029) were independent predictors of conversion. For those with at least 9 years of education, MoCA z-score (p = 0.004) (but not MMSE) was an independent predictor of conversion as well as Aβ42. CONCLUSIONS: This study confirms the role of CSF-AD-b, namely Aβ42, in predicting conversion from MCI to dementia and suggests the utility of MoCA in predicting conversion in highly educated subjects, supporting its use in the evaluation of MCI patients.

Moral Emotions and Their Brain Structural Correlates Across Neurodegenerative Disorders. - Baez, Sandra; Trujillo-Llano, Catalina; de Souza, Leonardo Cruz; Lillo, Patricia; Forno, Gonzalo; Santamaría-García, Hernando; Okuma, Cecilia; Alegria, Patricio; Huepe, David; Ibáñez, Agustín; Decety, Jean; Slachevsky, Andrea (J Alzheimers Dis, 2023)
BACKGROUND: Although social cognition is compromised in patients with neurodegenerative disorders such as behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD), research on moral emotions and their neural correlates in these populations is scarce. No previous study has explored the utility of moral emotions, compared to and in combination with classical general cognitive state tools, to discriminate bvFTD from AD patients. OBJECTIVE: To examine self-conscious (guilt and embarrassment) and other-oriented (pity and indignation) moral emotions, their subjective experience, and their structural brain underpinnings in bvFTD (n = 31) and AD (n = 30) patients, compared to healthy controls (n = 37). We also explored the potential utility of moral emotions measures to discriminate bvFTD from AD. METHODS: We used a modified version of the Moral Sentiment Task measuring the participants' accuracy scores and their emotional subjective experiences. RESULTS: bvFTD patients exhibited greater impairments in self-conscious and other-oriented moral emotions as compared with AD patients and healthy controls. Moral emotions combined with general cognitive state tools emerged as useful measures to discriminate bvFTD from AD patients. In bvFTD patients, lower moral emotions scores were associated with lower gray matter volumes in caudate nucleus and inferior and middle temporal gyri. In AD, these scores were associated with lower gray matter volumes in superior and middle frontal gyri, middle temporal gyrus, inferior parietal lobule and supramarginal gyrus. CONCLUSION: These findings contribute to a better understanding of moral emotion deficits across neurodegenerative disorders, highlighting the potential benefits of integrating this domain into the clinical assessment.
Keywords: Alzheimer Disease; Brain; Emotions; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Morals; Neuropsychological Tests

Multi-Site Cross-Site Inter-Rater and Test-Retest Reliability and Construct Validity of the MarkVCID White Matter Hyperintensity Growth and Regression Protocol. - Bahrani, Ahmed A; Abner, Erin L; DeCarli, Charles S; Barber, Justin M; Sutton, Abigail C; Maillard, Pauline; Sandoval, Francisco; Arfanakis, Konstantinos; Yang, Yung-Chuan; Evia, Arnold M; Schneider, Julie A; Habes, Mohamad; et al. (J Alzheimers Dis, 2023)
BACKGROUND: White matter hyperintensities (WMH) that occur in the setting of vascular cognitive impairment and dementia (VCID) may be dynamic increasing or decreasing volumes or stable over time. Quantifying such changes may prove useful as a biomarker for clinical trials designed to address vascular cognitive-impairment and dementia and Alzheimer's Disease. OBJECTIVE: Conducting multi-site cross-site inter-rater and test-retest reliability of the MarkVCID white matter hyperintensity growth and regression protocol. METHODS: The NINDS-supported MarkVCID Consortium evaluated a neuroimaging biomarker developed to track WMH change. Test-retest and cross-site inter-rater reliability of the protocol were assessed. Cognitive test scores were analyzed in relation to WMH changes to explore its construct validity. RESULTS: ICC values for test-retest reliability of WMH growth and regression were 0.969 and 0.937 respectively, while for cross-site inter-rater ICC values for WMH growth and regression were 0.995 and 0.990 respectively. Word list long-delay free-recall was negatively associated with WMH growth (p < 0.028) but was not associated with WMH regression. CONCLUSIONS: The present data demonstrate robust ICC validity of a WMH growth/regression protocol over a one-year period as measured by cross-site inter-rater and test-retest reliability. These data suggest that this approach may serve an important role in clinical trials of disease-modifying agents for VCID that may preferentially affect WMH growth, stability, or regression.

Neuropathologic Changes of Alzheimer's Disease and Related Dementias: Relevance to Future Prevention. - White, Lon R; Corrada, Maria M; Kawas, Claudia H; Cholerton, Brenna A; Edland, Steve E; Flanagan, Margaret E; Montine, Thomas J (J Alzheimers Dis, 2023)
BACKGROUND: Decedents with late-life dementia are often found at autopsy to have vascular pathology, cortical Lewy bodies, hippocampal sclerosis, and/or TDP-43 encephalopathy alone or with concurrent Alzheimer's disease (AD) lesions. Nonetheless, it is commonly believed that AD neuropathologic changes (NC) are the dominant or exclusive drivers of late-life dementia. OBJECTIVE: Assess associations of end-of-life cognitive impairment with any one or any combination of five distinct NC. Assess impairment prevalence among subjects having natural resistance to each type of NC. METHODS: Brains from 1,040 autopsied participants of the Honolulu-Asia Study, the Nun Study, and the 90 + Study were examined for NC of AD, Lewy body dementia, microvascular brain injury, hippocampal sclerosis, and limbic predominate TDP-43 encephalopathy. Associations with impairment were assessed for each NC and for NC polymorbidity (variable combinations of 2-5 concurrent NC). RESULTS: Among 387 autopsied decedents with severe cognitive impairment, 20.4% had only AD lesions (ADNC), 25.3% had ADNC plus 1 other NC, 11.1% had ADNC plus 2 or more other NC, 28.7% had no ADNC but 1-4 other NC, and 14.5% had no/negligible NC. Combinations of any two, three, or four NC were highly frequent among the impaired. Natural resistance to ADNC or any other single NC had a modest impact on overall cohort impairment levels. CONCLUSION: Polymorbidity involving 1-5 types of concurrent NC is a dominant neuropathologic feature of AD and related dementias. This represents a daunting challenge to future prevention and could explain failures of prior preventive intervention trials and of efforts to identify risk factors.

Neuropathology of Anti-Amyloid-β Immunotherapy: A Case Report. - Castellani, Rudolph J; Shanes, Elisheva; McCord, Matthew; Reish, Nicholas J; Flanagan, Margaret E; Mesulam, M-Marsel; Jamshidi, Pouya (J Alzheimers Dis, 2023)
Host responses to anti-amyloid-β (Aβ) antibody therapy are evident in neuroimaging changes and clinical symptoms in a subset of clinical trial subjects receiving such therapy. The pathological basis for the imaging changes and clinical symptoms is not known, nor is the precise mechanism of Aβ clearing. We report the autopsy findings in a 65-year-old woman who received three open label infusions of the experimental anti-Aβ drug lecanemab over about one month. Four days after the last infusion, she was treated with tissue plasminogen activator for acute stroke symptoms and died several days later with multifocal hemorrhage. Neuropathological examination demonstrated histiocytic vasculitis involving blood vessels with cerebral amyloid angiopathy. Fragmentation and phagocytosis of vascular Aβ were present throughout the cerebral cortex. Phagocytosis of parenchymal Aβ plaques was noted. Changes suggestive of Aβ and phosphorylated tau "clearing" were also noted. The findings overall suggest that anti-Aβ treatment stimulated a host response to Aβ, i.e., target engagement. The findings also provide evidence that amyloid-related imaging abnormalities might be indicative of an Aβ phagocytic syndrome within cerebral vasculature and parenchymal brain tissue in some cases.

Neuroprotective Properties of Eudesmin on a Cellular Model of Amyloid-β Peptide Toxicity. - Castillo, Carolina; Bravo-Arrepol, Gastón; Wendt, Aline; Saez-Orellana, Francisco; Millar, Camila; Burgos, Carlos F; Gavilán, Javiera; Pacheco, Carla; Ahumada-Rudolph, Ramón; Napiórkowska, Mariola; Pérez, Claudia; Becerra, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive impairment and memory loss. One of the hallmarks in AD is amyloid-β peptide (Aβ) accumulation, where the soluble oligomers of Aβ (AβOs) are the most toxic species, deteriorating the synaptic function, membrane integrity, and neuronal structures, which ultimately lead to apoptosis. Currently, there are no drugs to arrest AD progression, and current scientific efforts are focused on searching for novel leads to control this disease. Lignans are compounds extracted from conifers and have several medicinal properties. Eudesmin (Eu) is an extractable lignan from the wood of Araucaria araucana, a native tree from Chile. This metabolite has shown a range of biological properties, including the ability to control inflammation and antibacterial effects. OBJECTIVE: In this study, the neuroprotective abilities of Eu on synaptic failure induced by AβOs were analyzed. METHODS: Using neuronal models, PC12 cells, and in silico simulations we evaluated the neuroprotective effect of Eu (30 nM) against the toxicity induced by AβOs. RESULTS: In primary cultures from mouse hippocampus, Eu preserved the synaptic structure against AβOs toxicity, maintaining stable levels of the presynaptic protein SV2 at the same concentration. Eu also averted synapsis failure from the AβOs toxicity by sustaining the frequencies of cytosolic Ca2+ transients. Finally, we found that Eu (30 nM) interacts with the Aβ aggregation process inducing a decrease in AβOs toxicity, suggesting an alternative mechanism to explain the neuroprotective activity of Eu. CONCLUSION: We believe that Eu represents a novel lead that reduces the Aβ toxicity, opening new research venues for lignans as neuroprotective agents.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Lignans; Mice; Neuroprotective Agents; PC12 Cells; Rats

Non-Pharmacological Interventions for Feeding and Eating Disorders in Persons with Dementia: Systematic Review and Evidence Summary. - Chen, Hong-Li; Li, Cheng; Wang, Jing; Fei, Yang; Min, Min; Zhao, Yue; Shan, En-Fang; Yin, Yue-Heng; Liu, Chong-Yuan; Li, Xian-Wen (J Alzheimers Dis, 2023)
BACKGROUND: Feeding and eating disorders related to cognitive and psycho-behavioral symptoms are strongly associated with health status in persons with dementia (PWD). Non-pharmacological interventions have been the priority selection to address this significant issue. However, the direct targets of non-pharmacological interventions are unclear and there is no consistent evidence of recommendations on the intervention of different dementia stages and the settings of intervention practice. OBJECTIVE: To provide caregivers with a set of self-help non-pharmacological interventions for feeding and eating disorders in PWD. METHODS: Based on the process of evidence summary, a systematic literature search was performed on dementia websites and seven databases. Two researchers screened the studies independently and appraise the quality. The evidence was graded by Joanna Briggs Institute Grades of Recommendation. RESULTS: Twenty-eight articles were included. Twenty-three non-pharmacological intervention recommendations were categorized into six themes containing oral nutritional supplementation, assistance with eating and drinking, person-centered mealtime care, environmental modification, education or training, and multi-component intervention. These interventions corresponded to three direct targets including improving engagement, making up for loss ability, and increasing food intake directly. They were applied to different stages of dementia and most interventions were targeted at PWD in long-term care institutions. CONCLUSION: This article summarized the direct targets and the specific implementation of recommendations at different stages of dementia to provide caregivers with self-help non-pharmacological interventions. The practice of recommendations was more applicable to institutionalized PWD. When applied to PWD at home, caregivers need to identify the specific feeding and eating conditions at different stages and adopted the interventions in conjunction with the wishes of the PWD and professional advice.
Keywords: Caregivers; Dementia; Feeding and Eating Disorders; Health Status; Humans; Nutritional Status

Phonological and Semantic Fluency in Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Olmos-Villaseñor, Rocio; Sepulveda-Silva, Consuelo; Julio-Ramos, Teresa; Fuentes-Lopez, Eduardo; Toloza-Ramirez, David; Santibañez, Rodrigo A; Copland, David A; Mendez-Orellana, Carolina (J Alzheimers Dis, 2023)
BACKGROUND: Semantic and Phonological fluency (SF and PF) are routinely evaluated in patients with Alzheimer's disease (AD). There are disagreements in the literature regarding which fluency task is more affected while developing AD. Most studies focus on SF assessment, given its connection with the temporoparietal amnesic system. PF is less reported, it is related to working memory, which is also impaired in probable and diagnosed AD. Differentiating between performance on these tasks might be informative in early AD diagnosis, providing an accurate linguistic profile. OBJECTIVE: Compare SF and PF performance in healthy volunteers, volunteers with probable AD, and patients with AD diagnosis, considering the heterogeneity of age, gender, and educational level variables. METHODS: A total of 8 studies were included for meta-analysis, reaching a sample size of 1,270 individuals (568 patients diagnosed with AD, 340 with probable AD diagnosis, and 362 healthy volunteers). RESULTS: The three groups consistently performed better on SF than PF. When progressing to a diagnosis of AD, we observed a significant difference in SF and PF performance across our 3 groups of interest (p = 0.04). The age variable explained a proportion of this difference in task performance across the groups, and as age increases, both tasks equally worsen. CONCLUSION: The performance of SF and PF might play a differential role in early AD diagnosis. These tasks rely on partially different neural bases of language processing. They are thus worth exploring independently in diagnosing normal aging and its transition to pathological stages, including probable and diagnosed AD.
Keywords: Alzheimer Disease; Humans; Linguistics; Neuropsychological Tests; Semantics; Verbal Behavior

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

PM2.5 and Dementia in a Low Exposure Setting: The Influence of Odor Identification Ability and APOE. - Andersson, John; Sundström, Anna; Nordin, Maria; Segersson, David; Forsberg, Bertil; Adolfsson, Rolf; Oudin, Anna (J Alzheimers Dis, 2023)
BACKGROUND: Growing evidence show that long term exposure to air pollution increases the risk of dementia. OBJECTIVE: The aim of this study was to investigate associations between PM2.5 exposure and dementia in a low exposure area, and to investigate the role of olfaction and the APOE ɛ4 allele in these associations. METHODS: Data were drawn from the Betula project, a longitudinal study on aging, memory, and dementia in Sweden. Odor identification ability was assessed using the Scandinavian Odor Identification Test (SOIT). Annual mean PM2.5 concentrations were obtained from a dispersion-model and matched at the participants' residential address. Proportional hazard regression was used to calculate hazard ratios. RESULTS: Of 1,846 participants, 348 developed dementia during the 21-year follow-up period. The average annual mean PM2.5 exposure at baseline was 6.77μg/m3, which is 1.77μg/m3 above the WHO definition of clean air. In a fully adjusted model (adjusted for age, sex, APOE, SOIT, cardiovascular diseases and risk factors, and education) each 1μg/m3 difference in annual mean PM2.5-concentration was associated with a hazard ratio of 1.23 for dementia (95% CI: 1.01-1.50). Analyses stratified by APOE status (ɛ4 carriers versus non-carriers), and odor identification ability (high versus low), showed associations only for ɛ4 carriers, and for low performance on odor identification ability. CONCLUSION: PM2.5 was associated with an increased risk of dementia in this low pollution setting. The associations between PM2.5 and dementia seemed stronger in APOE carriers and those with below average odor identification ability.
Keywords: Air Pollutants; Air Pollution; Apolipoproteins E; Cohort Studies; Dementia; Environmental Exposure; Humans; Longitudinal Studies; Odorants; Particulate Matter

The Potential Role of Selection Bias in the Association Between Coronary Atherosclerosis and Cognitive Impairment. - Yahagi-Estevam, Maristella; Farias-Itao, Daniela Souza; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Pasqualucci, Carlos Augusto; Nitrini, Ricardo; Jacob-Filho, Wilson; Power, Melinda C; Suemoto, Claudia Kimie (J Alzheimers Dis, 2023)
BACKGROUND: Coronary atherosclerosis assessed in vivo was associated with cognitive impairment; however, conflicting findings have been reported in autopsy samples. OBJECTIVE: Our aims were to assess the association between atherosclerotic stenosis in the coronary arteries and cognitive impairment and to investigate the possibility of selection bias in an autopsy study. METHODS: Coronary arteries were collected, and the largest luminal stenosis was measured. Sociodemographic, clinical, and cognitive information were reported by a reliable next-of-kin. The association was tested using logistic and linear regressions adjusted for sociodemographic and clinical variables. We restricted the sample to individuals that were born in 1935 or earlier and stratified the analysis by cause of death to investigate the role of selection bias. RESULTS: In 253 participants (mean age = 78.0±8.5 years old, 48% male), stenosis was not associated with cognitive impairment (OR = 0.85, 95% CI = 0.69; 1.06, p = 0.15). In individuals who were born before 1936 in the absence of cardiovascular disease as the cause of death, greater stenosis was associated with cognitive impairment (OR = 4.02, 95% CI = 1.39; 11.6, p = 0.01). On the other hand, this association was not present among those born in 1935 or earlier who died of cardiovascular diseases (OR = 0.83, 95% CI = 0.60; 1.16, p = 0.28). CONCLUSION: We found that higher coronary stenosis was associated with cognitive impairment only in individuals born in 1935 or earlier and who had not died from cardiovascular diseases. Selection bias may be an important issue when investigating risk factors for chronic degenerative diseases in older individuals using autopsy samples.

Preventing Neurocognitive Decline in Adults Aging with HIV: Implications for Practice and Research. - Cody, Shameka L; Miller, Gabe H; Fazeli, Pariya L; Wang, Ge; Li, Wei; Goodin, Burel R; Vance, David E (J Alzheimers Dis, 2023)
Mild to moderate forms of neurocognitive impairment persist among people living with HIV (PLWH), despite being virally suppressed on antiretroviral therapy. PLWH are disproportionally impacted by physiological and psychosocial comorbidities compared to those without HIV. As adults live longer with HIV, the neurocognitive burden of physiological and psychosocial stressors can impair everyday functioning and may contribute to the development of neurodegenerative diseases such as Alzheimer's disease. This article outlines neurocognitive consequences of everyday stressors in PLWH. While some lifestyle factors can exacerbate inflammatory processes and promote negative neurocognitive health, novel interventions including the use of cannabinoids may be neuroprotective for aging PLWH who are at risk for elevated levels of inflammation from comorbidities. Studies of integrated neurocognitive rehabilitation strategies targeting lifestyle factors are promising for improving neurocognitive health, and may over time, reduce the risk of Alzheimer's disease in PLWH.
Keywords: Aging; Alzheimer Disease; Comorbidity; HIV Infections; Humans

Progression from Prodromal Alzheimer's Disease to Mild Alzheimer's Disease Dementia in the Verubecestat APECS Study: Adjudicating Diagnostic Transitions. - Voss, Tiffini; Kost, James; Mercer, Swati Pal; Furtek, Christine; Randolph, Christopher; Lines, Christopher; Egan, Michael F; Cummings, Jeffrey L (J Alzheimers Dis, 2023)
BACKGROUND: Delay of progression from prodromal Alzheimer's disease (AD) to dementia is an important outcome in AD trials. Centralized adjudication is intended to improve the consistency of dementia diagnosis but has not been scrutinized. OBJECTIVE: To evaluate centralized adjudication for determining progression to dementia compared with Site Investigator opinion or change in Clinical Dementia Rating (CDR). METHODS: We used data from the 2-year APECS trial of verubecestat versus placebo in 1,451 prodromal AD participants. Cases were triggered for central adjudication if: 1) the Site Investigator judged the participant had progressed to dementia, or 2) the participant's CDR sum-of-boxes score increased ≥2 points from baseline. Post-hoc analyses were performed on pooled treatment-group data to compare methods of assessing progression. RESULTS: 581/1,451 (40% ) participants had changes triggering adjudication and most (83% ) were confirmed as progression to dementia. Only 66% of those who met CDR criteria (regardless of whether they also met Site Investigator criteria) were adjudicated to have progressed to dementia and just 15% of those who met only CDR criteria were adjudicated to have progressed, representing 5% of progressors. In contrast, 99% of those who met Site Investigator criteria (regardless of whether they also met CDR criteria) were adjudicated to have progressed, and the same was true for those who met only Site Investigator criteria. CONCLUSION: A positive Site Investigator opinion is an excellent predictor for a positive adjudication decision regarding onset of dementia. Conversely, sole use of CDR sum-of-boxes change ≥2 is inadequate. The benefit of centralized adjudication appears doubtful.

Proteome Network Analysis Identifies Potential Biomarkers for Brain Aging. - Short, Meghan I; Fohner, Alison E; Skjellegrind, Håvard K; Beiser, Alexa; Gonzales, Mitzi M; Satizabal, Claudia L; Austin, Thomas R; Longstreth, W T; Bis, Joshua C; Lopez, Oscar; Hveem, Kristian; Selbæk, Geir; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease and related dementias (ADRD) involve biological processes that begin years to decades before onset of clinical symptoms. The plasma proteome can offer insight into brain aging and risk of incident dementia among cognitively healthy adults. OBJECTIVE: To identify biomarkers and biological pathways associated with neuroimaging measures and incident dementia in two large community-based cohorts by applying a correlation-based network analysis to the plasma proteome. METHODS: Weighted co-expression network analysis of 1,305 plasma proteins identified four modules of co-expressed proteins, which were related to MRI brain volumes and risk of incident dementia over a median 20-year follow-up in Framingham Heart Study (FHS) Offspring cohort participants (n = 1,861). Analyses were replicated in the Cardiovascular Health Study (CHS) (n = 2,117, mean 6-year follow-up). RESULTS: Two proteomic modules, one related to protein clearance and synaptic maintenance (M2) and a second to inflammation (M4), were associated with total brain volume in FHS (M2: p = 0.014; M4: p = 4.2×10-5). These modules were not significantly associated with hippocampal volume, white matter hyperintensities, or incident all-cause or AD dementia. Associations with TCBV did not replicate in CHS, an older cohort with a greater burden of comorbidities. CONCLUSIONS: Proteome networks implicate an early role for biological pathways involving inflammation and synaptic function in preclinical brain atrophy, with implications for clinical dementia.

Timing of Alzheimer's Disease by Intellectual Disability Level in Down Syndrome. - Hartley, Sigan L; Fleming, Victoria; Schworer, Emily K; Peven, Jamie; Handen, Benjamin L; Krinsky-McHale, Sharon; Hom, Christy; Lee, Laisze; Tudorascu, Dana L; Laymon, Charles; Minhas, Davneet; Luo, Weiquan; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Trisomy 21 causes Down syndrome (DS) and is a recognized cause of early-onset Alzheimer's disease (AD). OBJECTIVE: The current study sought to determine if premorbid intellectual disability level (ID) was associated with variability in age-trajectories of AD biomarkers and cognitive impairments. General linear mixed models compared the age-trajectory of the AD biomarkers PET Aβ and tau and cognitive decline across premorbid ID levels (mild, moderate, and severe/profound), in models controlling trisomy type, APOE status, biological sex, and site. METHODS: Analyses involved adults with DS from the Alzheimer's Biomarkers Consortium-Down Syndrome. Participants completed measures of memory, mental status, and visuospatial ability. Premorbid ID level was based on IQ or mental age scores prior to dementia concerns. PET was acquired using [11C] PiB for Aβ, and [18F] AV-1451 for tau. RESULTS: Cognitive data was available for 361 participants with a mean age of 45.22 (SD = 9.92) and PET biomarker data was available for 154 participants. There was not a significant effect of premorbid ID level by age on cognitive outcomes. There was not a significant effect of premorbid ID by age on PET Aβ or on tau PET. There was not a significant difference in age at time of study visit of those with mild cognitive impairment-DS or dementia by premorbid ID level. CONCLUSION: Findings provide robust evidence of a similar time course in AD trajectory across premorbid ID levels, laying the groundwork for the inclusion of individuals with DS with a variety of IQ levels in clinical AD trials.

Two-Year Changes in Physical Activity and Concurrent Changes in Cognitive Function in a Cohort of Adults with Metabolic Syndrome. - Rognoni, Teresa; Fernández-Matarrubia, Marta; Martínez-González, Miguel Ángel; Salas-Salvadó, Jordi; Corella, Dolores; Castañer, Olga; Martínez, J Alfredo; Alonso-Gómez, Ángel M; Gómez-Gracia, Enrique; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: It has been proposed that physical activity (PA) could prevent cognitive decline. OBJECTIVE: To evaluate the association between changes in PA and changes in cognitive function in a cohort of adults with metabolic syndrome. METHODS: Longitudinal observational study including 5,500 adults (mean age 65 years, SD = 5; women = 49.3%) with metabolic syndrome. Participants underwent physical activity measurements and cognitive evaluation at baseline and at two-years of follow-up. PA was quantified using the Minnesota questionnaire-shortened version. Cognitive function was evaluated using a battery of tests: Mini-Mental Test Examination, Clock Drawing Test, Trail Making Test A and B, Verbal Fluency Test, and Digit Span. The primary outcome was change in cognition at two-year follow-up, as measured through the Global Composite Score (GCS) of all neuropsychological tests. Multivariable-adjusted linear regression models were fitted with baseline PA and their changes as the main exposures and changes in cognitive function as the outcome. RESULTS: No significant association was found between PA levels (or their changes) and changes in cognitive function, as measured by the GCS. A greater increase in PA levels was associated with a more favorable two-year change in performance on the Trail Making Test A (Q4 versus Q1: b = -2.15, 95% CI -4.25 to -0.05; p-trend = 0.024). No significant association was found for other neuropsychological test. CONCLUSION: Our results do not support an association between increases in PA and the evolution of the global cognitive function at two-year follow-up, but they suggested a possible beneficial effect of PA on attentional function in older adults.

Validation of a Multivariate Prediction Model of the Clinical Progression of Alzheimer's Disease in a Community-Dwelling Multiethnic Cohort. - Stallard, Eric; Kociolek, Anton; Jin, Zhezhen; Ryu, Hyunnam; Lee, Seonjoo; Cosentino, Stephanie; Zhu, Carolyn; Gu, Yian; Fernandez, Kayri; Hernandez, Michelle; Kinosian, Bruce; Stern, Yaakov (J Alzheimers Dis, 2023)
BACKGROUND: The major aims of the three Predictors Studies have been to further our understanding of Alzheimer's disease (AD) progression sufficiently to predict the length of time from disease onset to major disease outcomes in individual patients with AD. OBJECTIVES: To validate a longitudinal Grade of Membership (L-GoM) prediction algorithm developed using clinic-based, mainly white patients from the Predictors 2 Study in a statistically representative community-based sample of Hispanic (N = 211) and non-Hispanic (N = 62) older adults (with 60 males and 213 females) from the Predictors 3 Study and extend the algorithm to mild cognitive impairment (MCI). METHODS: The L-GoM model was applied to data collected at the initial Predictors 3 visit for 150 subjects with AD and 123 with MCI. Participants were followed annually for up to seven years. Observed rates of survival and need for full-time care (FTC) were compared to those predicted by the algorithm. RESULTS: Initial MCI/AD severity in Predictors 3 was substantially higher than among clinic-based AD patients enrolled at the specialized Alzheimer's centers in Predictors 2. The observed survival and need for FTC followed the L-GoM model trajectories in individuals with MCI or AD, except for N = 32 subjects who were initially diagnosed with AD but reverted to a non-AD diagnosis on follow-up. CONCLUSION: These findings indicate that the L-GoM model is applicable to community-dwelling, multiethnic older adults with AD. They extend the use of the model to the prediction of outcomes for MCI. They also justify release of our L-GoM calculator at this time.

Alzheimer's Disease with Epileptiform EEG Activity: Abnormal Cortical Sources of Resting State Delta Rhythms in Patients with Amnesic Mild Cognitive Impairment. - Babiloni, Claudio; Noce, Giuseppe; Di Bonaventura, Carlo; Lizio, Roberta; Eldellaa, Ali; Tucci, Federico; Salamone, Enrico M; Ferri, Raffaele; Soricelli, Andrea; Nobili, Flavio; Famá, Francesco; Arnaldi, Dario; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Patients with amnesic mild cognitive impairment due to Alzheimer's disease (ADMCI) typically show a "slowing" of cortical resting-state eyes-closed electroencephalographic (rsEEG) rhythms. Some of them also show subclinical, non-convulsive, and epileptiform EEG activity (EEA) with an unclear relationship with that "slowing." OBJECTIVE: Here we tested the hypothesis that the "slowing" of rsEEG rhythms is related to EEA in ADMCI patients. METHODS: Clinical and instrumental datasets in 62 ADMCI patients and 38 normal elderly (Nold) subjects were available in a national archive. No participant had received a clinical diagnosis of epilepsy. The eLORETA freeware estimated rsEEG cortical sources. The area under the receiver operating characteristic curve (AUROCC) indexed the accuracy of eLORETA solutions in the classification between ADMCI-EEA and ADMCI-noEEA individuals. RESULTS: EEA was observed in 15% (N = 8) of the ADMCI patients. The ADMCI-EEA group showed: 1) more abnormal Aβ 42 levels in the cerebrospinal fluid as compared to the ADMCI-noEEA group and 2) higher temporal and occipital delta ( CONCLUSION: It can be speculated that in ADMCI-EEA patients, AD-related amyloid neuropathology may be related to an over-excitation in neurophysiological low-frequency (delta) oscillatory mechanisms underpinning cortical arousal and quiet vigilance.

Association Between High Serum Tetrahydrofolate and Low Cognitive Functions in the United States: A Cross-Sectional Study. - Fan, Yaohua; Liu, Wen; Chen, Si; Li, Mengzhu; Zhao, Lijun; Wu, Chunxiao; Liu, Helu; Zhu, Meiling (J Alzheimers Dis, 2022)
BACKGROUND: The relationship between serum folate status and cognitive functions is still controversial. OBJECTIVE: To evaluate the association between serum tetrahydrofolate and cognitive functions. METHODS: A total of 3,132 participants (60-80 years old) from the 2011-2014 NHANES were included in this cross-sectional study. The primary outcome measure was cognitive function assessment, determined by the Consortium to Establish a Registry for Alzheimer's Disease Word Learning Test (CERAD-WL), CERAD-Delayed Recall Test (CERAD-DR), Animal Fluency Test (AF), Digit Symbol Substitution Test (DSST), and global cognitive score. Generalized linear model (GLM), multivariate logistic regression models, weighted generalized additive models (GAM), and subgroup analyses were performed to evaluate the association between serum tetrahydrofolate and low cognitive functions. RESULTS: In GLM, and the crude model, model 1, model 2 of multivariate logistic regression models, increased serum tetrahydrofolate was associated with reduced cognitive functions via AF, DSST, CERAD-WL, CERAD-DR, and global cognitive score (p <  0.05). In GAM, the inflection points were 1.1, 2.8, and 2.8 nmol/L tetrahydrofolate, determined by a two-piece wise linear regression model of AF, DSST, and global cognitive score, respectively. Also, in GAM, there were no non-linear relationship between serum tetrahydrofolate and low cognitive functions, as determined by CERAD-WL or CERAD-DR. The results of subgroup analyses found that serum tetrahydrofolate levels and reduced cognitive functions as determined by AF had significant interactions for age and body mass index. The association between high serum tetrahydrofolate level and reduced cognitive functions as determined using DSST, CERAD-WL, CERAD-DR, or global cognitive score had no interaction with the associations between cognition and gender, or age, or so on. CONCLUSION: High serum tetrahydrofolate level is associated with significantly reduced cognitive function.

Association of Brain Volume and Retinal Thickness in the Early Stages of Alzheimer's Disease. - Mathew, Sunu; WuDunn, Darrell; Mackay, Devin D; Vosmeier, Aaron; Tallman, Eileen F; Deardorff, Rachael; Harris, Alon; Farlow, Martin R; Brosch, Jared R; Gao, Sujuan; Apostolova, Liana G; Saykin, Andrew J; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The eye has been considered a 'window to the brain,' and several neurological diseases including neurodegenerative conditions like Alzheimer's disease (AD) also show changes in the retina. OBJECTIVE: To investigate retinal nerve fiber layer (RNFL) thickness and its association with brain volume via magnetic resonance imaging (MRI) in older adults with subjective or objective cognitive decline. METHODS: 75 participants underwent ophthalmological and neurological evaluation including optical coherence tomography and MRI (28 cognitively normal subjects, 26 with subjective cognitive decline, 17 patients diagnosed with mild cognitive impairment, and 4 with AD). Differences in demographics, thickness of RNFL, and brain volume were assessed using ANCOVA, while partial Pearson correlations, covaried for age and sex, were used to compare thickness of the peripapillary RNFL with brain volumes, with p < 0.05 considered statistically significant. RESULTS: Mean RNFL thickness was significantly correlated with brain volumes, including global volume (right eye r = 0.235 p = 0.046, left eye r = 0.244, p = 0.037), temporal lobe (right eye r = 0.242 p = 0.039, left eye r = 0.290, p = 0.013), hippocampal (right eye r = 0.320 p = 0.005, left eye r = 0.306, p = 0.008), amygdala (left eye r = 0.332, p = 0.004), and occipital lobe (right eye r = 0.264 p = 0.024) volumes. CONCLUSION: RNFL thickness in both eyes was positively associated with brain volumes in subjects with subjective and objective cognitive decline. The RNFL, however, did not correlate with the disease, but the small sample number makes it important to conduct larger studies. RNFL thickness may be a useful non-invasive and inexpensive tool for detection of brain neurodegeneration and may assist with diagnosis and monitoring of progression and treatment in AD.

Association of Cholinergic Basal Forebrain Volume and Functional Connectivity with Markers of Inflammatory Response in the Alzheimer's Disease Spectrum. - Teipel, Stefan J; Dyrba, Martin; Ballarini, Tommaso; Brosseron, Frederic; Bruno, Davide; Buerger, Katharina; Cosma, Nicoleta-Carmen; Dechent, Peter; Dobisch, Laura; Düzel, Emrah; Ewers, Michael; Fliessbach, Klaus; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Inflammation has been described as a key pathogenic event in Alzheimer's disease (AD), downstream of amyloid and tau pathology. Preclinical and clinical data suggest that the cholinergic basal forebrain may moderate inflammatory response to different pathologies. OBJECTIVE: To study the association of cholinergic basal forebrain volume and functional connectivity with measures of neuroinflammation in people from the AD spectrum. METHODS: We studied 261 cases from the DELCODE cohort, including people with subjective cognitive decline, mild cognitive impairment, AD dementia, first degree relatives, and healthy controls. Using Bayesian ANCOVA, we tested associations of MRI indices of cholinergic basal forebrain volume and functional connectivity with cerebrospinal fluid (CSF) levels of sTREM2 as a marker of microglia activation, and serum levels of complement C3. Using Bayesian elastic net regression, we determined associations between basal forebrain measures and a large inflammation marker panel from CSF and serum. RESULTS: We found anecdotal to moderate evidence in favor of the absence of an effect of basal forebrain volume and functional connectivity on CSF sTREM2 and serum C3 levels both in Aβ42/ptau-positive and negative cases. Bayesian elastic net regression identified several CSF and serum markers of inflammation that were associated with basal forebrain volume and functional connectivity. The effect sizes were moderate to small. CONCLUSION: Our data-driven analyses generate the hypothesis that cholinergic basal forebrain may be involved in the neuroinflammation response to Aβ42 and phospho-tau pathology in people from the AD spectrum. This hypothesis needs to be tested in independent samples.
Keywords: Aged; Alzheimer Disease; Basal Forebrain; Biomarkers; Cholinergic Agents; Cognitive Dysfunction; Cohort Studies; Female; Humans; Inflammation; Magnetic Resonance Imaging; Male

Associations of Pulmonary Function with MRI Brain Volumes: A Coordinated Multi-Study Analysis. - Frenzel, Stefan; Bis, Josh C; Gudmundsson, Elias F; O'Donnell, Adrienne; Simino, Jeannette; Yaqub, Amber; Bartz, Traci M; Brusselle, Guy G O; Bülow, Robin; DeCarli, Charles S; Ewert, Ralf; Gharib, Sina A; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Previous studies suggest poor pulmonary function is associated with increased burden of cerebral white matter hyperintensities and brain atrophy among elderly individuals, but the results are inconsistent. OBJECTIVE: To study the cross-sectional associations of pulmonary function with structural brain variables. METHODS: Data from six large community-based samples (N = 11,091) were analyzed. Spirometric measurements were standardized with respect to age, sex, height, and ethnicity using reference equations of the Global Lung Function Initiative. Associations of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and their ratio FEV1/FVC with brain volume, gray matter volume, hippocampal volume, and volume of white matter hyperintensities were investigated using multivariable linear regressions for each study separately and then combined using random-effect meta-analyses. RESULTS: FEV1 and FVC were positively associated with brain volume, gray matter volume, and hippocampal volume, and negatively associated with white matter hyperintensities volume after multiple testing correction, with little heterogeneity present between the studies. For instance, an increase of FVC by one unit was associated with 3.5 ml higher brain volume (95% CI: [2.2, 4.9]). In contrast, results for FEV1/FVC were more heterogeneous across studies, with significant positive associations with brain volume, gray matter volume, and hippocampal volume, but not white matter hyperintensities volume. Associations of brain variables with both FEV1 and FVC were consistently stronger than with FEV1/FVC, specifically with brain volume and white matter hyperintensities volume. CONCLUSION: In cross-sectional analyses, worse pulmonary function is associated with smaller brain volumes and higher white matter hyperintensities burden.

"Captive by the Uncertainty"-Experiences with Anticipatory Guidance for People Living with Dementia and Their Caregivers at a Specialty Dementia Clinic. - Shafir, Adi; Ritchie, Christine S; Garrett, Sarah B; Bernstein Sideman, Alissa; Naasan, Georges; Merrilees, Jennifer; Widera, Eric; Flint, Lynn; Harrison, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: After a diagnosis of Alzheimer's disease and related disorders, people living with dementia (PWD) and caregivers wonder what disease trajectory to expect and how to plan for functional and cognitive decline. This qualitative study aimed to identify patient and caregiver experiences receiving anticipatory guidance about dementia from a specialty dementia clinic. OBJECTIVE: To examine PWD and caregiver perspectives on receiving anticipatory guidance from a specialty dementia clinic. METHODS: We conducted semi-structured interviews with PWD, and active and bereaved family caregivers, recruited from a specialty dementia clinic. Interviews were recorded, transcribed, and systematically summarized. Thematic analysis identified anticipatory guidance received from clinical or non-clinical sources and areas where respondents wanted additional guidance. RESULTS: Of 40 participants, 9 were PWD, 16 were active caregivers, and 15 were bereaved caregivers. PWD had a mean age of 75 and were primarily male (n = 6/9); caregivers had a mean age of 67 and were primarily female (n = 21/31). Participants felt they received incomplete or "hesitant" guidance on prognosis and expected disease course via their clinicians and filled the gap with information they found via the internet, books, and support groups. They appreciated guidance on behavioral, safety, and communication issues from clinicians, but found more timely and advance guidance from other non-clinical sources. Guidance on legal and financial planning was primarily identified through non-clinical sources. CONCLUSION: PWD and caregivers want more information about expected disease course, prognosis, and help planning after diagnosis. Clinicians have an opportunity to improve anticipatory guidance communication and subsequent care provision.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Qualitative Research; Uncertainty

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Circulating Cell-Free Genomic DNA Is Associated with an Increased Risk of Dementia and with Change in Cognitive and Physical Function. - Nidadavolu, Lolita S; Feger, Danielle; Wu, Yuqiong; Grodstein, Francine; Gross, Alden L; Bennett, David A; Walston, Jeremy D; Oh, Esther S; Abadir, Peter M (J Alzheimers Dis, 2022)
BACKGROUND: Altered cell homeostasis, seen in cognitive decline and frailty, leads to cell death and turnover, releasing circulating cell-free DNA (ccf-DNA). OBJECTIVE: The goal of this study is to determine if serum genomic cell-free DNA (ccf-gDNA) is associated with physical and cognitive decline in older adults. METHODS: We used serum from 631 community-dwelling individuals from the Religious Orders Study or Rush Memory and Aging Project who were without cognitive impairment at baseline. ccf-gDNA fragments in serum were quantified using digital PCR. An array of cognitive and physical traits, risk of dementia, global cognition, and frailty at or nearest the time of blood draw were regressed on ccf-DNA, with adjustment for age, sex, race, and education. RESULTS: Cross-sectionally, higher ccf-gDNA levels were associated with lower global cognition score and slower gait speed at the evaluation nearest to blood draw. Higher ccf-gDNA levels were associated with increased odds of incident dementia (OR 1.27, 95% CI 1.05, 1.54). Longitudinally, higher levels of ccf-gDNA were associated with steeper general cognitive decline and worsening frailty over eight years of follow up. CONCLUSION: This study demonstrates that ccf-gDNA fragments have utility for identifying persons at higher risk of developing dementia and worsening cognition and frailty.

Combinational Drug Repurposing from Genetic Networks Applied to Alzheimer's Disease. - Nabirotchkin, Serguei; Bouaziz, Jan; Glibert, Fabrice; Mandel, Jonas; Foucquier, Julie; Hajj, Rodolphe; Callizot, Noëlle; Cholet, Nathalie; Guedj, Mickaël; Cohen, Daniel (J Alzheimers Dis, 2022)
BACKGROUND: Human diseases are multi-factorial biological phenomena resulting from perturbations of numerous functional networks. The complex nature of human diseases explains frequently observed marginal or transitory efficacy of mono-therapeutic interventions. For this reason, combination therapy is being increasingly evaluated as a biologically plausible strategy for reversing disease state, fostering the development of dedicated methodological and experimental approaches. In parallel, genome-wide association studies (GWAS) provide a prominent opportunity for disclosing human-specific therapeutic targets and rational drug repurposing. OBJECTIVE: In this context, our objective was to elaborate an integrated computational platform to accelerate discovery and experimental validation of synergistic combinations of repurposed drugs for treatment of common human diseases. METHODS: The proposed approach combines adapted statistical analysis of GWAS data, pathway-based functional annotation of genetic findings using gene set enrichment technique, computational reconstruction of signaling networks enriched in disease-associated genes, selection of candidate repurposed drugs and proof-of-concept combinational experimental screening. RESULTS: It enables robust identification of signaling pathways enriched in disease susceptibility loci. Therapeutic targeting of the disease-associated signaling networks provides a reliable way for rational drug repurposing and rapid development of synergistic drug combinations for common human diseases. CONCLUSION: Here we demonstrate the feasibility and efficacy of the proposed approach with an experiment application to Alzheimer's disease.

Comparative Analysis of Alzheimer's Disease Cerebrospinal Fluid Biomarkers Measurement by Multiplex SOMAscan Platform and Immunoassay-Based Approach. - Timsina, Jigyasha; Gomez-Fonseca, Duber; Wang, Lihua; Do, Anh; Western, Dan; Álvarez, Ignacio; Aguilar, Miquel; Pastor, Pau; Henson, Rachel L; Herries, Elizabeth; Xiong, Chengjie; Schindler, Suzanne E; et al. (J Alzheimers Dis, 2022)
BACKGROUND: The SOMAscan assay has an advantage over immunoassay-based methods because it measures a large number of proteins in a cost-effective manner. However, the performance of this technology compared to the routinely used immunoassay techniques needs to be evaluated. OBJECTIVE: We performed comparative analyses of SOMAscan and immunoassay-based protein measurements for five cerebrospinal fluid (CSF) proteins associated with Alzheimer's disease (AD) and neurodegeneration: NfL, Neurogranin, sTREM2, VILIP-1, and SNAP-25. METHODS: We compared biomarkers measured in ADNI (N = 689), Knight-ADRC (N = 870), DIAN (N = 115), and Barcelona-1 (N = 92) cohorts. Raw protein values were transformed using z-score in order to combine measures from the different studies. sTREM2 and VILIP-1 had more than one analyte in SOMAscan; all available analytes were evaluated. Pearson's correlation coefficients between SOMAscan and immunoassays were calculated. Receiver operating characteristic curve and area under the curve were used to compare prediction accuracy of these biomarkers between the two platforms. RESULTS: Neurogranin, VILIP-1, and NfL showed high correlation between SOMAscan and immunoassay measures (r >  0.9). sTREM2 had a fair correlation (r >  0.6), whereas SNAP-25 showed weak correlation (r = 0.06). Measures in both platforms provided similar predicted performance for all biomarkers except SNAP-25 and one of the sTREM2 analytes. sTREM2 showed higher AUC for SOMAscan based measures. CONCLUSION: Our data indicate that SOMAscan performs as well as immunoassay approaches for NfL, Neurogranin, VILIP-1, and sTREM2. Our study shows promise for using SOMAscan as an alternative to traditional immunoassay-based measures. Follow-up investigation will be required for SNAP-25 and additional established biomarkers.

A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer's Disease. - Altomari, Natalia; Bruno, Francesco; Laganà, Valentina; Smirne, Nicoletta; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Frangipane, Francesca; Maletta, Raffaele; Puccio, Gianfranco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2022)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer's disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. OBJECTIVE: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stages: pre-T0 (before the onset of the disease), T0 (from onset to 5 years), and T1 (from 5 years onwards); 3) track the manifestation of BPSD sub-syndromes (i.e., hyperactivity, psychosis, affective, and apathy) in EOAD versus LOAD at T0 and T1. METHODS: The sample includes 1,538 LOAD and 387 EOAD diagnosed from 1996 to 2018. Comprehensive assessment batteries, including the Neuropsychiatric Inventory (NPI), were administered at the first medical assessment and at different follow-up period. RESULTS: The overall prevalence for the most of BPSD was significantly higher in EOAD compared to LOAD whereas most BPSD appeared significantly later in EOAD patients. Between the two groups, from pre-T0 to T1 we recorded a different pattern of BPSD prevalence over time as well as for BPSD sub-syndromes at T0 and T1. Results on severity of BPSD did not show significant differences. CONCLUSION: EOAD and LOAD represent two different forms of a single entity not only from a neuropathological, cognitive, and functional level but also from a psychiatric point of view.
Keywords: Affective Symptoms; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Apathy; Behavioral Symptoms; Dementia; Female; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Severity of Illness Index

Diabetic Retinopathy Predicts Risk of Alzheimer's Disease: A Danish Registry-Based Nationwide Cohort Study. - Pedersen, Frederik Nørregaard; Stokholm, Lonny; Pouwer, Frans; Hass Rubin, Katrine; Peto, Tunde; Frydkjær-Olsen, Ulrik; Thykjær, Anne Suhr; Andersen, Nis; Andresen, Jens; Bek, Toke; La Cour, Morten; Heegaard, Steffen; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Retinal neurodegeneration is evident in early diabetic retinopathy (DR) which may be associated with other neurodegenerative diseases like Alzheimer's disease (AD). OBJECTIVE: To investigate diabetes and DR as a risk marker of present and incident AD. METHODS: A register-based cohort study was performed. We included 134,327 persons with diabetes above 60 years of age, who had attended DR screening, and 651,936 age- and gender-matched persons without diabetes. RESULTS: At baseline, the prevalence of AD was 0.7% and 1.3% among patients with and without diabetes, respectively. In a multivariable regression model, patients with diabetes were less likely to have AD at baseline (adjusted OR 0.63, 95% CI 0.59-0.68). During follow-up, incident AD was registered for 1473 (0.35%) and 6,899 (0.34%) persons with and without diabetes, respectively. Compared to persons without diabetes, persons with diabetes and no DR had a lower risk to develop AD (adjusted HR 0.87, 95% CI 0.81-0.93), while persons with diabetes and DR had higher risk of AD (adjusted HR 1.24, 95% CI 1.08-1.43). When persons with diabetes and no DR were used as references, a higher risk of incident AD was observed in persons with DR (adjusted HR 1.34, 95% CI 1.18-1.53). CONCLUSION: Individuals with diabetes without DR were less likely to develop AD compared to persons without diabetes. However, individuals with DR had a 34% higher risk of incident AD, which raise the question whether screening for cognitive impairment should be done among individuals with DR.
Keywords: Alzheimer Disease; Cohort Studies; Denmark; Diabetes Mellitus; Diabetic Retinopathy; Humans; Registries; Risk Factors

The Effectiveness of GRADIOR: A Neuropsychological Rehabilitation Program for People with Mild Cognitive Impairment and Mild Dementia. Results of a Randomized Controlled Trial After 4 and 12 Months of Treatment. - Diaz Baquero, Angie A; Franco-Martín, Manuel A; Parra Vidales, Esther; Toribio-Guzmán, José Miguel; Bueno-Aguado, Yolanda; Martínez Abad, Fernando; Perea Bartolomé, María V; Asl, Aysan Mahmoudi; van der Roest, Henriëtte G (J Alzheimers Dis, 2022)
BACKGROUND: Computer-based cognitive training programs have been developed with promising results on the maintenance/improvement of cognitive performance in people with dementia. OBJECTIVE: The objective was to evaluate the effectiveness of the cognitive rehabilitation program "GRADIOR" in people with mild cognitive impairment and mild dementia. METHOD: This study was a single-blind multicenter randomized clinical trial. Participants were recruited from hospitals/day centers. The experimental group (EG) and control group (CG) received computer-based cognitive training (CCT) and routine daily care, respectively. Outcome measures at T0: baseline, T1: at 4 months, T2: at 12 months were compared within and between-groups. RESULTS: Significant differences or important effect sizes were detected at the intragroup and intergroup level for most variables, observing a trend of improvement and/or maintenance at 4 months by Visual Reasoning of Cambridge Cognitive Examination (CAMCOG), Digit and Arithmetic of WAIS-III, Semantic Verbal Fluency, Mini-Mental State Exam (MMSE), Trail Making Test (TMT)-A-Mistakes and at 12 months by Visual Reasoning of CAMCOG, Digit Symbol of WAIS-III, TMT-B-mistakes, Visual Memory of Rivermead Behavioural Memory Test, Lexical Verbal Fluency-P, Yesavage's Geriatric Depression Scale (GDS), TMT-A-time scales whose objective was to evaluate some executive functions and/or the memory. The CG presented a worsening trend for most of the measures towards 12 months. There was also a significant interaction between "time and group" for MMSE (F = 8.971; p = 0.03; η 2 = 0.019) and the GDS (F = 3.414; p = 0.04; η 2 = 0.041), as well as small effect sizes for TMT-A-time (F = 1.641; p = 0.21; η 2 = 0.021) and TMT-A-mistakes (F = 0.908; p = 0.41; η 2 = 0.019). CONCLUSION: CCT with GRADIOR has been proved to benefit cognitive functions (ISRCTN:15742788).

The Efficacy and Safety of Alzheimer's Disease Therapies: An Updated Umbrella Review. - Fan, Fangcheng; Liu, Hua; Shi, Xiaojie; Ai, Yangwen; Liu, Qingshan; Cheng, Yong (J Alzheimers Dis, 2022)
BACKGROUND: Evidence summaries for efficacy and safety of frequently employed treatments of Alzheimer's disease (AD) are sparse. OBJECTIVE: We aimed to perform an updated umbrella review to identify an efficacious and safe treatment for AD patients. METHODS: We conducted a search for meta-analyses and systematic reviews on the Embase, PubMed, The Cochrane Library, and Web of Science to address this knowledge gap. We examined the cognitive functions, behavioral symptoms, global clinical assessment, and Activities of Daily Living as efficacy endpoints, and the incidence of adverse events as safety profiles. RESULTS: Sixteen eligible papers including 149 studies were included in the umbrella review. The results showed that AChE inhibitors (donepezil, galantamine, rivastigmine, Huperzine A), Ginkgo biloba, and cerebrolysin appear to be beneficial for cognitive, global performances, and activities of daily living in patients with AD. Furthermore, anti-Aβ agents are unlikely to have an important effect on slowing cognitive or functional impairment in mild to moderate AD. CONCLUSION: Our study demonstrated that AChE inhibitors, Ginkgo biloba, and cerebrolysin are the optimum cognitive and activities of daily living medication for patients with AD.
Keywords: Activities of Daily Living; Alzheimer Disease; Amino Acids; Cholinesterase Inhibitors; Cognition; Donepezil; Galantamine; Ginkgo biloba; Humans; Nootropic Agents; Patient Safety; Plant Extracts; Rivastigmine

An Investigation into the Effects of Outer Membrane Vesicles and Lipopolysaccharide of Porphyromonas gingivalis on Blood-Brain Barrier Integrity, Permeability, and Disruption of Scaffolding Proteins in a Human in vitro Model. - Pritchard, Anna Barlach; Fabian, Zsolt; Lawrence, Clare L; Morton, Glyn; Crean, StJohn; Alder, Jane E (J Alzheimers Dis, 2022)
BACKGROUND: The effects of the key pathogens and virulence factors associated with gum disease such as Porphyromonas gingivalis (P. gingivalis) on the central nervous system is of great interest with respect to development of neuropathologies and hence therapeutics and preventative strategies. Chronic infections and associated inflammation are known to weaken the first line of defense for the brain, the blood-brain barrier (BBB). OBJECTIVE: The focus of this study is to utilize an established human in vitro BBB model to evaluate the effects of P. gingivalis virulence factors lipopolysaccharide (LPS) and outer membrane vesicles (OMVs) on a primary-derived human model representing the neurovascular unit of the BBB. METHODS: Changes to the integrity of the BBB after application of P. gingivalis LPS and OMVs were investigated and correlated with transport of LPS. Additionally, the effect of P. gingivalis LPS and OMVs on human brain microvascular endothelial cells in monolayer was evaluated using immunofluorescence microscopy. RESULTS: The integrity of the BBB model was weakened by application of P. gingivalis LPS and OMVs, as measured by a decrease in electrical resistance and a recovery deficit was seen in comparison to the controls. Application of P. gingivalis OMVs to a monoculture of human brain microvascular endothelial cells showed disruption of the tight junction zona occludens protein (ZO-1) compared to controls. CONCLUSION: These findings show that the integrity of tight junctions of the human BBB could be weakened by association with P. gingivalis virulence factors LPS and OMVs containing proteolytic enzymes (gingipains).

Lipid Peroxidation as a Marker of Apathy and Executive Dysfunction in Patients at Risk for Vascular Cognitive Impairment. - Bawa, Kritleen K; Ba, Joycelyn; Kiss, Alex; Wang, RuoDing; Feng, Vivian; Swardfager, Walter; Andreazza, Ana; Gallagher, Damien; Marotta, Giovanni; Herrmann, Nathan; Lanctôt, Krista L (J Alzheimers Dis, 2022)
BACKGROUND: The co-occurrence of apathy and executive dysfunction, a correlate of vascular cognitive impairment (VCI), is highly prevalent, yet facilitating factors are largely unknown. OBJECTIVE: This study investigates the relationship between lipid peroxidation, apathy, and executive dysfunction in patients at risk for VCI. METHODS: In participants with coronary artery disease, who are at a high risk of VCI, apathy (Apathy Evaluation Scale), and executive function (composite z-score based on age and education population norms from trails making test B, animal naming, and phonemic fluency tests) were assessed. Serum concentrations of an early (lipid hydroperoxide (LPH)) and late (8-isoprostane (8-ISO)) lipid peroxidation marker, were measured and the 8-ISO/LPH ratio was calculated. RESULTS: Participants (n = 206, age±SD = 63.0±7.5, 80% men, total years of education = 15.9±3.4, AES score = 28.3±8.8, executive function = 0±1) demonstrated significantly different 8-ISO/LPH ratios between groups (F(3, 202) = 10.915, p <  0.001) with increasing levels in the following order: no apathy or executive dysfunction, only executive dysfunction (executive function composite score≤-1), only apathy (AES≥28), and both apathy and executive dysfunction. A model adjusting for demographics showed that lipid peroxidation was associated with both apathy (B(SE) = 4.63 (0.954), t = 4.852, p <  0.001) and executive function (B(SE) = -0.19 (0.079), t = -2.377, p = 0.018). However, when controlling for both demographics and vascular risk factors, lipid peroxidation was associated with only apathy (B(SE) = 3.11 (0.987), t = 3.149, p = 0.002). CONCLUSION: The results highlight a potentially important involvement of lipid peroxidation in the co-occurrence of apathy and executive dysfunction in those at risk for VCI.

Longitudinal Changes in Resting-State Functional Connectivity and Gray Matter Volume Are Associated with Conversion to Hearing Impairment in Older Adults. - Fitzhugh, Megan C; Pa, Judy (J Alzheimers Dis, 2022)
BACKGROUND: Hearing loss was recently identified as a modifiable risk factor for dementia although the potential mechanisms explaining this relationship are unknown. OBJECTIVE: The current study examined longitudinal change in resting-state fMRI functional connectivity and gray matter volume in individuals who developed a hearing impairment compared to those whose hearing remained normal. METHODS: This study included 440 participants from the UK Biobank: 163 who had normal hearing at baseline and impaired hearing at follow-up (i.e., converters, mean age = 63.11±6.33, 53% female) and 277 who had normal hearing at baseline and maintained normal hearing at follow-up (i.e., non-converters, age = 63.31±5.50, 50% female). Functional connectivity was computed between a priori selected auditory seed regions (left and right Heschl's gyrus and cytoarchitectonic subregions Te1.0, Te1.1, and Te1.2) and select higher-order cognitive brain networks. Gray matter volume within these same regions was also obtained. RESULTS: Converters had increased connectivity from left Heschl's gyrus to left anterior insula and from right Heschl's gyrus to right anterior insula, and decreased connectivity between right Heschl's gyrus and right hippocampus, compared to non-converters. Converters also had reduced gray matter volume in left hippocampus and left lateral visual cortex compared to non-converters. CONCLUSION: These findings suggest that conversion to a hearing impairment is associated with altered brain functional connectivity and gray matter volume in the attention, memory, and visual processing regions that were examined in this study.

Low-Dose Radiation Therapy Reduces Amyloid Load in Young 3xTg-AD Mice. - Ceyzériat, Kelly; Tournier, Benjamin B; Millet, Philippe; Dipasquale, Giovanna; Koutsouvelis, Nikolaos; Frisoni, Giovanni B; Garibotto, Valentina; Zilli, Thomas (J Alzheimers Dis, 2022)
BACKGROUND: Low-dose radiation therapy (LD-RT) has been shown to decrease amyloidosis or inflammation in systemic diseases and has recently been proposed as possible treatment of Alzheimer's disease (AD). A positive effect of LD-RT on tauopathy, the other marker of AD, has also been suggested. These effects have been shown in preclinical studies, but their mechanisms are still not well understood. OBJECTIVE: This study aimed to evaluate if anti-amyloid and anti-inflammatory effects of LD-RT can be observed at an early stage of the disease. Its impact on tauopathy and behavioral alterations was also investigated. METHODS: The whole brain of 12-month-old 3xTg-AD mice was irradiated with 10 Gy in 5 daily fractions of 2 Gy. Mice underwent behavioral tests before and 8 weeks post treatment. Amyloid load, tauopathy, and neuroinflammation were measured using histology and/or ELISA. RESULTS: Compared with wild-type animals, 3xTg-AD mice showed a moderate amyloid and tau pathology restricted to the hippocampus, a glial reactivity restricted to the proximity of amyloid plaques. LD-RT significantly reduced Aβ 42 aggregated forms (-71%) in the hippocampus and tended to reduce other forms in the hippocampus and frontal cortex but did not affect tauopathy or cognitive performance. A trend for neuroinflammation markers reduction was also observed. CONCLUSION: When applied at an early stage, LD-RT reduced amyloid load and possibly neuroinflammation markers, with no impact on tauopathy. The long-term persistence of these beneficial effects of LD-RT should be evaluated in future studies.

Olfactory Bulb Integrity in Frontotemporal Dementia and Alzheimer's Disease. - Carnemolla, Sarah; Kumfor, Fiona; Liang, Cheng Tao; Foxe, David; Ahmed, Rebekah; Piguet, Olivier (J Alzheimers Dis, 2022)
BACKGROUND: Olfactory dysfunction is highly prevalent in dementia syndromes, including Alzheimer's disease (AD) and frontotemporal dementia (FTD). The structural integrity of the olfactory bulb (OB) is thought to play a critical role in odor detection and identification, but no MRI study has measured OB volume in FTD, or measured OB volume longitudinally in AD. OBJECTIVE: To measure OB volume in FTD and AD patients longitudinally using MRI. METHODS: This study measured OB volumes using MRI in patients diagnosed with behavioral-variant FTD (n = 55), semantic dementia (n = 34), progressive non-fluent aphasia (n = 30), AD (n = 50), and healthy age-matched controls (n = 55) at their first visit to a dementia research clinic ('baseline'). Imaging data in patients 12-months later were analyzed where available (n = 84) for longitudinal assessment. Volumes of subcortical and cortical olfactory regions ('olfactory network') were obtained via surface-based morphometry. RESULTS: Results revealed that in AD and FTD at baseline, OB volumes were similar to controls, whereas volumes of olfactory network regions were significantly reduced in all patient groups except in progressive non-fluent aphasia. Longitudinal data revealed that OB volume became significantly reduced (10-25% volume reduction) in all dementia groups with disease progression. CONCLUSION: Olfactory dysfunction is common in patients diagnosed with AD or FTD, but our results indicate that there is no detectable volume loss to the OBs upon first presentation to the clinic. Our findings indicate that the OBs become detectably atrophied later in the disease process. OB atrophy indicates the potential usefulness for OBs to be targeted in interventions to improve olfactory function.

Passive Immunotherapy Targeting Tau Oligomeric Strains Reverses Tauopathy Phenotypes in Aged Human-Tau Mice in a Mouse Model-Specific Manner. - Bittar, Alice; Al-Lahham, Rabab; Bhatt, Nemil; Moore, Kenya; Montalbano, Mauro; Jerez, Cynthia; Fung, Leiana; McAllen, Salome; Ellsworth, Anna; Kayed, Rakez (J Alzheimers Dis, 2022)
BACKGROUND: Tau oligomers are one of the most toxic species, displaying prion-like strains which have different conformations resulting in different tauopathies. Passive immunotherapy targeting different tau species is a promising therapeutic approach. Age is one of the greatest risk factors; however, most immunotherapy studies are done in young to middle-aged mice tauopathy models, which is not representative of the many clinical trials done with older humans with established tauopathies. OBJECTIVE: We utilized two different clones of tau oligomer monoclonal antibodies (TOMAs) in aged Htau and JNPL3 mouse models to investigate the potential of passive immunotherapy. METHODS: Aged mice received a single intravenous injection of 120 μg/animal of either TOMA1, TOMA3 clones or a non-specific IgG. Their cognitive functions were assessed one-week post-injection using Y-maze and novel object recognition tests. Brain tissues were analyzed using biochemical and immunological assays. RESULTS: TOMA 1 and 3 rescues cognitive phenotypes in aged animals in a mouse model-specific manner, indicative by a reduction in tau oligomers levels. The TOMAs were shown to have strong reactivity with different tau oligomeric species in the different mouse models in vitro and ex vivo. CONCLUSION: This is the first study testing tau passive immunotherapy in aged animals and supports our previous reports on of the role of oligomeric tau in disease progression further validating the potential of TOMAs to rescue the late-stage disease pathology and phenotype. Moreover, this study suggests that multiple tau oligomeric strains exist in aged animals; therefore, it is of great importance to further characterize these strains.

Prevalence of Depressive Symptoms in a Memory Clinic Cohort: A Retrospective Study. - Loreto, Flavia; Fitzgerald, Anna; Golemme, Mara; Gunning, Stephen; Win, Zarni; Patel, Neva; Carswell, Christopher; Perry, Richard; Kennedy, Angus; Edison, Paul; Malhotra, Paresh (J Alzheimers Dis, 2022)
BACKGROUND: Depression has been suggested to be a cause of reversible cognitive impairment but also a risk factor for neurodegenerative disease. Studies suggest that depression prevalence may be high in early onset dementia, particularly Alzheimer's disease, but this has not been systematically assessed in a biomarker-validated clinical dementia cohort to date. OBJECTIVE: To examine the prevalence, features, and association with amyloid pathology of lifetime depressive symptoms in a memory clinic cohort meeting appropriate use criteria for amyloid PET imaging. METHODS: We included 300 patients from a single-center memory clinic cohort that received diagnostic biomarker evaluation with amyloid PET imaging according to appropriate use criteria. History of lifetime depressive symptoms was retrospectively assessed through structured review of clinical correspondence. RESULTS: One hundred forty-two (47%) patients had a history of significant depressive symptoms ('D+'). Of these, 89% had ongoing symptoms and 60% were on antidepressants at the time of presentation to our Clinic. Depressive symptoms were equally highly prevalent in the amyloid-positive and the heterogeneous group of amyloid-negative patients. CONCLUSION: Approximately half of patients who meet appropriate use criteria for amyloid PET had a history of depressive symptoms. We suggest that depression is an important feature of both neurodegenerative and non-neurodegenerative cognitive impairment and may contribute to the diagnostic uncertainty behind referral to amyloid PET.

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

The Relationship Between Prior Cancer Diagnosis and All-Cause Dementia Progression Among US Adults. - Fowler, Mackenzie E; Wright, Nicole C; Triebel, Kristen; Rocque, Gabrielle B; Irvin, Ryan; Kennedy, Richard E (J Alzheimers Dis, 2022)
BACKGROUND: Cancer-related cognitive impairment (CRCI), a frequent effect of cancer and its treatments, shares common cognitive symptoms with dementia syndromes. Cross-sectional studies demonstrate an inverse relationship between cancer and dementia. However, the longitudinal relationship between dementia decline and cancer has not been investigated. OBJECTIVE: To evaluate the association between cancer and longitudinal progression of dementia. METHODS: We extracted electronic health record data from July 2003 to February 2020 from a single academic medical center. We identified dementia and cancer history prior to dementia using ICD-9/10 codes. We measured cognitive decline with the Alabama Brief Cognitive Screener (ABCs). We used adjusted linear mixed models to estimate baseline cognition and rate of progression by cancer history, including differences by race. RESULTS: The study included 3,809 participants with dementia, of which 672 (17.6%) had cancer history. Those with cancer history had higher baseline cognition (β: 0.62, 95% CI: -0.02-1.25), but similar rate of decline. Non-Hispanic Blacks had lower cognitive scores at baseline and throughout follow-up regardless of cancer status compared to non-Hispanic Whites and other races/ethnicities with and without cancer history. CONCLUSION: In this longitudinal retrospective study, participants with cancer history demonstrate better cognition at dementia diagnosis and no difference in cognitive decline than those without cancer history. Smoking and comorbidities attenuate this association and results indicate non-Hispanic Blacks have worse cognitive outcomes in dementia regardless of cancer history than other race/ethnicity groups. Further exploration of the role of smoking, comorbidities, and race/ethnicity on cancer and dementia-related cognitive decline is needed.

Risk of Dementia in Cancer Survivors: A Meta-Analysis of Population-Based Cohort Studies. - Zhang, Dan-Dan; Ou, Ya-Nan; Fu, Yan; Wang, Zhi-Bo; Huang, Liang-Yu; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: A negative association between cancer and Alzheimer's disease (AD) was revealed. OBJECTIVE: We aimed to further explore the dementia risk among cancer survivors and then among cancer survivors who received cancer treatment in subsequent subgroup analyses. METHODS: Databases of PubMed, Embase, and Cochrane Library were systematically searched from inception to April 1, 2021, following PRISMA and MOOSE guidelines. Relative risks (RR) of dementia were pooled by a random-effects model stratifying the data by potential confounding factors to explore the heterogeneity. This study is registered with PROSPERO, number CRD42021250654. RESULTS: A total of 36 studies were included in this meta-analysis, of which 16 studies were about the risk of dementia in cancer survivors, and 20 studies were about the risk of dementia in survivors who accepted cancer treatment. The pooled RR reached 0.89 ([95% CI = 0.82-0.97], I2 = 97.9%) for dementia and 0.89 ([0.83-0.95], I2 = 92.6%) for AD in cancer survivors compared with non-cancer controls. Notably, both dementia risk and AD risk significantly decreased in survivors of colon, leukemia, small intestine, and thyroid cancers (RR ranged from 0.64 to 0.92). Furthermore, prostate cancer patients treated with androgen deprivation therapy exhibited a significantly increased risk of dementia (RR:1.18 [1.09-1.27], I2 = 89.5%) and AD (RR:1.17 [1.08-1.25], I2 = 81.3%), with evidence of between-study heterogeneity. CONCLUSION: Currently, available evidence suggests that the risk of dementia among cancer survivors is decreased. However, large-scale prospective cohort studies are warranted to further prove the association.

Scavenging Reactive Oxygen Species Decreases Amyloid-β Levels via Activation of PI3K/Akt/GLUT1 Pathway in N2a/APP695swe Cells. - Peng, Yan; Zhang, Li; Zhou, Fanlin; Wang, Yangyang; Zhang, Xiong; Fan, Jianing; Li, Shijie; Li, Xiaoju; Li, Yu (J Alzheimers Dis, 2022)
BACKGROUND: Dysregulated glucose metabolism in the brain is considered to be one of the key causes of Alzheimer's disease (AD). Abnormal glucose uptake in AD is tightly associated with decreased levels of glucose transporter 1 (GLUT1) and GLUT3 in the brain, but the underlying mechanisms remain unclear. OBJECTIVE: We aimed to explore the cause and mechanism of impaired glucose uptake in AD. METHODS: N2a/WT and N2a/APP695swe cells were cultured in vitro, and cellular glucose uptake and ATP content, as well as the expression of GLUT1, GLUT3, and PI3K/Akt pathway members, were detected. Intracellular reactive oxygen species (ROS) levels were detected by flow cytometry. After treatment with the ROS scavenger N-acetyl-L-cysteine (NAC), the above indicators were detected again. RESULTS: GLUT1 expression was significantly decreased (p = 0.0138) in N2a/APP695swe cells, while GLUT3 expression was no statistical difference (p >  0.05). After NAC treatment, PI3K and Akt phosphorylation levels, GLUT1 expression, glucose uptake and ATP levels were remarkably increased (p = 0.0006, p = 0.0008, p = 0.0009, p = 0.0001, p = 0.0013), while Aβ levels were significantly decreased (p = 0.0058, p = 0.0066). After addition of the PI3K inhibitor LY29004, GLUT1 expression was reduced (p = 0.0008), and Aβ levels were increased (p = 0.0009, p = 0.0117). In addition, increases in glucose uptake and ATP levels induced by the Akt activator SC79 were hindered by the GLUT1 inhibitor WZB117 (p = 0.0002, p = 0.0005). Aβ levels were decreased after SC79 treatment and increased after WZB117 treatment (p = 0.0212, p = 0.0006). CONCLUSION: Taken together, scavenging of ROS prevents from Aβ deposition via activation of the PI3K/Akt/GLUT1 pathway, and improved the impaired glucose uptake in N2a/APP695swe cells.

Single Nucleus Transcriptome Data from Alzheimer's Disease Mouse Models Yield New Insight into Pathophysiology. - Weller, Andrew E; Ferraro, Thomas N; Doyle, Glenn A; Reiner, Benjamin C; Crist, Richard C; Berrettini, Wade H (J Alzheimers Dis, 2022)
BACKGROUND: 5XFAD humanized mutant mice and Trem2 knockout (T2KO) mice are two mouse models relevant to the study of Alzheimer's disease (AD)-related pathology. OBJECTIVE: To determine hippocampal transcriptomic and polyadenylation site usage alterations caused by genetic mutations engineered in 5XFAD and T2KO mice. METHODS: Employing a publicly available single-nucleus RNA sequencing dataset, we used Seurat and Sierra analytic programs to identify differentially expressed genes (DEGs) and differential transcript usage (DTU), respectively, in hippocampal cell types from each of the two mouse models. We analyzed cell type-specific DEGs further using Ingenuity Pathway Analysis (IPA). RESULTS: We identified several DEGs in both neuronal and glial cell subtypes in comparisons of wild type (WT) versus 5XFAD and WT versus T2KO mice, including Ttr, Fth1, Pcsk1n, Malat1, Rpl37, Rtn1, Sepw1, Uba52, Mbp, Arl6ip5, Gm26917, Vwa1, and Pgrmc1. We also observed DTU in common between the two comparisons in neuronal and glial subtypes, specifically in the genes Prnp, Rbm4b, Pnisr, Opcml, Cpne7, Adgrb1, Gabarapl2, Ubb, Ndfip1, Car11, and Stmn4. IPA identified 3 statistically significant canonical pathways that appeared in multiple cell types and that overlapped between 5XFAD and T2KO comparisons to WT, including 'FXR/RXR Activation', 'LXR/RXR Activation', and 'Acute Phase Response Signaling'. CONCLUSION: DEG, DTU, and IPA findings, derived from two different mouse models of AD, highlight the importance of energy imbalance and inflammatory processes in specific hippocampal cell types, including subtypes of neurons and glial cells, in the development of AD-related pathology. Additional studies are needed to further characterize these findings.

Weight Loss and Alzheimer's Disease in Down Syndrome. - Fleming, Victoria; Helsel, Brian C; Ptomey, Lauren T; Rosas, H Diana; Handen, Benjamin; Laymon, Charles; Christian, Bradley T; Head, Elizabeth; Mapstone, Mark; Lai, Florence; Krinsky-McHale, Sharon; Zaman, Shahid; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Virtually all adults with Down syndrome (DS) develop Alzheimer's disease (AD) pathology, but research gaps remain in understanding early signs of AD in DS. OBJECTIVE: The goal of the present study was to determine if unintentional weight loss is part of AD in DS. The specific aims were to: 1) examine relation between chronological age, weight, AD pathology, and AD-related cognitive decline were assessed in a large cohort of adults with DS, and 2) determine if baseline PET amyloid-β (Aβ) and tau PET status (-versus+) and/or decline in memory and mental status were associated with weight loss prior to AD progression. METHODS: Analyses included 261 adults with DS. PET data were acquired using [11C] PiB for Aβ and [18F] AV-1451 for tau. Body mass index (BMI) was calculated from weight and height. Direct measures assessed dementia and memory. Clinical AD status was determined using a case consensus process. Percent weight decline across 16-20 months was assessed in a subset of participants (n = 77). RESULTS: Polynomial regressions indicated an 0.23 kg/m2 decrease in BMI per year beginning at age 36.5 years, which occurs alongside the period during which Aβ and tau increase and memory and mental status decline. At a within-person level, elevated Aβ, decline in memory and mental status were associated with higher percent weight loss across 16-20 months. CONCLUSION: Unintentional weight loss occurs alongside Aβ deposition and prior to onset of AD dementia, and thus may be a useful sign of AD in DS.

Assessing the Progression of Alzheimer's Disease in Real-World Settings in Three European Countries. - Lladó, Albert; Froelich, Lutz; Khandker, Rezaul K; Roset, Montserrat; Black, Christopher M; Lara, Nuria; Chekani, Farid; Ambegaonkar, Baishali M (J Alzheimers Dis, 2021)
BACKGROUND: There exists considerable variation in disease progression rates among patients with Alzheimer's disease (AD). OBJECTIVE: The primary objective of this observational study is to assess the progression of AD by characterizing cognitive, functional, and behavioral changes during the follow-up period between 6 and 24 months. METHODS: A longitudinal prospective study with community-dwelling patients with an established clinical diagnosis of AD of mild to moderate severity was conducted in Germany, Spain and the UK. A sample of 616 patients from 69 sites was included. RESULTS: Patients had a mean of 1.9 years (SD = 1.9) since AD diagnosis at study inclusion. Cognitive symptoms were reported to have first occurred a mean of 1.1 years (SD = 1.7) prior to AD diagnosis and 1.4 (SD = 1.8) years prior to AD treatment. Patients initially diagnosed with mild and moderate AD spent a median (95%CI) of 3.7 (2.8; 4.4) and 11.1 (6.1, 'not reached') years until progression to moderate and severe AD, respectively, according to the Mini-Mental State Examination (MMSE) scores. A mixed model developed for cognitive, functional, and neuropsychiatric scores, obtained from study patients at baseline and during follow-up period, showed progressive deterioration of AD patients over time. CONCLUSION: The study showed a deterioration of cognitive, functional, and neuropsychiatric functions during the follow-up period. Cognitive deterioration was slightly faster in patients with moderate AD compared to mild AD. The duration of moderate AD can be overestimated due to the use of retrospective data, lack of availability of MMSE scores in clinical charts and exclusion of patients at time of institutionalization.
Keywords: Alzheimer Disease; Cholinesterase Inhibitors; Cognition Disorders; Disease Progression; Europe; Germany; Humans; Institutionalization; Neuropsychological Tests; Spain

Association of Midlife Depressive Symptoms with Regional Amyloid-β and Tau in the Framingham Heart Study. - Gonzales, Mitzi M; Samra, Jasmeet; O'Donnell, Adrienne; Mackin, R Scott; Salinas, Joel; Jacob, Mini; Satizabal, Claudia L; Aparicio, Hugo J; Thibault, Emma G; Sanchez, Justin S; Finney, Rebecca; Rubinstein, Zoe B; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms predict increased risk for dementia decades before the emergence of cognitive symptoms. Studies in older adults provide preliminary evidence for an association between depressive symptoms and amyloid-β (Aβ) and tau accumulation. It is unknown if similar alterations are observed in midlife when preventive strategies may be most effective. OBJECTIVE: The study aim was to evaluate the association between depressive symptoms and cerebral Aβ and tau in a predominately middle-aged cohort with examination of the apolipoprotein (APOE) ɛ4 allele as a moderator. METHODS: Participants included 201 adults (mean age 53±8 years) who underwent 11C-Pittsburgh Compound B amyloid and 18F-Flortaucipir tau positron emission tomography (PET) imaging. Depressive symptoms were evaluated with the Center for Epidemiological Studies Depression Scale (CES-D) at the time of PET imaging, as well as eight years prior. Associations between depressive symptoms at both timepoints, as well as depression (CES-D≥16), with regional Aβ and tau PET retention were evaluated with linear regression adjusting for age and sex. Interactions with the APOE ɛ4 allele were explored. RESULTS: Depressive symptoms and depression were not associated with PET outcomes in the overall sample. However, among APOE ɛ4 allele carriers, there was a significant cross-sectional association between depressive symptoms and increased tau PET uptake in the entorhinal cortex (β= 0.446, SE = 0.155, p = 0.006) and amygdala (β= 0.350, SE = 0.133, p = 0.012). CONCLUSION: Although longitudinal studies are necessary, the results suggest that APOE ɛ4 carriers with depressive symptoms may present with higher susceptibility to early tau accumulation in regions integral to affective regulation and memory consolidation.

Association of White Matter Hyperintensity Progression with Cognitive Decline in Patients with Amnestic Mild Cognitive Impairment. - Hirao, Kentaro; Yamashita, Fumio; Tsugawa, Akito; Haime, Rieko; Fukasawa, Raita; Sato, Tomohiko; Kanetaka, Hidekazu; Umahara, Takahiko; Sakurai, Hirofumi; Hanyu, Haruo; Shimizu, Soichiro (J Alzheimers Dis, 2021)
BACKGROUND: White matter hyperintensities (WMH) on MRI have been reported to increase the risk of conversion from mild cognitive impairment (MCI) to Alzheimer's disease (AD). However, effects of the progression of WMH on the cognition of patients with MCI remains unclear to date. OBJECTIVE: To investigate the association between WMH progression and cognitive decline in amnestic MCI patients. METHODS: Thirty-eight subjects with amnestic MCI were analyzed prospectively every year for 2 years. Fourteen MCI subjects dropped out on the final visit, and therefore 24 subjects with MCI were analyzed for the entire duration. The volumes of periventricular hyperintensities (PVH) and deep WMH (DWMH) were measured on T2 FLAIR using the 3D-slicer. The associations between PVH/DWMH progression and cognitive decline were investigated. RESULTS: An increase in DWMH volume significantly correlated with changes in Mini-Mental State Examination and category verbal fluency scores, whereas an increase in PVH volume did not correlate with changes in any item. CONCLUSION: DWMH progression was closely associated with a decline in frontal lobe function and semantic memory, suggesting that WMH progression might affect some AD pathophysiologies in amnestic MCI patients.

Automatic Subtyping of Individuals with Primary Progressive Aphasia. - Themistocleous, Charalambos; Ficek, Bronte; Webster, Kimberly; den Ouden, Dirk-Bart; Hillis, Argye E; Tsapkini, Kyrana (J Alzheimers Dis, 2021)
BACKGROUND: The classification of patients with primary progressive aphasia (PPA) into variants is time-consuming, costly, and requires combined expertise by clinical neurologists, neuropsychologists, speech pathologists, and radiologists. OBJECTIVE: The aim of the present study is to determine whether acoustic and linguistic variables provide accurate classification of PPA patients into one of three variants: nonfluent PPA, semantic PPA, and logopenic PPA. METHODS: In this paper, we present a machine learning model based on deep neural networks (DNN) for the subtyping of patients with PPA into three main variants, using combined acoustic and linguistic information elicited automatically via acoustic and linguistic analysis. The performance of the DNN was compared to the classification accuracy of Random Forests, Support Vector Machines, and Decision Trees, as well as to expert clinicians' classifications. RESULTS: The DNN model outperformed the other machine learning models as well as expert clinicians' classifications with 80% classification accuracy. Importantly, 90% of patients with nfvPPA and 95% of patients with lvPPA was identified correctly, providing reliable subtyping of these patients into their corresponding PPA variants. CONCLUSION: We show that the combined speech and language markers from connected speech productions can inform variant subtyping in patients with PPA. The end-to-end automated machine learning approach we present can enable clinicians and researchers to provide an easy, quick, and inexpensive classification of patients with PPA.
Keywords: Acoustics; Aged; Aphasia, Primary Progressive; Decision Trees; Female; Humans; Linguistics; Machine Learning; Male; Models, Theoretical; Neural Networks, Computer; Primary Progressive Nonfluent Aphasia; Reproducibility of Results; Support Vector Machine

B Vitamins Prevent Iron-Associated Brain Atrophy and Domain-Specific Effects of Iron, Copper, Aluminum, and Silicon on Cognition in Mild Cognitive Impairment. - Jakubowski, Hieronim; Zioła-Frankowska, Anetta; Frankowski, Marcin; Perła-Kaján, Joanna; Refsum, Helga; de Jager, Celeste A; Smith, A David (J Alzheimers Dis, 2021)

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome Scale (BPSD-DS II): Optimization and Further Validation. - Dekker, Alain D; Ulgiati, Aurora M; Groen, Henk; Boxelaar, Vincent A; Sacco, Silvia; Falquero, Ségolène; Carfi, Angelo; di Paola, Antonella; Benejam, Bessy; Valldeneu, Silvia; Fopma, Roelie; Oosterik, Marjo; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with Down syndrome (DS) are at high risk to develop Alzheimer's disease dementia (AD). Behavioral and psychological symptoms of dementia (BPSD) are common and may also serve as early signals for dementia. However, comprehensive evaluation scales for BPSD, adapted to DS, are lacking. Therefore, we previously developed the BPSD-DS scale to identify behavioral changes between the last six months and pre-existing life-long characteristic behavior. OBJECTIVE: To optimize and further study the scale (discriminative ability and reliability) in a large representative DS study population. METHODS: Optimization was based on item irrelevance and clinical experiences obtained in the initial study. Using the shortened and refined BPSD-DS II, informant interviews were conducted to evaluate 524 individuals with DS grouped according to dementia status: no dementia (DS, N = 292), questionable dementia (DS + Q, N = 119), and clinically diagnosed dementia (DS + AD, N = 113). RESULTS: Comparing item change scores between groups revealed prominent changes in frequency and severity for anxious, sleep-related, irritable, restless/stereotypic, apathetic, depressive, and eating/drinking behavior. For most items, the proportion of individuals displaying an increased frequency was highest in DS + AD, intermediate in DS + Q, and lowest in DS. For various items within sections about anxious, sleep-related, irritable, apathetic, and depressive behaviors, the proportion of individuals showing an increased frequency was already substantial in DS + Q, suggesting that these changes may serve as early signals of AD in DS. Reliability data were promising. CONCLUSION: The optimized scale yields largely similar results as obtained with the initial version. Systematically evaluating BPSD in DS may increase understanding of changes among caregivers and (timely) adaptation of care/treatment.
Keywords: Adult; Aged; Anxiety; Dementia; Down Syndrome; Female; Humans; Irritable Mood; Male; Middle Aged; Reproducibility of Results; Symptom Assessment

Copper Imbalance in Alzheimer's Disease and Its Link with the Amyloid Hypothesis: Towards a Combined Clinical, Chemical, and Genetic Etiology. - Squitti, Rosanna; Faller, Peter; Hureau, Christelle; Granzotto, Alberto; White, Anthony R; Kepp, Kasper P (J Alzheimers Dis, 2021)
The cause of Alzheimer's disease (AD) is incompletely defined. To date, no mono-causal treatment has so far reached its primary clinical endpoints, probably due to the complexity and diverse neuropathology contributing to the neurodegenerative process. In the present paper, we describe the plausible etiological role of copper (Cu) imbalance in the disease. Cu imbalance is strongly associated with neurodegeneration in dementia, but a complete biochemical etiology consistent with the clinical, chemical, and genetic data is required to support a causative association, rather than just correlation with disease. We hypothesize that a Cu imbalance in the aging human brain evolves as a gradual shift from bound metal ion pools, associated with both loss of energy production and antioxidant function, to pools of loosely bound metal ions, involved in gain-of-function oxidative stress, a shift that may be aggravated by chemical aging. We explain how this may cause mitochondrial deficits, energy depletion of high-energy demanding neurons, and aggravated protein misfolding/oligomerization to produce different clinical consequences shaped by the severity of risk factors, additional comorbidities, and combinations with other types of pathology. Cu imbalance should be viewed and integrated with concomitant genetic risk factors, aging, metabolic abnormalities, energetic deficits, neuroinflammation, and the relation to tau, prion proteins, α-synuclein, TAR DNA binding protein-43 (TDP-43) as well as systemic comorbidity. Specifically, the Amyloid Hypothesis is strongly intertwined with Cu imbalance because amyloid-β protein precursor (AβPP)/Aβ are probable Cu/Zn binding proteins with a potential role as natural Cu/Zn buffering proteins (loss of function), and via the plausible pathogenic role of Cu-Aβ.

COVID-19 Crisis Effects on Caregiver Distress in Neurocognitive Disorder. - Alexopoulos, Panagiotis; Soldatos, Rigas; Kontogianni, Evangelia; Frouda, Maria; Loanna Aligianni, Souzana; Skondra, Maria; Passa, Maria; Konstantopoulou, Georgia; Stamouli, Evangelia; Katirtzoglou, Evgenia; Politis, Anastasios; Economou, Polychronis; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The outbreak of the COVID-19 pandemic seems to have mental health implications for both people with neurocognitive disorder and their caregivers. OBJECTIVE: The study aimed to shed light on relations between caregiver mental reaction to the pandemic and caregiver distress related to neuropsychiatric symptoms, memory impairment progression, and functional impairment of people with neurocognitive disorder during the period of confinement in Greece. METHODS: The study included caregivers of patients with mild (N = 13) and major (N = 54) neurocognitive disorder. The caregiver-based telephone interview was based on items of the neuropsychiatric inventory questionnaire, the AD8 Dementia Screening Instrument, and the Bristol Activities of Daily Living Scale. Regarding the mental impact of the COVID-19 crisis on caregivers, four single questions referring to their worries in the last seven days were posed, in addition to the scales Generalized Anxiety Disorder 7-Item (GAD-7) and the 22-item Impact of Event Scale-revised (IES-R). A stepwise linear regression model was employed for studying the relationship between caregiver distress and demographic and clinical data and caregiver mental reaction to COVID-19 pandemic outbreak. RESULTS: Caregiver distress severity during the confinement period was influenced not only by memory deficits (p = 0.009) and neuropsychiatric symptoms (p < 0.001) of patients, but also by caregiver hyperarousal (p = 0.003) and avoidance symptoms (p = 0.033) and worries directly linked to the COVID-19 crisis (p = 0.022). CONCLUSION: These observations provide further evidence for the urgent need for support of caregivers of patients with neurocognitive disorder during the COVID-19 pandemic.
Keywords: Aged; Aged, 80 and over; Caregivers; COVID-19; Female; Greece; Humans; Male; Middle Aged; Neurocognitive Disorders; Quarantine

A Decade of Decline in Serious Cognitive Problems Among Older Americans: A Population-Based Study of 5.4 Million Respondents. - Fuller-Thomson, Esme; Ahlin, Katherine Marie (J Alzheimers Dis, 2021)
BACKGROUND: Numerous studies suggest the prevalence of dementia has decreased over the past several decades in Western countries. Less is known about whether these trends differ by gender or age cohort, and if generational differences in educational attainment explain these trajectories. OBJECTIVE: 1) To detect temporal trends in the age-sex-race adjusted prevalence of serious cognitive problems among Americans aged 65+; 2) To establish if these temporal trends differ by gender and age cohort; 3) To examine if these temporal trends are attenuated by generational differences in educational attainment. METHODS: Secondary analysis of 10 years of annual nationally representative data from the American Community Survey with 5.4 million community-dwelling and institutionalized older adults aged 65+. The question on serious cognitive problems was, "Because of a physical, mental, or emotional condition, does this person have serious difficulty concentrating, remembering, or making decisions?" RESULTS: The prevalence of serious cognitive problems in the US population aged 65 and older declined from 12.2%to 10.0%between 2008 and 2017. Had the prevalence remained at the 2008 levels, there would have been an additional 1.13 million older Americans with serious cognitive problems in 2017. The decline in memory problems across the decade was higher for women (23%) than for men (13%). Adjusting for education substantially attenuated the decline. CONCLUSION: Between 2008 and 2017, the prevalence of serious cognitive impairment among older Americans declined significantly, although these declines were partially attributable to generational differences in educational attainment.

Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care. - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen (J Alzheimers Dis, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Comorbidity; COVID-19; Humans; Neuroimaging; Neuroimmunomodulation; Patient Care; SARS-CoV-2

Depressive Symptoms Imputed Across the Life Course Are Associated with Cognitive Impairment and Cognitive Decline. - Brenowitz, Willa D; Zeki Al Hazzouri, Adina; Vittinghoff, Eric; Golden, Sherita H; Fitzpatrick, Annette L; Yaffe, Kristine (J Alzheimers Dis, 2021)
BACKGROUND: Depressive symptoms may increase risk for dementia, but findings are controversial because late-life depression may be a prodromal dementia symptom. Life course data on depression and dementia risk may clarify this association; however, data is limited. OBJECTIVE: To impute adult depressive symptoms trajectories across adult life stages and estimate the association with cognitive impairment and decline. METHODS: Using a pooled study of 4 prospective cohorts (ages 20-89), we imputed adult life course depressive symptoms trajectories based on Center for Epidemiologic Studies Depression Scale-10 (CESD-10) and calculated time-weighted averages for early adulthood (ages 20-49), mid-life (ages 50-69), and late-life (ages 70-89) for 6,122 older participants. Adjusted pooled logistic and mixed-effects models estimated associations of imputed depressive symptoms with two cognitive outcomes: cognitive impairment defined by established criteria and a composite cognitive score. RESULTS: In separate models, elevated depressive symptoms in each life stage were associated with cognitive outcomes: early adulthood OR for cognitive impairment = 1.59 (95%CI: 1.35,1.87); mid-life OR = 1.94 (95%CI:1.16, 3.26); and late-life OR = 1.77 (95%CI:1.42, 2.21). When adjusted for depressive symptoms in the other life-stages, elevated depressive symptoms in early adulthood (OR = 1.73; 95%CI: 1.42,2.11) and late-life (OR = 1.43; 95%CI: 1.08,1.89) remained associated with cognitive impairment and were also associated with faster rates of cognitive decline (p <  0.05). CONCLUSION: Imputing depressive symptom trajectories from pooled cohorts may help expand data across the life course. Our findings suggest early adulthood depressive symptoms may be a risk factor for cognitive impairment independent of mid- or late-life depressive symptoms.

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Effects of Peroral Omega-3 Fatty Acid Supplementation on Cerebrospinal Fluid Biomarkers in Patients with Alzheimer's Disease: A Randomized Controlled Trial-The OmegAD Study. - Tofiq, Avin; Zetterberg, Henrik; Blennow, Kaj; Basun, Hans; Cederholm, Tommy; Eriksdotter, Maria; Faxen-Irving, Gerd; Hjorth, Erik; Jernerén, Fredrik; Schultzberg, Marianne; Wahlund, Lars-Olof; Palmblad, Jan; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested a connection between a decrease in the levels of polyunsaturated fatty acids (PUFAs) and Alzheimer's disease (AD). We aimed to assess the effect of supplementation with omega-3 fatty acids (n-3 FAs) on biomarkers analyzed in the cerebrospinal fluid (CSF) of patients diagnosed with AD. OBJECTIVE: To investigate the effects of daily supplementation with 2.3 g of PUFAs in AD patients on the biomarkers in CSF described below. We also explored the possible correlation between these biomarkers and the performance in the cognitive test Mini-Mental State Examination (MMSE). METHODS: Thirty-three patients diagnosed with AD were randomized to either treatment with a daily intake of 2.3 g of n-3 FAs (n  =  18) or placebo (n  =  15). CSF samples were collected at baseline and after six months of treatment, and the following biomarkers were analyzed: Aβ 38, Aβ 40, Aβ 42, t-tau, p-tau, neurofilament light (NfL), chitinase-3-like protein 1 (YKL-40), acetylcholinesterase (AChE), butyrylcholinesterase (BuChE), soluble IL-1 receptor type II (sIL-1RII), and IL-6. RESULTS: There were no significant differences between the groups concerning the level of the different biomarkers in the CSF at baseline. Within the treatment group, there was a small but significant increase in both YKL-40 (p = 0.04) and NfL (p = 0.03), while the other CSF biomarkers remained stable. CONCLUSION: Supplementation with n-3 FAs had a statistically significant effect on NfL and YKL-40, resulting in an increase of both biomarkers, indicating a possible increase of inflammatory response and axonal damage. This increase in biomarkers did not correlate with MMSE score.

Enhancing the Sensitivity of Memory Tests: Reference Data for the Free and Cued Selective Reminding Test and the Logical Memory Task from Cognitively Healthy Subjects with Normal Alzheimer's Disease Cerebrospinal Fluid Biomarker Levels. - Brugulat-Serrat, Anna; Cañas, Alba; Canals, Lidia; Marne, Paula; Gramunt, Nina; Milà-Alomà, Marta; Suárez-Calvet, Marc; Arenaza-Urquijo, Eider M; Grau-Rivera, Oriol; González-de-Echávarri, José María; Minguillon, Carolina; Fauria, Karine; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Cognitive performance of a given individual should be interpreted in the context of reference standards obtained in cognitively healthy populations. Recent evidence has shown that removing asymptomatic individuals with biomarker evidence of Alzheimer's disease (AD) pathology from normative samples increases the sensitivity of norms to detect memory impairments. These kind of norms may be useful for defining subtle cognitive decline, the transitional cognitive decline between normal cognition and mild cognitive impairment. OBJECTIVE: The present study aims to provide norms for the Free and Cued Selective Reminding Test (FCSRT) and the Logical Memory subtest of the Wechsler Memory Scale-IV in a sample of individuals aged 50-70 years with normal levels of amyloid (A) and tau (T) cerebrospinal fluid (CSF) biomarkers. METHODS: The sample was composed of 248 individuals from the ALFA+ study with negative amyloid-β and tau CSF biomarker levels. Regression-based norms were developed, including adjustments for age, education, and sex when applicable. RESULTS: We found that education was associated with the performance in all the variables of both tests while age had a marginal effect only in the delayed free recall of the FCSRT. Sex was also related to the performance in the FCSRT, with women outperforming men. Equations to calculate z-scores and normative percentile tables were created. As compared with previously published norms the reference data presented were more sensitive but less specific, as expected. CONCLUSION: The use of the norms provided in this work, in combination with the already published conventional norms, may contribute to detecting subtle memory impairment.

Event-Related Potentials, Inhibition, and Risk for Alzheimer's Disease Among Cognitively Intact Elders. - Elverman, Kathleen H; Paitel, Elizabeth R; Figueroa, Christina M; McKindles, Ryan J; Nielson, Kristy A (J Alzheimers Dis, 2021)
BACKGROUND: Despite advances in understanding Alzheimer's disease (AD), prediction of AD prior to symptom onset remains severely limited, even when primary risk factors such as the apolipoprotein E (APOE) ɛ4 allele are known. OBJECTIVE: Although executive dysfunction is highly prevalent and is a primary contributor to loss of independence in those with AD, few studies have examined neural differences underlying executive functioning as indicators of risk for AD prior to symptom onset, when intervention might be effective. METHODS: This study examined event-related potential (ERP) differences during inhibitory control in 44 cognitively intact older adults (20 ɛ4+, 24 ɛ4-), relative to 41 young adults. All participants completed go/no-go and stop-signal tasks. RESULTS: Overall, both older adult groups exhibited slower reaction times and longer ERP latencies compared to young adults. Older adults also had generally smaller N200 and P300 amplitudes, except at frontal electrodes and for N200 stop-signal amplitudes, which were larger in older adults. Considered with intact task accuracy, these findings suggest age-related neural compensation. Although ɛ4 did not distinguish elders during go or no-go tasks, this study uniquely showed that the more demanding stop-signal task was sensitive to ɛ4 differences, despite comparable task and neuropsychological performance with non-carriers. Specifically, ɛ4+ elders had slower frontal N200 latency and larger N200 amplitude, which was most robust at frontal sites, compared with ɛ4-. CONCLUSION: N200 during a stop-signal task is sensitive to AD risk, prior to any evidence of cognitive dysfunction, suggesting that stop-signal ERPs may be an important protocol addition to neuropsychological testing.

Is the Frontal Lobe the Primary Target of SARS-CoV-2? - Toniolo, Sofia; Di Lorenzo, Francesco; Scarioni, Marta; Frederiksen, Kristian Steen; Nobili, Flavio (J Alzheimers Dis, 2021)
Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET imaging. We suggest that an inflammatory parainfectious process targeting preferentially the frontal lobes (and/or frontal networks) could be the underlying cause of these shared clinical, neurophysiological, and imaging findings in COVID-19 patients. We explore the biological mechanisms and the clinical biomarkers that might underlie such disruption of frontal circuits and highlight the need of standardized diagnostic procedures to be applied when investigating patients with these clinical findings. We also suggest the use of a unique label, to increase comparability across studies.
Keywords: Acute Febrile Encephalopathy; Biomarkers; COVID-19; Delirium; Electroencephalography; Frontal Lobe; Humans; Magnetic Resonance Imaging; Nerve Net; SARS-CoV-2; Virulence

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

Improving the Diagnosis of the Frontal Variant of Alzheimer's Disease with the DAPHNE Scale. - Lehingue, Elsa; Gueniat, Julien; Jourdaa, Sandra; Hardouin, Jean BenoÎt; Pallardy, Amandine; Courtemanche, Hélène; Rocher, Laetitia; Etcharry-Bouyx, Frédérique; Auriacombe, Sophie; Mollion, Hélène; Formaglio, Maıté; Rouaud, Olivier; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The frontal variant of Alzheimer's disease (fAD) is poorly understood and poorly defined. The diagnosis remains challenging. The main differential diagnosis is the behavioral variant of frontotemporal degeneration (bvFTD). For fAD, there is some dissociation between the clinical frontal presentation and imaging and neuropathological studies, which do not always find a specific involvement of the frontal lobes. DAPHNE is a behavioral scale, which demonstrated excellent performance to distinguish between bvFTD and AD. OBJECTIVE: The aim of the present study was to assess the reliability of this new tool to improve the clinical diagnosis of fAD. METHODS: Twenty fAD patients and their caregivers were prospectively included and were compared with 36 bvFTD and 22 AD patients. RESULTS: The three main behavioral disorders in the fAD patients were apathy, loss of empathy, and disinhibition. Three disorders were discriminant because they were less frequent and less severe in the fAD patients than in the bvFTD patients, namely hyperorality, neglect, and perseverations. This specific pattern of behavioral disorders was corroborated by SPECT or 18FDG PET-CT scan that showed that patients with fAD could have a medial frontal hypoperfusion, whereas in bvFTD patients the orbitofrontal cortex was the main involved region, with more diffuse hypoperfusion. CONCLUSION: We demonstrated that DAPHNE had good sensitivity and good specificity to discriminate between the three groups and in particular between fAD and bvFTD patients. DAPHNE is a quick tool that could help clinicians in memory clinics not only to differentiate bvFTD from typical AD but also from fAD.
Keywords: Aged; Alzheimer Disease; Cohort Studies; Diagnosis, Differential; Female; Frontal Lobe; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests

Internal Jugular Vein Velocity and Spontaneous Echo Contrast Correlate with Alzheimer's Disease and Cognitive Function. - Matsuzono, Kosuke; Suzuki, Masayuki; Miura, Kumiko; Ozawa, Tadashi; Mashiko, Takafumi; Koide, Reiji; Tanaka, Ryota; Fujimoto, Shigeru (J Alzheimers Dis, 2021)
BACKGROUND: Many issues persist in the today's Alzheimer's disease (AD) screening and the breakthrough method is desired. OBJECTIVE: We aim to validate the association between venous reflux and AD, and to develop a new method for AD screening. METHODS: We examined spontaneous echo contrast, area, diameter, retrograde velocity, and anterograde velocity of the bilateral cervical internal jugular vein (IJV) using carotid ultrasonography. RESULTS: A total of 112 patients participated in this study, with 26 diagnosed as AD. The proportion of both or either IJV spontaneous echo contrast (+) occupied 25 of total 26 AD patients, which showed 96.2%of sensitivity and 98.5%negative predictive value. The IJV velocities also showed significant correlation with AD diagnosis, although the IJV area or diameter did not. CONCLUSION: Our results indicate that the validation of the spontaneous echo contrast or velocities of the IJV are convenient AD diagnosis screening methods and that the venous reflux disturbance correlates with AD development.

Loneliness, Not Social Support, Is Associated with Cognitive Decline and Dementia Across Two Longitudinal Population-Based Cohorts. - Freak-Poli, Rosanne; Wagemaker, Nina; Wang, Rui; Lysen, Thom S; Ikram, M Arfan; Vernooij, Meike W; Dintica, Christina S; Vernooij-Dassen, Myrra; Melis, Rene J M; Laukka, Erica J; Fratiglioni, Laura; Xu, Weili; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Poor social health is likely associated with cognitive decline and risk of dementia; however, studies show inconsistent results. Additionally, few studies separate social health components or control for mental health. OBJECTIVE: To investigate whether loneliness and social support are independently associated with cognitive decline and risk of dementia, and whether depressive symptoms confound the association. METHODS: We included 4,514 participants from the population-based Rotterdam Study (RS; aged 71±7SD years) followed up to 14 years (median 10.8, interquartile range 7.4-11.6), and 2,112 participants from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K; aged 72±10SD years) followed up to 10 years (mean 5.9±1.6SD). At baseline, participants were free of major depression and scored on the Mini-Mental State Examination (MMSE) ≥26 for RS and ≥25 for SNAC-K. We investigated loneliness, perceived social support, and structural social support (specifically marital status and number of children). In both cohorts, dementia was diagnosed and cognitive function was repeatedly assessed with MMSE and a global cognitive factor (g-factor). RESULTS: Loneliness was prospectively associated with a decline in the MMSE in both cohorts. Consistently, persons who were lonely had an increased risk of developing dementia (RS: HR 1.34, 95%CI 1.08-1.67; SNAC-K: HR 2.16, 95%CI 1.12-4.17). Adjustment for depressive symptoms and exclusion of the first 5 years of follow-up did not alter results. Neither perceived or structural social support was associated with cognitive decline or dementia risk. CONCLUSION: Loneliness, not social support, predicted cognitive decline and incident dementia independently of depressive symptoms.

Longitudinal Trajectories in Cortical Thickness and Volume Atrophy: Superior Cognitive Performance Does Not Protect Against Brain Atrophy in Older Adults. - Gardener, Samantha L; Weinborn, Michael; Sohrabi, Hamid R; Doecke, James D; Bourgeat, Pierrick; Rainey-Smith, Stephanie R; Shen, Kai-Kai; Fripp, Jurgen; Taddei, Kevin; Maruff, Paul; Salvado, Olivier; Savage, Greg; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Previous research has identified a small subgroup of older adults that maintain a high level of cognitive functioning well into advanced age. Investigation of those with superior cognitive performance (SCP) for their age is important, as age-related decline has previously been thought to be inevitable. OBJECTIVE: Preservation of cortical thickness and volume was evaluated in 76 older adults with SCP and 100 typical older adults (TOAs) assessed up to five times over six years. METHODS: Regions of interest (ROIs) found to have been associated with super-aging status (a construct similar to SCP status) in previous literature were investigated, followed by a discovery phase analyses of additional regions. SCPs were aged 70 + at baseline, scoring at/above normative memory (CVLT-II) levels for demographically similar individuals aged 30-44 years old, and in the unimpaired range for all other cognitive domains over the course of the study. RESULTS: In linear mixed models, following adjustment for multiple comparisons, there were no significant differences between rates of thinning or volume atrophy between SCPs and TOAs in previously identified ROIs, or the discovery phase analyses. With only amyloid-β negative individuals in the analyses, again there were no significant differences between SCPs and TOAs. CONCLUSION: The increased methodological rigor in classifying groups, together with the influence of cognitive reserve, are discussed as potential factors accounting for our findings as compared to the extant literature on those with superior cognitive performance for their age.

Low Doses of Ionizing Radiation as a Treatment for Alzheimer's Disease: A Pilot Study. - Cuttler, Jerry M; Abdellah, Eslam; Goldberg, Yael; Al-Shamaa, Sarmad; Symons, Sean P; Black, Sandra E; Freedman, Morris (J Alzheimers Dis, 2021)
BACKGROUND: In 2015, a patient in hospice with Alzheimer's disease (AD) was treated with ionizing radiation to her brain using repeated CT scans. Improvement in cognition, speech, movement, and appetite was observed. These improvements were so momentous that she was discharged from the hospice to a long-term care home. Based on this case, we conducted a pilot clinical trial to examine the effect of low-dose ionizing radiation (LDIR) in severe AD. OBJECTIVE: To determine whether the previously reported benefits of LDIR in a single case with AD could be observed again in other cases with AD when the same treatments are given. METHODS: In this single-arm study, four patients were treated with three consecutive treatments of LDIR, each spaced two weeks apart. Qualitative changes in communication and behavior with close relatives were observed and recorded. Quantitative measures of cognition and behavior were administered pre and post LDIR treatments. RESULTS: Minor improvements on quantitative measures were noted in three of the four patients following treatment. However, the qualitative observations of cognition and behavior suggested remarkable improvements within days post-treatment, including greater overall alertness. One patient showed no change. CONCLUSION: LDIR may be a promising, albeit controversial therapy for AD. Trials of patients with less severe AD, double-blind and placebo-controlled, should be carried out to determine the benefits of LDIR. Quantitative measures are needed that are sensitive to the remarkable changes induced by LDIR, such as biological markers of oxidative stress that are associated with AD.
Keywords: Aged, 80 and over; Alzheimer Disease; Cranial Irradiation; Female; Humans; Male; Pilot Projects; Radiation, Ionizing

Metabolites Associated with Early Cognitive Changes Implicated in Alzheimer's Disease. - Darst, Burcu F; Huo, Zhiguang; Jonaitis, Erin M; Koscik, Rebecca L; Clark, Lindsay R; Lu, Qiongshi; Kremen, William S; Franz, Carol E; Rana, Brinda; Lyons, Michael J; Hogan, Kirk J; Zhao, Jinying; et al. (J Alzheimers Dis, 2021)

Mild Behavioral Impairment and Subjective Cognitive Decline Predict Cognitive and Functional Decline. - Ismail, Zahinoor; McGirr, Alexander; Gill, Sascha; Hu, Sophie; Forkert, Nils D; Smith, Eric E (J Alzheimers Dis, 2021)
BACKGROUND: Mild behavioral impairment (MBI) and subjective cognitive decline (SCD) are dementia risk states, and potentially represent neurobehavioral and neurocognitive manifestations, respectively, of early stage neurodegeneration. Both MBI and SCD predict incident cognitive decline and dementia, are associated with known dementia biomarkers, and are both represented in the NIA-AA research framework for AD in Stage 2 (preclinical disease). OBJECTIVE: To assess the associations of MBI and SCD, alone and in combination, with incident cognitive and functional decline in a population of older adults. We tested the hypothesis that MBI and SCD confer additive risk for decline. METHODS: Cognitively normal participants were followed up annually at Alzheimer's Disease Centers. Logistic regression assessed the relationship between baseline classification (MBI-SCD-, MBI-SCD+, MBI+SCD-, or MBI+SCD+) and 3-year outcome. RESULTS: Of 2,769 participants (mean age=76), 1,536 were MBI-SCD-, 254 MBI-SCD+, 743 MBI+SCD-, and 236 MBI+SCD+. At 3 years, 349 (12.6%) declined to CDR >0, including 23.1% of the MBI+group, 23.5% of the SCD+group, and 30.9% of the intersection group of both MBI+and SCD+participants. Compared to SCD-MBI-, we observed an ordinal progression in risk (ORs [95% CI]): 3.61 [2.42-5.38] for MBI-SCD+ (16.5% progression), 4.76 [3.57-6.34] for MBI+SCD- (20.7%), and 8.15 [5.71-11.64] for MBI+SCD+(30.9%). CONCLUSION: MBI and SCD together were associated with the greatest risk of decline. These complementary dementia risk syndromes can be used as simple and scalable methods to identify high-risk patients for workup or for clinical trial enrichment.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Disease Progression; Executive Function; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Odds Ratio; Risk Assessment

New Frontiers in the Prevention, Diagnosis, and Treatment of Alzheimer's Disease. - Guzmán-Martínez, Leonardo; Calfío, Camila; Farías, Gonzalo A; Vilches, Cristian; Prieto, Raul; Maccioni, Ricardo B (J Alzheimers Dis, 2021)
One of the major puzzles in medical research and public health systems worldwide is Alzheimer's disease (AD), reaching nowadays a prevalence near 50 million people. This is a multifactorial brain disorder characterized by progressive cognitive impairment, apathy, and mood and neuropsychiatric disorders. The main risk of AD is aging; a normal biological process associated with a continuum dynamic involving a gradual loss of people's physical capacities, but with a sound experienced view of life. Studies suggest that AD is a break from normal aging with changes in the powerful functional capacities of neurons as well as in the mechanisms of neuronal protection. In this context, an important path has been opened toward AD prevention considering that there are elements of nutrition, daily exercise, avoidance of toxic substances and drugs, an active social life, meditation, and control of stress, to achieve healthy aging. Here, we analyze the involvement of such factors and how to control environmental risk factors for a better quality of life. Prevention as well as innovative screening programs for early detection of the disease using reliable biomarkers are becoming critical to control the disease. In addition, the failure of traditional pharmacological treatments and search for new drugs has stimulated the emergence of nutraceutical compounds in the context of a "multitarget" therapy, as well as mindfulness approaches shown to be effective in the aging, and applied to the control of AD. An integrated approach involving all these preventive factors combined with novel pharmacological approaches should pave the way for the future control of the disease.
Keywords: Acupuncture Therapy; Aging; Alzheimer Disease; Biomarkers; Dietary Supplements; Early Diagnosis; Humans; Medicine, Chinese Traditional; Meditation; Quality of Life; Treatment Outcome

Niemann-Pick Type C 1 (NPC1) and NPC2 Gene Variability in Demented Patients with Evidence of Brain Amyloid Deposition. - Sorrentino, Federica; Arighi, Andrea; Serpente, Maria; Arosio, Beatrice; Arcaro, Marina; Visconte, Caterina; Rotondo, Emanuela; Vimercati, Roberto; Ferri, Evelyn; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variants in Niemann-Pick Type C genes (NPC1 and NPC2) have been suggested to play a role as risk or disease modifying factors for Alzheimer's disease (AD). OBJECTIVE: The aim of this study was to analyze NPC1 and NPC2 variability in demented patients with evidence of brain amyloid-β 1-42 (Aβ) deposition and to correlate genetic data with clinical phenotypes. METHODS: A targeted Next Generation Sequencing panel was customized to screen NPC1, NPC2, and main genes related to neurodegenerative dementias in a cohort of 136 demented patients with cerebrospinal fluid (CSF) low Aβ levels or positive PET with Aβ tracer and 200 non-demented geriatric subjects. RESULTS: Seven patients were carriers of NPC variants in heterozygosis. Four of them displayed pathogenic variants previously found in NPC patients and one AD patient had a novel variant. The latter was absent in 200 non-demented elderly subjects. Five of seven patients (70%) exhibited psychiatric symptoms at onset or later as compared with 43%in non-carriers (p >  0.05). CONCLUSION: The frequency of NPC1 and NPC2 heterozygous variants in patients with CSF evidence of Aβ deposition is higher than in the general population.

Paraoxonase 1, B Vitamins Supplementation, and Mild Cognitive Impairment. - Perła-Kaján, Joanna; Włoczkowska, Olga; Zioła-Frankowska, Anetta; Frankowski, Marcin; David Smith, A; de Jager, Celeste A; Refsum, Helga; Jakubowski, Hieronim (J Alzheimers Dis, 2021)
BACKGROUND: Identification of modifiable risk factors that affect cognitive decline is important for the development of preventive and treatment strategies. Status of paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme, may play a role in the development of neurological diseases, including Alzheimer's disease. OBJECTIVE: We tested a hypothesis that PON1 status predicts cognition in individuals with mild cognitive impairment (MCI). METHODS: Individuals with MCI (n = 196, 76.8-years-old, 60% women) participating in a randomized, double-blind placebo-controlled trial (VITACOG) were assigned to receive a daily dose of folic acid (0.8 mg), vitamin B12 (0.5 mg) and B6 (20 mg) (n = 95) or placebo (n = 101) for 2 years. Cognition was analyzed by neuropsychological tests. Brain atrophy was quantified in a subset of participants (n = 168) by MRI. PON1 status, including PON1 Q192R genotype, was determined by quantifying enzymatic activity of PON1 using paraoxon and phenyl acetate as substrates. RESULTS: In the placebo group, baseline phenylacetate hydrolase (PhAcase) activity of PON1 (but not paraoxonase activity or PON1 Q192R genotype) was significantly associated with global cognition (Mini-Mental State Examination, MMSE; Telephone Inventory for Cognitive Status-modified, TICS-m), verbal episodic memory (Hopkins Verbal Learning Test-revised: Total Recall, HVLT-TR; Delayed Recall, HVLT-DR), and attention/processing speed (Trail Making A and Symbol Digits Modalities Test, SDMT) at the end of study. In addition to PhAcase, baseline iron and triglycerides predicted MMSE, baseline fatty acids predicted SDMT, baseline anti-N-Hcy-protein autoantibodies predicted TICS-m, SDMT, Trail Making A, while BDNF V66M genotype predicted HVLT-TR and HVLT-DR scores at the end of study. B-vitamins abrogated associations of PON1 and other variables with cognition. CONCLUSION: PON1 is a new factor associated with impaired cognition that can be ameliorated by B-vitamins in individuals with MCI.

Pharmacological Strategies to Improve Dendritic Spines in Alzheimer's Disease. - Ettcheto, Miren; Busquets, Oriol; Cano, Amanda; Sánchez-López, Elena; Manzine, Patricia R; Espinosa-Jimenez, Triana; Verdaguer, Ester; Sureda, Francesc X; Olloquequi, Jordi; Castro-Torres, Ruben D; Auladell, Carme; Folch, Jaume; et al. (J Alzheimers Dis, 2021)
To deeply understand late onset Alzheimer's disease (LOAD), it may be necessary to change the concept that it is a disease exclusively driven by aging processes. The onset of LOAD could be associated with a previous peripheral stress at the level of the gut (changes in the gut microbiota), obesity (metabolic stress), and infections, among other systemic/environmental stressors. The onset of LOAD, then, may result from the generation of mild peripheral inflammatory processes involving cytokine production associated with peripheral stressors that in a second step enter the brain and spread out the process causing a neuroinflammatory brain disease. This hypothesis could explain the potential efficacy of Sodium Oligomannate (GV-971), a mixture of acidic linear oligosaccharides that have shown to remodel gut microbiota and slowdown LOAD. However, regardless of the origin of the disease, the end goal of LOAD-related preventative or disease modifying therapies is to preserve dendritic spines and synaptic plasticity that underlay and support healthy cognition. Here we discuss how systemic/environmental stressors impact pathways associated with the regulation of spine morphogenesis and synaptic maintenance, including insulin receptor and the brain derived neurotrophic factor signaling. Spine structure remodeling is a plausible mechanism to maintain synapses and provide cognitive resilience in LOAD patients. Importantly, we also propose a combination of drugs targeting such stressors that may be able to modify the course of LOAD by acting on preventing dendritic spines and synapsis loss.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Dendritic Spines; Diet, Healthy; Exercise; Gastrointestinal Microbiome; Humans; Mannose; Oligosaccharides; Synapses

Physical Activity and Trajectory of Cognitive Change in Older Persons: Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Syrjanen, Jeremy A; Bezold, Jelena; Trautwein, Sandra; Barisch-Fritz, Bettina; Boes, Klaus; Woll, Alexander; Forzani, Erica; Kremers, Walter K; Machulda, Mary M; Mielke, Michelle M; Knopman, David S; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Little is known about the association between physical activity (PA) and cognitive trajectories in older adults. OBJECTIVE: To examine the association between PA and change in memory, language, attention, visuospatial skills, and global cognition, and a potential impact of sex or Apolipoprotein E (APOE) ɛ4 status. METHODS: Longitudinal study derived from the population-based Mayo Clinic Study of Aging, including 2,060 cognitively unimpaired males and females aged ≥70 years. Engagement in midlife (ages 50-65) and late-life (last year) PA was assessed using a questionnaire. Neuropsychological testing was done every 15 months (mean follow-up 5.8 years). We ran linear mixed-effect models to examine whether mid- or late-life PA at three intensities (mild, moderate, vigorous) was associated with cognitive z-scores. RESULTS: Light intensity midlife PA was associated with less decline in memory function compared to the no-PA reference group (time x light PA; estimate [standard error] 0.047 [0.016], p = 0.004). Vigorous late-life PA was associated with less decline in language (0.033 [0.015], p = 0.030), attention (0.032 [0.017], p = 0.050), and global cognition (0.039 [0.016], p = 0.012). Females who were physically inactive in midlife experienced more pronounced cognitive decline than females physically active in midlife and males regardless of PA (p-values for time interaction terms with midlife PA levels and sex were all p <  0.05 for global cognition). APOE ɛ4 carriership did not moderate the association between PA and cognition. CONCLUSION: Engaging in PA, particularly of vigorous intensity in late-life, was associated with less pronounced decline in global and domain-specific cognition. This association may differ by sex.

Plasma EFEMP1 Is Associated with Brain Aging and Dementia: The Framingham Heart Study. - McGrath, Emer R; Himali, Jayandra J; Levy, Daniel; Yang, Qiong; DeCarli, Charles S; Courchesne, Paul; Satizabal, Claudia L; Finney, Rebecca; Vasan, Ramachandran S; Beiser, Alexa S; Seshadri, Sudha (J Alzheimers Dis, 2021)
BACKGROUND: Epidermal growth factor containing fibulin extracellular matrix protein-1 (EFEMP1) has been associated with increased white matter hyperintensities (WMH) burden and disorders of premature aging and may have a shared pathophysiological role in the development of WMH and dementia. OBJECTIVE: To determine the association between plasma EFEMP1 levels and MRI markers of vascular brain injury and incident all-cause and Alzheimer's disease (AD) dementia. METHODS: We measured plasma EFEMP1 levels in 1597 [53% women, mean age 68.7 (SD 5.7) years] dementia-free Framingham Offspring cohort participants between 1998-2001 and subsequently followed them for incident dementia. Secondary outcomes included stroke, structural MRI brain measures and neurocognitive test performance. RESULTS: During a median 11.8 [Q1, Q3 : 7.1, 13.3] year follow-up, 131 participants developed dementia. The highest quintile of plasma EFEMP1, compared to the bottom four quintiles, was associated with an increased risk of time to incident all-cause dementia (HR 1.77, 95% CI 1.18-2.64) and AD dementia (HR 1.76, 95% CI 1.11-2.81) but not with markers of vascular brain injury (WMH, covert brain infarcts or stroke). Higher circulating EFEMP1 concentrations were also cross-sectionally associated with lower total brain (β±SE, -0.28±0.11, p = 0.01) and hippocampal volumes (-0.006±0.003, p = 0.04) and impaired abstract reasoning (Similarities test, -0.18±0.08, p = 0.018 per standard deviation increment in EFEMP1). CONCLUSION: Elevated circulating EFEMP1 is associated with an increased risk of all-cause and AD dementia, smaller hippocampal and total brain volumes, and poorer cognitive performance. EFEMP1 may play an important biological role in the development of AD dementia. Further studies to validate these findings are warranted.

Plasma Total-Tau and Neurofilament Light Chain as Diagnostic Biomarkers of Alzheimer's Disease Dementia and Mild Cognitive Impairment in Adults with Down Syndrome. - Petersen, Melissa E; Rafii, Michael S; Zhang, Fan; Hall, James; Julovich, David; Ances, Beau M; Schupf, Nicole; Krinsky-McHale, Sharon J; Mapstone, Mark; Silverman, Wayne; Lott, Ira; Klunk, William; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The need for diagnostic biomarkers of cognitive decline is particularly important among aging adults with Down syndrome (DS). Growing empirical support has identified the utility of plasma derived biomarkers among neurotypical adults with mild cognitive impairment (MCI) and Alzheimer's disease (AD); however, the application of such biomarkers has been limited among the DS population. OBJECTIVE: This study aimed to investigate the cross-sectional diagnostic performance of plasma neurofilament light chain (Nf-L) and total-tau, individually and in combination among a cohort of DS adults. METHODS: Plasma samples were analyzed from n = 305 (n = 225 cognitively stable (CS); n = 44 MCI-DS; n = 36 DS-AD) participants enrolled in the Alzheimer's Biomarker Consortium -Down Syndrome. RESULTS: In distinguishing DS-AD participants from CS, Nf-L alone produced an AUC of 90%, total-tau alone reached 74%, and combined reached an AUC of 86%. When age and gender were included, AUC increased to 93%. Higher values of Nf-L, total-tau, and age were all shown to be associated with increased risk for DS-AD. When distinguishing MCI-DS participants from CS, Nf-L alone produced an AUC of 65%, while total-tau alone reached 56%. A combined model with Nf-L, total-tau, age, and gender produced an AUC of 87%. Both higher values in age and total-tau were found to increase risk for MCI-DS; Nf-L levels were not associated with increased risk for MCI-DS. CONCLUSION: Advanced assay techniques make total-tau and particularly Nf-L useful biomarkers of both AD pathology and clinical status in DS and have the potential to serve as outcome measures in clinical trials for future disease-modifying drugs.

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Quantifying and Examining Reserve in Symptomatic Former National Football League Players. - Foley, Éimear M; Tripodis, Yorghos; Yhang, Eukyung; Koerte, Inga K; Martin, Brett M; Palmisano, Joseph; Makris, Nikos; Schultz, Vivian; Lepage, Chris; Muehlmann, Marc; Wróbel, Paweł P; Guenette, Jeffrey P; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Repetitive head impacts (RHI) from contact sports have been associated with cognitive and neuropsychiatric disorders. However, not all individuals exposed to RHI develop such disorders. This may be explained by the reserve hypothesis. It remains unclear if the reserve hypothesis accounts for the heterogenous symptom presentation in RHI-exposed individuals. Moreover, optimal measurement of reserve in this population is unclear and likely unique from non-athlete populations. OBJECTIVE: We examined the association between metrics of reserve and cognitive and neuropsychiatric functioning in 89 symptomatic former National Football League players. METHODS: Individual-level proxies (e.g., education) defined reserve. We additionally quantified reserve as remaining residual variance in 1) episodic memory and 2) executive functioning performance, after accounting for demographics and brain pathology. Associations between reserve metrics and cognitive and neuropsychiatric functioning were examined. RESULTS: Higher reading ability was associated with better attention/information processing (β=0.25; 95% CI, 0.05-0.46), episodic memory (β=0.27; 95% CI, 0.06-0.48), semantic and phonemic fluency (β=0.24; 95% CI, 0.02-0.46; β=0.38; 95% CI, 0.17-0.59), and behavioral regulation (β=-0.26; 95% CI, -0.48, -0.03) performance. There were no effects for other individual-level proxies. Residual episodic memory variance was associated with better attention/information processing (β=0.45; 95% CI, 0.25, 0.65), executive functioning (β=0.36; 95% CI, 0.15, 0.57), and semantic fluency (β=0.38; 95% CI, 0.17, 0.59) performance. Residual executive functioning variance was associated with better attention/information processing (β=0.44; 95% CI, 0.24, 0.64) and episodic memory (β=0.37; 95% CI, 0.16, 0.58) performance. CONCLUSION: Traditional reserve proxies (e.g., years of education, occupational attainment) have limitations and may be unsuitable for use in elite athlete samples. Alternative approaches of reserve quantification may prove more suitable for this population.

Relation of a Socioeconomic Index with Cognitive Function and Neuroimaging in Hypertensive Individuals. - Paradela, Regina Silva; Ferreira, Naomi Vidal; Nucci, Mariana Penteado; Cabella, Brenno; Martino, Luiza Menoni; Torres, Laura Aló; Costa, Danielle Irigoyen da; Consolim-Colombo, Fernanda Marciano; Suemoto, Claudia Kimie; Irigoyen, Maria Claudia (J Alzheimers Dis, 2021)
BACKGROUND: Socioeconomic factors are important contributors to brain health. However, data from developing countries (where social inequalities are the most prominent) are still scarce, particularly about hypertensive individuals. OBJECTIVE: To evaluate the relationship between socioeconomic index, cognitive function, and cortical brain volume, as well as determine whether white matter hyperintensities are mediators of the association of the socioeconomic index with cognitive function in hypertensive individuals. METHODS: We assessed 92 hypertensive participants (mean age = 58±8.6 years, 65.2%female). Cognitive evaluation and neuroimaging were performed and clinical and sociodemographic data were collected using questionnaires. A socioeconomic index was created using education, income, occupation (manual or non-manual work), and race. The associations of the socioeconomic index with cognitive performance and brain volume were investigated using linear regression models adjusted for age, sex, time of hypertension since diagnosis, and comorbidities. A causal mediation analysis was also conducted. RESULTS: Better socioeconomic status was associated with better visuospatial ability, executive function, and global cognition. We found associations between a better socioeconomic index and a higher parietal lobe volume. White matter hyperintensities were also not mediators in the relationship between the socioeconomic index and cognitive performance. CONCLUSION: Socioeconomic disadvantages are associated with worse cognitive performance and brain volume in individuals with hypertension.

Relation of Literacy and Music Literacy to Dementia in Older Black and White Brazilians. - Capuano, Ana W; Wilson, Robert S; Leurgans, Sue E; Sampaio, Carolina; Farfel, Jose M; Barnes, Lisa L; Bennett, David A (J Alzheimers Dis, 2021)
BACKGROUND: Literacy is more consistently reported than education as protective against dementia in developing regions. OBJECTIVE: To study the association of verbal literacy, numeracy, and music literacy with dementia in older Black and White Brazilians with a broad spectrum of education. METHODS: We studied 1,818 Black, Mixed-race, and White deceased Brazilians 65 years or older at death (mean = 79.64). Data were retrospectively obtained within 36 hours after death in a face-to-face interview with an informant, usually a family member. Dementia was classified using the Clinical Dementia Rating (CDR) scale. Three forms of literacy were ascertained: verbal literacy (10 questions: reading and writing), numeracy (3 questions: multiplication, percentages, and use of a calculator), and music literacy (1 question: reading music). Black (11%) and Mixed-race (23%) older adults were combined in analyses. Models adjusted for age and sex. RESULTS: Dementia was identified in 531 people. Participants had 0 to 25 years of education (median = 4). More literacy was associated with lower odds of dementia (all p≤0.039). Participants that read music had about half the odds of having dementia. Participants in the highest quartile of numeracy and verbal literacy had respectively 27%and 15%lower odds of having dementia compared to the lowest quartile. Literacy was lower in Blacks (p <  0.001, except music p = 0.894) but the effect of literacy on dementia was similar (interaction p >  0.237). In secondary analyses, playing instruments without reading music was not associated with dementia (p = 0.887). CONCLUSION: In a large sample of Brazilians, verbal literacy, numeracy, and music literacy were associated with lower odds of dementia. The effect was similar across races.

Relationships Between Cognition and Neuropathological Tau in Alzheimer's Disease Assessed by 18F Flortaucipir PET. - Devous, Michael D; Fleisher, Adam S; Pontecorvo, Michael J; Lu, Ming; Siderowf, Andrew; Navitsky, Michael; Kennedy, Ian; Southekal, Sudeepti; Harris, Thomas S; Mintun, Mark A (J Alzheimers Dis, 2021)
BACKGROUND: Tau neurofibrillary tangle burden increases with Alzheimer's disease (AD) stage and correlates with degree of cognitive impairment. Tau PET imaging could facilitate understanding the relationship between tau pathology and cognitive impairment. OBJECTIVE: Evaluate the relationship between 18F flortaucipir uptake patterns and cognition across multiple cognitive domains. METHODS: We acquired flortaucipir PET scans in 84 amyloid-positive control, mild cognitive impairment (MCI), and AD subjects. Flortaucipir standardized uptake value ratio (SUVr) values were obtained from a neocortical volume of interest (VOI), a precuneus VOI, and VOIs defined by the correlation between flortaucipir SUVr images and domain-specific cognitive tests. Cognitive assessments included Mini-Mental State Exam (MMSE), Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-cog), and a neuropsychological test battery (i.e., Wechsler Memory Scale-Revised Logical Memory (WMS-R), Trail Making Test, Boston Naming Test, Digit Symbol Substitution Test, Animal List Generation, WMS-R Digit Span, American National Adult Reading Test, Clock Drawing Test, Judgment of Line Orientation, and WMS-R Logical Memory II (Delayed Recall)) and the Functional Activities Questionnaire (FAQ). Correlation analyses compared regional and voxel-wise VOIs to cognitive scores. RESULTS: Subjects included 5 controls, 47 MCI, and 32 AD subjects. Significant correlations were seen between both flortaucipir and florbetapir SUVrs and MMSE, ADAS-Cog, and FAQ. Cognitive impairment was associated with increased flortaucipir uptake in regionally specific patterns consistent with the neuroanatomy underlying specific cognitive tests. CONCLUSION: Flortaucipir SUVr values demonstrated significant inverse correlations with cognitive scores in domain-specific patterns. Findings support the hypothesis that PET imaging of neuropathologic tau deposits may reflect underlying neurodegeneration in AD.

Risk Variants in Three Alzheimer's Disease Genes Show Association with EEG Endophenotypes. - Macedo, Ana; Gómez, Carlos; Rebelo, Miguel Ângelo; Poza, Jesús; Gomes, Iva; Martins, Sandra; Maturana-Candelas, Aarón; Pablo, Víctor Gutiérrez-de; Durães, Luis; Sousa, Patrícia; Figueruelo, Manuel; Rodriguez, Maria; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Dementia due to Alzheimer's disease (AD) is a complex neurodegenerative disorder, which much of heritability remains unexplained. At the clinical level, one of the most common physiological alterations is the slowing of oscillatory brain activity, measurable by electroencephalography (EEG). Relative power (RP) at the conventional frequency bands (i.e., delta, theta, alpha, beta-1, and beta-2) can be considered as AD endophenotypes. OBJECTIVE: The aim of this work is to analyze the association between sixteen genes previously related with AD: APOE, PICALM, CLU, BCHE, CETP, CR1, SLC6A3, GRIN2 β, SORL1, TOMM40, GSK3 β, UNC5C, OPRD1, NAV2, HOMER2, and IL1RAP, and the slowing of the brain activity, assessed by means of RP at the aforementioned frequency bands. METHODS: An Iberian cohort of 45 elderly controls, 45 individuals with mild cognitive impairment, and 109 AD patients in the three stages of the disease was considered. Genomic information and brain activity of each subject were analyzed. RESULTS: The slowing of brain activity was observed in carriers of risk alleles in IL1RAP (rs10212109, rs9823517, rs4687150), UNC5C (rs17024131), and NAV2 (rs1425227, rs862785) genes, regardless of the disease status and situation towards the strongest risk factors: age, sex, and APOE ɛ4 presence. CONCLUSION: Endophenotypes reduce the complexity of the general phenotype and genetic variants with a major effect on those specific traits may be then identified. The found associations in this work are novel and may contribute to the comprehension of AD pathogenesis, each with a different biological role, and influencing multiple factors involved in brain physiology.

Sustained Hippocampal Neural Plasticity Questions the Reproducibility of an Amyloid-β-Induced Alzheimer's Disease Model. - Paulo, Sara L; Ribeiro-Rodrigues, Leonor; Rodrigues, Rui S; Mateus, Joana M; Fonseca-Gomes, João; Soares, Rita; Diógenes, Maria J; Solá, Susana; Sebastião, Ana M; Ribeiro, Filipa F; Xapelli, Sara (J Alzheimers Dis, 2021)
BACKGROUND: The use of Alzheimer's disease (AD) models obtained by intracerebral infusion of amyloid-β (Aβ) has been increasingly reported in recent years. Nonetheless, these models may present important challenges. OBJECTIVE: We have focused on canonical mechanisms of hippocampal-related neural plasticity to characterize a rat model obtained by an intracerebroventricular (icv) injection of soluble amyloid-β42 (Aβ42). METHODS: Animal behavior was evaluated in the elevated plus maze, Y-Maze spontaneous or forced alternation, Morris water maze, and open field, starting 2 weeks post-Aβ42 infusion. Hippocampal neurogenesis was assessed 3 weeks after Aβ42 injection. Aβ deposition, tropomyosin receptor kinase B levels, and neuroinflammation were appraised at 3 and 14 days post-Aβ42 administration. RESULTS: We found that immature neuronal dendritic morphology was abnormally enhanced, but proliferation and neuronal differentiation in the dentate gyrus was conserved one month after Aβ42 injection. Surprisingly, animal behavior did not reveal changes in cognitive performance nor in locomotor and anxious-related activity. Brain-derived neurotrophic factor related-signaling was also unchanged at 3 and 14 days post-Aβ icv injection. Likewise, astrocytic and microglial markers of neuroinflammation in the hippocampus were unaltered in these time points. CONCLUSION: Taken together, our data emphasize a high variability and lack of behavioral reproducibility associated with these Aβ injection-based models, as well as the need for its further optimization, aiming at addressing the gap between preclinical AD models and the human disorder.

tRNA-Derived Fragments in Alzheimer's Disease: Implications for New Disease Biomarkers and Neuropathological Mechanisms. - Wu, Wenzhe; Lee, Inhan; Spratt, Heidi; Fang, Xiang; Bao, Xiaoyong (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia caused by irreversible neurodegeneration, with the onset mechanisms elusive. tRNA-derived RNA fragments (tRFs), a recently discovered family of small non-coding RNAs (sncRNAs), have been found to associate with many human diseases, including infectious, metabolic, and neurological diseases. However, whether tRFs play a role in human AD development is not known. OBJECTIVE: This study aimed to explore whether tRFs are involved in human AD. METHODS: Thirty-four postmortem human hippocampus samples were used. The expression of Drosha, Dicer, and angiogenin (ANG), three ribonucleases responsible for the biogenesis of sncRNAs, was determined by qRT-PCR and western blot. The tRFs in the hippocampus was detected by qRT-PCR or northern blot. We also used qRT-PCR to quantify NOP2/Sun RNA methyltransferase 2 (NSun2) and polyadenylation factor I subunit 1 (CLP1), two tRNA modification enzymes. RESULTS: tRFs derived from a subset of tRNAs are significantly altered in the hippocampus of AD patients. The expression change of some tRFs showed age- and disease stage-dependent. ANG is significantly enhanced in AD, suggesting its role in inducing tRFs in AD. The expression of NSun2 in AD patients younger than 65 was significantly decreased. According to a previous report supporting NSun2-mediated tRNA methylation modification making tRNA less susceptible to ANG-mediated cleavage, our results suggested that the decrease in NSun2 may make tRNAs less methylated and subsequently enhanced tRF production from ANG-mediated tRNA cleavage. CONCLUSION: Our studies demonstrated for the first time the involvement of tRFs in human AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Blotting, Northern; Case-Control Studies; Hippocampus; Humans; Polymerase Chain Reaction; RNA, Small Untranslated; RNA, Transfer

Urban Air Pollution Nanoparticles from Los Angeles: Recently Decreased Neurotoxicity. - Zhang, Hongqiao; D'Agostino, Carla; Forman, Henry Jay; Cacciottolo, Mafalda; Thorwald, Max; Mack, William J; Liu, Qinghai; Shkirkova, Kristina; Lamorie-Foote, Krista; Sioutas, Constantinos; Pirhadi, Milad; Mack, Wendy Jean; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution is widely associated with accelerated cognitive decline at later ages and risk of Alzheimer's disease (AD). Correspondingly, rodent models demonstrate the neurotoxicity of ambient air pollution and its components. Our studies with nano-sized particulate matter (nPM) from urban Los Angeles collected since 2009 have shown pro-amyloidogenic and pro-inflammatory responses. However, recent batches of nPM have diminished induction of the glutamate receptor GluA1 subunit, Iba1, TNFα, Aβ42 peptide, and white matter damage. The same methods, materials, and mouse genotypes were used throughout. OBJECTIVE: Expand the nPM batch comparisons and evaluate archived brain samples to identify the earliest change in nPM potency. METHODS: Batches of nPM were analyzed by in vitro cell assays for NF-κB and Nrf2 induction for comparison with in vivo responses of mouse brain regions from mice exposed to these batches, analyzed by PCR and western blot. RESULTS: Five older nPM batches (2009-2017) and four recent nPM batches (2018, 2019) for NF-κB and Nrf2 induction showed declines in nPM potency after 2017 that paralleled declines of in vivo activity from independent exposures in different years. CONCLUSION: Transcription-based in vitro assays of nPM corresponded to the loss of in vivo potency for inflammatory and oxidative responses. These recent decreases of nPM neurotoxicity give a rationale for evaluating possible benefits to the risk of dementia and stroke in Los Angeles populations.

Visual Memory Deficits in Middle-Aged APOEɛ4 Homozygotes Detected Using Unsupervised Cognitive Assessments. - Lim, Yen Ying; Pase, Matthew P; Buckley, Rachel F; Yassi, Nawaf; Bransby, Lisa; Fowler, Christopher; Laws, Simon M; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2021)
BACKGROUND: The apolipoprotein E (APOE) ɛ4 allele is associated with dose-response effects on cognitive dysfunction and dementia risk in older adults. However, its effects on cognition in middle-aged adults remains unclear. OBJECTIVE: We examined effects of ɛ4 heterozygosity and homozygosity on objective and subjective cognition in middle-aged adults enrolled in the Healthy Brain Project (HBP) and in older adults from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. METHODS: HBP participants (1,000 non-carriers; 450 ɛ4 heterozygotes; 50 ɛ4 homozygotes) completed unsupervised assessments of the Cogstate Brief Battery (CBB), ratings of subjective cognitive function and provided a saliva sample. AIBL cognitively normal participants (650 non-carriers; 204 ɛ4 heterozygotes; 31 ɛ4 homozygotes) completed in-person assessments of the CBB, ratings of subjective cognitive function and provided a blood sample. RESULTS: Greater memory impairment was observed in middle-aged ɛ4 homozygotes compared with ɛ4 heterozygotes and non-carriers. When data from middle-aged (HBP) and older (AIBL) adults were pooled, the effect of ɛ4 homozygosity and memory impairment increased with age. In both middle-aged and older adults, ɛ4 heterozygotes did not differ from non-carriers on any measure of objective or subjective cognition. CONCLUSION: Memory impairment in ɛ4 homozygotes is evident in adults aged 50-60 years, and this can be detected through unsupervised cognitive assessments. The effect of ɛ4 homozygosity increases with older age. APOEɛ4 homozygosity has a negative impact on memory as early as midlife, but due to the subtle magnitude of effect, our findings support the necessity of online platforms in large cohorts to assess these complex relationships.

An Active Lifestyle Is Associated with Better Cognitive Function Over Time in APOE ɛ4 Non-Carriers. - Fernández-Matarrubia, Marta; Goni, Leticia; Rognoni, Teresa; Razquin, Cristina; Fernández-Lázaro, César Ignacio; Bes-Rastrollo, Maira; Martínez-González, Miguel Ángel; Toledo, Estefanía (J Alzheimers Dis, 2020)
BACKGROUND: Available evidence on the association of physical activity (PA) or sedentary behavior with cognitive decline is inconclusive. OBJECTIVE: To assess the association between an active lifestyle score and leisure-time physical activity (LTPA) and changes in cognitive function in the Seguimiento Universidad de Navarra (SUN) prospective cohort. METHODS: Cognitive function was evaluated in a subsample of 806 participants of the SUN cohort study using the validated Telephone Interview for Cognitive Status-modified (STICS-m) questionnaire at baseline and after 6 years. LTPA was evaluated with a previously validated 17-item self-administered questionnaire and with information on sedentary lifestyles. We also calculated a multidimensional 8-item PA score. Multivariable linear regression analysis evaluated the association between PA and changes in cognitive function and its interaction by APOE genotype. RESULTS: Mean age of participants was 66 (SD 5.3) years and 69.7% were male. When stratifying by APOE variants, no significant associations between the active lifestyle score or LTPA and changes in cognitive performance over time were found among APOE ɛ4 carriers. However, we observed that a higher adherence to an active lifestyle (high versus low PA score β= 0.76 95% CI 0.15,1.36; p trend = 0.011) and a high LTPA (Q4 versus Q1 β= 0.63; 95% CI -0.01,1.26; p trend = 0.030) were associated with more favorable changes in cognitive function over time among APOE ɛ4 non-carriers with statistically significant interactions in both cases (p for interaction = 0.042 for PA score, and p = 0.039 for LTPA). CONCLUSION: The results of the present study suggest that an active lifestyle is associated with a better status of cognitive function over time only among APOE ɛ4 non-carriers.

Is Alzheimer's Disease a Liver Disease of the Brain? - Bassendine, Margaret F; Taylor-Robinson, Simon D; Fertleman, Michael; Khan, Michael; Neely, Dermot (J Alzheimers Dis, 2020)
Clinical specialization is not only a force for progress, but it has also led to the fragmentation of medical knowledge. The focus of research in the field of Alzheimer's disease (AD) is neurobiology, while hepatologists focus on liver diseases and lipid specialists on atherosclerosis. This article on AD focuses on the role of the liver and lipid homeostasis in the development of AD. Amyloid-β (Aβ) deposits accumulate as plaques in the brain of an AD patient long before cognitive decline is evident. Aβ generation is a normal physiological process; the steady-state level of Aβ in the brain is determined by balance between Aβ production and its clearance. We present evidence suggesting that the liver is the origin of brain Aβ deposits and that it is involved in peripheral clearance of circulating Aβ in the blood. Hence the liver could be targeted to decrease Aβ production or increase peripheral clearance.

Brain Volume Predicts Behavioral and Psychological Symptoms in Alzheimer's Disease. - Boublay, Nawele; Bouet, Romain; Dorey, Jean-Michel; Padovan, Catherine; Makaroff, Zaza; Federico, Denis; Gallice, Isabelle; Barrellon, Marie-Odile; Robert, Philippe; Moreaud, Olivier; Rouch, Isabelle; Krolak-Salmon, Pierre (J Alzheimers Dis, 2020)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are frequent and troublesome for patients and caregivers. Considering possible preventive approaches, a better understanding of underlying neural correlates of BPSD is crucial. OBJECTIVE: The aim is to assess whether brain regional volume predicts behavioral changes in mild AD. METHODS: This work took part from the PACO study, a multicenter and prospective study that included 252 patients with mild AD from 2009 to 2014. Fifty-three patients were retained. Forty healthy matched control subjects from the ADNI cohort were included as controls. Voxel-based morphometry analysis was conducted to assess regional brain volume using baseline MRI scans as a predictor of future behavioral changes over a period of 18 months. Behavior was assessed at baseline and longitudinally at 6-month intervals using the shortened form of the Neuropsychiatric Inventory (NPI). RESULTS: The volume of 23 brain structures in frontal, temporal, parietal, occipital, subcortical regions and cerebellum predicted the evolution of NPI scores. Frontal volume was the most powerful predictor with frontal gyri, anterior cingulate cortex, and orbital gyri being particularly involved. CONCLUSION: To our knowledge, this is the first study assessing regional brain volumes as predictors of behavioral changes considered at earlier stages of AD. Up to 23 brain structures were associated with an increased risk of developing BPSD. Frontal lobe volume was the strongest predictor of future evolution of NPI. The involvement of multiple structures in the prediction of behavior suggests a role of the main large-scale networks involved in cognition.

Cerebrospinal Fluid Metals and the Association with Cerebral Small Vessel Disease. - Shams, Mana; Martola, Juha; Charidimou, Andreas; Granberg, Tobias; Ferreira, Daniel; Westman, Eric; Wintermark, Max; Iv, Michael; Larvie, Mykol; Kristoffersen Wiberg, Maria; Kaijser, Magnus; Forsgard, Niklas; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Brain metal homeostasis is essential for brain health, and deregulation can result in oxidative stress on the brain parenchyma. OBJECTIVE: Our objective in this study was to focus on two hemorrhagic MRI manifestations of small vessel disease [cerebral microbleeds (CMBs) and cortical superficial siderosis (cSS)] and associations with cerebrospinal fluid (CSF) iron levels. In addition, we aimed to analyze CSF biomarkers for dementia and associations with CSF metal levels. METHODS: This is a cross-sectional study of 196 patients who underwent memory clinic investigation, including brain MRI. CSF was collected and analyzed for metals, amyloid-β (Aβ) 42, total tau (T-tau), and phosphorylated tau (P-tau), and CSF/serum albumin ratios. Statistical analyses were performed using generalized linear models. RESULTS: No significant difference was found between CSF metal levels across diagnostic groups. Higher iron and copper levels were associated with higher CSF levels of Aβ42, T-tau, P-tau, and CSF/serum albumin ratios (p < 0.05). Zinc was associated with higher CSF/serum albumin ratios. There was no significant association between CMBs or cSS and CSF iron levels. An increase in CSF iron with the number of CMBs was seen in APOEɛ4 carriers. CONCLUSION: CSF iron levels are elevated with cerebral microbleeds in APOEɛ4 carriers, with no other association seen with hemorrhagic markers of small vessel disease. The association of elevated CSF iron and copper with tau could represent findings of increased neurodegeneration in these patients.

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study. - Martín-Jiménez, Paloma; Muñoz-García, Mariana I; Seoane, David; Roca-Rodríguez, Lucas; García-Reyne, Ana; Lalueza, Antonio; Maestro, Guillermo; Folgueira, Dolores; Blanco-Palmero, Víctor A; Herrero-San Martín, Alejandro; Llamas-Velasco, Sara; Pérez-Martínez, David A; et al. (J Alzheimers Dis, 2020)
We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comorbidity in deceased COVID-19 subjects and is associated with differences in care.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Comorbidity; COVID-19; Female; Hospital Mortality; Hospitals; Humans; Male; Middle Aged; Palliative Care; Patient Admission; Retrospective Studies; Spain; Young Adult

A Community-Based Study Identifying Metabolic Biomarkers of Mild Cognitive Impairment and Alzheimer's Disease Using Artificial Intelligence and Machine Learning. - Yilmaz, Ali; Ustun, Ilyas; Ugur, Zafer; Akyol, Sumeyya; Hu, William T; Fiandaca, Massimo S; Mapstone, Mark; Federoff, Howard; Maddens, Michael; Graham, Stewart F (J Alzheimers Dis, 2020)
BACKGROUND: Currently, there is no objective, clinically available tool for the accurate diagnosis of Alzheimer's disease (AD). There is a pressing need for a novel, minimally invasive, cost friendly, and easily accessible tool to diagnose AD, assess disease severity, and prognosticate course. Metabolomics is a promising tool for discovery of new, biologically, and clinically relevant biomarkers for AD detection and classification. OBJECTIVE: Utilizing artificial intelligence and machine learning, we aim to assess whether a panel of metabolites as detected in serum can be used as an objective and clinically feasible tool for the diagnosis of mild cognitive impairment (MCI) and AD. METHODS: Using a community-based sample cohort acquired from different sites across the US, we adopted an approach combining Proton Nuclear Magnetic Resonance Spectroscopy (1H NMR), Liquid Chromatography coupled with Mass Spectrometry (LC-MS). and various machine learning statistical approaches to identify a biomarker panel capable of identifying those patients with AD and MCI from healthy controls. RESULTS: Of the 212 measured metabolites, 5 were identified as optimal to discriminate between controls, and individuals with MCI or AD. Our models performed with AUC values in the range of 0.72-0.76, with the sensitivity and specificity values ranging from 0.75-0.85 and 0.69-0.81, respectively. Univariate and pathway analysis identified lipid metabolism as the most perturbed biochemical pathway in MCI and AD. CONCLUSION: A comprehensive method of acquiring metabolomics data, coupled with machine learning techniques, has identified a strong panel of diagnostic biomarkers capable of identifying individuals with MCI and AD. Further, our data confirm what other groups have reported in that lipid metabolism is significantly perturbed in those individuals suffering with dementia. This work may provide additional insight into AD pathogenesis and encourage more in-depth analysis of the AD lipidome.

Comorbidity of Cerebrovascular and Alzheimer's Disease in Aging. - Xia, Ying; Yassi, Nawaf; Raniga, Parnesh; Bourgeat, Pierrick; Desmond, Patricia; Doecke, James; Ames, David; Laws, Simon M; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph; Maruff, Paul; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrovascular disease often coexists with Alzheimer's disease (AD). While both diseases share common risk factors, their interrelationship remains unclear. Increasing the understanding of how cerebrovascular changes interact with AD is essential to develop therapeutic strategies and refine biomarkers for early diagnosis. OBJECTIVE: We investigate the prevalence and risk factors for the comorbidity of amyloid-β (Aβ) and cerebrovascular disease in the Australian Imaging, Biomarkers and Lifestyle Study of Ageing, and further examine their cross-sectional association. METHODS: A total of 598 participants (422 cognitively normal, 89 with mild cognitive impairment, 87 with AD) underwent positron emission tomography and structural magnetic resonance imaging for assessment of Aβ deposition and cerebrovascular disease. Individuals were categorized based on the comorbidity status of Aβ and cerebrovascular disease (V) as Aβ-V-, Aβ-V+, Aβ+V-, or Aβ+V+. RESULTS: Advancing age was associated with greater likelihood of cerebrovascular disease, high Aβ load and their comorbidity. Apolipoprotein E ɛ4 carriage was only associated with Aβ positivity. Greater total and regional WMH burden were observed in participants with AD. However, no association were observed between Aβ and WMH measures after stratification by clinical classification, suggesting that the observed association between AD and cerebrovascular disease was driven by the common risk factor of age. CONCLUSION: Our observations demonstrate common comorbid condition of Aβ and cerebrovascular disease in later life. While our study did not demonstrate a convincing cross-sectional association between Aβ and WMH burden, future longitudinal studies are required to further confirm this.

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

Costs of Early Stage Alzheimer's Disease in the United States: Cross-Sectional Analysis of a Prospective Cohort Study (GERAS-US)1. - Robinson, Rebecca L; Rentz, Dorene M; Andrews, Jeffrey Scott; Zagar, Anthony; Kim, Yongin; Bruemmer, Valerie; Schwartz, Ronald L; Ye, Wenyu; Fillit, Howard M (J Alzheimers Dis, 2020)
BACKGROUND: Costs associated with early stages of Alzheimer's disease (AD; mild cognitive impairment [MCI] and mild dementia [MILD]) are understudied. OBJECTIVE: To compare costs associated with MCI and MILD due to AD in the United States. METHODS: Data included baseline patient/study partner medical history, healthcare resource utilization, and outcome assessments as part of a prospective cohort study. Direct, indirect, and total societal costs were derived by applying standardized unit costs to resources for the 1-month pre-baseline period (USD2017). Costs/month for MCI and MILD cohorts were compared using analysis of variance models. To strengthen the confidence of diagnosis, amyloid-β (Aβ) tests were included and analyses were replicated stratifying within each cohort by amyloid status [+ /-]. RESULTS: Patients (N = 1327) with MILD versus MCI had higher total societal costs/month ($4243 versus $2816; p < 0.001). These costs were not significantly different within each severity cohort by amyloid status. The largest fraction of overall costs were informal caregiver costs (45.1%) for the MILD cohort, whereas direct medical patient costs were the largest for the MCI cohort (39.0%). Correspondingly, caregiver time spent on basic activities of daily living (ADLs), instrumental ADLs, and supervision time was twice as high for MILD versus MCI (all p < 0.001). CONCLUSION: Early AD poses a financial burden, and despite higher functioning among those with MCI, caregivers were significantly impacted. The major cost driver was the patient's clinical cognitive-functional status and not amyloid status. Differences were primarily due to rising need for caregiver support.

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Dickkopf-1 Overexpression in vitro Nominates Candidate Blood Biomarkers Relating to Alzheimer's Disease Pathology. - Shi, Liu; Winchester, Laura M; Liu, Benjamine Y; Killick, Richard; Ribe, Elena M; Westwood, Sarah; Baird, Alison L; Buckley, Noel J; Hong, Shengjun; Dobricic, Valerija; Kilpert, Fabian; Franke, Andre; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Previous studies suggest that Dickkopf-1 (DKK1), an inhibitor of Wnt signaling, plays a role in amyloid-induced toxicity and hence Alzheimer's disease (AD). However, the effect of DKK1 expression on protein expression, and whether such proteins are altered in disease, is unknown. OBJECTIVE: We aim to test whether DKK1 induced protein signature obtained in vitro were associated with markers of AD pathology as used in the amyloid/tau/neurodegeneration (ATN) framework as well as with clinical outcomes. METHODS: We first overexpressed DKK1 in HEK293A cells and quantified 1,128 proteins in cell lysates using aptamer capture arrays (SomaScan) to obtain a protein signature induced by DKK1. We then used the same assay to measure the DKK1-signature proteins in human plasma in two large cohorts, EMIF (n = 785) and ANM (n = 677). RESULTS: We identified a 100-protein signature induced by DKK1 in vitro. Subsets of proteins, along with age and apolipoprotein E ɛ4 genotype distinguished amyloid pathology (A + T-N-, A+T+N-, A+T-N+, and A+T+N+) from no AD pathology (A-T-N-) with an area under the curve of 0.72, 0.81, 0.88, and 0.85, respectively. Furthermore, we found that some signature proteins (e.g., Complement C3 and albumin) were associated with cognitive score and AD diagnosis in both cohorts. CONCLUSIONS: Our results add further evidence for a role of DKK regulation of Wnt signaling in AD and suggest that DKK1 induced signature proteins obtained in vitro could reflect theATNframework as well as predict disease severity and progression in vivo.

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Epilepsy in Neurodegenerative Dementias: A Clinical, Epidemiological, and EEG Study. - Arnaldi, Dario; Donniaquio, Andrea; Mattioli, Pietro; Massa, Federico; Grazzini, Matteo; Meli, Riccardo; Filippi, Laura; Grisanti, Stefano; Famá, Francesco; Terzaghi, Michele; Girtler, Nicola; Brugnolo, Andrea; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Seizures are common in patients with dementia but precise epidemiologic data of epilepsy in neurodegenerative dementia is lacking. OBJECTIVE: The first aim of the study was to investigate prevalence and clinical characteristics of epilepsy in a large cohort of patients with neurodegenerative dementias. Subsequently, we explored clinical, neuropsychological, and quantitative electroencephalogram (qEEG) data of Alzheimer's disease (AD) patients with epilepsy (AD-EPI) as compared to AD patients without epilepsy (AD-CTR). METHODS: We retrospectively evaluated consecutive patients with a diagnosis of a neurodegenerative dementia and a clinically diagnosed epilepsy that required antiepileptic drugs (AED). All patients underwent baseline comprehensive neuropsychological assessment. A follow-up of at least one year was requested to confirm the dementia diagnosis. In AD patients, qEEG power band analysis was performed. AD-CTR and AD-EPI patients were matched for age, Mini-Mental State Examination score, and gender. RESULTS: Thirty-eight out of 2,054 neurodegenerative dementia patients had epilepsy requiring AED. The prevalence of epilepsy was 1.82% for AD, 1.28% for the behavioral variant of frontotemporal dementia (bvFTD), 2.47% for dementia with Lewy bodies (DLB), and 12% for primary progressive aphasia. Epilepsy were more drug-responsive in AD than in non-AD dementias. Finally, no significant differences were found in neuropsychological and qEEG data between AD-EPI and AD-CTR patients. CONCLUSION: In our cohort, AD, FTD, and DLB dementias have similar prevalence of epilepsy, even if AD patients were more responsive to AED. Moreover, AD-EPI patients did not have significant clinical, neuropsychological qEEG differences compared with AD-CTR patients.

Exploration of Plasma Lipids in Mild Cognitive Impairment due to Alzheimer's Disease. - Bergland, Anne Katrine; Proitsi, Petroula; Kirsebom, Bjørn-Eivind; Soennesyn, Hogne; Hye, Abdul; Larsen, Alf Inge; Xu, Jin; Legido-Quigley, Cristina; Rajendran, Lawrence; Fladby, Tormod; Aarsland, Dag (J Alzheimers Dis, 2020)
BACKGROUND: Lipids have important structural roles in cell membranes and changes to these membrane lipids may influence β- and γ-secretase activities and thus contribute to Alzheimer's disease (AD) pathology. OBJECTIVE: To explore baseline plasma lipid profiling in participants with mild cognitive impairment (MCI) with and without AD pathology. METHODS: We analyzed 261 plasma lipid profiles using reversed phase chromatography mass spectrometry in cerebrospinal fluid amyloid positive (Aβ+) or negative (Aβ-) participants with MCI as compared to controls. Additionally, we analyzed the potential associations of plasma lipid profiles with performance on neuropsychological tests at baseline and after two years. RESULTS: Sphingomyelin (SM) concentrations, particularly, SM(d43:2), were lower in MCI Aβ+ individuals compared to controls. Further, SM(d43:2) was also nominally reduced in MCI Aβ+ individuals compared to MCI Aβ-. No plasma lipids were associated with performance on neuropsychological tests at baseline or between the two time points after correction for multiple testing. CONCLUSION: Reduced plasma concentrations of SM were associated with AD.

Fascicle- and Glucose-Specific Deterioration in White Matter Energy Supply in Alzheimer's Disease. - Roy, Maggie; Rheault, François; Croteau, Etienne; Castellano, Christian-Alexandre; Fortier, Mélanie; St-Pierre, Valérie; Houde, Jean-Christophe; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C; Descoteaux, Maxime (J Alzheimers Dis, 2020)
BACKGROUND: White matter energy supply to oligodendrocytes and the axonal compartment is crucial for normal axonal function. Although gray matter glucose hypometabolism is extensively reported in Alzheimer's disease (AD), glucose and ketones, the brain's two main fuels, are rarely quantified in white matter in AD. OBJECTIVE: Using adual-tracer PET method combined with a fascicle-specific diffusion MRI approach, robust to white matter hyper intensities and crossing fibers, we aimed to quantify both glucose and ketone metabolismin specific white matter fascicles associated with mild cognitive impairment (MCI; n = 51) and AD (n = 13) compared to cognitively healthy age-matched controls (Controls; n = 14). METHODS: Eight white matter fascicles of the limbic lobe and corpus callosum were extracted and analyzed into fascicle profiles of five sections. Glucose (18F-fluorodeoxyglucose) and ketone (11C-acetoacetate) uptake rates, corrected for partial volume effect, were calculated along each fascicle. RESULTS: The only fascicle with significantly lower glucose uptake in AD compared to Controls was the left posterior cingulate segment of the cingulum (-22%; p = 0.016). Non-significantly lower glucose uptake in this fascicle was also observed in MCI. In contrast to glucose, ketone uptake was either unchanged or higher in sections of the fornix and parahippocampal segment of the cingulum in AD. CONCLUSION: To our knowledge, this is the first report of brain fuel uptake calculated along white matter fascicles in humans. Energetic deterioration in white matter in AD appears to be specific to glucose and occurs first in the posterior cingulum.

Flickering Red-Light Stimulus for Promoting Coherent 40 Hz Neural Oscillation: A Feasibility Study. - Sahin, Levent; Figueiro, Mariana G (J Alzheimers Dis, 2020)
BACKGROUND: Coherent 40 Hz (gamma) neural oscillation indicates healthy brain activity and is known to be disrupted in Alzheimer's disease (AD) patients. 40 Hz entrainment by flickering light is known to significantly attenuate AD pathology in mice. OBJECTIVE: To demonstrate the feasibility of using a lighting intervention to promote coherent 40 Hz neural oscillation, improved working memory performance, and reduced subjective sleepiness among a population of healthy young adults. If successful, the intervention could be extended to address cognitive impairment associated with mild cognitive impairment and AD. METHODS: Nine healthy participants (median age 22 years, 5 females) were exposed to one of two lighting conditions per session in a within-subjects counterbalanced manner. The study's two sessions were separated by 1 week. Custom-built light masks provided either a 40 Hz flickering red light (FRL) intervention or a dark control condition (i.e., total darkness, light mask not energized) at participants' eyes. Data were collected 4 times per session: pre-exposure, after 25-min exposure, after 50-min exposure, and post-exposure. Each data collection period included a Karolinska Sleepiness Scale report, an electroencephalogram, and working memory (n-back) auditory performance testing. RESULTS: The FRL intervention induced a significant increase in 40 Hz power and a modest increase in low gamma power. The intervention had no significant impact on working memory performance and subjective sleepiness compared to the control. However, increases in 40 Hz power were significantly correlated with reduced subjective sleepiness. CONCLUSION: The results clearly demonstrate the feasibility of using a flickering light to increase 40 Hz power.

Functional Integrity of Synapses in the Central Nervous System of Cognitively Intact Individuals with High Alzheimer's Disease Neuropathology is Associated with Absence of Synaptic Tau Oligomers. - Singh, Ayush; Allen, Dyron; Fracassi, Anna; Tumurbaatar, Batbayar; Natarajan, Chandramouli; Scaduto, Pietro; Woltjer, Randy; Kayed, Rakez; Limon, Agenor; Krishnan, Balaji; Taglialatela, Giulio (J Alzheimers Dis, 2020)
BACKGROUND: Certain individuals, here referred to as Non-Demented with Alzheimer Neuropathology (NDAN), do not show overt neurodegeneration (N - ) and remain cognitively intact despite the presence of plaques (A+) and tangles (T+) that would normally be consistent with fully symptomatic Alzheimer's disease (AD). OBJECTIVE: The existence of NDAN (A + T +N - ) subjects suggests that the human brain utilizes intrinsic mechanisms that can naturally evade cognitive decline normally associated with the symptomatic stages of AD (A + T +N +). Deciphering the underlying mechanisms would prove relevant to develop complementing therapeutics to prevent progression of AD-related cognitive decline. METHODS: Previously, we have reported that NDAN present with preserved neurogenesis and synaptic integrity paralleled by absence of amyloid oligomers at synapses. Using postmortem brain samples from age-matched control subjects, demented AD patients and NDAN individuals, we performed immunofluorescence, western blots, micro transplantation of synaptic membranes in Xenopus oocytes followed by twin electrode voltage clamp electrophysiology and fluorescence assisted single synaptosome-long term potentiation studies. RESULTS: We report decreased tau oligomers at synapses in the brains of NDAN subjects. Furthermore, using novel approaches we report, for the first time, that such absence of tau oligomers at synapses is associated with synaptic functional integrity in NDAN subjects as compared to demented AD patients. CONCLUSION: Overall, these results give further credence to tau oligomers as primary actors of synaptic destruction underscoring cognitive demise in AD and support their targeting as a viable therapeutic strategy for AD and related tauopathies.

Gait Disturbances are Associated with Increased Cognitive Impairment and Cerebrospinal Fluid Tau Levels in a Memory Clinic Cohort. - Muurling, Marijn; Rhodius-Meester, Hanneke F M; Pärkkä, Juha; van Gils, Mark; Frederiksen, Kristian S; Bruun, Marie; Hasselbalch, Steen G; Soininen, Hilkka; Herukka, Sanna-Kaisa; Hallikainen, Merja; Teunissen, Charlotte E; Visser, Pieter Jelle; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Gait analysis with accelerometers is a relatively inexpensive and easy to use method to potentially support clinical diagnoses of Alzheimer's disease and other dementias. It is not clear, however, which gait features are most informative and how these measures relate to Alzheimer's disease pathology. OBJECTIVE: In this study, we tested if calculated features of gait 1) differ between cognitively normal subjects (CN), mild cognitive impairment (MCI) patients, and dementia patients, 2) are correlated with cerebrospinal fluid (CSF) biomarkers related to Alzheimer's disease, and 3) predict cognitive decline. METHODS: Gait was measured using tri-axial accelerometers attached to the fifth lumbar vertebra (L5) in 58 CN, 58 MCI, and 26 dementia participants, while performing a walk and dual task. Ten gait features were calculated from the vertical L5 accelerations, following principal component analysis clustered in four domains, namely pace, rhythm, time variability, and length variability. Cognitive decline over time was measured using MMSE, and CSF biomarkers were available in a sub-group. RESULTS: Linear mixed models showed that dementia patients had lower pace scores than MCI patients and CN subjects (p < 0.05). In addition, we found associations between the rhythm domain and CSF-tau, especially in the dual task. Gait was not associated with CSF Aβ42 levels and cognitive decline over time as measured with the MMSE. CONCLUSION: These findings suggest that gait-particularly measures related to pace and rhythm-are altered in dementia and have a direct link with measures of neurodegeneration.

Influence of Comorbidity of Cerebrovascular Disease and Amyloid-β on Alzheimer's Disease. - Yassi, Nawaf; Hilal, Saima; Xia, Ying; Lim, Yen Ying; Watson, Rosie; Kuijf, Hugo; Fowler, Christopher; Yates, Paul; Maruff, Paul; Martins, Ralph; Ames, David; Chen, Christopher; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Quantifying the contribution of cerebrovascular disease to the clinical and pathological profile of Alzheimer's disease is challenging. OBJECTIVE: We aimed to determine the influence of cerebrovascular disease, amyloid-β (Aβ), and their comorbidity on cognitive decline, hippocampal atrophy, and Aβ deposition, by evaluating data from the Australian Imaging, Biomarker and Lifestyle Study of Ageing. METHODS: Two-hundred and eighteen participants underwent Aβ PET, MRI, and cognitive assessment at 18-month intervals for up to 90 months. Aβ status was determined on baseline PET. Participants were also classified as V + on baseline MRI if they had≥1 large cortical infarcts, subcortical infarcts, or cortical cerebral microinfarcts; or white matter hyperintensity volume greater than the 90th percentile of healthy controls. Linear mixed models were conducted comparing slopes of change in cognition, hippocampal volume, and Aβ load between the four resultant groups. RESULTS: Mean age at baseline was 74 years (range 59-96). One-hundred and fifteen participants were cognitively normal, 54 had mild cognitive impairment, and 49 had Alzheimer's disease. Compared to the Aβ-/V- group, the Aβ+/V- and Aβ+/V+groups showed significantly faster cognitive decline and hippocampal atrophy over 90 months. V + status was associated with greater cognitive decline (Cohen's d = 0.85, p < 0.001) and hippocampal atrophy (d = 2.05, p < 0.001) in the Aβ+group but not in the Aβ- group. V + status was not associated with Aβ accumulation in any group. CONCLUSION: Comorbidity of cerebrovascular disease and Aβ was associated with cognitive decline and neurodegeneration. Cerebrovascular disease was not associated with the rate of Aβ accumulation.

Neurobiology of COVID-19. - Fotuhi, Majid; Mian, Ali; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2020)
Anosmia, stroke, paralysis, cranial nerve deficits, encephalopathy, delirium, meningitis, and seizures are some of the neurological complications in patients with coronavirus disease-19 (COVID-19) which is caused by acute respiratory syndrome coronavirus 2 (SARS-Cov2). There remains a challenge to determine the extent to which neurological abnormalities in COVID-19 are caused by SARS-Cov2 itself, the exaggerated cytokine response it triggers, and/or the resulting hypercoagulapathy and formation of blood clots in blood vessels throughout the body and the brain. In this article, we review the reports that address neurological manifestations in patients with COVID-19 who may present with acute neurological symptoms (e.g., stroke), even without typical respiratory symptoms such as fever, cough, or shortness of breath. Next, we discuss the different neurobiological processes and mechanisms that may underlie the link between SARS-Cov2 and COVID-19 in the brain, cranial nerves, peripheral nerves, and muscles. Finally, we propose a basic "NeuroCovid" classification scheme that integrates these concepts and highlights some of the short-term challenges for the practice of neurology today and the long-term sequalae of COVID-19 such as depression, OCD, insomnia, cognitive decline, accelerated aging, Parkinson's disease, or Alzheimer's disease in the future. In doing so, we intend to provide a basis from which to build on future hypotheses and investigations regarding SARS-Cov2 and the nervous system.
Keywords: Betacoronavirus; Brain; Coronavirus Infections; COVID-19; Humans; Inflammation Mediators; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2

Neuroimaging in Vascular Cognitive Impairment and Dementia: A Systematic Review. - Frantellizzi, Viviana; Pani, Arianna; Ricci, Maria; Locuratolo, Nicoletta; Fattapposta, Francesco; De Vincentis, Giuseppe (J Alzheimers Dis, 2020)
Cerebrovascular diseases are well established causes of cognitive impairment. Different etiologic entities, such as vascular dementia (VaD), vascular cognitive impairment, subcortical (ischemic) VaD, and vascular cognitive disorder, are included in the umbrella definition of vascular cognitive impairment and dementia (VCID). Because of the variability of VCID clinical presentation, there is no agreement on criteria defining the neuropathological threshold of this disorder. In fact, VCID is characterized by cerebral hemodynamic alteration which ranges from decreased cerebral blood flow to small vessels disease and involves a multifactorial process that leads to demyelination and gliosis, including blood-brain barrier disruption, hypoxia, and hypoperfusion, oxidative stress, neuroinflammation and alteration on neurovascular unit coupling, cerebral microbleeds, or superficial siderosis. Numerous criteria for the definition of VaD have been described: the National Institute of Neurological Disorders and Stroke Association Internationale pour Recherche'-et-l'Enseignement en Neurosciences criteria, the State of California Alzheimer's Disease Diagnostic and Treatment Centers criteria, DSM-V criteria, the Diagnostic Criteria for Vascular Cognitive Disorders (a VASCOG Statement), and Vascular Impairment of Cognition Classification Consensus Study. Neuroimaging is fundamental for definition and diagnosis of VCID and should be used to assess the extent, location, and type of vascular lesions. MRI is the most sensible technique, especially if used according to standardized protocols, even if CT plays an important role in several conditions. Functional neuroimaging, in particular functional MRI and PET, may facilitate differential diagnosis among different forms of dementia. This systematic review aims to explore the state of the art and future perspective of non-invasive diagnostics of VCID.

New BACE1 Chimeric Peptide Inhibitors Selectively Prevent AβPPβ Cleavage Decreasing Amyloid-β Production and Accumulation in Alzheimer's Disease Models. - Resende, Rosa; Ferreira-Marques, Marisa; Moreira, Patrícia; Coimbra, Judite R M; Baptista, Salete J; Isidoro, Ciro; Salvador, Jorge A R; Dinis, Teresa C P; Pereira, Cláudia F; Santos, Armanda E (J Alzheimers Dis, 2020)
BACKGROUND: A disease-modifying therapy for Alzheimer's disease (AD) is still an unmet clinical need. The formation of amyloid-β (Aβ) requires the initial cleavage of the amyloid-β protein precursor (AβPP) by BACE1 (beta-site AβPP cleaving enzyme 1), which is a prime therapeutic target for AD. OBJECTIVE: We aimed to design and develop a selective BACE1 inhibitor suitable to AD treatment. METHODS: The new BACE1 inhibitors consist on a chimeric peptide including a sequence related to the human Swedish mutant form of AβPP (AβPPswe) conjugated with the TAT carrier that facilitates cell membrane permeation and the crossing of the blood-brain barrier. Additionally to the chimeric peptide in the L-form, we developed a D-retro in verso chimeric peptide. The latter strategy, never used with BACE1 inhibitors, is considered to favor a significantly higher half-life and lower immunogenicity. RESULTS: We found that both chimeric peptides inhibit recombinant BACE1 activity and decrease Aβ40/42 production in Neuro-2a (N2A) cells expressing AβPPswe without inducing cytotoxicity. The intraperitoneal administration of these peptides to 3xTg-AD mice decreased plasma and brain Aβ40/42 levels, as well as brain soluble AβPPβ production. Also, a reduction of insoluble Aβ was observed in the brain after chronic treatment. Noteworthy, the chimeric peptides selectively inhibited the AβPPβ cleavage relatively to the proteolysis of other BACE1 substrates such as close homologue of L1 (CHL1) and seizure-related gene 6 (SEZ6). CONCLUSIONS: Overall these new BACE1 chimeric peptideshold promising potential as a selective disease-modifying therapy for AD.

Normal Pressure Hydrocephalus in Down Syndrome: The Report of Two Cases. - Marano, Massimo; Pompucci, Angelo; Motolese, Francesco; Rossi, Mariagrazia; Coletta, Ernesto; Di Lazzaro, Vincenzo; Fasano, Alfonso; Petrella, Gianpaolo (J Alzheimers Dis, 2020)
Down syndrome (DS) is the most common cause of intellectual disability in infants and has a well-known relationship with the Alzheimer's disease. The association between DS and the other pathologies of senescence, such as normal pressure hydrocephalus (NPH), has been poorly investigated. This series included two DS patients with NPH. In both cases, NPH symptoms were initially misdiagnosed as DS associated senescence. Patients were treated with ventricular-peritoneal shunt, showing a sustained improvement (1 and 4 years of follow-up). To our knowledge, this is the first description of the occurrence of NPH in adult patients with DS and surgical outcomes.

Older Patients with Alzheimer's Disease-Related Cortical Atrophy Who Develop Post-Operative Delirium May Be at Increased Risk of Long-Term Cognitive Decline After Surgery. - Racine, Annie M; Touroutoglou, Alexandra; Abrantes, Tatiana; Wong, Bonnie; Fong, Tamara G; Cavallari, Michele; Travison, Thomas G; Gou, Yun; Marcantonio, Edward R; Alsop, David C; Jones, Richard N; Inouye, Sharon K; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Older surgical patients with Alzheimer's disease (AD) dementia and delirium are at increased risk for accelerated long-term cognitive decline. OBJECTIVE: Investigate associations between a probabilistic marker of preclinical AD, delirium, and long-term cognitive decline. METHODS: The Successful Aging after Elective Surgery cohort includes older adults (≥70 years) without dementia who underwent elective surgery. 140 patients underwent preoperative magnetic resonance imaging and had≥6 months cognitive follow-up. Cortical thickness was measured in 'AD-Signature' regions. Delirium was evaluated each postoperative day by the Confusion Assessment Method. Cognitive performance was assessed using a detailed neuropsychological battery at baseline; months 1, 2, and 6; and every 6 months thereafter until 36 months. Using either a General Cognitive Performance composite (GCP) or individual test scores as outcomes, we performed linear mixed effects models to examine main effects of AD-signature atrophy and the interaction of AD-signature atrophy and delirium on slopes of cognitive change from post-operative months 2-36. RESULTS: Reduced baseline AD-signature cortical thickness was associated with greater 36-month cognitive decline in GCP (standardized beta coefficient, β = -0.030, 95% confidence interval [-0.060, -0.001]). Patients who developed delirium who also had thinner AD signature cortex showed greater decline on a verbal learning test (β = -0.100 [-0.192, -0.007]). CONCLUSION: Patients with the greatest baseline AD-related cortical atrophy who develop delirium after elective surgery appear to experience the greatest long-term cognitive decline. Thus, atrophy suggestive of preclinical AD and the development of delirium may be high-risk indicators for long-term cognitive decline following surgery.

Potential for Digital Monitoring to Enhance Wellbeing at Home for People with Mild Dementia and Their Family Carers. - Fowler-Davis, Sally; Barnett, Deborah; Kelley, John; Curtis, David (J Alzheimers Dis, 2020)
Digital technologies have the potential to assist people with dementia to monitor day to day activities and mitigate the risks of living independently. This purposive pilot study surveyed participants for frailty, wellbeing, and perceived carer burden using the 3Rings™ digital plug. 30 paired participants used the digital device for four months. People with dementia reported a decline in wellbeing and increased frailty. Family carers reported a decline in wellbeing but 18 reported a reduction in burden. The use of digital monitoring by family carers demonstrated a reduction in their perceived burden and the device was acceptable to people with mild dementia living alone.

Quantitative Mass Spectrometric Assay of Whole and CNBr-Cleaved Amyloid-β Peptides in Human Brain. - Furman, Ran; Ng, Sharon C W; Komatsu, Hiroaki; Axelsen, Paul H (J Alzheimers Dis, 2020)
Various amyloid-β (Aβ) peptides accumulate in brain in Alzheimer's disease, and the amounts of specific peptide variants may have pathological significance. The quantitative determination of these variants is challenging because losses inevitably occur during tissue processing and analysis. This report describes the use of stable-isotope-labeled Aβ peptides as internal standards for quantitative mass spectrometric assays, and the use of cyanogen bromide (CNBr) to remove C-terminal residues beyond Met35. The removal of residues beyond Met35 reduces losses due to aggregation, and facilitates the detection of post-translationally modified Aβ peptides. Results from 8 human brain samples suggest that the tissue concentrations of the 42-residue Aβ peptide tend to be similar in different patients. Concentrations of the 40-residue Aβ peptide are more variable, and may be greater or lesser than the 42-residue peptide. The concentration of the CNBr cleavage product closely matches the sum of the 40-residue and 42-residue peptide concentrations, indicating that these two Aβ peptides account for most of the C-terminal variants in these patients. CNBr treatment facilitated the detection of post-translational modifications such as pyroglutamyl and hexose-modified Aβ peptides.

Reduced Hippocampal Glutamate and Posterior Cingulate N-Acetyl Aspartate in Mild Cognitive Impairment and Alzheimer's Disease Is Associated with Episodic Memory Performance and White Matter Integrity in the Cingulum: A Pilot Study. - Wong, Dickson; Atiya, Samir; Fogarty, Jennifer; Montero-Odasso, Manuel; Pasternak, Stephen H; Brymer, Chris; Borrie, Michael J; Bartha, Robert (J Alzheimers Dis, 2020)
Identification of biological changes underlying the early symptoms of Alzheimer's disease (AD) will help to identify and stage individuals prior to symptom onset. The limbic system, which supports episodic memory and is impaired early in AD, is a primary target. In this study, brain metabolism and microstructure evaluated by high field (7 Tesla) proton magnetic resonance spectroscopy (1H-MRS) and diffusion tensor imaging (DTI) were evaluated in the limbic system of eight individuals with mild cognitive impairment (MCI), nine with AD, and sixteen normal elderly controls (NEC). Left hippocampal glutamate and posterior cingulate N-acetyl aspartate concentrations were reduced in MCI and AD compared to NEC. Differences in DTI metrics indicated volume and white matter loss along the cingulum in AD compared to NEC. Metabolic and microstructural changes were associated with episodic memory performance assessed using Craft Story 21 Recall and Benson Complex Figure Copy. The current study suggests that metabolite concentrations measured using 1H-MRS may provide insight into the underlying metabolic and microstructural processes of episodic memory impairment.

The Rhythmicity of Clock Genes is Disrupted in the Choroid Plexus of the APP/PS1 Mouse Model of Alzheimer's Disease. - Furtado, André; Astaburuaga, Rosario; Costa, Ana; Duarte, Ana C; Gonçalves, Isabel; Cipolla-Neto, José; Lemos, Manuel C; Carro, Eva; Relógio, Angela; Santos, Cecília R A; Quintela, Telma (J Alzheimers Dis, 2020)
BACKGROUND: The choroid plexus (CP), which constitutes the blood-cerebrospinal fluid barrier, was recently identified as an important component of the circadian clock system. OBJECTIVE: The fact that circadian rhythm disruption is closely associated to Alzheimer's disease (AD) led us to investigate whether AD pathology can contribute to disturbances of the circadian clock in the CP. METHODS: For this purpose, we evaluated the expression of core-clock genes at different time points, in 6- and 12-month-old female and male APP/PS1 mouse models of AD. In addition, we also assessed the effect of melatonin pre-treatment in vitro before amyloid-β stimulus in the daily pattern of brain and muscle Arnt-like protein 1 (Bmal1) expression. RESULTS: Our results showed a dysregulation of circadian rhythmicity of Bmal1 expression in female and male APP/PS1 transgenic 12-month-old mice and of Period 2 (Per2) expression in male mice. Besides, a significant circadian pattern of Bmal1 occurs in the intermittent melatonin pre-treatment group, showing that melatonin can reset the CP circadian clock. CONCLUSION: These results demonstrated a connection between AD and the disruption of circadian rhythm in the CP, representing an attractive target for disease prevention and/or treatment.

Role of Executive Functions in the Conversion from Mild Cognitive Impairment to Dementia. - Junquera Fernández, Almudena; García-Zamora, Estefanía; Olazarán Rodríguez, Javier; Parra Rodríguez, Mario A; Fernández-Guinea, Sara (J Alzheimers Dis, 2020)
BACKGROUND: Recent research pointed to executive dysfunction as a potential early predictor of the progression of mild cognitive impairment (MCI)-dementia in Alzheimer's clinical syndrome (ACS). Such cognitive impairments account for functional impairments in instrumental activities of daily living (IADL). OBJECTIVE: The present study analyzes the contributions of executive functions to predict MCI-dementia progression in ACS. METHODS: We assessed 145 participants, 51 cognitively unimpaired and 94 MCI. The latter were divided using the traditional, memory-based MCI classification (single domain amnestic, multidomain amnestic, and non-amnestic). Eight tests assessing executive functions were administered at baseline and at 1-year follow-up, together with cognitive screening tools and IADL measures. MCI patients were reclassified based on the outcomes from a K-mean cluster analysis which identified three groups. A simple lineal regression model was used to examine whether the classification based on executive functioning could more accurately predict progression to dementia a year later. RESULTS: Clusters based on executive function deficits explained a significant proportion of the variance linked to MCI-dementia conversion, even after controlling for the severity of MCI at baseline (F(1, 68) = 116.25, p = 0.000, R2 = 0.63). Classical memory-based MCI classification failed to predict such a conversion (F(1, 68) = 5.09, p = 0.955, R2 = 0.07). Switching, categories generation, and planning were the executive functions that best distinguished between MCI converters and stable. CONCLUSION: MCI with a dysexecutive phenotype significantly predicts conversion to dementia in ACS a year later. Switching abilities and verbal fluency (categories) must be evaluated in MCI patients to assess risk of future dementia.

Short-Chain Fatty Acids and Lipopolysaccharide as Mediators Between Gut Dysbiosis and Amyloid Pathology in Alzheimer's Disease. - Marizzoni, Moira; Cattaneo, Annamaria; Mirabelli, Peppino; Festari, Cristina; Lopizzo, Nicola; Nicolosi, Valentina; Mombelli, Elisa; Mazzelli, Monica; Luongo, Delia; Naviglio, Daniele; Coppola, Luigi; Salvatore, Marco; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Metagenomic data support an association between certain bacterial strains and Alzheimer's disease (AD), but their functional dynamics remain elusive. OBJECTIVE: To investigate the association between amyloid pathology, bacterial products such as lipopolysaccharide (LPS) and short chain fatty acids (SCFAs: acetate, valerate, butyrate), inflammatory mediators, and markers of endothelial dysfunction in AD. METHODS: Eighty-nine older persons with cognitive performance from normal to dementia underwent florbetapir amyloid PET and blood collection. Brain amyloidosis was measured with standardized uptake value ratio versus cerebellum. Blood levels of LPS were measured by ELISA, SCFAs by mass spectrometry, cytokines by using real-time PCR, and biomarkers of endothelial dysfunction by flow cytometry. We investigated the association between the variables listed above with Spearman's rank test. RESULTS: Amyloid SUVR uptake was positively associated with blood LPS (rho≥0.32, p≤0.006), acetate and valerate (rho≥0.45, p < 0.001), pro-inflammatory cytokines (rho≥0.25, p≤0.012), and biomarkers of endothelial dysfunction (rho≥0.25, p≤0.042). In contrast, it was negatively correlated with butyrate (rho≤-0.42, p≤0.020) and the anti-inflammatory cytokine IL10 (rho≤-0.26, p≤0.009). Endothelial dysfunction was positively associated with pro-inflammatory cytokines, acetate and valerate (rho≥0.25, p≤0.045) and negatively with butyrate and IL10 levels (rho≤-0.25, p≤0.038). CONCLUSION: We report a novel association between gut microbiota-related products and systemic inflammation with brain amyloidosis via endothelial dysfunction, suggesting that SCFAs and LPS represent candidate pathophysiologic links between the gut microbiota and AD pathology.

Sleep-Wake Cycle in Alzheimer's Disease Is Associated with Tau Pathology and Orexin Dysregulation. - Liguori, Claudio; Spanetta, Matteo; Izzi, Francesca; Franchini, Flaminia; Nuccetelli, Marzia; Sancesario, Giulia Maria; Di Santo, Simona; Bernardini, Sergio; Mercuri, Nicola Biagio; Placidi, Fabio (J Alzheimers Dis, 2020)
BACKGROUND: Alzheimer's disease (AD) is the most common form of dementia. It is mainly characterized by a progressive deterioration of cognition, but sleep-wake cycle disturbances frequently occur. Irregular sleep-wake cycle, insomnia, and daytime napping usually occur in patients with AD in the course of the disease. OBJECTIVE: The aim of the present study was to verify the sleep-wake cycle in mild to moderate AD patients compared to controls, and to evaluate the relationship between the sleep-wake cycle impairment and the neuropsychological testing, CSF AD biomarkers, and CSF orexin concentrations. METHODS: Mild to moderate AD patients were enrolled and underwent 14-day actigraphic recording, sleep diary, neuropsychological testing, and CSF biomarkers analysis. All patients were compared to controls. RESULTS: Eighteen AD patients were compared to ten controls. AD patients showed the alteration of the sleep-wake cycle, featured by sleep dysregulation and daytime wake fragmentation, with respect to controls. Considering the correlation analysis, we documented the correlation between tau proteins and orexin CSF levels and sleep-wake cycle dysregulation. CONCLUSION: This study confirmed the dysregulation of sleep-wake cycle in AD patients, as reflected by the daytime wake fragmentation, irregular sleep-wake rhythm, and nocturnal sleep impairment. This sleep-wake cycle disorder correlates with AD neuropathological in vivo features and brain orexin activity. Hence, we suppose that a more marked AD pathology coupled with orexinergic system dysregulation may promote sleep-wake cycle impairment in AD patients.

Structural Brain Changes in Pre-Clinical FTD MAPT Mutation Carriers. - Domínguez-Vivero, Clara; Wu, Liwen; Lee, Seonjoo; Manoochehri, Masood; Cines, Sarah; Brickman, Adam M; Rizvi, Batool; Chesebro, Anthony; Gazes, Yunglin; Fallon, Emer; Lynch, Timothy; Heidebrink, Judith L; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Frontotemporal dementia (FTD) is the second most common cause of early-onset neurodegenerative dementia. Several studies have focused on early imaging changes in FTD patients, but once subjects meet full criteria for the FTD diagnosis, structural changes are generally widespread. OBJECTIVE: This study aims to determine the earliest structural brain changes in asymptomatic MAPT MUTATION carriers. METHODS: This is a cross-sectional multicenter study comparing global and regional brain volume and white matter integrity in a group of MAPT mutation preclinical carriers and controls. Participants belong to multiple generations of six families with five MAPT mutations. All participants underwent a medical examination, neuropsychological tests, genetic analysis, and a magnetic resonance scan (3T, scout, T1-weighted image followed by EPI (BOLD), MPRAGE, DTI, FLAIR, and ASL sequences). RESULTS: Volumes of five cortical and subcortical areas were strongly correlated with mutation status: temporal lobe (left amygdala, left temporal pole), cingulate cortex (left rostral anterior cingulate gyrus, right posterior cingulate), and the lingual gyrus in the occipital lobe. We did not find significant differences in whole brain volume, white matter hyperintensities volume, and white matter integrity using DTI analysis. CONCLUSION: Temporal lobe, cingulate cortex and the lingual gyrus seem to be early targets of the disease and may serve as biomarkers for FTD prior to overt symptom onset.

Structural Brain Magnetic Resonance Imaging to Rule Out Comorbid Pathology in the Assessment of Alzheimer's Disease Dementia: Findings from the Ontario Neurodegenerative Disease Research Initiative (ONDRI) Study and Clinical Trials Over the Past 10 Years. - Kapoor, Arunima; Bartha, Robert; Black, Sandra E; Borrie, Michael; Freedman, Morris; Gao, Fuqiang; Herrmann, Nathan; Mandzia, Jennifer; Ozzoude, Miracle; Ramirez, Joel; Scott, Christopher J M; Symons, Sean; et al. (J Alzheimers Dis, 2020)
BACKGROUND/OBJECTIVE: Structural brain magnetic resonance imaging (MRI) is not mandatory in Alzheimer's disease (AD) research or clinical guidelines. We aimed to explore the use of structural brain MRI in AD/mild cognitive impairment (MCI) trials over the past 10 years and determine the frequency with which inclusion of standardized structural MRI acquisitions detects comorbid vascular and non-vascular pathologies. METHODS: We systematically searched ClinicalTrials.gov for AD clinical trials to determine their neuroimaging criteria and then used data from an AD/MCI cohort who underwent standardized MRI protocols, to determine type and incidence of clinically relevant comorbid pathologies. RESULTS: Of 210 AD clinical trials, 105 (50%) included structural brain imaging in their eligibility criteria. Only 58 (27.6%) required MRI. 16,479 of 53,755 (30.7%) AD participants were in trials requiring MRI. In the observational AD/MCI cohort, 141 patients met clinical criteria; 22 (15.6%) had relevant MRI findings, of which 15 (10.6%) were exclusionary for the study. DISCUSSION: In AD clinical trials over the last 10 years, over two-thirds of participants could have been enrolled without brain MRI and half without even a brain CT. In a study sample, relevant comorbid pathology was found in 15% of participants, despite careful screening. Standardized structural MRI should be incorporated into NIA-AA diagnostic guidelines (when available) and research frameworks routinely to reduce diagnostic heterogeneity.

Supplementation with Matured Hop Bitter Acids Improves Cognitive Performance and Mood State in Healthy Older Adults with Subjective Cognitive Decline. - Fukuda, Takafumi; Ohnuma, Tohru; Obara, Kuniaki; Kondo, Sumio; Arai, Heii; Ano, Yasuhisa (J Alzheimers Dis, 2020)
BACKGROUND: Prevention of age-related cognitive decline and depression is becoming urgent because of rapid growing aging populations. Effects of vagal nerve activation on brain function by food ingredients are inadequately investigated; matured hop bitter acid (MHBA) administration reportedly improves cognitive function and depression via vagal nerve activation in model mice. OBJECTIVE: We investigated the effects of MHBA supplementation on cognitive function and mood state in healthy older adults with perceived subjective cognitive decline. METHODS: Using a randomized double-blind placebo-controlled trial design, 100 subjects (aged 45-69 years) were randomly assigned into placebo (n = 50) and MHBA (n = 50) groups, and received placebo or MHBA capsules daily for 12 weeks. RESULTS: Symbol Digit Modalities Test (SDMT) score assessing divided attention at week 12 was significantly higher (p = 0.045) and β-endorphin at week 12 was significantly lower (p = 0.043) in the subjects receiving MHBA. Transthyretin in serum, a putative mild cognitive impairment marker, was significantly higher at week 12 in the MHBA group than in the placebo group (p = 0.048). Subgroup analysis classified by the subjective cognitive decline questionnaire revealed that in addition to improved SDMT scores, memory retrieval assessed using the standard verbal paired-associate learning tests and the Ray Verbal Learning Test at week 12 had significantly improved in the subgroup with perceived subjective cognitive decline and without requirement for medical assistance in the MHBA group compared with that in the placebo group. CONCLUSION: This study suggested that MHBA intake improves cognitive function, attention, and mood state in older adults.

Synaptic Vesicle Protein 2B Negatively Regulates the Amyloidogenic Processing of AβPP as a Novel Interaction Partner of BACE1. - Miyamoto, Masakazu; Kuzuya, Akira; Noda, Yasuha; Ueda, Sakiho; Asada-Utsugi, Megumi; Ito, Shinji; Fukusumi, Yoshiyasu; Kawachi, Hiroshi; Takahashi, Ryosuke; Kinoshita, Ayae (J Alzheimers Dis, 2020)
BACKGROUND: Given that amyloid-β (Aβ) peptide is produced and released at synapses, synaptic Aβ is one of the promising therapeutic targets to prevent synaptic dysfunction in Alzheimer's disease (AD). Although Aβ production begins with the cleavage of the amyloid-β protein precursor (AβPP) by β-site AβPP cleaving enzyme 1 (BACE1), the mechanism on how BACE1 is involved in AβPP processing at synapses remains unclear. OBJECTIVE: This study aimed to identify novel BACE1 interacting proteins regulating Aβ production at the synapse. METHODS: BACE1 interacting proteins were pulled down using a mass spectrometry-based proteomics of wild-type (WT) rat brain synaptoneurosome lysates utilizing anti-BACE1 antibody. Then, a novel BACE1 interactor was identified and characterized using experimental systems that utilized transfected cells and knockout (KO) mice. RESULTS: Synaptic vesicle protein 2B (SV2B) was identified as a novel presynaptic interaction partner of BACE1. In HEK293 cells, co-overexpression of SV2B with BACE1 significantly reduced the sAβPPβ and Aβ levels released in the media; thus, SV2B overexpression negatively affected the AβPP cleavage by BACE1. Compared with those of WT mice, the hippocampal lysates of SV2B knockout mice had significantly elevated Aβ levels, whereas the β-secretase activity and the AβPP and BACE1 protein levels remained unchanged. Finally, a fractionation assay revealed that BACE1 was mislocalized in SV2B KO mice; hence, SV2B may be involved in BACE1 trafficking downregulating the amyloidogenic pathway of AβPP. CONCLUSION: SV2B has a novel role of negatively regulating the amyloidogenic processing of AβPP at the presynapses.

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

Use of Immersive Virtual Reality in the Assessment and Treatment of Alzheimer's Disease: A Systematic Review. - Clay, Felix; Howett, David; Fitzgerald, James; Fletcher, Paul; Chan, Dennis; Price, Annabel (J Alzheimers Dis, 2020)
BACKGROUND: Immersive virtual reality (iVR) allows seamless interaction with simulated environments and is becoming an established tool in clinical research. It is unclear whether iVR is acceptable to people with Alzheimer's disease (AD) dementia or useful in their care. We explore whether iVR is a viable research tool that may aid the detection and treatment of AD. OBJECTIVES: This review examines the use of iVR in people with AD or mild cognitive impairment (MCI). METHODS: Medline, PsycINFO, Embase, CINAHL, and Web of Science databases were searched from inception. PRISMA guidelines were used with studies selected by at least two researchers. RESULTS: Nine studies were eligible for inclusion. None reported any issues with iVR tolerability in participants with MCI and AD on assessment or treatment tasks. One study demonstrated capability for detecting prodromal AD and correlated with neuroanatomical substrates. Two studies showed iVR to have high accuracy in differentiating participants with AD from controls but were not hypothesis driven or with adequate controls measures. In a small validation study and two longitudinal case studies, iVR cognitive training was positively rated but did not demonstrate reliable benefit. CONCLUSION: iVR is emerging as a viable method of assessing older adults and people with AD. Strongest benefits were seen when closely integrated with theoretical models of neurodegeneration and existing screening methods. Further randomized controlled trials integrated with clinical populations are required. This will consolidate the power of iVR for assessment of MCI and clarify treatment efficacy beyond current applications in physical rehabilitation.

Using Machine Learning to Predict Dementia from Neuropsychiatric Symptom and Neuroimaging Data. - Gill, Sascha; Mouches, Pauline; Hu, Sophie; Rajashekar, Deepthi; MacMaster, Frank P; Smith, Eric E; Forkert, Nils D; Ismail, Zahinoor (J Alzheimers Dis, 2020)
BACKGROUND: Machine learning (ML) is a promising technique for patient-specific prediction of mild cognitive impairment (MCI) and dementia development. Neuropsychiatric symptoms (NPS) might improve the accuracy of ML models but have barely been used for this purpose. OBJECTIVES: To investigate if baseline mild behavioral impairment (MBI) status used for NPS quantification along with brain morphology features are predictive of follow-up diagnosis, median 40 months later in patients with normal cognition (NC) or MCI. METHOD: Baseline neuroimaging, neuropsychiatric, and clinical data from 102 individuals with NC and 239 with MCI were extracted from the Alzheimer's Disease Neuroimaging Initiative database. Neuropsychiatric inventory questionnaire items were transformed to MBI domains using a published algorithm. Diagnosis at latest follow-up was used as the outcome variable and ground truth classification. A logistic model tree classifier combined with information gain feature selection was trained to predict follow-up diagnosis. RESULTS: In the binary classification (NC versus MCI/AD), the optimal ML model required only two features from over 200, MBI total score and left hippocampal volume. These features correctly classified participants as remaining normal or developing cognitive impairment with 84.4% accuracy (area under the receiver operating characteristics curve [ROC-AUC] = 0.86). Seven features were selected for the three-class model (NC versus MCI versus dementia) achieving an accuracy of 58.8% (ROC-AUC=0.73). CONCLUSION: Baseline NPS, categorized for MBI domain and duration, have prognostic utility in addition to brain morphology measures for predicting diagnosis change using ML. MBI total score, followed by impulse dyscontrol and affective dysregulation were most predictive of future diagnosis.

Validation of Plasma Proteomic Biomarkers Relating to Brain Amyloid Burden in the EMIF-Alzheimer's Disease Multimodal Biomarker Discovery Cohort. - Westwood, Sarah; Baird, Alison L; Anand, Sneha N; Nevado-Holgado, Alejo J; Kormilitzin, Andrey; Shi, Liu; Hye, Abdul; Ashton, Nicholas J; Morgan, Angharad R; Bos, Isabelle; Vos, Stephanie J B; Baker, Susan; et al. (J Alzheimers Dis, 2020)
We have previously investigated, discovered, and replicated plasma protein biomarkers for use to triage potential trials participants for PET or cerebrospinal fluid measures of Alzheimer's disease (AD) pathology. This study sought to undertake validation of these candidate plasma biomarkers in a large, multi-center sample collection. Targeted plasma analyses of 34 proteins with prior evidence for prediction of in vivo pathology were conducted in up to 1,000 samples from cognitively healthy elderly individuals, people with mild cognitive impairment, and in patients with AD-type dementia, selected from the EMIF-AD catalogue. Proteins were measured using Luminex xMAP, ELISA, and Meso Scale Discovery assays. Seven proteins replicated in their ability to predict in vivo amyloid pathology. These proteins form a biomarker panel that, along with age, could significantly discriminate between individuals with high and low amyloid pathology with an area under the curve of 0.74. The performance of this biomarker panel remained consistent when tested in apolipoprotein E ɛ4 non-carrier individuals only. This blood-based panel is biologically relevant, measurable using practical immunocapture arrays, and could significantly reduce the cost incurred to clinical trials through screen failure.

APOE Effect on Amyloid-β PET Spatial Distribution, Deposition Rate, and Cut-Points. - Toledo, Jon B; Habes, Mohamad; Sotiras, Aristeidis; Bjerke, Maria; Fan, Yong; Weiner, Michael W; Shaw, Leslie M; Davatzikos, Christos; Trojanowski, John Q (J Alzheimers Dis, 2019)
There are conflicting results regarding how APOE genotype, the strongest genetic risk factor for Alzheimer's disease (AD), influences spatial and longitudinal amyloid-β (Aβ) deposition and its impact on the selection of biomarker cut-points. In our study, we sought to determine the impact of APOE genotype on cross-sectional and longitudinal florbetapir positron emission tomography (PET) amyloid measures and its impact in classification of patients and interpretation of clinical cohort results. We included 1,019 and 1,072 Alzheimer's Disease Neuroimaging Initiative participants with cerebrospinal fluid Aβ1 - 42 and florbetapir PET values, respectively. 623 of these subjects had a second florbetapir PET scans two years after the baseline visit. We evaluated the effect of APOE genotype on Aβ distribution pattern, pathological biomarker cut-points, cross-sectional clinical associations with Aβ load, and longitudinal Aβ deposition rate measured using florbetapir PET scans. 1) APOEɛ4 genotype influences brain amyloid deposition pattern; 2) APOEɛ4 genotype does not modify Aβ biomarker cut-points estimated using unsupervised mixture modeling methods if white matter and brainstem references are used (but not when cerebellum is used as a reference); 3) findings of large differences in Aβ biomarker value differences based on APOE genotype are due to increased probability of having AD neuropathology and are most significant in mild cognitive impairment subjects; and 4) APOE genotype and age (but not gender) were associated with increased Aβ deposition rate. APOEɛ4 carrier status affects rate and location of brain Aβ deposition but does not affect choice of biomarker cut-points if adequate references are selected for florbetapir PET processing.

The Association between Mushroom Consumption and Mild Cognitive Impairment: A Community-Based Cross-Sectional Study in Singapore. - Feng, Lei; Cheah, Irwin Kee-Mun; Ng, Maisie Mei-Xi; Li, Jialiang; Chan, Sue Mei; Lim, Su Lin; Mahendran, Rathi; Kua, Ee-Heok; Halliwell, Barry (J Alzheimers Dis, 2019)
We examined the cross-sectional association between mushroom intake and mild cognitive impairment (MCI) using data from 663 participants aged 60 and above from the Diet and Healthy Aging (DaHA) study in Singapore. Compared with participants who consumed mushrooms less than once per week, participants who consumed mushrooms >2 portions per week had reduced odds of having MCI (odds ratio = 0.43, 95% CI 0.23-0.78, p = 0.006) and this association was independent of age, gender, education, cigarette smoking, alcohol consumption, hypertension, diabetes, heart disease, stroke, physical activities, and social activities. Our cross-sectional data support the potential role of mushrooms and their bioactive compounds in delaying neurodegeneration.

Association of Cognitive Function with Amyloid-β and Tau Proteins in the Vitreous Humor. - Wright, Lauren M; Stein, Thor D; Jun, Gyungah; Chung, Jaeyoon; McConnell, Kate; Fiorello, Marissa; Siegel, Nicole; Ness, Steven; Xia, Weiming; Turner, Kelley L; Subramanian, Manju L (J Alzheimers Dis, 2019)
BACKGROUND: The eye may serve as source for diagnostic testing for early detection of Alzheimer's disease (AD). Examination of amyloid-β (Aβ) and tau protein content in human vitreous and its correlation to neuro-cognition may improve ocular-based AD detection methods. OBJECTIVE: To evaluate levels of Aβ and tau protein in human vitreous humor and investigate the clinical predictive role of these proteins as early diagnostic markers of AD. METHODS: A prospective, single-center, multi-surgeon cohort study. Vitreous humor samples from 80 eyes were measured quantitatively for Aβ40-42, pTau, and tTau. Linear regression was used to test associations between AD biomarker levels, Mini-Mental State Exam (MMSE), and serum apolipoprotein E (APOE) allele status, with adjustment for age, sex, and education level of patients. RESULTS: Lower MMSE scores were significantly associated with lower levels of vitreous Aβ40 (p = 0.015), Aβ42 (p = 0.0066), and tTau (p = 0.0085), and these biomarkers were not associated with any pre-existing eye conditions. Presence of the ɛ4 allele and the ɛ2 allele approached significance with reduced Aβ40 level (p = 0.053) and increased p-Tau level (p = 0.056), respectively. CONCLUSION: Patients with poor cognitive function have significantly lower vitreous humor levels of AD-related biomarkers Aβ40, Aβ42, and tTau. These biomarkers do not correlate with underlying eye conditions, suggesting their specificity in association with cognitive change. This is the first study to our knowledge to correlate cognition with AD-related proteins in the vitreous humor. Results suggest ocular proteins may have a role for early dementia detection in individuals at risk for AD.

CD14 and Toll-Like Receptor 4 Promote Fibrillar Aβ42 Uptake by Microglia Through A Clathrin-Mediated Pathway. - Fujikura, Mai; Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Manabe, Tatsuo; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2019)
We previously demonstrated that microglia play an essential role in clearance of amyloid-β (Aβ) in Alzheimer's disease (AD)-like pathology. Our prior work also showed that several receptors expressed on microglia participated in Aβ phagocytosis. However, clathrin-mediated endocytosis (CME), which is associated with production and release of Aβ in neurons, has received much less attention in the context of microglial Aβ uptake. To elucidate the detailed mechanisms of microglial Aβ uptake pathways, we focused on CD14 and Toll-like receptor 4 (TLR4), which have been shown to mediate fibrillar Aβ1 - 42 (fAβ42) phagocytosis in microglia. CD14 has also been known to control lipopolysaccharide-induced internalization of TLR4 in a clathrin-dependent manner. However, it remains unclear whether CD14 and TLR4 engage in CME in microglial fAβ42 uptake, including whether CD14 interacts with TLR4 in the process. In the present study, we found that CD14-positive microglia increased in an age-dependent manner in the cortex of AD model mice. Immunostaining showed that CD14 interacted with TLR4 to internalize fAβ42 in the mouse microglial cell line MG6. Knock-down of CD14 and TLR4 in MG6 cells significantly reduced intracellular fAβ42, showing their involvement in fAβ42 uptake. We also found that clathrin participated in fAβ42 uptake by MG6 cells. Furthermore, CD14 and TLR4 mediated fAβ42 uptake via clathrin-dependent mechanisms. These results indicate that CD14 and TLR4 participate not only in phagocytosis but also in clathrin-dependent fAβ42 internalization in microglia. These findings provide novel molecular understanding of microglial fAβ42 uptake, which could be of therapeutic relevance for AD.

Cerebral Microbleeds Are Associated with Cerebral Hypoperfusion in Patients with Alzheimer's Disease. - Hatada, Yutaka; Hashimoto, Mamoru; Shiraishi, Shinya; Ishikawa, Tomohisa; Fukuhara, Ryuji; Yuki, Seiji; Tanaka, Hibiki; Miyagawa, Yusuke; Kitajima, Mika; Uetani, Hiroyuki; Tsunoda, Naoko; Koyama, Asuka; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Although cerebral microbleeds (CMBs) are commonly observed in patients with Alzheimer's disease (AD), their clinical relevance for AD remains unclear. OBJECTIVE: We investigated the significance of CMBs in AD by examining the relationship between CMBs and cerebral blood flow (CBF) in patients with AD. METHODS: Thirty-four patients (aged 77.9±7.6 years; 17 men) with probable AD and multiple (≥8) CMBs were selected from 394 consecutive patients. For each lobe of the brain, the correlation between the number of CMBs observed on susceptibility-weighted images and the decrease in CBF observed on single-photon emission computed tomography was assessed. RESULTS: The number of microbleeds was significantly correlated with the severity of decrease in the occipital lobe (Spearman's r = 0.531, p <  0.001) and temporal lobe (r = 0.437, p <  0.001) but not in the frontal lobe (r = 0.201, p = 0.101) and parietal lobe (r = 0.178, p = 0.146). These results were unchanged in the partial correlational analysis after controlling the effect of other small vessel disease such as lacunars and white matter hyperintensities. CONCLUSION: Multiple CMBs are associated with cerebral hypoperfusion in AD. The effects of CMBs on CBF differed according to brain location, possibly reflecting different distributions of the underlying cerebral amyloid angiopathy and AD-related histopathology, such as neurofibrillary tangles.

Cerebrospinal Fluid Level of Aquaporin4: A New Window on Glymphatic System Involvement in Neurodegenerative Disease? - Arighi, Andrea; Di Cristofori, Andrea; Fenoglio, Chiara; Borsa, Stefano; D'Anca, Marianna; Fumagalli, Giorgio Giulio; Locatelli, Marco; Carrabba, Giorgio; Pietroboni, Anna Margherita; Ghezzi, Laura; Carandini, Tiziana; Colombi, Annalisa; et al. (J Alzheimers Dis, 2019)
Aquaporin4 (AQP4) is a water channel protein located at astrocyte foot processes that plays a role in glymphatic system, a highly organized fluid transport pathway which seems to be involved in Alzheimer's disease (AD) and normal pressure hydrocephalus (NPH) pathophysiology. Cerebrospinal fluid (CSF) AQP4 levels were determined in 11 patients with AD, 10 patients with NPH, and 9 controls. We found significantly reduced AQP4 in AD patients, a trend in reduction in NPH patients, and a correlation between AQP4 and amyloid-β CSF levels. This study indicates the potential role of AQP4 and glymphatic system in neurodegenerative diseases pathophysiology.

Choroid Plexus Acts as Gatekeeper for TREM2, Abnormal Accumulation of ApoE, and Fibrillary Tau in Alzheimer's Disease and in Down Syndrome Dementia. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Vuono, Romina; Bickerton, Anastasia; Jones, Elizabeth; Fincham, Robert; Allinson, Kieren; Holland, Anthony; Zaman, Shahid H (J Alzheimers Dis, 2019)
BACKGROUND: Genetic factors that influence Alzheimer's disease (AD) risk include mutations in TREM2 and allelic variants of Apolipoprotein E, influencing AD pathology in the general population and in Down syndrome (DS). Evidence shows that dysfunction of the choroid plexus may compromise the blood-cerebrospinal fluid (CSF) barrier, altering secretary, transport and immune function that can affect AD pathology. OBJECTIVE: To investigate the genotype and phenotype of DS individuals in relation to choroid plexus damage and blood-CSF barrier leakage to identify markers that could facilitate early diagnosis of AD in DS. METHODS: To assess allele frequency and haplotype associations ApoE, Tau, TREM2, and HLA-DR were analyzed by SNP analysis in DS participants (n = 47) and controls (n = 50). The corresponding plasma protein levels were measured by ELISA. Postmortem brains from DS, AD, and age-matched controls were analyzed by immunohistochemistry. RESULTS: Haplotype analysis showed that individuals with Tau H1/H1 and ApoEɛ4 genotypes were more prevalent among DS participants with an earlier diagnosis of dementia (17%) compared to H1/H2 haplotypes (6%). Plasma TREM2 levels decreased whereas phospho-tau levels increased with age in DS. In AD and DS brain, insoluble tau and ApoE were found to accumulate in the choroid plexus. CONCLUSION: Accumulation of tau and ApoE in the choroid plexus may increase the oligomerization rate of Aβ42 and impair tau trafficking, leading to AD pathology. We have identified a high-risk haplotype: ApoEɛ4, Tau/H1, and TREM2/T, that manifests age-related changes potentially opening a window for treatment many years prior to the manifestation of the AD dementia.

Circulating and Extracellular Vesicles Levels of N-(1-Carboxymethyl)-L-Lysine (CML) Differentiate Early to Moderate Alzheimer's Disease. - Haddad, Mohamed; Perrotte, Morgane; Landri, Sarra; Lepage, Aurelie; Fülöp, Tamás; Ramassamy, Charles (J Alzheimers Dis, 2019)
BACKGROUND: Both advanced glycation end products (AGEs) N-(1-carboxymethyl)-L-lysine (CML) and pentosidine were found in the brain from Alzheimer's disease (AD) patients and were associated with the neuropathological hallmarks of AD. In AD patients, the circulating level of both AGEs remains unknown. Moreover, their levels in peripheral extracellular vesicles (EVs) and their association with AD remain to be determined. Finally, it is not known if neuronal cells can release AGEs via EVs and propagate AGEs. OBJECTIVE: To determine the levels of circulating CML and pentosidine during the progression of AD. Moreover, their levels in circulating EVs were determined and their association with the clinical cognitive scores were analyzed. Finally, we have studied the possibility that neuronal cells eliminate and transfer these AGEs through EVs. METHODS: CML and pentosidine levels were measured in serum and in circulating EVs. Released-EVs from SK-N-SH neuronal cells were isolated and CML levels were also determined. RESULTS: The levels of CML in albumin-free serum proteins were higher in the early stage of AD while the levels of pentosidine remained unchanged. In contrast, the levels of CML in the EVs were lower in the moderate stage of AD. Interestingly, the levels of CML in serum were negatively correlated with the clinical cognitive scores MMSE and MoCA. For the first time, we were able to demonstrate that CML was present in EVs released from neuronal cells in culture. CONCLUSION: Peripheral and circulating EVs levels of CML can differentiate early to moderate AD. In the brain, neuronal CML can propagate from cells-to-cells via EVs.

Developing Effective Alzheimer's Disease Therapies: Clinical Experience and Future Directions. - Elmaleh, David R; Farlow, Martin R; Conti, Peter S; Tompkins, Ronald G; Kundakovic, Ljiljana; Tanzi, Rudolph E (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) clinical trials, focused on disease modifying drugs and conducted in patients with mild to moderate AD, as well as prodromal (early) AD, have failed to reach efficacy endpoints in improving cognitive function in most cases to date or have been terminated due to adverse events. Drugs that have reached clinical stage were reviewed using web resources (such as clinicaltrials.gov, alzforum.org, company press releases, and peer reviewed literature) to identify late stage (Phase II and Phase III) efficacy clinical trials and summarize reasons for their failure. For each drug, only the latest clinical trials and ongoing trials that aimed at improving cognitive function were included in the analysis. Here we highlight the potential reasons that have hindered clinical success, including clinical trial design and choice of outcome measures, heterogeneity of patient populations, difficulties in diagnosing and staging the disease, drug design, mechanism of action, and toxicity related to the long-term use. We review and suggest approaches for AD clinical trial design aimed at improving our ability to identify novel therapies for this devastating disease.

Head Position During Sleep: Potential Implications for Patients with Neurodegenerative Disease. - Levendowski, Daniel J; Gamaldo, Charlene; St Louis, Erik K; Ferini-Strambi, Luigi; Hamilton, Joanne M; Salat, David; Westbrook, Philip R; Berka, Chris (J Alzheimers Dis, 2019)
BACKGROUND: The characterization of sleep in those with neurodegenerative disease (NDD) is essential in understanding the potential neurobiological mechanisms that underlie the connection between sleep disruption and NDD manifestations and progression. OBJECTIVE: Explore the inter-relationships between NDD and age, sex, diagnosis of obstructive sleep apnea, snoring, and duration of sleep time with the head in the supine and non-supine positions. METHODS: A case-control design was used to evaluate differences in sleep position obtained from multi-night, in-home Sleep Profiler recordings in 45 patients with diagnosed NDD (24 with mild cognitive impairment, 15 with Alzheimer's disease, and 6 with Lewy Body, Parkinson's, or other dementias) and 120 age-sex matched controls with normal cognition (NC). RESULTS: The frequency of supine sleep >2 h/night was significantly greater in the NDD than in the NC group (p < 0.001, odds ratio = 3.7), and remained significant after controlling for age, sex, snoring, and obstructive sleep apnea diagnosis (p = 0.01). There were no group differences in nocturnal mobility i.e., number of head position changes/h. CONCLUSION: This study demonstrates the utility of in-home measurements of sleep in defining the association of supine sleep position with neurodegenerative disorders. Our findings warrant further investigation, particularly in light of the recent evidence suggesting that sleep may an active role in the brain's ability to clear CNS neurotoxins and metabolites.

Higher Body Mass Index Is Associated with Lower Cortical Amyloid-β Burden in Cognitively Normal Individuals in Late-Life. - Thirunavu, Vineeth; McCullough, Austin; Su, Yi; Flores, Shaney; Dincer, Aylin; Morris, John C; Cruchaga, Carlos; Benzinger, Tammie L S; Gordon, Brian A (J Alzheimers Dis, 2019)
BACKGROUND: Both low and high body mass index (BMI) have been associated with an increased risk of dementia, including that caused by Alzheimer's disease (AD). Specifically, high middle-age BMI or a low late-age BMI has been considered a predictor for the development of AD dementia. Less studied is the relationship between BMI and AD pathology. OBJECTIVE: We explored the association between BMI and cortical amyloid-β (Aβ) burden in cognitively normal participants that were either in mid-life (45-60 years) or late-life (>60). METHODS: We analyzed cross-sectional baseline data from the Knight Alzheimer Disease Research Center (ADRC) at Washington University. Aβ pathology was measured in 373 individuals with Aβ PET imaging and was quantified using Centiloid units. We split the cohort into mid- and late-life groups for analyses (n = 96 and n = 277, respectively). We ran general linear regression models to predict Aβ levels from BMI while controlling for age, sex, years of education, and APOE4 status. Analyses were also conducted to test the interaction between BMI and APOE4 genotype and between BMI and sex. RESULTS: Higher BMI was associated with lower cortical Aβ burden in late-life (β= -0.81, p = 0.0066), but no relationship was found in mid-life (β= 0.04, p > 0.5). The BMI×APOE4+ and BMI×male interaction terms were not significant in the mid-life (β= 0.28, p = 0.41; β= 0.64, p = 0.13) or the late-life (β= 0.17, p > 0.5; β= 0.50, p = 0.43) groups. CONCLUSION: Higher late-life BMI is associated with lower cortical Aβ burden in cognitively normal individuals.

Maintain Your Brain: Protocol of a 3-Year Randomized Controlled Trial of a Personalized Multi-Modal Digital Health Intervention to Prevent Cognitive Decline Among Community Dwelling 55 to 77 Year Olds. - Heffernan, Megan; Andrews, Gavin; Fiatarone Singh, Maria A; Valenzuela, Michael; Anstey, Kaarin J; Maeder, Anthony J; McNeil, John; Jorm, Louisa; Lautenschlager, Nicola T; Sachdev, Perminder S; Ginige, Jeewani A; Hobbs, Megan J; et al. (J Alzheimers Dis, 2019)
BACKGROUND: Maintain Your Brain (MYB) is a randomized controlled trial of an online multi-modal lifestyle intervention targeting modifiable dementia risk factors with its primary aim being to reduce cognitive decline in an older age cohort. METHODS: MYB aims to recruit 8,500 non-demented community dwelling 55 to 77 year olds from the Sax Institute's 45 and Up Study in New South Wales, Australia. Participants will be screened for risk factors related to four modules that comprise the MYB intervention: physical activity, nutrition, mental health, and cognitive training. Targeting risk factors will enable interventions to be personalized so that participants receive the most appropriate modules. MYB will run for three years and up to four modules will be delivered sequentially each quarter during year one. Upon completing a module, participants will continue to receive less frequent booster activities for their eligible modules (except for the mental health module) until the end of the trial. DISCUSSION: MYB will be the largest internet-based trial to attempt to prevent cognitive decline and potentially dementia. If successful, MYB will provide a model for not just effective intervention among older adults, but an intervention that is scalable for broad use.

NP03, a Microdose Lithium Formulation, Blunts Early Amyloid Post-Plaque Neuropathology in McGill-R-Thy1-APP Alzheimer-Like Transgenic Rats. - Wilson, Edward N; Do Carmo, Sonia; Welikovitch, Lindsay A; Hall, Hélène; Aguilar, Lisi Flores; Foret, Morgan K; Iulita, M Florencia; Jia, Dan Tong; Marks, Adam R; Allard, Simon; Emmerson, Joshua T; Ducatenzeiler, Adriana; et al. (J Alzheimers Dis, 2019)
Epidemiological, preclinical, and clinical studies have suggested a role for microdose lithium in reducing Alzheimer's disease (AD) risk by modulating key mechanisms associated with AD pathology. The novel microdose lithium formulation, NP03, has disease-modifying effects in the McGill-R-Thy1-APP transgenic rat model of AD-like amyloidosis at pre-plaque stages, before frank amyloid-β (Aβ) plaque deposition, during which Aβ is primarily intraneuronal. Here, we are interested in determining whether the positive effects of microdose lithium extend into early Aβ post-plaque stages. We administered NP03 (40μg Li/kg; 1 ml/kg body weight) to McGill-R-Thy1-APP transgenic rats for 12 weeks spanning the transition phase from plaque-free to plaque-bearing. The effect of NP03 on remote working memory was assessed using the novel object recognition task. Levels of human Aβ38, Aβ40, and Aβ42 as well as levels of pro-inflammatory mediators were measured in brain-extracts and plasma using electrochemiluminescent assays. Mature Aβ plaques were visualized with a thioflavin-S staining. Vesicular acetylcholine transporter (VAChT) bouton density and levels of chemokine (C-X-C motif) ligand 1 (CXCL1), interleukin-6 (IL-6), and 4-hydroxynonenal (4-HNE) were probed using quantitative immunohistochemistry. During the early Aβ post-plaque stage, we find that NP03 rescues functional deficits in object recognition, reduces loss of cholinergic boutons in the hippocampus, reduces levels of soluble and insoluble cortical Aβ42 and reduces hippocampal Aβ plaque number. In addition, NP03 reduces markers of neuroinflammation and cellular oxidative stress. Together these results indicate that microdose lithium NP03 is effective at later stages of amyloid pathology, after appearance of Aβ plaques.

A Randomized, Double-Blind, Placebo-Controlled, Phase II Study Assessing Safety, Tolerability, and Efficacy of Bryostatin in the Treatment of Moderately Severe to Severe Alzheimer's Disease. - Farlow, Martin R; Thompson, Richard E; Wei, Lee-Jen; Tuchman, Alan J; Grenier, Elaine; Crockford, David; Wilke, Susanne; Benison, Jeffrey; Alkon, Daniel L (J Alzheimers Dis, 2019)
BACKGROUND: Bryostatin-activated PKC epsilon pre-clinically induces synaptogenesis, anti-apoptosis, anti-amyloid-β oligomers, and anti-hyperphosphorylated tau. OBJECTIVES: To investigate bryostatin safety, tolerability, and efficacy to improve cognition in advanced Alzheimer's disease (AD) patients. METHODS: A double-blind, randomized, placebo-controlled Phase II, 12-week trial of i.v. bryostatin for 150 advanced AD patients (55-85) with MMSE-2 of 4-15, randomized 1:1:1 into 20 μg and 40 μg bryostatin, and placebo arms. The Full Analysis Set (FAS) and the Completer Analysis Set (CAS) were pre-specified alternative assessments (1-sided, p < 0.1 for primary efficacy, and 2-sided, p < 0.05 for pre-specified and post hoc exploratory analyses). RESULTS: The safety profile was similar for 20 μg treatment and placebo patients. The 40 μg patients showed safety and drop-out issues, but no efficacy. Primary improvement of Severe Impairment Battery (SIB) scores at 13 weeks was not significant (p = 0.134) in the FAS, although in the CAS, the SIB comparison favored 20 μg bryostatin compared to placebo patients (p < 0.07). Secondary analyses at weeks 5 and 15 (i.e., 30 days post-final dosing) also favored 20 μg bryostatin compared to placebo patients. A pre-specified ANCOVA for baseline memantine blocking bryostatin and positive post-hoc trend analyses were statistically significant (2-sided, p < 0.05). CONCLUSION: Although the primary endpoint was not significant in the FAS, primary and secondary analyses in the CAS, and pre-specified and post-hoc exploratory analyses did favor bryostatin 20 μg compared to the placebo cohort. These promising Phase II results support further trials of 20 μg bryostatin- without memantine- to treat AD.

Stem Cell-Derived Neurons as Cellular Models of Sporadic Alzheimer's Disease. - Foveau, Bénédicte; Correia, Ana Sofia; Hébert, Sébastien S; Rainone, Sara; Potvin, Olivier; Kergoat, Marie-Jeanne; Belleville, Sylvie; Duchesne, Simon; LeBlanc, Andréa C (J Alzheimers Dis, 2019)
Alzheimer's disease (AD) occurs as either an autosomal dominant inherited disease or sporadically. While familial mutant genes can be expressed in cells or in animal models to assess dysregulated functions, sporadic AD cannot be replicated in models given our lack of understanding of causality. Furthermore, the study of sporadic forms of AD is difficult given the inaccessibility of brain tissues in living individuals and the manifestation of symptoms years after the onset of disease. Here, the objective was to assess if induced pluripotent stem cell-derived neurons from well-ascertained sporadic AD individuals could represent potential cellular models to determine the underlying molecular mechanisms of disease. We used cryopreserved peripheral blood mononuclear cells from three well-ascertained sporadic AD and three non-cognitively impaired (NCI) individuals of the CIMA-Q cohort to obtain iPSC-derived neurons. Microtubule associated protein 2 was decreased in AD neurons, whereas expression of AD-associated amyloid precursor protein, tau, and amyloid-β peptide was similar in AD and NCI individuals. RNA sequencing identified several upregulated and downregulated mRNAs in AD relative to NCI neurons. Of these, complement Factor H (CFH), signal regulatory protein beta1 (SIRPB1), and insulin like growth factor binding protein 5 (IGFBP5) were previously associated with AD. In addition, several transcription factors not previously associated with AD, but involved in neuronal proliferation and differentiation were differentially expressed. The results identify novel avenues for the study of the underlying causes of sporadic AD and support the establishment of additional lines to identify mechanisms of disease in sporadic AD individuals.

Subjective Cognitive Decline May Be a Stronger Predictor of Incident Dementia in Women than in Men. - Heser, Kathrin; Kleineidam, Luca; Wiese, Birgitt; Oey, Anke; Roehr, Susanne; Pabst, Alexander; Kaduszkiewicz, Hanna; van den Bussche, Hendrik; Brettschneider, Christian; König, Hans-Helmut; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: Subjective cognitive decline (SCD) has often been associated with an increased risk for subsequent dementia. However, sex-specific associations are understudied until now. METHODS: Cross-sectional and longitudinal associations over a follow-up period of up to 13 years were investigated in a sample of participants without objective cognitive impairment at baseline (n = 2,422, mean age = 79.63 years). Logistic regression and Cox proportional hazards models were conducted. RESULTS: Women less frequently reported SCD without worries (p <  0.001), but tended to report more often SCD with worries (p = 0.082) at baseline compared to men. In models adjusted for age, education, cognitive status, and depressive symptoms, SCD at baseline increased the risk for subsequent dementia (p <  0.001), and this effect was less pronounced in males (interaction sex×SCD: p = 0.022). Stratified analyses showed that SCD increased the risk for subsequent dementia in women (HR = 1.77, p <  0.001), but not in men (HR = 1.07, p = 0.682). Similar results were found in analyses with SCD without and with worries, except that SCD with worries also predicted subsequent Alzheimer's disease (AD) in men (p = 0.037). CONCLUSION: At baseline, men reported more SCD without worries and women tended to report more SCD with worries. SCD in women was more strongly associated with subsequent dementia. SCD without and with worries was related to incident dementia and AD in women, whereas in men only SCD with worries increased the risk for AD, but not for all-cause dementia.

Telomere Length and the Risk of Alzheimer's Disease: The Rotterdam Study. - Fani, Lana; Hilal, Saima; Sedaghat, Sanaz; Broer, Linda; Licher, Silvan; Arp, Pascal P; van Meurs, Joyce B J; Ikram, M Kamran; Ikram, M Arfan (J Alzheimers Dis, 2019)
There is a wide interest in biomarkers that capture the burden of detrimental factors as these accumulate with the passage of time, i.e., increasing age. Telomere length has received considerable attention as such a marker, because it is easily quantified and it may aid in disentangling the etiology of dementia or serve as predictive marker. We determined the association of telomere length with risk of Alzheimer's disease and all-cause dementia in a population-based setting. Within the Rotterdam Study, we performed quantitative PCR to measure mean leukocyte telomere length in blood. We determined the association of telomere length with risk of Alzheimer's disease until 2016, using Cox regression models. Of 1,961 participants (mean age 71.4±9.3 years, 57.1% women) with a median follow-up of 8.3 years, 237 individuals were diagnosed with Alzheimer's disease. We found a U-shaped association between telomere length and risk of Alzheimer's disease: compared to the middle tertile the adjusted hazard ratio was 1.59 (95% confidence interval (CI), 1.13-2.23) for the lowest tertile and 1.47 (1.03-2.10) for the highest tertile. Results were similarly U-shaped but slightly attenuated for all-cause dementia. In conclusion, shorter and longer telomere length are both associated with an increased risk of Alzheimer's disease in the general population.

Telomere Shortening in the Alzheimer's Disease Neuroimaging Initiative Cohort. - Nudelman, Kelly N H; Lin, Jue; Lane, Kathleen A; Nho, Kwangsik; Kim, Sungeun; Faber, Kelley M; Risacher, Shannon L; Foroud, Tatiana M; Gao, Sujuan; Davis, Justin W; Weiner, Michael W; Saykin, Andrew J (J Alzheimers Dis, 2019)
BACKGROUND: Although shorter telomeres have been associated with Alzheimer's disease (AD), it is unclear whether longitudinal change in telomere length is associated with AD progression. OBJECTIVE: To investigate the association of telomere length change with AD diagnosis and progression. METHODS: In 653 individuals from the Alzheimer's Disease Neuroimaging Initiative (ADNI) cohort, T/S ratio (telomere versus single copy gene), a proxy of telomere length, was measured for up to five visits per participant (N = 1918 samples post-QC) using quantitative PCR (qPCR). T/S ratio was adjusted for batch effects and DNA storage time. A mixed effects model was used to evaluate association of telomere length with AD diagnostic group and interaction of age and diagnosis. Another mixed effects model was used to compare T/S ratio changes pre- to post-conversion to MCI or AD to telomere change in participants with stable diagnoses. RESULTS: Shorter telomeres were associated with older age (Effect Size (ES) = -0.23) and male sex (ES = -0.26). Neither baseline T/S ratio (ES = -0.036) nor T/S ratio change (ES = 0.046) differed significantly between AD diagnostic groups. MCI/AD converters showed greater, but non-significant, telomere shortening compared to non-converters (ES = -0.186). CONCLUSIONS: Although AD compared to controls showed small, non-significant effects for baseline T/S ratio and T/S ratio shortening, we did observe a larger, though still non-significant effect for greater telomere shortening in converters compared to non-converters. Although our results do not support telomere shortening as a robust biomarker of AD progression, further investigation in larger samples and for subgroups of participants may be informative.

Traffic-Related Air Pollution as a Risk Factor for Dementia: No Clear Modifying Effects of APOEɛ4 in the Betula Cohort. - Oudin, Anna; Andersson, John; Sundström, Anna; Nordin Adolfsson, Annelie; Oudin Åström, Daniel; Adolfsson, Rolf; Forsberg, Bertil; Nordin, Maria (J Alzheimers Dis, 2019)
It is widely known that the apolipoprotein E (APOE) ɛ4 allele imposes a higher risk for Alzheimer's disease (AD). Recent evidence suggests that exposure to air pollution is also a risk factor for AD, and results from a few studies indicate that the effect of air pollution on cognitive function and dementia is stronger in APOEɛ4 carriers than in non-carriers. Air pollution and interaction with APOEɛ4 on AD risk thus merits further attention. We studied dementia incidence over a 15-year period from the longitudinal Betula study in Northern Sweden. As a marker for long-term exposure to traffic-related air pollution, we used modelled annual mean nitrogen oxide levels at the residential address of the participants at start of follow-up. Nitrogen oxide correlate well with fine particulate air pollution levels in the study area. We had full data on air pollution, incidence of AD and vascular dementia (VaD), APOEɛ4 carrier status, and relevant confounding factors for 1,567 participants. As expected, air pollution was rather clearly associated with dementia incidence. However, there was no evidence for a modifying effect by APOEɛ4 on the association (p-value for interaction > 0.30 for both total dementia (AD+VaD) and AD). The results from this study do not imply that adverse effects of air pollution on dementia incidence is limited to, or stronger in, APOEɛ4 carriers than in the total population.

Vascular Burden Score Impacts Cognition Independent of Amyloid PET and MRI Measures of Alzheimer's Disease and Vascular Brain Injury. - DeCarli, Charles; Villeneuve, Sylvia; Maillard, Pauline; Harvey, Danielle; Singh, Baljeet; Carmichael, Owen; Fletcher, Evan; Olichney, John; Farias, Sarah; Jagust, William; Reed, Bruce; Mungas, Dan (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: To determine the impact of vascular burden on rates of decline in episodic memory and executive function. We hypothesize that greater vascular burden will have an additive negative impact on cognition after accounting for baseline cognitive impairment, positron emission tomography (PET) amyloid burden, and magnetic resonance imaging (MRI) measures. METHODS: Individuals were followed an average of 5 years with serial cognitive assessments. Predictor variables include vascular burden score (VBS), quantitative brain MRI assessment, and amyloid imaging. Subjects consisted of 65 individuals, 53% of whom were male, aged 73.2±7.2 years on average with an average of 15.5±3.3 years of educational achievement. RESULTS: Baseline cognitive impairment was significantly associated poorer episodic memory (p < 0.0001), smaller hippocampal volume (p < 0.0001), smaller brain volume (p = 0.0026), and greater global Pittsburg Imaging Compound B (PiB) index (p = 0.0008). Greater amyloid burden was associated with greater decline in episodic memory over time (β= -0.20±0.07, p < 0.005). VBS was significantly associated with the level of executive function performance (β= -0.14±0.05, p < 0.005) and there was a significant negative interaction between VBS, cognitive impairment, and PiB index (β= -0.065±0.03, p = 0.03). CONCLUSIONS: Our results find a significant influence of VBS independent of standard MRI measures and cerebral amyloid burden on executive function. In addition, VBS reduced the amount of cerebral amyloid burden needed to result in cognitive impairment. We conclude that the systemic effects of vascular disease as reflected by the VBS independently influence cognitive ability.

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

18F-Flortaucipir Binding in Choroid Plexus: Related to Race and Hippocampus Signal. - Lee, Christopher M; Jacobs, Heidi I L; Marquié, Marta; Becker, John A; Andrea, Nicolas V; Jin, David S; Schultz, Aaron P; Frosch, Matthew P; Gómez-Isla, Teresa; Sperling, Reisa A; Johnson, Keith A (J Alzheimers Dis, 2018)
BACKGROUND: On target 18F-Flortaucipir (FTP) binding of Alzheimer's disease tau aggregates and off-target binding of melanocytes have been demonstrated with autoradiography. OBJECTIVE: We aimed to investigate the hypothesis that if binding in choroid plexus (CP) is due to melanocytes, the signal would be elevated in Black/African American (B/AA) compared to White (W) participants. In addition, we examined whether CP signal affects measurements in adjacent regions, and whether correcting for spill-in effects has an influence on associations between hippocampus (HC) FTP and amyloid or cognition. METHODS: FTP race differences in 147 Harvard Aging Brain Study participants (23 B/AA, 124W) were examined in CP, HC, HC covaried for CP, amygdala, inferior temporal gyrus, entorhinal cortex, and fusiform regions. Associations between CP FTP and other regions-of-interest (ROIs) were probed to assess spill-in effects. A statistical regression approach to attenuate CP spill-in was tested by relating adjusted HC SUVR residuals and unadjusted HC SUVR to race, cognition and amyloid. All analyses were covaried for age, sex, education and amyloid deposition, and Bonferroni-corrected for multiple comparisons. RESULTS: B/AA individuals had elevated CP and HC SUVR (p < 0.007), whereas other ROI SUVR and HC SUVR covaried for CP SUVR did not show race differences (p > 0.05). CP SUVR was associated with HC SUVR (p < 10-14), but with no other ROI SUVR (p > 0.05). When adjusting HC SUVR for CP SUVR, no race differences in residual HC SUVR were detected, and relationships with amyloid and memory became apparent. CONCLUSION: Melanocyte FTP binding may account partially for high CP signal. This off-target binding affects mainly HC FTP measurements, which should be interpreted with caution.

[18F]-Flutemetamol Uptake in Cortex and White Matter: Comparison with Cerebrospinal Fluid Biomarkers and [18F]-Fludeoxyglucose. - Kalheim, Lisa Flem; Fladby, Tormod; Coello, Christopher; Bjørnerud, Atle; Selnes, Per (J Alzheimers Dis, 2018)
Flutemetamol (18F-Flut) is an [18F]-labelled amyloid PET tracer with increasing availability. The main objectives of this study were to investigate 1) cerebrospinal fluid (CSF) Aβ 1-42 (Aβ42) concentrations associated with regional 18F-Flut uptake, 2) associations between cortical 18F-Flut and [18F]-fludeoxyglucose (18F-FDG)-PET, and 3) the potential use of 18F-Flut in WM pathology. Cognitively impaired, nondemented subjects were recruited (n = 44). CSF was drawn, and 18F-Flut-PET, 18F-FDG-PET, and MRI performed. Our main findings were: 1) Different Alzheimer's disease predilection areas showed increased 18F-Flut retention at different CSF Aβ42 concentrations (posterior regions were involved at higher concentrations). 2) There were strong negative correlations between regional cortical 18F-Flut and 18F-FDG uptake. 3) Increased 18F-Flut uptake were observed in multiple subcortical regions in amyloid positive subjects, including investigated reference regions. However, WM hyperintensity 18F-Flut standardized uptake value ratios (SUVr) were not significantly different, thus we cannot definitely conclude that the higher uptake in 18F-Flut(+) is due to amyloid deposition. In conclusion, our findings support clinical use of CSF Aβ42, putatively relate decreasing CSF Aβ42 concentrations to a sequence of regional amyloid deposition, and associate amyloid pathology to cortical hypometabolism. However, we cannot conclude that 18F-Flut-PET is a suitable marker for WM pathology due to high aberrant WM uptake.

ABCA7 Downregulation Modifies Cellular Cholesterol Homeostasis and Decreases Amyloid-β Peptide Efflux in an in vitro Model of the Blood-Brain Barrier. - Lamartinière, Yordenca; Boucau, Marie-Christine; Dehouck, Lucie; Krohn, Markus; Pahnke, Jens; Candela, Pietra; Gosselet, Fabien; Fenart, Laurence (J Alzheimers Dis, 2018)
The role of ABCA7 in brain homeostasis and Alzheimer's disease (AD) is currently under intense scrutiny, since it has been reported that polymorphisms in the Abca7 gene and a loss of function of the protein are closely linked to excessive accumulation of amyloid peptides and disturbed cholesterol homeostasis. The blood-brain barrier (BBB), which isolates the brain from the blood compartment, is involved in both of these processes. We therefore hypothesized that ABCA7 downregulation might affect cholesterol and amyloid exchanges at the BBB. Using siRNA and primary cultures of mouse endothelial cells purified from brain microvessels and seeded on Transwell ® inserts, we investigated the role of ABCA7 in cholesterol and amyloid exchanges across the BBB. Our results showed that a decrease in ABCA7 expression at the BBB provokes in vitro a reduction in ABCA1 expression and a decrease in APOE secretion. In vitro, these decreases reduce cholesterol exchange across the BBB, particularly for high-density lipoproteins and ApoA-I particles. When ABCA7 was absent, we observed a reduction in Aβ peptide basolateral-to-apical transport in the presence of ApoA-I, with non-significant changes in the expression levels of Rage, Lrp1, Abcb1, Abcc1, and Abcg2. Our study in murine BBB model highlighted a putative new role for ABCA7 in AD via the protein's involvement in cholesterol metabolism and amyloid clearance at the BBB.

Abnormalities of Resting State Cortical EEG Rhythms in Subjects with Mild Cognitive Impairment Due to Alzheimer's and Lewy Body Diseases. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Catania, Valentina; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2018)
The present study tested the hypothesis that cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and dementia with Lewy bodies (DLBMCI) as compared to cognitively normal elderly (Nold) subjects. Clinical and rsEEG data in 30 ADMCI, 23 DLBMCI, and 30 Nold subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) score was matched between the ADMCI and DLBMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROCC) classified these sources across individuals. Compared to Nold, IAF showed marked slowing in DLBMCI and moderate in ADMCI. Furthermore, the posterior alpha 2 and alpha 3 source activities were more abnormal in the ADMCI than the DLBMCI group, while widespread delta source activities were more abnormal in the DLBMCI than the ADMCI group. The posterior delta and alpha sources correlated with the MMSE score and correctly classified the Nold and MCI individuals (area under the ROCC >0.85). In conclusion, the ADMCI and DLBMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test the clinical validity of these rsEEG markers.

Accuracy of Inferred APOE Genotypes for a Range of Genotyping Arrays and Imputation Reference Panels. - Lupton, Michelle K; Medland, Sarah E; Gordon, Scott D; Goncalves, Tabatha; MacGregor, Stuart; Mackey, David A; Young, Terri L; Duffy, David L; Visscher, Peter M; Wray, Naomi R; Nyholt, Dale R; Bain, Lisa; et al. (J Alzheimers Dis, 2018)
Cohort studies investigating aging and dementia require APOE genotyping. We compared directly measured APOE genotypes to 'hard-call' genotypes derived from imputing genome-wide genotyping data from a range of platforms using several imputation panels. Older GWAS arrays imputed to 1000 Genomes Project (1KGP) phases and the Haplotype Reference Consortium (HRC) reference panels were able to achieve concordance rates of over 98% with stringent quality control (hard-call-threshold 0.8). However, this resulted in high levels of missingness (>12% with 1KGP and 5% with HRC). With recent GWAS arrays, concordance of 99% could be obtained with relatively lenient QC, resulting in no missingness.

Added Diagnostic Value of Cerebrospinal Fluid Biomarkers for Differential Dementia Diagnosis in an Autopsy-Confirmed Cohort. - Niemantsverdriet, Ellis; Feyen, Bart F E; Le Bastard, Nathalie; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Bjerke, Maria; Engelborghs, Sebastiaan (J Alzheimers Dis, 2018)
BACKGROUND: Differential dementia diagnosis remains a challenge due to overlap of clinical profiles, which often results in diagnostic doubt. OBJECTIVE: Determine the added diagnostic value of cerebrospinal fluid (CSF) biomarkers for differential dementia diagnosis as compared to autopsy-confirmed diagnosis. METHODS: Seventy-one dementia patients with autopsy-confirmed diagnoses were included in this study. All neuropathological diagnoses were established according to standard neuropathological criteria and consisted of Alzheimer's disease (AD) or other dementias (NONAD). CSF levels of Aβ1 - 42, T-tau, and P-tau181 were determined and interpreted based on the IWG-2 and NIA-AA criteria, separately. A panel of three neurologists experienced with dementia made clinical consensus dementia diagnoses. Clinical and CSF biomarker diagnoses were compared to the autopsy-confirmed diagnoses. RESULTS: Forty-two patients (59%) had autopsy-confirmed AD, whereas 29 patients (41%) had autopsy-confirmed NONAD. Of the 24 patients with an ambiguous clinical dementia diagnosis, a correct diagnosis would have been established in 67% of the cases applying CSF biomarkers in the context of the IWG-2 or the NIA-AA criteria respectively. CONCLUSION: AD CSF biomarkers have an added diagnostic value in differential dementia diagnosis and can help establishing a correct dementia diagnosis in case of ambiguous clinical dementia diagnoses.

Age-Dependent Changes in the Sarkosyl-Insoluble Proteome of APPSWE/PS1ΔE9 Transgenic Mice Implicate Dysfunctional Mitochondria in the Pathogenesis of Alzheimer's Disease. - Thygesen, Camilla; Metaxas, Athanasios; Larsen, Martin R; Finsen, Bente (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD), the most common cause of dementia, is characterized by the intra- and extracellular aggregation and accumulation of proteins. The major molecular hallmark is the aggregation of amyloid-β (Aβ) and hyperphosphorylated tau proteins into plaques and tangles, respectively. Evidence points to the pre-fibrillary states of protein aggregates harboring the greatest neurotoxicity. OBJECTIVE: This study was designed to identify and quantify pre-fibrillary protein species enriched by their insolubility in the detergent sarkosyl in the APPSWE/PS1ΔE9 (APP/PS1) transgenic mouse model of AD. Sarkosyl insoluble fractions were isolated from the brains of APP/PS1 and littermate wild type (Wt) mice to identify pre-fibrillary protein species associated with AD. METHODS: Pre-fibrillary protein species were isolated from the brains of 3- and 24-month-old APP/PS1 and littermate Wt mice using sarkosyl extraction and subjected to quantitative proteomics analysis by the use of isobaric tags for relative and absolute quantitation (iTRAQ). RESULTS: The sarkosyl-insoluble pre-fibrillary proteome showed differential age- and genotype-induced effects. In addition to Aβ and tau, old APP/PS1 mice showed significant enrichment in proteins in the sarkosyl fraction involved in oxidative phosphorylation and mitochondrial function. CONCLUSION: The results of this study implicate dysfunctional mitochondria as playing a key role of Aβ- and potentially tau-induced pathological events in the APP/PS1 transgenic mouse model of AD.

Aging without Dementia is Achievable: Current Evidence from Epidemiological Research. - Qiu, Chengxuan; Fratiglioni, Laura (J Alzheimers Dis, 2018)
Both the incidence and the prevalence of dementia increase exponentially with increasing age. This raises the question of whether dementia is an inevitable consequence of aging or whether aging without dementia is achievable. In this review article, we sought to summarize the current evidence from epidemiological and neuropathological studies that investigated this topic. Epidemiological studies have shown that dementia could be avoided even at extreme old ages (e.g., centenarians or supercentenarians). Furthermore, clinico-neuropathological studies found that nearly half of centenarians with dementia did not have sufficient brain pathology to explain their cognitive symptoms, while intermediate-to-high Alzheimer pathology was present in around one-third of very old people without dementia or cognitive impairment. This suggests that certain compensatory mechanisms (e.g., cognitive reserve or resilience) may play a role in helping people in extreme old ages escape dementia syndrome. Finally, evidence has been accumulating in recent years indicating that the incidence of dementia has declined in Europe and North America, which supports the view that the risk of dementia in late life is modifiable. Evidence has emerged that intervention strategies that promote general health, maintain vascular health, and increase cognitive reserve are likely to help preserve cognitive function till late life, thus achieving the goal of aging without dementia.

Alterations in Acrolein Metabolism Contribute to Alzheimer's Disease. - Tsou, Han-Hsing; Hsu, Wen-Chin; Fuh, Jong-Ling; Chen, Shih-Pin; Liu, Tsung-Yun; Wang, Hsiang-Tsui (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a detrimental neurodegenerative disease, and early diagnosis appears to be the key to successful treatment. Acrolein, a byproduct of lipid peroxidation, has been shown to contribute to the pathological process of AD. This study recruited 118 elderly subjects consisting of 58 non-demented control subjects and 62 AD patients. We analyzed the acrolein-related metabolites in the plasma, cerebrospinal fluid (CSF), and urine of all subjects. We found that the levels of acrolein-conjugated protein (Acr-PC) in the plasma (p = 0.00012) and CSF (p = 0.00161) of AD patients were significantly higher than those of control subjects, whereas the levels of a urinary acrolein metabolite, 3-hydroxypropyl mercapturic acid (3-HPMA), were markedly decreased (p = 0.00882) in AD patients. These data suggest that deregulated acrolein metabolism may be correlated with neuronal damage in AD patients, which might provide further insights into the disease progression and early diagnosis of AD.
Keywords: Acetylcysteine; Acrolein; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Creatinine; Disease Progression; Early Diagnosis; Female; Humans; Male; Middle Aged

Alterations in the Plasma Levels of Specific Choline Phospholipids in Alzheimer's Disease Mimic Accelerated Aging. - Dorninger, Fabian; Moser, Ann B; Kou, Jianqiu; Wiesinger, Christoph; Forss-Petter, Sonja; Gleiss, Andreas; Hinterberger, Margareta; Jungwirth, Susanne; Fischer, Peter; Berger, Johannes (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common neurodegenerative disease and of continuously rising prevalence. The identification of easy-to-measure biomarkers capable to assist in the prediction and early diagnosis of AD is currently a main research goal. Lipid metabolites in peripheral blood of human patients have recently gained major attention in this respect. Here, we analyzed plasma of 174 participants (not demented at baseline; mean age: 75.70±0.44 years) of the Vienna Transdanube Aging (VITA) study, a longitudinal, population-based birth cohort study, at baseline and after 90 months or at diagnosis of probable AD. We determined the levels of specific choline phospholipids, some of which have been suggested as potential biomarkers for the prediction of AD. Our results show that during normal aging the levels of lysophosphatidylcholine, choline plasmalogen, and lyso-platelet activating factor increase significantly. Notably, we observed similar but more pronounced changes in the group that developed probable AD. Thus, our results imply that, in terms of choline-containing plasma phospholipids, the conversion to AD mimics an accelerated aging process. We conclude that age, even in the comparatively short time frame between 75 and 82.5 years, is a crucial factor in the quest for plasma lipid biomarkers for AD that must be carefully considered in future studies and trials.

Alterations of Effective Connectivity Patterns in Mild Cognitive Impairment: An MEG Study. - Gómez, Carlos; Juan-Cruz, Celia; Poza, Jesús; Ruiz-Gómez, Saúl J; Gomez-Pilar, Javier; Núñez, Pablo; García, María; Fernández, Alberto; Hornero, Roberto (J Alzheimers Dis, 2018)
Neuroimaging techniques have demonstrated over the years their ability to characterize the brain abnormalities associated with different neurodegenerative diseases. Among all these techniques, magnetoencephalography (MEG) stands out by its high temporal resolution and noninvasiveness. The aim of the present study is to explore the coupling patterns of resting-state MEG activity in subjects with mild cognitive impairment (MCI). To achieve this goal, five minutes of spontaneous MEG activity were acquired with a 148-channel whole-head magnetometer from 18 MCI patients and 26 healthy controls. Inter-channel relationships were investigated by means of two complementary coupling measures: coherence and Granger causality. Coherence is a classical method of functional connectivity, while Granger causality quantifies effective (or causal) connectivity. Both measures were calculated in the five conventional frequency bands: delta (δ, 1-4 Hz), theta (θ, 4-8 Hz), alpha (α, 8-13 Hz), beta (β, 13-30 Hz), and gamma (γ, 30-45 Hz). Our results showed that connectivity values were lower for MCI patients than for controls in all frequency bands. However, only Granger causality revealed statistically significant differences between groups (p-values < 0.05, FDR corrected Mann-Whitney U-test), mainly in the beta band. Our results support the role of MCI as a disconnection syndrome, which elicits early alterations in effective connectivity patterns. These findings can be helpful to identify the neural substrates involved in prodromal stages of dementia.

Altered Expression of Circulating Cdc42 in Frontotemporal Lobar Degeneration. - Saraceno, Claudia; Catania, Marcella; Paterlini, Anna; Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Binetti, Giuliano; Di Fede, Giuseppe; Caroppo, Paola; Benussi, Luisa; Ghidoni, Roberta; Bolognin, Silvia (J Alzheimers Dis, 2018)
The term frontotemporal lobar degeneration (FTLD) defines a group of heterogeneous conditions histologically characterized by neuronal degeneration, inclusions of various proteins, and synaptic loss. However, the molecular mechanisms contributing to these alterations are still unknown. As the Rho-GTPase family member Cell division cycle 42 (Cdc42) plays a key role in the regulation of actin cytoskeleton dynamics and spine formation, we investigated whether Cdc42 protein levels were altered in the disease. Cdc42 was increased in the frontal cortex of FTLD patients compared to age-matched controls, but also in Alzheimer's disease (AD) patients included in the data-set. On the other hand, the pool of circulating Cdc42 in the plasma was altered in FTLD but not in AD patients. Interestingly, the stratification of the FTLD patients according to the different clinical variants showed a specific decrease of Cdc42 expression in the behavioral subgroup. This data support a role of Cdc42 in FTLD and specifically in the behavioral variant.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Case-Control Studies; cdc42 GTP-Binding Protein; Female; Frontotemporal Lobar Degeneration; Humans; Male; Middle Aged

Alzheimer's Disease: A Journey from Amyloid Peptides and Oxidative Stress, to Biomarker Technologies and Disease Prevention Strategies-Gains from AIBL and DIAN Cohort Studies. - Martins, Ralph N; Villemagne, Victor; Sohrabi, Hamid R; Chatterjee, Pratishtha; Shah, Tejal M; Verdile, Giuseppe; Fraser, Paul; Taddei, Kevin; Gupta, Veer B; Rainey-Smith, Stephanie R; Hone, Eugene; Pedrini, Steve; et al. (J Alzheimers Dis, 2018)
Worldwide there are over 46 million people living with dementia, and this number is expected to double every 20 years reaching about 131 million by 2050. The cost to the community and government health systems, as well as the stress on families and carers is incalculable. Over three decades of research into this disease have been undertaken by several research groups in Australia, including work by our original research group in Western Australia which was involved in the discovery and sequencing of the amyloid-β peptide (also known as Aβ or A4 peptide) extracted from cerebral amyloid plaques. This review discusses the journey from the discovery of the Aβ peptide in Alzheimer's disease (AD) brain to the establishment of pre-clinical AD using PET amyloid tracers, a method now serving as the gold standard for developing peripheral diagnostic approaches in the blood and the eye. The latter developments for early diagnosis have been largely achieved through the establishment of the Australian Imaging Biomarker and Lifestyle research group that has followed 1,100 Australians for 11 years. AIBL has also been instrumental in providing insight into the role of the major genetic risk factor apolipoprotein E ɛ4, as well as better understanding the role of lifestyle factors particularly diet, physical activity and sleep to cognitive decline and the accumulation of cerebral Aβ.

Alzheimer's Disease, Oligomers, and Inflammation. - Forloni, Gianluigi; Balducci, Claudia (J Alzheimers Dis, 2018)
The production of soluble amyloid-β oligomers (AβOs) and the activation of inflammation are two important early steps in the pathogenesis of Alzheimer's disease (AD). The central role of oligomers as responsible for the neuronal dysfunction associated with the clinical features has been extended to the other protein misfolding disorders definable, on this basis, as oligomeropathies. In AD, recent evidence indicates that the mechanism of inflammation as a consequence of neurodegeneration must be assessed in favor of a more direct role of glial activation in the alteration of synaptic function. Our own experimental models demonstrate the efficacy of anti-inflammatory treatments in preventing the cognitive deficits induced acutely by AβOs applied directly in the brain. Moreover, some promising clinical tools are based on immunological activation reducing the presence of cerebral Aβ deposits. However, the strategies based on the control of inflammatory factors as well as the amyloid aggregation show poor or non-therapeutic efficacy. Numerous studies have examined inflammatory factors in biological fluids as possible markers of the neuroinflammation in AD. In some cases, altered levels of cytokines or other inflammatory markers in cerebrospinal fluid correlate with the severity of the disease. Here we propose, according to the precision medicine principles, innovative therapeutic approaches to AD based on the patient's inflammatory profile/state. The earlier intervention and a multifactor approach are two other elements considered essential to improve the chances of effective therapy in AD.

Alzheimer's Disease Progression: Factors Influencing Cognitive Decline. - Ferrari, Camilla; Lombardi, Gemma; Polito, Cristina; Lucidi, Giulia; Bagnoli, Silvia; Piaceri, Irene; Nacmias, Benedetta; Berti, Valentina; Rizzuto, Debora; Fratiglioni, Laura; Sorbi, Sandro (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) patients present high variability in the rate of cognitive decline. Despite the wide knowledge on factors influencing dementia risk, little is known on what accounts for AD progression. Previous studies on this topic have mainly analyzed each factor separately without taking into account the interaction between genetic and non-genetic factors. OBJECTIVE: The aim of the present study is to evaluate the role of demographic, clinical, therapeutic, and genetic factors and their interaction on cognitive decline among newly diagnosed AD patients. METHODS: We retrospectively selected 160 AD patients diagnosed at the Neurology Unit of Careggi University Hospital of Florence. We evaluated the occurrence of rapid cognitive changes defined as the worsening of more than four points at the Mini-Mental State Examination after 2-year follow up period. RESULTS: Among the 160 AD patients, 50% presented rapid disease progression. Extrapyramidal signs at disease onset were predictors of worse outcome (OR 2.2), especially among Apolipoprotein E (APOE) ɛ4 allele carriers, while the presence of family history for dementia decreased the risk of rapid progression by about 50%. Higher educated ɛ4-carriers showed a slower AD progression. We identified the chronic use of aspirin as potential secondary preventative strategy for the non ɛ4-carriers. CONCLUSION: At dementia onset, some clinical and demographic data can be predictors of future progression. The outcomes of the present study support the already hypothesized interaction between genetic and non-genetic factors during disease course and suggest genetic-based approaches.
Keywords: Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Aspirin; Cognitive Dysfunction; Disease Progression; Female; Heterozygote; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Retrospective Studies; Secondary Prevention

Alzheimer's Disease, Visual Search, and Instrumental Activities of Daily Living: A Review and a New Perspective on Attention and Eye Movements. - Ramzaoui, Hanane; Faure, Sylvane; Spotorno, Sara (J Alzheimers Dis, 2018)
Many instrumental activities of daily living (IADLs), like cooking and managing finances and medications, involve finding efficiently and in a timely manner one or several objects within complex environments. They may thus be disrupted by visual search deficits. These deficits, present in Alzheimer's disease (AD) from its early stages, arise from impairments in multiple attentional and memory mechanisms. A growing body of research on visual search in AD has examined several factors underlying search impairments in simple arrays. Little is known about how AD patients search in real-world scenes and in real settings, and about how such impairments affect patients' functional autonomy. Here, we review studies on visuospatial attention and visual search in AD. We then consider why analysis of patients' oculomotor behavior is promising to improve understanding of the specific search deficits in AD, and of their role in impairing IADL performance. We also highlight why paradigms developed in research on real-world scenes and real settings in healthy individuals are valuable to investigate visual search in AD. Finally, we indicate future research directions that may offer new insights to improve visual search abilities and autonomy in AD patients.

Amyloid-β25-35 Upregulates Endogenous Neuroprotectant Neuroglobin via NFκB Activation in vitro. - Liu, Ning; Yu, Zhanyang; Xun, Yu; Shu, Pan; Yue, Yiwei; Yuan, Shishan; Jiang, Yinghua; Huang, Zixuan; Yang, Xiaoping; Feng, Xing; Xiang, Shuanglin; Wang, Xiaoying (J Alzheimers Dis, 2018)
Neuroglobin (Ngb) has been reported to be increased in early and moderately advanced Alzheimer's disease (AD) stages but declined in the severe stage. However, its regulatory mechanisms and pathophysiological roles in the disease remain to be defined. In this study, we found that Ngb expression was significantly upregulated by low dose Aβ25-35, the neurotoxic fragment of Aβ1 - 40 and Aβ1 - 42, but was not further increased by a higher dose of Aβ25-35. Mutation analysis and supershift assay demonstrated that transcription factor Nuclear Factor κB (NFκB), κB2 and κB3 sites located in mouse Ngb promoter region were involved in dynamic regulation of Ngb expression in response to different doses of Aβ25-35 stimulation. In addition, we found that suppression of endogenous Ngb expression exacerbated Aβ25-35-induced neuronal cell death and mitochondrial dysfunction. Our results indicate that endogenous Ngb expression may be upregulated by low dose Aβ25-35, which is responsible for protecting against Aβ25-35-mediated neurotoxicity. These experimental findings suggest that upregulation of endogenous Ngb expression might be an effective intervention approach for AD.

Amyloid-β/Drug Interactions from Computer Simulations and Cell-Based Assays. - Nguyen, Phuong H; Del Castillo-Frias, Maria P; Berthoumieux, Olivia; Faller, Peter; Doig, Andrew J; Derreumaux, Philippe (J Alzheimers Dis, 2018)
Targeting the early oligomers formed by the amyloid-β (Aβ) peptide of 40 and 42 amino acids is considered one promising therapeutic approach for Alzheimer's disease (AD). In vitro experiments and computer simulations are often used in synergy to reveal the modes of interactions of drugs. In this account, we present our contribution to understanding how small molecules bind to Aβ40/Aβ42 peptides, based either on extensive coarse-grained and all-atom simulations, or a variety of experimental techniques. We conclude by offering several perspectives on the future of this field to design more efficient drugs.

Anticholinergic Burden and Risk of Stroke and Death in People with Different Types of Dementia. - Tan, Edwin C K; Eriksdotter, Maria; Garcia-Ptacek, Sara; Fastbom, Johan; Johnell, Kristina (J Alzheimers Dis, 2018)
BACKGROUND: Anticholinergic burden is associated with poorer cognitive and functional outcomes in people with dementia. However, the impact of anticholinergics on significant adverse outcomes such as stroke has not been studied previously. OBJECTIVE: To investigate the association between total anticholinergic cognitive burden (ACB) and risk of stroke and death in people with different dementia subtypes. METHODS: This was a cohort study of 39,107 people with dementia and no prior history of stroke registered in the Swedish Dementia Registry (SveDem) from 2008-2014. Data were extracted from the Swedish Prescribed Drug Register, the Swedish National Patient Register, and the Swedish Total Population Register. Competing risk regression models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between time-varying ACB score and risk of stroke and all-cause mortality. RESULTS: During a mean follow-up period of 2.31 (standard deviation 1.66) years, 11,224 (28.7%) individuals had a stroke or died. Compared with non-users of anticholinergic medications, ACB score of 1 (HR 1.09, 95% CI 1.04-1.14) and ACB score of ≥2 (HR 1.20, 95% CI 1.14-1.26) increased the risk of developing the composite outcome of stroke and death. When stratifying by dementia disorder, the association remained significant in Alzheimer's disease, mixed dementia, and vascular dementia. CONCLUSIONS: The use of anticholinergic medicines may be associated with an increased risk of stroke and death in people with dementia. A dose-response relationship was observed. Careful consideration should be made when prescribing medications with anticholinergic properties to people with dementia.

Application of Weighted Gene Co-Expression Network Analysis to Explore the Key Genes in Alzheimer's Disease. - Liang, Jia-Wei; Fang, Zheng-Yu; Huang, Yong; Liuyang, Zhen-Yu; Zhang, Xiao-Lin; Wang, Jing-Lin; Wei, Hui; Wang, Jian-Zhi; Wang, Xiao-Chuan; Zeng, Ji; Liu, Rong (J Alzheimers Dis, 2018)
BACKGROUND: Weighted co-expression network analysis (WGCNA) is a powerful systems biology method to describe the correlation of gene expression based on the microarray database, which can be used to facilitate the discovery of therapeutic targets or candidate biomarkers in diseases. OBJECTIVE: To explore the key genes in the development of Alzheimer's disease (AD) by using WGCNA. METHODS: The whole gene expression data GSE1297 from AD and control human hippocampus was obtained from the GEO database in NCBI. Co-expressed genes were clustered into different modules. Modules of interest were identified through calculating the correlation coefficient between the module and phenotypic traits. GO and pathway enrichment analyses were conducted, and the central players (key hub genes) within the modules of interest were identified through network analysis. The expression of the identified key genes was confirmed in AD transgenic mice through using qRT-PCR. RESULTS: Two modules were found to be associated with AD clinical severity, which functioning mainly in mineral absorption, NF-κB signaling, and cGMP-PKG signaling pathways. Through analysis of the two modules, we found that metallothionein (MT), Notch2, MSX1, ADD3, and RAB31 were highly correlated with AD phenotype. Increase in expression of these genes was confirmed in aged AD transgenic mice. CONCLUSION: WGCNA analysis can be used to analyze and predict the key genes in AD. MT1, MT2, MSX1, NOTCH2, ADD3, and RAB31 are identified to be the most relevant genes, which may be potential targets for AD therapy.

Argyrophilic Grain Pathology in Frontotemporal Lobar Degeneration: Demographic, Clinical, Neuropathological, and Genetic Features. - Gil, María José; Manzano, María Sagrario; Cuadrado, María Luz; Fernández, Cristina; Góméz, Elena; Matesanz, Carmen; Calero, Miguel; Rábano, Alberto (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a clinically, pathologically, and genetically heterogeneous group of disorders that affect the frontal and temporal lobes of the brain. FTLD classification distinguishes three main neuropathological groups: FTLD-tau, FTLD-TDP, and FTLD-FUS. As a four-repeat tauopathy, argyrophilic grain disease (AGD) is included in the FTLD-tau group. AGD may also appear in association with other neuropathological disorders. We describe the demographic, clinical, neuropathological, and genetic characteristics of a series of FTLD cases presenting with AGD. For this purpose, a clinico-pathological study of 71 autopsy-confirmed FTLD cases from different tissue banks was performed. AGD was found in 52.1% of FTLD cases. The presence of AGD increased with the increasing age (up to 88.9% in cases older than 80 years; p < 0.001) and was associated with higher ages at onset (p < 0.001) and death (p < 0.001). In AGD cases, progressive supranuclear palsy (PSP) was the most frequent clinical diagnosis (29.7%) and gait disturbance was the most common symptom (64.5%); behavioral and language symptoms were less frequent as compared with non-AGD cases (p = 0.055; p = 0.012). PSP was the most frequent neuropathological diagnosis among cases with AGD (32.4%). This group also showed less brain atrophy (p = 0.094) and higher prevalence of Alzheimer (p = 0.002) and vascular pathology (p = 0.047) as compared to the non-AGD group. We also observed that H1/H1 genotype was overrepresented in AGD cases (p = 0.018) and that there was no association with any specific APOE allele. A subanalysis of PSP cases according to the AGD status was carried out, yielding no significant differences.

Assessing Mild Behavioral Impairment with the Mild Behavioral Impairment-Checklist in People with Mild Cognitive Impairment. - Mallo, Sabela C; Ismail, Zahinoor; Pereiro, Arturo X; Facal, David; Lojo-Seoane, Cristina; Campos-Magdaleno, María; Juncos-Rabadán, Onésimo (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) are non-cognitive, behavioral, or psychiatric symptoms, common in mild cognitive impairment (MCI) and associated with a higher risk of dementia. Mild behavioral impairment (MBI) is a validated diagnostic entity, that describes the emergence of later life NPS in pre-dementia states. The Mild Behavioral Impairment Checklist (MBI-C) is the first measure developed to assess MBI. OBJECTIVE: To estimate the prevalence of MBI in people with MCI and to study the score distribution, sensitivity, specificity, diagnostic utility of the MBI-C, and its correlations with neuropsychological tests. METHODS: One hundred eleven MCI participants were evaluated with the Questionnaire for Subjective Memory Complaints (QSMC), Mini-Mental State Examination, Cambridge Cognitive Assessment-Revised, Neuropsychiatric Inventory-Questionnaire (NPI-Q), Geriatric Depression Scale-15 items (GDS-15), Lawton and Brody Index, and the MBI-C, which was administered by phone to participants' informants. Descriptive, logistic regression, ROC curve, and bivariate correlations analyses were performed. RESULTS: MBI diagnosis prevalence was 14.2%. The total MBI-C score differentiated people with MBI at a cutoff-point of 6.5, optimizing sensitivity and specificity. MBI-C total score correlated positively with NPI-Q, QSMC, GDS-15, and Lawton and Brody Index. CONCLUSION: The total MBI-C score, obtained by phone administration, is sensitive for detecting MBI in people with MCI. The MBI-C scores indicated that MCI participants had subtle NPS that were correlated to their subjective memory complaints reported by informants, depressive symptoms, and negatively with Instrumental Activities of Daily Living. Further research should be done to clarify the predictive role of NPS in MCI for incident dementia.

Assessment of the Genetic Architecture of Alzheimer's Disease Risk in Rate of Memory Decline. - Del-Aguila, Jorge L; Fernández, Maria Victoria; Schindler, Suzanne; Ibanez, Laura; Deming, Yuetiva; Ma, Shengmei; Saef, Ben; Black, Kathleen; Budde, John; Norton, Joanne; Chasse, Rachel; Harari, Oscar; et al. (J Alzheimers Dis, 2018)
Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from ADNI and the Knight-ADRC at Washington University, and we calculated PRS (polygenic risk score) based on the IGAP study to compare the genetic architecture of AD risk and dementia progression. Dementia progression was measured by the change of Clinical Dementia Rating Sum of Boxes (CDR)-SB per year. Out of the 21 loci for AD risk, no association with the rate of dementia progression was found. The PRS rate was significantly associated with the rate of dementia progression (β= 0.146, p = 0.03). In the case of rare variants, TREM2 (β= 0.309, p = 0.02) was also associated with the rate of dementia progression. TREM2 variant carriers showed a 23% faster rate of dementia compared with non-variant carriers. In conclusion, our results indicate that the recently identified common and rare variants for AD susceptibility have a limited impact on the rate of dementia progression in AD patients.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Longitudinal Studies; Male; Membrane Glycoproteins; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Immunologic; Risk Assessment

The Association Between Body Mass Index, and Cognitive, Functional, and Behavioral Declines for Incident Dementia. - Michaud, Tzeyu L; Siahpush, Mohammad; Farazi, Paraskevi A; Kim, Jungyoon; Yu, Fang; Su, Dejun; Murman, Daniel L (J Alzheimers Dis, 2018)
BACKGROUND: Association between high adiposity and the clinical progression of dementia remains puzzling. OBJECTIVE: To separately examine the association between body mass index (BMI) and cognitive, functional, and behavioral declines before, at, and after diagnosis of dementia, and further stratified by age groups, and sex. METHODS: A total of 1,141 individuals with incident dementia were identified from the Uniform Data Set of the National Alzheimer's Coordinating Center. Cognitive function was evaluated by Mini-Mental State Exam, functional abilities were assessed using Functional Activities Questionnaire, and behavioral symptoms were captured by Neuropsychiatric Inventory Questionnaire at each follow-up visit. We used separate linear-mixed effects models to examine the association. RESULTS: Compared to moderate baseline BMI, high baseline BMI was associated with 0.30-point slower annual progression rates in functional decline. For individuals aged 76 and over, high baseline BMI was associated with 0.42-point faster progression rates in cognitive decline annually. A U-shaped association between baseline BMI and cognitive decline was observed among men. CONCLUSION: BMI levels before dementia diagnosis may facilitate the identification of different risk profiles for progression rates of cognitive and functional declines in individuals who developed dementia.

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Atherosclerosis, Hypertension, and Diabetes in Alzheimer's Disease, Vascular Dementia, and Mixed Dementia: Prevalence and Presentation. - Javanshiri, Keivan; Waldö, Maria Landqvist; Friberg, Niklas; Sjövall, Fredrik; Wickerström, Karin; Haglund, Mattias; Englund, Elisabet (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is the most prevalent cause of dementia with vascular dementia (VaD) being second alongside with mixed AD and VaD, according to some. For some time, it has been proposed that cardiovascular disease (CaVD), hypertension, and diabetes mellitus (DM), which are known risk factors for VaD, also are associated with and contribute to the development of AD. OBJECTIVE: The aim of this study was to investigate the prevalence of these proposed general risk factors, and to document presence of CaVD as evidenced from clinical records or from autopsy findings, further to correlate these with the diagnoses AD, VaD and mixed AD-VaD (MD), respectively. METHODS: Autopsy reports at the Clinical Department of Pathology in Lund from 1992-2017 were analyzed. All cases with a complete autopsy report and a neuropathologically diagnosed dementia disorder (AD, VaD, or MD) were selected on the condition of a clinical diagnosis of dementia. Clinical data were retrieved through medical records and the Swedish National Diabetes Register (NDR). A total of 268 subjects were included. RESULTS: In AD, there was less CaVD as significantly less organ/tissue findings (p < 0.05), significantly less hypertension (p < 0.001), and likewise significantly less DM (p = 0.0014) than in VaD, with the MD group results being set between these two in all aspects studied. CONCLUSION: AD and VaD exhibit such different profiles of organ and vascular damage as well as of hypertension and DM that they clearly point toward different pathogenic origin with low likelihood of shared risk factors.

Atrophy in Distributed Networks Predicts Cognition in Alzheimer's Disease and Type 2 Diabetes. - Buss, Stephanie S; Padmanabhan, Jaya; Saxena, Sadhvi; Pascual-Leone, Alvaro; Fried, Peter J (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) and type 2 diabetes (T2DM) are common causes of cognitive decline among older adults and share strong epidemiological links. Distinct patterns of cortical atrophy are observed in AD and T2DM, but robust comparisons between structure-function relationships across these two disease states are lacking. OBJECTIVE: To compare how atrophy within distributed brain networks is related to cognition across the spectrum of cognitive aging. METHODS: The relationship between structural MRI changes and cognition was studied in 22 mild-to-moderate AD, 28 T2DM, and 27 healthy participants. Cortical thickness measurements were obtained from networks of interest (NOIs) matching the limbic, default, and frontoparietal resting-state networks. Composite cognitive scores capturing domains of global cognition, memory, and executive function were created. Associations between cognitive scores and the NOIs were assessed using linear regression, with age as a covariate. Within-network General Linear Model (GLM) analysis was run in Freesurfer 6.0 to visualize differences in patterns of cortical atrophy related to cognitive function in each group. A secondary analysis examined hemispheric differences in each group. RESULTS: Across all groups, cortical atrophy within the limbic NOI was significantly correlated with Global Cognition (p = 0.009) and Memory Composite (p = 0.002). Within-network GLM analysis and hemispheric analysis revealed qualitatively different patterns of atrophy contributing to cognitive dysfunction between AD and T2DM. CONCLUSION: Brain network atrophy is related to cognitive function across AD, T2DM, and healthy participants. Differences in cortical atrophy patterns were seen between AD and T2DM, highlighting neuropathological differences.

The Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) Scale: Comprehensive Assessment of Psychopathology in Down Syndrome. - Dekker, Alain D; Sacco, Silvia; Carfi, Angelo; Benejam, Bessy; Vermeiren, Yannick; Beugelsdijk, Gonny; Schippers, Mieke; Hassefras, Lyanne; Eleveld, José; Grefelman, Sharina; Fopma, Roelie; Bomer-Veenboer, Monique; et al. (J Alzheimers Dis, 2018)
People with Down syndrome (DS) are prone to develop Alzheimer's disease (AD). Behavioral and psychological symptoms of dementia (BPSD) are core features, but have not been comprehensively evaluated in DS. In a European multidisciplinary study, the novel Behavioral and Psychological Symptoms of Dementia in Down Syndrome (BPSD-DS) scale was developed to identify frequency and severity of behavioral changes taking account of life-long characteristic behavior. 83 behavioral items in 12 clinically defined sections were evaluated. The central aim was to identify items that change in relation to the dementia status, and thus may differentiate between diagnostic groups. Structured interviews were conducted with informants of persons with DS without dementia (DS, n = 149), with questionable dementia (DS+Q, n = 65), and with diagnosed dementia (DS+AD, n = 67). First exploratory data suggest promising interrater, test-retest, and internal consistency reliability measures. Concerning item relevance, group comparisons revealed pronounced increases in frequency and severity in items of anxiety, sleep disturbances, agitation & stereotypical behavior, aggression, apathy, depressive symptoms, and eating/drinking behavior. The proportion of individuals presenting an increase was highest in DS+AD, intermediate in DS+Q, and lowest in DS. Interestingly, among DS+Q individuals, a substantial proportion already presented increased anxiety, sleep disturbances, apathy, and depressive symptoms, suggesting that these changes occur early in the course of AD. Future efforts should optimize the scale based on current results and clinical experiences, and further study applicability, reliability, and validity. Future application of the scale in daily care may aid caregivers to understand changes, and contribute to timely interventions and adaptation of caregiving.

Berberine Alleviates Tau Hyperphosphorylation and Axonopathy-Associated with Diabetic Encephalopathy via Restoring PI3K/Akt/GSK3β Pathway. - Wang, Shanshan; He, Benhong; Hang, Weijian; Wu, NingHua; Xia, Liangtao; Wang, Xu; Zhang, Qianying; Zhou, Xinwen; Feng, Zuohua; Chen, Qingjie; Chen, Juan (J Alzheimers Dis, 2018)
BACKGROUND: Axonopathy is closely linked to the development of diabetic encephalopathy induced by type II diabetes (T2D). Berberine has been shown to cross the blood-brain barrier and holds promising effect for neuronal damage in diabetes. OBJECTIVE: The present study investigated the protective effect and the underlying mechanism of berberine on neuronal axonopathy in both in vitro and in vivo models. METHODS: High glucose/high fat diet and streptozotocin injection-induced T2D rat model was used. Berberine was administered p.o. to T2D rat model for 10 weeks. Morris water maze test, in vivo neuronal tracing, immunohistochemistry, and western blot analysis were performed to evaluate the protective effects of berberine in T2D-induced diabetic encephalopathy rats. Primary cultured neurons were used to further explore the underlying mechanisms in vitro. RESULTS: Berberine dramatically reduced blood glucose and serum insulin levels and alleviated insulin resistance. Berberine significantly attenuated memory impairment, axonopathy, and tau hyperphosphorylation, and also restored PI3K/Akt/GSK3β signaling pathway in T2D rats. In vitro, berberine induced an increase in the phosphorylation of PI3K/Akt as well as GSK3β in high glucose-treated primary neurons. Furthermore, berberine-induced PI3K/Akt activation also resulted in the dephosphorylation of tau protein, which could improve axonal transport impairment in high glucose-treated primary neurons. Pretreated neurons with LY294002, an inhibitor of PI3K, partially blocked berberine-inhibited tau phosphorylation and berberine-activated PI3K/Akt signaling pathway. CONCLUSIONS: Berberine exerts the protective effect against cognitive deficits by improving tau hyperphosphorylation and the axonal damage through restoring PI3K/Akt/GSK3β signaling pathway.

Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

Brain Amyloid Contribution to Cognitive Dysfunction in Early-Stage Parkinson's Disease: The PPMI Dataset. - Fiorenzato, Eleonora; Biundo, Roberta; Cecchin, Diego; Frigo, Anna Chiara; Kim, Jinhee; Weis, Luca; Strafella, Antonio P; Antonini, Angelo (J Alzheimers Dis, 2018)
BACKGROUND: The pathological processes underlying cognitive impairment in Parkinson's disease (PD) are heterogeneous and the contribution of cerebral amyloid deposits is poorly defined, particularly in the early stages of the disease. OBJECTIVE: To investigate regional [18F]florbetaben binding to amyloid-β (Aβ) and its contribution to cognitive dysfunction in early stage PD. METHODS: A multicenter cohort of 48 PD patients from the Parkinson's Progression Marker Initiative (PPMI) underwent [18F]florbetaben positron emission tomography (PET) scanning. Clinical features, including demographic characteristics, motor severity, cerebrospinal fluid (CSF), and cognitive testing were systematically assessed according to the PPMI study protocol. For the purpose of this study, we analyzed various neuropsychological tests assessing all cognitive functions. RESULTS: There were 10/48 (21%) amyloid positive PD patients (PDAβ+). Increased [18F]florbetaben uptake in widespread cortical and subcortical regions was associated with poorer performance on global cognition, as assessed by Montreal Cognitive Assessment (MoCA), and impaired performance on Symbol Digit Modality test (SDMT). Further, we found that PDAβ+ patients had higher CSF total-tau/Aβ1 - 42 (p = 0.001) and phosphorylated-tau/Aβ1 - 42 in (p = 0.002) compared to amyloid-negative PD. CONCLUSION: These findings suggest that multiple disease processes are associated with PD cognitive impairment and amyloid deposits may be observed already in early stages. However, prevalence of amyloid positivity is in the range of literature age-matched control population. Increased cortical and subcortical amyloid is associated with poor performance in attentive-executive domains while cognitive deficits at MoCA and SDMT may identify amyloid-related dysfunction in early PD.

Brain Inflammation Connects Cognitive and Non-Cognitive Symptoms in Alzheimer's Disease. - Selles, M Clara; Oliveira, Mauricio M; Ferreira, Sergio T (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the main form of dementia in the elderly and affects greater than 47 million people worldwide. Care for AD patients poses very significant personal and economic demands on individuals and society, and the situation is expected to get even more dramatic in the coming decades unless effective treatments are found to halt the progression of the disease. Although AD is most commonly regarded as a disease of the memory, the entire brain is eventually affected by neuronal dysfunction or neurodegeneration, which brings about a host of other behavioral disturbances. AD patients often present with apathy, depression, eating and sleeping disorders, aggressive behavior, and other non-cognitive symptoms, which deeply affect not only the patient but also the caregiver's health. These symptoms are usually associated with AD pathology but are often neglected as part of disease progression due to the early and profound impact of disease on memory centers such as the hippocampus and entorhinal cortex. Yet, a collection of findings offers biochemical insight into mechanisms underlying non-cognitive symptoms in AD, and indicate that, at the molecular level, such symptoms share common mechanisms. Here, we review evidence indicating mechanistic links between memory loss and non-cognitive symptoms of AD. We highlight the central role of the pro-inflammatory activity of microglia in behavioral alterations in AD patients and in experimental models of the disease. We suggest that a deeper understanding of non-cognitive symptoms of AD may illuminate a new beginning in AD research, offering a fresh approach to elucidate mechanisms involved in disease progression and potentially unveiling yet unexplored therapeutic targets.

Brains for Dementia Research: Evolution in a Longitudinal Brain Donation Cohort to Maximize Current and Future Value. - Francis, Paul T; Costello, Helen; Hayes, Gillian M (J Alzheimers Dis, 2018)
Brain banking has a long and distinguished past, contributing greatly to our understanding of human neurological and psychiatric conditions. Brain banks have been operationally diverse, collecting primarily end stage disease, with variable quality clinical data available, yet it is now recognized the most informative brain donations are from those in longitudinally studied cohorts. The Brains for Dementia Research (BDR) cohort and program was for planned brain donation across five UK brain banks and one donation point, with standardized operating procedures, following longitudinal clinical and psychometric assessments for people with no cognitive impairment as well as those with dementia. Lay representatives with experience of dementia were involved from inception of BDR and 74.5% of all enquiries about participation came through routes that were directly attributable to or influenced by lay representatives. Ten years after inception, this ongoing project has received over 700 brain donations from the recruited cohort of 3,276 potential brain donors. At cohort census for this paper, 72.2% of the living cohort have no cognitive impairment by assessment, whereas only 28.3% of the donated cohort were without cognitive impairment. It is important that brain banks are agile and reflect the changing needs of the research community, given that 'big data', readiness cohorts, and GWAS demand large sample numbers of highly characterized individuals to facilitate new approaches and understanding of pathological processes in dementia.

Caregiving and Caregiver Burden in Dementia Home Care: Results from the Prospective Dementia Registry (PRODEM) of the Austrian Alzheimer Society. - Ransmayr, Gerhard; Hermann, Philipp; Sallinger, Katharina; Benke, Thomas; Seiler, Stephan; Dal-Bianco, Peter; Marksteiner, Josef; Defrancesco, Michaela; Sanin, Günter; Struhal, Walter; Guger, Michael; Vosko, Milan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Comprehensive studies on caregiver burden (CB) of persons caring for dementia patients differ methodologically and show variable results. OBJECTIVE: Analysis of known and hypothesized factors of CB in home care of dementia patients. METHODS: Multicenter longitudinal study comprising 585 persons caring mostly for Alzheimer's disease patients (age median 77.25 years, Mini-Mental State Examination raw score median 23) using the Zarit Caregiver Burden Interview (CBI). Known patient-related determinants of CB were studied, such as dementia severity (Clinical Dementia Rating, CDR), neuropsychological deficits (CERAD-Plus), neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI), disability (Disability Assessment for Dementia, DAD), dependency (Dependency Scale, DS), and moreover, unclarified potential factors (age, sex, education of patients; age, sex, occupational status of the caregivers; family relationship). Psychological and somatic effects of CB were analyzed (factor analysis). RESULTS: Caregiver age was median 61. Female caregivers prevailed (67.8%). Median CBI sum score (CBIss) was 16 at baseline. After two years, CBIss was 22 and 37% of the caregivers reported mild to moderate (CBIss 21-40), 16.8% moderate to severe or severe (≥41), and 46.2% absent to little CB (CBIss ≤ 20). CB correlated positively with NPI, CDR, DS scores, disability (DAD), years of education of the patients, and proximity of patient and caregiver sex (female), and negatively with caregiver age. Caregivers reported restrictions of time, health problems, and negative emotions. CONCLUSION: The findings are applicable to identify persons at risk for substantial CB and its consequences. There is demand for personal, psychological, and medical support of caregivers and increasing male participation.

Ceftriaxone Improves Cognitive Function and Upregulates GLT-1-Related Glutamate-Glutamine Cycle in APP/PS1 Mice. - Fan, ShuJuan; Xian, XiaoHui; Li, Li; Yao, XiaoGuang; Hu, YuYan; Zhang, Min; Li, WenBin (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by progressive impairment of learning, memory, and cognitive deficits. Glutamate is the major excitatory neurotransmitter in the central nervous system and plays an important role in learning, memory, and cognition. The homeostasis and reutilization of glutamate are dependent on astrocytic uptake by glutamate transporter-1 (GLT-1) and the subsequent glutamate-glutamine cycle. Increasing evidence showed impairments in GLT-1 expression and uptake activity and glutamate-glutamine cycle in AD. Ceftriaxone (Cef) has been reported to upregulate the expression and uptake of GLT-1. Therefore, the present study was undertaken to explore whether Cef can improve cognitive deficits of APP/PS1 mice in early stage of AD by upregulating GLT-1 expression, and then promoting the glutamate-glutamine cycle. It was shown that Cef treatment significantly alleviated the cognitive deficits measured by Morris water maze test and upregulated GLT-1 protein expression in the hippocampus of APP/PS1 mice. Particularly, the activity of glutamine synthetase (GS) and the protein expression of system N glutamine transporter 1 (SN1), which are the key factors involved in the glutamate-glutamine cycle, were significantly upregulated as well after the Cef treatment. Furthermore, inhibition of GLT-1 uptake activity by dihydrokainic acid, an inhibitor of GLT-1, blocked the Cef-induced improvement on the cognitive deficits, GS activity, and SN1 expression. The above results suggested that Cef could improve cognitive deficits of APP/PS1 mice in early stage of AD by upregulating the GLT-1 expression, GS activity, and SN1 expression, which would lead to stimulating the glutamate-glutamine cycle.

Cerebral Amyloid Angiopathy and Cerebral Amyloid Angiopathy-Related Inflammation: Comparison of Hemorrhagic and DWI MRI Features. - Renard, Dimitri; Tatu, Lavinia; Collombier, Laurent; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Boukriche, Yassine; Chiper, Laura; Fourcade, Genevieve; Azakri, Souhayla; Gaillard, Nicolas; Mercier, Erick; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy (CAA) can be associated with primary vasculitis of small/medium-sized leptomeningeal and cortical arteries, called CAA-related inflammation (CAA-ri). OBJECTIVE: To compare hemorrhagic and diffusion-weighted imaging (DWI) MRI features in CAA and CAA-ri. METHODS: We prospectively scored in a consecutive CAA and CAA-ri cohort: presence/number of chronic intracerebral hemorrhage (ICH), cerebral microbleeds (CMB), and cortical superficial siderosis (CSS) on initial T2*-weighted imaging, and DWI lesions on both initial and follow-up imaging. In a subgroup, ApoE, CSF, and 18F-florbetaben-positron emission tomography (FBB-PET) were also analyzed. RESULTS: In CAA-ri, CMB presence was more frequent (100% versus 40%, p < 0.001) and CMB numbers higher (mean 137 versus 8, p < 0.001). No difference was observed for chronic ICH or CSS. DWI lesions were more frequent in acute compared to chronic CAA-ri (p = 0.025), whereas no such difference was observed between acute and chronic CAA (p = 0.18). Both ApoE4 (genotyping available in 22 CAA-ri and 48 CAA patients) carriers and homozygosity were more frequent in CAA-ri (48% versus 19% [p = 0.014] and 32% versus 2% [p < 0.001] respectively). CSF biomarker analyses (performed in 20 CAA-ri and 45 CAA patients) showed lower Aβ42 levels in CAA-ri compared to CAA (median 312 versus 422 pg/mL, p = 0.0032). FBB-PET (performed in 11 CAA-ri and 20 CAA patients) showed higher standardized uptake value ratios in CAA-ri compared with CAA, only significant when the pons was used as reference (p = 0.037). CONCLUSION: Compared to CAA, CAA-ri was associated with higher CMB numbers, more frequent ApoE4 carriers and homozygotes, lower CSF Aβ42 levels, and more severe amyloid load on FBB-PET.

Cerebrospinal Fluid and Plasma Levels of Inflammation Differentially Relate to CNS Markers of Alzheimer's Disease Pathology and Neuronal Damage. - Bettcher, Brianne M; Johnson, Sterling C; Fitch, Ryan; Casaletto, Kaitlin B; Heffernan, Kate S; Asthana, Sanjay; Zetterberg, Henrik; Blennow, Kaj; Carlsson, Cynthia M; Neuhaus, John; Bendlin, Barbara B; Kramer, Joel H (J Alzheimers Dis, 2018)
Inflammatory markers have been shown to predict neurocognitive outcomes in aging adults; however, the degree to which peripheral markers mirror the central nervous system remains unknown. We investigated the association between plasma and cerebrospinal fluid (CSF) markers of inflammation, and explored whether these markers independently predict CSF indicators of Alzheimer's disease (AD) pathology or neuronal damage. Plasma and CSF samples were analyzed for inflammatory markers in a cohort of asymptomatic older adults (n = 173). CSF samples were analyzed for markers of AD pathology (Aβ42, phosphorylated tau [p-tau], sAβPPβ) or neuronal damage (total tau; neurofilament light chain) (n = 147). Separate linear models for each analyte were conducted with CSF and plasma levels entered simultaneously as predictors and markers of AD pathology or neuronal damage as outcome measures. Strong associations were noted between CSF and plasma MIP-1β levels, and modest associations were observed for remaining analytes. With respect to AD pathology, higher levels of plasma and CSF IL-8, CSF MIP-1β, and CSF IP-10 were associated with higher levels of p-tau. Higher levels of CSF IL-8 were associated with higher levels of CSF Aβ42. Higher CSF sAβPPβ levels were associated with higher plasma markers only (IL-8; MCP-1). In terms of neuronal injury, higher levels of plasma and CSF IL-8, CSF IP-10, and CSF MIP-1β were associated with higher levels of CSF total tau. Exploratory analyses indicated that CSF Aβ42 modifies the relationship between plasma inflammatory levels and CSF tau levels. Results suggest that both plasma and CSF inflammatory markers independently relay integral information about AD pathology and neuronal damage.

Change in Fitness and the Relation to Change in Cognition and Neuropsychiatric Symptoms After Aerobic Exercise in Patients with Mild Alzheimer's Disease. - Sobol, Nanna A; Dall, Christian Have; Høgh, Peter; Hoffmann, Kristine; Frederiksen, Kristian Steen; Vogel, Asmus; Siersma, Volkert; Waldemar, Gunhild; Hasselbalch, Steen G; Beyer, Nina (J Alzheimers Dis, 2018)
BACKGROUND: Physical activity has the potential to improve physical function in patients with Alzheimer's disease (AD) and may contribute to modify disease processes and cognitive function. OBJECTIVE: The aim of this study was to investigate 1) the effect of moderate-high-intensity aerobic exercise on cardiorespiratory fitness, i.e., peak oxygen uptake (VO2peak) determined by direct breath-by-breath cardiopulmonary exercise test, and 2) the association between changes in VO2peak and changes in cognition and neuropsychiatric symptoms in patients with mild AD. METHODS: The study is based on secondary outcome analyses from the large single-blinded multi-center study ADEX (Preserving Cognition, Quality of Life, Physical Health and Functional Ability in Alzheimer's Disease: The Effect of Physical Exercise). A preselected sub-group of 55 participants (age 52-83 years), 29 from the intervention group (IG) and 26 from the control group (CG), was included. IG performed 16 weeks of supervised moderate-to-high intensity aerobic exercise. Assessments of VO2peak, mental speed and attention (Symbol Digit Modalities Test, SDMT), and neuropsychiatric symptoms (Neuropsychiatric Inventory, NPI) were performed at baseline and at 16 weeks. RESULT: VO2peak increased 13% in the IG and a between-group difference in mean change (3.92 ml/kg/min, 95% CI 6.34-1.51, p = 0.003) was present in favor of the IG. Combined data from IG and CG showed positive associations between changes in VO2peak and changes in NPI (Rho = - 0.41, p = 0.042) and changes in SDMT (Rho = 0.36, p = 0.010), respectively. CONCLUSION: Aerobic exercise improves VO2peak in community-dwelling patients with mild AD. Furthermore, changes in VO2peak appear to be associated to changes in cognition and neuropsychiatric symptoms.

Chronic Lithium Treatment Increases Telomere Length in Parietal Cortex and Hippocampus of Triple-Transgenic Alzheimer's Disease Mice. - Cardillo, Giancarlo de Mattos; De-Paula, Vanessa de Jesus Rodrigues; Ikenaga, Eliza Hiromi; Costa, Luciana Rodrigues; Catanozi, Sergio; Schaeffer, Evelin Lisete; Gattaz, Wagner Farid; Kerr, Daniel Shikanai; Forlenza, Orestes Vicente (J Alzheimers Dis, 2018)
Telomere length (TL) is a biomarker of cell aging, and its shortening has been linked to several age-related diseases. In Alzheimer's disease (AD), telomere shortening has been associated with neuroinflammation and oxidative stress. The majority of studies on TL in AD were based on leucocyte DNA, with little information about its status in the central nervous system. In addition to other neuroprotective effects, lithium has been implicated in the maintenance of TL. The present study aims to determine the effect of chronic lithium treatment on TL in different regions of the mouse brain, using a triple-transgenic mouse model (3xTg-AD). Eighteen transgenic and 22 wild-type (Wt) male mice were treated for eight months with chow containing 1.0 g (Li1) or 2.0 g (Li2) of lithium carbonate/kg, or standard chow (Li0). DNA was extracted from parietal cortex, hippocampus and olfactory epithelium and TL was quantified by real-time PCR. Chronic lithium treatment was associated with longer telomeres in the hippocampus (Li2, p = 0.0159) and in the parietal cortex (Li1, p = 0.0375) of 3xTg-AD compared to Wt. Our findings suggest that chronic lithium treatment does affect telomere maintenance, but the magnitude and nature of this effect depend on the working concentrations of lithium and characteristics of the tissue. This effect was observed when comparing 3xTg-AD with Wt mice, suggesting that the presence of AD pathology was required for the lithium modulation of TL.

Clinical Subtypes of Dementia with Lewy Bodies Based on the Initial Clinical Presentation. - Morenas-Rodriguez, Estrella; Sala, Isabel; Subirana, Andrea; Pascual-Goñi, Elba; Sánchez-Saudinós, Ma Belén; Alcolea, Daniel; Illán-Gala, Ignacio; Carmona-Iragui, María; Ribosa-Nogué, Roser; Camacho, Valle; Blesa, Rafael; Fortea, Juan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Dementia with Lewy bodies (DLB) is a heterogeneous disease in which clinical presentation, symptoms, and evolution widely varies between patients. OBJECTIVE: To investigate the existence of clinical subtypes in DLB based on the initial clinical presentation. METHODS: 81 patients with a clinical diagnosis of probable DLB were consecutively included. All patients underwent a neurological evaluation including a structured questionnaire about neuropsychiatric symptoms and sleep, an assessment of motor impairment (Unified Parkinson Disease Rating Scale subscale III), and a formal neuropsychological evaluation. Onset of core symptoms (hallucinations, parkinsonism, and fluctuations) and dementia were systematically reviewed from medical records. We applied a K-means clustering method based on the initial clinical presentation. RESULTS: Cluster analysis yielded three different groups. Patients in cluster I (cognitive-predominant, n = 46) presented more frequently with cognitive symptoms (95.7%, n = 44, p < 0.001), and showed a longer duration from onset to DLB diagnosis (p < 0.001) than the other clusters. Patients in cluster II (neuropsychiatric-predominant, n = 22) were older at disease onset (78.1±5 versus 73.6±6.1 and 73.6±4.2 in clusters I and III, respectively, both p < 0.01), presented more frequently with psychotic symptoms (77.3%, n = 17), and had a shorter duration until the onset of hallucinations (p < 0.001). Patients in cluster III (parkinsonism-predominant, n = 13) showed a shorter time from onset to presence of parkinsonism (p < 0.001) and dementia (0.008). CONCLUSIONS: Three clinical subtypes of DLB can be defined when considering the differential initial presentations. The proposed subtypes have distinct clinical profiles and progression patterns.

Cognitive Impairment is Associated with Mortality in Hemodialysis Patients. - Angermann, Susanne; Schier, Johannes; Baumann, Marcus; Steubl, Dominik; Hauser, Christine; Lorenz, Georg; Günthner, Roman; Braunisch, Matthias C; Kemmner, Stephan; Satanovskij, Robin; Haller, Bernhard; Heemann, Uwe; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The prevalence of cognitive impairment in hemodialysis patients is notably high. In previous studises performed in the general population, cognitive impairment has been associated with increased mortality. OBJECTIVE: We evaluated the relationship between global cognitive function tested by a short screening instrument and mortality in hemodialysis patients. METHODS: Cognitive testing was performed in 242 maintenance hemodialysis patients under standardized conditions at baseline using the Montreal Cognitive Assessment (MoCA).Cognitive impairment was defined as a MoCA test score ≤24 points, as published previously. All-cause mortality was monitored during a median follow-up of 3.54 years. Kaplan-Meier plot and Cox regression model adjusted for known risk factors for mortality in hemodialysis patients were used to examine a possible association between global cognitive function and all-cause mortality. RESULTS: A MoCA test score ≤24 points resulted in a significant almost 3-fold higher hazard for all-cause mortality (unadjusted hazard ratio [HR]: 2.812; 95% confidence interval [95% CI]: 1.683-4.698; p < 0.001). After adjustment, this association was attenuated but remained significant (adjusted HR: 1.749; 95% CI: 1.007-3.038; p = 0.047). CONCLUSION: Impairment of global cognitive function measured by a short screening instrument was identified for the first time as an independent predictor of all-cause mortality in hemodialysis patients. Thus, implementing the MoCA test in clinical routine could contribute to a better risk stratification of this patient population.

Combining Cognitive, Genetic, and Structural Neuroimaging Markers to Identify Individuals with Increased Dementia Risk. - Payton, Nicola M; Kalpouzos, Grégoria; Rizzuto, Debora; Fratiglioni, Laura; Kivipelto, Miia; Bäckman, Lars; Laukka, Erika J (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive and biological markers have shown varying degrees of success in identifying persons who will develop dementia. OBJECTIVE: To evaluate different combinations of cognitive and biological markers and identify prediction models with the highest accuracy for identifying persons with increased dementia risk. METHODS: Neuropsychological assessment, genetic testing (apolipoprotein E -APOE), and structural magnetic resonance imaging (MRI) were performed for 418 older individuals without dementia (60-97 years) from a population-based study (SNAC-K). Participants were followed for six years. RESULTS: Cognitive, genetic, and MRI markers were systematically combined to create prediction models for dementia at six years. The most predictive individual markers were perceptual speed or carrying at least one APOEɛ4 allele (AUC = 0.875). The most predictive model (AUC = 0.924) included variables from all three modalities (category fluency, general knowledge, any ɛ4 allele, hippocampal volume, white matter-hyperintensity volume). CONCLUSION: This study shows that combining markers within and between modalities leads to increased predictivity for future dementia. However, minor increases in predictive value should be weighed against the cost of additional tests in larger-scale screening.

Complexity and Selectivity of γ-Secretase Cleavage on Multiple Substrates: Consequences in Alzheimer's Disease and Cancer. - Medoro, Alessandro; Bartollino, Silvia; Mignogna, Donatella; Passarella, Daniela; Porcile, Carola; Pagano, Aldo; Florio, Tullio; Nizzari, Mario; Guerra, Germano; Di Marco, Roberto; Intrieri, Mariano; Raimo, Gennaro; et al. (J Alzheimers Dis, 2018)
The processing of the amyloid-β protein precursor (AβPP) by β- and γ-secretases is a pivotal event in the genesis of Alzheimer's disease (AD). Besides familial mutations on the AβPP gene, or upon its overexpression, familial forms of AD are often caused by mutations or deletions in presenilin 1 (PSEN1) and 2 (PSEN2) genes: the catalytic components of the proteolytic enzyme γ-secretase (GS). The "amyloid hypothesis", modified over time, states that the aberrant processing of AβPP by GS induces the formation of specific neurotoxic soluble amyloid-β (Aβ) peptides which, in turn, cause neurodegeneration. This theory, however, has recently evidenced significant limitations and, in particular, the following issues are debated: 1) the concept and significance of presenilin's "gain of function" versus "loss of function"; and 2) the presence of several and various GS substrates, which interact with AβPP and may influence Aβ formation. The latter consideration is suggestive: despite the increasing number of GS substrates so far identified, their reciprocal interaction with AβPP itself, even in the AD field, is significantly unexplored. On the other hand, GS is also an important pharmacological target in the cancer field; inhibitors or GS activity are investigated in clinical trials for treating different tumors. Furthermore, the function of AβPP and PSENs in brain development and in neuronal migration is well known. In this review, we focused on a specific subset of GS substrates that directly interact with AβPP and are involved in its proteolysis and signaling, by evaluating their role in neurodegeneration and in cell motility or proliferation, as a possible connection between AD and cancer.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Humans; Neoplasms; Presenilin-1

Is Computerized Working Memory Training Effective in Healthy Older Adults? Evidence from a Multi-Site, Randomized Controlled Trial. - Simon, Sharon S; Tusch, Erich S; Feng, Nicole C; Håkansson, Krister; Mohammed, Abdul H; Daffner, Kirk R (J Alzheimers Dis, 2018)
BACKGROUND: Developing effective interventions to attenuate age-related cognitive decline and prevent or delay the onset of dementia are major public health goals. Computerized cognitive training (CCT) has been marketed increasingly to older adults, but its efficacy remains unclear. Working memory (WM), a key determinant of higher order cognitive abilities, is susceptible to age-related decline and a relevant target for CCT in elders. OBJECTIVE: To evaluate the efficacy of CCT focused on WM compared to an active control condition in healthy older adults. METHODS: Eighty-two cognitively normal adults from two sites (USA and Sweden) were randomly assigned to Cogmed Adaptive or Non-Adaptive (active control) CCT groups. Training was performed in participants' homes, five days per week over five weeks. Changes in the performance of the Cogmed trained tasks, and in five neuropsychological tests (Trail Making Test Part A and Part B, Digit Symbol, Controlled Oral Word Association Test and Semantic Fluency) were used as outcome measures. RESULTS: The groups were comparable at baseline. The Adaptive group showed robust gains in the trained tasks, and there was a time-by-group interaction for the Digit Symbol test, with significant improvement only after Adaptive training. In addition, the magnitude of the intervention effect was similar at both sites. CONCLUSION: Home-based CCT Adaptive WM training appears more effective than Non-Adaptive training in older adults from different cultural backgrounds. We present evidence of improvement in trained tasks and on a demanding untrained task dependent upon WM and processing speed. The benefits over the active control group suggest that the Adaptive CCT gains were linked to providing a continuously challenging level of WM difficulty.

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

Connected Speech Features from Picture Description in Alzheimer's Disease: A Systematic Review. - Slegers, Antoine; Filiou, Renée-Pier; Montembeault, Maxime; Brambati, Simona Maria (J Alzheimers Dis, 2018)
The language changes that occur over the course of Alzheimer's disease (AD) can impact communication abilities and have profound functional consequences. Picture description tasks can be used to approximate everyday communication abilities of AD patients. As various methods and variables have been studied over the years, current knowledge about the most affected features of AD discourse in the context of picture descriptions is difficult to summarize. This systematic review aims to provide researchers with an overview of the most common areas of impairment in AD discourse as they appear in picture description tasks. Based on the 44 articles fulfilling inclusion criteria, our findings reflect a multidimensional pattern of changes in the production (speech rate), syntactic (length of utterance), lexical (word-frequency and use of pronouns), fluency (repetitions and word-finding difficulties), semantic (information units), and discourse (efficiency) domains. We discuss our findings in the light of current research and point to potential scientific and clinical uses of picture description tasks in the context of AD.

Correlates of Subjective Cognitive Decline in Lesbian, Gay, Bisexual, and Transgender Older Adults. - Flatt, Jason D; Johnson, Julene K; Karpiak, Stephen E; Seidel, Liz; Larson, Britta; Brennan-Ing, Mark (J Alzheimers Dis, 2018)
BACKGROUND: Little is known about subjective cognitive decline (SCD) in lesbian, gay, bisexual, and transgender (LGBT) older adults. OBJECTIVES: To examine SCD and its association with dementia risk factors, other physical and psychosocial health factors in LGBT older adults. METHODS: A cross-sectional study of SCD was conducted with LGBT older adults, aged 50 and older (n = 210). SCD was categorized based on endorsement of memory problems and one other cognitive domain. Hierarchical logistic regression examined the associations between demographic factors, dementia risk factors, other health and psychosocial factors, and SCD. RESULTS: Nearly 25% of LGBT older adults were classified as having SCD. LGBT older adults who were people of color (OR = 2.5; 95% CI = 1.1- 7.8), depressed (OR = 2.9; 95% CI = 1.3- 6.9), or reported having functional impairment (OR = 2.6; 95% CI = 1.1- 6.5) were significantly more likely to be classified as having SCD (Nagelkerke pseudo R2 = 0.27). CONCLUSION: Depression and functional impairment should be considered when screening LGBT older adults for cognitive impairment and dementia. Future research on the cognitive impairment and dementia risk in LGBT older adults is needed.

Decreased Event-Related Beta Synchronization During Memory Maintenance Marks Early Cognitive Decline in Mild Cognitive Impairment. - Fodor, Zsuzsanna; Sirály, Enikő; Horváth, András; Salacz, Pál; Hidasi, Zoltán; Csibri, Éva; Szabó, Ádám; Csukly, Gábor (J Alzheimers Dis, 2018)
Mild cognitive impairment (MCI) refers to a measurable deficit in cognition in the absence of dementia or impairment in activities of daily living. Working memory impairment is among the earliest signs of MCI. Oscillatory analysis of working memory might be a potential tool for identifying patients at increased risk of developing dementia. Our study aimed to assess the temporospatial pattern of spectral differences during working memory maintenance between MCI patients and healthy controls and to compare the sources of oscillatory activity between the two groups. Event-related spectral perturbation of 17 MCI patients and 21 healthy control participants was studied with 128-channel EEG during the Sternberg working memory task. Source localization was performed by using the eLORETA software. Among the participants, 13 MCI and 15 control participants underwent a structural brain MRI examination. Event-related synchronization (ERS) in the alpha and beta frequency band was significantly lower in MCI patients compared to healthy control participants during retention. Both study groups showed significant memory load-related enhancement in both frequency band. In the MCI group, source localization revealed significantly attenuated beta oscillatory activity in the inferior and middle temporal gyrus, in the fusiform gyrus, and in the cuneus. Beta ERS correlated significantly with the size of the hippocampus, entorhinal cortex, and parahippocampal gyrus. During the retention period, MCI is characterized by decreased alpha and beta ERS compared to controls indicating early impairment in neural networks serving working memory maintenance. The assessment of electrophysiological changes in the beta frequency range may provide a useful diagnostic tool for the early detection of cognitive impairment.

Deep Brain Stimulation Targeting the Fornix for Mild Alzheimer Dementia (the ADvance Trial): A Two Year Follow-up Including Results of Delayed Activation. - Leoutsakos, Jeannie-Marie S; Yan, Haijuan; Anderson, William S; Asaad, Wael F; Baltuch, Gordon; Burke, Anna; Chakravarty, M Mallar; Drake, Kristen E; Foote, Kelly D; Fosdick, Lisa; Giacobbe, Peter; Mari, Zoltan; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Given recent challenges in developing new treatments for Alzheimer dementia (AD), it is vital to explore alternate treatment targets, such as neuromodulation for circuit dysfunction. We previously reported an exploratory Phase IIb double-blind trial of deep brain stimulation targeting the fornix (DBS-f) in mild AD (the ADvance trial). We reported safety but no clinical benefits of DBS-f versus the delayed-on (sham) treatment in 42 participants after one year. However, secondary post hoc analyses of the one-year data suggested a possible DBS-f benefit for participants≥65 years. OBJECTIVE: To examine the long-term safety and clinical effects of sustained and delayed-on DBS-f treatment of mild AD after two years. METHODS: 42 participants underwent implantation of DBS-f electrodes, with half randomized to active DBS-f stimulation (early on) for two years and half to delayed-on (sham) stimulation after 1 year to provide 1 year of active DBS-f stimulation (delayed on). We evaluated safety and clinical outcomes over the two years of the trial. RESULTS: DBS-f had a favorable safety profile with similar rates of adverse events across both trial phases (years 1 and 2) and between treatment arms. There were no differences between treatment arms on any primary clinical outcomes. However, post-hoc age group analyses suggested a possible benefit among older (>65) participants. CONCLUSION: DBS-f was safe. Additional study of mechanisms of action and methods for titrating stimulation parameters will be needed to determine if DBS has potential as an AD treatment. Future efficacy studies should focus on patients over age 65.

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Depression and Alzheimer's Disease Biomarkers Predict Driving Decline. - Babulal, Ganesh M; Chen, Suzie; Williams, Monique M; Trani, Jean-Francois; Bakhshi, Parul; Chao, Grace L; Stout, Sarah H; Fagan, Anne M; Benzinger, Tammie L S; Holtzman, David M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2018)
BACKGROUND: Symptomatic Alzheimer's disease (AD) and depression independently increase crash risk. Additionally, depression is both a risk factor for and a consequence of AD. OBJECTIVE: To examine whether a depression diagnosis, antidepressant use, and preclinical AD are associated with driving decline among cognitively normal older adults. METHODS: Cognitively normal participants, age ≥65, were enrolled. Cox proportional hazards models evaluated whether a depression diagnosis, depressive symptoms (Geriatric Depression Scale), antidepressant use, cerebrospinal fluid (amyloid-β42 [Aβ42], tau, phosphorylated tau181 [ptau181]), and amyloid imaging biomarkers (Pittsburgh Compound B and Florbetapir) were associated with time to receiving a rating of marginal/fail on a road test. Age was adjusted for in all models. RESULTS: Data were available from 131 participants with age ranging from 65.4 to 88.2 years and mean follow up of 2.4 years (SD = 1.0). A depression diagnosis was associated with a faster time to receiving a marginal/fail rating on a road test and antidepressant use (p = 0.024, HR = 2.62). Depression diagnosis and CSF and amyloid PET imaging biomarkers were associated with driving performance on the road test (p≤0.05, HR = 2.51-3.15). In the CSF ptau181 model, depression diagnosis (p = 0.031, HR = 2.51) and antidepressant use (p = 0.037, HR = 2.50) were statistically significant predictors. There were no interaction effects between depression diagnosis, antidepressant use, and biomarker groups. Depressive symptomology was not a statistically significant predictor of driving performance. CONCLUSIONS: While, as previously shown, preclinical AD alone predicts a faster time to receiving a marginal/fail rating, these results suggest that also having a diagnosis of depression accelerates the onset of driving problems in cognitively normal older adults.

Detection of Dementia Cases in Two Swedish Health Registers: A Validation Study. - Rizzuto, Debora; Feldman, Adina L; Karlsson, Ida K; Dahl Aslan, Anna K; Gatz, Margaret; Pedersen, Nancy L (J Alzheimers Dis, 2018)
BACKGROUND: Population-based health registers are potential assets in epidemiological research; however, the quality of case ascertainment is crucial. OBJECTIVE: To compare the case ascertainment of dementia, from the National Patient Register (NPR) and the Cause of Death Register (CDR) with dementia diagnoses from six Swedish population based studies. METHODS: Sensitivity, specificity, and positive predictive value (PPV) of dementia identification in NPR and CDR were estimated by individual record linkage with six Swedish population based studies (n = 19,035). Time to detection in NPR was estimated using data on dementia incidence from longitudinal studies with more than two decades of follow-up. RESULTS: Barely half of the dementia cases were ever detected by NPR or CDR. Using data from longitudinal studies we estimated that a record with a dementia diagnosis appears in the NPR on average 5.5 years after first diagnosis. Although the ability of the registers to detect dementia cases was moderate, the ability to detect non-dementia cases was almost perfect (99%). When registers indicate that there is a dementia diagnosis, there are very few instances in which the clinicians determined the person was not demented. Indeed, PPVs were close to 90%. However, misclassification between dementia subtype diagnoses is quite common, especially in NPR. CONCLUSIONS: Although the overall sensitivity is low, the specificity and the positive predictive value are very high. This suggests that hospital and death registers can be used to identify dementia cases in the community, but at the cost of missing a large proportion of the cases.
Keywords: Aged; Aged, 80 and over; Cause of Death; Dementia; Female; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Registries; Sensitivity and Specificity; Sweden; Twin Studies as Topic

Diagnosis of Mild Cognitive Impairment Due to Alzheimer's Disease with Transcranial Magnetic Stimulation. - Padovani, Alessandro; Benussi, Alberto; Cantoni, Valentina; Dell'Era, Valentina; Cotelli, Maria Sofia; Caratozzolo, Salvatore; Turrone, Rosanna; Rozzini, Luca; Alberici, Antonella; Altomare, Daniele; Depari, Alessandro; Flammini, Alessandra; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Considering the increasing evidence that disease-modifying treatments for Alzheimer's disease (AD) must be administered early in the disease course, the development of diagnostic tools capable of accurately identifying AD at early disease stages has become a crucial target. In this view, transcranial magnetic stimulation (TMS) has become an effective tool to discriminate between different forms of neurodegenerative dementia. OBJECTIVE: To determine whether a TMS multi-paradigm approach can be used to correctly identify mild cognitive impairment (MCI) due to AD (AD MCI). METHODS: A sample of 69 subjects with MCI were included and classified as AD MCI or MCI unlikely due to AD (non-AD MCI) based on 1) extensive neurological and neuropsychological evaluation, 2) MRI imaging, and 3) cerebrospinal fluid analysis or/and amyloid PET imaging. A paired-pulse TMS multi-paradigm approach assessing short interval intracortical inhibition-facilitation (SICI-ICF), dependent on GABAergic and glutamatergic intracortical circuits, respectively, and short latency afferent inhibition (SAI), dependent on cholinergic circuits, was performed. RESULTS: We observed a significant impairment of SAI and unimpaired SICI and ICF in AD MCI as compared to non-AD MCI. According to ROC curve analysis, the SICI-ICF / SAI index differentiated AD MCI from non-AD MCI with a specificity of 87.9% and a sensitivity of 94.4%. CONCLUSIONS: The assessment of intracortical connectivity with TMS could aid in the characterization of MCI subtypes, correctly identifying AD pathophysiology. TMS can be proposed as an adjunctive, non-invasive, inexpensive, and time-saving screening tool in MCI differential diagnosis.

Diaphanous 1 (DIAPH1) is Highly Expressed in the Aged Human Medial Temporal Cortex and Upregulated in Myeloid Cells During Alzheimer's Disease. - Derk, Julia; Bermudez Hernandez, Keria; Rodriguez, Moises; He, Meilun; Koh, Hyunwook; Abedini, Andisheh; Li, Huilin; Fenyö, David; Schmidt, Ann Marie (J Alzheimers Dis, 2018)
BACKGROUND: The receptor for advanced glycation end products (RAGE) is linked to cellular stress and inflammation during Alzheimer's disease (AD). RAGE signals through Diaphanous-1 (DIAPH1); however, the expression of DIAPH1 in the healthy and AD human brain has yet to be methodically addressed. OBJECTIVE: To delineate the cell- and disease-state specific expression of DIAPH1 in the human medial temporal cortex during healthy aging and AD. METHODS: We used semi-quantitative immunohistochemistry in the human medial temporal cortex paired with widefield and confocal microscopy and automated analyses to determine colocalization and relative expression of DIAPH1 with key cell markers and molecules in the brains of subjects with AD versus age-matched controls. RESULTS: We report robust colocalization of DIAPH1 with myeloid cells and increased expression during AD, which strongly correlated to increased neutral lipids and morphology of inflamed myeloid cells. DIAPH1 moderately colocalized with markers of endothelial cells, astrocytes, neurons, and oligodendrocytes. DISCUSSION: Our findings localize DIAPH1 particularly to myeloid cells in the CNS, especially in AD in the locations of lipid droplet accumulation, thereby implicating RAGE-DIAPH1 signaling in dysregulated lipid metabolism and morphological changes of inflamed myeloid cells in this disorder.

Diazepam Toxicity Presenting as a Dementia Disorder. - Kurlawala, Zimple; Roberts, Jeffrey A; McMillan, Joseph D; Friedland, Robert P (J Alzheimers Dis, 2018)
The toxicity associated with long-standing benzodiazepine use in older persons is a critical issue. Several epidemiological reports have studied correlation between benzodiazepine use and risk of dementia development. In this manuscript, we used a case report to demonstrate how chronic diazepam use can cause cognitive deficits that resemble Alzheimer's disease and related conditions. Benzodiazepine use is common in the geriatric population and is often taken for long periods of time in improper doses. In combination with age-related cortical atrophy on the MRI, our patient risked being misdiagnosed with Alzheimer's disease or another dementing disorder if not for the systematic investigation to resolve his symptoms. With elimination of the offending dispensable drug (diazepam), the patient's cognition improved greatly.

Different Abnormalities of Cortical Neural Synchronization Mechanisms in Patients with Mild Cognitive Impairment due to Alzheimer's and Chronic Kidney Diseases: An EEG Study. - Lizio, Roberta; Babiloni, Claudio; Del Percio, Claudio; Losurdo, Antonia; Vernò, Lucia; De Tommaso, Marina; Montemurno, Anna; Dalfino, Giuseppe; Cirillo, Pietro; Soricelli, Andrea; Ferri, Raffaele; Noce, Giuseppe; et al. (J Alzheimers Dis, 2018)
This study tested whether resting state alpha rhythms (8-13 Hz) may characterize mild cognitive impairment due to Alzheimer's disease (ADMCI) compared with MCI due to chronic kidney disease (CKDMCI). Clinical and resting state eyes-closed electroencephalographic (rsEEG) rhythms from 40 ADMCI, 29 CKDMCI, and 45 cognitively normal elderly (Nold) subjects were available in a national archive. Age, gender, and education were matched in the three groups, and Mini-Mental State Evaluation (MMSE) score was paired in the ADMCI and CKDMCI groups. Delta (<4 Hz), theta (4-8 Hz), alpha 1 (8-10.5 Hz), alpha 2 (10.5-13 Hz), beta 1 (13-20 Hz), beta 2 (20-30 Hz), and gamma (30-40 Hz) cortical sources were estimated by eLORETA freeware and classified across individuals by area under the receiver operating characteristic curve (AUROCC). Compared with Nold group, posterior alpha 1 source activities were more reduced in ADMCI than CKDMCI group. In contrast, widespread delta source activities were greater in CKDMCI than ADMCI group. These source activities correlated with the MMSE score and correctly classified between Nold and all MCI individuals (AUROCC = 0.8-0.85) and between ADMCI and CKDMCI subjects (AUROCC = 0.75). These results suggest that early AD affects cortical neural synchronization at alpha frequencies underpinning brain arousal and low vigilance in the quiet wakefulness. In contrast, CKD may principally affect cortical neural synchronization at the delta frequencies. Future prospective cross-validation studies will have to test these candidate rsEEG markers for clinical applications and drug discovery.

Dipeptidyl-Peptidase Activity of Meprin β Links N-truncation of Aβ with Glutaminyl Cyclase-Catalyzed pGlu-Aβ Formation. - Schlenzig, Dagmar; Cynis, Holger; Hartlage-Rübsamen, Maike; Zeitschel, Ulrike; Menge, Katja; Fothe, Anja; Ramsbeck, Daniel; Spahn, Claudia; Wermann, Michael; Roßner, Steffen; Buchholz, Mirko; Schilling, Stephan; et al. (J Alzheimers Dis, 2018)
The formation of amyloid-β (Aβ) peptides is causally involved in the development of Alzheimer's disease (AD). A significant proportion of deposited Aβ is N-terminally truncated and modified at the N-terminus by a pGlu-residue (pGlu-Aβ). These forms show enhanced neurotoxicity compared to full-length Aβ. Although the truncation may occur by aminopeptidases after formation of Aβ, recently discovered processing pathways of amyloid-β protein precursor (AβPP) by proteases such as meprin β may also be involved. Here, we assessed a role of meprin β in forming Aβ3-40/42, which is the precursor of pGlu-Aβ3-40/42 generated by glutaminyl cyclase (QC). Similar to QC, meprin β mRNA is significantly upregulated in postmortem brain from AD patients. A histochemical analysis supports the presence of meprin β in neurons and astrocytes in the vicinity of pGlu-Aβ containing deposits. Cleavage of AβPP-derived peptides by meprin β in vitro results in peptides Aβ1-x, Aβ2-x, and Aβ3-x. The formation of N-truncated Aβ by meprin β was also corroborated in cell culture. A subset of the generated peptides was converted into pGlu-Aβ3-40 by an addition of glutaminyl cyclase, supporting the preceding formation of Aβ3-40. Further analysis of the meprin β cleavage revealed a yet unknown dipeptidyl-peptidase-like activity specific for the N-terminus of Aβ1-x. Thus, our data suggest that meprin β contributes to the formation of N-truncated Aβ by endopeptidase and exopeptidase activity to generate the substrate for QC-catalyzed pGlu-Aβ formation.

Disease Course Varies According to Age and Symptom Length in Alzheimer's Disease. - Barnes, Josephine; Bartlett, Jonathan W; Wolk, David A; van der Flier, Wiesje M; Frost, Chris (J Alzheimers Dis, 2018)
Health-care professionals, patients, and families seek as much information as possible about prognosis for patients with Alzheimer's disease (AD); however, we do not yet have a robust understanding of how demographic factors predict prognosis. We evaluated associations between age at presentation, age of onset, and symptom length with cognitive decline as measured using the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating sum-of-boxes (CDR-SOB) in a large dataset of AD patients. Age at presentation was associated with post-presentation decline in MMSE (p < 0.001), with younger patients showing faster decline. There was little evidence of an association with change in CDR-SOB. Symptom length, rather than age, was the strongest predictor of MMSE and CDR-SOB at presentation, with increasing symptom length associated with worse outcomes. The evidence that younger AD patients have a more aggressive disease course implies that early diagnosis is essential.

Distinct Cognitive and Brain Morphological Features in Healthy Subjects Unaware of Informant-Reported Cognitive Decline. - Sánchez-Benavides, Gonzalo; Grau-Rivera, Oriol; Cacciaglia, Raffaele; Suárez-Calvet, Marc; Falcon, Carles; Minguillon, Carolina; Gramunt, Nina; Sala-Vila, Aleix; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Subtle cognitive decline preceding cognitive impairment can be self-perceived, referred to as subjective cognitive decline (SCD), or go unrecognized. OBJECTIVE: To study the clinical, cognitive, and structural neuroimaging characteristics of psychometrically normal subjects without self-awareness of cognitive decline (unaware decliners, UD) and to compare them with SCD participants and controls. METHODS: 2,640 participants from the ALFA cohort, 1,899 controls, 173 UD (decline reported by the informant only), and 568 SCD underwent clinical and cognitive explorations. A subset of 530 underwent structural MRI (379 Controls; 43 UD; 108 SCD). Linear models adjusting for confounders (age, sex, education, and mood state) were used to assess group differences on cognition and voxel-wise grey matter (GM) volumes. RESULTS: 6.6% were UD while 21.5% SCD. No differences in anxiety and depression were observed between controls and UD, while SCD did (p < 0.01). UD showed lower performance in the Memory Binding Test free recall (p < 0.005) than controls, but no differences compared to SCD. Right medial frontal and insular increments of GM volumes were observed in UD with respect to controls. Informant report of decline in UD and SCD was associated with lower left hippocampal GM volume but related to memory performance only in UD (rho = 0.46, p = 0.002). CONCLUSIONS: UD had worse memory performance than controls which correlated with hippocampal GM volume and presented brain volume increments in self-appraisal areas (medial frontal and insula). Individuals unaware of cognitive decline may represent a distinct group at risk for cognitive impairment and support the usefulness of informant-reported cognitive decline.

Distinct Neuroanatomical Correlates of Neuropsychiatric Symptoms in the Three Main Forms of Genetic Frontotemporal Dementia in the GENFI Cohort. - Sellami, Leila; Bocchetta, Martina; Masellis, Mario; Cash, David M; Dick, Katrina M; van Swieten, John; Borroni, Barbara; Galimberti, Daniela; Tartaglia, Maria Carmela; Rowe, James B; Graff, Caroline; Tagliavini, Fabrizio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The overlap between frontotemporal dementia (FTD) and primary psychiatric disorders has been brought to light by reports of prominent neuropsychiatric symptoms (NPS) in FTD-related genetic mutations, particularly among C9orf72 and GRN carriers. It has been recently demonstrated that early neuroanatomical changes in genetic FTD may be different across the major disease-causing mutations. OBJECTIVE: We aimed to identify whether NPS could be driven by distinct structural correlates. METHODS: One hundred and sixty-seven mutation carriers (75 GRN, 60 C9orf72, and 32 MAPT) were included from the Genetic FTD Initiative (GENFI) study, a large international cohort of genetic FTD. Neuropsychiatric symptoms including delusions, hallucinations (visual, auditory, and tactile), depression, and anxiety were investigated using a structured interview. Voxel-based morphometry was performed to identify neuroanatomical correlates of NPS. RESULTS: Psychotic symptoms correlated mainly with grey matter (GM) atrophy in the anterior insula, left thalamus, cerebellum, and cortical regions including frontal, parietal, and occipital lobes in GRN mutations carriers. GM atrophy in posterior structures of the default-mode network was associated with anxiety in the GRN group. Delusions in C9orf72 expansion carriers were mainly associated with left frontal cortical atrophy. Cerebellar atrophy was found to be correlated only with anxiety in C9orf72 carriers. NPS in the MAPT group were mainly associated with volume loss in the temporal lobe. CONCLUSION: Neuroanatomical correlates of NPS appear to be distinct across the main forms of genetic FTD. Overall, our findings support overlapping brain structural changes between FTD and primary psychiatric disorders.

The Distribution of Urinary Alzheimer-Associated Neuronal Thread Protein and Its Association with Common Chronic Diseases in the General Population. - Jin, He; Guan, Shaochen; Wang, Rong; Fang, Xianghua; Liu, Hongjun; Wu, Yanchuan; Zhang, Yanlei; Liu, Chunxiao (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer-associated neuronal thread protein (AD7c-NTP) has been found to be a biomarker for Alzheimer's disease (AD). OBJECTIVE: The aim of the present study was to investigate the distribution of Alzheimer-associated neuronal thread protein and its relationship to common chronic diseases in the general population. METHODS: Urine samples of 1,805 participants were collected from four districts (Xi Cheng, Fang Shan, Tong Zhou, and Yan Qing) in Beijing. The assessment in this study included a questionnaire that captured participants' demographic information, use of medication and histories of disease, neurological examinations, psychometric evaluations, physical and clinical examinations, and laboratory tests. RESULTS: Urine AD7c-NTP level was increased among the population over 60 years old and females exhibited higher levels than males. These results controlled for other demographic factors such as education levels, employment status, body mass index and current residence. The urine AD7c-NTP levels exhibited no association with non-neurological diseases (0.3346±0.4482 ng/ml), such as hypertension (0.3445±0.4187), stroke (0.3652±0.4010), diabetes (0.3319±0.4371), dyslipidemia (0.3440±0.4314), renal insufficiency (0.3223±0.3909), cancer (0.5055±1.0006), chronic lung disease (0.2911±0.2852), chronic liver disease (0.5579±0.6726), severe depression symptoms (0.5186±0.7040), and mild depression symptoms (0.3669±0.3811). CONCLUSIONS: Cut-off values for urine AD7c-NTP levels for different age groups and genders should be established. AD7c-NTP levels proved relatively stable in the body and were not impacted by demographic factors or common chronic diseases.

DJ-1 Suppresses Cytoplasmic TDP-43 Aggregation in Oxidative Stress-Induced Cell Injury. - Lei, Yang; Zhang, Zhi-Feng; Lei, Rui-Xue; Wang, Shu; Zhuang, Yang; Liu, An-Chun; Wu, Yan; Chen, Juan; Tang, Jun-Chun; Pan, Meng-Xian; Liu, Rui; Liao, Wei-Jing; et al. (J Alzheimers Dis, 2018)
DJ-1 (also called PARK7) is a multifunctional redox-sensitive protein that is protective against oxidative stress-induced cell death. TAR DNA-binding protein 43 (TDP-43) is a major protein component of pathological inclusions in amyotrophic lateral sclerosis and frontotemporal dementia. Reducing aberrant aggregation of TDP-43 is a potential approach to prevent cell death. To investigate whether DJ-1 might inhibit TDP-43 aggregation to exert a protective effect in oxidative stress-induced injury, we tested the protein level and subcellular localization of TDP-43 and DJ-1 in SH-SY5Y cells transfected with wild-type DJ-1, DJ-1 mutant (L166P) cDNA, or DJ-1 siRNA. We show that oxidative stress induced by paraquat leads to the formation of cytosolic TDP-43 aggregation in SH-SY5Y cells. DJ-1 overexpression decreases paraquat-induced cytoplasmic accumulation of TDP-43 in SH-SY5Y cells and protects against paraquat-induced cell death. Transfection of DJ-1 L166P mutant or DJ-1 siRNA leads to increased cytosolic aggregation of TDP-43 in paraquat-treated SH-SY5Y cells and promotes cell death. These data suggest that DJ-1 may protect against oxidative stress-induced cell death through the suppression of cytoplasmic TDP-43 aggregation.

Do Cardiometabolic Risk Factors Influence Amyloid, Tau, and Neuronal Function in APOE4 Carriers and Non-Carriers in Alzheimer's Disease Trajectory? - Femminella, Grazia Daniela; Taylor-Davies, Genevieve; Scott, James; Edison, Paul (J Alzheimers Dis, 2018)
Cardiovascular risk could be calculated using Qrisk2. It is suggested that cardiovascular risk factors influence the progression of Alzheimer's disease (AD). However, studies have not specifically evaluated the influence of cardiovascular risk using Qrisk2 on neuropathological progression and AD biomarkers. The aim of the study was to evaluate the influence of cardiovascular risk factors using Qrisk2 on CSF amyloid-β (Aβ) and tau, 18F-AV45-PET, 18F-FDG-PET, MRI, and cognitive measures in APOE4 negative cognitively normal and mild cognitive impairment (MCI) subjects. 614 cognitively normal, early, and late MCI subjects were selected from the ADNI cohort with a 2-year follow-up. CSF Aβ and tau, 18F-AV45-PET, 18F-FDG-PET, MRI, and cognitive measures along with modified Qrisk2 were evaluated. APOE4 non-carrier, high cardiovascular risk sub-group of early and late MCI and cognitively normal subjects, demonstrated worse biomarker and cognitive profile at baseline and during follow up compared to low cardiovascular risk group. Additionally, similar pattern was also observed in APOE4 carriers. We demonstrated that Qrisk2 and APOE4 were independent predictors of biomarker and clinical progression in AD trajectory. High cardiovascular risk is associated with biomarker changes in APOE4 non-carriers in prodromal AD, which may suggest that treatment of cardiovascular risk is an effective prevention strategy even in APOE4 negative subjects and may influence disease progression independent of amyloid pathology. Demonstration of accelerated neuropathological changes in both APOE4 carriers and non-carriers suggest that focusing on modifiable cardiovascular risk factors is an effective preventative strategy while we eagerly waiting for new treatments.

Does Fatty Acid Composition in Subcutaneous Adipose Tissue Differ between Patients with Alzheimer's Disease and Cohabiting Proxies? - Faxen-Irving, Gerd; Falahati, Farshad; Basun, Hans; Eriksdotter, Maria; Vedin, Inger; Wahlund, Lars-Olof; Schultzberg, Marianne; Hjorth, Erik; Palmblad, Jan; Cederholm, Tommy; Freund-Levi, Yvonne (J Alzheimers Dis, 2018)
Low tissue levels of the major marine ω3 fatty acids (FAs) DHA and EPA are found in Alzheimer's disease (AD). We investigated if healthy proxies to AD patients have higher levels of these ω3 FAs. We observed lower levels of EPA and DHA in subcutaneous adipose tissue biopsies from 64 AD patients compared with 16 cognitively healthy proxies. No significant difference was observed when pairwise comparisons were made between a subset of 16 AD patients and their co-habiting proxies. Larger studies are needed to replicate these findings and to determine if they could depend on FA intake or differences in metabolism.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Dietary Supplements; Fatty Acids, Omega-3; Female; Humans; Male; Regression Analysis; Subcutaneous Fat

Does the Genetic Feature of the Chinese Tree Shrew (Tupaia belangeri chinensis) Support Its Potential as a Viable Model for Alzheimer's Disease Research? - Fan, Yu; Luo, Rongcan; Su, Ling-Yan; Xiang, Qun; Yu, Dandan; Xu, Ling; Chen, Jia-Qi; Bi, Rui; Wu, Dong-Dong; Zheng, Ping; Yao, Yong-Gang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease with increasing incidence across the world and no cure at the present time. An ideal animal model would facilitate the understanding of the pathogenesis of AD and discovery of potential therapeutic targets. The Chinese tree shrew (Tupaia belangeri chinensis) has a closer genetic affinity to primates relative to rodents, and can attain ages of 8 years or older, which represents another advantage for the study of neurodegenerative diseases such as AD compared to primates. Here, we analyzed 131 AD-related genes in the Chinese tree shrew brain tissues based on protein sequence identity, positive selection, mRNA, and protein expression by comparing with those of human, rhesus monkey, and mouse. In particular, we focused on the Aβ and neurofibrillary tangles formation pathways, which are crucial to AD pathogenesis. The Chinese tree shrew had a generally higher sequence identity with human than that of mouse versus human for the AD pathway genes. There was no apparent selection on the tree shrew lineage for the AD-related genes. Moreover, expression pattern of the Aβ and neurofibrillary tangle formation pathway genes in tree shrew brain tissues resembled that of human brain tissues, with a similar aging-dependent effect. Our results provided an essential genetic basis for future AD research using the tree shrew as a viable model.
Keywords: Alzheimer Disease; Amino Acid Sequence; Animals; Biomedical Research; Disease Models, Animal; Gene Expression Profiling; Humans; Male; Mice; Tupaia

Drugs for Dementia and Excess of Hospitalization: A Longitudinal French Study. - François, Mathilde; Sicsic, Jonathan; Pelletier Fleury, Nathalie (J Alzheimers Dis, 2018)
BACKGROUND: The impact of adverse effects of drugs for dementia on the risk of hospitalization has not been much studied despite the impact of hospitalizations on cognitive decline. OBJECTIVE: To determine if the main adverse effects of cholinesterase inhibitors and memantine may be associated with excess of hospitalization and to quantify the subsequent impact on healthcare expenditures. METHODS: A representative sample of the French national health insurance beneficiaries aged 65 and older and suffering from dementia were included and followed from 2007 to 2014. Binary logit models for longitudinal data (GEE estimation technique) were used to estimate the excess of hospitalization events related to the adverse effects of anti-dementia drugs and then to derive the additional costs of hospitalizations for the public health insurance fund. RESULTS: In total, 7,668 patients were followed, generating 111,133 individual observations over the 8-year period. Treated patients were hospitalized significantly more than non-treated patients (adjusted Odd Ratio (OR) = 1.08, 95% confidence interval (95% CI) = [1.02 to 1.13], p = 0.004), mainly with cholinesterase inhibitors for cardiac (OR = 1.21, 95% CI = [1.01 to 1.46], p = 0.034) and gastrointestinal events (OR = 1.43, 95% CI = [1.01-2.05], p = 0.045), especially with rivastigmine. When extrapolated to the entire population, this corresponded to an annual additional cost of € 55,000. CONCLUSION: Prescription of antidementia drugs, more specifically rivastigmine, increases the risk of hospitalizations via their cardiac and gastrointestinal adverse effects and lead to additional health care expenditures. Even though these results must be confirmed, they may encourage cautious consideration of the balance between benefits and harms before a prescription is given.
Keywords: Aged; Aged, 80 and over; Cholinesterase Inhibitors; Dementia; Female; France; Health Expenditures; Hospitalization; Humans; Longitudinal Studies; Male; Rivastigmine

Dual Time-Point [18F]Florbetaben PET Delivers Dual Biomarker Information in Mild Cognitive Impairment and Alzheimer's Disease. - Florek, Lisa; Tiepolt, Solveig; Schroeter, Matthias L; Berrouschot, Jörg; Saur, Dorothee; Hesse, Swen; Jochimsen, Thies; Luthardt, Julia; Sattler, Bernhard; Patt, Marianne; Hoffmann, Karl-Titus; Villringer, Arno; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Current research diagnostic criteria for Alzheimer's disease (AD) and mild cognitive impairment (MCI) due to AD include biomarkers to supplement clinical testing. Recently, we demonstrated that dual time-point [18F]FBB PET is able to deliver both blood flow and amyloid-β (Aβ) load surrogates. OBJECTIVE: The aim of this study was to investigate whether these surrogates can be utilized as AD biomarkers. METHODS: 112 subjects (41 with MCI, 50 with probable/possible AD, 21 with other dementias) underwent dual time-point [18F]FBB PET. Data were visually and relative quantitatively (Herholz scores for the early and composite SUVRs for the late PET data) analyzed. RESULTS: In the early images AD-typical patterns were present in 42% /27% /33% of probable/possible AD/MCI/other dementia cases. In late [18F]FBB PET, 42% /29% /38% of probable/possible AD/ MCI/other dementia cases were Aβ-positive. 17% of the MCIs were categorized as "MCI due to AD-high likelihood", 44% of the probable ADs as "probable AD with high evidence of AD pathophysiological process" and 28% of the possible ADs as "possible AD with evidence of AD pathophysiological process". 27% of all subjects showed a positive diagnostic and progression biomarker. Herholz scores were lower (0.85±0.05 versus 0.88±0.04, p = 0.015) for probable/possible AD versus MCI. Composite late phase SUVRs were significantly higher (1.65±0.23 versus 1.15±0.17, p < 0.005) in Aβ-positive versus Aβ-negative patients. Herholz and MMSE scores were positively correlated (R = 0.30 p = 0.006). CONCLUSION: Dual time-point [18F]FBB PET provides dual biomarker information which enables to categorize MCI and AD dementia patients according to established diagnostic criteria. Thus, dual time-point [18F]FBB PET has great potential to supplement diagnostic dementia workups.

Dual-Task Gait and Alzheimer's Disease Genetic Risk in Cognitively Normal Adults: A Pilot Study. - Whitson, Heather E; Potter, Guy G; Feld, Jody A; Plassman, Brenda L; Reynolds, Kelly; Sloane, Richard; Welsh-Bohmer, Kathleen A (J Alzheimers Dis, 2018)
BACKGROUND: Dual-task paradigms, in which an individual performs tasks separately and then concurrently, often demonstrate that people with neurodegenerative disorders experience more dual-task interference, defined as worse performance in the dual-task condition compared to the single-task condition. OBJECTIVE: To examine how gait-cognition dual-task performance differs between cognitively normal older adults with and without an APOE ɛ4 allele. METHODS: Twenty-nine individuals ages 60 to 72 with normal cognition completed a dual-task protocol in which walking and cognitive tasks (executive function, memory) were performed separately and concurrently. Fourteen participants carried APOE ɛ4 alleles (ɛ3/ɛ4 or ɛ2/ɛ4); fifteen had APOE genotypes (ɛ2/ɛ2, ɛ2/ɛ3, or ɛ3/ɛ3) associated with lower risk of Alzheimer's disease (AD). RESULTS: The two risk groups did not differ by age, sex, race, education, or gait or cognitive measures under single-task conditions. Compared to low risk participants, APOE ɛ4 carriers tended to exhibit greater dual-task interference. Both the memory and executive function tasks resulted in dual-task interference on gait, but effect sizes for a group difference were larger when the cognitive task was executive function. In the dual-task protocol that combined walking and the executive function task, effect sizes for group difference in gait interference were larger (0.62- 0.70) than for cognitive interference (0.45- 0.47). DISCUSSION: Dual-task paradigms may reveal subtle changes in brain function in asymptomatic individuals at heightened risk of AD.

Early Intervention with a Multi-Ingredient Dietary Supplement Improves Mood and Spatial Memory in a Triple Transgenic Mouse Model of Alzheimer's Disease. - Hutton, Craig P; Lemon, Jennifer A; Sakic, Boris; Rollo, C David; Boreham, Douglas R; Fahnestock, Margaret; Wojtowicz, J Martin; Becker, Suzanna (J Alzheimers Dis, 2018)
The increasing global burden of Alzheimer's disease (AD) and failure of conventional treatments to stop neurodegeneration necessitates an alternative approach. Evidence of inflammation, mitochondrial dysfunction, and oxidative stress prior to the accumulation of amyloid-β in the prodromal stage of AD (mild cognitive impairment; MCI) suggests that early interventions which counteract these features, such as dietary supplements, may ameliorate the onset of MCI-like behavioral symptoms. We administered a polyphenol-containing multiple ingredient dietary supplement (MDS), or vehicle, to both sexes of triple transgenic (3xTg-AD) mice and wildtype mice for 2 months from 2-4 months of age. We hypothesized that the MDS would preserve spatial learning, which is known to be impaired in untreated 3xTg-AD mice by 4 months of age. Behavioral phenotyping of animals was done at 1-2 and 3-4 months of age using a comprehensive battery of tests. As previously reported in males, both sexes of 3xTg-AD mice exhibited increased anxiety-like behavior at 1-2 months of age, prior to deficits in learning and memory, which did not appear until 3-4 months of age. The MDS did not reduce this anxiety or prevent impairments in novel object recognition (both sexes) or on the water maze probe trial (females only). Strikingly, the MDS specifically prevented 3xTg-AD mice (both sexes) from developing impairments (exhibited by untreated 3xTg-AD controls) in working memory and spatial learning. The MDS also increased sucrose preference, an indicator of hedonic tone. These data show that the MDS can prevent some, but not all, psychopathology in an AD model.

Economic Burden, Mortality, and Institutionalization in Patients Newly Diagnosed with Alzheimer's Disease. - Black, Christopher M; Fillit, Howard; Xie, Lin; Hu, Xiaohan; Kariburyo, M Furaha; Ambegaonkar, Baishali M; Baser, Onur; Yuce, Huseyin; Khandker, Rezaul K (J Alzheimers Dis, 2018)
BACKGROUND: Current information is scarce regarding comorbid conditions, treatment, survival, institutionalization, and health care utilization for Alzheimer's disease (AD) patients. OBJECTIVES: Compare all-cause mortality, rate of institutionalization, and economic burden between treated and untreated newly-diagnosed AD patients. METHODS: Patients aged 65-100 years with ≥1 primary or ≥2 secondary AD diagnoses (ICD-9-CM:331.0] with continuous medical and pharmacy benefits for ≥12 months pre-index and ≥6 months post-index date (first AD diagnosis date) were identified from Medicare fee-for-service claims 01JAN2011-30JUN2014. Patients with AD treatment claims or AD/AD-related dementia diagnosis during the pre-index period were excluded. Patients were assigned to treated and untreated cohorts based on AD treatment received post-index date. Total 8,995 newly-diagnosed AD patients were identified; 4,037 (44.8%) were assigned to the treated cohort. Time-to-death and institutionalization were assessed using Cox regression. To compare health care costs and utilizations, 1 : 1 propensity score matching (PSM) was used. RESULTS: Untreated patients were older (83.85 versus 81.44 years; p < 0.0001), with more severe comorbidities (mean Charlson comorbidity index: 3.54 versus 3.22; p < 0.0001). After covariate adjustment, treated patients were less likely to die (hazard ratio[HR] = 0.69; p < 0.0001) and were associated with 20% lower risk of institutionalization (HR = 0.801; p = 0.0003). After PSM, treated AD patients were less likely to have hospice visits (3.25% versus 9.45%; p < 0.0001), and incurred lower annual all-cause costs ($25,828 versus $30,110; p = 0.0162). CONCLUSION: After controlling for comorbidities, treated AD patients have better survival, lower institutionalization, and sometimes fewer resource utilizations, suggesting that treatment and improved care management could be beneficial for newly-diagnosed AD patients from economic and clinical perspectives.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Comorbidity; Cost of Illness; Female; Humans; Institutionalization; Male; Neuropsychological Tests

Effect of Fluvoxamine on Amyloid-β Peptide Generation and Memory. - Kim, Woojin Scott; Fu, YuHong; Dobson-Stone, Carol; Hsiao, Jen-Hsiang T; Shang, Kani; Hallupp, Marianne; Schofield, Peter R; Garner, Brett; Karl, Tim; Kwok, John B J (J Alzheimers Dis, 2018)
Alzheimer's disease is characterized by abnormal amyloid-β (Aβ) peptide accumulation beginning decades before symptom onset. An effective prophylactic treatment aimed at arresting the amyloidogenic pathway would therefore need to be initiated prior to the occurrence of Aβ pathology. The SIGMAR1 gene encodes a molecular chaperone that modulates processing of the amyloid-β protein precursor (AβPP). Fluvoxamine is a selective serotonin reuptake inhibitor and a potent SIGMAR1 agonist. We therefore hypothesized that fluvoxamine treatment would reduce Aβ production and improve cognition. We firstly investigated the impact of SIGMAR1 on AβPP processing, and found that overexpression and knockdown of SIGMAR1 significantly affected γ-secretase activity in SK-N-MC neuronal cells. We then tested the impact of fluvoxamine on Aβ production in an amyloidogenic cell model, and found that fluvoxamine significantly reduced Aβ production by inhibiting γ-secretase activity. Finally, we assessed the efficacy of long-term treatment (i.e., ∼8 months) of 10 mg/kg/day fluvoxamine in the J20 amyloidogenic mouse model; the treatment was initiated prior to the occurrence of predicted Aβ pathology. Physical examination of the animals revealed no overt pathology or change in weight. We conducted a series of behavioral tests to assess learning and memory, and found that the fluvoxamine treatment significantly improved memory function as measured by novel object recognition task. Two other tests revealed no significant change in memory function. In conclusion, fluvoxamine has a clear impact on γ-secretase activity and AβPP processing to generate Aβ, and may have a protective effect on cognition in the J20 mice.

Effectiveness of a Personalized Brain-Computer Interface System for Cognitive Training in Healthy Elderly: A Randomized Controlled Trial. - Yeo, Si Ning; Lee, Tih Shih; Sng, Wei Theng; Heo, Min Quan; Bautista, Dianne; Cheung, Yin Bun; Zhang, Hai Hong; Wang, Chuanchu; Chin, Zheng Yang; Feng, Lei; Zhou, Juan; Chong, Mei Sian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Cognitive training has been demonstrated to improve cognitive performance in older adults. To date, no study has explored personalized training that targets the brain activity of each individual. OBJECTIVE: This is the first large-scale trial that examines the usefulness of personalized neurofeedback cognitive training. METHODS: We conducted a randomized-controlled trial with participants who were 60-80 years old, with Clinical Dementia Rating (CDR) score of 0-0.5, Mini-Mental State Examination (MMSE) score of 24 and above, and with no neuropsychiatric diagnosis. Participants were randomly assigned to the Intervention or Waitlist-Control group. The training system, BRAINMEM, has attention, working memory, and delayed recall game components. The intervention schedule comprised 24 sessions over eight weeks and three monthly booster sessions. The primary outcome was the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) total score after the 24-session training. RESULTS: There were no significant between-subjects differences in overall cognitive performance post-intervention. However, a sex moderation effect (p = 0.014) was present. Men in the intervention group performed better than those in the waitlist group (mean difference, +4.03 (95% CI 0.1 to 8.0), p = 0.046. Among females, however, both waitlist-control and intervention participants improved from baseline, although the between-group difference in improvement did not reach significance. BRAINMEM also received positive appraisal and intervention adherence from the participants. CONCLUSION: A personalized neurofeedback intervention is potentially feasible for use in cognitive training for older males. The sex moderation effect warrants further investigation and highlights the importance of taking sex into account during cognitive training.

Effects of Physical Exercise on Alzheimer's Disease Biomarkers: A Systematic Review of Intervention Studies. - Frederiksen, Kristian Steen; Gjerum, Le; Waldemar, Gunhild; Hasselbalch, Steen Gregers (J Alzheimers Dis, 2018)
Physical exercise may be an important adjunct to pharmacological treatment of Alzheimer's disease (AD). Animal studies indicate that exercise may be disease modifying through several mechanisms including reduction of AD pathology. We carried out a systematic review of intervention studies of physical exercise with hippocampal volume (on MRI), amyloid-β, total tau, phosphorylated tau in cerebrospinal fluid (CSF), 18F-FDG-PET or amyloid PET as outcome measures in healthy subjects, patients with subjective memory complaints, mild cognitive impairment, or AD. We identified a total of 8 studies of which 6 investigated the effects of exercise on hippocampal volume in healthy subjects and 1 on CSF biomarkers and 1 on hippocampal volume in AD, and none investigating the remaining outcome measures or patient groups. Methodological quality of identified studies was generally low. One study found a detrimental effect on hippocampal volume and one found a positive effect, whereas the remaining studies did not find an effect of exercise on outcome measures. The present systematic study identified a relatively small number of studies, which did not support an effect of exercise on hippocampal volume. Methodological issues such small to moderate sample sizes and inadequate ramdomization procedures further limits conclusions. Our findings highlight the difficulties in conducting high quality studies of exercise and further studies are needed before definite conclusions may be reached.
Keywords: Alzheimer Disease; Biomarkers; Exercise; Hippocampus; Humans; Outcome Assessment (Health Care); Physical Therapy Modalities

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

The Ethyl Acetate Extract of Leaves of Ugni molinae Turcz. Improves Neuropathological Hallmarks of Alzheimer's Disease in Female APPswe/PS1dE9 Mice Fed with a High Fat Diet. - Jara-Moreno, Daniela; Castro-Torres, Rubn D; Ettcheto, Miren; Auladell, Carme; Kogan, Marcelo J; Folch, Jaume; Verdaguer, Ester; Cano, Amanda; Busquets, Oriol; Delporte, Carla; Camins, Antoni (J Alzheimers Dis, 2018)
The most common type of dementia is Alzheimer's disease (AD), a progressive neurodegenerative disease characterized by impairment in cognitive performance in aged individuals. Currently, there is no effective pharmacological treatment that cures the disease due to the lack of knowledge on the actual mechanisms involved in its pathogenesis. In the last decades, the amyloidogenic hypothesis has been the most studied theory trying to explain the origin of AD, yet it does not address all the concerns relating to its development. In the present study, a possible new preclinical treatment of AD was evaluated using the ethyl acetate extract (EAE) of leaves of Ugni molinae Turcz. (synonym Myrtus ugni Molina Family Myrtacea). The effects were assessed on female transgenic mice from a preclinical model of familial AD (APPswe/PS1dE9) combined with a high fat diet. This preclinical model was selected due to the already available experimental and observational data proving the relationship between obesity, gender, metabolic stress, and cognitive dysfunction; related to characteristics of sporadic AD. According to chemical analyses, EAE would contain polyphenols such as tannins, flavonoid derivatives, and phenolic acids, as well as pentacyclic triterpenoids that exhibit neuroprotective, anti-inflammatory, and antioxidant effects. In addition, the treatment evidenced its capacity to prevent deterioration of memory capacity and reduction of progression speed of AD neuropathology.

Examining the Relationship between Trace Lithium in Drinking Water and the Rising Rates of Age-Adjusted Alzheimer's Disease Mortality in Texas. - Fajardo, Val Andrew; Fajardo, Val Andrei; LeBlanc, Paul J; MacPherson, Rebecca E K (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mortality rates have steadily increased over time. Lithium, the current gold standard treatment for bipolar disorder, can exert neuroprotective effects against AD. OBJECTIVE: We examined the relationship between trace levels of lithium in drinking water and changes in AD mortality across several Texas counties. METHODS: 6,180 water samples from public wells since 2007 were obtained and averaged for 234 of 254 Texas counties. Changes in AD mortality rates were calculated by subtracting aggregated age-adjusted mortality rates obtained between 2000-2006 from those obtained between 2009-2015. Using aggregated rates maximized the number of counties with reliable mortality data. Correlational analyses between average lithium concentrations and changes in AD mortality were performed while also adjusting for gender, race, education, rural living, air pollution, physical inactivity, obesity, and type 2 diabetes. RESULTS: Age-adjusted AD mortality rate was significantly increased over time (+27%, p < 0.001). Changes in AD mortality were negatively correlated with trace lithium levels (p = 0.01, r = -0.20), and statistical significance was maintained after controlling for most risk factors except for physical inactivity, obesity, and type 2 diabetes. Furthermore, the prevalence of obesity and type 2 diabetes positively correlated with changes in AD mortality (p = 0.01 and 0.03, respectively), but also negatively correlated with trace lithium in drinking water (p = 0.05 and <0.0001, respectively). CONCLUSION: Trace lithium in water is negatively linked with changes in AD mortality, as well as obesity and type 2 diabetes, which are important risk factors for AD.
Keywords: Adult; Age Factors; Alzheimer Disease; Drinking Water; Female; Humans; Lithium; Longitudinal Studies; Male; Obesity; Prevalence; Risk Factors; Statistics as Topic; Texas; Young Adult

Exercise Training on Locomotion in Patients with Alzheimer's Disease: A Feasibility Study. - Pedrinolla, Anna; Venturelli, Massimo; Fonte, Cristina; Munari, Daniele; Benetti, Maria Vittoria; Rudi, Doriana; Tamburin, Stefano; Muti, Ettore; Zanolla, Luisa; Smania, Nicola; Schena, Federico (J Alzheimers Dis, 2018)
BACKGROUND: Although current literature has shown that patients with Alzheimer's disease (AD) have worse locomotion compared with healthy counterparts, no studies have focused on the efficacy of exercise training in improving gait abnormalities including biomechanics and metabolic aspects, in this population. OBJECTIVE: To verify the effectiveness of exercise training (ET) on gait parameters (i.e., speed, step and stride length, single and double support, and energy cost of walking (Cw)) in patients with AD with respect to a standard cognitive treatment (CT). METHODS: In this study, we included a small portion of data belonging to a larger study (ClinicalTrials.gov number, NCT03034746). Patients with AD (Mini-Mental State Examination 22±5) were included in the study. Gait parameters and Cw were assessed at baseline and after 6 months (72 treatment sessions) of treatment. ET included 90 min of aerobic and strength training. CT included 90 min of cognitive stimuli. RESULTS: The 16 patients assigned to ET exhibited significant improvement of Cw (-0.9±0.1 J/kg·m-1), while differences in gait parameters were negligible. The effect on gait parameters were undetectable in the 18 patients assigned to CT (-0.2±0.5 J/kg·m-1). CONCLUSIONS: Data from this study showed that ET program seems effective in improving Cw in patients with AD. Interestingly, the positive effect of ET on Cw was not coupled with ameliorations of patient's gait parameters, suggesting that the gain of metabolic aspects of locomotion were the main factors responsible for this positive result.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomechanical Phenomena; Exercise Test; Exercise Therapy; Feasibility Studies; Female; Gait; Humans; Italy; Male; Single-Blind Method

Exploring the Profile of Incidental Memory in Patients with Amnestic Mild Cognitive Impairment and Mild Alzheimer's Disease. - Kontaxopoulou, Dionysia; Beratis, Ion N; Fragkiadaki, Stella; Pavlou, Dimosthenis; Andronas, Nikos; Yannis, George; Economou, Alexandra; Papanicolaou, Andrew C; Papageorgiou, Sokratis G (J Alzheimers Dis, 2018)
Incidental memory can be defined as the ability to acquire information unintentionally. The present study investigated incidental memory performance in amnestic mild cognitive impairment (aMCI) and mild Alzheimer's disease (AD) patients; additionally, hippocampal atrophy between groupswas examined. Twenty-nine aMCI patients (14 with hippocampal atrophy, measured by the Medial Temporal Lobe Atrophy scale), 15 mild AD patients, and 20 cognitively intact individuals underwent a detailed medical and neuropsychological assessment examining intentional memory, using the Hopkins Verbal Learning Test-Revised and the Brief Visuospatial Memory Test. Participants first took part in a driving simulator experiment, followed by an unexpected incidental memory questionnaire referring to elements related to the driving simulation. The mild AD group performed worse than the aMCI group and the control group both in incidental and intentional memory tasks, whereas the aMCI group differed significantly from the control group only in the intentional memory tasks. The incidental recognition memory task was the only measure that differed between aMCI patients with and without hippocampal atrophy. Moreover, incidental memory tasks were the only measures that correlated significantly with both left and right hippocampal atrophy. The current findings indicate that incidental memory testing may provide potentially useful information for detecting aMCI patients with greater hippocampal atrophy, who may be considered at higher risk of developing dementia due to AD.

FDDNP-PET Tau Brain Protein Binding Patterns in Military Personnel with Suspected Chronic Traumatic Encephalopathy1. - Chen, Stephen T; Siddarth, Prabha; Merrill, David A; Martinez, Jacqueline; D Emerson, Natacha; Liu, Jie; Wong, Koon-Pong; Satyamurthy, Nagichettiar; Giza, Christopher C; Huang, Sung-Cheng; Fitzsimmons, Robert P; Bailes, Julian; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Our group has shown that in vivo tau brain binding patterns from FDDNP-PET scans in retired professional football players with suspected chronic traumatic encephalopathy differ from those of tau and amyloid aggregate binding observed in Alzheimer's disease (AD) patients and cognitively-intact controls. OBJECTIVE: To compare these findings with those from military personnel with histories of mild traumatic brain injury(mTBI). METHODS: FDDNP-PET brain scans were compared among 7 military personnel and 15 retired players with mTBI histories and cognitive and/or mood symptoms, 24 AD patients, and 28 cognitively-intact controls. Nonparametric ANCOVAs with Tukey-Kramer adjusted post-hoc comparisons were used to test for significant differences in regional FDDNP binding among subject groups. RESULTS: FDDNP brain binding was higher in military personnel compared to controls in the amygdala, midbrain, medial thalamus, pons, frontal and anterior and posterior cingulate regions (p < 0.01-0.0001). Binding patterns in the military personnel were similar to those of the players except for the amygdala and striatum (binding higher in players; p = 0.02-0.003). Compared with the AD group, the military personnel showed higher binding in the midbrain (p = 0.0008) and pons (p = 0.002) and lower binding in the medial temporal, lateral temporal, and parietal regions (all p = 0.02). CONCLUSION: This first study of in vivo tau and amyloid brain signals in military personnel with histories of mTBI shows binding patterns similar to those of retired football players and distinct from the binding patterns in AD and normal aging, suggesting the potential value of FDDNP-PET for early detection and treatment monitoring in varied at-risk populations.

Forgetting Rate on the Recency Portion of a Word List Differentiates Mild to Moderate Alzheimer's Disease from Other Forms of Dementi. - Turchetta, Chiara Stella; Perri, Roberta; Fadda, Lucia; Caruso, Giulia; De Simone, Maria Stefania; Caltagirone, Carlo; Carlesimo, Giovanni Augusto (J Alzheimers Dis, 2018)
Patients with Alzheimer's disease (AD) demonstrate a disproportionately larger forgetting rate in episodic memory tasks. Previous studies documented that, in comparison with healthy controls, the increased forgetting manifested by AD patients in word list recall tasks is confined to the recency portion of the list with normal forgetting rates on the primacy and mid-list portions. In this study we compared the primacy, mid-list, and recency ratios, obtained by dividing the immediate and delayed recall of words in position 1-4, 5-11, and 12-15 of a 15-word list, in different groups of demented patients, i.e., AD, frontal variant of frontotemporal dementia (fvFTD), Lewy body disease (LBD), subcortical ischemic vascular dementia (SIVD), and a group of normal controls (NC). The aim was to investigate whether the above reported forgetting pattern would differentiate AD performance from that of other dementia groups. Results of the statistical analysis showed that only the recency ratio differentiated AD from patients in the other dementia groups. Consistently, hierarchical logistic regression analyses demonstrated that the recency ratio discriminated between AD patients and individuals affected by other forms of dementia. In particular, the discrimination power was high in differentiating AD from fvFTD patients but was less accurate in differentiating AD from LBD and SIVD patients. We assume that the increased forgetting in AD patients is due to a deficit in memory consolidation mechanisms (specific to AD) that prevent the terminal items in a list from being transferred from a temporary short-term memory store to a stable long-term memory store.

Free Heme and Amyloid-β: A Fatal Liaison in Alzheimer's Disease. - Chiziane, Elisabeth; Telemann, Henriette; Krueger, Martin; Adler, Juliane; Arnhold, Jürgen; Alia, A; Flemmig, Jörg (J Alzheimers Dis, 2018)
While the etiology of Alzheimer's disease (AD) is still unknown, an increased formation of amyloid-β (Aβ) peptide and oxidative processes are major pathological mechanism of the disease. The interaction of Aβ with free heme leads to the formation of peroxidase-active Aβ-heme complexes. However, enzyme-kinetic data and systematic mutational studies are still missing. These aspects were addressed in this study to evaluate the role of Aβ-heme complexes in AD. The enzyme-kinetic measurements showed peroxidase-specific pH- and H2O2-dependencies. In addition, the enzymatic activity of Aβ-heme complexes constantly increased at higher peptide excess. Moreover, the role of the Aβ sequence for the named enzymatic activity was tested, depicting human-specific R5, Y10, and H13 as essential amino acids. Also by studying Y10 as an endogenous peroxidase substrate for Aβ-heme complexes, ratio-specific effects were observed, showing an optimal dityrosine formation at an about 40-fold peptide excess. As dityrosine formation promotes Aβ fibrillation while free heme disturbs protein aggregation, we also investigated the effect of Aβ-heme complex-derived peroxidase activity on the formation of Aβ fibrils. The fluorescence measurements showed a different fibrillation behavior at strong peroxidase activity, leading also to altered fibril morphologies. The latter was detected by electron microscopy. As illustrated by selected in vivo measurements on a mouse model of AD, the disease is also characterized by Aβ-derived microvessel destructions and hemolytic processes. Thus, thrombo-hemorrhagic events are discussed as a source for free heme in brain tissue. In summary, we suggest the formation and enzymatic activity of Aβ-heme complexes as pathological key features of AD.
Keywords: Alzheimer Disease; Amino Acid Sequence; Amyloid; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Heme; Humans; Hydrogen Peroxide; Mice; Mice, Transgenic; Oxidation-Reduction; Peptide Fragments; Peroxidases

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

Frontotemporal Dementia Misdiagnosed for Post-Treatment Lyme Disease Syndrome or vice versa? A Treviso Dementia (TREDEM) Registry Case Report. - Di Battista, Maria Elena; Dell'Acqua, Carola; Baroni, Luciana; Fenoglio, Chiara; Galimberti, Daniela; Gallucci, Maurizio (J Alzheimers Dis, 2018)
We describe the case of a 61-year-old woman diagnosed with Borreliosis at the age of 57. Subsequently, the patient developed depression, anxiety, and behavioral disturbances. A lumbar puncture excluded the condition of Neuroborreliosis. The diagnostic workup included: an MRI scan, a 18F-FDG PET, a 123I-ioflupane-SPECT, an amyloid-β PET, a specific genetic analysis, and a neuropsychological evaluation. Based on our investigation, the patient was diagnosed with probable behavioral-frontotemporal dementia (bvFTD), whereas in the previous years, the patient had been considered firstly as a case of Post-Treatment-Lyme Disease and, secondly, a psychiatric patient. We believe that, in the present case, such initial symptoms of Borrelia infection may have superimposed on those of bvFTD rather than playing as a contributory cause.

Generation and Partial Characterization of Rabbit Monoclonal Antibody to Pyroglutamate Amyloid-β3-42 (pE3-Aβ). - Mehta, Pankaj D; Patrick, Bruce A; Barshatzky, Marc; Mehta, Sangita P; Frackowiak, Janusz; Mazur-Kolecka, Bozena; Wegiel, Jerzy; Wisniewski, Thomas; Miller, David L (J Alzheimers Dis, 2018)
N-terminally truncated pyroglutamate amyloid-β (Aβ) peptide starting at position 3 represents a significant fraction of Aβ peptides (pE3-Aβ) in amyloid plaques of postmortem brains from patients with Alzheimer's disease (AD) and older persons with Down syndrome (DS). Studies in transgenic mouse models of AD also showed that pE3-Aβ is a major component of plaques, and mouse monoclonal antibody to pE3-Aβ appears to be a desirable therapeutic agent for AD. Since small peptides do not typically elicit a good immune response in mice, but do so favorably in rabbits, our aims were to generate and partially characterize a rabbit monoclonal antibody (RabmAb) to pE3-Aβ. The generated RabmAb was found to be specific for pE3-Aβ, since it showed no reactivity with Aβ16, Aβ40, Aβ42, Aβ3-11, and pE11-17 Aβ peptides in an enzyme linked immunosorbent assay (ELISA). The isotype of the antibody was found to be IgG class. The antibody possesses high affinity to pE3-Aβ with dissociation constant (KD) for the antibody of 1 nM. The epitope of the antibody lies within the sequence of pE3-FRHD. In dot blotting, the optimal detection of pE3-Aβ was at an antibody concentration of 0.5 μg/ml. The threshold of pE3-Aβ detection was 2 fmol. The antibody was sensitive enough to detect 10 pg/ml of pE3-Aβ in sandwich ELISA. pE3-Aβ was detected in AD and DS brain extracts in ELISA and immunoblotting. Immunohistological studies showed immunolabeling of plaques and blood vessels in brains from patients with AD, and DS showing AD pathology. Thus, the antibody can be widely applied in AD and DS research, and therapeutic applications.

Genetic Risk for Age-Related Cognitive Impairment Does Not Predict Cognitive Performance in Middle Age. - Korthauer, Laura E; Awe, Elizabeth; Frahmand, Marijam; Driscoll, Ira (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by memory loss and executive dysfunction, which correspond to structural changes to the medial temporal lobes (MTL) and prefrontal cortex (PFC), respectively. Given the overlap in cognitive deficits between healthy aging and the earliest stages of AD, early detection of AD remains a challenge. The goal of the present study was to study MTL- and PFC-dependent cognitive functioning in middle-aged individuals at genetic risk for AD or cognitive impairment who do not currently manifest any clinical symptoms. Participants (N = 150; aged 40-60 years) underwent genotyping of 47 single nucleotide polymorphisms (SNPs) in six genes previously associated with memory or executive functioning: APOE, SORL1, BDNF, TOMM40, KIBRA, and COMT. They completed two MTL-dependent tasks, the virtual Morris Water Task (vMWT) and transverse patterning discriminations task (TPDT), and the PFC-dependent reversal learning task. Although age was associated with poorer performance on the vMWT and TPDT within this middle-aged sample, there were no genotype-associated differences in cognitive performance. Although the vMWT and TPDT may be sensitive to age-related changes in cognition, carriers of APOE, SORL1, BDNF, TOMM40, KIBRA, and COMT risk alleles do not exhibit alteration in MTL- and PFC-dependent functioning in middle age compared to non-carriers.

Genotyping of the Alzheimer's Disease Genome-Wide Association Study Index Single Nucleotide Polymorphisms in the Brains for Dementia Research Cohort. - Brookes, Keeley J; McConnell, George; Williams, Kirsty; Chaudhury, Sultan; Madhan, Gaganjit; Patel, Tulsi; Turley, Christopher; Guetta-Baranes, Tamar; Bras, Jose; Guerreiro, Rita; Hardy, John; Francis, Paul T; et al. (J Alzheimers Dis, 2018)
The Brains for Dementia Research project is a recently established longitudinal cohort which aims to provide brain tissue for research purposes from neuropathologically defined samples. Here we present the findings from our analysis on the 19 established GWAS index SNPs for Alzheimer's disease, in order to demonstrate if the BDR sample also displays association to these variants. A highly significant association of the APOEɛ4 allele was identified (p = 3.99×10-12). Association tests for the 19 GWAS SNPs found that although no SNPs survive multiple testing, nominal significant findings were detected and concordance with the Lambert et al. GWAS meta-analysis was observed.

Geographical Distribution and Diversity of Gut Microbial NADH:Ubiquinone Oxidoreductase Sequence Associated with Alzheimer's Disease. - Paley, Elena L; Merkulova-Rainon, Tatiana; Faynboym, Aleksandr; Shestopalov, Valery I; Aksenoff, Igor (J Alzheimers Dis, 2018)
Earlier we reported induction of neurotoxicity and neurodegeneration by tryptophan metabolites that link the metabolic alterations to Alzheimer's disease (AD). Tryptophan is a product of Shikimate pathway (SP). Human cells lack SP, which is found in human gut bacteria exclusively using SP to produce aromatic amino acids (AAA). This study is a first attempt toward gene-targeted analysis of human gut microbiota in AD fecal samples. The oligonucleotide primers newly-designed for this work target SP-AAA in environmental bacteria associated with human activity. Using polymerase chain reaction (PCR), we found unique gut bacterial sequence in most AD patients (18 of 20), albeit rarely in controls (1 of 13). Cloning and sequencing AD-associated PCR products (ADPP) enables identification of Na(+)-transporting NADH: Ubiquinone reductase (NQR) in Clostridium sp. The ADPP of unrelated AD patients possess near identical sequences. NQR substrate, ubiquinone is a SP product and human neuroprotectant. A deficit in ubiquinone has been determined in a number of neuromuscular and neurodegenerative disorders. Antibacterial therapy prompted an ADPP reduction in an ADPP-positive control person who was later diagnosed with AD-dementia. We explored the gut microbiome databases and uncovered a sequence similarity (up to 97%) between ADPP and some healthy individuals from different geographical locations. Importantly, our main finding of the significant difference in the gut microbial genotypes between the AD and control human populations is a breakthrough.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Anti-Bacterial Agents; Biological Transport; DNA Primers; Electron Transport Complex I; Feces; Female; Gastrointestinal Microbiome; Geography; Host-Pathogen Interactions; Humans; Male; Middle Aged; Sequence Analysis, DNA; Young Adult

Ginkgo biloba Extract EGb 761 and Its Specific Components Elicit Protective Protein Clearance Through the Autophagy-Lysosomal Pathway in Tau-Transgenic Mice and Cultured Neurons. - Qin, Yiren; Zhang, Yu; Tomic, Inge; Hao, Wenlin; Menger, Michael D; Liu, Chunfeng; Fassbender, Klaus; Liu, Yang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease pathologically characterized by extracellular amyloid-β (Aβ) deposits and intracellular neurofibrillary tangles (NFT) in many brain regions. NFT are primarily composed of hyperphosphorylated tau protein (p-Tau). Aβ and p-Tau are two major pathogenic molecules with tau acting downstream to Aβ to induce neuronal degeneration. In this study, we investigated whether Ginkgo biloba extract EGb 761 reduces cerebral p-Tau level and prevents AD pathogenesis. Human P301S tau mutant-transgenic mice were fed with EGb 761, added to the regular diet for 2 or 5 months. We observed that treatment with EGb 761 for 5 months significantly improved the cognitive function of mice, attenuated the loss of synaptophysin and recovered the phosphorylation of CREB in the mouse brain. Treatment with EGb 761 for 5 but not 2 months also decreased p-Tau protein amount and shifted microglial pro-inflammatory to anti-inflammatory activation in the brain. As potential therapeutic mechanisms, we demonstrated that treatment with EGb 761, especially the components of ginkgolide A, bilobalide, and flavonoids, but not with purified ginkgolide B or C, increased autophagic activity and degradation of p-Tau in lysosomes of neurons. Inhibiting ATG5 function or treating cells with Bafilomycin B1 abolished EGb 761-enhanced degradation of p-Tau in cultured neurons. Additionally, we observed that 5- instead of 2-month-treatment with EGb 761 inhibited the activity of p38-MAPK and GSK-3β. Therefore, long-term treatment with Ginkgo biloba extract EGb 761, a clinically available and well-tolerated herbal medication, ameliorates AD pathology through mechanisms against multiple AD pathogenic processes.

Gut Microbiome is Altered in Patients with Alzheimer's Disease. - Zhuang, Zhen-Qian; Shen, Lin-Lin; Li, Wei-Wei; Fu, Xue; Zeng, Fan; Gui, Li; Lü, Yang; Cai, Min; Zhu, Chi; Tan, Yin-Ling; Zheng, Peng; Li, Hui-Yun; et al. (J Alzheimers Dis, 2018)
Previous studies suggest that gut microbiota is associated with neuropsychiatric disorders, such as Parkinson's disease, amyotrophic lateral sclerosis, and depression. However, whether the composition and diversity of gut microbiota is altered in patients with Alzheimer's disease (AD) remain largely unknown. In the present study, we collected fecal samples from 43 AD patients and 43 age- and gender-matched cognitively normal controls. 16S ribosomal RNA sequencing technique was used to analyze the microbiota composition in feces. The composition of gut microbiota was different between the two groups. Several bacteria taxa in AD patients were different from those in controls at taxonomic levels, such as Bacteroides, Actinobacteria, Ruminococcus, Lachnospiraceae, and Selenomonadales. Our findings suggest that gut microbiota is altered in AD patients and may be involved in the pathogenesis of AD.

The GWAS Risk Genes for Depression May Be Actively Involved in Alzheimer's Disease. - Ni, Hua; Xu, Min; Zhan, Gui-Lai; Fan, Yu; Zhou, Hejiang; Jiang, Hong-Yan; Lu, Wei-Hong; Tan, Liwen; Zhang, Deng-Feng; Yao, Yong-Gang; Zhang, Chen (J Alzheimers Dis, 2018)
Depression is one of the most frequent psychiatric symptoms observed in people during the development of Alzheimer's disease (AD). We hypothesized that genetic factors conferring risk of depression might affect AD development. In this study, we screened 31 genes, which were located in 19 risk loci for major depressive disorder (MDD) identified by two recent large genome-wide association studies (GWAS), in AD patients at the genomic and transcriptomic levels. Association analysis of common variants was performed by using summary statistics of the International Genomics of Alzheimer's Project (IGAP), and association analysis of rare variants was conducted by sequencing the entire coding region of the 31 MDD risk genes in 107 Han Chinese patients with early-onset and/or familial AD. We also quantified the mRNA expression alterations of these MDD risk genes in brain tissues of AD patients and AD mouse models, followed by protein-protein interaction network prediction to show their potential effects in AD pathways. We found that common and rare variants of L3MBTL2 were significantly associated with AD. mRNA expression levels of 18 MDD risk genes, in particular SORCS3 and OAT, were differentially expressed in AD brain tissues. 13 MDD risk genes were predicted to physically interact with core AD genes. The involvement of HACE1, NEGR1, and SLC6A15 in AD was supported by convergent lines of evidence. Taken together, our results showed that MDD risk genes might play an active role in AD pathology and supported the notion that depression might be the "common cold" of psychiatry.

The Heritability of Frontotemporal Lobar Degeneration: Validation of Pedigree Classification Criteria in a Northern Italy Cohort. - Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Zanetti, Orazio; Binetti, Giuliano; Ghidoni, Roberta; Benussi, Luisa (J Alzheimers Dis, 2018)
A large portion of frontotemporal lobar degeneration (FTLD) patients has a family history of disease and the presence of a pathogenic mutation confirms the clinical diagnosis. Recently, standardized criteria to evaluate FTLD pedigree, based on first- and second-degree affected relatives, their age at onset, and clinical phenotype, were proposed and validated in an American cohort. Herein we applied these criteria to 402 Italian FTLD pedigrees and assessed mutation frequencies in GRN, C9orf72, and MAPT genes with the aim of validating these criteria. Moreover, we evaluated whether genetic counseling requests reflect the estimated family risk. 12.4% of pedigrees had high family history, 6.5% medium, 15.4% low; 39% were apparent sporadic cases and 26.6% had family history of unknown significance. Mutations frequencies were in line with the categorization proposed: the highest rate was found in the most at-risk families (74%) and decreased in other categories (medium: 15.4%; low: 9.7%; sporadic: 1.3%). Mutation carriers with unknown family history (5.6%) were mostly early-onset patients. Detected mutation frequency was comparable with the US-cohort (13.7%), but mutations distribution among genes was different, with higher frequency of GRN mutations (9.4%) in our cohort. An elevated proportion of FTLD patients belonging to "high risk" pedigrees asked for genetic counseling (42%); requests decreased according to the estimated family risk (medium: 26.9%; low: 17.7%; sporadic: 5.1%). In conclusion, the proposed pedigree classification criteria, herein further validated, should be incorporated in the FTLD diagnostic work-up. Moreover, our data suggest to extend genetic screening to early-onset patients with unknown family history.
Keywords: Age of Onset; Aged; C9orf72 Protein; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Middle Aged; Mutation; Pedigree; Progranulins; tau Proteins

Hippocampal Stratum Radiatum, Lacunosum, and Moleculare Sparing in Mild Cognitive Impairment. - Su, Li; Hayes, Lawrence; Soteriades, Soteris; Williams, Guy; Brain, Susannah A E; Firbank, Michael J; Longoni, Giulia; Arnold, Robert J; Rowe, James B; O'Brien, John T (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is associated with atrophy in entorhinal cortex (ERC), the hippocampus, and its subfields Cornu Ammonis 1 (CA1) and subiculum, which predict conversion from mild cognitive impairment (MCI) to clinical AD. The stratum radiatum, lacunosum, and moleculare (SRLM) are also important gateways involving ERC and CA1, which are affected by early AD pathology. OBJECTIVE: To assess whether the SRLM is affected in MCI and AD. METHODS: In this proof-of-concept study, 27 controls, 13 subjects with AD, and 22 with MCI underwent 3T MRI. T1 maps were used for whole-hippocampal volumetry, T2 maps were segmented for hippocampal subfield areas, entorhinal cortex and subiculum thickness, and evaluated for SRLM integrity. RESULTS: Significant CA1 atrophy and subiculum thinning were found in both AD and MCI compared to similarly aged controls. However, SRLM integrity was only significantly reduced in AD but not in MCI compared to controls. There were no significant differences in other hippocampal subfields (CA2, CA3/dentate gyrus) or ERC thickness between the groups. Finally, CA1 and CA3/DG areas and SRLM clarity were correlated with clinical and cognitive measurements of disease severity. CONCLUSION: Although this study was cross sectional, it suggests a progression of specific subfield changes from MCI to established AD that is associated with the reduced integrity of SRLM, which may reflect more widespread hippocampal involvement as the disease progresses and the relative preservation of SRLM in MCI. These results provide new MRI biomarkers for disease staging and understanding of the neurobiology in AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Atrophy; Cognitive Dysfunction; Disease Progression; Entorhinal Cortex; Female; Hippocampus; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Male; Middle Aged; Reproducibility of Results

Homocysteine and Dementia: An International Consensus Statement. - Smith, A David; Refsum, Helga; Bottiglieri, Teodoro; Fenech, Michael; Hooshmand, Babak; McCaddon, Andrew; Miller, Joshua W; Rosenberg, Irwin H; Obeid, Rima (J Alzheimers Dis, 2018)
Identification of modifiable risk factors provides a crucial approach to the prevention of dementia. Nutritional or nutrient-dependent risk factors are especially important because dietary modifications or use of dietary supplements may lower the risk factor level. One such risk factor is a raised concentration of the biomarker plasma total homocysteine, which reflects the functional status of three B vitamins (folate, vitamins B12, B6). A group of experts reviewed literature evidence from the last 20 years. We here present a Consensus Statement, based on the Bradford Hill criteria, and conclude that elevated plasma total homocysteine is a modifiable risk factor for development of cognitive decline, dementia, and Alzheimer's disease in older persons. In a variety of clinical studies, the relative risk of dementia in elderly people for moderately raised homocysteine (within the normal range) ranges from 1.15 to 2.5, and the Population Attributable risk ranges from 4.3 to 31%. Intervention trials in elderly with cognitive impairment show that homocysteine-lowering treatment with B vitamins markedly slows the rate of whole and regional brain atrophy and also slows cognitive decline. The findings are consistent with moderately raised plasma total homocysteine (>11 μmol/L), which is common in the elderly, being one of the causes of age-related cognitive decline and dementia. Thus, the public health significance of raised tHcy in the elderly should not be underestimated, since it is easy, inexpensive, and safe to treat with B vitamins. Further trials are needed to see whether B vitamin treatment will slow, or prevent, conversion to dementia in people at risk of cognitive decline or dementia.
Keywords: Cognition; Cognitive Dysfunction; Consensus; Dementia; Dietary Supplements; Homocysteine; Humans; Meta-Analysis as Topic; Review Literature as Topic; Risk Factors; Vitamin B Complex

Imaging Biomarkers of Neurodegeneration in Alzheimer's Disease: Distinct Contributions of Cortical MRI Atrophy and FDG-PET Hypometabolism. - Benvenutto, Agnès; Giusiano, Bernard; Koric, Lejla; Gueriot, Claude; Didic, Mira; Felician, Olivier; Guye, Maxime; Guedj, Eric; Ceccaldi, Mathieu (J Alzheimers Dis, 2018)
BACKGROUND: Neurodegeneration biomarkers are routinely used in the diagnosis of Alzheimer's disease (AD). OBJECTIVE: To evaluate the respective contributions of two neuroimaging biomarkers, structural MRI and 18FDG-PET, in the assessment of neurodegeneration in AD dementia. METHODS: Patients with mild AD dementia diagnosed based on clinical and cerebrospinal fluid criteria and cognitively healthy subjects, from the Marseille cohort ADAge with cognitive, structural MRI and 18FDG-PET assessments, were included. Extent of atrophy on MRI and of hypometabolism on 18FDG-PET were individually evaluated in each patient using a voxel-based analysis on whole-brain approach and compared to healthy subjects. Patients were divided in distinct groups according to their atrophy extent on the one hand and to their hypometabolism extent on the other, then, to their imaging profile combining the extent of the two biomarkers. RESULTS: Fifty-two patients were included. The MMSE score was significantly lower in the "Extensive hypometabolism" group than in the "Limited hypometabolism" group (respectively 19.5/30 versus 23/30). A lower Innotest Amyloid Tau Index was associated with an extensive hypometabolism (p = 0.04). There were more patients with low educational level in the "Extensive atrophy" group, while a higher educational level was more found in the "Limited atrophy" group (p = 0.005). CONCLUSION: 18FDG-PET hypometabolism extent is associated with the pathological processes and clinical severity of AD, while MRI atrophy seems to be influenced by the cognitive reserve. In the context of mild AD dementia, these two biomarkers of neurodegeneration are thus not interchangeable and require to be considered in combination rather than in isolation.

Immunotherapy of Mild Cognitive Impairment by ω-3 Supplementation: Why Are Amyloid-β Antibodies and ω-3 Not Working in Clinical Trials? - Fiala, Milan; Restrepo, Lucas; Pellegrini, Matteo (J Alzheimers Dis, 2018)
This article reviews the basic tenets of a clinical approach to effective immunotherapy of Alzheimer's disease (AD) in patients with mild cognitive impairment (MCI). Although one randomized controlled study in early MCI patients by fish-derived omega-3 fatty acids (ω-3) showed slowing of disease progression, large clinical trials with different products have failed to show cognitive effects. Macrophages of healthy subjects phagocytize and degrade amyloid-β1 - 42 (Aβ) in the brain tissues, whereas macrophages of patients with AD and MCI are functionally defective. ω-3 and ω-3-derived specialized proresolving mediators (SPMs), such as resolvin D1, have powerful biochemical and immunological effects, which may repair the functions of MCI patients' macrophages in the brain's clearance of Aβ. Unfortunately, ω-3 products on the market have a variable quality. Nutritional supplementation with a combination drink called Smartfish with an emulsion of ω-3 and other fatty acids, antioxidants, 1,25-dihydroxy vitamin D3, and resveratrol improved the innate immune system of MCI patients by modulation of macrophage type to the pro-phagocytic M1-M2 type with an effective unfolded protein response against endoplasmic reticulum stress. Some MCI patients maintained their initial cognitive status for three years on Smartfish supplementation. Future randomized clinical trials should investigate the immune effects of ω-3, 1,25-dihydroxy vitamin D3, and SPMs on macrophage type, function, and biochemistry in parallel with cognitive effects.

Increased Prevalence of Obesity/Type 2 Diabetes and Lower Levels of Lithium in Rural Texas Counties May Explain Greater Alzheimer's Disease Risk. - Baranowski, Bradley J; Hayward, Grant C; Fajardo, Val A; MacPherson, Rebecca E K (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: To compare Alzheimer's disease (AD) mortality rates and coinciding risk factors in rural and urban Texas populations. METHODS: 155 Texas counties were divided into 73 rural and 82 urban areas using the U.S. Census Bureau definition of rurality. Changes in age-adjusted AD mortality across these counties were calculated using a 7-year aggregation model from 2000-2006 and 2009-2015. Data pertaining to gender, race, education, obesity, diabetes, physical inactivity, and lithium concentrations in tap water were also collected from readily available databases. RESULTS: Change in age-adjusted AD mortality was higher in rural counties (9.5±1.4) versus urban (5.9±1.1) over the time period examined. Similarly, obesity (30.2±0.2% ), diabetes (11.0±0.1% ), and physical inactivity (29.4±0.2% ) levels were significantly higher in rural populations compared to urban (29.1±0.2%, 9.7±0.1%, and 26.7±0.3, respectively). In contrast, the percent of population with some college education (40.1±0.7% ) was lower compared to urban (29.4±0.2% and 44.4±0.9%, respectively). Lithium concentrations in tap water was significantly lower in rural counties compared to urban (63.3±8.2 and 33.4±4.7μg/L, respectively). No significant differences were observed among females and however, we did find significant differences in the percent of African American and Hispanics. Correlational analysis uncovered a negative association between education status and AD mortality over time (r = -0.17). Further analysis controlling for physical inactivity, education, and trace lithium concentrations results in a loss of statistical significance. CONCLUSIONS: AD mortality rates are higher in rural counties when compared to urban counties, and this may be linked to greater physical inactivity, obesity, and diabetes, as well as lower trace lithium levels in tap water.

Increased Vulnerability of the Hippocampus in Transgenic Mice Overexpressing APP and Triple Repeat Tau. - Arner, Andrew; Rockenstein, Edward; Mante, Michael; Florio, Jazmin; Masliah, Deborah; Salehi, Bahar; Adame, Anthony; Overk, Cassia; Masliah, Eliezer; Rissman, Robert A (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is the most common tauopathy, characterized by progressive accumulation of amyloid-β (Aβ) and hyperphosphorylated tau. While pathology associated with the 4-repeat (4R) tau isoform is more abundant in corticobasal degeneration and progressive supranuclear palsy, both 3R and 4R tau isoforms accumulate in AD. Many studies have investigated interactions between Aβ and 4R tau in double transgenic mice, but few, if any, have examined the effects of Aβ with 3R tau. To examine this relationship, we crossed our APP751 mutant line with our recently characterized 3R tau mutant model to create a bigenic line (hAPP-3RTau) to model AD neuropathology. Mice were analyzed at 3 and 6 months of age for pathological and behavioral endpoints. While both the 3RTau and the hAPP-3RTau mice showed neuronal loss, increased tau aggregation, Aβ plaques and exhibited more behavioral deficits compared to the non-tg control, the bigenic mice often displaying relatively worsening levels. We found that even in young animals we found that the presence of APP/Aβ increased the accumulation of 3R tau in the neocortex and hippocampus. This observation was accompanied by activation of GSK3 and neurodegeneration in the neocortex and CA1 region. These results suggest that in addition to 4R tau, APP/Aβ may also enhance accumulation of 3R tau, a process which may be directly relevant to pathogenic pathways in AD. Our results demonstrate that this bigenic model closely parallels the pathological course of AD and may serve as a valuable model for testing new pharmacological interventions.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Glycogen Synthase Kinase 3; Hippocampus; Humans; Male; Mice; Mice, Transgenic; Neocortex; tau Proteins; Tauopathies

The Independent Associations of Physical Activity and Sleep with Cognitive Function in Older Adults. - Falck, Ryan S; Best, John R; Davis, Jennifer C; Liu-Ambrose, Teresa (J Alzheimers Dis, 2018)
BACKGROUND: Current evidence suggests physical activity (PA) and sleep are important for cognitive health; however, few studies examining the role of PA and sleep for cognitive health have measured these behaviors objectively. OBJECTIVE: We cross-sectionally examined whether 1) higher PA is associated with better cognitive performance independently of sleep quality; 2) higher sleep quality is associated with better cognitive performance independently of PA; and 3) whether higher PA is associated with better sleep quality. METHODS: We measured PA, subjective sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and objective sleep quality (i.e., fragmentation, efficiency, duration, and latency) using the MotionWatch8© in community-dwelling adults (N = 137; aged 55+). Cognitive function was indexed using the Alzheimer's Disease Assessment Scale-Plus. Correlation analyses were performed to determine relationships between PA, sleep quality, and cognitive function. We then used latent variable modelling to examine the relationships of PA with cognitive function independently of sleep quality, sleep quality with cognitive function independently of PA, and PA with sleep quality. RESULTS: We found greater PA was associated with better cognitive performance independently of 1) PSQI (β= -0.03; p < 0.01); 2) sleep fragmentation (β= -0.02; p < 0.01); 3) sleep duration (β= -0.02; p < 0.01); and 4) sleep latency (β= -0.02; p < 0.01). In addition, better sleep efficiency was associated with better cognitive performance independently of PA (β= -0.01; p = 0.04). We did not find any associations between PA and sleep quality. CONCLUSIONS: PA is associated with better cognitive performance independently of sleep quality, and sleep efficiency is associated with better cognitive performance independently of PA. However, PA is not associated with sleep quality and thus PA and sleep quality may be related to cognitive performance through independent mechanisms.

Induction of Amyloid-β42 Production by Fipronil and Other Pyrazole Insecticides. - Cam, Morgane; Durieu, Emilie; Bodin, Marion; Manousopoulou, Antigoni; Koslowski, Svenja; Vasylieva, Natalia; Barnych, Bogdan; Hammock, Bruce D; Bohl, Bettina; Koch, Philipp; Omori, Chiori; Yamamoto, Kazuo; et al. (J Alzheimers Dis, 2018)
Generation of amyloid-β peptides (Aβs) by proteolytic cleavage of the amyloid-β protein precursor (AβPP), especially increased production of Aβ42/Aβ43 over Aβ40, and their aggregation as oligomers and plaques, represent a characteristic feature of Alzheimer's disease (AD). In familial AD (FAD), altered Aβ production originates from specific mutations of AβPP or presenilins 1/2 (PS1/PS2), the catalytic subunits of γ-secretase. In sporadic AD, the origin of altered production of Aβs remains unknown. We hypothesize that the 'human chemical exposome' contains products able to favor the production of Aβ42/Aβ43 over Aβ40 and shorter Aβs. To detect such products, we screened a library of 3500 + compounds in a cell-based assay for enhanced Aβ42/Aβ43 production. Nine pyrazole insecticides were found to induce a β- and γ-secretase-dependent, 3-10-fold increase in the production of extracellular Aβ42 in various cell lines and neurons differentiated from induced pluripotent stem cells derived from healthy and FAD patients. Immunoprecipitation/mass spectrometry analyses showed increased production of Aβs cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and shorter. Strongly supporting a direct effect on γ-secretase activity, pyrazoles shifted the cleavage pattern of another γ-secretase substrate, alcadeinα, and shifted the cleavage of AβPP by highly purified γ-secretase toward Aβ42/Aβ43. Focusing on fipronil, we showed that some of its metabolites, in particular the persistent fipronil sulfone, also favor the production of Aβ42/Aβ43 in both cell-based and cell-free systems. Fipronil administered orally to mice and rats is known to be metabolized rapidly, mostly to fipronil sulfone, which stably accumulates in adipose tissue and brain. In conclusion, several widely used pyrazole insecticides enhance the production of toxic, aggregation prone Aβ42/Aβ43 peptides, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in sporadic AD.

The Influence of the Val66Met Polymorphism of Brain-Derived Neurotrophic Factor on Neurological Function after Traumatic Brain Injury. - Finan, John D; Udani, Shreya V; Patel, Vimal; Bailes, Julian E (J Alzheimers Dis, 2018)
Functional outcomes after traumatic brain injury (TBI) vary widely across patients with apparently similar injuries. This variability hinders prognosis, therapy, and clinical innovation. Recently, single nucleotide polymorphism (SNPs) that influence outcome after TBI have been identified. These discoveries create opportunities to personalize therapy and stratify clinical trials. Both of these changes would propel clinical innovation in the field. This review focuses on one of most well-characterized of these SNPs, the Val66Met SNP in the brain-derived neurotrophic factor (BDNF) gene. This SNP influences neurological function in healthy subjects as well as TBI patients and patients with similar acute insults to the central nervous system. A host of other patient-specific factors including ethnicity, age, gender, injury severity, and post-injury time point modulate this influence. These interactions confound efforts to define a simple relationship between this SNP and TBI outcomes. The opportunities and challenges associated with personalizing TBI therapy around this SNP and other similar SNPs are discussed in light of these results.

Inhibition of Histone Acetylation by ANP32A Induces Memory Deficits. - Chai, Gao-Shang; Feng, Qiong; Ma, Rong-Hong; Qian, Xiao-Hang; Luo, Dan-Ju; Wang, Zhi-Hao; Hu, Yu; Sun, Dong-Sheng; Zhang, Jun-Fei; Li, Xiao; Li, Xiao-Guang; Ke, Dan; et al. (J Alzheimers Dis, 2018)
There is accumulating evidence that decreased histone acetylation is involved in normal aging and neurodegenerative diseases. Recently, we found that ANP32A, a key component of INHAT (inhibitor of acetyltransferases) that suppresses histone acetylation, increased in aged and cognitively impaired C57 mice and expressing wild-type human full length tau (htau) transgenic mice. Downregulating ANP32A restored cognitive function and synaptic plasticity through upregulation of the expressions of synaptic-related proteins via increasing histone acetylation. However, there is no direct evidence that ANP32A can induce neurodegeneration and memory deficits. In the present study, we overexpressed ANP32A in the hippocampal CA3 region of C57 mice and found that ANP32A overexpression induced cognitive abilities and synaptic plasticity deficits, with decreased synaptic-related protein expression and histone acetylation. Combined with our recent studies, our findings reveal that upregulated ANP32A induced-suppressing histone acetylation may underlie the cognitive decline in neurodegenerative disease, and suppression of ANP32A may represent a promising therapeutic approach for neurodegenerative diseases including Alzheimer's disease.

Interactions between Atrial Fibrillation, Cardiovascular Risk Factors, and ApoE Genotype in Promoting Cognitive Decline in Patients with Alzheimer's Disease: A Prospective Cohort Study. - Falsetti, Lorenzo; Viticchi, Giovanna; Buratti, Laura; Grigioni, Francesco; Capucci, Alessandro; Silvestrini, Mauro (J Alzheimers Dis, 2018)
BACKGROUND: An association between non-valvular atrial fibrillation (NVAF) and cognitive impairment has been hypothesized. OBJECTIVE: We sought to evaluate whether and how permanent NVAF (pNVAF) is associated with progression of cognitive impairment in patients with Alzheimer's disease (AD) in the presence of vascular or genetic risk factors. METHODS: 310 consecutive patients affected by mild-moderate AD were included and followed for a 24-month period. At the end of the follow-up, based on the results of the neuropsychological evaluation patients were classified as stable or deteriorated to severe AD. Clinical history, therapy, time in therapeutic range for anticoagulation, Framingham cardiovascular risk profile (FCRP), CHA2DS2-VASc score, Mini-Mental State Examination (MMSE), ApoE genotype, brain CT-scan, carotid ultrasound, and ECG were collected. Binary logistic and path analysis were adopted to assess relationships between pNVAF, ApoE, and cognitive outcome. RESULTS: Despite anticoagulant therapy, pNVAF was associated with lower entry MMSE, higher mean intima-media thickness (mIMT) and higher FCRP. Among patients carrying ApoE ɛ4 allele and affected by pNVAF, the lowest MMSE (14.90±7.62) and the highest mIMT (1.16±0.17 mm) and FCRP (26.24±3.96) values were detected. In this group, the risk of cognitive deterioration reached the highest probability. pNVAF was associated with an increased cognitive deterioration in subjects with high FCRP, CHA2DS2-VASc, or mIMT. CONCLUSIONS: pNVAF seems to identify AD patients with a significant atherosclerotic burden and reduced cognitive performances. The interaction between pNVAF and ApoE ɛ4 genotype, especially with aggregated risk factors and an advanced stage of vascular damage is associated with higher risk of fast cognitive deterioration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Atherosclerosis; Atrial Fibrillation; Carotid Intima-Media Thickness; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prospective Studies; Risk Factors; Tomography, X-Ray Computed

Internal Consistency Over Time of Subjective Cognitive Decline: Drawing Preclinical Alzheimer's Disease Trajectories. - Ávila-Villanueva, Marina; Maestú, Fernando; Fernández-Blázquez, Miguel A (J Alzheimers Dis, 2018)
BACKGROUND: Early intervention to prevent, or delay, the transition from healthy cognition to cognitive impairment in older adults is an important goal. In this way, it is critical to find sensitive, reproducible, and early markers to use low cost methods for the detection of that transition. One of those early markers for symptomatic manifestation of AD is subjective cognitive decline (SCD). OBJECTIVE: To examine the internal consistency of the concept of SCD and to evaluate its clinical significance on the progression through the continuum of AD. METHODS: 1,091 cognitively healthy individuals from the Vallecas Project cohort were followed for three years. Cognitive complaints were systematically collected and analyzed along with clinical data. All participants were classified in three groups at every visit based on specific features of their complaints. RESULTS: Concordance analyses showed a good agreement in longitudinal classification of SCD. The Multi-state Markov Model highlighted a unidirectional transition from the status of no cognitive complaints to SCD. Interestingly, a more severe condition of SCD, namely SCD Plus, showed the highest risk of progression to mild cognitive impairment. CONCLUSIONS: The concept of SCD is stable over time when it is operationally defined and consistently assessed. It provides not only a fast identification of individuals at higher risk of future mild cognitive impairment, but also it allows us to track longitudinal trajectories.

Ketogenic Medium Chain Triglycerides Increase Brain Energy Metabolism in Alzheimer's Disease. - Croteau, Etienne; Castellano, Christian-Alexandre; Richard, Marie Anne; Fortier, Mélanie; Nugent, Scott; Lepage, Martin; Duchesne, Simon; Whittingstall, Kevin; Turcotte, Éric E; Bocti, Christian; Fülöp, Tamás; Cunnane, Stephen C (J Alzheimers Dis, 2018)
BACKGROUND: In Alzheimer's disease (AD), it is unknown whether the brain can utilize additional ketones as fuel when they are derived from a medium chain triglyceride (MCT) supplement. OBJECTIVE: To assess whether brain ketone uptake in AD increases in response to MCT as it would in young healthy adults. METHODS: Mild-moderate AD patients sequentially consumed 30 g/d of two different MCT supplements, both for one month: a mixture of caprylic (55%) and capric acids (35%) (n = 11), followed by a wash-out and then tricaprylin (95%; n = 6). Brain ketone (11C-acetoacetate) and glucose (FDG) uptake were quantified by PET before and after each MCT intervention. RESULTS: Brain ketone consumption doubled on both types of MCT supplement. The slope of the relationship between plasma ketones and brain ketone uptake was the same as in healthy young adults. Both types of MCT increased total brain energy metabolism by increasing ketone supply without affecting brain glucose utilization. CONCLUSION: Ketones from MCT compensate for the brain glucose deficit in AD in direct proportion to the level of plasma ketones achieved.

Leisure-Time Physical Activity and the Risk of Incident Dementia: The Mayo Clinic Study of Aging. - Krell-Roesch, Janina; Feder, Nathanael T; Roberts, Rosebud O; Mielke, Michelle M; Christianson, Teresa J; Knopman, David S; Petersen, Ronald C; Geda, Yonas E (J Alzheimers Dis, 2018)
We conducted a prospective cohort study derived from the population-based Mayo Clinic Study of Aging. We investigated if leisure-time physical activity among individuals with mild cognitive impairment (MCI) was associated with a decreased risk of developing dementia. 280 persons aged≥70 years (median 81 years, 165 males) with MCI and available data from neurologic evaluation, neuropsychological testing, and questionnaire-based physical activity assessment, were followed for a median of 3 years to the outcomes of incident dementia or censoring variables. We conducted Cox proportional hazards regression analyses with age as a time scale and adjusted for sex, education, medical comorbidity, depression, and APOE ɛ4 status. Moderate intensity midlife physical activity among MCI participants was significantly associated with a decreased risk of incident dementia (HR = 0.64; 95% CI, 0.41-0.98). There was a non-significant trend for a decreased risk of dementia for light and vigorous intensity midlife physical activity, as well as light and moderate intensity late-life physical activity. In conclusion, we observed that physical activity may be associated with a reduced risk of dementia among individuals with MCI. Furthermore, intensity and timing of physical activity may be important factors when investigating this association.

Lipid Metabolism and Survival Across the Frontotemporal Dementia-Amyotrophic Lateral Sclerosis Spectrum: Relationships to Eating Behavior and Cognition. - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicolette; Ramsey, Eleanor; Zoing, Margaret; Kim, Woojin Scott; Halliday, Glenda M; Piguet, Olivier; Hodges, John R; Farooqi, I Sadaf; Kiernan, Matthew C (J Alzheimers Dis, 2018)
BACKGROUND: Patients with frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behavior that could potentially affect lipid levels. OBJECTIVE: This study aimed to document changes in lipid metabolism across the ALS-FTD spectrum to identify potential relationships to eating behavior (including fat intake), cognitive change, body mass index (BMI), and effect on survival. METHODS: One hundred and twenty-eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioral change (ALS-Plus), 13 ALS-FTD, 31 behavioral variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behavior (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. RESULTS: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p < 0.001), total cholesterol/HDL ratio (p < 0.001), and lower HDL levels (p = 0.001) in all patient groups compared to controls. While there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p = 0.008). Triglyceride and HDL cholesterol levels correlated to fat intake, BMI, and measures of cognition and disease duration. CONCLUSION: A spectrum of changes in lipid metabolism has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.
Keywords: Adult; Aged; Amyotrophic Lateral Sclerosis; Australia; Body Mass Index; Case-Control Studies; Cholesterol; Cholesterol, HDL; Cognition; Energy Intake; Feeding Behavior; Female; Frontotemporal Dementia; Humans; Lipid Metabolism; Male; Middle Aged; Neuropsychological Tests; Survival Analysis

Long-Term Follow Up of Patients with Mild-to-Moderate Alzheimer's Disease Treated with Bapineuzumab in a Phase III, Open-Label, Extension Study. - Salloway, Stephen P; Sperling, Reisa; Fox, Nick C; Sabbagh, Marwan N; Honig, Lawrence S; Porsteinsson, Anton P; Rofael, Hany; Ketter, Nzeera; Wang, Daniel; Liu, Enchi; Carr, Stephen; Black, Ronald S; et al. (J Alzheimers Dis, 2018)
BACKGROUND: A 3-year extension of two Phase III parent studies of intravenous (IV) bapineuzumab in patients with mild-to-moderate Alzheimer's disease dementia (apolipoprotein (APOE) ɛ4 carriers and noncarriers) is summarized. OBJECTIVES: The primary and secondary objectives were to evaluate the long-term safety, tolerability, and maintenance of efficacy of bapineuzumab. METHODS: A multicenter study in patients who had participated in double-blind placebo-controlled parent studies. Patients enrolled in the extension study were assigned to receive IV infusions of bapineuzumab (0.5 or 1.0 mg/kg) every 13 weeks until termination but were blinded to whether they had received bapineuzumab or placebo in the parent studies. RESULTS: A total of 1,462 (688 were APOEɛ4 carriers and 774 were noncarriers) patients were enrolled. Extension-onset adverse events occurred in >81% of the patients in each dose group. Fall, urinary tract infection, agitation, and ARIA-E occurred in ≥10% of participants. The incidence proportion of ARIA-E was higher among carriers and noncarriers who received bapineuzumab for the first time in the extension study (11.8% and 5.4%, respectively) versus those who were previously exposed in the parent studies (5.1% and 1.3%, respectively). After 6 to 12 months exposure to bapineuzumab IV in the extension study, similar deterioration of cognition and function occurred with no significant differences between the dose groups. CONCLUSIONS: Infusion of bapineuzumab 0.5 or 1.0 mg/kg every 13 weeks for up to 3 years was generally well tolerated, with a safety and tolerability profile similar to that in previous studies.

Lower Serum Antibodies Against Tau Protein and Heavy Neurofilament in Alzheimer's Disease. - Bartos, Ales; Fialová, Lenka; Švarcová, Jana (J Alzheimers Dis, 2018)
BACKGROUND: Unlike antibodies against amyloid-β, little is known about serum antibodies to neuron-specific cytoskeletal proteins in patients with Alzheimer's disease (AD). OBJECTIVE: We aimed to study IgG autoantibodies against tau protein, light (NFL) and heavy subunits (NFH) of neurofilaments in serum of AD patients and elderly controls and to explore the evolution of antineurocytoskeletal antibody levels over time. METHODS: Antibodies against three targets (tau, NFL, and NFH) were measured using ELISA in 100 serum samples from 51 cognitively normal elderly controls and 49 patients with AD. Our primary cross-sectional design was further extended to monitor fluctuations over 1-2 years in a subset of individuals. RESULTS: The AD patients had lower levels of anti-tau antibodies (p = 0.03) and even lower anti-NFH antibodies (p = 0.005) than those in the control group at baseline. On the contrary, anti-NFL antibodies or total IgG concentrations in serum did not differ. All three antibodies remained stable in both groups except for a selective and significant anti-tau decline in AD patients (p = 0.03). CONCLUSIONS: The different responses to these antigens suggest some antibody selectivity in AD. The significant decline was observed for only serum anti-tau antibodies in AD patients over time and it corresponds to lower anti-tau levels in these patients. Our findings indicate a special feature of disease-relevant antigens and humoral autoimmunity in AD.

Mapping the Proxies of Memory and Learning Function in Senior Adults with High-performing, Normal Aging and Neurocognitive Disorders. - Lu, Hanna; Ni, Xi; Fung, Ada W T; Lam, Linda C W (J Alzheimers Dis, 2018)
BACKGROUND: Memory and learning, as the core brain function, shows controversial results across studies focusing on aging and dementia. One of the reasons is because of the multi-faceted nature of memory and learning. However, there is still a dearth of comparable proxies with psychometric and morphometric portrait in clinical and non-clinical populations. OBJECTIVE: We aim to investigate the proxies of memory and learning function with direct and derived measures and examine their associations with morphometric features in senior adults with different cognitive status. METHODS: Based on two modality-driven tests, we assessed the component-specific memory and learning in the individuals with high performing (HP), normal aging, and neurocognitive disorders (NCD) (n = 488). Structural magnetic resonance imaging was used to measure the regional cortical thickness with surface-based morphometry analysis in a subsample (n = 52). METHODS: Compared with HP elderly, the ones with normal aging and minor NCD showed declined recognition memory and working memory, whereas had better learning performance (derived scores). Meanwhile, major NCD patients showed more breakdowns of memory and learning function. The correlation between proxies of memory and learning and cortical thickness exhibited the overlapped and unique neural underpinnings. CONCLUSIONS: The proxies of memory and learning could be characterized by component-specific constructs with psychometric and morphometric bases. Overall, the constructs of memory are more likely related to the pathological changes, and the constructs of learning tend to reflect the cognitive abilities of compensation.

Medical and Research Consent Decision-Making Capacity in Patients with Alzheimer's Disease: A Systematic Review. - van Duinkerken, Eelco; Farme, Juliana; Landeira-Fernandez, Jesus; Dourado, Marcia C; Laks, Jerson; Mograbi, Daniel C (J Alzheimers Dis, 2018)
The capacity to make decisions is an important feature of daily living, which is closely linked to proper cognitive functioning. In conditions in which cognitive functioning becomes compromised, such as in Alzheimer's disease (AD), decision-making capacity can also get affected. Especially in AD, this has important implications, since over the course of the condition many important clinical decisions have to be made. For caregivers as well as physicians, it is sometimes difficult to determine how and when to intervene in the decision-making process. The aim of this systematic literature review was to identify studies that have evaluated medical and research consent decision-making capacity in patients with AD. Studies consistently show that decision-making capabilities are impaired in patients with AD. The cognitive and neuronal correlates of this process are, however, poorly studied. The few studies that investigated correlations have shown worse cognitive performance, mainly on the MMSE, to be related to poorer decision-making capacity. As most of these correlations have been performed in groups combining patients and controls, it remains unknown if these associations are disease specific. There is a need to study more systematically the decision-making process in relation to cognitive functioning and neural correlates to be able to develop a framework of decision-making capacity in AD, ultimately aiding clinicians and caregivers to understand and evaluate those capabilities in patients.

Melatonin in Synaptic Impairments of Alzheimer's Disease. - Shi, Yan; Fang, Ying-Yan; Wei, Yu-Ping; Jiang, Qian; Zeng, Peng; Tang, Na; Lu, Youming; Tian, Qing (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) underlies dementia for millions of people worldwide with no effective treatment. The dementia of AD is thought stem from the impairments of the synapses because of their critical roles in cognition. Melatonin is a neurohormone mainly released by the pineal gland in a circadian manner and it regulates brain functions in various manners. It is reported that both the melatonin deficit and synaptic impairments are present in the very early stage of AD and strongly contribute to the progress of AD. In the mammalian brains, the effects of melatonin are mainly relayed by two of its receptors, melatonin receptor type 1a (MT1) and 1b (MT2). To have a clear idea on the roles of melatonin in synaptic impairments of AD, this review discussed the actions of melatonin and its receptors in the stabilization of synapses, modulation of long-term potentiation, as well as their contributions in the transmissions of glutamatergic, GABAergic and dopaminergic synapses, which are the three main types of synapses relevant to the synaptic strength. The synaptic protective roles of melatonin in AD treatment were also summarized. Regarding its protective roles against amyloid-β neurotoxicity, tau hyperphosphorylation, oxygenation, inflammation as well as synaptic dysfunctions, melatonin may be an ideal therapeutic agent against AD at early stage.

Memantine for the Treatment of Dementia: A Review on its Current and Future Applications. - Folch, Jaume; Busquets, Oriol; Ettcheto, Miren; Sánchez-López, Elena; Castro-Torres, Ruben Dario; Verdaguer, Ester; Garcia, Maria Luisa; Olloquequi, Jordi; Casadesus, Gemma; Beas-Zarate, Carlos; Pelegri, Carme; Vilaplana, Jordi; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the presence in the brain of extracellular amyloid-β protein (Aβ) and intracellular neurofibrillary tangles composed of hyperphosphorylated tau protein. The N-Methyl-D-aspartate receptors (NMDAR), ionotropic glutamate receptor, are essential for processes like learning and memory. An excessive activation of NMDARs has been associated with neuronal loss. The discovery of extrasynaptic NMDARs provided a rational and physiological explanation between physiological and excitotoxic actions of glutamate. Memantine (MEM), an antagonist of extrasynaptic NMDAR, is currently used for the treatment of AD jointly with acetylcholinesterase inhibitors. It has been demonstrated that MEM preferentially prevents the excessive continuous extrasynaptic NMDAR disease activation and therefore prevents neuronal cell death induced by excitotoxicity without disrupting physiological synaptic activity. The problem is that MEM has shown no clear positive effects in clinical applications while, in preclinical stages, had very promising results. The data in preclinical studies suggests that MEM has a positive impact on improving AD brain neuropathology, as well as in preventing Aβ production, aggregation, or downstream neurotoxic consequences, in part through the blockade of extrasynaptic NMDAR. Thus, the focus of this review is primarily to discuss the efficacy of MEM in preclinical models of AD, consider possible combinations of this drug with others, and then evaluate possible reasons for its lack of efficacy in clinical trials. Finally, applications in other pathologies are also considered.

Metabolic Dysfunction in Alzheimer's Disease: From Basic Neurobiology to Clinical Approaches. - Clarke, Julia R; Ribeiro, Felipe C; Frozza, Rudimar L; De Felice, Fernanda G; Lourenco, Mychael V (J Alzheimers Dis, 2018)
Clinical trials have extensively failed to find effective treatments for Alzheimer's disease (AD) so far. Even after decades of AD research, there are still limited options for treating dementia. Mounting evidence has indicated that AD patients develop central and peripheral metabolic dysfunction, and the underpinnings of such events have recently begun to emerge. Basic and preclinical studies have unveiled key pathophysiological mechanisms that include aberrant brain stress signaling, inflammation, and impaired insulin sensitivity. These findings are in accordance with clinical and neuropathological data suggesting that AD patients undergo central and peripheral metabolic deregulation. Here, we review recent basic and clinical findings indicating that metabolic defects are central to AD pathophysiology. We further propose a view for future therapeutics that incorporates metabolic defects as a core feature of AD pathogenesis. This approach could improve disease understanding and therapy development through drug repurposing and/or identification of novel metabolic targets.

Metabolic Syndrome and Amyloid Accumulation in the Aging Brain. - Gomez, Gabriela; Beason-Held, Lori L; Bilgel, Murat; An, Yang; Wong, Dean; Studenski, Stephanie; Ferrucci, Luigi; Resnick, Susan M (J Alzheimers Dis, 2018)
BACKGROUND: Recent studies show links between metabolic syndrome and Alzheimer's disease (AD) neuropathology. Understanding the link between vascular-related health conditions and dementia will help target at risk populations and inform clinical strategies for early detection and prevention of AD. OBJECTIVE: To determine whether metabolic syndrome is associated with global cerebral amyloid-β (Aβ) positivity and longitudinal Aβ accumulation. METHODS: Prospective study of 165 participants who underwent (11)C-Pittsburgh compound B (PiB) PET neuroimaging to measure Aβ, from June 2005 to May 2016. Metabolic syndrome was defined using the revised Third Adults Treatment Panel of the National Cholesterol Education Program criteria. Participants were classified as PiB+/- . Linear mixed effects models assessed the relationships between baseline metabolic syndrome and PiB status and regional Aβ change over time. RESULTS: A total of 165 cognitively normal participants of the Baltimore Longitudinal Study of Aging (BLSA) Neuroimaging substudy, aged 55-92 years (mean baseline age = 76.4 years, 85 participants were male), received an average of 2.5 PET-PiB scans over an average interval of 2.6 (3.08 SD) years between first and last visits. Metabolic syndrome was not associated with baseline PiB positivity or concurrent regional Aβ. Metabolic syndrome was associated with increased rates of Aβ accumulation in superior parietal and precuneus regions over time in the PiB+ group. Elevated fasting glucose and blood pressure showed individual associations with accelerated Aβ accumulation. CONCLUSION: Metabolic syndrome was associated with accelerated Aβ accumulation in PiB+ individuals and may be an important factor in the progression of AD pathology.

Mitochondrial Function, Dynamics, and Permeability Transition: A Complex Love Triangle as A Possible Target for the Treatment of Brain Aging and Alzheimer's Disease. - Stockburger, Carola; Eckert, Schamim; Eckert, Gunter P; Friedland, Kristina; Müller, Walter E (J Alzheimers Dis, 2018)
Because of the failure of all amyloid-β directed treatment strategies for Alzheimer's disease (AD), the concept of mitochondrial dysfunction as a major pathomechanism of the cognitive decline in aging and AD has received substantial support. Accordingly, improving mitochondrial function as an alternative strategy for new drug development became of increasing interest and many different compounds have been identified which improve mitochondrial function in preclinical in vitro and in vivo experiments. However, very few if any have been investigated in clinical trials, representing a major drawback of the mitochondria directed drug development. To overcome these problems, we used a top-down approach by investigating several older antidementia drugs with clinical evidence of therapeutic efficacy. These include EGb761® (standardized ginkgo biloba extract), piracetam, and Dimebon. All improve experimentally many aspects of mitochondrial dysfunction including mitochondrial dynamics and also improve cognition and impaired neuronal plasticity, the functionally most relevant consequences of mitochondrial dysfunction. All partially inhibit opening events of the mitochondrial permeability transition pore (mPTP) which previously has mainly been discussed as a mechanism relevant for the induction of apoptosis. However, as more recent work suggests the mPTP as a master regulator of many mitochondrial functions, our data suggest the mPTP as a possible relevant drug target within the love triangle between mPTP regulation, mitochondrial dynamics, and mitochondrial function including regulation of neuronal plasticity. Drugs interfering with mPTP function will improve not only mitochondrial impairment in aging and AD but also will have beneficial effects on impaired neuronal plasticity, the pathomechanism which correlates best with functional deficits (cognition, behavior) in aging and AD.

Mitochondrial Translocase of the Outer Membrane Alterations May Underlie Dysfunctional Oxidative Phosphorylation in Alzheimer's Disease. - Chai, Yuek Ling; Xing, Huayang; Chong, Joyce R; Francis, Paul T; Ballard, Clive G; Chen, Christopher P; Lai, Mitchell K P (J Alzheimers Dis, 2018)
BACKGROUND: The translocase of the outer membrane (TOM) is a vital mitochondrial transport system facilitating the importation of nuclear encoded proteins into the organelle. While mitochondrial dysfunction, including perturbation of oxidative phosphorylation (OXPHOS) complex, is evident in Alzheimer's disease (AD), it remains unclear whether the observed OXPHOS deficits may be associated with TOM alterations. OBJECTIVES: To correlate TOM subunits with OXPHOS complex proteins in AD. METHODS: Postmortem neocortex (BA40) from AD and age-matched controls were processed to obtain mitochondrial enriched homogenates for the measurement of Tom20, Tom22, Tom40, and Tom70 as well as components of OXPHOS complex I-V by immunoblotting. RESULTS: Tom20 and Tom70 immunoreactivities were significantly reduced in AD, as were components of OXPHOS complex I and III. Both Tom20 and Tom70 positively correlated with complex III and V, while Tom20 also correlated withcomplex IV. CONCLUSION: Reductions in certain TOM subunits and their correlations with specific OXPHOS complex proteins suggest that an impaired mitochondrial transportation system may contribute to previously observed oxidative phosphorylation deficits in AD. Follow-up studies are needed to corroborate the present correlative study.
Keywords: Aged, 80 and over; Alzheimer Disease; Autopsy; Brain; Female; Humans; Male; Mitochondria; Mitochondrial Membrane Transport Proteins; Multivariate Analysis; Oxidative Phosphorylation

MRI-Based Screening of Preclinical Alzheimer's Disease for Prevention Clinical Trials. - Casamitjana, Adrià; Petrone, Paula; Tucholka, Alan; Falcon, Carles; Skouras, Stavros; Molinuevo, José Luis; Vilaplana, Verónica; Gispert, Juan Domingo (J Alzheimers Dis, 2018)
The identification of healthy individuals harboring amyloid pathology represents one important challenge for secondary prevention clinical trials in Alzheimer's disease (AD). Consequently, noninvasive and cost-efficient techniques to detect preclinical AD constitute an unmet need of critical importance. In this manuscript, we apply machine learning to structural MRI (T1 and DTI) of 96 cognitively normal subjects to identify amyloid-positive ones. Models were trained on public ADNI data and validated on an independent local cohort. Used for subject classification in a simulated clinical trial setting, the proposed method is able to save 60% of unnecessary CSF/PET tests and to reduce 47% of the cost of recruitment. This recruitment strategy capitalizes on available MR scans to reduce the overall amount of invasive PET/CSF tests in prevention trials, demonstrating a potential value as a tool for preclinical AD screening. This protocol could foster the development of secondary prevention strategies for AD.

Multicenter Resting State Functional Connectivity in Prodromal and Dementia Stages of Alzheimer's Disease. - Teipel, Stefan J; Metzger, Coraline D; Brosseron, Frederic; Buerger, Katharina; Brueggen, Katharina; Catak, Cihan; Diesing, Dominik; Dobisch, Laura; Fliebach, Klaus; Franke, Christiana; Heneka, Michael T; Kilimann, Ingo; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Alterations of intrinsic networks from resting state fMRI (rs-fMRI) have been suggested as functional biomarkers of Alzheimer's disease (AD). OBJECTIVE: To determine the diagnostic accuracy of multicenter rs-fMRI for prodromal and preclinical stages of AD. METHODS: We determined rs-fMRI functional connectivity based on Pearson's correlation coefficients and amplitude of low-frequency fluctuation in people with subjective cognitive decline, people with mild cognitive impairment, and people with AD dementia compared with healthy controls. We used data of 247 participants of the prospective DELCODE study, a longitudinal multicenter observational study, imposing a unified fMRI acquisition protocol across sites. We determined cross-validated discrimination accuracy based on penalized logistic regression to account for multicollinearity of predictors. RESULTS: Resting state functional connectivity reached significant cross-validated group discrimination only for the comparison of AD dementia cases with healthy controls, but not for the other diagnostic groups. AD dementia cases showed alterations in a large range of intrinsic resting state networks, including the default mode and salience networks, but also executive and language networks. When groups were stratified according to their CSF amyloid status that was available in a subset of cases, diagnostic accuracy was increased for amyloid positive mild cognitive impairment cases compared with amyloid negative controls, but still inferior to the accuracy of hippocampus volume. CONCLUSION: Even when following a strictly harmonized data acquisition protocol and rigorous scan quality control, widely used connectivity measures of multicenter rs-fMRI do not reach levels of diagnostic accuracy sufficient for a useful biomarker in prodromal stages of AD.

A Natural Benzofuran from the Patagonic Aleurodiscus vitellinus Fungus has Potent Neuroprotective Properties on a Cellular Model of Amyloid-β Peptide Toxicity. - González-Ramírez, Mariela; Gavilán, Javiera; Silva-Grecchi, Tiare; Cajas-Madriaga, Daniel; Triviño, Sergio; Becerra, José; Saez-Orellana, Francisco; Pérez, Claudia; Fuentealba, Jorge (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by amyloid plaques that form due to an increase in amyloid-β peptide (Aβ) aggregation. One strategy in the search of new treatments for AD focuses on compounds that decrease Aβ accumulation. Compounds containing a benzofuran ring have been described to play an important role in decreasing Aβ-induced toxicity; however, only synthetic benzofurans have been tested thus far. The aim of the present study was to examine the in vitro neuroprotective properties of fomannoxin (Fx), a natural benzofuran isolated from cultures of the Andean-Patagonian fungi Aleurodiscus vitellinus, and evaluate its effect on Aβ peptide. We tested the effect of Fx at a wide concentration range (10-11-10-4 M) in PC-12 cells, and found the compound did not alter cellular viability. Fx also showed a concentration-dependent effect on the Aβ-induced toxicity in PC12 cells, showing viability above 100% at 10-6 M. We then measured the effect of Fx (10-7-10-5 M) on the frequency of cytosolic Ca2+ transients in rat hippocampal neurons at both acute and chronic (24 h) times. Acute incubation with Fx increased the frequency of cytosolic Ca2+ transients to values around 200%, whereas chronic incubation with Fx increased the frequency of Ca2+ transients. Finally, the Aβ-induced decrease in intracellular Ca2+ transients was prevented when Fx (10-6 M) was co-incubated with Aβ (5×10-6 M). The results suggest a potent neuroprotective effect of this naturally occurring benzofuran against Aβ peptide toxicity that could be mediated by an interference with it binding to plasma membrane, and lead Fx as new chemical entity to develop pharmacological tools against Aβ peptide neurotoxicity.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Basidiomycota; Benzofurans; Cell Survival; Hippocampus; Neurons; Neuroprotective Agents; PC12 Cells; Plaque, Amyloid; Rats

Naturalistic Driving Study Investigating Self-Regulation Behavior in Early Alzheimer's Disease: A Pilot Study. - Paire-Ficout, Laurence; Lafont, Sylviane; Conte, Fanny; Coquillat, Amandine; Fabrigoule, Colette; Ankri, Joël; Blanc, Frédéric; Gabel, Cécilia; Novella, Jean-Luc; Morrone, Isabella; Mahmoudi, Rachid (J Alzheimers Dis, 2018)
BACKGROUND: Because cognitive processes decline in the earliest stages of Alzheimer's disease (AD), the driving abilities are often affected. The naturalistic driving approach is relevant to study the driving habits and behaviors in normal or critical situations in a familiar environment of participants. OBJECTIVE: This pilot study analyzed in-car video recordings of naturalistic driving in patients with early-stage AD and in healthy controls, with a special focus on tactical self-regulation behavior. METHODS: Twenty patients with early-stage AD (Diagnosis and Statistical Manual of Mental Disorders, Fourth Edition [DSM-IV] criteria), and 21 healthy older adults were included in the study. Data collection equipment was installed in their personal vehicles. Two expert psychologists assessed driving performance using a specially designed Naturalistic Driving Assessment Scale (NaDAS), paying particular attention to tactical self-regulation behavior, and they recorded all critical safety events. RESULTS: Poorer driving performance was observed among AD drivers: their tactical self-regulation behavior was of lower quality. AD patients had also twice as many critical events as healthy drivers and three times more "unaware" critical events. CONCLUSION: This pilot study used a naturalistic approach to accurately show that AD drivers have poorer tactical self-regulation behavior than healthy older drivers. Future deployment of assistance systems in vehicles should specifically target tactical self-regulation components.

Neural Correlates of Sleep Disturbance in Alzheimer's Disease: Role of the Precuneus in Sleep Disturbance. - Matsuoka, Teruyuki; Imai, Ayu; Fujimoto, Hiroshi; Kato, Yuka; Shibata, Keisuke; Nakamura, Kaeko; Yokota, Hajime; Yamada, Kei; Narumoto, Jin (J Alzheimers Dis, 2018)
BACKGROUND: Sleep disturbance may affect the development of Alzheimer's disease (AD), but the neural correlates of sleep disturbance in AD have not been fully clarified. OBJECTIVE: To examine the factors associated with sleep disturbance in AD. METHODS: A retrospective study was performed in 63 patients with AD. None of the patients had been prescribed antidementia or psychoactive drugs, and all underwent brain magnetic resonance imaging (MRI) before medication. Sleep disturbance was defined as a score of at least 1 point on the sleep disturbance subscale of the Neuropsychiatric Inventory (NPI). Whole brain image analysis was performed using SPM8 and VBM8. A two-sample t-test was used to compare patients with AD with (n = 19) and without (n = 44) sleep disturbance, with age and gender included as covariates. The statistical thresholds were set to an uncorrected p-value of 0.001 at the voxel level and a corrected p-value of 0.05 at the cluster level. In addition, pineal gland volume (PGV) measured using MRI, and white matter hyperintensity (WMH) assessed with the modified Fazekas scale were compared between patients with AD with and without sleep disturbance using independent group t-tests. RESULTS: In whole brain analysis, the precuneus volume in patients with AD with sleep disturbance was significantly smaller than those without sleep disturbance. There were no significant differences in PGV and WMH between the two groups. CONCLUSION: Sleep disturbance in AD was associated with reduction of precuneus volume. This suggests that the precuneus might be an important region in sleep disturbance in AD.

Neuroanatomical Comparison of the "Word" and "Picture" Versions of the Free and Cued Selective Reminding Test in Alzheimer's Disease. - Slachevsky, Andrea; Barraza, Paulo; Hornberger, Michael; Muñoz-Neira, Carlos; Flanagan, Emma; Henriquez, Fernando; Bravo, Eduardo; Farías, Mauricio; Delgado, Carolina (J Alzheimers Dis, 2018)
Episodic memory tests with cued recall, such as the Free and Cued Selective Reminding Test (FCSRT), allow for the delineation of hippocampal and prefrontal atrophy contributions to memory performance in Alzheimer's disease (AD). Both Word and Picture versions of the test exist but show different profiles, with the Picture version usually scoring higher across different cohorts. One possible explanation for this divergent performance between the different modality versions of the test might be that they rely on different sets of neural correlates. The current study explores this by contrasting the neural correlates of the Word and Picture versions of the FCSRT with voxel-based morphometry (VBM) in AD and healthy subjects. We predicted that the Picture version would be associated with different cortical regions than the Word version, which might be more hippocampal-centric. When comparing 35 AD patients and 34 controls, AD patients exhibited impairments on both versions of the FCSRT and both groups performed higher in the Picture version. A region of interest analysis based on prior work revealed significant correlations between free recall of either version with atrophy of the temporal pole and hippocampal regions. Thus, contrary to expectations, performance on both the Word and the Picture version of the FCSRT is associated with largely overlapping networks. Free recall is associated with hippocampal volume and might be properly considered as an indicator of hippocampal structural integrity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Cues; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation

Neuroepigenetics and Alzheimer's Disease: An Update. - Zusso, Morena; Barbierato, Massimo; Facci, Laura; Skaper, Stephen D; Giusti, Pietro (J Alzheimers Dis, 2018)
Epigenetics is the study of changes in gene expression which may be triggered by both genetic and environmental factors, and independent from changes to the underlying DNA sequence-a change in phenotype without a change in genotype-which in turn affects how cells read genes. Epigenetic changes represent a regular and natural occurrence but can be influenced also by factors such as age, environment, and disease state. Epigenetic modifications can manifest themselves not only as the manner in which cells terminally differentiate, but can have also deleterious effects, resulting in diseases such as cancer. At least three systems including DNA methylation, histone modification, and non-coding RNA (ncRNA)-associated gene silencing are thought to initiate and sustain epigenetic change. For example, in Alzheimer's disease (AD), both genetic and non-genetic factors contribute to disease etiopathology. While over 250 gene mutations have been related to familial AD, less than 5% of AD cases are explained by known disease genes. More than likely, non-genetic factors, probably triggered by environmental factors, are causative factors of late-onset AD. AD is associated with dysregulation of DNA methylation, histone modifications, and ncRNAs. Among the classes of ncRNA, microRNAs (miRNAs) have a well-established regulatory relevance. MicroRNAs are highly expressed in CNS neurons, where they play a major role in neuron differentiation, synaptogenesis, and plasticity. MicroRNAs impact higher cognitive functions, as their functional impairment is involved in the etiology of neurological diseases, including AD. Alterations in the miRNA network contribute to AD disease processes, e.g., in the regulation of amyloid peptides, tau, lipid metabolism, and neuroinflammation. MicroRNAs, both as biomarkers for AD and therapeutic targets, are in the early stages of exploration. In addition, emerging data suggest that altered transcription of long ncRNAs, endogenous, ncRNAs longer than 200 nucleotides, may be involved in an elevated risk for AD.

Neuropathologic Correlates of Psychiatric Symptoms in Alzheimer's Disease. - Ehrenberg, Alexander J; Suemoto, Claudia K; França Resende, Elisa de Paula; Petersen, Cathrine; Leite, Renata Elaine Paraizo; Rodriguez, Roberta Diehl; Ferretti-Rebustini, Renata Eloah de Lucena; You, Michelle; Oh, Jun; Nitrini, Ricardo; Pasqualucci, Carlos Augusto; Jacob-Filho, Wilson; et al. (J Alzheimers Dis, 2018)
Clarifying the relationships between neuropsychiatric symptoms and Alzheimer's disease (AD)-related pathology may open avenues for effective treatments. Here, we investigate the odds of developing neuropsychiatric symptoms across increasing burdens of neurofibrillary tangle and amyloid-β pathology. Participants who passed away between 2004 and 2014 underwent comprehensive neuropathologic evaluation at the Biobank for Aging Studies from the Faculty of Medicine at the University of São Paulo. Postmortem interviews with reliable informants were used to collect information regarding neuropsychiatric and cognitive status. Of 1,092 cases collected, those with any non-Alzheimer pathology were excluded, bringing the cohort to 455 cases. Braak staging was used to evaluate neurofibrillary tangle burden, and the CERAD neuropathology score was used to evaluate amyloid-β burden. The 12-item neuropsychiatric inventory was used to evaluate neuropsychiatric symptoms and CDR-SOB score was used to evaluate dementia status. In Braak I/II, significantly increased odds were detected for agitation, anxiety, appetite changes, depression, and sleep disturbances, compared to controls. Increased odds of agitation continue into Braak III/IV. Braak V/VI is associated with higher odds for delusions. No increased odds for neuropsychiatric symptoms were found to correlate with amyloid-β pathology. Increased odds of neuropsychiatric symptoms are associated with early neurofibrillary tangle pathology, suggesting that subcortical neurofibrillary tangle accumulation with minimal cortical pathology is sufficient to impact quality of life and that neuropsychiatric symptoms are a manifestation of AD biological processes.

Neuroprotective Effects of Ginsenoside Rf on Amyloid-β-Induced Neurotoxicity in vitro and in vivo. - Du, Yehong; Fu, Min; Wang, Yu Tian; Dong, Zhifang (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by the deposition of amyloid-β peptides (Aβ). Aβ accumulation leads to the formation of neurofibrillary tangles, inflammation, axonal injury, synapse loss, and neuronal apoptosis. Thus, reducing Aβ levels should exert a neuroprotective effect against AD. Ginsenoside Rf, an extract from Panax notoginseng, has potent anti-fatigue, anti-nociception, anti-oxidation, and anti-inflammation properties. However, it is unclear whether ginsenoside Rf is effective in the treatment of AD. Here, we reported that ginsenoside Rf could significantly attenuate Aβ-induced apoptosis in N2A cells, as reflected by a dramatic increase in mitochondrial membrane potential and decrease in Ca2 + concentration, reactive oxygen species, and active caspase-3 expression. Meanwhile, ginsenoside Rf could alleviate the Aβ-induced inflammation reaction, such as the decrease of interferon-gamma (IFN-γ) and active caspase-1 expression and the increase of interleukin-13. Furthermore, we also found that Rf is able to accelerate Aβ clearance and subsequently reduces Aβ level in N2A cells stably transfected with human Swedish mutant APP695 (N2A-APP). More importantly, daily Rf treatment (20 mg/kg, i.p.) throughout the experiment dramatically improved spatial learning and memory in Aβ42-induced mouse model of AD. Taken together, these results indicate that ginsenoside Rf may decrease Aβ-induced neurotoxicity and memory decline via anti-inflammatory response during AD development, suggesting that Rf may be a potential therapeutic agent for treating AD.

Neuropsychiatric and Cognitive Subtypes among Community-Dwelling Older Persons and the Association with DSM-5 Mild Neurocognitive Disorder: Latent Class Analysis. - Liew, Tau Ming; Yu, Junhong; Mahendran, Rathi; Ng, Tze-Pin; Kua, Ee-Heok; Feng, Lei (J Alzheimers Dis, 2018)
BACKGROUND: Neuropsychiatric symptoms (NPS) have been shown to increase the risk of neurocognitive disorders (NCD), leading to the recently-published criteria of mild behavioral impairment (MBI) to identify pre-dementia using NPS alone. However, MBI drew concerns about over-diagnosing subclinical psychiatric disorders. OBJECTIVE: We hypothesized that the specificity of NPS in predicting NCD may be improved by considering NPS together with various domains of cognitive deficits. We tested this hypothesis by identifying subtypes based on the combination of NPS and cognitive deficits among community-dwelling older persons, and evaluating how the identified subtypes were associated with mild NCD. METHODS: Our participants were from a community-based cohort study. They completed assessments such as Geriatric Depression Scale (GDS), Geriatric Anxiety Inventory (GAI), and Montreal Cognitive Assessment (MoCA). Those with possible cognitive impairment underwent further evaluations for mild NCD. Latent class analysis was conducted using GDS, GAI, and MoCA domains. Logistic regression was performed to investigate the association between the latent-classes and mild NCD. RESULTS: We included 825 participants, and identified four distinct subtypes: Subtype 1 (no NPS or cognitive deficits), Subtype 2 (NPS alone), Subtype 3 (cognitive deficits alone), and Subtype 4 (both NPS and cognitive deficits). Subtype 1 and 2 had low risk of prevalent mild NCD (OR 0.92- 1.00), while Subtype 3 conferred a moderate risk (OR 4.47- 4.85) and Subtype 4 had the highest risk (OR 7.95- 8.63). CONCLUSION: We demonstrated the benefits of combining NPS and cognitive deficits to predict those at highest risk of prevalent mild NCD. Our findings highlighted the relevance of subclinical psychiatric symptoms in predicting NCD, and indirectly supported the need for longer durations of NPS to improve its specificity.
Keywords: Aged; Cognition; Cognitive Dysfunction; Diagnostic and Statistical Manual of Mental Disorders; Female; Humans; Latent Class Analysis; Logistic Models; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

No Effects of Black Tea on Cognitive Decline Among Older US Men: A Prospective Cohort Study. - Feng, Lei; Langsetmo, Lisa; Yaffe, Kristine; Sun, Ye; Fink, Howard A; Shikany, James M; Leung, P C; Lane, Nancy E; Cauley, Jane A (J Alzheimers Dis, 2018)
BACKGROUND: Accumulating evidence supports the neuroprotective effects of bioactive compounds from tea leaves. There are limited data from black tea consumption populations. OBJECTIVE: To determine whether black tea consumption is associated with cognitive decline among older men. METHODS: We chose to study the association between black tea consumption and cognition using data from the Osteoporotic Fractures in Men (MrOS) cohort, which collected information on tea consumption at baseline and has repeatedly assessed cognitive function in 3,844 men aged 65+ years (mean = 72.4 years). We defined tea drinkers as those who drank black tea at least once per week and further grouped them into weekly drinkers and daily drinkers. Cognitive function was assessed at baseline and approximately 7 years later using the Modified Mini-Mental State Examination (3MSE). Multivariable logistic regression and linear regression models were constructed to assess the association between black tea consumption and risk of fast cognitive decline as a binary variable and change in 3MSE scores as continuous variable. Fast cognitive decline was defined as decline in 3MSE >1.5 standard deviation of mean change score. Models were adjusted for age, education level, and baseline cognitive scores. RESULTS: Weekly and daily black tea drinkers were 24.8% and 12.4% of the study cohort, respectively. Fast cognitive decline occurred in 243 (6.3%) participants. Tea consumption was not associated with risk of cognitive decline, nor was tea associated with cognitive decline measured by absolute change in 3MSE scores. CONCLUSIONS: There was no association of black tea consumption and cognitive decline among older men in the US.

Non-Phosphorylated Tau in Cerebrospinal Fluid is a Marker of Alzheimer's Disease Continuum in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Mukherjee, Partha S; Waniek, Katharina; Holzer, Max; Chao, Chih-Kai; Thompson, Charles; Ruiz-Ramos, Rubén; Calderón-Garcidueñas, Ana; Franco-Lira, Maricela; Reynoso-Robles, Rafael; González-Maciel, Angelica; Lachmann, Ingolf (J Alzheimers Dis, 2018)
Long-term exposure to fine particulate matter (PM2.5) and ozone (O3) above USEPA standards is associated with Alzheimer's disease (AD) risk. Metropolitan Mexico City (MMC) children exhibit subcortical pretangles in infancy and cortical tau pre-tangles, NFTs, and amyloid phases 1-2 by the 2nd decade. Given their AD continuum, we measured in 507 normal cerebrospinal fluid (CSF) samples (MMC 354, controls 153, 12.82±6.73 y), a high affinity monoclonal non-phosphorylated tau antibody (non-P-Tau), as a potential biomarker of AD and axonal damage. In 81 samples, we also measured total tau (T-Tau), tau phosphorylated at threonine 181 (P-Tau), amyloid-β1-42, BDNF, and vitamin D. We documented by electron microscopy myelinated axonal size and the pathology associated with combustion-derived nanoparticles (CDNPs) in anterior cingulate cortex white matter in 6 young residents (16.25±3.34 y). Non-P-Tau showed a strong increase with age significantly faster among MMC versus controls (p = 0.0055). Aβ1 - 42 and BDNF concentrations were lower in MMC children (p = 0.002 and 0.03, respectively). Anterior cingulate cortex showed a significant decrease (p = <0.0001) in the average axonal size and CDNPs were associated with organelle pathology. Significant age increases in non-P-Tau support tau changes early in a population with axonal pathology and evolving AD hallmarks in the first two decades of life. Non-P-Tau is an early biomarker of axonal damage and potentially valuable to monitor progressive longitudinal changes along with AD multianalyte classical CSF markers. Neuroprotection of young urbanites with PM2.5 and CDNPs exposures ought to be a public health priority to halt the development of AD in the first two decades of life.

Novel GRN Mutations in Alzheimer's Disease and Frontotemporal Lobar Degeneration. - Piaceri, Irene; Imperiale, Daniele; Ghidoni, Enrico; Atzori, Cristiana; Bagnoli, Silvia; Ferrari, Camilla; Ungari, Silvana; Ambrogio, Luca; Sorbi, Sandro; Nacmias, Benedetta (J Alzheimers Dis, 2018)
BACKGROUND: During the twentieth century, frontotemporal dementia (FTD) was often misdiagnosed, confused with Alzheimer's disease or psychiatric disorders, jeopardizing care and research. OBJECTIVE: To analyze the FTD genes in the DNA samples of patients belonging to families clinically classified as probable Alzheimer's disease (FAD) in the early 1990s and not carrying mutation in the three main genes linked to FAD (Presenilin 1, Presenilin 2, and Amyloid precursor protein). METHODS: The genetic screening was performed on 63 probands diagnosed as FAD before the early 2000s. RESULTS: Four patients out of the 63 studied (4/63, 6.3%) resulted as carrying four different GRN genetic variations: p.T272SfsX10, p.R110X, p.C149LfsX10, and p.W304C. The first two mutations (p.T272SfsX10, p.R110X) are the most frequent ones in Italy in FTD patients; the latter two (p.C149LfsX10 and p.W304C) are not described in the scientific literature. CONCLUSION: Our data suggest that it can be important to re-examine FAD patients diagnosed when the FTD spectrum was not well recognized and the causative FTD genes had not yet been identified. Moreover, we propose initially analyzing genes associated with the first form of suspected dementia and, if the results are negative, studying genes implicated in the other form of dementia.

Nutrition: Review on the Possible Treatment for Alzheimer's Disease. - Botchway, Benson O A; Moore, Masania K; Akinleye, Faith O; Iyer, Ishwari C; Fang, Marong (J Alzheimers Dis, 2018)
Since its discovery some hundred years ago, Alzheimer's disease (AD), a neurodegenerative disease and an eminent cause of most dementia, continues to pose problems for affected families and society, especially in developed countries. With the approved medications by the Food and Drugs Administration in the United States, effectual treatment of AD apropos to the complete eradication of the disease continues to be elusive due to complexities relating to the pathophysiology of the disease. Nutrition has and continues to play a salient role in the survival of living organisms with no exception for human beings. Herein, we report the connection between nutrition and AD with particular attention to vitamins, curcumin, and the Mediterranean diet.
Keywords: Alzheimer Disease; Curcumin; Diet, Mediterranean; Dietary Supplements; Humans; Nutritional Status; Risk Factors; Vitamins

Overactive BRCA1 Affects Presenilin 1 in Induced Pluripotent Stem Cell-Derived Neurons in Alzheimer's Disease. - Wezyk, Michalina; Szybinska, Aleksandra; Wojsiat, Joanna; Szczerba, Marcelina; Day, Kelly; Ronnholm, Harriet; Kele, Malin; Berdynski, Mariusz; Peplonska, Beata; Fichna, Jakub Piotr; Ilkowski, Jan; Styczyńska, Maria; et al. (J Alzheimers Dis, 2018)
The BRCA1 protein, one of the major players responsible for DNA damage response has recently been linked to Alzheimer's disease (AD). Using primary fibroblasts and neurons reprogrammed from induced pluripotent stem cells (iPSC) derived from familial AD (FAD) patients, we studied the role of the BRCA1 protein underlying molecular neurodegeneration. By whole-transcriptome approach, we have found wide range of disturbances in cell cycle and DNA damage response in FAD fibroblasts. This was manifested by significantly increased content of BRCA1 phosphorylated on Ser1524 and abnormal ubiquitination and subcellular distribution of presenilin 1 (PS1). Accordingly, the iPSC-derived FAD neurons showed increased content of BRCA1(Ser1524) colocalized with degraded PS1, accompanied by an enhanced immunostaining pattern of amyloid-β. Finally, overactivation of BRCA1 was followed by an increased content of Cdc25C phosphorylated on Ser216, likely triggering cell cycle re-entry in FAD neurons. This study suggests that overactivated BRCA1 could both influence PS1 turnover leading to amyloid-β pathology and promote cell cycle re-entry-driven cell death of postmitotic neurons in AD.

Oxidative Stress in Elderly with Different Cognitive Status: My Mind Project. - Fattoretti, Patrizia; Malavolta, Marco; Fabbietti, Paolo; Papa, Roberta; Giacconi, Robertina; Costarelli, Laura; Galeazzi, Roberta; Paoloni, Cristina; Postacchini, Demetrio; Lattanzio, Fabrizia; Giuli, Cinzia (J Alzheimers Dis, 2018)
BACKGROUND: Biomarkers of oxidative stress have been associated with cognitive status in humans and have been proposed to guide prognosis/treatment in Alzheimer's disease (AD) and mild cognitive impairment (MCI). OBJECTIVE: The aim of this study was to compare oxidative stress status in the plasma of mild-moderate AD, MCI, and healthy elderly with normal cognition (HE) undergoing a non-pharmacological intervention including multi-modal cognitive training ("My Mind Project"). METHODS: A prospective randomized trial involving 321 elderly people enrolled in Marche Region, Italy. Each subject was randomly assigned to an experimental (cognitive training) or to a control group. Cognitive performances and biomarkers have been analyzed before intervention (baseline), immediately after termination (follow-up 1), after 6 months (follow-up 2), and after 2 years (follow-up 3). The biological antioxidant potential (BAP) to Diacron reactive oxygen metabolites (d-ROM) ratio has been used as an indicator of oxidative stress status and as outcome variable. RESULTS: We have found no differences in the oxidative status among AD, MCI, and HE. Neither did we find a significant effect of the intervention within experimental groups. Gender was the sole factor with a strong significant effect on BAP/d-ROM. CONCLUSIONS: Based on these results, the utility of biomarkers of oxidative stress to guide prognosis/treatment in AD or MCI seems to be limited by lack of specificity, large interindividual variability, and gender bias.

Palmitoylethanolamide Blunts Amyloid-β42-Induced Astrocyte Activation and Improves Neuronal Survival in Primary Mouse Cortical Astrocyte-Neuron Co-Cultures. - Beggiato, Sarah; Borelli, Andrea Celeste; Ferraro, Luca; Tanganelli, Sergio; Antonelli, Tiziana; Tomasini, Maria Cristina (J Alzheimers Dis, 2018)
BACKGROUND: Based on the pivotal role of astrocytes in brain homeostasis and the strong metabolic cooperation existing between neurons and astrocytes, it has been suggested that astrocytic dysfunctions might cause and/or contribute to neuroinflammation and neurodegenerative processes. Therapeutic approaches aimed at both neuroprotection and neuroinflammation reduction may prove particularly effective in slowing the progression of these diseases. The endogenous lipid mediator palmitoylethanolamide (PEA) displayed neuroprotective and anti(neuro)inflammatory properties, and demonstrated interesting potential as a novel treatment for Alzheimer's disease. OBJECTIVE AND METHODS: We firstly evaluated whether astrocytes could participate in regulating the Aβ42-induced neuronal damage, by using primary mouse astrocytes cell cultures and mixed astrocytes-neurons cultures. Furthermore, the possible protective effects of PEA against Aβ42-induced neuronal toxicity have also been investigated by evaluating neuronal viability, apoptosis, and morphometric parameters. RESULTS: The presence of astrocytes pre-exposed to Aβ42 (0.5μM; 24 h) induced a reduction of neuronal viability in primary mouse astrocytes-neurons co-cultures. Furthermore, under these experimental conditions, an increase in the number of neuronal apoptotic nuclei and a decrease in the number of MAP-2 positive neurons were observed. Finally, astrocytic Aβ42 pre-exposure induced an increase in the number of neurite aggregations/100μm as compared to control (i.e., untreated) astrocytes-neurons co-cultures. These effects were not observed in neurons cultured in the presence of astrocytes pre-exposed to PEA (0.1μM), applied 1 h before and maintained during Aβ42 treatment. CONCLUSION: Astrocytes contribute to Aβ42-induced neurotoxicity and PEA, by blunting Aβ42-induced astrocyte activation, improved neuronal survival in mouse astrocyte-neuron co-cultures.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Animals, Newborn; Anti-Inflammatory Agents, Non-Steroidal; Astrocytes; Cell Survival; Cells, Cultured; Cerebral Cortex; Coculture Techniques; Ethanolamines; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Neurons; Palmitic Acids; Peptide Fragments; Time Factors

Parietal Involvement in the Semantic Variant of Primary Progressive Aphasia with Alzheimer's Disease Cerebrospinal Fluid Profile. - Bera, Géraldine; Migliaccio, Raffaella; Michelin, Thibaut; Lamari, Foudil; Ferrieux, Sophie; Nogues, Marie; Bertin, Hugo; Habert, Marie Odile; Dubois, Bruno; Teichmann, Marc; Kas, Aurélie (J Alzheimers Dis, 2018)
Semantic variant of primary progressive aphasia (svPPA) is typically associated with non-Alzheimer's disease (AD) pathology. However, some anatomopathological studies have found AD lesions in those patients. We compared brain perfusion SPECT of 18 svPPA patients with cerebrospinal fluid (CSF) biomarkers indicative of non-AD pathology (svPPA-nonAD) and three svPPA patients with CSF biomarkers indicative of underlying AD (svPPA-AD). All svPPA patients had severe left temporopolar hypoperfusion. SvPPA-nonAD had additional anterior cingulate and mediofrontal hypoperfusion, whereas svPPA-AD had greater left parietal and posterior cingulate involvement. Parietal damage in svPPA constitutes a biomarker for underlying Alzheimer pathology thus refining the classification of this PPA variant.

Past to Future: What Animal Models Have Taught Us About Alzheimer's Disease. - Martini, Alessandra C; Forner, Stefania; Trujillo-Estrada, Laura; Baglietto-Vargas, David; LaFerla, Frank M (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) impairs memory and causes significant cognitive deficits. The disease course is prolonged, with a poor prognosis, and thus exacts an enormous economic and social burden. Over the past two decades, genetically engineered mouse models have proven indispensable for understanding AD pathogenesis, as well as for discovering new therapeutic targets. Here we highlight significant studies from our laboratory that have helped advance the AD field by elucidating key pathogenic processes operative in AD and exploring a variety of aspects of the disease which may yield novel therapeutic strategies for combatting this burdensome disease.

Perspectives on Communicating Biomarker-Based Assessments of Alzheimer's Disease to Cognitively Healthy Individuals. - Milne, Richard; Bunnik, Eline; Diaz, Ana; Richard, Edo; Badger, Shirlene; Gove, Dianne; Georges, Jean; Fauria, Karine; Molinuevo, Jose-Luis; Wells, Katie; Ritchie, Craig; Brayne, Carol (J Alzheimers Dis, 2018)
In clinical trials which target pathophysiological mechanisms associated with Alzheimer's disease, research participants who are recruited based on biomarker test results should be informed about their increased risk of developing Alzheimer's dementia. This paper presents the results of a qualitative focus group study of attitudes and concerns toward learning information about biomarker-based risk status among healthy research participants in the United Kingdom and Spain and people with dementia and their supporters/caregivers from countries represented in the European Working Group of People with Dementia of Alzheimer Europe. The study identified expectations related to learning risk status and preferences related to the content, quality, and follow-up of the disclosure process. The latter emphasize distinctions between risk and diagnoses, the importance of clear information about risk, and suggestions for risk reduction, as well as expectations for follow up and support. The implications of these preferences for practice are discussed. Providing details of research participants' experience and views may serve as a guide for the development of processes for the responsible disclosure of Alzheimer's disease biomarkers.
Keywords: Adult; Aged; Alzheimer Disease; Biomarkers; Caregivers; Disclosure; Female; Focus Groups; Humans; Male; Middle Aged; Qualitative Research; Risk Factors; Spain; United Kingdom

PICALM Gene Methylation in Blood of Alzheimer's Disease Patients Is Associated with Cognitive Decline. - Mercorio, Roberta; Pergoli, Laura; Galimberti, Daniela; Favero, Chiara; Carugno, Michele; Dalla Valle, Elisabetta; Barretta, Francesco; Cortini, Francesca; Scarpini, Elio; Valentina, Valentina Bollati; Pesatori, Angela Cecilia (J Alzheimers Dis, 2018)
Epigenetic mechanisms might be involved in Alzheimer's disease (AD). Genetic polymorphisms in several genes, including APOE (Apolipoprotein E), PSEN1 (Presenilin 1), CR1 (Complement receptor 1), and PICALM (Phosphatidylinositol binding clathrin assembly protein), have been associated to an increased AD risk. However, data regarding methylation of these specific genes are lacking. We evaluated DNA methylation measured by quantitative bisulfite-PCR pyrosequencing in 43 AD patients and 38 healthy subjects (HS). In a multivariate age- and gender-adjusted model, PICALM methylation was decreased in AD compared to HS (mean = 3.54 and 4.63, respectively, p = 0.007). In AD, PICALM methylation level was also positively associated to Mini-Mental Scale Examination (MMSE) score (percent change 3.48%, p = 0.008). Moreover, a negative association between PICALM methylation and age was observed only in HS (percent change - 2.29%, p = 0.002). In conclusion, our data suggest a possible role of PICALM methylation in AD, particularly related to cognitive function. Given the small study sample and the associative nature of our study, further prospective investigations are required to assess the dynamics of DNA methylation in the early stages of AD development.

Post Traumatic Stress Disorder Heralding the Onset of Semantic Frontotemporal Dementia. - Bonanni, Laura; Franciotti, Raffaella; Martinotti, Giovanni; Vellante, Federica; Flacco, Maria Elena; Di Giannantonio, Massimo; Thomas, Astrid; Onofrj, Marco (J Alzheimers Dis, 2018)
BACKGROUND: Post traumatic stress disorder (PTSD) is associated with cognitive decline. The dementia type following PTSD is unclear. OBJECTIVE: To assess whether PTSD is associated with a specific dementia. METHODS: Prospective study: 46 PTSD patients (DSM-IV-TR) were followed for 6-10 years with clinical, neuropsychological, imaging evaluations for possible development of dementia.Retrospective study:849 dementia patients followed during 1999-2014 (509 Alzheimer's disease, AD; 207 dementia with Lewy bodies, DLB; 90 vascular dementia, VaD; 43 frontotemporal dementia, FTD) and 287 patients with any neurological condition (including patients with/without dementia) were evaluated for the presence of PTSD in their history. RESULTS: Prospective study: 8 patients developed dementia; 1 AD, 1 DLB, 6 semantic FTD (13.0% of the PTSD population). Retrospective study: 38 patients (4.5%) had a history of PTSD; 3.5% of AD, 4.3% of DLB, 14.0% of FTD, 5.6% of VaD. The percentage was higher in FTD than in AD or DLB (χ2 = 10, p = 0.001, and χ2 = 6, p = 0.02). At difference with AD, DLB, or VaD, FTD incidence among dementia patients with PTSD history (38 patients) was higher than in the dementia population overall (16% versus 5%, χ2 = 8, p = 0.005). The impact of possible demographical/clinical confounders (age, gender, MMSE) was excluded by Poisson regression. PTSD prevalence in the comparative group without dementia matched the prevalence in the Italian general population (1.1%). PTSD prevalence in the demented comparative group matched the prevalence in our dementia retrospective cohort, 3.7%). DISCUSSION: PTSD was associated with the development of semantic FTD.

Potential of Low Dose Leuco-Methylthioninium Bis(Hydromethanesulphonate) (LMTM) Monotherapy for Treatment of Mild Alzheimer's Disease: Cohort Analysis as Modified Primary Outcome in a Phase III Clinical Trial. - Wilcock, Gordon K; Gauthier, Serge; Frisoni, Giovanni B; Jia, Jianping; Hardlund, Jiri H; Moebius, Hans J; Bentham, Peter; Kook, Karin A; Schelter, Bjoern O; Wischik, Damon J; Davis, Charles S; Staff, Roger T; et al. (J Alzheimers Dis, 2018)
BACKGROUND: LMTM is being developed as a treatment for AD based on inhibition of tau aggregation. OBJECTIVES: To examine the efficacy of LMTM as monotherapy in non-randomized cohort analyses as modified primary outcomes in an 18-month Phase III trial in mild AD. METHODS: Mild AD patients (n = 800) were randomly assigned to 100 mg twice a day or 4 mg twice a day. Prior to unblinding, the Statistical Analysis Plan was revised to compare the 100 mg twice a day as monotherapy subgroup (n = 79) versus 4 mg twice a day as randomized (n = 396), and 4 mg twice a day as monotherapy (n = 76) versus 4 mg twice a day as add-on therapy (n = 297), with strong control of family-wise type I error. RESULTS: The revised analyses were statistically significant at the required threshold of p < 0.025 in both comparisons for change in ADAS-cog, ADCS-ADL, MRI atrophy, and glucose uptake. The brain atrophy rate was initially typical of mild AD in both add-on and monotherapy groups, but after 9 months of treatment, the rate in monotherapy patients declined significantly to that reported for normal elderly controls. Differences in severity or diagnosis at baseline between monotherapy and add-on patients did not account for significant differences in favor of monotherapy. CONCLUSIONS: The results are consistent with earlier studies in supporting the hypothesis that LMTM might be effective as monotherapy and that 4 mg twice a day may serve as well as higher doses. A further suitably randomized trial is required to test this hypothesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antipsychotic Agents; Cohort Studies; Double-Blind Method; Female; Humans; International Cooperation; Male; Mental Status and Dementia Tests; Methylene Blue; Middle Aged; Treatment Outcome

Predicting and Tracking Short Term Disease Progression in Amnestic Mild Cognitive Impairment Patients with Prodromal Alzheimer's Disease: Structural Brain Biomarkers. - Marizzoni, Moira; Ferrari, Clarissa; Jovicich, Jorge; Albani, Diego; Babiloni, Claudio; Cavaliere, Libera; Didic, Mira; Forloni, Gianluigi; Galluzzi, Samantha; Hoffmann, Karl-Titus; Molinuevo, José Luis; Nobili, Flavio; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Early Alzheimer's disease (AD) detection using cerebrospinal fluid (CSF) biomarkers has been recommended as enrichment strategy for trials involving mild cognitive impairment (MCI) patients. OBJECTIVE: To model a prodromal AD trial for identifying MRI structural biomarkers to improve subject selection and to be used as surrogate outcomes of disease progression. METHODS: APOE ɛ4 specific CSF Aβ42/P-tau cut-offs were used to identify MCI with prodromal AD (Aβ42/P-tau positive) in the WP5-PharmaCog (E-ADNI) cohort. Linear mixed models were performed 1) with baseline structural biomarker, time, and biomarker×time interaction as factors to predict longitudinal changes in ADAS-cog13, 2) with Aβ42/P-tau status, time, and Aβ42/P-tau status×time interaction as factors to explain the longitudinal changes in MRI measures, and 3) to compute sample size estimation for a trial implemented with the selected biomarkers. RESULTS: Only baseline lateral ventricle volume was able to identify a subgroup of prodromal AD patients who declined faster (interaction, p = 0.003). Lateral ventricle volume and medial temporal lobe measures were the biomarkers most sensitive to disease progression (interaction, p≤0.042). Enrichment through ventricular volume reduced the sample size that a clinical trial would require from 13 to 76%, depending on structural outcome variable. The biomarker needing the lowest sample size was the hippocampal subfield GC-ML-DG (granule cells of molecular layer of the dentate gyrus) (n = 82 per arm to demonstrate a 20% atrophy reduction). CONCLUSION: MRI structural biomarkers can enrich prodromal AD with fast progressors and significantly decrease group size in clinical trials of disease modifying drugs.

Predictors of Delirium Development in Older Medical Inpatients: Readily Identifiable Factors at Admission. - O'Regan, Niamh A; Fitzgerald, James; Adamis, Dimitrios; Molloy, David William; Meagher, David; Timmons, Suzanne (J Alzheimers Dis, 2018)
BACKGROUND: Identifying patients at high risk of delirium is crucial to facilitate prevention. Although dementia is the most consistent risk factor across populations, it remains under-diagnosed. Hence understanding other markers of delirium vulnerability on admission is important. OBJECTIVE: We aimed to identify predictors of incident delirium development in older medical inpatients that were readily identifiable at presentation to the emergency department. METHODS: Medical inpatients of ≥70 years were assessed on admission for delirium using the Revised Delirium Rating Scale (DRS-R98) and those with prevalent delirium were excluded. Consenting non-delirious patients were then assessed daily using the DRS-R98. Data pertaining to multiple baseline delirium risk factors were collected, including pre-morbid dementia. Multivariable logistic regression was used to examine which factors predicted the development of incident delirium. RESULTS: Of 555 patients approached, 184 (33.1%) had prevalent delirium. Following other exclusions, 191 were included in the study and 61 developed incident delirium. Predictors of incident delirium on multivariable analysis, controlling for confounders, were dementia (OR 2.54, 95% CI 1.01-6.43, p = 0.048); Barthel Index score (OR 1.15 for each unit decrease in score, 95% CI 1.06-1.25, p = 0.001), and Modified Cumulative Illness Rating Scale score (OR 1.13 for each unit increase in score, 95% CI 1.05-1.22, p = 0.001). CONCLUSION: Dementia is a well-known risk factor for delirium; however, it too is under-recognized and on admission can be missed. Conversely, the Barthel Index is a simple and widely used measure of functional ability that may prove useful in stratifying those at risk of in-hospital delirium on admission.

Preoperative Phosphorylated Tau Concentration in the Cerebrospinal Fluid Can Predict Cognitive Function Three Years after Shunt Surgery in Patients with Idiopathic Normal Pressure Hydrocephalus. - Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Kawamura, Kaito; Kamohara, Chihiro; Fusegi, Keiko; Harada, Yoshinao; Hara, Takeshi; Sugano, Hidenori; Tange, Yuichi; Karagiozov, Kostadin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Idiopathic normal pressure hydrocephalus (iNPH) is commonly treated by cerebrospinal fluid (CSF) shunting. However, the long-term efficacy of shunt intervention in the presence of comorbid Alzheimer's disease (AD) pathology is debated. OBJECTIVE: To identify AD-associated CSF biomarkers predictive of shunting surgery outcomes in patients with iNPH. METHODS: Preoperative levels of total and phosphorylated Tau (p-Tau) were measured in 40 patients with iNPH divided into low (<30 pg/mL) and high (≥30 pg/mL) p-Tau groups and followed up for three years after lumboperitoneal shunting. The modified Rankin Scale (mRS), Mini-Mental State Examination (MMSE), Frontal Assessment Battery, and iNPH Grading Scale scores were compared between the age-adjusted low (n = 24; mean age 75.7 years [SD 5.3]) and high (n = 11; mean age 76.0 years [SD 5.6]) p-Tau groups. RESULTS: Cognitive function improved early in the low p-Tau group and was maintained thereafter (p = 0.005). In contrast, the high p-Tau group showed a gradual decline to baseline levels by the third postoperative year (p = 0.040). Although the p-Tau concentration did not correlate with the preoperative MMSE score, a negative correlation appeared and strengthened during follow-up (R2 = 0.352, p < 0.001). Furthermore, the low p-Tau group showed rapid and sustained mRS grade improvement, whereas mRS performance gradually declined in the high p-Tau group. CONCLUSIONS: Preoperative CSF p-Tau concentration predicted some aspects of cognitive function after shunt intervention in patients with iNPH. The therapeutic effects of shunt treatment were shorter-lasting in patients with coexisting AD pathology.

Prevalence, Safety, and Effectiveness of Oral Anticoagulant Use in People with and without Dementia or Cognitive Impairment: A Systematic Review and Meta-Analysis. - Fanning, Laura; Ryan-Atwood, Taliesin E; Bell, J Simon; Meretoja, Atte; McNamara, Kevin P; Dārziņš, Pēteris; Wong, Ian C K; Ilomäki, Jenni (J Alzheimers Dis, 2018)
BACKGROUND: Differences in management and outcomes of oral anticoagulant (OAC) use may exist for people with and without dementia or cognitive impairment (CI). OBJECTIVE: To systematically review the prevalence and safety and effectiveness outcomes of OAC use in people with and without dementia or CI. METHODS: MEDLINE, EMBASE, and CINAHL were searched for studies reporting prevalence or safety and effectiveness outcomes of OAC use for people with and without dementia, published between 2000 to September 2017. Study selection, data extraction, and quality assessment were performed by two reviewers. RESULTS: studies met pre-specified inclusion criteria (21 prevalence studies, 6 outcomes studies). People with dementia had 52% lower odds of receiving OAC compared to people without dementia. Mean OAC prevalence was 32% for people with dementia, compared to 48% without dementia. There was no difference in the composite outcome of embolic events, myocardial infarction, and all-cause death between dementia and non-dementia groups (adjusted hazard ratio (HR) 0.72, 95% CI, 0.45-1.14, p = 0.155). Bleeding rate was lower for people without dementia (HR 0.56, 95% CI, 0.37-0.85). Adverse warfarin events were more common for residents of long-term care with dementia (adjusted incidence rate ratio 1.48, 95% CI, 1.20-1.82). Community-dwelling people with dementia treated with warfarin had poorer anticoagulation control than those without dementia (mean time in therapeutic range (TTR) % ±SD, 38±26 (dementia), 61±27 (no dementia), p < 0.0001). CONCLUSION: A lower proportion of people with dementia received oral anticoagulation compared with people without dementia. People with dementia had higher bleeding risk and poorer anticoagulation control when treated with warfarin.

Prodromal Alzheimer's Disease Demonstrates Increased Errors at a Simple and Automated Anti-Saccade Task. - Holden, John G; Cosnard, Alexandre; Laurens, Brice; Asselineau, Julien; Biotti, Damien; Cubizolle, Stéphanie; Dupouy, Sandrine; Formaglio, Maıté; Koric, Lejla; Seassau, Magali; Tilikete, Caroline; Vighetto, Alain; et al. (J Alzheimers Dis, 2018)
Saccade alterations are potential early signs of Alzheimer's disease. However, uncertainty persists in how early and reliably automated saccade recording systems detect impairments. This multicenter pathophysiological case-control transversal study explored saccade execution in carefully diagnosed amnestic mild cognitive impairment patients fulfilling research criteria for prodromal Alzheimer's disease (n = 29), as compared to both aged-matched mild Alzheimer's disease patients (n = 23) and controls (n = 27). Auto-coded saccades from horizontal (gap) vertical (step) stimulus elicited pro-saccades, and anti-saccade (gap) tasks were compared across the 3 groups. Mild cognitive impairment patients committed significantly more anti-saccade errors compared to controls (46.9 versus 24.3%, p < 0.001). Conventional analyses of the auto-coded stimulus elicited saccades parameters did not distinguish the amnestic mild cognitive impairment from controls or the mild Alzheimer's disease group. However, an offline analysis of manually coded saccade latencies, using resampling statistics did reveal subtle differences among the groups. Analysis of the manually coded data revealed that the mild Alzheimer's disease group had a reliably larger self-corrected error-rate than in amnestic mild cognitive impairment and controls (p = 0.003). Analysis of the manually coded saccade latencies, using more sensitive lognormal bootstrap analysis revealed a continuum, from amnestic mild cognitive impairment to mild Alzheimer's disease, of an increased severity of impaired inhibition of stimulus elicited saccades and correct voluntary saccade initiation. Anti-saccade error rates and psychometric measures of executive and several other cognitive functions were moderately and negatively correlated. Overall, inhibitory impairments in stimulus elicited saccades, characteristic of Alzheimer's disease, may be detected early in presumed prodromal patients using a simple, automated anti-saccade task.

Profiling of Specific Gene Expression Pathways in Peripheral Cells from Prodromal Alzheimer's Disease Patients. - Serpente, Maria; Fenoglio, Chiara; Cioffi, Sara Maria Giulia; Oldoni, Emanuela; Arcaro, Marina; Arighi, Andrea; Fumagalli, Giorgio Giulio; Ghezzi, Laura; Scarpini, Elio; Galimberti, Daniela (J Alzheimers Dis, 2018)
Herein, we performed a gene expression profiling in a cohort of 10 mild cognitive impairment (MCI), subdivided, according to the analysis of cerebrospinal fluid biomarkers, in prodromal Alzheimer's disease (AD) and non-AD MCI, as compared with 27 AD patients and 24 controls, in order to detect early gene expression alterations. We observed a significant upregulation of insulin (INS) and INS Receptor (INSR) expression levels in AD both prodromal and fully symptomatic, as compared with controls, but not in MCI subjects. Our results suggest an early dysregulation of INS and INSR in AD pathogenesis and pave the way to a possible utility of these transcripts as peripheral biomarkers.
Keywords: Aged; Alzheimer Disease; Antigens, CD; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Female; Gene Expression Profiling; Humans; Insulin; Male; Middle Aged; Receptor, Insulin

Quantitative Genetics Validates Previous Genetic Variants and Identifies Novel Genetic Players Influencing Alzheimer's Disease Cerebrospinal Fluid Biomarkers. - Ramos de Matos, Mafalda; Ferreira, Catarina; Herukka, Sanna-Kaisa; Soininen, Hilkka; Janeiro, André; Santana, Isabel; Baldeiras, Ines; Almeida, Maria Rosário; Lleo, Alberto; Dols-Icardo, Oriol; Alcolea, Daniel; Benussi, Luisa; et al. (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers have been extensively investigated in the Alzheimer's disease (AD) field, and are now being applied in clinical practice. CSF amyloid-beta (Aβ1-42), total tau (t-tau), and phosphorylated tau (p-tau) reflect disease pathology, and may be used as quantitative traits for genetic analyses, fostering the identification of new genetic factors and the proposal of novel biological pathways of the disease. In patients, the concentration of CSF Aβ1-42 is decreased due to the accumulation of Aβ1-42 in amyloid plaques in the brain, while t-tau and p-tau levels are increased, indicating the extent of neuronal damage. To better understand the biological mechanisms underlying the regulation of AD biomarkers, and its relation to AD, we examined the association between 36 selected single nucleotide polymorphisms (SNPs) and AD biomarkers Aβ1-42, t-tau, and p-tau in CSF in a cohort of 672 samples (571 AD patients and 101 controls) collected within 10 European consortium centers.Our results highlighted five genes, APOE, LOC100129500, PVRL2, SNAR-I, and TOMM40, previously described as main players in the regulation of CSF biomarkers levels, further reinforcing a role for these in AD pathogenesis. Three new AD susceptibility loci, INPP5D, CD2AP, and CASS4, showed specific association with CSF tau biomarkers. The identification of genes that specifically influence tau biomarkers point out to mechanisms, independent of amyloid processing, but in turn related to tau biology that may open new venues to be explored for AD treatment.

The Rationale and Design of the Reducing Pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR) Trial. - Kehoe, Patrick G; Blair, Peter S; Howden, Beth; Thomas, David L; Malone, Ian B; Horwood, Jeremy; Clement, Clare; Selman, Lucy E; Baber, Hannah; Lane, Athene; Coulthard, Elizabeth; Passmore, Anthony Peter; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Anti-hypertensives that modify the renin angiotensin system may reduce Alzheimer's disease (AD) pathology and reduce the rate of disease progression. OBJECTIVE: To conduct a phase II, two arm, double-blind, placebo-controlled, randomized trial of losartan to test the efficacy of Reducing pathology in Alzheimer's Disease through Angiotensin TaRgeting (RADAR). METHODS: Men and women aged at least 55 years with mild-to-moderate AD will be randomly allocated 100 mg encapsulated generic losartan or placebo once daily for 12 months after successful completion of a 2-week open-label phase and 2-week placebo washout to establish drug tolerability. 228 participants will provide at least 182 subjects with final assessments to provide 84% power to detect a 25% difference in atrophy rate (therapeutic benefit) change over 12 months at an alpha level of 0.05. We will use intention-to-treat analysis, estimating between-group differences in outcomes derived from appropriate (linear or logistic) multivariable regression models adjusting for minimization variables. RESULTS: The primary outcome will be rate of whole brain atrophy as a surrogate measure of disease progression. Secondary outcomes will include changes to 1) white matter hyperintensity volume and cerebral blood flow; 2) performance on a standard series of assessments of memory, cognitive function, activities of daily living, and quality of life. Major assessments (for all outcomes) and relevant safety monitoring of blood pressure and bloods will be at baseline and 12 months. Additional cognitive assessment will also be conducted at 6 months along with safety blood pressure and blood monitoring. Monitoring of blood pressure, bloods, and self-reported side effects will occur during the open-label phase and during the majority of the post-randomization dispensing visits. CONCLUSION: This study will identify whether losartan is efficacious in the treatment of AD and whether definitive Phase III trials are warranted.
Keywords: Activities of Daily Living; Alzheimer Disease; Antihypertensive Agents; Atrophy; Blood Pressure Monitors; Brain; Clinical Trials, Phase II as Topic; Disease Progression; Double-Blind Method; Female; Humans; Losartan; Magnetic Resonance Imaging; Male; Multivariate Analysis; Quality of Life; Randomized Controlled Trials as Topic; Regression Analysis; Renin-Angiotensin System

Reappraisal of Aβ40 and Aβ42 Peptides Measurements in Cerebrospinal Fluid of Patients with Alzheimer's Disease. - Fiorini, Michele; Bongianni, Matilde; Benedetti, Maria Donata; Monaco, Salvatore; Zanusso, Gianluigi (J Alzheimers Dis, 2018)
Cerebrospinal fluid (CSF) biomarkers are currently included in the diagnostic criteria for Alzheimer's disease (AD), in particular, decreased concentrations of amyloid-β peptide 1-42 (Aβ42) in the CSF, coupled with increased levels of tau and phosphorylated tau proteins, are supportive of AD diagnosis. To date, the quantification of Aβ42 levels with antibody-dependent immunoassay shows a marked variability among different laboratories and is also affected by different pre-analytical factors, suggesting that part of Aβ42 peptides might be aggregated and thus undetected by antibodies. To bypass an antibody-dependent measurement, we determined the Aβ40 and Aβ42 levels by immunoblot. We analyzed CSF samples from 35 patients with clinical diagnosis of probable AD and from 15 age-matched normal controls; CSF Aβ levels were determined by two different ELISA kits and by immunoblot analysis. Aβ40 levels measured by ELISA were comparable to those obtained by immunoblot, whereas CSF concentrations of Aβ42 measured by ELISA were significantly lower compared to values obtained by immunoblot quantification. Biochemical analysis, following 1D- and 2D-PAGE analysis, showed that the qualitative composition of Aβ peptides in the CSF is similar in AD and controls but different from that of AD brain tissues. Moreover, sedimentation velocity in sucrose gradient of CSF and brain homogenate from AD demonstrated that Aβ42 in CSF is different from Aβ42 in brain in terms of solubility and aggregation state.

Regional White Matter Hyperintensity Influences Grey Matter Atrophy in Mild Cognitive Impairment. - Vipin, Ashwati; Foo, Heidi Jing Ling; Lim, Joseph Kai Wei; Chander, Russell Jude; Yong, Ting Ting; Ng, Adeline Su Lyn; Hameed, Shahul; Ting, Simon Kang Seng; Zhou, Juan; Kandiah, Nagaendran (J Alzheimers Dis, 2018)
The association between cerebrovascular disease pathology (measured by white matter hyperintensities, WMH) and brain atrophy in early Alzheimer's disease (AD) remain to be elucidated. Thus, we investigated how WMH influence neurodegeneration and cognition in prodromal and clinical AD. We examined 51 healthy controls, 35 subjects with mild cognitive impairment (MCI), and 30 AD patients. We tested how total and regional WMH is related to specific grey matter volume (GMV) reductions in MCI and AD compared to controls. Stepwise regression analysis was further performed to investigate the association of GMV and regional WMH volume with global cognition. We found that total WMH volume was highest in AD but showed the strongest association with lower GMV in MCI. Frontal and parietal WMH had the most extensive influence on GMV loss in MCI. Additionally, parietal lobe WMH volume (but not hippocampal atrophy) was significantly associated with global cognition in MCI while smaller hippocampal volume (but not WMH volume) was associated with lower global cognition in AD. Thus, although WMH volume was highest in AD subjects, it had a more pervasive influence on brain structure and cognitive impairment in MCI. Our study thus highlights the importance of early detection of cerebrovascular disease, as its intervention at the MCI stage might potentially slow down neurodegeneration.

REM Sleep Behavior Disorder and Alzheimer's Disease: Definitely No Relationship? - Galbiati, Andrea; Carli, Giulia; Hensley, Michael; Ferini-Strambi, Luigi (J Alzheimers Dis, 2018)
Rapid eye movement (REM) sleep behavior disorder (RBD) is a REM sleep parasomnia characterized by the loss of the typical muscular atonia present during healthy REM sleep. RBD can occur in the absence of other neurological conditions or in association with a neurodegenerative disorder. It is now well established that RBD is a strong predictor of neurodegeneration, in particular synucleinopathies, such as Parkinson's disease, Lewy body dementia (LBD), or multiple system atrophy. However, some longitudinal studies report that a minority of patients develop either overlapping form of dementia or Alzheimer disease's (AD). Although AD is reported as a possible development in patients with RBD, it is in a limited number of cases and there are concerns about the accuracy of the diagnostic criteria. Neuropsychological impairments identified in cross-sectional studies of RBD patients describe a profile similar to that observed in dementia related to synucleinopathies. However, only deficits in executive function predict the development of neurodegeneration. Longitudinal studies reported the development of AD in RBD patients in about 7% of cases with variability ranging from 3% and 11%. Since the majority of longitudinal investigations do not report AD as a possible development for RBD patients the proportion may be overestimated. The study of the relationship between RBD and AD may be confounded by two factors that lead to misdiagnosis: the use of clinical criteria alone and the overlap between the clinical features and neuropathology of AD and LBD. Future studies to investigate this association must use updated diagnostic criteria incorporating ancillary investigations.

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Risk of Conversion to Dementia in a Mild Behavioral Impairment Group Compared to a Psychiatric Group and to a Mild Cognitive Impairment Group. - Taragano, Fernando E; Allegri, Ricardo F; Heisecke, Silvina L; Martelli, María I; Feldman, Mónica L; Sánchez, Viviana; García, Virginia A; Tufro, Graciela; Castro, Diego M; Leguizamón, Patricio Perez; Guelar, Verónica; Ruotolo, Eva; et al. (J Alzheimers Dis, 2018)
BACKGROUND: There is insufficient available information on behavioral changes in the absence of cognitive impairment as factors increasing the risk of conversion to dementia. OBJECTIVE: To observe and analyze patients with mild behavioral impairment (MBI), mild cognitive impairment (MCI), and a psychiatry group (PG) to compare the risk of progression to dementia. METHODS: From 677 initially assessed ≥60-year-old patients, a series of 348 patients was studied for a five-year period until censoring or conversion to dementia: 96 with MBI, 87 with MCI, and 165 with general psychiatry disorders, including 4 subgroups: Anxiety, Depression, Psychosis and Others. All patients were assessed with clinical, psychiatric, neurological, neuropsychological, and neuroimaging studies. RESULTS: From 348 patients, 126 evolved to dementia (36.2%). Conversion was significantly higher in MBI (71.5%), followed by the MCI-MBI overlap (59.6%) and MCI (37.8%) groups, compared to PG (13.9%) (Log-rank p < 0.001). MCI patients mostly converted to Alzheimer's dementia, while MBI converted to frontotemporal dementia and Lewy body dementia. Patients in PG converted to Lewy body dementia and frontotemporal dementia. CONCLUSION: Conversion to dementia is significantly higher in patients with neuropsychiatric symptoms. The MBI concept generates a new milestone in the refining of diagnosis of neurodegenerative diseases and the possibility of creating neuropsychiatric profiles. Its earlier identification will allow new possibilities for therapeutic intervention.

Role of Amyloid-β and Tau Proteins in Alzheimer's Disease: Confuting the Amyloid Cascade. - Gulisano, Walter; Maugeri, Daniele; Baltrons, Marian A; Fà, Mauro; Amato, Arianna; Palmeri, Agostino; D'Adamio, Luciano; Grassi, Claudio; Devanand, D P; Honig, Lawrence S; Puzzo, Daniela; Arancio, Ottavio (J Alzheimers Dis, 2018)
The "Amyloid Cascade Hypothesis" has dominated the Alzheimer's disease (AD) field in the last 25 years. It posits that the increase of amyloid-β (Aβ) is the key event in AD that triggers tau pathology followed by neuronal death and eventually, the disease. However, therapeutic approaches aimed at decreasing Aβ levels have so far failed, and tau-based clinical trials have not yet produced positive findings. This begs the question of whether the hypothesis is correct. Here we have examined literature on the role of Aβ and tau in synaptic dysfunction, memory loss, and seeding and spreading of AD, highlighting important parallelisms between the two proteins in all of these phenomena. We discuss novel findings showing binding of both Aβ and tau oligomers to amyloid-β protein precursor (AβPP), and the requirement for the presence of this protein for both Aβ and tau to enter neurons and induce abnormal synaptic function and memory. Most importantly, we propose a novel view of AD pathogenesis in which extracellular oligomers of Aβ and tau act in parallel and upstream of AβPP. Such a view will call for a reconsideration of therapeutic approaches directed against Aβ and tau, paving the way to an increased interest toward AβPP, both for understanding the pathogenesis of the disease and elaborating new therapeutic strategies.

The Role of Cognitive Reserve in Alzheimer's Disease and Aging: A Multi-Modal Imaging Review. - Menardi, Arianna; Pascual-Leone, Alvaro; Fried, Peter J; Santarnecchi, Emiliano (J Alzheimers Dis, 2018)
Comforts in modern society have generally been associated with longer survival rates, enabling individuals to reach advanced age as never before in history. With the increase in longevity, however, the incidence of neurodegenerative diseases, especially Alzheimer's disease, has also doubled. Nevertheless, most of the observed variance, in terms of time of clinical diagnosis and progression, often remains striking. Only recently, differences in the social, educational and occupational background of the individual, as proxies of cognitive reserve (CR), have been hypothesized to play a role in accounting for such discrepancies. CR is a well-established concept in literature; lots of studies have been conducted in trying to better understand its underlying neural substrates and associated biomarkers, resulting in an incredible amount of data being produced. Here, we aimed to summarize recent relevant published work addressing the issue, gathering evidence for the existence of a common path across research efforts that might ease future investigations by providing a general perspective on the actual state of the arts. An innovative model is hereby proposed, addressing the role of CR across structural and functional evidences, as well as the potential implementation of non-invasive brain stimulation techniques in the causal validation of such theoretical frame.

Role of Genetics and Epigenetics in the Pathogenesis of Alzheimer's Disease and Frontotemporal Dementia. - Fenoglio, Chiara; Scarpini, Elio; Serpente, Maria; Galimberti, Daniela (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and frontotemporal dementia (FTD) represent the first cause of dementia in senile and pre-senile population, respectively. A percentage of cases have a genetic cause, inherited with an autosomal dominant pattern of transmission. The majority of cases, however, derive from complex interactions between a number of genetic and environmental factors. Gene variants may act as risk or protective factors. Their combination with a variety of environmental exposures may result in increased susceptibility to these diseases or may influence their course. The scenario is even more complicated considering the effect of epigenetics, which encompasses mechanisms able to alter the expression of genes without altering the DNA sequence. In this review, an overview of the current genetic and epigenetic progresses in AD and FTD will be provided, with particular focus on 1) causative genes, 2) genetic risk factors and disease modifiers, and 3) epigenetics, including methylation, non-coding RNAs and chromatin remodeling.
Keywords: Alzheimer Disease; Animals; Epigenesis, Genetic; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans

The Role of the Gut Microbiota in the Metabolism of Polyphenols as Characterized by Gnotobiotic Mice. - Pasinetti, Giulio Maria; Singh, Risham; Westfall, Susan; Herman, Francis; Faith, Jeremiah; Ho, Lap (J Alzheimers Dis, 2018)
A growing body of experimental data suggests that microbes in the gut influence behavior and can alter brain physiology and neurochemistry. Although promising, researchers are only starting to understand the potential of the gut microbiota for use in neurological disease. Recent evidence demonstrated that gastrointestinal activities are linked to mood disorders such as anxiety, depression, and most recently, cognitive functions in age-related neurodegenerative disorders. Studies from our group and others are uncovering new evidence suggesting that the gut microbiota plays a crucial role in the metabolism and bioavailability of certain dietary compounds and synthetic drugs. Based on this evidence, this review article will discuss the implications of the gut microbiota in mechanisms of bioavailability and biotransformation with an emphasis on dietary polyphenol compounds. This will be followed by a survey of ongoing innovative research identifying the ability of individual gut bacteria to enhance the bioavailability of gut-derived, brain-penetrating, bioactive polyphenol metabolites that ultimately influence mechanisms associated with the promotion of resilience against psychological and cognitive impairment in response to stress. Lastly, current research initiatives aimed at promoting the generation of brain bioactive polyphenol metabolites by specialized gut microbes will be discussed, specifically the use of gnotobiotic mice to develop bioengineered second generation probiotics. We propose that leveraging the gut microbial ecosystem to generate brain targeted bioactive metabolites from dietary polyphenols can attenuate lifestyle risk factors and promote resilience against age-related cognitive decline.

Separating Symptomatic Alzheimer's Disease from Depression based on Structural MRI. - Klöppel, Stefan; Kotschi, Maria; Peter, Jessica; Egger, Karl; Hausner, Lucrezia; Frölich, Lutz; Förster, Alex; Heimbach, Bernhard; Normann, Claus; Vach, Werner; Urbach, Horst; Abdulkadir, Ahmed (J Alzheimers Dis, 2018)
Older patients with depression or Alzheimer's disease (AD) at the stage of early dementia or mild cognitive impairment may present with objective cognitive impairment, although the pathology and thus therapy and prognosis differ substantially. In this study, we assessed the potential of an automated algorithm to categorize a test set of 65 T1-weighted structural magnetic resonance images (MRI). A convenience sample of elderly individuals fulfilling clinical criteria of either AD (n = 28) or moderate and severe depression (n = 37) was recruited from different settings to assess the potential of the pattern recognition method to assist in the differential diagnosis of AD versus depression. We found that our algorithm learned discriminative patterns in the subject's grey matter distribution reflected by an area under the receiver operator characteristics curve of up to 0.83 (confidence interval ranged from 0.67 to 0.92) and a balanced accuracy of 0.79 for the separation of depression from AD, evaluated by leave-one-out cross validation. The algorithm also identified consistent structural differences in a clinically more relevant scenario where the data used during training were independent from the data used for evaluation and, critically, which included five possible diagnoses (specifically AD, frontotemporal dementia, Lewy body dementia, depression, and healthy aging). While the output was insufficiently accurate to use it directly as a means for classification when multiple classes are possible, the continuous output computed by the machine learning algorithm differed between the two groups that were investigated. The automated analysis thus could complement, but not replace clinical assessments.

Serum Copper is not Altered in Frontotemporal Lobar Degeneration. - Squitti, Rosanna; Fostinelli, Silvia; Siotto, Mariacristina; Ferrari, Clarissa; Binetti, Giuliano; Benussi, Luisa; Rongioletti, Mauro; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Meta-analyses show copper dyshomeostasis in Alzheimer's disease. However, a study evaluating copper changes in other neurodegenerative forms of dementia has not yet been performed. In this study, we assessed copper, ceruloplasmin, copper not bound to ceruloplasmin, and copper to ceruloplasmin ratio in 85 patients affected by frontotemporal lobar degeneration (FTLD) and 55 healthy controls. Data were analyzed through multivariate ANOVA models taking into account age and sex as covariates and the stratification for FTLD variants, after calculating power analysis to ensure the reliability of the conclusions drawn. The study revealed no difference between the groups.

Serum C-Peptide, Visfatin, Resistin, and Ghrelin are Altered in Sporadic and GRN-Associated Frontotemporal Lobar Degeneration. - Zanardini, Roberta; Benussi, Luisa; Fostinelli, Silvia; Saraceno, Claudia; Ciani, Miriam; Borroni, Barbara; Padovani, Alessandro; Binetti, Giuliano; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a group of complex neurodegenerative disease characterized by progressive deterioration of the frontal and anterior temporal lobes of the brain resulting in different heterogeneous conditions, mainly characterized by personality changes, behavioral disturbances, such as binge eating, and deficits in language and executive functions. Null mutations in progranulin gene (GRN) are one of the most frequent genetic determinants in familial frontotemporal dementia. Recently, progranulin was recognized as an adipokine involved in diet-induced obesity and insulin resistance revealing its metabolic function. Increasing evidence suggests that neurodegenerative dementias are associated with a higher prevalence of metabolic changes than in the general population. According to these findings, the aim of this study is to investigate putative alterations in markers linked to metabolic functions (i.e., C-peptide, ghrelin, glucose-dependent insulinotropic polypeptide, glucagon-like peptide-1, glucagon, insulin, resistin, and three adipokines as visfatin, leptin, and plasminogen activator inhibitor-1 total) in sporadic and GRN-related FTLD. We found that 1) C-peptide is increased in sporadic and GRN-mutated FTLD patients; in addition, we demonstrated an anticipation of the disease in patients with the highest C-peptide concentrations; 2) visfatin is slightly reduced in the whole FTLD group; 3) resistin, an adipokine involved in inflammatory-related diseases, is specifically increased in FTLD due to GRN null mutations; 4) ghrelin concentration is specifically increased in pre-symptomatic subjects and FTLD patients with GRN mutations. These findings support the hypothesis that alterations in metabolic pattern are involved in FTLD progression highlighting novel putative targets for the development of preventive and personalized therapies.
Keywords: Aged; Biomarkers; C-Peptide; Female; Frontotemporal Lobar Degeneration; Ghrelin; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Nicotinamide Phosphoribosyltransferase; Progranulins; Resistin

Sex-Dependent Differences in Spontaneous Autoimmunity in Adult 3xTg-AD Mice. - Kapadia, Minesh; Mian, M Firoz; Michalski, Bernadeta; Azam, Amber B; Ma, Donglai; Salwierz, Patrick; Christopher, Adam; Rosa, Elyse; Zovkic, Iva B; Forsythe, Paul; Fahnestock, Margaret; Sakic, Boris (J Alzheimers Dis, 2018)
The triple-transgenic (3xTg-AD) mouse strain is a valuable model of Alzheimer's disease (AD) because it develops both amyloid-β (Aβ) and tau brain pathology. However, 1-year-old 3xTg-AD males no longer show plaques and tangles, yet early in life they exhibit diverse signs of systemic autoimmunity. The current study aimed to address whether females, which exhibit more severe plaque/tangle pathology at 1 year of age, show similar autoimmune phenomena and if so, whether these immunological changes coincide with prodromal markers of AD pathology, markers of learning and memory formation, and epigenetic markers of neurodegenerative disease. Six-month-old 3xTg-AD and wild-type mice of both sexes were examined for T-cell phenotype (CD3+, CD8+, and CD4+ populations), serological measures (autoantibodies, hematocrit), soluble tau/phospho-tau and Aβ levels, brain-derived neurotrophic factor (BDNF) expression, and expression of histone H2A variants. Although no significant group differences were seen in tau/phospho-tau levels, 3xTg-AD mice had lower brain mass and showed increased levels of soluble Aβ and downregulation of BDNF expression in the cortex. Splenomegaly, depleted CD+ T-splenocytes, increased autoantibody levels and low hematocrit were more pronounced in 3xTg-AD males than in females. Diseased mice also failed to exhibit sex-specific changes in histone H2A variant expression shown by wild-type mice, implicating altered nucleosome composition in these immune differences. Our study reveals that the current 3xTg-AD model is characterized by systemic autoimmunity that is worse in males, as well as transcriptional changes in epigenetic factors of unknown origin. Given the previously observed lack of plaque/tangle pathology in 1-year-old males, an early, sex-dependent autoimmune mechanism that interferes with the formation and/or deposition of aggregated protein species is hypothesized. These results suggest that more attention should be given to studying sex-dependent differences in the immunological profiles of human patients.

Single Subject Classification of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Using Anatomical, Diffusion Tensor, and Resting-State Functional Magnetic Resonance Imaging. - Bouts, Mark J R J; Möller, Christiane; Hafkemeijer, Anne; van Swieten, John C; Dopper, Elise; van der Flier, Wiesje M; Vrenken, Hugo; Wink, Alle Meije; Pijnenburg, Yolande A L; Scheltens, Philip; Barkhof, Frederik; Schouten, Tijn M; et al. (J Alzheimers Dis, 2018)
BACKGROUND/OBJECTIVE: Overlapping clinical symptoms often complicate differential diagnosis between patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD). Magnetic resonance imaging (MRI) reveals disease specific structural and functional differences that aid in differentiating AD from bvFTD patients. However, the benefit of combining structural and functional connectivity measures to-on a subject-basis-differentiate these dementia-types is not yet known. METHODS: Anatomical, diffusion tensor (DTI), and resting-state functional MRI (rs-fMRI) of 30 patients with early stage AD, 23 with bvFTD, and 35 control subjects were collected and used to calculate measures of structural and functional tissue status. All measures were used separately or selectively combined as predictors for training an elastic net regression classifier. Each classifier's ability to accurately distinguish dementia-types was quantified by calculating the area under the receiver operating characteristic curves (AUC). RESULTS: Highest AUC values for AD and bvFTD discrimination were obtained when mean diffusivity, full correlations between rs-fMRI-derived independent components, and fractional anisotropy (FA) were combined (0.811). Similarly, combining gray matter density (GMD), FA, and rs-fMRI correlations resulted in highest AUC of 0.922 for control and bvFTD classifications. This, however, was not observed for control and AD differentiations. Classifications with GMD (0.940) and a GMD and DTI combination (0.941) resulted in similar AUC values (p = 0.41). CONCLUSION: Combining functional and structural connectivity measures improve dementia-type differentiations and may contribute to more accurate and substantiated differential diagnosis of AD and bvFTD patients. Imaging protocols for differential diagnosis may benefit from also including DTI and rs-fMRI.

Small Vessel Cerebrovascular Pathology Identified by Magnetic Resonance Imaging Is Prevalent in Alzheimer's Disease and Mild Cognitive Impairment: A Potential Target for Intervention. - Scott, Tammy M; Bhadelia, Rafeeque A; Qiu, Wei Qiao; Folstein, Marshal F; Rosenberg, Irwin H (J Alzheimers Dis, 2018)
BACKGROUND: There is evidence that Alzheimer's disease (AD) has significant cerebrovascular etiopathogenesis. Understanding potentially modifiable risk factors for vascular disease can help design long-term intervention strategies for controlling or preventing cognitive dysfunction attributable to cerebrovascular disease. OBJECTIVE: To evaluate the presence and severity of markers of cerebrovascular pathology, its relationship to diagnostic categories of dementia, including AD, and association with the metabolic biomarker homocysteine. METHODS: In a cross-sectional observational study, 340 community-dwelling elders received a clinical evaluation including brain MRI and neuropsychological tests. Dementia and mild cognitive impairment (MCI) were diagnosed by consensus committee. Fasting total plasma homocysteine was measured. Statistical analyses were adjusted for demographics and cerebrovascular risk factors. RESULTS: Nearly 25% of those diagnosed with AD had small vessel infarcts (SVI). Periventricular white matter hyperintensity (pvWMHI) was prevalent in participants with AD (61%) or MCI (amnesic 61% and non-amnesic 54%, respectively). Participants with SVI and/or pvWMHI also had greater brain atrophy. Homocysteine concentrations were higher in individuals with cerebrovascular findings than in those without. In individuals with cerebrovascular disease, homocysteine was inversely related to executive function (p = 0.022) and directly related to degree of brain atrophy (p = 0.009). CONCLUSIONS: We demonstrated a significant prevalence of small vessel markers of cerebrovascular pathology in individuals diagnosed with AD, with a significant concurrence between cerebrovascular disease and brain and ventricular atrophy. While current research on AD has focused on amyloid-βpeptide deposition, tau-pathology, and microglial activation and inflammation, greater attention to the cerebrovascular contribution to this neurodegenerative disease presents an additional target for therapeutic prevention and intervention.

Spatial Navigation in the Elderly with Alzheimer's Disease: A Cross-Sectional Study. - Zanco, Marcos; Plácido, Jessica; Marinho, Valeska; Ferreira, José Vinicius; de Oliveira, Felipe; Monteiro-Junior, Renato; Barca, Maria; Engedal, Knut; Laks, Jerson; Deslandes, Andrea (J Alzheimers Dis, 2018)
BACKGROUND: Spatial navigation is a fundamental cognitive ability that allows an individual to maintain independence by facilitating the safe movement from one place to another. It emerges as one of the first deficits in patients with Alzheimer's disease (AD). OBJECTIVE: To compare spatial navigation performance in the healthy elderly and AD patients through use of the Floor Maze Test (FMT)- an easy-to-apply two-dimensional (2D) maze- and determine which cognitive and functional capacities were associated with performance in this task. METHODS: The FMT was administered to 24 AD patients and 36 healthy controls. Spatial navigation was evaluated through the FMT. Functional capacity was evaluated through the Senior Fitness Test battery of tests. Cognitive functions were evaluated through the Mini-Mental State Examination (MMSE), verbal fluency, digit span test, and the Rey Auditory Verbal Learning Test (RAVLT). RESULTS: The group with AD was significantly slower and presented more errors at all stages of the FMT. Planning Time (PT) performance was associated with cardiorespiratory resistance (Step test) and delayed memory according to the RAVLT (R2 = 0.395, p < 0.001). Performance in the Immediate Maze Time (IMT) and Delayed Maze Time (DMT) was associated with global cognitive status (MMSE) (R2 = 0.509) and delayed memory (R2 = 0.540). CONCLUSION: Patients with AD present significant spatial navigation deficits. Their performance on the FMT is influenced by cardiorespiratory capacity, memory, and global cognitive function. As exercise helps to improve executive function and functional capacity, future intervention studies should be carried out to analyze the possible effects of physical exercise on spatial navigation.

Stabilized Low-n Amyloid-β Oligomers Induce Robust Novel Object Recognition Deficits Associated with Inflammatory, Synaptic, and GABAergic Dysfunction in the Rat. - Watremez, William; Jackson, Joshua; Almari, Bushra; McLean, Samantha L; Grayson, Ben; Neill, Joanna C; Fischer, Nicolas; Allouche, Ahmad; Koziel, Violette; Pillot, Thierry; Harte, Michael K (J Alzheimers Dis, 2018)
BACKGROUND: With current treatments for Alzheimer's disease (AD) only providing temporary symptomatic benefits, disease modifying drugs are urgently required. This approach relies on improved understanding of the early pathophysiology of AD. A new hypothesis has emerged, in which early memory loss is considered a synapse failure caused by soluble amyloid-β oligomers (Aβo). These small soluble Aβo, which precede the formation of larger fibrillar assemblies, may be the main cause of early AD pathologies. OBJECTIVE: The aim of the current study was to investigate the effect of acute administration of stabilized low-n amyloid-β1-42 oligomers (Aβo1-42) on cognitive, inflammatory, synaptic, and neuronal markers in the rat. METHODS: Female and male Lister Hooded rats received acute intracerebroventricular (ICV) administration of either vehicle or 5 nmol of Aβo1-42 (10μL). Cognition was assessed in the novel object recognition (NOR) paradigm at different time points. Levels of inflammatory (IL-1β, IL-6, TNF-α), synaptic (PSD-95, SNAP-25), and neuronal (n-acetylaspartate, parvalbumin-positive cells) markers were investigated in different brain regions (prefrontal and frontal cortex, striatum, dorsal and ventral hippocampus). RESULTS: Acute ICV administration of Aβo1-42 induced robust and enduring NOR deficits. These deficits were reversed by acute administration of donepezil and rolipram but not risperidone. Postmortem analysis revealed an increase in inflammatory markers, a decrease in synaptic markers and parvalbumin containing interneurons in the frontal cortex, with no evidence of widespread neuronal loss. CONCLUSION: Taken together the results suggest that acute administration of soluble low-n Aβo may be a useful model to study the early mechanisms involved in AD and provide us with a platform for testing novel therapeutic approaches that target the early underlying synaptic pathology.

Stereological Quantification of Plaques and Tangles in Neocortex from Alzheimer's Disease Patients. - Madsen, Jes Buster; Folke, Jonas; Pakkenberg, Bente (J Alzheimers Dis, 2018)
We estimated by stereological methods the neocortical volume occupied by plaques and tangles in females dying with severe Alzheimer's disease (AD), age-matched female subjects with severe vascular dementia (VaD), and normal control brains. Stereological investigations include a uniform sampling of the tissue in the whole of neocortex and its subdivisions. Resultant volume estimates provide information about the overall burden of these two pathological changes and their volume fractions and allow for correlational studies between the pathological changes and factors such as the total neocortical neuronal cell numbers, dementia test scores, and age. We estimated the volume of plaques and tangles in the entire neocortex and frontal-, temporal-, parietal-, and occipital cortex in nine female AD brains, four female patients dying with VaD, and six neurologically normal female control brains using point-counting in uniform samples of neocortex. The volume occupied by plaques comprised approximately 1% of neocortex, while the neocortical tangles made up approximately 0.1% of neocortex of AD patients but were scarcely present in the other study groups. The individual tangle and plaque volumes did not correlate to the ultimate dementia score of the AD subjects, despite correlating with reduced neocortical volume. In neocortex of AD patients, the burden of plaques and tangles is much higher than that in patients with severe vascular dementia or normal older women but only occupy a small fraction of the neocortical volume.

Structural Anatomical Investigation of Long-Term Memory Deficit in Behavioral Frontotemporal Dementia. - Bertoux, Maxime; Flanagan, Emma C; Hobbs, Matthew; Ruiz-Tagle, Amparo; Delgado, Carolina; Miranda, Marcelo; Ibáñez, Agustín; Slachevsky, Andrea; Hornberger, Michael (J Alzheimers Dis, 2018)
Although a growing body of work has shown that behavioral variant frontotemporal dementia (bvFTD) could present with severe amnesia in approximately half of cases, memory assessment is currently the clinical standard to distinguish bvFTD from Alzheimer's disease (AD). Thus, the concept of "relatively preserved episodic memory" in bvFTD remains the basis of its clinical distinction from AD and a criterion for bvFTD's diagnosis. This view is supported by the idea that bvFTD is not characterized by genuine amnesia and hippocampal degeneration, by contrast to AD. In this multicenter study, we aimed to investigate the neural correlates of memory performance in bvFTD as assessed by the Free and Cued Selective Reminding Test (FCSRT). Imaging explorations followed a two-step procedure, first relying on a visual rating of atrophy of 35 bvFTD and 34 AD patients' MRI, contrasted with 29 controls; and then using voxel-based morphometry (VBM) in a subset of bvFTD patients. Results showed that 43% of bvFTD patients presented with a genuine amnesia. Data-driven analysis on visual rating data showed that, in bvFTD, memory recall & storage performances were significantly predicted by atrophy in rostral prefrontal and hippocampal/perihippocampal regions, similar to mild AD. VBM results in bvFTD (pFWE<0.05) showed similar prefrontal and hippocampal regions in addition to striatal and lateral temporal involvement. Our findings showed the involvement of prefrontal as well as medial/lateral temporal atrophy in memory deficits of bvFTD patients. This contradicts the common view that only frontal deficits explain memory impairment in this disease and plead for an updated view on memory dysfunctions in bvFTD.

Structural Connectivity Alterations Along the Alzheimer's Disease Continuum: Reproducibility Across Two Independent Samples and Correlation with Cerebrospinal Fluid Amyloid-β and Tau. - Tucholka, Alan; Grau-Rivera, Oriol; Falcon, Carles; Rami, Lorena; Sánchez-Valle, Raquel; Lladó, Albert; Gispert, Juan Domingo; Molinuevo, José Luis (J Alzheimers Dis, 2018)
BACKGROUND: Gray matter changes associated with the progression of Alzheimer's disease (AD) have been thoroughly studied. However, alterations in white matter tracts have received less attention, particularly during early or preclinical stages of the disease. OBJECTIVE: To identify the structural connectivity changes across the AD continuum. METHODS: We performed probabilistic tractography in a total of 183 subjects on two independent samples that include control (n = 68) and preclinical AD individuals (n = 28), patients diagnosed with mild cognitive impairment (MCI) due to AD (n = 44), and AD patients (n = 43). We compared the connectivity between groups, and with CSF Aβ42 and tau biomarkers. RESULTS: We observed disconnections in preclinical individuals, mainly located in the temporal lobe. This pattern of disconnection spread to the parietal and frontal lobes at the MCI stage and involved almost all the brain in AD. These findings were not driven by gray matter atrophy. DISCUSSION: Using tractography, we were able to identify white matter changes between subsequent disease stages and, notably, also in preclinical AD. Therefore, this method may be useful for detecting early and specific brain structural changes during preclinical AD stage.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Gray Matter; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Reproducibility of Results; Spain; tau Proteins; White Matter

A Study of Amyloid-β and Phosphotau in Plaques and Neurons in the Hippocampus of Alzheimer's Disease Patients. - Furcila, Diana; DeFelipe, Javier; Alonso-Nanclares, Lidia (J Alzheimers Dis, 2018)
The main pathological hallmarks in Alzheimer's disease (AD) are the presence of extracellular amyloid plaques, primarily consisting of amyloid-β (Aβ) peptide, and the accumulation of paired helical filaments of hyperphosphorylated tau protein (PHF-Tau) within neurons. Since CA1 is one of the most affected regions in AD, mainly at early stages, we have performed a detailed analysis of the CA1 region from 11 AD patients (demented and clinically similar; Braak stages IV-VI) to better understand the possible relationship between the presence and distribution of different neurochemical types of Aβ plaques and PHF-Tau immunoreactive  (- ir)  neurons. Hence, we have examined hippocampal sections in confocal microscopy images from double and triple-immunostained sections, to study labeled plaques and PHF-Tau-ir neurons using specific software tools. There are four main findings in the present study. First, the pyramidal layer of proximal CA1 (close to CA2) contains the smallest number of both plaques and PHF-Tau-ir neurons. Second, a large proportion of Aβ-ir plaques were also characterized by the presence of PHF-Tau-ir. Third, all plaques containing one of the two PHF-Tau isoforms also express the other isoform, that is, if a plaque contains PHFpS396, it also contains PHFAT8, and vice versa. Fourth, the coexpression study of both PHF-Tau isoforms in CA1 neurons revealed that most of the labeled neurons express only PHFpS396. Our findings further support the idea that AD is not a unique entity even within the same neuropathological stage, since the microanatomical/neurochemical changes that occur in the hippocampus greatly vary from one patient to another.

A Survey of Patient and Partner Outcome and Treatment Preferences in Mild Cognitive Impairment. - Smith, Glenn E; Chandler, Melanie; Fields, Julie A; Aakre, Jeremiah; Locke, Dona E C (J Alzheimers Dis, 2018)
BACKGROUND: The patient-centered movement in health care is increasing efforts to design studies and interventions that address the outcomes that matter most to patients and their families. Research has not adequately addressed Alzheimer's disease patient and caregiver preferences. OBJECTIVE: To survey the outcome and treatment preferences of patients and caregivers who had completed a multicomponent behavioral intervention for mild cognitive impairment (MCI). METHODS: Extending prior work, we conducted an online survey regarding outcome and intervention preferences. Participants were patients with MCI and partners who completed the HABIT Healthy Action to Benefit Independence & Thinking ® program. RESULTS: Both patient and partner respondents ranked patient quality of life as the highest priority, followed by patient self-efficacy, functional status, patient mood, and patient memory performance. Distressing behaviors and caregiver outcomes (burden, mood, and self-efficacy) had low rankings. Regarding the importance of HABIT ® program components, memory compensation training was ranked highest and wellness education lowest by all groups. CONCLUSION: Additional research should compare patient preference for patient reported outcomes, traditional neuropsychological and clinician outcomes, and modern biomarker outcomes.

A Systematic Review and Aggregated Analysis on the Impact of Amyloid PET Brain Imaging on the Diagnosis, Diagnostic Confidence, and Management of Patients being Evaluated for Alzheimer's Disease. - Fantoni, Enrico R; Chalkidou, Anastasia; O' Brien, John T; Farrar, Gill; Hammers, Alexander (J Alzheimers Dis, 2018)
BACKGROUND: Amyloid PET (aPET) imaging could improve patient outcomes in clinical practice, but the extent of impact needs quantification. OBJECTIVE: To provide an aggregated quantitative analysis of the value added by aPET in cognitively impaired subjects. METHODS: Systematic literature searches were performed in Embase and Medline until January 2017. 1,531 cases over 12 studies were included (1,142 cases over seven studies in the primary analysis where aPET was the key biomarker; the remaining cases included as defined groups in the secondary analysis). Data was abstracted by consensus among two observers and assessed for bias. Clinical utility was measured by diagnostic change, diagnostic confidence, and patient management before and after aPET. Three groups were further analyzed: control patients for whom feedback of aPET scan results was delayed; aPET Appropriate Use Criteria (AUC+) cases; and patients undergoing additional FDG/CSF testing. RESULTS: For 1,142 cases with only aPET, 31.3% of diagnoses were revised, whereas 3.2% of diagnoses changed in the delayed aPET control group (p < 0.0001). Increased diagnostic confidence following aPET was found for 62.1% of 870 patients. Management changes with aPET were found in 72.2% of 740 cases and in 55.5% of 299 cases in the control group (p < 0.0001). The diagnostic value of aPET in AUC+ patients or when FDG/CSF were additionally available did not substantially differ from the value of aPET alone in the wider population. CONCLUSIONS: Amyloid PET contributed to diagnostic revision in almost a third of cases and demonstrated value in increasing diagnostic confidence and refining management plans.

TDP-43 Neuropathologic Associations in the Nun Study and the Honolulu-Asia Aging Study. - Flanagan, Margaret E; Cholerton, Brenna; Latimer, Caitlin S; Hemmy, Laura S; Edland, Steven D; Montine, Kathleen S; White, Lon R; Montine, Thomas J (J Alzheimers Dis, 2018)
Transactive response binding protein-43 (TDP-43) cytoplasmic neuronal and glial aggregates (pathologic TDP-43) have been described in multiple brain diseases. We describe the associations between neuropathologically confirmed TDP-43 and cognition in two population-based cohorts: the Nun Study (NS) and the Honolulu-Asia Aging Study (HAAS). In the HAAS, there was a significant association between hippocampal sclerosis (HS) and TDP-43 (OR = 11.04, p < 0.0001, 95% CI 3.57-34.13). In the NS, there were significant associations between TDP-43 and HS (OR = 16.44, p > 0.001 95%, CI 7.10-38.00) and Alzheimer's disease (AD) severity (OR = 1.74, p = 0.009, 95% CI 1.15-2.64). When cognitive scores were added to the model, HS remained significant but the other variables were not. When HS was removed from the model, the overall model remained significant and the associations between cognitive performance and TDP-43 (OR = 2.11, p = 0.022, 95% CI 1.11-4.02) were significant. In the NS, there was a significant association between cognitive performance and TDP-43 (OR 1.94 p = 0.005, 95% CI 1.22-3.09) (HS remained significant, but AD did not). When HS was removed from the model, only CERAD was significant (OR = 2.43 p < 0.001, 95% CI 1.58-3.74). These results support a consistent association between pathologic TDP-43, HS, and the development of cognitive impairment in two large studies of brain aging, while the relationship between AD pathology and TDP-43 may vary according to cohort-specific features.

Testing Hippocampal Memory in Prodromal Dementia with Lewy Bodies. - Bussè, Cinzia; Caffarra, Paolo; Rossi, Alice; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Pompanin, Sara; Di Bernardo, Gian Antonio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding test (FCSRT) was used to assess memory in 19 patients with prodromal dementia with Lewy bodies (DLB) and 25 Alzheimer's disease (AD) patients. DLB scored better than AD in selective measures of the FCSRT: immediate total recall (p = 0.01) and index of sensitivity of cueing (p = 0.001), while free delayed and total memory scores were similarly impaired. The index of sensitivity of cueing held a sensitivity of 76% and specificity of 79% in distinguishing DLB. FCSRT could help in disentangling hippocampal memory deficits from memory impairment due to ineffective recall strategies.

TLR4 Gene Expression and Pro-Inflammatory Cytokines in Alzheimer's Disease and in Response to Hippocampal Deafferentation in Rodents. - Miron, Justin; Picard, Cynthia; Frappier, Josée; Dea, Doris; Théroux, Louise; Poirier, Judes (J Alzheimers Dis, 2018)
One important aspect in Alzheimer's disease pathology is the presence of chronic inflammation. Considering its role as a key receptor in the microglial innate immune system, TLR4 was shown to regulate the binding and phagocytosis of amyloid plaques by microglia in several mouse models of amyloidosis, as well as the production of pro-inflammatory cytokines. To our knowledge, TLR4 and its association with cytokines have not been thoroughly examined in the brains of subjects affected with Alzheimer's disease. Using quantitative reverse transcription polymerase chain reaction (qRT-PCR) in postmortem human brains, we observed increased expression for the TLR4 and TNF genes (p = 0.001 and p = 0.025, respectively), as well as a trend for higher IL6 gene expression in the frontal cortex of AD subjects when compared to age-matched controls. Similarly, using a mouse model of hippocampal deafferentation without amyloidosis, (i.e., the entorhinal cortex lesioned mouse), we observed significant increases in the expression of both the Tlr4 (p = 0.0367 and p = 0.0193 compared to sham-lesioned mice or to the contralateral side, respectively) and Il1b (p = 0.0055 and p = 0.0066 compared to sham-lesioned mice or to the contralateral side, respectively) genes in the deafferentation phase, but not during the ensuing reinnervation process. In conclusion, we suggest that the modulation of cytokines by TLR4 is differentially regulated whether by the presence of amyloid plaques or by the ongoing deafferentation process.

Transcranial Sonography in Neurodegenerative Diseases with Cognitive Decline. - Favaretto, Silvia; Walter, Uwe; Baracchini, Claudio; Cagnin, Annachiara (J Alzheimers Dis, 2018)
Transcranial sonography (TCS) of the brain parenchyma detects alterations in the substantia nigra (SN), raphe nuclei and basal ganglia; this technique has been established as a tool for the early diagnosis of Parkinson's disease and differential diagnosis from atypical parkinsonian syndromes. Here, we aimed to review the main applications of TCS in neurodegenerative diseases presenting with dementia syndrome, focusing on Alzheimer's disease (AD), dementia with Lewy bodies (DLB), frontotemporal lobar degeneration, idiopathic normal pressure hydrocephalus, and atypical and secondary parkinsonisms. The finding of bilaterally marked hyperechogenicity of the SN appears as a characteristic feature of DLB, while it is found only in a minority of AD patients. SN hyperechogenicity is also detected in most patients with corticobasal degeneration and in about one third of patients with progressive supranuclear palsy, in which is constantly associated with hyperechogenic alterations of the basal ganglia. In conclusion, TCS is a valid supportive tool in the diagnostic workup of patients with dementia due to different neurodegenerative conditions. A promising new application is the differentiation of DLB from AD even at the early stages of these diseases.
Keywords: Cognition Disorders; Humans; Neurodegenerative Diseases; Ultrasonography, Doppler, Transcranial

Treatment of Atrial Fibrillation in Patients with Dementia: A Cohort Study from the Swedish Dementia Registry. - Subic, Ana; Cermakova, Pavla; Religa, Dorota; Han, Shuang; von Euler, Mia; Kåreholt, Ingemar; Johnell, Kristina; Fastbom, Johan; Bognandi, Liselia; Winblad, Bengt; Kramberger, Milica G; Eriksdotter, Maria; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Patients with dementia might have higher risk for hemorrhagic complications with anticoagulant therapy prescribed for atrial fibrillation (AF). OBJECTIVE: This study assesses the risks and benefits of warfarin, antiplatelets, and no treatment in patients with dementia and AF. METHODS: Of 49,792 patients registered in the Swedish Dementia Registry 2007-2014, 8,096 (16%) had a previous diagnosis of AF. Cox proportional hazards models were used to calculate the risk for ischemic stroke (IS), nontraumatic intracranial hemorrhage, any-cause hemorrhage, and death. RESULTS: Out of the 8,096 dementia patients with AF, 2,143 (26%) received warfarin treatment, 2,975 (37%) antiplatelet treatment, and 2,978 (37%) had no antithrombotic treatment at the time of dementia diagnosis. Patients on warfarin had fewer IS than those without treatment (5.2% versus 8.7%; p < 0.001) with no differences compared to antiplatelets. In adjusted analyses, warfarin was associated with a lower risk for IS (HR 0.76, CI 0.59-0.98), while antiplatelets were associated with increased risk (HR 1.25, CI 1.01-1.54) compared to no treatment. For any-cause hemorrhage, there was a higher risk with warfarin (HR 1.28, CI 1.03-1.59) compared to antiplatelets. Warfarin and antiplatelets were associated with a lower risk for death compared to no treatment. CONCLUSIONS: Warfarin treatment in Swedish patients with dementia is associated with lower risk of IS and mortality, and a small increase in any-cause hemorrhage. This study supports the use of warfarin in appropriate cases in patients with dementia. The low percentage of patients on warfarin treatment indicates that further gains in stroke prevention are possible.
Keywords: Aged; Aged, 80 and over; Anticoagulants; Atrial Fibrillation; Dementia; Female; Hemorrhage; Humans; Longitudinal Studies; Male; Registries; Risk Factors; Stroke; Survival Analysis; Sweden; Warfarin

Underlying Biological Processes in Mild Cognitive Impairment: Amyloidosis Versus Neurodegeneration. - Santana, Isabel; Baldeiras, Ines; Santiago, Beatriz; Duro, Diana; Freitas, Sandra; Pereira, Miguel Tábuas; Almeida, Maria Rosário; Oliveira, Catarina Resende (J Alzheimers Dis, 2018)
The amyloid cascade hypothesis proposes amyloid-β (Aβ) as the earliest and key pathological hallmark of Alzheimer's disease (AD), but this mandatory "amyloid-first pathway" has been contested. Longitudinal studies of mild cognitive impairment (MCI) patients represent an opportunity to investigate the intensity of underlying biological processes (amyloidosis versus neurodegeneration) and their relevance for progression to AD. We re-examined our cohort of amnestic MCI, grouped according to cerebrospinal fluid (CSF) biomarkers, aiming at establishing their prognostic value for Alzheimer-type dementia and testing the hypothetical model of biomarkers sequence, based on the amyloid cascade. Our baseline population consisted of 217 MCI patients, 63% with neurodegeneration markers and 47% with amyloidosis. Within the longitudinal study-group (n = 165), 85 progressed to AD and 80 remained cognitively stable. Age, CSF Aβ42, and t-Tau were identified as the best single predictors of conversion to AD. Regarding MCI classification according to the NIA-AA criteria, the high-AD-likelihood group (HL-both amyloid and neurodegeneration markers) was the most frequent (42%); followed by the Suspected Non-Alzheimer Pathophysiology group (SNAP-26%), the low-AD-likelihood group (LL-negative biomarkers-22%), and the Isolated Amyloid Pathology group (IAP-10%). Risk of progression to AD was higher in HL in relation to the LL group (HR = 6.1, 95% CI = 2.1-18.0, p = 0.001). SNAP and IAP groups were equivalent in terms of risk of progression to AD (IAP: HR = 2.6, 95% CI = 0.7-9.3, p = 0.141; SNAP: HR = 3.1, 95% CI = 1.1-9.6; p = 0.046), but only SNAP was significantly different from the LL group. These results support different neurobiological pathways to AD beyond the amyloid hypothesis, highlighting the alternative "neurodegeneration-first pathway" for further investigation.

The Use of Mobile Games to Assess Cognitive Function of Elderly with and without Cognitive Impairment. - Bonnechère, Bruno; Van Vooren, Mélissa; Bier, Jean-Christophe; De Breucker, Sandra; Van Hove, Olivier; Van Sint Jan, Serge; Feipel, Véronique; Jansen, Bart (J Alzheimers Dis, 2018)
BACKGROUND: In the past few years numerous mobile games have been developed to train the brain. There is a lack of information about the relation between the scores obtained in these games and the cognitive abilities of the patients. OBJECTIVE: The aim of this study was to determine whether or not mobile games can be used to assess cognitive abilities of elderly. METHODS: Twenty healthy young adults, 29 old patients with cognitive impairments (Mini-Mental State Exam (MMSE) [20- 24]) and 27-aged controls participated in this study. Scores obtained in 7 mobile games were correlated with MMSE and the Addenbrooke's Cognitive Evaluation revised (ACE-R). RESULTS: Statistically significant differences were found for all games between patients with cognitive impairments and the aged controls. Correlations between the average scores of the games and the MMSE and ACE-R are significant (R = 0.72 [p < 0.001] and R = 0.81 [p < 0.001], respectively). CONCLUSION: Scores of cognitive mobile games could be used as an alternative to MMSE and ACE-R to evaluate cognitive function of aged people with and without cognitive impairment at least when MMSE is higher than 20/30.

Validation of the Delayed Matching-to-Sample Task 48 (DMS48) in Elderly Chinese. - Feng, Xueyan; Zhou, Aihong; Liu, Zhixin; Li, Fangyu; Wei, Cuibai; Zhang, Guili; Jia, Jianping (J Alzheimers Dis, 2018)
BACKGROUND: Delayed Matching-to-Sample Task 48 (DMS48), a brief tool measuring visual recognition memory, is valid to identify the early stage of Alzheimer's disease (AD) in Caucasians. However, little data is available in Chinese. OBJECTIVE: To develop norms and optimal cutoff points for the DMS48 in Chinese elders. METHODS: A cross-sectional study was conducted in seven memory clinics from five cities across China. DMS48 was applied to 369 Chinese aged 50 or older (138 cognitively normal [CN], 112 mild cognitive impairment due to AD (MCI-A), and 119 mild AD dementia). The demographic factors which influence DMS48 scores were investigated and the norms were established considering those factors. Receiver operating characteristic (ROC) analysis was used to determine the optimal cutoff points. RESULTS: Age was shown to influence DMS48 scores (r = -0.36, p < 0.05), and we presented the age-stratified normative data for the DMS48. The optimal cutoff point is 42/43 for identifying cognitive impairment (MCI-A and AD dementia) against CN (sensitivity 97.80% and specificity 89.13%) and MCI-A against CN (sensitivity 86.60% and specificity 94.20%). A cutoff of 39/40 obtained good sensitivity (100.00%) and specificity (94.90%) in discriminating AD dementia from CN. The age-stratified optimal cutoff points for identifying MCI-A were 43/44 for individuals aged 50 to 59 years old, 42/43 for 60 to 69 years old, 41/42 for 70 to 79 years old, and 40/41 for 80 or older, respectively (sensitivity 84.80% and specificity 95.70%). CONCLUSION: This study proved that DMS48 is of good validation in screening MCI-A in elderly Chinese.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; China; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Memory Disorders; Middle Aged; Neuropsychological Tests; ROC Curve; Sensitivity and Specificity; Severity of Illness Index

Visual Processing during Short-Term Memory Binding in Mild Alzheimer's Disease. - Fernández, Gerardo; Orozco, David; Agamennoni, Osvaldo; Schumacher, Marcela; Sañudo, Silvana; Biondi, Juan; Parra, Mario A (J Alzheimers Dis, 2018)
Patients with Alzheimer's disease (AD) typically present with attentional and oculomotor abnormalities that can have an impact on visual processing and associated cognitive functions. Over the last few years, we have witnessed a shift toward the analyses of eye movement behaviors as a means to further our understanding of the pathophysiology of common disorders such as AD. However, little work has been done to unveil the link between eye moment abnormalities and poor performance on cognitive tasks known to be markers for AD patients, such as the short-term memory-binding task. We analyzed eye movement fixation behaviors of thirteen healthy older adults (Controls) and thirteen patients with probable mild AD while they performed the visual short-term memory binding task. The short-term memory binding task asks participants to detect changes across two consecutive arrays of two bicolored object whose features (i.e., colors) have to be remembered separately (i.e., Unbound Colors), or combined within integrated objects (i.e., Bound Colors). Patients with mild AD showed the well-known pattern of selective memory binding impairments. This was accompanied by significant impairments in their eye movements only when they processed Bound Colors. Patients with mild AD remarkably decreased their mean gaze duration during the encoding of color-color bindings. These findings open new windows of research into the pathophysiological mechanisms of memory deficits in AD patients and the link between its phenotypic expressions (i.e., oculomotor and cognitive disorders). We discuss these findings considering current trends regarding clinical assessment, neural correlates, and potential avenues for robust biomarkers.

Voxel-Based Acetylcholinesterase PET Study in Early and Late Onset Alzheimer's Disease. - Hirano, Shigeki; Shinotoh, Hitoshi; Shimada, Hitoshi; Ota, Tsuneyoshi; Sato, Koichi; Tanaka, Noriko; Zhang, Ming-Rong; Higuchi, Makoto; Fukushi, Kiyoshi; Irie, Toshiaki; Kuwabara, Satoshi; Suhara, Tetsuya (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by chronic progressive cognitive decline and displays underlying brain cholinergic dysfunction, providing a rationale for treatment with cholinomimetic medication. The clinical presentations and courses of AD patients may differ by age of onset. OBJECTIVE: The objective of the present study was to illustrate the regional differences of brain acetylcholinesterase (AChE) activity as quantified by N-[11C]methylpiperidinyl-4-acetate ([11C]MP4A) and PET using parametric whole brain analysis and clarify those differences as a function of age. METHODS: 22 early onset AD (EOAD) with age at onset under 65, the remaining 26 as late onset AD (LOAD), and 16 healthy controls (HC) were enrolled. Voxel-based AChE activity estimation of [11C]MP4A PET images was conducted by arterial input and unconstrained nonlinear least-squares method with subsequent parametrical analyses. Statistical threshold was set as Family Wise Error corrected, p-value <0.05 on cluster-level and cluster extent over 30 voxels. RESULTS: Voxel-based group comparison showed that, compared to HC, both EOAD and LOAD showed cortical AChE decrement in parietal, temporal, and occipital cortices, with wider and stringent cortical involvement in the EOAD group, most prominently demonstrated in the temporal region. There was no significant correlation between age and regional cerebral AChE activity except for a small left superior temporal region in the AD group (Brodmann's area 22, Zmax = 5.13, 396 voxels), whereas no significant cluster was found in the HC counterpart. CONCLUSION: Difference in cortical cholinergic dysfunction between EOAD and LOAD may shed some light on the cholinomimetic drug efficacy in AD.

When Art Meets Gardens: Does It Enhance the Benefits? The Nancy Hypothesis of Care for Persons with Alzheimer's Disease. - Jonveaux, Thérèse Rivasseau; Fescharek, Reinhard (J Alzheimers Dis, 2018)
The creation of healing gardens for persons with Alzheimer's disease and related diseases (ADRD) offers vast potential. They can play a role in the scaffolding of cognitive disorders, emotional stress, sensory processing, sense of harmony, and appeasement. These effects are achieved through a distributed interplay of psychological functions with the immediate environment and local culture on the one hand, and dialogue on the other. The garden, a natural canvas created by man, shares with art the ability to foster an esthetic sense for which the perception can be measured by functional neurological imaging exploration. Art represents a mediator for the collaborative realization of distributed psychological functions between different individuals. Based on the hypothesis of an optimization of the therapeutic potential of a garden by a design adapted to the neuro-psycho-social and cultural specificities of its users combined with the thoughtful introduction of an artistic dimension, the "art, memory and life" healing garden was created at the University Hospital of Nancy as a prototype for persons with ADRD. The design concept was based on two hypotheses that we formulate herein, discuss their theoretical foundation, and suggest enhanced design for therapeutic gardens based upon our experience.
Keywords: Alzheimer Disease; Art Therapy; Cognition; Cognitive Behavioral Therapy; France; Gardening; Humans

White Matter and Cognition in Traumatic Brain Injury. - Filley, Christopher M; Kelly, James P (J Alzheimers Dis, 2018)
Traumatic brain injury (TBI) is a leading cause of disability and produces a wide range of cognitive, emotional, and physical consequences. The impact of TBI on cognition is among the most important questions in this field but remains incompletely understood. The immediate cognitive effects of concussion, while usually short-lived, may be profound and lasting in some individuals, and long-term sequelae of TBI may include dementia of several varieties including post-traumatic leukoencephalopathy, chronic traumatic encephalopathy, and Alzheimer's disease. Whereas the etiopathogenesis of cognitive dysfunction after TBI remains uncertain, a reasonable point to begin is a focus on the white matter of the brain, where the neuropathological lesion known as diffuse axonal injury (DAI) is routinely identified. White matter is not typically accorded the significance granted to cortical gray matter in discussions of cognitive dysfunction and dementia, but increasing evidence is accumulating to suggest that cognitive decline after TBI is a direct result of white matter injury, and that lesions in this brain component are crucial in the sequence of events leading ultimately to dementia of several types. In this review, we consider the topic of white matter and cognition in TBI, beginning with DAI and proceeding to the role of inflammation in the pathogenesis of cognitive dysfunction and dementia that can follow. A brief review of possible therapeutic options will also be offered, including the use of anti-inflammatory agents and the exploitation of white matter plasticity, to treat acute and post-acute injuries, and lower the incidence of dementia resulting from TBI.

Word and Picture Version of the Free and Cued Selective Reminding Test (FCSRT): Is There Any Difference? - Arighi, Andrea; Carandini, Tiziana; Mercurio, Matteo; Carpani, Giovanni; Pietroboni, Anna Margherita; Fumagalli, Giorgio; Ghezzi, Laura; Basilico, Paola; Calvi, Alberto; Scarioni, Marta; De Riz, Milena; Fenoglio, Chiara; et al. (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding Test (FCSRT) is the most commonly used neuropsychological test to evaluate episodic memory. Two variants of FCSRT exist, using the recall of words (FCSRT-w) or pictures (FCSRT-p). Fourteen patients with mild cognitive impairment underwent neuropsychological evaluation and brain magnetic resonance. We found differences in FCSRT-w and FCSRT-p variants scores. FCSRT-p was correlated with atrophy in areas involved in visual stimuli processing while FCSRT-w was correlated to hippocampal atrophy. Our study suggests that FCSRT-w and FCSRT-p scores are not equivalent, but a larger cohort of patients is needed to validate these results.
Keywords: Aged; Aged, 80 and over; Association Learning; Cognitive Dysfunction; Cues; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation; Vocabulary

Zinc Exacerbates Tau Pathology in a Tau Mouse Model. - Craven, Kristen M; Kochen, William R; Hernandez, Carlos M; Flinn, Jane M (J Alzheimers Dis, 2018)
Hyperphosphorylated tau protein is a key pathology in Alzheimer's disease (AD), frontotemporal dementia, chronic traumatic encephalopathy, and Parkinson's disease. The essential trace element zinc exacerbates tauopathy in vitro as well as in a Drosophila model of AD. However, the interaction has never been assessed behaviorally or biochemically in mammals. Zinc supplementation is prevalent in society, finding use as a treatment for macular degeneration and cataracts, and is also taken as an immune system booster with high levels appearing in multivitamins marketed toward the elderly. Using a transgenic mouse model that contains the human gene for tau protein (P301L), we assessed the effects of excess chronic zinc supplementation on tau pathology. Behavioral tests included nest building, circadian rhythm, Morris Water Maze, fear conditioning, and open field. Biochemically, total tau and Ser396 phosphorylation were assessed using western blot. Number of tangles were assessed by Thioflavin-S and free zinc levels were assessed by Zinpyr-1. Tau mice demonstrated behavioral deficits compared to control mice. Zinc supplementation exacerbated tauopathic deficits in circadian rhythm, nesting behavior, and Morris Water Maze. Biochemically, zinc-supplemented tau mice showed increased phosphorylation at pSer396. Zinc supplementation in tau mice also increased tangle numbers in the hippocampus while decreasing free-zinc levels, demonstrating that tangles were sequestering zinc. These results show that zinc intensified the deficits in behavior and biochemistry caused by tau.

The 2002 NIMH Provisional Diagnostic Criteria for Depression of Alzheimer's Disease (PDC-dAD): Gauging their Validity over a Decade Later. - Sepehry, Amir A; Lee, Philip E; Hsiung, Ging-Yuek R; Beattie, B Lynn; Feldman, Howard H; Jacova, Claudia (J Alzheimers Dis, 2017)
Presented herein is evidence for criterion, content, and convergent/discriminant validity of the NIMH-Provisional Diagnostic Criteria for depression of Alzheimer's Disease (PDC-dAD) that were formulated to address depression in Alzheimer's disease (AD). Using meta-analytic and systematic review methods, we examined criterion validity evidence in epidemiological and clinical studies comparing the PDC-dAD to Diagnostic and Statistical Manual of Mental Disorders fourth edition (DSM-IV), and International Classification of Disease (ICD 9) depression diagnostic criteria. We estimated prevalence of depression by PDC, DSM, and ICD with an omnibus event rate effect-size. We also examined diagnostic agreement between PDC and DSM. To gauge content validity, we reviewed rates of symptom endorsement for each diagnostic approach. Finally, we examined the PDC's relationship with assessment scales (global cognition, neuropsychiatric, and depression definition) for convergent validity evidence. The aggregate evidence supports the validity of the PDC-dAD. Our findings suggest that depression in AD differs from other depressive disorders including Major Depressive Disorder (MDD) in that dAD is more prevalent, with generally a milder presentation and with unique features not captured by the DSM. Although the PDC are the current standard for diagnosis of depression in AD, we identified the need for their further optimization based on predictive validity evidence.

A 3-Month Aerobic Training Program Improves Brain Energy Metabolism in Mild Alzheimer's Disease: Preliminary Results from a Neuroimaging Study. - Castellano, Christian-Alexandre; Paquet, Nancy; Dionne, Isabelle J; Imbeault, Hélène; Langlois, Francis; Croteau, Etienne; Tremblay, Sébastien; Fortier, Mélanie; Matte, J Jacques; Lacombe, Guy; Fülöp, Tamás; Bocti, Christian; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Aerobic training has some benefits for delaying the onset or progression of Alzheimer's disease (AD). Little is known about the implication of the brain's two main fuels, glucose and ketones (acetoacetate), associated with thesebenefits. OBJECTIVE: To determine whether aerobic exercise training modifies brain energy metabolism in mild AD. METHODS: In this uncontrolled study, ten patients with mild AD participated in a 3-month, individualized, moderate-intensity aerobic training on a treadmill (Walking). Quantitative measurement of brain uptake of glucose (CMRglu) and acetoacetate (CMRacac) using neuroimaging and cognitive testing were done before and after the Walking program. RESULTS: Four men and six women with an average global cognitive score (MMSE) of 26/30 and an average age of 73 y completed the Walking program. Average total distance and treadmill speed were 8 km/week and 4 km/h, respectively. Compared to the Baseline, after Walking, CMRacac was three-fold higher (0.6±0.4 versus 0.2±0.1 μmol/100 g/min; p = 0.01). Plasma acetoacetate concentration and the blood-to-brain acetoacetate influx rate constant were also increased by 2-3-fold (all p≤0.03). CMRglu was unchanged after Walking (28.0±0.1 μmol/100 g/min; p = 0.96). There was a tendency toward improvement in the Stroop-color naming test (-10% completion time, p = 0.06). Performance on the Trail Making A&B tests was also directly related to plasma acetoacetate and CMRacac (all p≤0.01). CONCLUSION: In mild AD, aerobic training improved brain energy metabolism by increasing ketone uptake and utilization while maintaining brain glucose uptake, and could potentially be associated with some cognitive improvement.

A 9-microRNA Signature in Serum Serves as a Noninvasive Biomarker in Early Diagnosis of Alzheimer's Disease. - Guo, Rui; Fan, Gang; Zhang, Jian; Wu, Chunxiao; Du, Yifeng; Ye, Hui; Li, Zhang; Wang, Lili; Zhang, Zhihui; Zhang, Lu; Zhao, Yueran; Lu, Zhiming (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common type of age-related neurodegenerative disorder; nevertheless, nowadays there are no reliable biomarkers or non-invasive techniques available for its early detection. Recent studies have indicated that the circulating level profiles of microRNAs (miRNAs) have the potential to be used as valuable biomarkers for diagnosis, staging, and progress monitoring of various diseases. Here we report a novel 9-miRNA signature (hsa-miR-26a-5p, hsa-miR-181c-3p, hsa-miR-126-5p, hsa-miR-22-3p, hsa-miR-148b-5p, hsa-miR-106b-3p, hsa-miR-6119-5p, hsa-miR-1246, and hsa-miR-660-5p) that can be utilized as biomarker for detecting AD. We respectively profiled the serum miRNAs from 19 AD patients and 9 healthy control (HC) participants using the Next-Generation Sequencing (NGS). The NGS results were validated by quantitative real-time polymerase chain reaction (qRT-PCR) on a larger cohort of 121 AD and 86 HC cases. All the patients were divided into three groups (mild, moderate, and severe AD) based on the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating (CDR). Our research indicates that abnormal expression of distinct serum miRNAs occurs at different stages of AD. The difference of the area under the receiver operator characteristics curve (AUC) between the AD and the HC is between 70% and 85%. Among the 9 miRNAs, hsa-miR-22-3p has the best sensitivity (81.8%) and specificity (70.9%). The miRNA-panel is more valuable for AD diagnosis. The data suggest that the differentially expressed serum miRNAs could be used as biomarkers to improve the diagnosis of AD, particularly at the early stage, and to classify its clinical stages.

ABCA1 Deficiency Affects Basal Cognitive Deficits and Dendritic Density in Mice. - Fitz, Nicholas F; Carter, Alexis Y; Tapias, Victor; Castranio, Emilie L; Kodali, Ravindra; Lefterov, Iliya; Koldamova, Radosveta (J Alzheimers Dis, 2017)
ATP-binding cassette transporter A1 (ABCA1) mediates cholesterol efflux to lipid-free apolipoproteins and regulates the generation of high density lipoproteins. Previously, we have shown that lack of Abca1 significantly increases amyloid deposition and cognitive deficits in Alzheimer's disease model mice expressing human amyloid-β protein precursor (APP). The goal of this study was to determine if ABCA1 plays a role in memory deficits caused by amyloid-β (Aβ) oligomers and examine neurite architecture of pyramidal hippocampal neurons. Our results confirm previous findings that Abca1 deficiency significantly impairs spatial memory acquisition and retention in the Morris water maze and long-term memory in novel object recognition of APP transgenic mice at a stage of early amyloid pathology. Neither test demonstrated a significant difference between Abca1ko and wild-type (WT) mice. We also examined the effect of intra-hippocampal infused Aβ oligomers on cognitive performance of Abca1ko mice, compared to control infusion of scrambled Aβ peptide. Age-matched WT mice undergoing the same infusions were also used as controls. In this model system, we found a statistically significant difference between WT and Abca1ko mice infused with scrambled Aβ, suggesting that Abca1ko mice are vulnerable to the effect of mild stresses. Moreover, examination of neurite architecture in the hippocampi revealed a significant decrease in neurite length, number of neurite segments, and branches in Abca1ko mice when compared to WT mice. We conclude that mice lacking ABCA1 have basal cognitive deficits that prevent them from coping with additional stressors, which is in part due to impairment of neurite morphology in the hippocampus.

Abnormalities of Cortical Neural Synchronization Mechanisms in Subjects with Mild Cognitive Impairment due to Alzheimer's and Parkinson's Diseases: An EEG Study. - Babiloni, Claudio; Del Percio, Claudio; Lizio, Roberta; Noce, Giuseppe; Cordone, Susanna; Lopez, Susanna; Soricelli, Andrea; Ferri, Raffaele; Pascarelli, Maria Teresa; Nobili, Flavio; Arnaldi, Dario; Famá, Francesco; et al. (J Alzheimers Dis, 2017)
The aim of this retrospective and exploratory study was that the cortical sources of resting state eyes-closed electroencephalographic (rsEEG) rhythms might reveal different abnormalities in cortical neural synchronization in groups of patients with mild cognitive impairment due to Alzheimer's disease (ADMCI) and Parkinson's disease (PDMCI) as compared to healthy subjects. Clinical and rsEEG data of 75 ADMCI, 75 PDMCI, and 75 cognitively normal elderly (Nold) subjects were available in an international archive. Age, gender, and education were carefully matched in the three groups. The Mini-Mental State Evaluation (MMSE) was matched between the ADMCI and PDMCI groups. Individual alpha frequency peak (IAF) was used to determine the delta, theta, alpha1, alpha2, and alpha3 frequency band ranges. Fixed beta1, beta2, and gamma bands were also considered. eLORETA estimated the rsEEG cortical sources. Receiver operating characteristic curve (ROC) classified these sources across individuals. Results showed that compared to the Nold group, the posterior alpha2 and alpha3 source activities were more abnormal in the ADMCI than the PDMCI group, while the parietal delta source activities were more abnormal in the PDMCI than the ADMCI group. The parietal delta and alpha sources correlated with MMSE score and correctly classified the Nold and diseased individuals (area under the ROC = 0.77-0.79). In conclusion, the PDMCI and ADMCI patients showed different features of cortical neural synchronization at delta and alpha frequencies underpinning brain arousal and vigilance in the quiet wakefulness. Future prospective cross-validation studies will have to test these rsEEG markers for clinical applications and drug discovery.

Accuracy of Clinical Diagnosis of Dementia with Lewy Bodies versus Neuropathology. - Skogseth, Ragnhild; Hortobágyi, Tibor; Soennesyn, Hogne; Chwiszczuk, Luiza; Ffytche, Dominic; Rongve, Arvid; Ballard, Clive; Aarsland, Dag (J Alzheimers Dis, 2017)
BACKGROUND: The first consensus criteria for dementia with Lewy bodies (DLB) published in 1996 were revised in 2005, partly because the original clinical criteria had suboptimal sensitivity. Few studies have assessed the accuracy of the 2005 criteria applied prospectively in newly diagnosed patients who have been followed longitudinally. OBJECTIVE: To explore the correlation between clinical and pathological diagnoses in patients with DLB and Parkinson's disease with dementia (PDD). METHODS: From a prospective referral cohort study with enriched recruitment of patients with DLB and PDD, we included the first 56 patients coming to autopsy. Patients had mild dementia at inclusion and were followed annually until death with standardized clinical assessments. Pathological assessment was performed blind to clinical information according to standardized protocols and consensus criteria for DLB. RESULTS: 20 patients received a pathological diagnosis of Lewy body disease; the corresponding clinical diagnoses were probable DLB (n = 11), PDD (n = 5), probable (n = 2) or possible (n = 2) Alzheimer's disease (AD). Of 14 patients with a clinical diagnosis of probable DLB, 11 had DLB/PDD and 3 had AD at pathology. One patient with clinically possible DLB fulfilled criteria for pathological AD. Sensitivity, specificity, positive predictive value, and negative predictive values for probable DLB were 73%, 93%, 79%, and 90%. CONCLUSION: Our findings suggest that the international clinical consensus criteria for DLB perform reasonably well. However, false positive and false negative diagnoses still occur, indicating that the criteria need to be improved, that biomarkers may be needed, and that neuropathological feedback is vital to improve accuracy.

Adherence to Clinical Practice Guidelines during Dementia Work-Up in a Real-World Setting: A Study from the Registry of Dementias of Girona. - Turró-Garriga, Oriol; Calvó-Perxas, Laia; Vilalta-Franch, Joan; Hernández-Ferrándiz, Marta; Flaqué, Margarita; Linares, Marta; Cullell, Marta; Gich, Jordi; Casas, Isabel; Perkal, Héctor; Garre-Olmo, Josep (J Alzheimers Dis, 2017)
BACKGROUND: There are several position statements and clinical practice guidelines (CPG) for diagnosing dementia. OBJECTIVE: Our aims were to evaluate the adherence to CPG among specialists in the 7 memory clinics included in the Registry of Dementias of Girona (ReDeGi), and to compare the results between 2007-2011 and 2012-2015. We also determined the time and number of visits required to achieve a diagnosis, the supplementary tests ordered, and the drugs prescribed according to dementia subtypes. METHODS: Medical charts of a stratified random sample of 475 ReDeGi cases were reviewed. Basic dementia work-up was evaluated using as a reference evidence-based CPG. An Index of Adherence (AI) was calculated using the following items in the medical chart: cognitive symptomatology; functional disability evaluation; physical examination; neurological examination; psychiatric examination; brief cognitive examination; activities of daily living performance examination; blood test; structural neuroimaging (CT-scan or MRI). RESULTS: The mean AI to CPG among specialists was of 8.2 points, and it improved from 7.9 points in 2007-2011 to 8.5 points in 2012-2015 (Cohen's d = 0.46). A lower adherence was detected in the most severe cases. A dementia diagnosis required 3.5 visits, regardless of the subtype of dementia, although milder cases required more time, more visits, and more supplementary tests than severe cases. CONCLUSION: The adherence to CPG in the catchment area of the ReDeGi is high, and an epidemiological surveillance system such as the ReDeGi may help in improving it. Dementia guidelines should establish procedures adapted to clinical practice, with simplified recommendations for most severe cases.

Adult-Onset Epilepsy in Presymptomatic Alzheimer's Disease: A Retrospective Study. - DiFrancesco, Jacopo C; Tremolizzo, Lucio; Polonia, Valeria; Giussani, Giorgia; Bianchi, Elisa; Franchi, Carlotta; Nobili, Alessandro; Appollonio, Ildebrando; Beghi, Ettore; Ferrarese, Carlo (J Alzheimers Dis, 2017)
BACKGROUND: The prevalence of epilepsy with onset in adulthood increases with age, mainly due to the accumulation of brain damage. However, a significant proportion of patients experience seizures of unknown cause. Alzheimer's disease (AD) is associated with an increased risk of seizures. Seizure activity is interpreted as a secondary event related to hyperexcitability caused by amyloid-β aggregation. OBJECTIVE: Since neurodegenerative processes begin several years before clinical symptoms, epilepsy could be more frequent in the presymptomatic stages of dementia. METHODS: We retrospectively reviewed the prevalence of epilepsy of unknown origin with adult onset before cognitive decline in a large cohort of AD patients (EPS-AD) recruited based on clinical and neuropsychological data. Data of patients with epilepsy followed by AD were compared with two control groups: patients with AD without seizures (no EPS-AD) and a large reference population (RP). RESULTS: In AD patients, the prevalence of epilepsy of unknown origin, with onset in the adulthood before cognitive decline is 17.1 times higher compared with the RP (95% CI: 10.3-28.3). In EPS-AD, seizures begin on average 4.6 years (median 2.0) before the onset of cognitive symptoms and cognitive decline starts 3.6 years earlier compared with noEPS-AD. CONCLUSIONS: Neurodegenerative processes of dementia could play a key role in the pathogenesis of epilepsy in a subgroup of individuals intended to develop cognitive decline. Adult-onset epilepsy of undefined cause could thus represent a risk factor for the ongoing neurodegenerative damage, even preceding by years the onset of clinical symptoms of dementia.

Alcohol Intake and Cognitively Healthy Longevity in Community-Dwelling Adults: The Rancho Bernardo Study. - Richard, Erin L; Kritz-Silverstein, Donna; Laughlin, Gail A; Fung, Teresa T; Barrett-Connor, Elizabeth; McEvoy, Linda K (J Alzheimers Dis, 2017)
To better understand the association of alcohol intake with cognitively healthy longevity (CHL), we explored the association between amount and frequency of alcohol intake and CHL among 1,344 older community-dwelling adults. Alcohol intake was assessed by questionnaire in 1984-1987. Cognitive function was assessed in approximate four-year intervals between 1988 and 2009. Multinomial logistic regression, adjusting for multiple lifestyle and health factors, was used to examine the association between alcohol consumption and CHL (living to age 85 without cognitive impairment), survival to age 85 with cognitive impairment (MMSE score >1.5 standard deviations below expectation for age, sex, and education), or death before age 85. Most participants (88%) reported some current alcohol intake; 49% reported a moderate amount of alcohol intake, and 48% reported drinking near-daily. Relative to nondrinkers, moderate and heavy drinkers (up to 3 drinks/day for women and for men 65 years and older, up to 4 drinks/day for men under 65 years) had significantly higher adjusted odds of survival to age 85 without cognitive impairment (p's < 0.05). Near-daily drinkers had 2-3 fold higher adjusted odds of CHL versus living to at least age 85 with cognitive impairment (odds ratio (OR) = 2.06; 95% confidence interval (CI): 1.21, 3.49) or death before 85 (OR = 3.24; 95% CI: 1.92, 5.46). Although excessive drinking has negative health consequences, these results suggest that regular, moderate drinking may play a role in cognitively healthy longevity.

Alterations in the Peripheral Immune System in Dementia. - Busse, Mandy; Michler, Enrico; von Hoff, Franz; Dobrowolny, Henrik; Hartig, Roland; Frodl, Thomas; Busse, Stefan (J Alzheimers Dis, 2017)
Alterations in the immune response that result in inflammation might play a role in the pathology of dementias. In order to analyze changes of the peripheral immune system associated with different types of dementias, we determined several innate and adaptive cell populations in whole blood using flow cytometry. We included patients with Alzheimer's disease (AD; n = 60), vascular dementia (VaD; n = 20), and frontotemporal dementia (FTD; n = 12) at the time point of diagnosis and 24 age-matched neuropsychiatric healthy persons. Monocytes and NK cells were diminished in VaD, but not in AD and FTD. B cell and T cell numbers were decreased in all investigated forms of dementia. Changes in the contribution of naïve/memory T cells were only present in AD. Correlation and regression analyses revealed associations between altered immune cell populations and Q Albumin as marker for the integrity of the blood-cerebrospinal fluid-barrier, Mini-Mental State Examination values, and age. The peripheral immune system is altered in AD, VaD, and FTD. However, each disorder presents unique changes in the investigated cell types indicating different mechanisms underlying the pathology.

Altered Gut Microbiota in a Mouse Model of Alzheimer's Disease. - Zhang, Ling; Wang, Ying; Xiayu, Xia; Shi, Changhua; Chen, Wei; Song, Nan; Fu, Xinjing; Zhou, Rui; Xu, Yan-Feng; Huang, Lan; Zhu, Hua; Han, Yunlin; et al. (J Alzheimers Dis, 2017)
The topic of gut microbiota is currently attracting considerable interest as a potential factor in Alzheimer's disease (AD). However, the extent and time course of alterations in the gut microbiota, and their effects on AD pathology remain uncertain. Herein, we compared the fecal microbiomes and fecal short chain fatty acid composition (SCFAs) between wild-type and AD model mice at different ages under strictly controlled specific pathogen free conditions, and also conducted microscopic investigations of intestinal structures. Our results showed that the microbiota composition and diversity were perturbed and the level of SCFAs was reduced in AD mice, predicting alterations in more than 30 metabolic pathways, which may be associated with amyloid deposition and ultrastructural abnormalities in AD mouse intestine. These findings indicate that AD pathology might not only affect brain function directly, but also exacerbate cognitive deficits through reducing the level of SCFAs via alterations of gut microbiota induced by intestinal amyloid deposition. Our data may support a role of gut microbiota, and suggest a novel route for therapeutic intervention in AD.

Anomalous White Matter Structure and the Effect of Age in Down Syndrome Patients. - Fenoll, Raquel; Pujol, Jesus; Esteba-Castillo, Susanna; de Sola, Susana; Ribas-Vidal, Núria; García-Alba, Javier; Sánchez-Benavides, Gonzalo; Martínez-Vilavella, Gerard; Deus, Joan; Dierssen, Mara; Novell-Alsina, Ramón; de la Torre, Rafael (J Alzheimers Dis, 2017)
BACKGROUND: Neural tissue alterations in Down syndrome are fully expressed at relatively late developmental stages. In addition, there is an early presence of neurodegenerative changes in the late life stages. OBJECTIVE: The aims of this study were both to characterize white matter abnormalities in the brain of adult Down syndrome patients using diffusion tensor imaging (DTI) and to investigate whether degenerative alterations in white matter structure are detectable before dementia is clinically evident. METHODS: Forty-five adult non-demented Down syndrome patients showing a wide age range (18-52 years) and a matched 45-subject control group were assessed. DTI fractional anisotropy (FA) brain maps were generated and selected cognitive tests were administered. RESULTS: Compared with healthy controls, non-demented Down syndrome patients showed lower DTI FA in white matter involving the major pathways, but with more severe alterations in the frontal-subcortical circuits. White matter FA decreased with age at a similar rate in both DS and control groups. CONCLUSIONS: Our results contribute to characterizing the expression of white matter structural alterations in adult Down syndrome. However, an accelerated aging effect was not demonstrated, which may suggest that the FA measurements used are not sufficiently sensitive or, alternatively, age-related white matter neurodegeneration is not obvious prior to overt clinical dementia.

Aortic Valve Calcification and the Risk of dementia: A Population-Based Study. - Wolters, Frank J; Bos, Daniel; Vernooij, Meike W; Franco, Oscar H; Hofman, Albert; Koudstaal, Peter J; van der Lugt, Aad; Ikram, M Arfan (J Alzheimers Dis, 2017)
The association of aortic valve calcification (AVC) with dementia remains unknown. In 2,428 non-demented participants from the population-based Rotterdam Study, we investigated the association of CT-assessed AVC with risk of dementia and cognitive decline. AVC was present in 33.1% of the population. During a median follow-up of 9.3 years, 160 participants developed dementia. We found no association between presence of AVC and risk of all-cause dementia [hazard ratio (HR): 0.89 (95% confidence interval (CI):0.63;1.26)]. Presence of AVC was not associated with cognitive decline on any of the cognitive tests, nor with a measure of global cognition.

APOEɛ4 Genotype, Amyloid, and Clinical Disease Progression in Cognitively Normal Older Adults. - Hollands, Simone; Lim, Yen Ying; Laws, Simon M; Villemagne, Victor L; Pietrzak, Robert H; Harrington, Karra; Porter, Tenielle; Snyder, Peter; Ames, David; Fowler, Christopher; Rainey-Smith, Stephanie R; Martins, Ralph N; et al. (J Alzheimers Dis, 2017)
BACKGROUND: In cognitively normal (CN) older adults, carriage of the apolipoprotein E (APOE) ɛ4 allele is associated with increased risk for dementia of the Alzheimer type (AD-dementia). It is unclear whether this occurs solely through APOEɛ4 increasing amyloid-β (Aβ) accumulation or through processes independent of Aβ. OBJECTIVE: To determine the extent and nature to which APOEɛ4 increases risk for clinical disease progression in CN older adults. METHODS: Data from the total (n = 765) and Aβ-imaged (n = 423) CN cohort in the Australian Imaging, Biomarker and Lifestyle (AIBL) Study of Ageing was analyzed using Cox proportional hazard models to estimate ɛ4 risk for clinical disease progression over a 72-month follow-up. RESULTS: With Aβ status unknown and risk from demographic characteristics controlled, ɛ4 carriage increased risk for clinical disease progression over 72 months by 2.66 times compared to risk of non-ɛ4 carriage. Re-analysis with Aβ status included showed that abnormally high Aβ increased risk for clinical disease progression over 72 months by 2.11 times compared to risk of low Aβ. However, with Aβ level known, ɛ4 carriage was no longer predictive of clinical disease progression. CONCLUSION: In CN older adults, the risk of ɛ4 for clinical disease progression occurs through the effect of ɛ4 increasing Aβ levels.

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.

Association Between Later Life Lifestyle Factors and Alzheimer's Disease Biomarkers in Non-Demented Individuals: A Longitudinal Descriptive Cohort Study. - Reijs, Babette L R; Vos, Stephanie J B; Soininen, Hilkka; Lötjönen, Jyrki; Koikkalainen, Juha; Pikkarainen, Maria; Hall, Anette; Vanninen, Ritva; Liu, Yawu; Herukka, Sanna-Kaisa; Freund-Levi, Yvonne; Frisoni, Giovanni B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Lifestyle factors have been associated with the risk of dementia, but the association with Alzheimer's disease (AD) remains unclear. OBJECTIVE: To examine the association between later life lifestyle factors and AD biomarkers (i.e., amyloid-β 1-42 (Aβ42) and tau in cerebrospinal fluid (CSF), and hippocampal volume) in individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI). In addition, to examine the effect of later life lifestyle factors on developing AD-type dementia in individuals with MCI. METHODS: We selected individuals with SCD (n = 111) and MCI (n = 353) from the DESCRIPA and Kuopio Longitudinal MCI studies. CSF Aβ42 and tau concentrations were assessed with ELISA assay and hippocampal volume with multi-atlas segmentation. Lifestyle was assessed by clinical interview at baseline for: social activity, physical activity, cognitive activity, smoking, alcohol consumption, and sleep. We performed logistic and Cox regression analyses adjusted for study site, age, gender, education, and diagnosis. Prediction for AD-type dementia was performed in individuals with MCI only. RESULTS: Later life lifestyle factors were not associated with AD biomarkers or with conversion to AD-type dementia. AD biomarkers were strongly associated with conversion to AD-type dementia, but these relations were not modulated by lifestyle factors. Apolipoprotein E (APOE) genotype did not influence the results. CONCLUSIONS: Later life lifestyle factors had no impact on key AD biomarkers in individuals with SCD and MCI or on conversion to AD-type dementia in MCI.

Baseline Telomere Length and Effects of a Multidomain Lifestyle Intervention on Cognition: The FINGER Randomized Controlled Trial. - Sindi, Shireen; Ngandu, Tiia; Hovatta, Iiris; Kåreholt, Ingemar; Antikainen, Riitta; Hänninen, Tuomo; Levälahti, Esko; Laatikainen, Tiina; Lindström, Jaana; Paajanen, Teemu; Peltonen, Markku; Khalsa, Dharma Singh; et al. (J Alzheimers Dis, 2017)
Leukocyte telomere length (LTL) is a biomarker of aging, and it is associated with lifestyle. It is currently unknown whether LTL is associated with the response to lifestyle interventions. The goal is to assess whether baseline LTL modified the cognitive benefits of a 2-year multidomain lifestyle intervention (exploratory analyses). The Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) was a 2-year randomized controlled trial including 1,260 people at risk of cognitive decline, aged 60-77 years identified from the general population. Participants were randomly assigned to the lifestyle intervention (diet, exercise, cognitive training, and vascular risk management) and control (general health advice) groups. Primary outcome was change in cognition (comprehensive neuropsychological test battery). Secondary outcomes were changes in cognitive domains: memory, executive functioning, and processing speed. 775 participants (392 control, 383 intervention) had baseline LTL (peripheral blood DNA). Mixed effects regression models with maximum likelihood estimation were used to analyze change in cognition as a function of randomization group, time, baseline LTL, and their interaction. Intervention and control groups did not significantly differ at baseline. Shorter LTL was related to less healthy baseline lifestyle. Intervention benefits on executive functioning were more pronounced among those with shorter baseline LTL (p-value for interaction was 0.010 adjusted for age and sex, and 0.007 additionally adjusted for baseline lifestyle factors). The FINGER intervention cognitive benefits were more pronounced with shorter baseline LTL, particularly for executive functioning, indicating that the multidomain lifestyle intervention was especially beneficial among higher-risk individuals.

Beyond a Differential Diagnosis: Cognitive and Morphometric Decoding of Information Processing Speed in Senior Adults with DSM-5 Mild Neurocognitive Disorders. - Lu, Hanna; Chan, Sandra S M; Fung, Ada W T; Lam, Linda C W (J Alzheimers Dis, 2017)
BACKGROUND: Processing speed has been highlighted as a diagnostic item for neurocognitive disorders (NCD) in DSM-5. The utility of information processing speed (IPS) enclosed with multiscale constructs in the diagnosis of NCD warrants exploration. OBJECTIVE: We aimed to investigate the IPS with two types of measurements in the patients with NCD due to vascular disease (NCD-vascular) and NCD due to Alzheimer's disease (NCD-AD), and examine the associations between IPS measures and morphometric features. METHODS: The IPS was evaluated using trail making test (TMT) and flanker test (n = 204). Direct scores, derived scores, and reaction time (RT) were used as IPS measures. Further, surface-based morphometry cortical volume was calculated in a subsample (n = 44) with structural MRI data. RESULTS: All IPS measures showed a significant value to differentiate NCD patients from healthy subjects. Only mean RT could distinguish NCD-AD from NCD-vascular groups. TMT-B score and difference score were correlated with gray matter volume (GMV) of inferior frontal gyrus, precuneus and superior temporal cortex. Mean RT was associated with the GMV of post-central gyrus (r = -0.327, p = 0.035), and executive speed was associated with inferior frontal cortex (r = -0.475, p = 0.001), cingulate gyrus (r = -0.497, p = 0.001), and superior temporal gyrus (r = -0.36, p = 0.019). CONCLUSION: The cognitive and morphometric correlates of IPS measures indicate that complex IPS might be decomposed into the domain-specific components with corresponding neural underpinnings. Our findings may also provide essential insights into the diagnostic item of NCD.

Blood Pressure and Hispanic/Latino Cognitive Function: Hispanic Community Health Study/Study of Latinos Results. - Tarraf, Wassim; Rodríguez, Carlos J; Daviglus, Martha L; Lamar, Melissa; Schneiderman, Neil; Gallo, Linda; Talavera, Gregory A; Kaplan, Robert C; Fornage, Myriam; Conceicao, Alan; González, Hector M (J Alzheimers Dis, 2017)
BACKGROUND: Hispanics/Latinos are at increased risk for cardiovascular disease and cognitive decline and dementias. High blood pressure (BP) has been implicated in both stroke and dementias. Associations between BP and cognition among diverse Latinos are still unpublished. OBJECTIVE: We examined associations between cognition and four BP based measures among diverse Hispanics/Latinos. We hypothesized that higher BP, particularly systolic pressure, and increased arterial stiffness (i.e., pulse pressure), would be associated with lower cognitive function. METHODS: We used baseline (2008-2011) Hispanic Community Health Study/Study of Latinos (HCHS/SOL; n = 9,019; ages 45-74 years) data to examine cognition in relation to BP measures. RESULTS: In age, sex, and education adjusted models, systolic, pulse, and mean arterial pressure were consistently negatively associated with executive function, psychomotor speed and sustained attention, verbal episodic learning and memory, speech fluency, and mental status measures. These associations were attenuated but remained statistically significant in fully adjusted models. CONCLUSION: Among middle-aged and older diverse Hispanics/Latinos, we found modest but consistent associations between indicators of arterial stiffness, and compromised blood flow and lower cognitive function. Clinical management and public health interventions to raise awareness and enhance BP management beginning in midlife could reduce disparities and improve population health by reducing cognitive decline burdens.

Capsaicin Attenuates Amyloid-β-Induced Synapse Loss and Cognitive Impairments in Mice. - Chen, Long; Huang, Zhilin; Du, Yehong; Fu, Min; Han, Huili; Wang, Yutian; Dong, Zhifang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is the most common cause of progressive cognitive impairment in the aged. The aggregation of the amyloid β-protein (Aβ) is a hallmark of AD and is linked to synapse loss and cognitive impairment. Capsaicin, a specific agonist of the transient receptor potential vanilloid 1 (TRPV1), has been proven to ameliorate stress-induced AD-like pathological and cognitive impairments, but it is unclear whether TRPV1 activation can affect cognitive and synaptic functions in Aβ-induced mouse model of AD. In this study, we investigated the effects of TRPV1 activation on spatial memory and synaptic plasticity in mice treated with Aβ. To induce AD-like pathological and cognitive impairments, adult C57Bl/6 mice were microinjected with Aβ42 (100 μM, 2.5 μl/mouse, i.c.v.). Two weeks after Aβ42 microinjection, spatial learning and memory as well as hippocampal long-term potentiation (LTP) were examined. The results showed that Aβ42 microinjection significantly impaired spatial learning and memory in the Morris water maze and novel object recognition tests compared with controls. These behavioral changes were accompanied by synapse loss and impaired LTP in the CA1 area of hippocampus. More importantly, daily capsaicin (1 mg/kg, i.p.) treatment throughout the experiment dramatically improved spatial learning and memory and synaptic function, as reflected by enhanced hippocampal LTP and reduced synapse loss, whereas the TRPV1 antagonist capsazepine (1 mg/kg, i.p.) treatment had no effects on cognitive and synaptic function in Aβ42-treated mice. These results indicate that TRPV1 activation by capsaicin rescues cognitive deficit in the Aβ42-induced mouse model of AD both structurely and functionally.

Cerebrospinal Fluid Aβ42/40 Corresponds Better than Aβ42 to Amyloid PET in Alzheimer's Disease. - Lewczuk, Piotr; Matzen, Anja; Blennow, Kaj; Parnetti, Lucilla; Molinuevo, José Luis; Eusebi, Paolo; Kornhuber, Johannes; Morris, John C; Fagan, Anne M (J Alzheimers Dis, 2017)
BACKGROUND: Decreased concentrations of amyloid-β 1-42 (Aβ42) in cerebrospinal fluid (CSF) and increased retention of Aβ tracers in the brain on positron emission tomography (PET) are considered the earliest biomarkers of Alzheimer's disease (AD). However, a proportion of cases show discrepancies between the results of the two biomarker modalities which may reflect inter-individual differences in Aβ metabolism. The CSF Aβ42/40 ratio seems to be a more accurate biomarker of clinical AD than CSF Aβ42 alone. OBJECTIVE: We tested whether CSF Aβ42 alone or the Aβ42/40 ratio corresponds better with amyloid PET status and analyzed the distribution of cases with discordant CSF-PET results. METHODS: CSF obtained from a mixed cohort (n = 200) of cognitively normal and abnormal research participants who had undergone amyloid PET within 12 months (n = 150 PET-negative, n = 50 PET-positive according to a previously published cut-off) was assayed for Aβ42 and Aβ40 using two recently developed immunoassays. Optimal CSF cut-offs for amyloid positivity were calculated, and concordance was tested by comparison of the areas under receiver operating characteristic (ROC) curves (AUC) and McNemar's test for paired proportions. RESULTS: CSF Aβ42/40 corresponded better than Aβ42 with PET results, with a larger proportion of concordant cases (89.4% versus 74.9%, respectively, p < 0.0001) and a larger AUC (0.936 versus 0.814, respectively, p < 0.0001) associated with the ratio. For both CSF biomarkers, the percentage of CSF-abnormal/PET-normal cases was larger than that of CSF-normal/PET-abnormal cases. CONCLUSION: The CSF Aβ42/40 ratio is superior to Aβ42 alone as a marker of amyloid-positivity by PET. We hypothesize that this increase in performance reflects the ratio compensating for general between-individual variations in CSF total Aβ.

Cerebrospinal Fluid Biomarkers and Clinical Progression in Patients with Subjective Cognitive Decline and Mild Cognitive Impairment. - Wolfsgruber, Steffen; Polcher, Alexandra; Koppara, Alexander; Kleineidam, Luca; Frölich, Lutz; Peters, Oliver; Hüll, Michael; Rüther, Eckart; Wiltfang, Jens; Maier, Wolfgang; Kornhuber, Johannes; Lewczuk, Piotr; et al. (J Alzheimers Dis, 2017)
BACKGROUND: There is very limited data on the prevalence of abnormal cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) and their predictive value for clinical progression in memory clinic patients with subjective cognitive decline (SCD). OBJECTIVE: To assess the frequency of abnormal CSF biomarkers of AD and their predictive value for clinical progression in memory clinic patients with SCD in comparison to patients with mild cognitive impairment (MCI) from the same cohort. METHODS: We analyzed prospective data from memory clinic patients of the German Competence Network Dementia cohort with a baseline diagnosis of SCD (n = 82) or MCI (n = 134), distinguished by actuarial neuropsychological MCI criteria ("Jak-Bondi criteria"). Risk of clinical progression during 3-year follow-up was evaluated with Cox-Proportional-Hazard models. RESULTS: Prevalence of abnormal values in CSF markers of tau-mediated neurodegeneration (67.8% versus 46.3%) but not of amyloid deposition (40.3% versus 35.4%) was significantly higher in MCI compared to SCD. The rate of incident AD dementia (26.1% versus 12.2%) was also significantly higher in MCI. In SCD, additional 22% progressed to MCI during follow-up. Combined amyloid/tau abnormality was the strongest predictor of clinical progression in both groups. CONCLUSION: High prevalence of biomarker abnormality and clinical progression, together with the predictive value of CSF biomarkers, in memory clinic patients with SCD support the validity and usefulness of this condition as a "pre-MCI" at risk stage of AD.

Cerebrospinal Fluid Biomarkers for the Differential Diagnosis between Alzheimer's Disease and Frontotemporal Lobar Degeneration: Systematic Review, HSROC Analysis, and Confounding Factors. - Rivero-Santana, Amado; Ferreira, Daniel; Perestelo-Pérez, Lilisbeth; Westman, Eric; Wahlund, Lars-Olof; Sarría, Antonio; Serrano-Aguilar, Pedro (J Alzheimers Dis, 2017)
BACKGROUND: Differential diagnosis in dementia is at present one of the main challenges both in clinical practice and research. Cerebrospinal fluid (CSF) biomarkers are included in the current diagnostic criteria of Alzheimer's disease (AD) but their clinical utility is still unclear. OBJECTIVE: We performed a systematic review of studies analyzing the diagnostic performance of CSF Aβ42, total tau (t-tau), and phosphorylated tau (p-tau) in the discrimination between AD and frontotemporal lobar degeneration (FTLD) dementias. METHODS: The following electronic databases were consulted until May 2016: Medline and PreMedline, EMBASE, PsycInfo, CINAHL, Cochrane Library, and CRD. For the first-time in the field, a Hierarchical Summary Receiver Operating Characteristic (HRSOC) model was applied, which avoids methodological problems of meta-analyses based on summary points of sensitivity and specificity values. We also investigated relevant confounders of CSF biomarkers' diagnostic performance such as age, disease duration, and global cognitive impairment. RESULTS: The p-tau/Aβ42 ratio showed the best diagnostic performance. No statistically significant effects of the confounders were observed. Nonetheless, the p-tau/Aβ42 ratio may be especially indicated for younger patients. P-tau may be preferable for less cognitively impaired patients (high MMSE scores) and the t-tau/Aβ42 ratio for more cognitively impaired patients (low MMSE scores). CONCLUSION: The p-tau/Aβ42 ratio has potential for being implemented in the clinical routine for the differential diagnosis between AD and FTLD. It is of utmost importance that future studies report information on confounders such as age, disease duration, and cognitive impairment, which should also stimulate understanding of the role of these factors in disease mechanisms and pathophysiology.

Cerebrospinal Fluid Neurogranin as a Biomarker of Neurodegenerative Diseases: A Cross-Sectional Study. - Lista, Simone; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J; Cavedo, Enrica; Dos Santos, Antonio Melo; Epelbaum, Stéphane; Lamari, Foudil; Dubois, Bruno; et al. (J Alzheimers Dis, 2017)
We investigated cerebrospinal fluid (CSF) concentrations of the postsynaptic biomarker neurogranin at baseline in cognitively healthy controls (HC) compared to individuals with mild cognitive impairment (MCI), patients with Alzheimer's disease (AD) dementia, and patients with frontotemporal dementia (FTD). CSF neurogranin was quantified using an in-house immunoassay in a cross-sectional multicenter study of 108 participants [AD dementia (n = 35), FTD (n = 9), MCI (n = 41), cognitively HC (n = 23)]. CSF neurogranin concentrations were significantly higher in AD patients compared with both HC subjects and FTD patients, suggesting that increased CSF neurogranin concentrations may indicate AD-related pathophysiology. CSF neurogranin was independently associated with both total tau and hyperphosphorylated tau proteins, whereas a non-significant correlation with the 42-amino acid-long amyloid-β peptide was evident. CSF neurogranin, however, was not superior to core AD biomarkers in differentiating HC from the three diagnostic groups, and it did not improve their diagnostic accuracy. We conclude that further classification and longitudinal studies are required to shed more light into the potential role of neurogranin as a pathophysiological biomarker of neurodegenerative diseases.

Challenges and Considerations Related to Studying Dementia in Blacks/African Americans. - Ighodaro, Eseosa T; Nelson, Peter T; Kukull, Walter A; Schmitt, Frederick A; Abner, Erin L; Caban-Holt, Allison; Bardach, Shoshana H; Hord, Derrick C; Glover, Crystal M; Jicha, Gregory A; Van Eldik, Linda J; Byrd, Alexander X; et al. (J Alzheimers Dis, 2017)
Blacks/African Americans have been reported to be ∼2-4 times more likely to develop clinical Alzheimer's disease (AD) compared to Whites. Unfortunately, study design challenges (e.g., recruitment bias), racism, mistrust of healthcare providers and biomedical researchers, confounders related to socioeconomic status, and other sources of bias are often ignored when interpreting differences in human subjects categorized by race. Failure to account for these factors can lead to misinterpretation of results, reification of race as biology, discrimination, and missed or delayed diagnoses. Here we provide a selected historical background, discuss challenges, present opportunities, and suggest considerations for studying health outcomes among racial/ethnic groups. We encourage neuroscientists to consider shifting away from using biologic determination to interpret data, and work instead toward a paradigm of incorporating both biological and socio-environmental factors known to affect health outcomes with the goal of understanding and improving dementia treatments for Blacks/African Americans and other underserved populations.

Changes in Plasma β-NGF and Its Receptors Expression on Peripheral Blood Monocytes During Alzheimer's Disease Progression. - Crispoltoni, Lucia; Stabile, Anna Maria; Pistilli, Alessandra; Venturelli, Massimo; Cerulli, Giuliano; Fonte, Cristina; Smania, Nicola; Schena, Federico; Rende, Mario (J Alzheimers Dis, 2017)
Alzheimer's disease (AD), the most common cause of dementia, is characterized by the deposition of extracellular amyloid-β (Aβ) plaques and intracellular neurofibrillary tangles, and by neuroinflammation. During the pathogenesis of AD, monocyte-macrophage lineage cells become increasingly ineffective in clearing Aβ deposits, less able to differentiate, and shift toward pro-inflammatory processes. Beta-nerve growth factor (β-NGF) and its receptors, TrKA and p75NTR, produce several biological responses, including cell apoptosis and survival, and inflammation. In the central nervous system, the involvement of these receptors in several critical hallmarks of AD is well known, but their role in circulating monocytes during the progression of dementia is unclear. We investigated the relationship between plasma β-NGF concentration and TrkA/p75NTR receptor expression in monocytes of patients with mild cognitive impairment (MCI), mild AD, and severe AD. We observed that plasma β-NGF concentration was increased with a higher expression of TrKA, but not of p75NTR, in monocytes from patients with MCI and mild AD, whereas β-NGF concentration and TrKA expression were decreased and p75NTR expression was increased, associated with caspase 3-mediated apoptosis, in patients with severe AD. In our study, we show evidence of variation in plasmatic β-NGF and monocytic TrkA/p75NTR receptor expression during the progression of dementia. These novel findings add evidence to support the hypothesis for the involvement of β-NGF and its receptors on monocytes during AD progression.

Changes in Synaptic Plasticity and Glutamate Receptors in Type 2 Diabetic KK-Ay Mice. - Yin, Huajing; Wang, Weiping; Yu, Wenwen; Li, Jiang; Feng, Nan; Wang, Ling; Wang, Xiaoliang (J Alzheimers Dis, 2017)
In the present study, the progressive alteration of cognition and the mechanisms of reduction in long-term potentiation (LTP) in spontaneous obese KK-Ay type 2 diabetic mice were investigated. In the study, 3-, 5-, and 7-month-old KK-Ay mice were used. The results indicated that KK-Ay mice showed cognitive deficits in the Morris water maze test beginning at the age of 3 months. LTP was significantly impaired in KK-Ay mice during whole study period (3 to 7 months). The above deficits were reversible at an early stage (3 to 5 months old) by diet intervention. Moreover, we found the underlying mechanisms of LTP impairment in KK-Ay mice might be attributed to abnormal phosphorylation or expression of postsynaptic glutamate receptor subunits instead of alteration of basal synaptic transmission. The expression levels of NR1, NR2A, and NR2B subunits of N-methyl-d-aspartate receptors (NMDARs) were unchanged while the Tyr-dependent phosphorylation of both NR2A and NR2B subunits were significantly reduced in KK-Ay mice. The level of p-Src expression mediating this process was decreased, and the level of αCaMKII autophosphorylation was also reduced. Meanwhile, the GluR1 of α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs) was decreased, and GluR2 was significantly increased. These data suggest that deficits in synaptic plasticity in KK-Ay mice may arise from the abnormal phosphorylation of the NR2 subunits and the alteration of subunit composition of AMPARs. Diet intervention at an early stage of diabetes might alleviate the cognitive deficits and LTP reduction in KK-Ay mice.

Chinese Calligraphy Writing for Augmenting Attentional Control and Working Memory of Older Adults at Risk of Mild Cognitive Impairment: A Randomized Controlled Trial. - Chan, Sam C C; Chan, Chetwyn C H; Derbie, Abiot Y; Hui, Irene; Tan, Davynn G H; Pang, Marco Y C; Lau, Stephen C L; Fong, Kenneth N K (J Alzheimers Dis, 2017)
BACKGROUND: Nonpharmacological intervention for individuals with mild cognitive impairment (MCI) needs further investigation. OBJECTIVE: Test efficacy of an eight-week Chinese calligraphy writing training course in improving attentional control and working memory. METHODS: Ninety-nine participants with MCI were randomized into the eight-week calligraphy writing (n = 48) or control (tablet computer) training (n = 51). Outcomes of the interventions were attentional control, working memory, visual scan and processing speed. They were measured at baseline, post-training, and six-month follow-up. RESULTS: Calligraphy writing, when compared with control, significantly improved working memory as reflected from DST-Backward sequence (p = 0.009) and span scores (p = 0.002), and divided attention as reflected from CTT2 (p < 0.001), and at the post-training. The unique improvement in working memory (span: p < 0.001; sequence: p = 0.008) of the intervention group was also found at follow-up when comparing with those at baseline. Changes in the other outcome measures were not statistically significant. CONCLUSION: The findings provide support that Chinese calligraphy writing training for eight weeks using a cognitive approach would improve working memory and to a lesser extent attentional control functions of patients with early MCI. They also demonstrate the usefulness of using mind-and-body practice for improving specific cognitive functions.

Chronic Verubecestat Treatment Suppresses Amyloid Accumulation in Advanced Aged Tg2576-AβPPswe Mice Without Inducing Microhemorrhage. - Villarreal, Stephanie; Zhao, Fuqiang; Hyde, Lynn A; Holder, Daniel; Forest, Thomas; Sondey, Marie; Chen, Xia; Sur, Cyrille; Parker, Eric M; Kennedy, Matthew E (J Alzheimers Dis, 2017)
Verubecestat is a potent BACE1 enzyme inhibitor currently being investigated in Phase III trials for the treatment of mild-to-moderate and prodromal Alzheimer's disease. Multiple anti-amyloid immunotherapies have been dose-limited by adverse amyloid related imaging abnormalities such as vasogenic edema (ARIA-E) and microhemorrhage (ARIA-H) observed in human trials and mice. Verubecestat was tested in a 12-week nonclinical study for the potential to exacerbate microhemorrhage (ARIA-H) profiles in 18-22-month-old post-plaque Tg2576-AβPPswe mice. Animals were treated with verubecestat or controls including the anti-Aβ antibody analog of bapineuzumab (3D6) as a positive control for ARIA induction. ARIA-H was measured using in-life longitudinal T2*-MRI and Prussian blue histochemistry at study end. Verubecestat reduced plasma and cerebrospinal fluid Aβ40 and Aβ42 by >90% and 62% to 68%, respectively. The ARIA-H profile of verubecestat-treated mice was not significantly different than controls. Anti-Aβ treatment significantly increased ARIA-H detected by Prussian blue staining; however, anti-Aβ antibody treatment did not impact plaque status. Verubecestat treatment significantly suppressed the accumulation of total levels of brain Aβ40 and Aβ42 and Thioflavin S positive plaque load. Stereological analysis of cortex and hippocampus plaque load similarly revealed significantly reduced area of Aβ immunoreactivity and reduced plaque number in verubecestat-treated animals compared to controls. The absence of elevated ARIA events in verubecestat-treated mice was associated with a significant reduction in the level of accumulated CNS amyloid pathology and brain Aβ peptides; effects consistent with the desired therapeutic mechanism of verubecestat in AD patients. These data will be compared with longitudinal MRI profiles from ongoing clinical trials.

The Clinical Use of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease Diagnosis: The Italian Selfie. - Sancesario, Giulia M; Toniolo, Sofia; Chiasserini, Davide; Di Santo, Simona G; Zegeer, Josh; Bernardi, Gaetano; Musicco, Massimo; Caltagirone, Carlo; Parnetti, Lucilla; Bernardini, Sergio (J Alzheimers Dis, 2017)
Although the use of cerebrospinal fluid (CSF) amyloid β1-42 (Aβ42), tau (T-tau), and phosphorylated tau (p-tau181) gives added diagnostic and prognostic values, the diffusion is still limited in clinical practice and only a restricted number of patients receive an integrated clinico-biological diagnosis. By a survey, we aimed to do a "selfie" of the use and diffusion of CSF biomarkers of dementia in Italy, the standardization of pre-analytical procedures, the harmonization of ranges, and the participation to Quality Control programs. An online questionnaire was sent to the members of SIBioC and SINdem-ITALPLANED and to main neurological clinics all over Italy. In Italy, 25 laboratories provide biomarkers analysis in addition to a network of 15 neighboring hospitals. In sum, 40 neurological centers require CSF analyses. 7/20 regions (35%) lack CSF laboratories. Standardization of pre-analytical procedures is present in 62.02% of the laboratories; only 56.00% of the laboratories participate in International Quality Control. There is no harmonization of cut-offs. In Italy, the use of CSF biomarkers is still limited in clinical practice. Standardization and harmonization of normal ranges are needed. To optimize and expand the use of CSF biomarkers, a cost-benefit analysis should be promoted by scientific societies and national health services.

A Common Variant in the MC1R Gene (p.V92M) is associated with Alzheimer's Disease Risk. - Tell-Marti, Gemma; Puig-Butille, Joan Anton; Potrony, Miriam; Plana, Estel; Badenas, Celia; Antonell, Anna; Sánchez-Valle, Raquel; Molinuevo, José L; Lleo, Alberto; Alcolea, Daniel; Fortea, Juan; Fernández-Santiago, Rubén; et al. (J Alzheimers Dis, 2017)
Despite the recent identification of some novel risk genes for Alzheimer's disease (AD), the genetic etiology of late-onset Alzheimer's disease (LOAD) remains largely unknown. The inclusion of these novel risk genes to the risk attributable to the APOE gene accounts for roughly half of the total genetic variance in LOAD. The evidence indicates that undiscovered genetic factors may contribute to AD susceptibility. In the present study, we sequenced the MC1R gene in 525 Spanish LOAD patients and in 160 controls. We observed that a common MC1R variant p.V92M (rs2228479), not related to pigmentation traits, was present in 72 (14%) patients and 15 (9%) controls and confers increased risk of developing LOAD (OR: 1.99, 95% CI: 1.08-3.64, p = 0.026), especially in those patients whose genetic risk could not be explained by APOE genotype. This association remains and even increased in the subset of 69 patients with typical AD cerebrospinal fluid profile (OR: 3.40 95% CI: 1.40-8.27, p = 0.007). We did not find an association between p.V92M and age of onset of AD. Further studies are necessary to elucidate the role of MC1R in brain cells through the different MC1R pathways.

A Common Variant of IL-6R is Associated with Elevated IL-6 Pathway Activity in Alzheimer's Disease Brains. - Haddick, Patrick C G; Larson, Jessica L; Rathore, Nisha; Bhangale, Tushar R; Phung, Qui T; Srinivasan, Karpagam; Hansen, David V; Lill, Jennie R; Pericak-Vance, Margaret A; Haines, Jonathan; Farrer, Lindsay A; Kauwe, John S; et al. (J Alzheimers Dis, 2017)
The common p.D358A variant (rs2228145) in IL-6R is associated with risk for multiple diseases and with increased levels of soluble IL-6R in the periphery and central nervous system (CNS). Here, we show that the p.D358A allele leads to increased proteolysis of membrane bound IL-6R and demonstrate that IL-6R peptides with A358 are more susceptible to cleavage by ADAM10 and ADAM17. IL-6 responsive genes were identified in primary astrocytes and microglia and an IL-6 gene signature was increased in the CNS of late onset Alzheimer's disease subjects in an IL6R allele dependent manner. We conducted a screen to identify variants associated with the age of onset of Alzheimer's disease in APOE ɛ4 carriers. Across five datasets, p.D358A had a meta P = 3 ×10-4 and an odds ratio = 1.3, 95% confidence interval 1.12 -1.48. Our study suggests that a common coding region variant of the IL-6 receptor results in neuroinflammatory changes that may influence the age of onset of Alzheimer's disease in APOE ɛ4 carriers.

Computerized Cognitive Screen (CoCoSc): A Self-Administered Computerized Test for Screening for Cognitive Impairment in Community Social Centers. - Wong, Adrian; Fong, Ching-Hang; Mok, Vincent Chung-Tong; Leung, Kam-Tat; Tong, Raymond Kai-Yu (J Alzheimers Dis, 2017)
BACKGROUND: Computerized cognitive tests may serve as a preliminary, low-cost method to identify individuals with suspected cognitive impairment in the community. OBJECTIVE: To develop a self-administered computerized test, namely the "Computerized Cognitive Screen (CoCoSc), Hong Kong version", for screening of individuals with cognitive impairment (CI) in community settings. METHODS: The CoCoSc is a 15-min computerized cognitive screen covering memory, executive functions, orientation, attention and working memory, and prospective memory administered on a touchscreen computer. Individuals with CI and cognitively normal controls were administered the CoCoSc and the Montreal Cognitive Assessment (MoCA). Validity of the CoCoSc was assessed based on the relationship with the MoCA using Pearson correlation. Receiver operating characteristic curve (ROC) was used to examine the ability of the CoCoSc to differentiate CI from controls. RESULTS: Fifty-nine individuals with CI and 101 controls were recruited. Seventy-five (46.9%) participants had ≤6 years of education. Performance on the CoCoSc differed between normal and CI groups in both low and high education subgroups. Total scores of the CoCoSc and MoCA were significantly correlated (r = 0.71, p < 0.001). The area under ROC was 0.78, p < 0.001 for the CoCoSc total score in differentiating the CI group from the cognitively normal group. A cut-off of ≤30 on the CoCoSc was associated with a sensitivity of 0.78 and specificity of 0.69. The CoCoSc was well accepted by attendees of community social centers. CONCLUSION: The CoCoSc is a promising computerized cognitive screen for self-administration in community social centers. It is feasible for testing individuals with high or low education levels.

Coordinate-Based Meta-Analysis of the Default Mode and Salience Network for Target Identification in Non-Invasive Brain Stimulation of Alzheimer's Disease and Behavioral Variant Frontotemporal Dementia Networks. - Pievani, Michela; Pini, Lorenzo; Ferrari, Clarissa; Pizzini, Francesca B; Boscolo Galazzo, Ilaria; Cobelli, Chiara; Cotelli, Maria; Manenti, Rosa; Frisoni, Giovanni B (J Alzheimers Dis, 2017)
BACKGROUND: The accurate choice of the site of non-invasive brain stimulation (NIBS) is an important factor in trial design. OBJECTIVE: Based on the observation that Alzheimer's disease (AD) and behavioral frontotemporal dementia (bvFTD) affect specific large-scale networks, i.e., the default mode network (DMN) and the salience network (SN), respectively, we aimed to identify population-average coordinates of these networks that could be used as potential targets in NIBS trials aiming to modulate these circuits. METHODS: A systematic literature search of resting-state functional MRI studies reporting DMN and SN stereotactic coordinates was performed according to PRISMA guidelines. Coordinate-based meta-analyses were conducted to identify consistent nodes of the DMN and SN using GingerALE BrainMap software and the activation likelihood estimation method. RESULTS: DMN coordinates mapped primarily to mesial areas (posterior cingulate cortex/precuneus [Brodmann Area - BA 23/31] and medial prefrontal cortex [BA 9/10/32]). More superficial areas mapped to the bilateral parietal (angular gyrus [BA 39]), temporal (middle gyrus [BA 21]) and dorsolateral prefrontal (superior gyrus [BA 8]) cortex. SN coordinates mapped primarily to mesial and deep frontal areas (anterior insula, anterior cingulate cortex [BA 24/32]), but more superficial areas mapped to the bilateral parietal (supramarginal gyrus [BA 40]) and the right dorsolateral prefrontal (middle gyrus [BA 9/10]) cortex. CONCLUSIONS: NIBS should target the bilateral angular, the middle temporal cortex, or superior frontal gyri in AD for DMN modulation, and the right middle frontal or supramarginal gyri in bvFTD for SN modulation.
Keywords: Alzheimer Disease; Brain; Databases, Bibliographic; Deep Brain Stimulation; Electroencephalography; Frontotemporal Dementia; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Models, Neurological

Cortical Cerebral Microinfarcts on 3 Tesla MRI in Patients with Vascular Cognitive Impairment. - Ferro, Doeschka A; van Veluw, Susanne J; Koek, Huiberdina L; Exalto, Lieza G; Biessels, Geert Jan (J Alzheimers Dis, 2017)
BACKGROUND: Cerebral microinfarcts (CMIs) are small ischemic lesions that are a common neuropathological finding in patients with stroke or dementia. CMIs in the cortex can now be detected in vivo on 3 Tesla MRI. OBJECTIVE: To determine the occurrence of CMIs and associated clinical features in patients with possible vascular cognitive impairment (VCI). METHOD: 182 memory-clinic patients (mean age 71.4±10.6, 55% male) with vascular injury on brain MRI (i.e., possible VCI) underwent a standardized work-up including 3 Tesla MRI and cognitive assessment. A control group consisted of 70 cognitively normal subjects (mean age 70.6±4.7, 60% male). Cortical CMIs and other neuroimaging markers of vascular brain injury were rated according to established criteria. RESULT: Occurrence of CMIs was higher (20%) in patients compared to controls (10%). Among patients, the presence of CMIs was associated with male sex, history of stroke, infarcts, and white matter hyperintensities. CMI presence was also associated with a diagnosis of vascular dementia and reduced performance in multiple cognitive domains. CONCLUSION: CMIs on 3 Tesla MRI are common in patients with possible VCI and co-occur with imaging markers of small and large vessel disease, likely reflecting a heterogeneous etiology. CMIs are associated with worse cognitive performance, independent of other markers of vascular brain injury.

Cortical Metabolic and Cognitive Correlates of Disorientation in Alzheimer's Disease. - Weissberger, Gali H; Melrose, Rebecca J; Fanale, Candace M; Veliz, Joseph V; Sultzer, David L (J Alzheimers Dis, 2017)
Orientation to time, date, and place is commonly utilized in clinical settings to aid in diagnosis, staging, and monitoring of Alzheimer's disease (AD). This study aimed to identify the cerebral metabolic correlates of orientation in patients with AD, and the degree to which regions associated with orientation overlap with memory-related structures. Eighty-five patients with a diagnosis of probable AD underwent fluorodeoxyglucose positron emission tomography (FDG-PET) and neuropsychological testing. Orientation items from the Dementia Rating Scale and recognition performance from the Consortium to Establish a Registry for AD (CERAD) Word List Learning test were correlated with cerebral glucose metabolism. Post-hoc analyses examined neuropsychological predictors of orientation. Better orientation performance related to greater cerebral metabolism in the bilateral middle-inferior temporal lobes, bilateral middle-posterior cingulate, left angular gyrus, and left middle occipital gyrus. In comparison, higher CERAD recognition discriminability score was associated with greater metabolic activity in left medial temporal lobe regions including the hippocampal and parahippocampal gyri, and the left fusiform gyrus. Post-hoc behavioral analyses revealed multiple cognitive functions to be related to orientation, including list learning, recognition memory, visuospatial functioning, attention, and language. Findings from the present study suggest that disorientation in AD results from dysfunction of a network of structures and cognitive abilities commonly found to be implicated in AD. The study supports the notion that memory is necessary but not sufficient for successful orientation.

Cross-Sectional and Longitudinal Cognitive Correlates of FDDNP PET and CSF Amyloid-β and Tau in Parkinson's Disease1. - Buongiorno, Mariateresa; Antonelli, Francesca; Compta, Yaroslau; Fernandez, Yolanda; Pavía, Javier; Lomeña, Francisco; Ríos, José; Ramírez, Isabel; García, José Ramón; Soler, Marina; Cámara, Ana; Fernández, Manel; et al. (J Alzheimers Dis, 2017)
Tau and amyloid-β (Aβ) aggregates have been suggested to play a role in the development of dementia in Parkinson's disease (PD). Positron emission tomography (PET) with [18F]FDDNP and the determination of cerebrospinal fluid (CSF) levels of these proteins constitute a means to visualize in vivo Aβ and tau brain accumulation. Information about longitudinal changes of these CSF and PET biomarkers in PD with regard to progression to dementia is lacking. We assessed the cross-sectional and longitudinal associations of CSF and PET biomarkers of tau and Aβ with PD-related cognitive dysfunction in 6 healthy-controls (HC), 16 patients with PD without dementia (PDND), and 8 PD with dementia (PDD). All subjects underwent comprehensive neuropsychological testing, [18F]FDDNP PET, and CSF Aβ-tau determination. After 18 months, the PDND group was re-assessed clinically and by neuropsychological, PET, and CSF determinations. Cross-sectionally, PDD had higher [18F]FDDNP binding in lateral temporal regions and lower levels of CSF Aβ levels compared to PDND, with a congruent correlation between the [18F]FDDNP binding and CSF Aβ levels. Longitudinally, higher baseline lateral temporal [18F]FDDNP binding was associated to longitudinal worsening in cognitive performances and progression to dementia among subjects classified as PDND at baseline, who additionally disclosed at follow-up an increase in lateral-temporal FDDNP binding, as well as a reduction in CSF Aβ and an increase in CSF tau levels. These results confirm the relevance of these CSF and PET biomarkers to PDD, being specifically the first to show [18F]FDDNP PET as a dementia risk biomarker in PD, along with longitudinal CSF and PET changes over time.

Curcumin Ameliorates Neuroinflammation, Neurodegeneration, and Memory Deficits in p25 Transgenic Mouse Model that Bears Hallmarks of Alzheimer's Disease. - Sundaram, Jeyapriya Raja; Poore, Charlene Priscilla; Sulaimee, Noor Hazim Bin; Pareek, Tej; Cheong, Wei Fun; Wenk, Markus R; Pant, Harish C; Frautschy, Sally A; Low, Chian-Ming; Kesavapany, Sashi (J Alzheimers Dis, 2017)
Several studies have indicated that neuroinflammation is indeed associated with neurodegenerative disease pathology. However, failures of recent clinical trials of anti-inflammatory agents in neurodegenerative disorders have emphasized the need to better understand the complexity of the neuroinflammatory process in order to unravel its link with neurodegeneration. Deregulation of Cyclin-dependent kinase 5 (Cdk5) activity by production of its hyperactivator p25 is involved in the formation of tau and amyloid pathology reminiscent of Alzheimer's disease (AD). Recent studies show an association between p25/Cdk5 hyperactivation and robust neuroinflammation. In addition, we recently reported the novel link between the p25/Cdk5 hyperactivation-induced inflammatory responses and neurodegenerative changes using a transgenic mouse that overexpresses p25 (p25Tg). In this study, we aimed to understand the effects of early intervention with a potent natural anti-inflammatory agent, curcumin, on p25-mediated neuroinflammation and the progression of neurodegeneration in p25Tg mice. The results from this study showed that curcumin effectively counteracted the p25-mediated glial activation and pro-inflammatory chemokines/cytokines production in p25Tg mice. Moreover, this curcumin-mediated suppression of neuroinflammation reduced the progression of p25-induced tau/amyloid pathology and in turn ameliorated the p25-induced cognitive impairments. It is widely acknowledged that to treat AD, one must target the early-stage of pathological changes to protect neurons from irreversible damage. In line with this, our results demonstrated that early intervention of inflammation could reduce the progression of AD-like pathological outcomes. Moreover, our data provide a rationale for the potential use of curcuminoids in the treatment of inflammation associated neurodegenerative diseases.

Cyclic cis-Locked Phospho-Dipeptides Reduce Entry of AβPP into Amyloidogenic Processing Pathway. - Fisher, Carolyn L; Resnick, Ross J; De, Soumya; Acevedo, Lucila A; Lu, Kun Ping; Schroeder, Frank C; Nicholson, Linda K (J Alzheimers Dis, 2017)
The cis/trans isomerization of X-Pro peptide bonds in proteins in some instances acts as a molecular switch in biological pathways. Our prior work suggests that the cis isomer of the phospho-Thr668-Pro669 motif, located in the cytoplasmic domain of the amyloid-β protein precursor (AβPP), is correlated with an increase in amyloidogenic processing of AβPP and production of amyloid-beta (Aβ), the neurotoxic peptide fragment in Alzheimer's disease (AD). We designed a 100% cis-locked cyclic dipeptide composed of cyclized phospho-Thr-Pro (pCDP) as a mimic for this putative pathological conformation, and three phosphate-blocked derivatives (pCDP-diBzl, pCDP-Bzl, and pCDP-diPOM). Two H4 neuroglioma cell lines were established as AD cell models for use in testing these compounds: H4-AβPP695 for stable overexpression of wild-type AβPP695, and H4-BACE1 for stable overexpression of β-site AβPP cleaving enzyme-1 (BACE1). The level of the secreted AβPP fragment resulting from BACE1 activity, sAβPPβ, served as a key proxy for amyloidogenic processing, since cleavage of AβPP by BACE1 is a requisite first step in Aβ production. Of the compounds tested, pCDP-diBzl decreased sAβPPβ levels in both cell lines, while pCDP-diPOM decreased sAβPPβ levels in only H4-BACE1 cells, all with similar dose-dependences and patterns of proteolytic AβPP fragments. Enzymatic assays showed that none of the pCDP derivatives directly inhibit BACE1 catalytic activity. These results suggest a model in which pCDP-diBzl and pCDP-diPOM act at a common point to inhibit entry of AβPP into the amyloidogenic AβPP processing pathway but through different targets, and provide important insights for the development of novel AD therapeutics.

Damage to the Frontal Aslant Tract Accounts for Visuo-Constructive Deficits in Alzheimer's Disease. - Serra, Laura; Gabrielli, Giulia Bechi; Tuzzi, Elisa; Spanò, Barbara; Giulietti, Giovanni; Failoni, Virginia; Marra, Camillo; Caltagirone, Carlo; Koch, Giacomo; Cercignani, Mara; Bozzali, Marco (J Alzheimers Dis, 2017)
The frontal aslant tract (FAT) has been described as a bundle connecting the Broca's area to the supplementary motor area (SMA) and the pre-SMA in both hemispheres. The functional properties of this tract and its role in degenerative dementia, such as Alzheimer's disease (AD), still need to be fully clarified. The aim of this study was to explore the microstructural integrity of the FAT in patients with AD and its potential relationship with cognitive functioning. Twenty-three patients with AD and 25 healthy subjects (HS) were enrolled. All subjects underwent cognitive and MRI examination. MRI, including diffusion sequences, was used for probabilistic tractography analysis. We reconstructed individual FATs bilaterally and assessed their microstructural integrity using fractional anisotropy (FA), computed as both mean tract value and voxel-wise using SPM-8. Mean FA values were then used to test for correlations with cognitive measures. Mean tract FA and voxel-wise analyses revealed that patients with AD, compared to HS, had decreased FA in the FAT bilaterally. In addition, positive associations were found between FA in the FATs and patients' performance at tests for constructional praxis and visuospatial logical reasoning. The present results reveal a bilateral damage of FAT in AD patients. The association between FATs' microscopic abnormalities and constructive abilities fits well with the knowledge of a functional involvement of SMA and pre-SMA in movement sequences when executing constructive praxis tasks. The FAT is an associative bundle critically involved in the network sub-serving constructional praxis in patients with AD.

Deficit in Central Auditory Processing as a Biomarker of Pre-Clinical Alzheimer's Disease. - Tuwaig, Miranda; Savard, Mélissa; Jutras, Benoît; Poirier, Judes; Collins, D Louis; Rosa-Neto, Pedro; Fontaine, David; Breitner, John C S (J Alzheimers Dis, 2017)
Prevention of dementia due to Alzheimer's disease (d/AD) requires interventions that slow the disease process prior to symptom onset. To develop such interventions, one needs metrics that assess pre-symptomatic disease progression. Familiar measures of progression include cerebrospinal fluid (CSF) biochemical and imaging analyses, as well as cognitive testing. Changes in the latter can sometimes be difficult to distinguish from effects of "normal" aging. A different approach involves testing of "central auditory processing" (CAP), which enables comprehension of auditory stimuli amidst a distracting background (e.g., conversation in a noisy bar or restaurant). Such comprehension is often impaired in d/AD. Similarly, effortful or diminished auditory comprehension is sometimes reported by cognitively healthy elders, raising the possibility that CAP deficit may be a marker of pre-symptomatic AD. In 187 cognitively and physically healthy members of the aging, AD family history-positive PREVENT-AD cohort, we therefore evaluated whether CAP deficits were associated with known markers of AD neurodegeneration. Such markers included CSF tau concentrations and magnetic resonance imaging volumetric and cortical thickness measures in key AD-related regions. Adjusting for age, sex, education, pure-tone hearing, and APOEɛ4 status, we observed a persistent relationship between CAP scores and CSF tau levels, entorhinal and hippocampal cortex volumes, cortical thickness, and deficits in cognition (Repeatable Battery for Assessment of Neuropsychological Status total score, and several of its index scales). These cross-sectional observations suggest that CAP may serve as a novel metric for pre-symptomatic AD pathogenesis. They are therefore being followed up longitudinally with larger samples.

Detecting At-Risk Alzheimer's Disease Cases. - Fladby, Tormod; Pålhaugen, Lene; Selnes, Per; Waterloo, Knut; Bråthen, Geir; Hessen, Erik; Almdahl, Ina Selseth; Arntzen, Kjell-Arne; Auning, Eirik; Eliassen, Carl Fredrik; Espenes, Ragna; Grambaite, Ramune; et al. (J Alzheimers Dis, 2017)
While APOEɛ4 is the major genetic risk factor for Alzheimer's disease (AD), amyloid dysmetabolism is an initial or early event predicting clinical disease and is an important focus for secondary intervention trials. To improve identification of cases with increased AD risk, we evaluated recruitment procedures using pathological CSF concentrations of Aβ42 (pAβ) and APOEɛ4 as risk markers in a multi-center study in Norway. In total, 490 subjects aged 40-80 y were included after response to advertisements and media coverage or memory clinics referrals. Controls (n = 164) were classified as normal controls without first-degree relatives with dementia (NC), normal controls with first-degree relatives with dementia (NCFD), or controls scoring below norms on cognitive screening. Patients (n = 301) were classified as subjective cognitive decline or mild cognitive impairment. Subjects underwent a clinical and cognitive examination and MRI according to standardized protocols. Core biomarkers in CSF from 411 and APOE genotype from 445 subjects were obtained. Cases (both self-referrals (n = 180) and memory clinics referrals (n = 87)) had increased fractions of pAβ and APOEɛ4 frequency compared to NC. Also, NCFD had higher APOEɛ4 frequencies without increased fraction of pAβ compared to NC, and cases recruited from memory clinics had higher fractions of pAβ and APOEɛ4 frequency than self-referred. This study shows that memory clinic referrals are pAβ enriched, whereas self-referred and NCFD cases more frequently are pAβ negative but at risk (APOEɛ4 positive), suitable for primary intervention.

Development of Nasal Lipid Nanocarriers Containing Curcumin for Brain Targeting. - Vaz, Gustavo Richter; Hädrich, Gabriela; Bidone, Juliana; Rodrigues, Jamile Lima; Falkembach, Mariana Corrêa; Putaux, Jean-Luc; Hort, Mariana Appel; Monserrat, José Maria; Varela Junior, Antônio Sergio; Teixeira, Helder Ferreira; Muccillo-Baisch, Ana Luiza; Horn, Ana Paula; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Curcumin (CUR) has properties that can be useful for the treatment of Alzheimer's disease. Such properties are the inhibition of amyloid-β-protein (Aβ) aggregation, Aβ-induced inflammation, and activities of β-secretase and acetylcholinesterase. However, previous studies have revealed that CUR exhibited low bioavailability and difficulties in reaching the brain. OBJECTIVE: To overcome such drawbacks, this study aims at developing nasal lipid nanocarriers loaded with CUR to effectively target the brain. METHODS: The lipid nanocarriers (NE) were prepared using the hot solvent diffusion associated with the phase inversion temperature methods. Physico-chemical and morphological characterizations and in vitro drug release of the nanocarriers were carried out. The CUR permeation/retention was analyzed in Franz-type diffusion cell using porcine nasal mucosa. Confocal laser scan and histopathological studies were also performed. RESULTS: The results showed that the NE sizes ranged between 18 nm and 44 nm with negative zeta potential. The CUR content ranged from 0.24 to 1.50 mg/mL with an encapsulation efficiency of 99%. The profiles of CUR release indicated a biphasic kinetics. CUR-NE permeation across the porcine nasal mucosa was higher when compared to free CUR. These results have also been validated through an analysis on a confocal microscopy. In addition, no toxicity on the nasal mucosa has been observed in a histopathological analysis. CONCLUSION: These results suggest that it is possible to develop NEs with a high content of CUR and small particle size. Such an encapsulation increases the potential of CUR permeation across the porcine nasal mucosa.

Diabetes and Alzheimer's Disease: Can Tea Phytochemicals Play a Role in Prevention? - Fernando, Warnakulasuriya M A D B; Somaratne, Geeshani; Goozee, Kathryn G; Williams, Shehan; Singh, Harjinder; Martins, Ralph N (J Alzheimers Dis, 2017)
Dementia and diabetes mellitus are prevalent disorders in the elderly population. While recognized as two distinct diseases, diabetes has more recently recognized as a significant contributor to risk for developing dementia, and some studies make reference to type 3 diabetes, a condition resulting from insulin resistance in the brain. Alzheimer's disease, the most common form of dementia, and diabetes, interestingly, share underlying pathological processes, commonality in risk factors, and, importantly, pathways for intervention. Tea has been suggested to possess potent antioxidant properties. It is rich in phytochemicals including, flavonoids, tannins, caffeine, polyphenols, boheic acid, theophylline, theobromine, anthocyanins, gallic acid, and finally epigallocatechin-3-gallate, which is considered to be the most potent active ingredient. Flavonoid phytochemicals, known as catechins, within tea offer potential benefits for reducing the risk of diabetes and Alzheimer's disease by targeting common risk factors, including obesity, hyperlipidemia, hypertension, cardiovascular disease, and stroke. Studies also show that catechins may prevent the formation of amyloid-β plaques and enhance cognitive functions, and thus may be useful in treating patients who have Alzheimer's disease or dementia. Furthermore, other phytochemicals found within tea offer important antioxidant properties along with innate properties capable of modulating intracellular neuronal signal transduction pathways and mitochondrial function.

Diabetes is Not Associated with Alzheimer's Disease Neuropathology. - Dos Santos Matioli, Maria Niures Pimentel; Suemoto, Claudia Kimie; Rodriguez, Roberta Diehl; Farias, Daniela Souza; da Silva, Magnólia Moreira; Leite, Renata Elaine Paraizo; Ferretti-Rebustini, Renata Eloah Lucena; Farfel, José Marcelo; Pasqualucci, Carlos Augusto; Jacob Filho, Wilson; Arvanitakis, Zoe; Naslavsky, Michel Satya; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Previous evidence linking diabetes to Alzheimer's disease (AD) neuropathology is mixed and scant data are available from low- and middle-income countries. OBJECTIVE: To investigate the association between diabetes and AD neuropathology in a large autopsy study of older Brazilian adults. METHODS: In this cross-sectional study, diabetes was defined by diagnosis during life or use of antidiabetic medication. A standardized neuropathological examination was performed using immunohistochemistry. The associations of diabetes with Consortium to Establish and Registry for Alzheimer Disease (CERAD) scores for neuritic plaques and Braak-Braak (BB) scores for neurofibrillary tangles were investigated using multivariable ordinal logistic regression. We investigated effect modification of education, race, and APOE on these associations. RESULTS: Among 1,037 subjects (mean age = 74.4±11.5 y; mean education = 4.0±3.7 y; 48% male, 61% White), diabetes was present in 279 subjects. Diabetes was not associated with BB (OR = 1.12, 95% CI = 0.81-1.54, p = 0.48) or with CERAD (OR = 0.97, 95% CI = 0.68-1.38, p = 0.86) scores on analyses adjusted for sociodemographic and clinical variables. We observed effect modification by the APOE allele ɛ4 on the association between diabetes mellitus and BB scores. CONCLUSION: No evidence of an association between diabetes and AD neuropathology was found in a large sample of Brazilians; however, certain subgroups, such as APOE allele ɛ4 carriers, had higher odds of accumulation of neurofibrillary tangles.

Diagnostic and Prognostic Value of the Combination of Two Measures of Verbal Memory in Mild Cognitive Impairment due to Alzheimer's Disease. - Sala, Isabel; Illán-Gala, Ignacio; Alcolea, Daniel; Sánchez-Saudinós, Ma Belén; Salgado, Sergio Andrés; Morenas-Rodriguez, Estrella; Subirana, Andrea; Videla, Laura; Clarimón, Jordi; Carmona-Iragui, María; Ribosa-Nogué, Roser; Blesa, Rafael; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory impairment is the core feature of typical Alzheimer's disease. OBJECTIVE: To evaluate the performance of two commonly used verbal memory tests to detect mild cognitive impairment due to Alzheimer's disease (MCI-AD) and to predict progression to Alzheimer's disease dementia (AD-d). METHODS: Prospective study of MCI patients in a tertiary memory disorder unit. Patients underwent an extensive neuropsychological battery including two tests of declarative verbal memory: The Free and Cued Selective Reminding Test (FCSRT) and the word list learning task from the Consortium to Establish a Registry for Alzheimer's disease (CERAD-WL). Cerebrospinal fluid (CSF) was obtained from all patients and MCI-AD was defined by means of the t-Tau/Aβ1-42 ratio. Logistic regression analyses tested whether the combination of FCSRT and CERAD-WL measures significantly improved the prediction of MCI-AD. Progression to AD-d was analyzed in a Cox regression model. RESULTS: A total of 202 MCI patients with a mean follow-up of 34.2±24.2 months were included and 98 (48.5%) met the criteria for MCI-AD. The combination of FCSRT and CERAD-WL measures improved MCI-AD classification accuracy based on CSF biomarkers. Both tests yielded similar global predictive values (59.9-65.3% and 59.4-62.8% for FCSRT and CERAD-WL, respectively). MCI-AD patients with deficits in both FCSRT and CERAD-WL had a faster progression to AD-d than patients with deficits in only one test. CONCLUSIONS: The combination of FCSRT and CERAD-WL improves the classification of MCI-AD and defines different prognostic profiles. These findings have important implications for clinical practice and the design of clinical trials.

Diaschisis-Like Association of Hippocampal Atrophy and Posterior Cingulate Cortex Hypometabolism in Cognitively Normal Elderly Depends on Impaired Integrity of Parahippocampal Cingulum Fibers. - Fischer, Florian U; Wolf, Dominik; Fellgiebel, Andreas (J Alzheimers Dis, 2017)
Hippocampal atrophy and hypometabolism of the posterior cingulate cortex (PCC), early markers of Alzheimer's disease (AD), have been shown to be associated in late mild cognitive impairment and early AD via atrophy of connecting cingulum fibers. Recently, a direct association of hippocampal atrophy and PCC hypometabolism has been shown in cognitively normal elderly. We aimed to investigate if this association might be modulated by partly non-hippocampogenic alterations of parahippocampal cingulum (PHC) integrity. 45 cognitively healthy elderly aged 59 to 89 years were included from the Alzheimer's Disease Neuroimaging Initiative. Hippocampal volumes and PCC glucose metabolism were measured using MRI and FDG-PET. PHC fibers connecting the hippocampus and the PCC were reconstructed using diffusion weighted MRI and measures of diffusivity were calculated. Using robust linear regression, interaction effects of PHC diffusivity and hippocampal volume on PCC metabolism were calculated. For both hemispheres, significant interaction effects were found for PHC mean diffusivity. Interaction effects were such that the association of hippocampal volume and PCC metabolism was higher in subjects with increased mean diffusivity in PHC fibers. In cognitively normal elderly, compromised integrity of the PHC may increase the risk of PCC hypometabolism due to hippocampal atrophy. Spared PHC fiber integrity may protect against PCC hypometabolism due to hippocampal atrophy.

Differential Regional Distribution of Juxtacortical White Matter Signal Abnormalities in Aging and Alzheimer's Disease. - Lindemer, Emily R; Greve, Douglas N; Fischl, Bruce; Augustinack, Jean C; Salat, David H (J Alzheimers Dis, 2017)
BACKGROUND: White matter signal abnormalities (WMSA) (also known as 'hyperintensities') on MRI are commonly seen in normal aging and increases have been noted in Alzheimer's disease (AD), but whether there is a spatial specificity to these increases is unknown. OBJECTIVE: To discern whether or not there is a spatial pattern of WMSA in the brains of individuals with AD that differs from those who exhibit cognitively healthy aging. METHOD: Structural MRI data from the Alzheimer's Disease Neuroimaging Initiative public database were used to quantify WMSA in 35 regions of interest (ROIs). Regional measures were compared between cognitively healthy older controls (OC; n = 107) and individuals with a clinical diagnosis of AD (n = 127). Regional WMSA volume was also assessed in individuals with mild cognitive impairment (MCI; n = 74) who were 6, 12, and 24 months away from AD conversion. RESULTS: WMSA volume was significantly greater in AD compared to OC in 24 out of 35 ROIs after controlling for age, and nine were significantly higher after normalizing for total WMSA. Regions with greater WMSA volume in AD included rostral frontal, inferior temporal, and inferior parietal WM. In MCI, frontal and temporal regions demonstrated significantly greater WMSA volume with decreasing time-to-AD-conversion. DISCUSSION: Individuals with AD have greater regional volume of WMSA compared to OC regardless of age or total WMSA volume. Accumulation of regional WMSA is linked to time to AD conversion in individuals with MCI. These findings indicate WMSA is an important pathological component of AD development.

Disinhibition in Alzheimer's Disease is Associated with Reduced Right Frontal Pole Cortical Thickness. - Finger, Elizabeth; Zhang, Jing; Dickerson, Bradford; Bureau, Yves; Masellis, Mario (J Alzheimers Dis, 2017)
Neuropsychiatric symptoms in Alzheimer's disease are among the most disabling and difficult aspects for caregivers and treating health professionals to manage. Despite the high prevalence of these behaviors, little is known about the factors which lead some patients to develop florid behavioral symptoms while others may progress to severe dementia without such phenomenon. We examined whether regional brain volumes as measured by cortical thickness would predict the presence or absence of disinhibition in patients with Alzheimer's disease. Using data from the ADNI, we identified 758 patients with caregiver ratings on the Neuropsychiatric Inventory and a volumetric MRI scan with cortical thickness measurements completed in FreeSurfer by the UCSF core. Of these, 177 patients were found to have disinhibition. Logistic regression models demonstrated that reduced cortical thickness in the right frontal pole was associated with the presence of disinhibition even when controlling for age, disease severity, total intracranial volume, gender, and APOE genotype. The results are considered in the context of leading models of the functions of frontopolar cortex.

Dissociable Effects of Aging and Mild Cognitive Impairment on Bottom-Up Audiovisual Integration. - Festa, Elena K; Katz, Andrew P; Ott, Brian R; Tremont, Geoffrey; Heindel, William C (J Alzheimers Dis, 2017)
Effective audiovisual sensory integration involves dynamic changes in functional connectivity between superior temporal sulcus and primary sensory areas. This study examined whether disrupted connectivity in early Alzheimer's disease (AD) produces impaired audiovisual integration under conditions requiring greater corticocortical interactions. Audiovisual speech integration was examined in healthy young adult controls (YC), healthy elderly controls (EC), and patients with amnestic mild cognitive impairment (MCI) using McGurk-type stimuli (providing either congruent or incongruent audiovisual speech information) under conditions differing in the strength of bottom-up support and the degree of top-down lexical asymmetry. All groups accurately identified auditory speech under congruent audiovisual conditions, and displayed high levels of visual bias under strong bottom-up incongruent conditions. Under weak bottom-up incongruent conditions, however, EC and amnestic MCI groups displayed opposite patterns of performance, with enhanced visual bias in the EC group and reduced visual bias in the MCI group relative to the YC group. Moreover, there was no overlap between the EC and MCI groups in individual visual bias scores reflecting the change in audiovisual integration from the strong to the weak stimulus conditions. Top-down lexicality influences on visual biasing were observed only in the MCI patients under weaker bottom-up conditions. Results support a deficit in bottom-up audiovisual integration in early AD attributable to disruptions in corticocortical connectivity. Given that this deficit is not simply an exacerbation of changes associated with healthy aging, tests of audiovisual speech integration may serve as sensitive and specific markers of the earliest cognitive change associated with AD.

Early Detection of Learning Difficulties when Confronted with Novel Information in Preclinical Alzheimer's Disease Stage 1. - Tort-Merino, Adrià; Valech, Natalia; Peñaloza, Claudia; Grönholm-Nyman, Petra; León, María; Olives, Jaume; Estanga, Ainara; Ecay-Torres, Mirian; Fortea, Juan; Martínez-Lage, Pablo; Molinuevo, José L; Laine, Matti; et al. (J Alzheimers Dis, 2017)
We employed a highly demanding experimental associative learning test (the AFE-T) to explore memory functioning in Preclinical Alzheimer's Disease stage 1 (PreAD-1) and stage 2 (PreAD-2). The task consisted in the learning of unknown object/name pairs and our comprehensive setup allowed the analysis of learning curves, immediate recall, long-term forgetting rates at one week, three months, and six months, and relearning curves. Forty-nine cognitively healthy subjects were included and classified according to the presence or absence of abnormal CSF biomarkers (Control, n = 31; PreAD-1, n = 14; PreAD-2, n = 4). Control and PreAD-1 performances on the experimental test were compared by controlling for age and education. These analyses showed clear learning difficulties in PreAD-1 subjects (F = 6.98; p = 0.01). Between-group differences in long-term forgetting rates were less notable, reaching statistical significance only for the three-month cued forgetting rate (F = 4.83; p = 0.03). Similarly, relearning sessions showed only statistical trends between the groups (F = 3.22; p = 0.08). In the whole sample, significant correlations between CSF Aβ42/tau ratio and the AFE-T were found, both in the total learning score (r = 0.52; p < 0.001) and in the three-month cued forgetting rate (r = -0.38; p < 0.01). Descriptive subanalyses involving PreAD-2 suggested greater learning and recall difficulties in these subjects when compared with the PreAD-1 group. The present results suggest that explicit learning difficulties when binding information could be one of the earliest signs of the future emergence of episodic memory difficulties on the Alzheimer's disease continuum. Our findings indicate that the AFE-T is a sensitive test, capable of detecting subtle memory difficulties in PreAD-1.

Effect of a Comprehensive Intervention on Plasma BDNF in Patients with Alzheimer's Disease. - Balietti, Marta; Giuli, Cinzia; Fattoretti, Patrizia; Fabbietti, Paolo; Papa, Roberta; Postacchini, Demetrio; Conti, Fiorenzo (J Alzheimers Dis, 2017)
A comprehensive intervention (CI) on patients with Alzheimer's disease was assessed by measuring plasmabrain-derived neurotrophic factor (pBDNF) and ADAS-Cog score (ADAS-Cogscore) before, immediately after (FU1), and 6 (FU2) and 24 months (FU3) after the CI. Baseline pBDNF was higher in patients with moderate AD (but not mild AD) than in healthy controls. At FU1, pBDNF and ADAS-Cogscore decreased significantly. At FU2 and FU3, patients' cognitive status worsened and pBDNF further increased versus baseline, suggesting that CI interruption may be a stress event that prevents return to homeostasis. CI exerted positive short-term effects, but more information is needed on long-term consequences.

Effect of APOE Genotype on Amyloid Deposition, Brain Volume, and Memory in Cognitively Normal Older Individuals. - Lim, Yen Ying; Williamson, Robert; Laws, Simon M; Villemagne, Victor L; Bourgeat, Pierrick; Fowler, Christopher; Rainey-Smith, Stephanie; Salvado, Olivier; Martins, Ralph N; Rowe, Christopher C; Masters, Colin L; Maruff, Paul (J Alzheimers Dis, 2017)
BACKGROUND: The association between the apolipoprotein E (APOE) ɛ4 allele and high risk of developing Alzheimer's disease (AD) dementia before the age of 80 has been recognized for over 30 years. However, the timing and mode of action of APOE is not understood, nor has there been a detailed analysis of the effect of APOE genotype on memory, hippocampal volume, and amyloid-β (Aβ) levels in cognitively normal adults. OBJECTIVE: Examine the effect of APOE allelic genotype on the relationship between Aβ levels, hippocampal volume, and memory in cognitively normal adults. METHODS: This is a cross-sectional study of 989 cognitively normal older adults enrolled in the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, all of whom underwent APOE genotyping and memory assessment. A subset of this group underwent PET neuroimaging for Aβ (n = 585) and MRI for hippocampal volume (n = 303). RESULTS: APOEɛ4 homozygotes (ɛ4/ɛ4) showed significantly worse episodic memory and higher Aβ levels than ɛ4 heterozygotes. The relationship between increasing Aβ levels and worse episodic memory was significant for ɛ3 homozygotes (ɛ3/ɛ3), ɛ4 heterozygotes, and strongest for ɛ4 homozygotes. There were no differences in hippocampal volume between APOE groups; the relationship between smaller hippocampal volume and worse episodic memory was significant only for ɛ4 homozygotes. CONCLUSION: APOE acts in a co-dominant fashion on Aβ levels, episodic memory, and hippocampal volume in cognitively normal older adults. APOEɛ4 is central to the events that lead to AD in cognitively normal older adults, likely through a quantitative role in the disruption of Aβ clearance.

Effect of Spinal Manometers on Cerebrospinal Fluid Amyloid-β Concentration. - Toombs, Jamie; Foiani, Martha S; Paterson, Ross W; Heslegrave, Amanda; Wray, Selina; Schott, Jonathan M; Fox, Nick C; Lunn, Michael P; Blennow, Kaj; Zetterberg, Henrik (J Alzheimers Dis, 2017)
The effect of spinal manometers on cerebrospinal fluid (CSF) amyloid-β (Aβ) concentration was investigated. Pooled human CSF samples were divided in two, one half passed through a manometer into a collection tube, the other transferred directly to a collection tube. CSF was analyzed for Aβ38/40/42 using an electrochemiluminescence immunoassay. Relative to control, use of a manometer decreased Aβ38/40/42 concentration by 5.6% (±1.5SE), 4.4% (±1.7SE), and 4.3% (±2.4SE), respectively. The ratios of Aβ42 :40, Aβ42 :38, and Aβ40 :38 were not affected by manometer treatment. Factors which artificially lower CSF Aβ concentrations are relevant to clinical diagnosis for AD and study design.

The Effect of the Association between Donepezil and Choline Alphoscerate on Behavioral Disturbances in Alzheimer's Disease: Interim Results of the ASCOMALVA Trial. - Carotenuto, Anna; Rea, Raffaele; Traini, Enea; Fasanaro, Angiola Maria; Ricci, Giovanna; Manzo, Valentino; Amenta, Francesco (J Alzheimers Dis, 2017)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) are a group of psychological reactions, psychiatric symptoms, and behaviors commonly found in Alzheimer's disease (AD). Four clusters of BPSD have been described: mood disorders (depression, anxiety, and apathy), psychotic symptoms (delusions and hallucinations), aberrant motor behaviors (pacing, wandering, and other purposeless behaviors), and inappropriate behaviors (agitation, disinhibition, and euphoria). Most of them are attributed to acetylcholine deficiency. OBJECTIVE: To evaluate if a higher amount of acetylcholine obtained by associating donepezil and choline alphoscerate might have a favorable effect on BPSD. METHODS: BPSD were measured at baseline and after 24 months in 113 mild/moderate AD patients, included in the double-blind randomized trial ASCOMALVA, by the Neuropsychiatric Inventory (NPI). Two matched groups were compared: group A treated with donepezil (10 mg/day) plus choline alphoscerate (1200 mg/day), and group B treated with donepezil (10 mg/day) plus placebo. RESULTS: Data of NPI revealed a significant decrease of BPSD severity and distress of the caregiver in patients of group A compared with group B. Mood disorders (depression, anxiety and apathy) were significantly decreased in subjects treated with donepezil and choline alphoscerate, while their severity and frequency was increased in the other group. CONCLUSIONS: Patients treated with donepezil plus choline alphoscerate showed a lower level of behavioral disturbances than subjects treated with donepezil only, suggesting that the association can have beneficial effects.

Effects of Multiple Genetic Loci on Age at Onset in Frontotemporal Dementia. - Ferrari, Raffaele; Grassi, Mario; Graziano, Francesca; Palluzzi, Fernando; Archetti, Silvana; Bonomi, Elisa; Bruni, Amalia C; Maletta, Raffaele G; Bernardi, Livia; Cupidi, Chiara; Colao, Rosanna; Rainero, Innocenzo; et al. (J Alzheimers Dis, 2017)
In frontotemporal dementia (FTD), age at disease onset (AAO) is unpredictable in both early and late-onset cases; AAO variability is found even in autosomal dominant FTD. The present study was aimed at identifying genetic modifiers modulating AAO in a large cohort of Italian FTD patients. We conducted an association analysis on 411 FTD patients, belonging to 7 Italian Centers, and for whom AAO was available. Population structure was evaluated by principal component analysis to infer continuous axes of genetic variation, and single linear regression models were applied. A genetic score (GS) was calculated on the basis of suggestive single nucleotide polymorphisms (SNPs) found by association analyses. GS showed genome-wide significant slope decrease by -3.86 (95% CI: -4.64 to -3.07, p < 2×10-16) per standard deviation of the GS for 6 SNPs mapping to genes involved in neuronal development and signaling, axonal myelinization, and glutamatergic/GABA neurotransmission. An increase of the GS was associated with a decrease of the AAO. Our data indicate that there is indeed a genetic component that underpins and modulates up to 14.5% of variability of AAO in Italian FTD. Future studies on genetic modifiers in FTD are warranted.

Effects of Regular and Long-Acting Insulin on Cognition and Alzheimer's Disease Biomarkers: A Pilot Clinical Trial. - Craft, Suzanne; Claxton, Amy; Baker, Laura D; Hanson, Angela J; Cholerton, Brenna; Trittschuh, Emily H; Dahl, Deborah; Caulder, Erin; Neth, Bryan; Montine, Thomas J; Jung, Youngkyoo; Maldjian, Joseph; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Long acting insulin detemir administered intranasally for three weeks enhanced memory for adults with Alzheimer's disease dementia (AD) or amnestic mild cognitive impairment (MCI). The investigation of longer-term administration is necessary to determine whether benefits persist, whether they are similar to benefits provided by regular insulin, and whether either form of insulin therapy affects AD biomarkers. OBJECTIVE: The present study aimed to determine whether four months of treatment with intranasal insulin detemir or regular insulin improves cognition, daily functioning, and AD biomarkers for adults with MCI or AD. METHODS: This randomized, double-blind, placebo-controlled trial included an intent-to-treat sample consisting of 36 adults diagnosed with MCI or mild to moderate AD. Participants received placebo (n = 12), 40 IU of insulin detemir (n = 12), or 40 IU of regular insulin (n = 12) daily for four months, administered with a nasal delivery device. A cognitive battery was administered at baseline and after two and four months of treatment. MRI was administered for all participants and lumbar puncture for a subset (n = 20) at baseline and four months. The primary outcome was change from baseline to four months on a memory composite (sum of Z scores for delayed list and story recall). Secondary outcomes included: global cognition (Alzheimer's Disease Assessment Scale-Cognition), daily functioning (Dementia Severity Rating Scale), MRI volume changes in AD-related regions of interest, and cerebrospinal fluid AD markers. RESULTS: The regular insulin treated group had better memory after two and four months compared with placebo (p < 0.03). No significant effects were observed for the detemir-assigned group compared with the placebo group, or for daily functioning for either group. Regular insulin treatment was associated with preserved volume on MRI. Regular insulin treatment was also associated with reduction in the tau-P181/Aβ42 ratio. CONCLUSION: Future research is warranted to examine the mechanistic basis of treatment differences, and to further assess the efficacy and safety of intranasal insulin.

Effects of Risperidone and Galantamine Treatment on Alzheimer's Disease Biomarker Levels in Cerebrospinal Fluid. - Bloniecki, Victor; Aarsland, Dag; Blennow, Kaj; Cummings, Jeffrey; Falahati, Farshad; Winblad, Bengt; Freund-Levi, Yvonne (J Alzheimers Dis, 2017)
BACKGROUND: Treatment for neuropsychiatric symptoms (NPS) in dementia is insufficient. Antipsychotics and acetylcholinesterase inhibitors are used generating symptomatic improvements in behavior and cognition, but few studies have investigated their effect on Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF). OBJECTIVE: This is a secondary analysis based on an earlier clinical trial comparing the treatment effects on NPS. The aim of this study was to examine whether treatment with risperidone and galantamine affect levels of the biomarkers T-Tau, P-Tau, Aβ1-42, and Aβ42/40-ratio in CSF. The secondary aim was to test if baseline levels of these biomarkers are associated with the clinical course of NPS. METHODS: 83 patients (mean + SD 77.9.6±7.7 years) with dementia and NPS were randomized to galantamine (n = 44) or risperidone (n = 39) treatment. CSF samples were collected at baseline and after 12 weeks. RESULTS: Changes in levels of biomarkers between the two treatment groups did not differ significantly. Low baseline levels of Aβ1 - 42 was significantly associated with reduction of irritability at follow up. Low baseline levels of Aβ1-42, Aβ42/40, and P-Tau were significant correlates of reduction in appetite and eating disorders. CSF Aβ1-42 levels in patients treated with risperidone were significantly decreased at follow up, showing an 8% (40 pg/mL) reduction as compared with baseline (p = 0.03). CONCLUSIONS: Our results suggest that risperidone may affect the CSF profile of AD biomarkers indicating more amyloid pathology. Treatment with galantamine did not affect the CSF biomarkers in any direction. The AD CSF biomarkers displayed correlations with specific NPS suggesting potential research questions to be pursued.

Effects of Short-Term Exercise Interventions on Behavioral and Psychological Symptoms in Patients with Dementia: A Systematic Review. - Fleiner, Tim; Leucht, Stefan; Förstl, Hans; Zijlstra, Wiebren; Haussermann, Peter (J Alzheimers Dis, 2017)
Observational and interventional studies indicate a direct link between the patients' physical activity and the extent of behavioral and psychological symptoms of dementia (BPSD). At present, there are no evidence-based recommendations for physical exercise in the acute dementia care settings. Hence, this systematic review investigates the effects of short-term exercise trials on BPSD. Trials with a length up to three months investigating the effects of structured exercise interventions on BPSD in acute dementia care settings were included. Five trials, referring to a total of N = 206 patients, met the inclusion criteria. The trial durations ranged from three up to twelve weeks. All trials conducted three sessions per week of 30 to 45 minutes. Three trials reported significant reductions of BPSD and differences in comparison to the pre-test and control groups. Out of the three trials investigating the effects of exercise interventions on depressive symptoms, one reported significant reduction and two reported no differences in pre-post analysis. Exercise represents a potentially worthwhile approach for the treatment of patients suffering from BPSD. Given the scarcity of available studies, more randomized controlled short-term exercise trials in acute dementia care settings are needed to define appropriate exercise recommendations for clinicians treating these patients.

Efficacy and Safety of Plasma Exchange with 5% Albumin to Modify Cerebrospinal Fluid and Plasma Amyloid-β Concentrations and Cognition Outcomes in Alzheimer's Disease Patients: A Multicenter, Randomized, Controlled Clinical Trial. - Boada, Merce; Anaya, Fernando; Ortiz, Pilar; Olazarán, Javier; Shua-Haim, Joshua R; Obisesan, Thomas O; Hernandez, Isabel; Muñoz, Joan; Buendia, Mar; Alegret, Montserrat; Lafuente, Asunción; Tárraga, Lluís; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Studies conducted in animal models and humans suggest the presence of a dynamic equilibrium of amyloid-β (Aβ) peptide between cerebrospinal fluid (CSF) and plasma compartments. OBJECTIVE: To determine whether plasma exchange (PE) with albumin replacement was able to modify Aβ concentrations in CSF and plasma as well as to improve cognition in patients with mild-moderate Alzheimer's disease (AD). METHODS: In a multicenter, randomized, patient- and rater-blind, controlled, parallel-group, phase II study, 42 AD patients were assigned (1 : 1) to PE treatment or control (sham) groups. Treated patients received a maximum of 18 PE with 5% albumin (Albutein®, Grifols) with three different schedules: two PE/weekly (three weeks), one PE/weekly (six weeks), and one PE/bi- weekly (12 weeks), plus a six-month follow-up period. Plasma and CSF Aβ1-40 and Aβ1-42 levels, as well as cognitive, functional, and behavioral measures were determined. RESULTS: CSF Aβ1-42 levels after the last PE compared to baseline were marginally higher in PE-treated group versus controls (adjusted means of variation: 75.3 versus -45.5 pg/mL; 95% CI: -19.8, 170.5 versus 135.1, 44.2; p = 0.072). Plasma Aβ1-42 levels were lower in the PE-treated group after each treatment period (p < 0.05). Plasma Aβ1-40 levels showed a saw-tooth pattern variation associated with PE. PE-treated patients scored better in the Boston Naming Test and Semantic Verbal Fluency (p < 0.05) throughout the study. Neuropsychiatric Inventory scores were higher in controls during the PE phase (p < 0.05). CONCLUSION: PE with human albumin modified CSF and plasma Aβ1-42 levels. Patients treated with PE showed improvement in memory and language functions, which persisted after PE was discontinued.

The Efficacy of Emotion Recognition Rehabilitation for People with Alzheimer's Disease. - García-Casal, J Antonio; Goñi-Imizcoz, Miguel; Perea-Bartolomé, M Victoria; Soto-Pérez, Felipe; Smith, Sarah Jane; Calvo-Simal, Sara; Franco-Martín, Manuel (J Alzheimers Dis, 2017)
BACKGROUND: The ability to recognize emotional expression is essential for social interactions, adapting to the environment, and quality of life. Emotion recognition is impaired in people with Alzheimer's disease (AD), thus rehabilitation of these skills has the potential to elicit significant benefits. OBJECTIVE: This study sought to establish whether emotion recognition capacity could be rehabilitated in people with AD. METHODS: Thirty-six participants with AD were assigned to one of three conditions: an experimental group (EG) that received 20 sessions of rehabilitation of emotion recognition and 20 sessions of cognitive stimulation therapy (CST), a control group (CG) that received 40 sessions of CST, and a treatment as usual group (TAU). RESULTS: A positive treatment effect favoring the EG was found; participants were better able to correctly identify emotions (p = 0.021), made fewer errors of commission (p = 0.002), had greater precision of processing (p = 0.021), and faster processing speed (p = 0.001). Specifically, the EG were better able to identify sadness (p = 0.016), disgust (p = 0.005), and the neutral expression (p = 0.014), with quicker processing speed for disgust (p = 0.002). These gains were maintained at one month follow-up with the exception of processing speed for surprise, which improved. CONCLUSION: Capacity to recognize facial expressions of emotions can be improved through specific rehabilitation in people with AD, and gains are still present at a one month follow up. These findings have implications for the design of rehabilitation techniques for people with AD that may lead to improved quality of life and social interactions for this population.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Therapy; Depression; Emotions; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Outcome Assessment (Health Care); Recognition (Psychology); Single-Blind Method; Statistics, Nonparametric

Episodic Memory Dysfunction in Behavioral Variant Frontotemporal Dementia: A Clinical And FDG-PET Study. - Fernández-Matarrubia, Marta; Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Moreno-Ramos, Teresa; Valles-Salgado, María; Carreras, José Luis; Matías-Guiu, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: Episodic memory disturbance is still considered as an exclusion criterion for behavioral variant frontotemporal dementia (bvFTD), but growing evidence suggests that memory can be impaired. OBJECTIVE: Our main purposes were to assess episodic memory in a group of bvFTD patients comparatively with Alzheimer's disease (AD) patients, and analyze the relationship between episodic memory and brain metabolism measured using positron emission tomography imaging with 18F-fluorodeoxyglucose (FDG-PET). METHODS: Twenty-six bvFTD, 29 AD, and 24 healthy controls were included. Episodic memory was assessed by the Free and Cued Selective Reminding Test (FCSRT), which controls for effective encoding and measures memory consolidation processing. All participants underwent FDG-PET brain scans to provide data for voxel-based brain mapping analysis. RESULTS: Half of bvFTD patients had a deficit of total, free delayed, and total free delayed recall as severe as AD patients (amnestic-FTD). The other half had FCSRT scores similar to controls (non-amnestic-FTD). Imaging analyses revealed that amnestic-FTD showed bilateral lower metabolism than non-amnestic-FTD in anterior parahippocampal and inferior temporal gyri. Additionally, FCSRT total and total delayed scores were inversely correlated with parahippocampal metabolism in both bvFTD and AD. Besides, bvFTD showed an inverse association among FCSRT and inferior temporal metabolism. CONCLUSIONS: Our findings support that bvFTD could present a genuine amnesia affecting storage and consolidation abilities, which involves structures implicated in the Papez circuit, as occurs in AD, and also inferior temporal regions. These results contribute to understanding the mechanisms underpinning memory dysfunction in bvFTD, and may be relevant to further revisions of the current diagnostic criteria.

Evaluation of a DNA Aβ42 Vaccine in Aged NZW Rabbits: Antibody Kinetics and Immune Profile after Intradermal Immunization with Full-Length DNA Aβ42 Trimer. - Lambracht-Washington, Doris; Fu, Min; Wight-Carter, Mary; Riegel, Matthew; Rosenberg, Roger N (J Alzheimers Dis, 2017)
A pathological hallmark of Alzheimer's disease (AD) are amyloid plaques in the brain consisting of aggregated amyloid-β 42 peptide (Aβ42) derived from cellular amyloid-β protein precursor (AβPP). Based on successful experiments in mouse AD models, active immunization with Aβ42 peptide and passive immunizations with anti-Aβ42 antibodies were started in clinical trials. Active Aβ42 peptide immunization in humans had led to an inflammatory autoimmune response, and the trial was stopped. Passive immunizations had shown some effects in slowing AD pathology. Active DNA Aβ42 immunizations administered with the gene gun into the skin elicits a different immune response and is non-inflammatory. While in rodents, good responses had been found for this type of immunization, positive results in larger mammals are missing. We present here results from sixteen New Zealand White Rabbits, which underwent intradermal DNA Aβ42 immunization via gene gun. The humoral immune response was analyzed from blood throughout the study, and cellular immune responses were determined from spleens at the end of the study. A good anti-Aβ antibody response was found in the rabbit model. The T cell response after re-stimulation in cell culture showed no IFNγ producing cells when ELISPOT assays were analyzed from PBMC, but low numbers of IFNγ and IL-17 producing cells were found in ELISPOTS from spleens (both 5 immunizations). Brains from immunized rabbits showed no signs of encephalitis. Based on these results, DNA Aβ42 immunization is highly likely to be safe and effective to test in a possible clinical AD prevention trial in patients.

Face-Name Associative Recognition Deficits in Subjective Cognitive Decline and Mild Cognitive Impairment. - Polcher, Alexandra; Frommann, Ingo; Koppara, Alexander; Wolfsgruber, Steffen; Jessen, Frank; Wagner, Michael (J Alzheimers Dis, 2017)
BACKGROUND: There is a need for more sensitive neuropsychological tests to detect subtle cognitive deficits emerging in the preclinical stage of Alzheimer's disease (AD). Associative memory is a cognitive function supported by the hippocampus and affected early in the process of AD. OBJECTIVE: We developed a short computerized face-name associative recognition test (FNART) and tested whether it would detect memory impairment in memory clinic patients with mild cognitive impairment (MCI) and subjective cognitive decline (SCD). METHODS: We recruited 61 elderly patients with either SCD (n = 32) or MCI (n = 29) and 28 healthy controls (HC) and compared performance on FNART, self-reported cognitive deterioration in different domains (ECog-39), and, in a reduced sample (n = 46), performance on the visual Paired Associates Learning of the CANTAB battery. RESULTS: A significant effect of group on FNART test performance in the total sample was found (p < 0.001). Planned contrasts indicated a significantly lower associative memory performance in the SCD (p = 0.001, d = 0.82) and MCI group (p < 0.001, d = 1.54), as compared to HCs, respectively. The CANTAB-PAL discriminated only between HC and MCI, possibly because of reduced statistical power. Adjusted for depression, performance on FNART was significantly related to ECog-39 Memory in SCD patients (p = 0.024) but not in MCI patients. CONCLUSIONS: Associative memory is substantially impaired in memory clinic patients with SCD and correlates specifically with memory complaints at this putative preclinical stage of AD. Further studies will need to examine the predictive validity of the FNART in SCD patients with regard to longitudinal (i.e., conversion to MCI/AD) and biomarker outcomes.

Feasibility of Lumbar Puncture in the Study of Cerebrospinal Fluid Biomarkers for Alzheimer's Disease in Subjects with Down Syndrome. - Carmona-Iragui, María; Santos, Telma; Videla, Sebastián; Fernández, Susana; Benejam, Bessy; Videla, Laura; Alcolea, Daniel; Blennow, Kaj; Blesa, Rafael; Lleo, Alberto; Fortea, Juan (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) is the main medical problem in older adults with Down syndrome (DS). Studies of cerebrospinal fluid (CSF) AD biomarkers are limited and the feasibility of lumbar puncture (LP) is controversial in this population. OBJECTIVE: To analyze the frequency of complications after a LP in DS. METHODS: We collected data from 80 adults with DS that underwent a LP within the Down Alzheimer Barcelona Neuroimaging Initiative. Demographics, cognitive status, headache history, and presence of complications after the LP were recorded in every subject. In 53 of them (active group), this information was collected following a semi-structured and validated protocol that actively looks for complications. Other variables related to the LP procedure were also recorded. A telephone interview to the caregiver was performed 5-7 days after the procedure to ask about complications. Data from 27 subjects (clinical practice group), from whom the presence of complications was obtained in a medical follow-up visit within the three months after the LP, were also included. RESULTS: There were no adverse events in 90% of our participants. The most frequent complication was headache (6.25%); only one subject reported a typical post-lumbar puncture headache with moderate severity that required analgesic treatment. Dizziness (3.75%) and back pain (1.25%) were also reported. All the participants that reported complications belonged to the active group. CONCLUSION: LP can be safely performed to study CSF biomarkers in DS. The reported complications are qualitatively similar to the general population, but are less frequently reported, even when actively searched for.

Framingham Risk Score and the Risk of Progression from Mild Cognitive Impairment to Dementia. - Viticchi, Giovanna; Falsetti, Lorenzo; Buratti, Laura; Sajeva, Giulia; Luzzi, Simona; Bartolini, Marco; Provinciali, Leandro; Silvestrini, Mauro (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) often represents the clinical manifestation of cognitive deterioration preceding Alzheimer's disease (AD). Currently, there are no reliable approaches for an objective evaluation of the risk of developing AD in MCI patients. OBJECTIVE: The aim of this study was to verify whether the Framingham cardiovascular risk profile (FCRP) could be useful to identify patients at the highest risk of conversion from MCI to AD. METHODS: Patients with amnestic MCI (aMCI) were carefully investigated to assess their vascular risk profile. They were also submitted to a comprehensive neuropsychological evaluation. The FCRP was calculated for each patient and the apolipoprotein E (ApoE) genotype was determined from peripheral blood cells. The main outcome was defined as a conversion to AD within 24 months after inclusion. RESULTS: 385 consecutive aMCI subjects were included. Age, FCRP, and vascular age showed a fairly predictive value on conversion to AD. Selecting the subpopulation of ApoE ɛ4 carriers, we observed that FCRP had an increased performance in predicting the conversion. The rate of conversion increased from 12.5% in the FCRP low-risk group to 43.2% in the high-risk group (p < 0.0001). ApoE ɛ4 carriers had a 3.7-times increased probability of conversion with respect to the other subjects (p < 0.0001). CONCLUSIONS: FCRP assessment could be considered a reliable approach to predict conversion to AD in aMCI subjects. The presence of ApoE ɛ4 increases significantly the risk of conversion. These data confirm the narrow relationship between genetic and vascular risk factors in influencing the evolution of cognitive impairment.

Functional Disintegration of the Default Mode Network in Prodromal Alzheimer's Disease. - Dillen, Kim N H; Jacobs, Heidi I L; Kukolja, Juraj; Richter, Nils; von Reutern, Boris; Onur, Özgür A; Langen, Karl-Josef; Fink, Gereon R (J Alzheimers Dis, 2017)
Neurodegenerative brain changes can affect the functional connectivity strength between nodes of the default-mode network (DMN), which may underlie changes in cognitive performance. It remains unclear how the functional connectivity strength of DMN nodes differs from healthy to pathological aging and whether these changes are cognitively relevant. We used resting-state functional magnetic resonance imaging to investigate the functional connectivity strength across five DMN nodes in 25 healthy controls (HC), 28 subjective cognitive decline (SCD) participants, and 25 prodromal Alzheimer's disease (AD) patients. After identifying the ventral medial prefrontal cortex (vmPFC), posterior cingulate cortex (PCC), retrosplenial cortex (RSC), inferior parietal lobule, and the hippocampus we investigated the functional strength between DMN nodes using temporal network modeling. Functional coupling of the vmPFC and PCC in prodromal AD patients was disrupted. This vmPFC-PCC coupling correlated positively with memory performance in prodromal AD. Furthermore, the hippocampus de-coupled from posterior DMN nodes in SCD and prodromal AD patients. There was no coupling between the hippocampus and the anterior DMN. Additional mediation analyses indicated that the RSC enables communication between the hippocampus and DMN regions in HC but none of the other two groups. These results suggest an anterior-posterior disconnection and a hippocampal de-coupling from posterior DMN nodes with disease progression. Hippocampal de-coupling already occurring in SCD may provide valuable information for the development of a functional biomarker.

Generation and Partial Characterization of Rabbit Monoclonal Antibody to Amyloid-β Peptide 1-37 (Aβ37). - Mehta, Pankaj D; Blain, Jean-Francois; Freeman, Emily A; Patrick, Bruce A; Barshatzky, Marc; Hrdlicka, Lori A; Mehta, Sangita P; Frackowiak, Janusz; Mazur-Kolecka, Bozena; Wegiel, Jerzy; Patzke, Holger; Miller, David L (J Alzheimers Dis, 2017)
Secreted soluble amyloid-β 1-37 (Aβ37) peptide is one of the prominent Aβ forms next to Aβ40, and is found in cerebrospinal fluid (CSF) and blood. Recent studies have shown the importance of quantitation of CSF Aβ37 levels in combination with Aβ38, Aβ40, and Aβ42 to support the diagnosis of patients with probable Alzheimer's disease (AD), and the value of antibody to Aβ37 to facilitate drug discovery studies. However, the availability of reliable and specific monoclonal antibody to Aβ37 is very limited. Our aims were: 1) to generate and partially characterize rabbit monoclonal antibody (RabmAb) to Aβ37, and 2) to determine whether the antibody detects changes in Aβ37 levels produced by a γ-secretase modulator (GSM). Our generated RabmAb to Aβ37 was found to be specific to Aβ37, since it did not react with Aβ36, Aβ38, Aβ39, Aβ40, and Aβ42 in an ELISA or immunoblotting. The epitope of the antibody was contained in the seven C-terminal residues of Aβ37. The antibody was sensitive enough to measure CSF and plasma Aβ37 levels in ELISA. Immunohistological studies showed the presence of Aβ37-positive deposits in the brain of AD, and Down syndrome persons diagnosed with AD. Our studies also showed that the antibody detected Aβ37 increases in CSF and brains of rodents following treatment with a GSM. Thus, our antibody can be widely applied to AD research, and in a panel based approach it may have potential to support the diagnosis of probable AD, and in testing the effect of GSMs to target AD.

Genetic Prion Disease Caused by PRNP Q160X Mutation Presenting with an Orbitofrontal Syndrome, Cyclic Diarrhea, and Peripheral Neuropathy. - Fong, Jamie C; Rojas, Julio C; Bang, Jee; Legati, Andrea; Rankin, Katherine P; Forner, Sven; Miller, Zachary A; Karydas, Anna M; Coppola, Giovanni; Grouse, Carrie K; Ralph, Jeffrey; Miller, Bruce L; et al. (J Alzheimers Dis, 2017)
Patients with pathogenic truncating mutations in the prion gene (PRNP) usually present with prolonged disease courses with severe neurofibrillary tangle and cerebral amyloidosis pathology, but more atypical phenotypes also occur, including those with dysautonomia and peripheral neuropathy. We describe the neurological, cognitive, neuroimaging, and electrophysiological features of a 31-year-old man presenting with an orbitofrontal syndrome, gastrointestinal symptoms, and peripheral neuropathy associated with PRNP Q160X nonsense mutation, with symptom onset at age 27. The mutation was also detected in his asymptomatic father and a symptomatic paternal cousin; several members of prior generations died from early onset dementia. This is the first report of a family affected with the nonsense PRNP mutation Q160X displaying clear autosomal dominant disease in multiple family members and reduced penetrance. This case strengthens the evidence suggesting an association between PRNP truncating mutations and prion systemic amyloidosis. PRNP gene testing should be considered in any patient with atypical dementia, especially with early onset and neuropathy, even in the absence of a family history.

Genetic Risk as a Marker of Amyloid-β and Tau Burden in Cerebrospinal Fluid. - Voyle, Nicola; Patel, Hamel; Folarin, Amos; Newhouse, Stephen; Johnston, Caroline; Visser, Pieter Jelle; Dobson, Richard J B; Kiddle, Steven J (J Alzheimers Dis, 2017)
BACKGROUND: The search for a biomarker of Alzheimer's disease (AD) pathology (amyloid-β (Aβ) and tau) is ongoing, with the best markers currently being measurements of Aβ and tau in cerebrospinal fluid (CSF) and via positron emission tomography (PET) scanning. These methods are relatively invasive, costly, and often have high screening failure rates. Consequently, research is aiming to elucidate blood biomarkers of Aβ and tau. OBJECTIVE: This study aims to investigate a case/control polygenic risk score (PGRS) as a marker of tau and investigate blood markers of a combined Aβ and tau outcome for the first time. A sub-study also considers plasma tau as markers of Aβ and tau pathology in CSF. METHODS: We used data from the EDAR*, DESCRIPA**, and Alzheimer's Disease Neuroimaging Initiative (ADNI) cohorts in a logistic regression analysis to investigate blood markers of Aβ and tau in CSF. In particular, we investigated the extent to which a case/control PGRS is predictive of CSF tau, CSF amyloid, and a combined amyloid and tau outcome. The predictive ability of models was compared to that of age, gender, and APOE genotype ('basic model'). RESULTS: In EDAR and DESCRIPA test data, inclusion of a case/control PGRS was no more predictive of Aβ, and a combined Aβ and tau endpoint than the basic models (accuracies of 66.0%, and 73.3% respectively). The tau model saw a small increase in accuracy compared to basic models (59.6%). ADNI 2 test data also showed a slight increase in accuracy for the Aβ model when compared to the basic models (61.4%). CONCLUSION: We see some evidence that a case/control PGRS is marginally more predictive of Aβ and tau pathology than the basic models. The search for predictive factors of Aβ and tau pathologies, above and beyond demographic information, is still ongoing. Better understanding of AD risk alleles, development of more sensitive assays, and studies of larger sample size are three avenues that may provide such factors. However, the clinical utility of possible predictors of brain Aβ and tau pathologies must also be investigated.*'Beta amyloid oligomers in the early diagnosis of AD and as marker for treatment response'**'Development of screening guidelines and criteria for pre-dementia Alzheimer's disease'.

Growth Arrest Specific 6 Concentration is Increased in the Cerebrospinal Fluid of Patients with Alzheimer's Disease. - Sainaghi, Pier Paolo; Bellan, Mattia; Lombino, Franco; Alciato, Federica; Carecchio, Miryam; Galimberti, Daniela; Fenoglio, Chiara; Scarpini, Elio; Cantello, Roberto; Pirisi, Mario; Comi, Cristoforo (J Alzheimers Dis, 2017)
Growth arrest specific 6 (Gas6) has neurotrophic and neuroinflammatory functions, and may play a role in Alzheimer's disease (AD). In keeping with this hypothesis, we observed that cerebrospinal fluid (CSF) Gas6 is increased in AD patients compared to controls (63 versus 67 subjects; median value 13.3 versus 9.1 ng/ml; p < 0.0001). Thereafter, we assessed whether CSF Gas6 concentration was correlated to the following parameters: disease duration, MMSE score two years after clinical diagnosis, AD CSF biomarkers, and years of formal schooling. We detected an inverse correlation between CSF Gas6 levels at diagnosis and both disease duration (p < 0.0001) and decrease in the MMSE score two years later (p < 0.0001). Conversely, we found no correlation between CSF Gas6 and both AD biomarkers and years of formal schooling. In conclusion, our results suggest that upregulation of CSF Gas6 may be part of a defensive response aimed at counteracting AD progression.

Health Advice in a Digital World: Quality and Content of Online Information about the Prevention of Alzheimer's Disease. - Robillard, Julie M; Feng, Tanya L (J Alzheimers Dis, 2017)
BACKGROUND: As the number of older adults turning to the Internet for health information increases, so does the potential for online information to have a substantial impact on the patient-physician relationship and on their health. Inaccurate information may weaken patient-physician relationships or result in increased physician visits and health anxiety, while high quality information may allow Internet users to make better decisions about their health. OBJECTIVE: To assess the quality and content of available online resources about the prevention of Alzheimer's disease (AD). METHODS: A sample of 308 articles related to the prevention of AD was collected from the first three pages of location-independent keyword searches on Google.com between September 17-30, 2014. Content analysis was applied to articles that met criteria (n = 298) and a quality evaluation tool was developed to generate a quality score for each of the articles (n = 290). RESULTS: We found that articles on the high end of the quality spectrum focused on modifiable risk factors and tended to present balanced information, while articles of low quality emphasized nutrition as a method of prevention and were more likely to be in conflict of interest. CONCLUSION: This study provides the first insight into the content and quality of prevention information for AD currently available online and highlights the importance of future research to better understand the impact of this information on the patient-physician relationship and health decision-making of older adults.

Humanin Specifically Interacts with Amyloid-β Oligomers and Counteracts Their in vivo Toxicity. - Romeo, Margherita; Stravalaci, Matteo; Beeg, Marten; Rossi, Alessandro; Fiordaliso, Fabio; Corbelli, Alessandro; Salmona, Mario; Gobbi, Marco; Cagnotto, Alfredo; Diomede, Luisa (J Alzheimers Dis, 2017)
The 24-residue peptide humanin (HN) has been proposed as a peptide-based inhibitor able to interact directly with amyloid-β (Aβ) oligomers and interfere with the formation and/or biological properties of toxic Aβ species. When administered exogenously, HN, or its synthetic S14G-derivative (HNG), exerted multiple cytoprotective effects, counteracting the Aβ-induced toxicity. Whether these peptides interact directly with Aβ, particularly with the soluble oligomeric assemblies, remains largely unknown. We here investigated the ability of HN and HNG to interact directly with highly aggregating Aβ42, and interfere with the formation and toxicity of its oligomers. Experiments were run in cell-free conditions and in vivo in a transgenic C. elegans strain in which the Aβ toxicity was specifically due to oligomeric species. Thioflavin-T assay indicated that both HN and HNG delay the formation and reduce the final amount of Aβ42 fibrils. In vitro surface plasmon resonance studies indicated that they interact with Aβ42 oligomers favoring the formation of amorphous larger assemblies, observed with turbidity and electron microscopy. In vivo studies indicated that both HN and HNG decrease the relative abundance of A11-positive prefibrillar oligomers as well as OC-positive fibrillar oligomers and had similar protective effects. However, while HN possibly decreased the oligomers by promoting their assembly into larger aggregates, the reduction of oligomers caused by HNG can be ascribed to a marked decrease of the total Aβ levels, likely the consequence of the HNG-induced overexpression of the Aβ-degrading enzyme neprilysin. These findings provide information on the mechanisms underlying the anti-oligomeric effects of HN and HNG and illustrate the role of S14G substitution in regulating the in vivo mechanism of action.
Keywords: Amyloid beta-Peptides; Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Circular Dichroism; Disease Models, Animal; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Intracellular Signaling Peptides and Proteins; Microscopy, Atomic Force; Microscopy, Electron, Transmission; Neprilysin; Paralysis; Peptide Fragments; Surface Plasmon Resonance

Humans with Type-2 Diabetes Show Abnormal Long-Term Potentiation-Like Cortical Plasticity Associated with Verbal Learning Deficits. - Fried, Peter J; Schilberg, Lukas; Brem, Anna-Katharine; Saxena, Sadhvi; Wong, Bonnie; Cypess, Aaron M; Horton, Edward S; Pascual-Leone, Alvaro (J Alzheimers Dis, 2017)
BACKGROUND: Type-2 diabetes mellitus (T2DM) accelerates cognitive aging and increases risk of Alzheimer's disease. Rodent models of T2DM show altered synaptic plasticity associated with reduced learning and memory. Humans with T2DM also show cognitive deficits, including reduced learning and memory, but the relationship of these impairments to the efficacy of neuroplastic mechanisms has never been assessed. OBJECTIVE: Our primary objective was to compare mechanisms of cortical plasticity in humans with and without T2DM. Our secondary objective was to relate plasticity measures to standard measures of cognition. METHODS: A prospective cross-sectional cohort study was conducted on 21 adults with T2DM and 15 demographically-similar non-diabetic controls. Long-term potentiation-like plasticity was assessed in primary motor cortex by comparing the amplitude of motor evoked potentials (MEPs) from single-pulse transcranial magnetic stimulation before and after intermittent theta-burst stimulation (iTBS). Plasticity measures were compared between groups and related to neuropsychological scores. RESULTS: In T2DM, iTBS-induced modulation of MEPs was significantly less than controls, even after controlling for potential confounds. Furthermore, in T2DM, modulation of MEPs 10-min post-iTBS was significantly correlated with Rey Auditory Verbal Learning Task (RAVLT) performance. CONCLUSION: Humans with T2DM show abnormal cortico-motor plasticity that is correlated with reduced verbal learning. Since iTBS after-effects and the RAVLT are both NMDA receptor-dependent measures, their relationship in T2DM may reflect brain-wide alterations in the efficacy of NMDA receptors. These findings offer novel mechanistic insights into the brain consequences of T2DM and provide a reliable means to monitor brain health and evaluate the efficacy of clinical interventions.

Impaired Processing of Serial Order Determines Working Memory Impairments in Alzheimer's Disease. - De Belder, Maya; Santens, Patrick; Sieben, Anne; Fias, Wim (J Alzheimers Dis, 2017)
BACKGROUND: Working memory (WM) problems are commonly observed in Alzheimer's disease (AD), but the affected mechanisms leading to impaired WM are still insufficiently understood. The ability to efficiently process serial order in WM has been demonstrated to be fundamental to fluent daily life functioning. The decreased capability to mentally process serial position in WM has been put forward as the underlying explanation for generally compromised WM performance. OBJECTIVE: Determine which mechanisms, such as order processing, are responsible for deficient WM functioning in AD. METHOD: A group of AD patients (n = 32) and their partners (n = 25), assigned to the control group, were submitted to an extensive battery of neuropsychological and experimental tasks, assessing general cognitive state and functioning of several aspects related to serial order WM. RESULTS: The results revealed an impaired ability to bind item information to serial position within WM in AD patients compared to controls. It was additionally observed that AD patients experienced specific difficulties with directing spatial attention when searching for item information stored in WM. CONCLUSION: The processing of serial order and the allocation of attentional resources are both disrupted, explaining the generally reduced WM functioning in AD patients. Further studies should now clarify whether this observation could explain disease-related problems for other cognitive functions such as verbal expression, auditory comprehension, or planning.

Improved Cerebrospinal Fluid-Based Discrimination between Alzheimer's Disease Patients and Controls after Correction for Ventricular Volumes. - van Waalwijk van Doorn, Linda J C; Gispert, Juan D; Kuiperij, H Bea; Claassen, Jurgen A H R; Arighi, Andrea; Baldeiras, Ines; Blennow, Kaj; Bozzali, Marco; Castelo-Branco, Miguel; Cavedo, Enrica; Emek-Savaş, Derya D; Eren, Erden; et al. (J Alzheimers Dis, 2017)
Cerebrospinal fluid (CSF) biomarkers may support the diagnosis of Alzheimer's disease (AD). We studied if the diagnostic power of AD CSF biomarker concentrations, i.e., Aβ42, total tau (t-tau), and phosphorylated tau (p-tau), is affected by differences in lateral ventricular volume (VV), using CSF biomarker data and magnetic resonance imaging (MRI) scans of 730 subjects, from 13 European Memory Clinics. We developed a Matlab-algorithm for standardized automated segmentation analysis of T1 weighted MRI scans in SPM8 for determining VV, and computed its ratio with total intracranial volume (TIV) as proxy for total CSF volume. The diagnostic power of CSF biomarkers (and their combination), either corrected for VV/TIV ratio or not, was determined by ROC analysis. CSF Aβ42 levels inversely correlated to VV/TIV in the whole study population (Aβ42: r = -0.28; p < 0.0001). For CSF t-tau and p-tau, this association only reached statistical significance in the combined MCI and AD group (t-tau: r = -0.15; p-tau: r = -0.13; both p < 0.01). Correction for differences in VV/TIV improved the differentiation of AD versus controls based on CSF Aβ42 alone (AUC: 0.75 versus 0.81) or in combination with t-tau (AUC: 0.81 versus 0.91). In conclusion, differences in VV may be an important confounder in interpreting CSF Aβ42 levels.

In vivo Patterns of Tau Pathology, Amyloid-β Burden, and Neuronal Dysfunction in Clinical Variants of Alzheimer's Disease. - Dronse, Julian; Fliessbach, Klaus; Bischof, Gérard N; von Reutern, Boris; Faber, Jennifer; Hammes, Jochen; Kuhnert, Georg; Neumaier, Bernd; Onur, Oezguer A; Kukolja, Juraj; van Eimeren, Thilo; Jessen, Frank; et al. (J Alzheimers Dis, 2017)
The clinical heterogeneity of Alzheimer's disease is not reflected in the rather diffuse cortical deposition of amyloid-β. We assessed the relationship between clinical symptoms, in vivo tau pathology, amyloid distribution, and hypometabolism in variants of Alzheimer's disease using novel multimodal PET imaging techniques. Tau pathology was primarily observed in brain regions related to clinical symptoms and overlapped with areas of hypometabolism. In contrast, amyloid-β deposition was diffusely distributed over the entire cortex. Tau PET imaging may thus serve as a valuable biomarker for the localization of neuronal injury in vivo and may help to validate atypical subtypes of Alzheimer's disease.

Increased Carbohydrate Intake is Associated with Poorer Performance in Verbal Memory and Attention in an APOE Genotype-Dependent Manner. - Gardener, Samantha L; Rainey-Smith, Stephanie R; Sohrabi, Hamid R; Weinborn, Michael; Verdile, Giuseppe; Fernando, W M A D Binosha; Lim, Yen Ying; Harrington, Karra; Burnham, Samantha; Taddei, Kevin; Masters, Colin L; Macaulay, Stuart L; et al. (J Alzheimers Dis, 2017)
Evidence suggests that a diet low in carbohydrates can impact on cognitive performance among those with Alzheimer's disease (AD). However, there is a lack of data assessing this relationship among cognitively normal (CN) older adults at increased future risk of developing AD due to carriage of the apolipoprotein E (APOE) ɛ4 allele. We assessed the cross-sectional association between carbohydrate intake, cognitive performance, and cerebral amyloid-β (Aβ) load in CN older adults, genotyped for APOEɛ4 allele carrier status. Greater carbohydrate intake was associated with poorer performance in verbal memory in APOEɛ4 allele non-carriers, and poorer performance in attention in APOEɛ4 allele carriers. There were no associations between carbohydrate intake and cerebral Aβ load. These results provide support to the idea that decreasing carbohydrate intake may offer neurocognitive benefits, with specific cognitive domains affected in an APOE genotype-dependent manner. These findings warrant further investigation utilizing a longitudinal study design.

Increased PCSK9 Cerebrospinal Fluid Concentrations in Alzheimer's Disease. - Zimetti, Francesca; Caffarra, Paolo; Ronda, Nicoletta; Favari, Elda; Adorni, Maria Pia; Zanotti, Ilaria; Bernini, Franco; Barocco, Federica; Spallazzi, Marco; Galimberti, Daniela; Ricci, Chiara; Ruscica, Massimiliano; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) has been associated with dysregulation of brain cholesterol trafficking and abnormal production of apolipoprotein E isoform 4 (apoE4). Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protein present in serum and cerebrospinal fluid (CSF) degrading the low-density lipoprotein receptor (LDLr) and other apoE-binding receptors involved in neuron cholesterol uptake. The role of PCSK9 in AD is controversial. OBJECTIVE: We compared PCSK9 levels in CSF of AD patients and non-AD controls and looked at correlations with CSF total apoE and apoE4. METHODS: CSF from AD (n = 30) and from age and sex-matched non-AD patients (n = 30) was collected by lumbar puncture for routine diagnosis. CSF PCSK9, total apoE, and apoE4 levels were measured by ELISA. AD patients showed the typical CSF neurobiomarker pattern (decreased Aβ42 and increased tau and phospho-tau) and impaired cognitive performances, as indicated by the scores of the Mini-Mental State Examination test. RESULTS: PCSK9 levels in CSF were higher in AD than in non-AD subjects (+1.45 fold; p = 0.0049). CSF total apoE concentrations did not differ between the two groups, while apoE4 levels were higher in AD subjects (+3.34 fold; p = 0.0068). Considering all samples, a significant positive correlation was found between PCSK9 and apoE4 (r = 0.4409; p = 0.0006). PCSK9 levels were higher in APOE ɛ4 carriers, reaching statistical significance in the AD group (+1.45 fold; p = 0.0454). CONCLUSION: These results report for the first time an alteration of CSF PCSK9 levels in AD and suggest a pathophysiological link between PCSK9, apoE4, and AD.

Increased Transforming Growth Factor β2 in the Neocortex of Alzheimer's Disease and Dementia with Lewy Bodies is Correlated with Disease Severity and Soluble Aβ42 Load. - Chong, Joyce R; Chai, Yuek Ling; Lee, Jasinda H; Howlett, David; Attems, Johannes; Ballard, Clive G; Aarsland, Dag; Francis, Paul T; Chen, Christopher P; Lai, Mitchell K P (J Alzheimers Dis, 2017)
BACKGROUND: Of the three transforming growth factor (TGF)-β isoforms known, TGFβ1 deficits have been widely reported in Alzheimer's disease (AD) and studied as a potential therapeutic target. In contrast, the status of TGFβ2, which has been shown to mediate amyloid-β (Aβ)-mediated neuronal death, are unclear both in AD and in Lewy body dementias (LBD) with differential neuritic plaque and neurofibrillary tangle burden. OBJECTIVE: To measure neocortical TGFβ2 levels and their correlations with neuropathological and clinical markers of disease severity in a well-characterized cohort of AD as well as two clinical subtypes of LBD, dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), known to manifest relatively high and low Aβ plaque burden, respectively. METHODS: Postmortem samples from temporal cortex (BA21) were measured for TGFβ2 using a Luminex-based platform, and correlated with scores for neuritic plaques, neurofibrillary tangles, α-synuclein pathology, dementia severity (as measured by annual decline of Mini-Mental State Examination scores) as well as soluble and total fractions of brain Aβ42. RESULTS: TGFβ2 was significantly increased in AD and DLB, but not in PDD. TGFβ2 also correlated with scores for neurofibrillary tangles, Lewy bodies (within the LBD group), dementia severity, and soluble Aβ42 concentration, but not with neuritic plaque scores, total Aβ42, or monomeric α-synuclein immunoreactivity. CONCLUSIONS: TGFβ2 is increased in the temporal cortex of AD and DLB, and its correlations with neuropathological and clinical markers of disease severity as well as with soluble Aβ42 load suggest a potential pathogenic role in mediating the neurotoxicity of non-fibrillar Aβ. Our study also indicates the potential utility of targeting TGFβ2 in pharmacotherapeutic approaches to AD and DLB.

Inflammation, Amyloid, and Atrophy in The Aging Brain: Relationships with Longitudinal Changes in Cognition. - Sala-Llonch, Roser; Idland, Ane-Victoria; Borza, Tom; Watne, Leiv Otto; Wyller, Torgeir Bruun; Brækhus, Anne; Zetterberg, Henrik; Blennow, Kaj; Walhovd, Kristine Beate; Fjell, Anders Martin (J Alzheimers Dis, 2017)
Amyloid deposition occurs in aging, even in individuals free from cognitive symptoms, and is often interpreted as preclinical Alzheimer's disease (AD) pathophysiology. YKL-40 is a marker of neuroinflammation, being increased in AD, and hypothesized to interact with amyloid-β (Aβ) in causing cognitive decline early in the cascade of AD pathophysiology. Whether and how Aβ and YKL-40 affect brain and cognitive changes in cognitively healthy older adults is still unknown. We studied 89 participants (mean age: 73.1 years) with cerebrospinal fluid samples at baseline, and both MRI and cognitive assessments from two time-points separated by two years. We tested how baseline levels of Aβ42 and YKL-40 correlated with changes in cortical thickness and cognition. Thickness change correlated with Aβ42 only in Aβ42+ participants (<600 pg/mL, n = 27) in the left motor and premotor cortices. Aβ42 was unrelated to cognitive change. Increased YKL-40 was associated with less preservation of scores on the animal naming test in the total sample (r = -0.28, p = 0.012) and less preservation of a score reflecting global cognitive function for Aβ42+ participants (r = -0.58, p = 0.004). Our results suggest a role for inflammation in brain atrophy and cognitive changes in cognitively normal older adults, which partly depended on Aβ accumulation.

Insula and Inferior Frontal Gyrus' Activities Protect Memory Performance Against Alzheimer's Disease Pathology in Old Age. - Lin, Feng; Ren, Ping; Lo, Raymond Y; Chapman, Benjamin P; Jacobs, Alanna; Baran, Timothy M; Porsteinsson, Anton P; Foxe, John J (J Alzheimers Dis, 2017)
Apolipoprotein E (APOE) ɛ4 carriers and patients with amnestic mild cognitive impairment (MCI) have high risk of developing Alzheimer's disease (AD). The Scaffolding Theory of Aging and Cognition proposes that recruitment of additional frontal brain regions can protect cognition against aging. This thesis has yet to be fully tested in older adults at high risk for AD. In the present study, 75 older participants (mean age: 74 years) were included. Applying a voxel-wise approach, fractional amplitude of low-frequency fluctuations (fALFF) in resting-state functional neuroimaging data were analyzed as a function of APOEɛ4 status (carrier versus noncarrier) and clinical status (healthy control [HC] versus MCI) using a 2×2 analysis of covariance (ANCOVA). Measures of cognition and cerebrospinal fluid levels of amyloid- β were also obtained. Three frontal regions were identified with significant interaction effects using ANCOVA (corrected p < 0.01): left-insula, left-inferior frontal gyrus (IFG), and right-precentral gyrus. The HC/APOEɛ4 carrier group had significantly higher fALFF in all three regions than other groups. In the entire sample, for two regions (left insula and left IFG), a significant positive relationship between amyloid-β and memory was only observed among individuals with low fALFF. Our results suggest higher activity in frontal regions may explain being cognitively normal among a subgroup of APOEɛ4 carriers and protect against the negative impact of AD-associated pathology on memory. This is an observation with potential implications for AD therapeutics.

Intelligent Assistive Technology for Alzheimer's Disease and Other Dementias: A Systematic Review. - Ienca, Marcello; Fabrice, Jotterand; Elger, Bernice; Caon, Maurizio; Pappagallo, Alessandro Scoccia; Kressig, Reto W; Wangmo, Tenzin (J Alzheimers Dis, 2017)
Intelligent assistive technologies (IATs) have the potential of offering innovative solutions to mitigate the global burden of dementia and provide new tools for dementia care. While technological opportunities multiply rapidly, clinical applications are rare as the technological potential of IATs remains inadequately translated into dementia care. In this article, the authors present the results of a systematic review and the resulting comprehensive technology index of IATs with application in dementia care. Computer science, engineering, and medical databases were extensively searched and the retrieved items were systematically reviewed. For each IAT, the authors examined their technological type, application, target population, model of development, and evidence of clinical validation. The findings reveal that the IAT spectrum is expanding rapidly in volume and variety over time, and encompasses intelligent systems supporting various assistive tasks and clinical uses. At the same time, the results confirm the persistence of structural limitations to successful adoption including partial lack of clinical validation and insufficient focus on patients' needs. This index is designed to orient clinicians and relevant stakeholders involved in the implementation and management of dementia care across the current capabilities, applications, and limitations of IATs and to facilitate the translation of medical engineering research into clinical practice. In addition, a discussion of the major methodological challenges and policy implications for the successful and ethically responsible implementation of IAT into dementia care is provided.

Intranasal Insulin Transport is Preserved in Aged SAMP8 Mice and is Altered by Albumin and Insulin Receptor Inhibition. - Rhea, Elizabeth M; Humann, Samantha R; Nirkhe, Surabhi; Farr, Susan A; Morley, John E; Banks, William A (J Alzheimers Dis, 2017)
Insulin delivered to the level of the cribriform plate (intranasal insulin) is being investigated for its ability to enhance memory in people with Alzheimer's disease (AD). Recent work has shown intranasal insulin can be detected in young CD-1 mice within 5 min and is still present 60 min after injection. The current study determined whether intranasal insulin transport and the subsequent brain distribution of insulin varies in young, healthy mice (CD-1) compared to those with an AD-like phenotype (aged SAMP8) or those pre-disposed to develop such a phenotype (young SAMP8). We showed transport does not vary among these three mouse cohorts, suggesting that intranasal uptake and brain pharmacokinetics do not differ with AD-like signs or the genetic predisposition to developing them. We found that co-administration with bovine serum albumin increased levels of insulin in most brain regions. In addition, the insulin receptor inhibitor, S961, decreases the amount of insulin transported throughout the brain after intranasal injection. These results show insulin delivery to the brain by intranasal administration can be modified with agents such as albumin, may be dependent on the insulin receptor, and is not affected by an AD-like phenotype as presented by the SAMP8 mouse.

Investigating Simulated Driving Errors in Amnestic Single- and Multiple-Domain Mild Cognitive Impairment. - Hird, Megan A; Vesely, Kristin A; Fischer, Corinne E; Graham, Simon J; Naglie, Gary; Schweizer, Tom A (J Alzheimers Dis, 2017)
The areas of driving impairment characteristic of mild cognitive impairment (MCI) remain unclear. This study compared the simulated driving performance of 24 individuals with MCI, including amnestic single-domain (sd-MCI, n = 11) and amnestic multiple-domain MCI (md-MCI, n = 13), and 20 age-matched controls. Individuals with MCI committed over twice as many driving errors (20.0 versus 9.9), demonstrated difficulty with lane maintenance, and committed more errors during left turns with traffic compared to healthy controls. Specifically, individuals with md-MCI demonstrated greater driving difficulty compared to healthy controls, relative to those with sd-MCI. Differentiating between different subtypes of MCI may be important when evaluating driving safety.

Investigations into Retinal Pathology in the Early Stages of a Mouse Model of Alzheimer's Disease. - Chidlow, Glyn; Wood, John P M; Manavis, Jim; Finnie, John; Casson, Robert J (J Alzheimers Dis, 2017)
There is increasing recognition that visual performance is impaired in early stages of Alzheimer's disease (AD); however, no consensus exists as to the mechanisms underlying this visual dysfunction, in particular regarding the timing, nature, and extent of retinal versus cortical pathology. If retinal pathology presents sufficiently early, it offers great potential as a source of novel biomarkers for disease diagnosis. The current project utilized an array of immunochemical and molecular tools to perform a characterization of retinal pathology in the early stages of disease progression using a well-validated mouse model of AD (APPSWE/PS1ΔE9). Analytical endpoints included examination of aberrant amyloid and tau in the retina, quantification of any neuronal degeneration, delineation of cellular stress responses of neurons and particularly glial cells, and investigation of oxidative stress. Brain, eyes, and optic nerves were taken from transgenic and wild-type mice of 3 to 12 months of age and processed for immunohistochemistry, qPCR, or western immunoblotting. The results revealed robust expression of the human APP transgene in the retinas of transgenic mice, but a lack of identifiable retinal pathology during the period when amyloid deposits were dramatically escalating in the brain. We were unable to demonstrate the presence of amyloid plaques, dystrophic neurites, neuronal loss, macro- or micro-gliosis, aberrant cell cycle re-entry, oxidative stress, tau hyperphosphorylation, or upregulations of proinflammatory cytokines or stress signaling molecules in the retina. The overall results do not support the hypothesis that detectable retinal pathology occurs concurrently with escalating amyloid deposition in the brains of APPSWE/PS1ΔE9 mice.

Kidins220 Correlates with Tau in Alzheimer's Disease Brain and Cerebrospinal Fluid. - Gamir-Morralla, Andrea; Belbin, Olivia; Fortea, Juan; Alcolea, Daniel; Ferrer, Isidro; Lleo, Alberto; Iglesias, Teresa (J Alzheimers Dis, 2017)
Identification of neurodegeneration-monitoring biomarkers would be of great clinical value for Alzheimer's disease (AD) diagnosis. Using N- or C-terminal antibodies, we studied the pro-survival synaptic effector, Kidins220, in the brain and cerebrospinal fluid (CSF) of controls and AD patients. Only the N-terminal antibody showed a positive correlation between Kidins220 and phosphorylated tau in AD brains. Using this antibody, Kidins220 was detected in CSF from AD patients where it positively correlated with CSF phosphorylated tau and tau. This study highlights the potential of Kidins220 as a CSF biomarker in AD.

Left Frontal Hub Connectivity during Memory Performance Supports Reserve in Aging and Mild Cognitive Impairment. - Franzmeier, Nicolai; Hartmann, Julia C; Taylor, Alexander N W; Araque Caballero, Miguel Á; Simon-Vermot, Lee; Buerger, Katharina; Kambeitz-Ilankovic, Lana M; Ertl-Wagner, Birgit; Mueller, Claudia; Catak, Cihan; Janowitz, Daniel; Stahl, Robert; et al. (J Alzheimers Dis, 2017)
Reserve in aging and Alzheimer's disease (AD) is defined as maintaining cognition at a relatively high level in the presence of neurodegeneration, an ability often associated with higher education among other life factors. Recent evidence suggests that higher resting-state functional connectivity within the frontoparietal control network, specifically the left frontal cortex (LFC) hub, contributes to higher reserve. Following up these previous resting-state fMRI findings, we probed memory-task related functional connectivity of the LFC hub as a neural substrate of reserve. In elderly controls (CN, n = 37) and patients with mild cognitive impairment (MCI, n = 17), we assessed global connectivity of the LFC hub during successful face-name association learning, using generalized psychophysiological interaction analyses. Reserve was quantified as residualized memory performance, accounted for gender and proxies of neurodegeneration (age, hippocampus atrophy, and APOE genotype). We found that greater education was associated with higher LFC-connectivity in both CN and MCI during successful memory. Furthermore, higher LFC-connectivity predicted higher residualized memory (i.e., reserve). These results suggest that higher LFC-connectivity contributes to reserve in both healthy and pathological aging.

The Link between Type 2 Diabetes and Neurodegeneration: Roles for Amyloid-β, Amylin, and Tau Proteins. - Bharadwaj, Prashant; Wijesekara, Nadeeja; Liyanapathirana, Milindu; Newsholme, Philip; Ittner, Lars; Fraser, Paul; Verdile, Giuseppe (J Alzheimers Dis, 2017)
A wealth of evidence indicates a strong link between type 2 diabetes (T2D) and neurodegenerative diseases such as Alzheimer's disease (AD). Although the precise mechanism remains unclear, T2D can exacerbate neurodegenerative processes. Brain atrophy, reduced cerebral glucose metabolism, and central nervous system insulin resistance are features of both AD and T2D. The T2D phenotype (glucose dyshomeostasis, insulin resistance, impaired insulin signaling) also promotes AD pathology, namely accumulation of amyloid-β (Aβ) and hyperphosphorylated tau and can induce other aspects of neuronal degeneration including inflammatory and oxidative processes. Aβ and hyperphosphorylated tau may also have roles in pancreatic β-cell dysfunction and in reducing insulin sensitivity and glucose uptake by peripheral tissues such as liver, skeletal muscle, and adipose tissue. This suggests a role for these AD-related proteins in promoting T2D. The accumulation of the islet amyloid polypeptide (IAPP, or amylin) within islet β-cells is a major pathological feature of the pancreas in patients with chronic T2D. Co-secreted with insulin, amylin accumulates over time and contributes to β-cell toxicity, ultimately leading to reduced insulin secretion and onset of overt (insulin dependent) diabetes. Recent evidence also suggests that this protein accumulates in the brain of AD patients and may interact with Aβ to exacerbate the neurodegenerative process. In this review, we highlight evidence indicating T2D in promoting Aβ and tau mediated neurodegeneration and the potential contributions of Aβ and tau in promoting a diabetic phenotype that could further exacerbate neurodegeneration. We also discuss underlying mechanisms by which amylin can contribute to the neurodegenerative processes.

Living Alone with Alzheimer's Disease: Data from SveDem, the Swedish Dementia Registry. - Cermakova, Pavla; Nelson, Maja; Secnik, Juraj; Garcia-Ptacek, Sara; Johnell, Kristina; Fastbom, Johan; Kilander, Lena; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2017)
BACKGROUND: Many people with Alzheimer's disease (AD) live alone in their own homes. There is a lack of knowledge about whether these individuals receive the same quality of diagnostics and treatment for AD as patients who are cohabiting. OBJECTIVES: To investigate the diagnostic work-up and treatment of community-dwelling AD patients who live alone. METHODS: We performed a cross-sectional cohort study based on data from the Swedish Dementia Registry (SveDem). We studied patients diagnosed with AD between 2007 and 2015 (n = 26,163). Information about drugs and comorbidities was acquired from the Swedish Prescribed Drug Register and the Swedish Patient Register. RESULTS: 11,878 (46%) patients lived alone, primarily older women. After adjusting for confounders, living alone was inversely associated with receiving computed tomography (OR 0.90; 95% CI 0.82-0.99), magnetic resonance imaging (OR 0.91; 95% CI 0.83-0.99), and lumbar puncture (OR 0.86; 95% CI 0.80-0.92). Living alone was also negatively associated with the use of cholinesterase inhibitors (OR 0.81; 95% CI 0.76; 0.87), memantine (OR 0.77; 95% CI 0.72; 0.83), and cardiovascular medication (OR 0.92; 0.86; 0.99). On the other hand, living alone was positively associated with the use of antidepressants (OR 1.15; 95% CI 1.08; 1.22), antipsychotics (OR 1.41; 95% CI 1.25; 1.58), and hypnotics and sedatives (OR 1.09; 95% CI 1.02; 1.17). CONCLUSIONS: Solitary living AD patients do not receive the same extent of care as those who are cohabiting.

Long-Term Cognitive Decline in Dementia with Lewy Bodies in a Large Multicenter, International Cohort. - Kramberger, Milica G; Auestad, Bjørn; Garcia-Ptacek, Sara; Abdelnour, Carla; Olmo, Josep Garre; Walker, Zuzana; Lemstra, Afina W; Londos, Elisabet; Blanc, Frédéric; Bonanni, Laura; McKeith, Ian; Winblad, Bengt; et al. (J Alzheimers Dis, 2017)
BACKGROUND/OBJECTIVE: The aim of this study was to describe the rate and clinical predictors of cognitive decline in dementia with Lewy bodies (DLB), and compare the findings with Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) patients. METHODS: Longitudinal scores for the Mini-Mental State Examination (MMSE) in 1,290 patients (835 DLB, 198 PDD, and 257 AD) were available from 18 centers with up to three years longitudinal data. Linear mixed effects analyses with appropriate covariates were used to model MMSE decline over time. Several subgroup analyses were performed, defined by anti-dementia medication use, baseline MMSE score, and DLB core features. RESULTS: The mean annual decline in MMSE score was 2.1 points in DLB, compared to 1.6 in AD (p = 0.07 compared to DLB) and 1.8 in PDD (p = 0.19). Rates of decline were significantly higher in DLB compared to AD and PDD when baseline MMSE score was included as a covariate, and when only those DLB patients with an abnormal dopamine transporter SPECT scan were included. Decline was not predicted by sex, baseline MMSE score, or presence of specific DLB core features. CONCLUSIONS: The average annual decline in MMSE score in DLB is approximately two points. Although in the overall analyses there were no differences in the rate of decline between the three neurodegenerative disorders, there were indications of a more rapid decline in DLB than in AD and PDD. Further studies are needed to understand the predictors and mechanisms of cognitive decline in DLB.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cognition Disorders; Cohort Studies; Female; Humans; International Cooperation; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged

Low Florbetapir PET Uptake and Normal Aβ1-42 Cerebrospinal Fluid in an APP Ala713Thr Mutation Carrier. - Lombardi, Gemma; Berti, Valentina; Tedde, Andrea; Bagnoli, Silvia; Piaceri, Irene; Polito, Cristina; Lucidi, Giulia; Ferrari, Camilla; Ginestroni, Andrea; Moretti, Marco; Pupi, Alberto; Nacmias, Benedetta; et al. (J Alzheimers Dis, 2017)
According to the literature, the APP Ala713Thr mutation is associated with Alzheimer's disease and cerebral amyloid angiopathy. We describe a case of dementia clinically compatible with frontotemporal dementia in an APP Ala713Thr mutation carrier in which both [18F]Florbetapir PET uptake and Aβ1-42 cerebrospinal fluid levels were normal. Further evidences are required to establish if this association is only incidental.
Keywords: Alanine; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Aniline Compounds; Brain; Ethylene Glycols; Humans; Male; Middle Aged; Mutation; Peptide Fragments; Positron-Emission Tomography; Threonine

Magnetic Resonance Imaging and Anatomical Correlation of Human Temporal Lobe Landmarks, in 3D Euclidean Space: A Study of Control and Alzheimer's Disease Subjects. - Delgado-González, José-Carlos; Florensa-Vila, José; Mansilla-Legorburo, Francisco; Insausti, Ricardo; Artacho-Pérula, Emilio (J Alzheimers Dis, 2017)
BACKGROUND: The medial temporal lobe (MTL), and in particular the hippocampal formation, is essential in the processing and consolidation of declarative memory. The 3D environment of the anatomical structures contained in the MTL is an important issue. OBJECTIVE: Our aim was to explore the spatial relationship of the anatomical structures of the MTL and changes in aging and/or Alzheimer's disease (AD). METHODS: MTL anatomical landmarks are identified and registered to create a 3D network. The brain network is quantitatively described as a plane, rostrocaudally-oriented, and presenting Euclidean/real distances. Correspondence between 1.5T RM, 3T RM, and histological sections were assessed to determine the most important recognizable changes in AD, based on statistical significance. RESULTS: In both 1.5T and 3T RM images and histology, inter-rater reliability was high. Sex and hemisphere had no influence on network pattern. Minor changes were found in relation to aging. Distances from the temporal pole to the dentate gyrus showed the most significant differences when comparing control and AD groups. The best discriminative distance between control and AD cases was found in the temporal pole/dentate gyrus rostrocaudal length in histological sections. Moreover, more distances between landmarks were required to obtain 100% discrimination between control (divided into <65 years or >65 years) and AD cases. DISCUSSION: Changes in the distance between MTL anatomical landmarks can successfully be detected by using measurements of 3D network patterns in control and AD cases.

Memory Complaints and Cognitive Decline: Data from the GUIDAGE Study1. - Dardenne, Sophie; Delrieu, Julien; Sourdet, Sandrine; Cantet, Christelle; Andrieu, Sandrine; Mathiex-Fortunet, Hélène; Fougère, Bertrand; Vellas, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may be a very early symptom of Alzheimer's disease (AD) and may be associated with a cognitive decline in a cognitively normal population. The McNair and Kahn Scale was used to assess memory complaints in the GuidAge study. OBJECTIVE: Our objectives were to examine if the McNair and Kahn Scale can predict cognitive decline and to screen which (if any) of the question(s) of this scale would better predict this cognitive decline. METHODS: The GuidAge study was a phase III, multicenter, randomized, double blind, placebo-controlled study. Individuals aged 70 years and older, without cognitive impairment (Clinical Dementia Rate (CDR = 0)) at baseline who had spontaneously reported SCD were included in this study. The 20-item version of the McNair and Kahn Scale was used to assess SCD and a standardized neuropsychological assessment was used to assess the cognitive status. RESULTS: 1,307 patients with SCD and with CDR = 0 at baseline were included. During the 5 years of follow-up, 519 patients showed cognitive decline. Incidence of aggravation score of CDR was 13.40% person years (95% CI [12.24-14.56]). Results showed a significant relationship between the McNair and Kahn Scale score and decline in cognitive performance (HR 1.012; 95% CI [1.002-1.021]; p = 0.0156). Among the 20 items, 5 were statistically significant to predict cognitive decline after adjustment. CONCLUSION: SCD is a promising indicator of memory impairment. Our study found that using the McNair and Kahn scale can predict cognitive decline. A 5-item version of this scale could be used to screen patients in clinical practice and in clinical research.

Methylene Blue (Tetramethylthionine Chloride) Influences the Mobility of Adult Neural Stem Cells: A Potentially Novel Therapeutic Mechanism of a Therapeutic Approach in the Treatment of Alzheimer's Disease. - van der Ven, Amelie T; Pape, Julius C; Hermann, Dirk; Schloesser, Robert; Genius, Just; Fischer, Nadine; Mößner, Rainald; Scherbaum, Norbert; Wiltfang, Jens; Rujescu, Dan; Benninghoff, Jens (J Alzheimers Dis, 2017)
An interest in neurogenesis in the adult human brain as a relevant and targetable process has emerged as a potential treatment option for Alzheimer's disease and other neurodegenerative conditions. The aim of this study was to investigate the effects of tetramethylthionine chloride (methylene blue, MB) on properties of adult murine neural stem cells. Based on recent clinical studies, MB has increasingly been discussed as a potential treatment for Alzheimer's disease. While no differences in the proliferative capacity were identified, a general potential of MB in modulating the migratory capacity of adult neural stem cells was indicated in a cell mobility assay. To our knowledge, this is the first time that MB could be associated with neural mobility. The results of this study add insight to the spectrum of features of MB within the central nervous system and may be helpful for understanding the molecular mechanisms underlying a potential therapeutic effect of MB.

The Methylenetetrahydrofolate Reductase C677T Polymorphism and Risk for Late-Onset Alzheimer's disease: Further Evidence in an Italian Multicenter Study. - Stoccoro, Andrea; Tannorella, Pierpaola; Salluzzo, Maria Grazia; Ferri, Raffaele; Romano, Corrado; Nacmias, Benedetta; Siciliano, Gabriele; Migliore, Lucia; Coppedè, Fabio (J Alzheimers Dis, 2017)
BACKGROUND: A functional polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene, namely C677T (rs1801133), results in increased Hcy levels and has been associated with risk of late-onset Alzheimer's disease (LOAD). Many investigators reported association between rs1801133 and LOAD risk in Asian populations and in carriers of the apolipoprotein E (APOE) ɛ4 allele, but recent meta-analyses suggest a contribution also in other populations, including Caucasians and/or northern Africans. OBJECTIVE: To further address this issue, we performed a relatively large case-control study, including 581 LOAD patients and 468 matched controls of Italian origin. APOE data were available for a subgroup of almost 600 subjects. METHODS: Genotyping for rs1801133 was performed with PCR-RFLP techniques. RESULTS: In the total population, the MTHFR 677T allele (OR = 1.20; 95% CI = 1.01-1.43) and carriers of the MTHFR 677T allele (CT+TT versus CC: OR = 1.34; 95% CI = 1.03-1.73) resulted in increased LOAD risk. Similarly, in APOEɛ4 carriers, we observed an increased frequency of MTHFR 677CT carriers (CT versus CC: OR = 2.82; 95% CI = 1.25-6.32). Very interestingly, also in non-APOEɛ4 carriers, both MTHFR 677T allele (OR = 1.38; 95% CI = 1.03-1.85) and MTHFR 677TT genotype (OR = 2.08; 95% CI = 1.11-3.90) were associated with LOAD. All these associations survived after corrections for age, gender, and multiple testing. CONCLUSIONS: The present results suggest that the MTHFR C677T polymorphism is likely a LOAD risk factor in our cohort, either in APOEɛ4 or in non-APOEɛ4 carriers.

Microglial and Neuronal TDP-43 Pathology in Anti-IgLON5-Related Tauopathy. - Cagnin, Annachiara; Mariotto, Sara; Fiorini, Michele; Gaule, Marina; Bonetto, Nicola; Tagliapietra, Matteo; Buratti, Emanuele; Zanusso, Gianluigi; Ferrari, Sergio; Monaco, Salvatore (J Alzheimers Dis, 2017)
A novel neuronal tauopathy, mainly confined to hypothalamus and brainstem tegmentum, has recently been reported in patients with autoantibodies to the neuronal cell-adhesion molecule IgLON5. We describe a patient with anti-IgLON5 syndrome, who presented with dysautonomia and sleep disorder, followed by subacute dementia. Postmortem brain examination disclosed neuronal tau pathology prevailing in the hippocampus, amygdala, and locus coeruleus, in addition to microglial/neuronal TDP-43 pathology, with overexpression of aberrantly phosphorylated forms and neurotoxic truncated fragments, in basal ganglia, nucleus basalis, thalamus, and midbrain. These findings suggest that neurodegeneration in anti-IgLON5 syndrome might also occur via a microglia-triggered non-cell autonomous pathway.

The Mild Behavioral Impairment Checklist (MBI-C): A Rating Scale for Neuropsychiatric Symptoms in Pre-Dementia Populations. - Ismail, Zahinoor; Agüera-Ortiz, Luis; Brodaty, Henry; Cieslak, Alicja; Cummings, Jeffrey; Fischer, Corinne E; Gauthier, Serge; Geda, Yonas E; Herrmann, Nathan; Kanji, Jamila; Lanctôt, Krista L; Miller, David S; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Mild behavioral impairment (MBI) is a construct that describes the emergence at ≥50 years of age of sustained and impactful neuropsychiatric symptoms (NPS), as a precursor to cognitive decline and dementia. MBI describes NPS of any severity, which are not captured by traditional psychiatric nosology, persist for at least 6 months, and occur in advance of or in concert with mild cognitive impairment. While the detection and description of MBI has been operationalized in the International Society to Advance Alzheimer's Research and Treatment - Alzheimer's Association (ISTAART-AA) research diagnostic criteria, there is no instrument that accurately reflects MBI as described. OBJECTIVE: To develop an instrument based on ISTAART-AA MBI criteria. METHODS: Eighteen subject matter experts participated in development using a modified Delphi process. An iterative process ensured items reflected the five MBI domains of 1) decreased motivation; 2) emotional dysregulation; 3) impulse dyscontrol; 4) social inappropriateness; and 5) abnormal perception or thought content. Instrument language was developed a priori to pertain to non-demented functionally independent older adults. RESULTS: We present the Mild Behavioral Impairment Checklist (MBI-C), a 34-item instrument, which can easily be completed by a patient, close informant, or clinician. CONCLUSION: The MBI-C provides the first measure specifically developed to assess the MBI construct as explicitly described in the criteria. Its utility lies in MBI case detection, and monitoring the emergence of MBI symptoms and domains over time. Studies are required to determine the prognostic value of MBI for dementia development, and for predicting different dementia subtypes.

Modifiable Risk Factors for Prevention of Dementia in Midlife, Late Life and the Oldest-Old: Validation of the LIBRA Index. - Vos, Stephanie J B; van Boxtel, Martin P J; Schiepers, Olga J G; Deckers, Kay; de Vugt, Marjolein; Carrière, Isabelle; Dartigues, Jean-François; Pérès, Karine; Artero, Sylvaine; Ritchie, Karen; Galluzzo, Lucia; Scafato, Emanuele; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Recently, the LIfestyle for BRAin health (LIBRA) index was developed to assess an individual's prevention potential for dementia. OBJECTIVE: We investigated the predictive validity of the LIBRA index for incident dementia in midlife, late life, and the oldest-old. METHODS: 9,387 non-demented individuals were recruited from the European population-based DESCRIPA study. An individual's LIBRA index was calculated solely based on modifiable risk factors: depression, diabetes, physical activity, hypertension, obesity, smoking, hypercholesterolemia, coronary heart disease, and mild/moderate alcohol use. Cox regression was used to test the predictive validity of LIBRA for dementia at follow-up (mean 7.2 y, range 1-16). RESULTS: In midlife (55-69 y, n = 3,256) and late life (70-79 y, n = 4,320), the risk for dementia increased with higher LIBRA scores. Individuals in the intermediate- and high-risk groups had a higher risk of dementia than those in the low-risk group. In the oldest-old (80-97 y, n = 1,811), higher LIBRA scores did not increase the risk for dementia. CONCLUSION: LIBRA might be a useful tool to identify individuals for primary prevention interventions of dementia in midlife, and maybe in late life, but not in the oldest-old.

Motor Phenotype in Neurodegenerative Disorders: Gait and Balance Platform Study Design Protocol for the Ontario Neurodegenerative Research Initiative (ONDRI). - Montero-Odasso, Manuel; Pieruccini-Faria, Frederico; Bartha, Robert; Black, Sandra E; Finger, Elizabeth; Freedman, Morris; Greenberg, Barry; Grimes, David A; Hegele, Robert A; Hudson, Christopher; Kleinstiver, Peter W; Lang, Anthony E; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The association of cognitive and motor impairments in Alzheimer's disease and other neurodegenerative diseases is thought to be related to damage in the common brain networks shared by cognitive and cortical motor control processes. These common brain networks play a pivotal role in selecting movements and postural synergies that meet an individual's needs. Pathology in this "highest level" of motor control produces abnormalities of gait and posture referred to as highest-level gait disorders. Impairments in cognition and mobility, including falls, are present in almost all neurodegenerative diseases, suggesting common mechanisms that still need to be unraveled. OBJECTIVE: To identify motor-cognitive profiles across neurodegenerative diseases in a large cohort of patients. METHODS: Cohort study that includes up to 500 participants, followed every year for three years, across five neurodegenerative disease groups: Alzheimer's disease/mild cognitive impairment, frontotemporal degeneration, vascular cognitive impairment, amyotrophic lateral sclerosis, and Parkinson's disease. Gait and balance will be assessed using accelerometers and electronic walkways, evaluated at different levels of cognitive and sensory complexity, using the dual-task paradigm. RESULTS: Comparison of cognitive and motor performances across neurodegenerative groups will allow the identification of motor-cognitive phenotypes through the standardized evaluation of gait and balance characteristics. CONCLUSIONS: As part of the Ontario Neurodegenerative Research Initiative (ONDRI), the gait and balance platform aims to identify motor-cognitive profiles across neurodegenerative diseases. Gait assessment, particularly while dual-tasking, will help dissect the cognitive and motor contribution in mobility and cognitive decline, progression to dementia syndromes, and future adverse outcomes including falls and mortality.

A Multi-Cohort Study of ApoE ɛ4 and Amyloid-β Effects on the Hippocampus in Alzheimer's Disease. - Khan, Wasim; Giampietro, Vincent; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun L W; Büchel, Christian; Conrod, Patricia; Flor, Herta; Frouin, Vincent; Garavan, Hugh; Gowland, Penny; Heinz, Anreas; et al. (J Alzheimers Dis, 2017)
The apolipoprotein E (APOE) gene has been consistently shown to modulate the risk of Alzheimer's disease (AD). Here, using an AD and normal aging dataset primarily consisting of three AD multi-center studies (n = 1,781), we compared the effect of APOE and amyloid-β (Aβ) on baseline hippocampal volumes in AD patients, mild cognitive impairment (MCI) subjects, and healthy controls. A large sample of healthy adolescents (n = 1,387) was also used to compared hippocampal volumes between APOE groups. Subjects had undergone a magnetic resonance imaging (MRI) scan and APOE genotyping. Hippocampal volumes were processed using FreeSurfer. In the AD and normal aging dataset, hippocampal comparisons were performed in each APOE group and in ɛ4 carriers with positron emission tomography Aβ who were dichotomized (Aβ+/Aβ-) using previous cut-offs. We found a linear reduction in hippocampal volumes with ɛ4 carriers possessing the smallest volumes, ɛ3 carriers possessing intermediate volumes, and ɛ2 carriers possessing the largest volumes. Moreover, AD and MCI ɛ4 carriers possessed the smallest hippocampal volumes and control ɛ2 carriers possessed the largest hippocampal volumes. Subjects with both APOE ɛ4 and Aβ+ had the lowest hippocampal volumes when compared to Aβ- ɛ4 carriers, suggesting a synergistic relationship between APOE ɛ4 and Aβ. However, we found no hippocampal volume differences between APOE groups in healthy 14-year-old adolescents. Our findings suggest that the strongest neuroanatomic effect of APOE ɛ4 on the hippocampus is observed in AD and groups most at risk of developing the disease, whereas hippocampi of old and young healthy individuals remain unaffected.

A Multifunctional Biocompatible Drug Candidate is Highly Effective in Delaying Pathological Signs of Alzheimer's Disease in 5XFAD Mice. - Segal-Gavish, Hadar; Danino, Ortal; Barhum, Yael; Ben-Zur, Tali; Shai, Ella; Varon, David; Offen, Daniel; Fischer, Bilha (J Alzheimers Dis, 2017)
BACKGROUND: Metal-ion-chelation was suggested to prevent zinc and copper ions-induced amyloid-β (Aβ) aggregation and oxidative stress, both implicated in the pathophysiology of Alzheimer's disease (AD). In a quest for biocompatible metal-ion chelators potentially useful for AD therapy, we previously tested a series of nucleoside 5'-phosphorothioate derivatives as agents for decomposition of Cu(I)/Cu(II)/Zn(II)-Aβ-aggregates, and as inhibitors of OH radicals formation in Cu(I) or Fe(II) /H2O2 solution. Specifically, in our recent study we have identified 2-SMe-ADP(α-S), designated as SAS, as a most promising neuroprotectant. OBJECTIVE: To further explore SAS ability to protect the brain from Aβ toxicity both in vitro and in vivo. METHODS: We evaluated SAS ability to decompose or inhibit the formation of Aβ42-M(II) aggregates, and rescue primary neurons and astrocytes from Aβ42 toxicity. Furthermore, we aimed at exploring the therapeutic effect of SAS on behavioral and cognitive deficits in the 5XFAD mouse model of AD. RESULTS: We found that SAS can rescue primary culture of neurons and astrocytes from Aβ42 toxicity and to inhibit the formation and dissolve Aβ42-Zn(II)/Cu(II) aggregates. Furthermore, we show that SAS treatment can prevent behavioral disinhibition and ameliorate spatial working memory deficits in 5XFAD mice. Notably, the mice were treated at the age of 2 months, before the onset of AD symptoms, for a duration of 2 months, while the effect was demonstrated at the age of 6 months. CONCLUSION: Our results indicate that SAS has the potential to delay progression of core pathological characteristics of AD in the 5XFAD mouse model.

Multifunctional Compound AD-35 Improves Cognitive Impairment and Attenuates the Production of TNF-α and IL-1β in an Aβ25-35-induced Rat Model of Alzheimer's Disease. - Li, Lin; Xu, Shaofeng; Liu, Lifei; Feng, Rentian; Gong, Yongxiang; Zhao, Xuyang; Li, Jiang; Cai, Jie; Feng, Nan; Wang, Ling; Wang, Xiaoliang; Peng, Ying (J Alzheimers Dis, 2017)
The dyshomeostasis of transition metal ions, accumulation of amyloid-β (Aβ) senile plaques and neuroinflammatory response found in the brain of patients with Alzheimer's disease (AD) have been suggested to be involved in AD pathogenesis. Novel compounds capable of targeting metal-Aβ species and neuroinflammation would be valuable. AD-35 is such a patented small-molecule compound derived from innovative modification of the chemical structure of donepezil. This compound could moderately inhibit acetylcholinesterase and metal-induced Aβ aggregation in vitro and showed disassembly of Aβ aggregates. The effects of AD-35 on cognitive impairments and neuroinflammatory changes caused by intracerebroventricular injection of Aβ25-35 were studied in rats. Compared to sham group, Aβ25-35 injection significantly led to learning and memory deficits, astrocyte activation, and pro-inflammatory cytokines releases (TNF-α and IL-1β). Further studies indicated that the phosphorylation of extracellular signal-regulated kinase was involved in astrocyte activation and pro-inflammatory cytokines production. Oral administration of AD-35 could markedly attenuate Aβ25-35 injection-induced astrocyte activation, pro-inflammatory cytokines TNF-α and IL-1β release, and memory deficits. On the contrary, donepezil only showed inhibition of IL-1β production, but failed to block astrocyte activation and TNF-α production. These results showed that AD-35 would be a novel multi-mechanism drug for the prevention and/or treatment of AD.

Music Perception in Dementia. - Golden, Hannah L; Clark, Camilla N; Nicholas, Jennifer M; Cohen, Miriam H; Slattery, Catherine F; Paterson, Ross W; Foulkes, Alexander J M; Schott, Jonathan M; Mummery, Catherine J; Crutch, Sebastian J; Warren, Jason D (J Alzheimers Dis, 2017)
Despite much recent interest in music and dementia, music perception has not been widely studied across dementia syndromes using an information processing approach. Here we addressed this issue in a cohort of 30 patients representing major dementia syndromes of typical Alzheimer's disease (AD, n = 16), logopenic aphasia (LPA, an Alzheimer variant syndrome; n = 5), and progressive nonfluent aphasia (PNFA; n = 9) in relation to 19 healthy age-matched individuals. We designed a novel neuropsychological battery to assess perception of musical patterns in the dimensions of pitch and temporal information (requiring detection of notes that deviated from the established pattern based on local or global sequence features) and musical scene analysis (requiring detection of a familiar tune within polyphonic harmony). Performance on these tests was referenced to generic auditory (timbral) deviance detection and recognition of familiar tunes and adjusted for general auditory working memory performance. Relative to healthy controls, patients with AD and LPA had group-level deficits of global pitch (melody contour) processing while patients with PNFA as a group had deficits of local (interval) as well as global pitch processing. There was substantial individual variation within syndromic groups. Taking working memory performance into account, no specific deficits of musical temporal processing, timbre processing, musical scene analysis, or tune recognition were identified. The findings suggest that particular aspects of music perception such as pitch pattern analysis may open a window on the processing of information streams in major dementia syndromes. The potential selectivity of musical deficits for particular dementia syndromes and particular dimensions of processing warrants further systematic investigation.

Neural Dynamics of Multiple Object Processing in Mild Cognitive Impairment and Alzheimer's Disease: Future Early Diagnostic Biomarkers? - Bagattini, Chiara; Mazza, Veronica; Panizza, Laura; Ferrari, Clarissa; Bonomini, Cristina; Brignani, Debora (J Alzheimers Dis, 2017)
The aim of this study was to investigate the behavioral and electrophysiological dynamics of multiple object processing (MOP) in mild cognitive impairment (MCI) and Alzheimer's disease (AD), and to test whether its neural signatures may represent reliable diagnostic biomarkers. Behavioral performance and event-related potentials [N2pc and contralateral delay activity (CDA)] were measured in AD, MCI, and healthy controls during a MOP task, which consisted in enumerating a variable number of targets presented among distractors. AD patients showed an overall decline in accuracy for both small and large target quantities, whereas in MCI patients, only enumeration of large quantities was impaired. N2pc, a neural marker of attentive individuation, was spared in both AD and MCI patients. In contrast, CDA, which indexes visual short term memory abilities, was altered in both groups of patients, with a non-linear pattern of amplitude modulation along the continuum of the disease: a reduction in AD and an increase in MCI. These results indicate that AD pathology shows a progressive decline in MOP, which is associated to the decay of visual short-term memory mechanisms. Crucially, CDA may be considered as a useful neural signature both to distinguish between healthy and pathological aging and to characterize the different stages along the AD continuum, possibly becoming a reliable candidate for an early diagnostic biomarker of AD pathology.

Neurodegenerative Markers are Increased in Postmortem BA21 Tissue from African Americans with Alzheimer's Disease. - Ferguson, Sherry A; Panos, John J; Sloper, Daniel; Varma, Vijayalakshmi (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) presents with an earlier onset age and increased symptom severity in African Americans and Hispanics. OBJECTIVE: Although the prevalence of plaques and tangles may not exhibit ethnicity-related differences, levels of neurodegenerative proteins have not been described. METHODS: Here, levels of five proteins (i.e., S100B, sRAGE, GDNF, Aβ40, and Aβ42) and the Aβ42/Aβ40 ratio were measured in postmortem samples of the middle temporal gyrus (BA21) from age-matched African Americans and Caucasians with AD (n = 6/gender/ethnicity). RESULTS: S100B levels were increased 17% in African Americans (p < 0.003) while sRAGE was mildly decreased (p < 0.09). Aβ42 levels were increased 121% in African Americans (p < 0.02), leading to a 493% increase in the Aβ42/Aβ40 ratio (p < 0.002). Analysis of GDNF levels did not indicate any significant effects. There were no significant effects of gender and no significant ethnicity with gender interactions on any analyte. Effect size calculations indicated "medium" to "very large" effects. CONCLUSION: S100B is typically elevated in AD cases; however, the increased levels in African Americans here may be indicative of increased severity in specific populations. Increased Aβ42/Aβ40 ratios in the current study are compatible with increased disease severity and might indicate increased AD pathogenesis in African Americans. Overall, these results are compatible with a hypothesis of increased neuroinflammation in African Americans with AD.

Neuroimaging Feature Terminology: A Controlled Terminology for the Annotation of Brain Imaging Features. - Iyappan, Anandhi; Younesi, Erfan; Redolfi, Alberto; Vrooman, Henri; Khanna, Shashank; Frisoni, Giovanni B; Hofmann-Apitius, Martin (J Alzheimers Dis, 2017)
Ontologies and terminologies are used for interoperability of knowledge and data in a standard manner among interdisciplinary research groups. Existing imaging ontologies capture general aspects of the imaging domain as a whole such as methodological concepts or calibrations of imaging instruments. However, none of the existing ontologies covers the diagnostic features measured by imaging technologies in the context of neurodegenerative diseases. Therefore, the Neuro-Imaging Feature Terminology (NIFT) was developed to organize the knowledge domain of measured brain features in association with neurodegenerative diseases by imaging technologies. The purpose is to identify quantitative imaging biomarkers that can be extracted from multi-modal brain imaging data. This terminology attempts to cover measured features and parameters in brain scans relevant to disease progression. In this paper, we demonstrate the systematic retrieval of measured indices from literature and how the extracted knowledge can be further used for disease modeling that integrates neuroimaging features with molecular processes.

Neuronal Expression of Truncated Tau Efficiently Promotes Neurodegeneration in Animal Models: Pitfalls of Toxic Oligomer Analysis. - Skrabana, Rostislav; Kovacech, Branislav; Filipcik, Peter; Zilka, Norbert; Jadhav, Santosh; Smolek, Tomas; Kontsekova, Eva; Novak, Michal (J Alzheimers Dis, 2017)
Animal models of neurodegeneration induced by neuronal expression of truncated tau protein emerge as an important tool for understanding the pathogenesis of human tauopathies and for therapy development. Here we highlight common features of truncated tau models and make a critical assessment of possible pitfalls in their analysis. Particularly, the amount of soluble tau oligomers, which are suspected to be neurotoxic agents participating on the spreading of pathology inside the brain, may be overestimated due to a post-lysis oxidative tau oligomerization. Using a mouse brain lysate spiked with recombinant truncated and full length tau forms, we show that tau oligomers might inadvertently be produced during the isolation procedure. This finding is further corroborated by the analysis of brain lysates originated from a mouse model expressing truncated tau variant. Our results underline the necessity of thiol-protecting conditions during the analysis of tau oligomers involved in the etiopathogenesis of various tauopathies including Alzheimer's disease.

Neuroprotective Effect of TREM-2 in Aging and Alzheimer's Disease Model. - Raha, Animesh Alexander; Henderson, James W; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Friedland, Robert P; Zaman, Shahid H; Raha-Chowdhury, Ruma (J Alzheimers Dis, 2017)
Neuroinflammation and activation of innate immunity are early events in neurodegenerative diseases including Alzheimer's disease (AD). Recently, a rare mutation in the gene Triggering receptor expressed on myeloid cells 2 (TREM2) has been associated with a substantial increase in the risk of developing late onset AD. To uncover the molecular mechanisms underlying this association, we investigated the RNA and protein expression of TREM2 in APP/PS1 transgenic mice. Our findings suggest that TREM2 not only plays a critical role in inflammation, but is also involved in neuronal cell survival and in neurogenesis. We have shown that TREM2 is a soluble protein transported by macrophages through ventricle walls and choroid plexus, and then enters the brain parenchyma via radial glial cells. TREM2 protein is essential for neuroplasticity and myelination. During the late stages of life, a lack of TREM2 protein may accelerate aging processes and neuronal cell loss and reduce microglial activity, ultimately leading to neuroinflammation. As inflammation plays a major role in neurodegenerative diseases, a lack of TREM2 could be a missing link between immunomodulation and neuroprotection.

Neuropsychiatric Symptoms and Alzheimer's Disease Biomarkers Predict Driving Decline: Brief Report. - Babulal, Ganesh M; Stout, Sarah H; Head, Denise; Holtzman, David M; Fagan, Anne M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2017)
We examined whether neuropsychiatric symptoms (NPS) interact with cerebrospinal fluid (CSF) biomarkers (amyloid-β42 [Aβ42], tau, phosphorylated tau181 [ptau181], tau/Aβ42, and ptau181/Aβ42) of Alzheimer's disease pathology to predict driving decline among cognitively-normal older adults (N = 116) aged ≥65. Cox proportional hazards models examined time to receiving a rating of marginal or fail on the driving test. Age, education, and gender were adjusted in the models. Participants with more abnormal CSF (Aβ42, tau/Aβ42, ptau181/Aβ42) and NPS were faster to receive a marginal/fail on the road test compared to those without NPS. NPS interact with abnormal CSF biomarkers to impact driving performance among cognitively-normal older adults.

New Gold in Them Thar Hills: Testing a Novel Supply Route for Plant-Derived Galanthamine. - Fraser, Mariecia D; Davies, John R T; Chang, Xianmin (J Alzheimers Dis, 2017)
Many secondary plant compounds are synthesized in response to stressed growing conditions. We tested the feasibility of exploiting this feature in a novel strategy for the commercial production of the plant alkaloid galanthamine. Experimental lines of Narcissus pseudonarcissus were established under marginal upland permanent pasture at four different sites. Over 80% of bulbs successfully established at each site. There was no effect of altitude or planting density on galanthamine concentrations within vegetative tissues, which were higher than anticipated. The results confirm that planting N. pseudonarcissus under grass competition in upland areas could offer a novel and sustainable source of plant-derived galanthamine.

No Genetic Overlap Between Circulating Iron Levels and Alzheimer's Disease. - Lupton, Michelle K; Benyamin, Beben; Proitsi, Petroula; Nyholt, Dale R; Ferreira, Manuel A; Montgomery, Grant W; Heath, Andrew C; Madden, Pamela A; Medland, Sarah E; Gordon, Scott D; Lovestone, Simon; Tsolaki, Magda; et al. (J Alzheimers Dis, 2017)
Iron deposition in the brain is a prominent feature of Alzheimer's disease (AD). Recently, peripheral iron measures have also been shown to be associated with AD status. However, it is not known whether these associations are causal: do elevated or depleted iron levels throughout life have an effect on AD risk? We evaluate the effects of peripheral iron on AD risk using a genetic profile score approach by testing whether variants affecting iron, transferrin, or ferritin levels selected from GWAS meta-analysis of approximately 24,000 individuals are also associated with AD risk in an independent case-control cohort (n∼10,000). Conversely, we test whether AD risk variants from a GWAS meta-analysis of approximately 54,000 account for any variance in iron measures (n∼9,000). We do not identify a genetic relationship, suggesting that peripheral iron is not causal in the initiation of AD pathology.

Non-Phosphorylated Tau as a Potential Biomarker of Alzheimer's Disease: Analytical and Diagnostic Characterization. - Lewczuk, Piotr; Lelental, Natalia; Lachmann, Ingolf; Holzer, Max; Flach, Katharina; Brandner, Sebastian; Engelborghs, Sebastiaan; Teunissen, Charlotte E; Zetterberg, Henrik; Molinuevo, José Luis; Mroczko, Barbara; Blennow, Kaj; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Virtually nothing is known about a potential diagnostic role of non-phospho-epitopes of Tau (Non-P-Tau) in cerebrospinal fluid (CSF). OBJECTIVE: To establish and analytically and clinically characterize the first assay capable to measure concentrations of Non-P-Tau in human CSF. METHODS: An antibody (1G2) was developed that selectively binds to the Tau molecule non-phosphorylated at the positions T175 and T181, and was used in establishing a sandwich ELISA capable to measure Non-P-Tau in human CSF, following analytical and clinical validation of the method. RESULTS: The 1G2 antibody shows decreasing reactivity to tau peptides containing phosphorylation mainly at positions T175 and T181. Detection limit of the assay is 25 pg/ml; the coefficients of variation (CVs) of the optical densities of the repeated standard curves were between 3.6-15.9%. Median intra-assay imprecision of double measurements was 4.8%; inter-assay imprecision was in the range of 11.2% - 15.3%. Non-P-Tau concentrations are stable in the CSF samples sent to distinct laboratories under ambient temperature; inter-laboratory variation was approximately 30%. The Non-P-Tau CSF concentrations were highly significantly increased in patients with Alzheimer's disease in stage of mild cognitive impairment or dementia (AD/MCI, n = 58, 109.2±32.0 pg/mL) compared to the non-demented Controls (n = 42, 62.1±9.3 pg/mL, p < 0.001). At the cut-off of 78.3 pg/mL, the sensitivity and the specificity were 94.8% and 97.6%, respectively. CONCLUSION: For the first time, an assay is reported to reliably measure concentrations of non-phosphorylated Tau in human CSF.

Novel Blood-Based Biomarkers of Cognition, Stress, and Physical or Cognitive Training in Older Adults at Risk of Dementia: Preliminary Evidence for a Role of BDNF, Irisin, and the Kynurenine Pathway. - Küster, Olivia C; Laptinskaya, Daria; Fissler, Patrick; Schnack, Cathrin; Zügel, Martina; Nold, Verena; Thurm, Franka; Pleiner, Sina; Karabatsiakis, Alexander; von Einem, Björn; Weydt, Patrick; Liesener, André; et al. (J Alzheimers Dis, 2017)
Psychosocial stress and physical, cognitive, and social activity predict the risk of cognitive decline and dementia. The aim of this study was to elucidate brain-derived neurotrophic factor (BDNF), irisin, and the kynurenine pathway (KP) as potential underlying biological correlates. We evaluated associations of irisin and the KP with BDNF in serum and with cognition, stress, and activities. Furthermore, changes in serum concentrations of BDNF, irisin, and KP metabolites were investigated after physical or cognitive training. Forty-seven older adults at risk of dementia were assigned to 10 weeks of physical training, cognitive training, or a wait-list control condition. Previous physical, cognitive, and social activities and stressful life events were recorded; global cognition, episodic memory, and executive functions were assessed. Serum levels of L-kynurenine, kynurenic acid, 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN) were determined by validated assays based on liquid chromatography coupled to tandem mass spectrometry. BDNF and irisin serum levels were determined with enzyme-linked immunosorbent assays. BDNF and irisin correlated positively with global cognition and episodic memory, while the neurotoxic metabolite QUIN correlated negatively with executive functions. Stressful life events were associated with reduced BDNF and increased 3-HK. 3-HK decreased after cognitive training, while BDNF tended to increase after physical training. This suggests that psychosocial stress as well as cognitive and physical training may impact BDNF serum levels and the KP. Irisin and QUIN may constitute novel serum biomarkers of cognitive impairment, in addition to BDNF. Larger scale trials are needed to replicate and extend these novel findings.

One-Year Evolution of Behavioral and Psychological Symptoms of Dementia in Patients Initially Hospitalized in Cognitive Behavioral Units: The EVITAL Prospective Cohort. - Rouch, Isabelle; Pongan, Elodie; Trombert, Béatrice; Fabre, Florence; Auguste, Nicolas; Sellier, Claire; Freulon, Magalie; Jacqueline, Sophie; Federico, Denis; Mouchoux, Christelle; Martin-Gaujard, Géraldine; Krolak-Salmon, Pierre; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The 2008-2012 French Alzheimer's Plan has provided hospital Cognitive and Behavioral Units (CBU) to improve the management of patients with productive behavioral and psychological symptoms of dementia (BPSD). Little is known concerning the behavioral outcome of these patients after discharge. OBJECTIVE: The present study investigated the long-term evolution of BPSD over one year after CBU discharge. METHODS: The EVITAL cohort included 221 participants admitted to the CBUs of 3 French hospitals. BPSD were collected using the Neuropsychiatric Inventory (NPI) at admission and 3, 6, and 12 months after hospitalization. The global NPI score evolution was assessed using a linear mixed-effect model. A four-factor model of the NPI including behavioral dyscontrol, psychosis, mood, and agitation subscores was also analyzed. RESULTS: Our analysis focused on 148 patients followed up during 12 months and evaluated at each visit. The global NPI score was 48.5 (SD 21.7) at baseline, 28.8 (SD 18.7) at 3-month, 23.2 (SD 16.4) at 6-month and 20.9 (SD 15.9) at 12-month follow-up. The score significantly decreased from baseline to follow-up (F = 109.3 p < 0.0001). Moreover, the decrease was observed for each NPI subscores. The Clinical Dementia Rating (CDR) scale score was significantly linked to the baseline NPI score (t = 2.76, p = 0.009). Conversely, the NPI decline was observed whatever the CDR level. CONCLUSION: The present study showed a decrease in the global NPI score and all its subscores during the year following the CBU hospitalization, regardless of the initial CDR score.

Optical Coherence Tomography Reveals Retinal Neuroaxonal Thinning in Frontotemporal Dementia as in Alzheimer's Disease. - Ferrari, Laura; Huang, Su-Chun; Magnani, Giuseppe; Ambrosi, Alessandro; Comi, Giancarlo; Leocani, Letizia (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) and frontotemporal dementia (FTD) are leading causes of cognitive decline. Optical coherence tomography (OCT) allows the measurement of thickness of retinal neuroaxonal layers. While in AD and mild cognitive impairment (MCI), retinal nerve fiber layer (RNFL) thinning is frequently reported, less information is available on ganglion cell layer-inner plexiform layer (GCL-IPL). Data on FTD are lacking. OBJECTIVE: To obtain cross-sectional information on RNFL and GCL-IPL thickness among MCI, AD, FTD, and healthy controls (HC), and their correlations with dementia severity. METHODS: Peripapillary OCT scans were obtained in 27 MCI, 39 AD, 17 FTD, 49 HC using high-definition Heidelberg Spectral-domain OCT, with RNFL and GCL-IPL thickness measurement. Statistical analysis tested group effects and correlation with gender, disease duration and severity (Mini-Mental State Examination, MMSE). RESULTS: RNFL showed a significant group effect [F(4,132) = 3.786, p = 0.006], being reduced versus controls in MCI (p = 0.033), moderate AD (p = 0.025), and FTD (p < 0.001), and versus mild AD in FTD (p = 0.042). GCL-IPL showed a significant group effect as well [F(4,121) = 5.104, p < 0.001], with reduction in moderate AD versus HC (p < 0.001), MCI (p = 0.037), and mild AD (p = 0.009); in FTD versus HC (p = 0.002) and mild AD (p = 0.038). In AD, GCL-IPL correlated with MMSE (r = 0.487, p = 0.003), without significant effects of age, gender, or disease duration. CONCLUSION: Retinal neuroaxonal thinning occurs in MCI/AD consistently with previous reports, as well as in FTD. Correlation with disease severity in AD suggests that retinal and brain neurodegeneration may occur in parallel to some extent, and prompts larger studies aimed at providing surrogate endpoints for clinical trials in AD.

Overexpression of Ubiquilin-1 Alleviates Alzheimer's Disease-Caused Cognitive and Motor Deficits and Reduces Amyloid-β Accumulation in Mice. - Adegoke, Oludotun O; Qiao, Fangfang; Liu, Yanying; Longley, Kirsty; Feng, Shelley; Wang, Hongmin (J Alzheimers Dis, 2017)
Ubiquilin-1 (Ubqln1) is a ubiquitin-like protein that has been implicated in Alzheimer's disease (AD). However, whether Ubqln1 modulates learning and memory and alters AD-like behavior and/or pathology has not been determined in animal models. To understand the function of Ubqln1 in vivo, we previously generated Ubqln1 transgenic (TG) mice that overexpress mouse Ubqln1. With the model, we here characterized the TG mouse cognitive behaviors and found that Ubqln1 TG mice showed better spatial learning and memory capabilities than their wild-type littermates in both radial arm water maze and Y-maze tests. Additionally, we crossed the Ubqln1 TG mice with the AβPPswe/PSEN1dE9 double transgenic AD mouse to generate the AD/Ubqln1 triple TG (AD/TG) mice. Our results suggest that at 12 months of age following the onset of AD, AD/TG mice showed better spatial learning and memory than AD mice. AD/TG mice also exhibited better motor function than AD mice at the same age. Furthermore, compared to AD mice, AD/TG mice showed significant reduction in amyloid-β 40 (Aβ40) and Aβ42 levels in the cerebral cortex and in the hippocampus at the post-onset stage. The number of Aβ plaques was significantly decreased in the cerebral cortex of AD/TG mice at this post-onset stage. Moreover, mature AβPP level in AD/TG hippocampus was lower than that in AD hippocampus. These data not only provide a direct link between overexpression of Ubqln1 and altered learning and memory, but also raise the possibility that Ubqln1 is a potential therapeutic target for treating AD and possibly other neurodegenerative disorders.

PE859, A Novel Curcumin Derivative, Inhibits Amyloid-β and Tau Aggregation, and Ameliorates Cognitive Dysfunction in Senescence-Accelerated Mouse Prone 8. - Okuda, Michiaki; Fujita, Yuki; Hijikuro, Ichiro; Wada, Mei; Uemura, Takuya; Kobayashi, Yukako; Waku, Tomonori; Tanaka, Naoki; Nishimoto, Takaaki; Izumi, Yasuhiko; Kume, Toshiaki; Akaike, Akinori; et al. (J Alzheimers Dis, 2017)
Aggregation of amyloid-β (Aβ) and tau plays a crucial role in the onset and progression of Alzheimer's disease (AD). Therefore, the inhibition of Aβ and tau aggregation may represent a potential therapeutic target for AD. Herein, we designed and synthesized both Aβ and tau dual aggregation inhibitors based on the structure of curcumin and developed the novel curcumin derivative PE859. In this study, we investigated the inhibitory activity of PE859 on Aβ aggregationin vitro and the therapeutic effects of PE859 on cognitive dysfunction via dual inhibition of Aβ and tau aggregation in vivo. PE859 inhibited Aβ aggregation in vitro and protected cultured cells from Aβ-induced cytotoxicity. Furthermore, PE859 ameliorated cognitive dysfunction and reduced the amount of aggregated Aβ and tau in brains of senescence-accelerated mouse prone 8 (SAMP8). These results warrant consideration of PE859 as a candidate drug for AD.

PET Tau and Amyloid-β Burden in Mild Alzheimer's Disease: Divergent Relationship with Age, Cognition, and Cerebrospinal Fluid Biomarkers. - Koychev, Ivan; Gunn, Roger N; Firouzian, Azadeh; Lawson, Jennifer; Zamboni, Giovanna; Ridha, Basil; Sahakian, Barbara J; Rowe, James B; Thomas, Alan; Rochester, Lynn; Ffytche, Dominic; Howard, Robert; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Combining PET amyloid-β (Aβ) and tau imaging may be critical for tracking disease progression in Alzheimer's disease (AD). OBJECTIVE: We sought to characterize the relationship between Aβ and tau ligands as well as with other measures of pathology. METHODS: We conducted a multi-center observational study in early AD (MMSE >20) participants aged 50 to 85 y. The schedule included cognitive assessments (ADAS-Cog) and CSF measurement of Aβ and tau at baseline and 6 months; PET-CT imaging with Aβ ([18F]AV45) and tau ([18F]AV1451) ligands at baseline. RESULTS: 22 participants took part in the study with 20 completing its 6-month duration and 12 having both tau and amyloid PET. The PET biomarker analysis revealed a strong negative correlation between age and tau in multiple regions. Entorhinal cortex tau and age interacted significantly in terms of cognitive change over 6 months which may have been to older participants deteriorating faster despite lower levels of cortical tau. Cortical Aβ associated with entorhinal cortex tau while CSF tau/Aβ ratio correlated strongly with cortical tau but not Aβ. CONCLUSION: The negative relationship between age and cortical tau whereby younger patients with mild AD had relatively greater tau burden is potentially important. It suggests that younger-age onset AD may be primarily driven by tau pathology while AD developing later may depend on a multitude of pathological mechanisms. These data also suggest that PET-tau performs better than PET-amyloid in predicting the best validated AD diagnostic marker- the CSF total tau/Aβ ratio.

Physical Exercise Moderates the Relationship of Apolipoprotein E (APOE) Genotype and Dementia Risk: A Population-Based Study. - Fenesi, Barbara; Fang, Hanna; Kovacevic, Ana; Oremus, Mark; Raina, Parminder; Heisz, Jennifer J (J Alzheimers Dis, 2017)
Genetics and lifestyle independently determine dementia risk, but the interaction is unclear. We assessed the interactive relationship of apolipoprotein E (APOE) genotype and physical exercise on dementia risk over a 5-year period in 1,646 older adults from the Canadian Study of Health and Aging who were dementia-free at baseline. Physical exercise moderated the relationship between genotype and dementia (p < 0.01). Specifically, for APOE ɛ4 non-carriers, the odds of developing dementia were higher in non-exercisers than exercisers (OR = 1.98, 95% CI = 1.44, 2.71, p < 0.001), whereas, for APOE ɛ4 carriers, the odds of developing dementia were not significantly different between non-exercisers and exercisers (OR = 0.71, 95% CI = 0.46, 1.31, p = 0.34). Given that most individuals are not at genetic risk, physical exercise may be an effective strategy for preventing dementia.

Polymorphonuclear Neutrophil Functions are Differentially Altered in Amnestic Mild Cognitive Impairment and Mild Alzheimer's Disease Patients. - Le Page, Aurélie; Lamoureux, Julie; Bourgade, Karine; Frost, Eric H; Pawelec, Graham; Witkowski, Jacek M; Larbi, Anis; Dupuis, Gilles; Fülöp, Tamás (J Alzheimers Dis, 2017)
The mechanisms of neurodegeneration in Alzheimer's disease (AD) remain under investigation. Alterations in the blood-brain barrier facilitate exchange of inflammatory mediators and immune cells between the brain and the periphery in AD. Here, we report analysis of phenotype and functions of polymorphonuclear neutrophils (PMN) in peripheral blood from patients with amnestic mild cognitive impairment (aMCI, n = 13), patients with mild AD (mAD, n = 15), and healthy elderly controls (n = 13). Results showed an increased expression of CD177 in mAD but not in healthy or aMCI patients. IL-8 stimulated increased expression of the CD11b integrin in PMN of healthy subjects in vitro but PMN of aMCI and mAD patients failed to respond. CD14 and CD16 expression was lower in PMN of mAD but not in aMCI individuals relative to controls. Only PMN of aMCI subjects expressed lower levels of CD88. Phagocytosis toward opsonized E. coli was differentially impaired in PMN of aMCI and mAD subjects whereas the capacity to ingest Dextran particles was absent only in mAD subjects. Killing activity was severely impaired in aMCI and mAD subjects whereas free radical production was only impaired in mAD patients. Inflammatory cytokine (TNFα, IL-6, IL-1β, IL-12p70) and chemokine (MIP-1α, MIP-1β, IL-8) production in response to LPS stimulation was very low in aMCI and nearly absent in mAD subjects. TLR2 expression was low only in aMCI. Our data showed a differentially altered capacity of PMN of aMCI and mAD subjects to respond to pathological aggression that may impact impaired responses associated with AD development.

Preclinical Amyloid-β and Axonal Degeneration Pathology in Delirium. - Idland, Ane-Victoria; Wyller, Torgeir Bruun; Støen, Randi; Eri, Lars Magne; Frihagen, Frede; Ræder, Johan; Chaudhry, Farrukh Abbas; Hansson, Oskar; Zetterberg, Henrik; Blennow, Kaj; Bogdanovic, Nenad; Brækhus, Anne; et al. (J Alzheimers Dis, 2017)
BACKGROUND: The clinical relevance of brain β-amyloidosis in older adults without dementia is not established. As delirium and dementia are strongly related, studies on patients with delirium may give pathophysiological clues. OBJECTIVE: To determine whether the Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers amyloid-β 1-42 (Aβ42), total tau (T-tau), and phosphorylated tau (P-tau) are associated with delirium in hip fracture patients with and without dementia. METHODS: CSF was collected in conjunction to spinal anesthesia in 129 patients. Delirium was assessed using the Confusion Assessment Method once daily in all patients, both pre- and postoperatively. The diagnosis of dementia at admission was based upon clinical consensus. CSF levels of Aβ42, T-tau, and P-tau were analyzed. RESULTS: In patients without dementia, we found lower CSF Aβ42 levels (median, 310 ng/L versus 489 ng/L, p = 0.006), higher T-tau levels (median, 505 ng/L versus 351 ng/L, p = 0.02), but no change in P-tau in patients who developed delirium (n = 16) compared to those who remained lucid (n = 49). Delirious patients also had lower ratios of Aβ42 to T-tau (p < 0.001) and P-tau (p = 0.001) relative to those without delirium. CSF Aβ42 and T-tau remained significantly associated with delirium status in adjusted analyses. In patients with dementia, CSF biomarker levels did not differ between those with (n = 54) and without delirium (n = 10). CONCLUSION: The reduction in CSF Aβ42, indicating β-amyloidosis, and increase in T-tau, indicating neurodegeneration, in hip fracture patients without dementia developing delirium indicates that preclinical AD brain pathology is clinically relevant and possibly plays a role in delirium pathophysiology.

Predicting Development of Amyotrophic Lateral Sclerosis in Frontotemporal Dementia. - Van Langenhove, Tim; Piguet, Olivier; Burrell, James R; Leyton, Cristian; Foxe, David; Abela, Melissa; Bartley, Lauren; Kim, Woojin S; Jary, Eve; Huang, Yue; Dobson-Stone, Carol; Kwok, John B; et al. (J Alzheimers Dis, 2017)
BACKGROUND: A proportion of patients with frontotemporal dementia (FTD) also develop amyotrophic lateral sclerosis (ALS). OBJECTIVE: We aimed to establish the risk of developing ALS in patients presenting with FTD and to identify the relevant clinical variables associated with progression from FTD to FTD-ALS. METHODS: Of 218 consecutive patients with FTD, 10.1% had a dual FTD-ALS diagnosis at presentation. The remaining 152 FTD patients with follow-up of at least 12 months were included in the present study. We calculated the rate of progression to FTD-ALS and compared the baseline characteristics of FTD patients who developed ALS to those who did not develop ALS. RESULTS: Five percent of FTD patients developed ALS. The incidence rate of ALS was 6.7/100 patient-years in patients with FTD symptoms since 1 year, which declined with duration of FTD symptoms. No FTD patients developed ALS after 5 years. Five out of 8 FTD patients who developed ALS had presented with a mixed behavioral variant FTD and progressive non-fluent aphasia (bvFTD+PNFA) phenotype, 2 with bvFTD, and 1 with PNFA. Progression to FTD-ALS was significantly more frequent in patients with bvFTD+PNFA compared to those without this phenotype (p < 0.0001, OR 38.3, 95% CI: 7.3 to 199.2), and in FTD patients who carried the C9orf72 repeat expansion compared to those without the repeat expansion (p = 0.02, OR 8.0, 95% CI: 1.7 to 38.6). CONCLUSIONS: FTD patients with a mixed bvFTD+PNFA phenotype and with a C9orf72 repeat expansion should be closely monitored for the possible development of ALS. The risk of developing ALS in FTD appears to decline with the duration of FTD symptoms.

Predictors of Discharge Destinations and Three-Month Evolution of Patients Initially Hospitalized in a Cognitive Behavioral Unit. - Pongan, Elodie; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Federico, Denis; Sellier, Claire; Auguste, Nicolas; Fabre, Florence; Laurent, Bernard; Trombert-Paviot, Béatrice; Rouch, Isabelle (J Alzheimers Dis, 2017)
BACKGROUND: Previous studies showed that a third of patients living at home entered an institution after hospitalization in Cognitive and Behavioral Units (CBUs). OBJECTIVE: The main objective of this study was to identify predictors of discharge destination for these patients. The secondary objective was to estimate whether institutionalization can have an impact on a patient's long-term prognosis. METHODS: The study population was selected from the EVITAL study and included 140 participants living at home before hospitalization in CBUs. Factors favoring nursing-home admission were investigated and the impact of discharge destinations (i.e., home or nursing home) on patients' prognosis was examined. RESULTS: Institutionalized patients were more likely to be women (F = 4.7; p = 0.03), with a higher dementia severity (F = 9.82; p = 0.007), often living alone (F = 19.69; p = 0.001), with a caregiver other than spouse (F = 8.93; p = 0.003), and with a higher patient quality of life (QoL) according to the caregiver (F = 11.73; p = 0.001). When using multivariate logistic linear regressions, we showed a relationship between marital status (OR = 0.19, 95% CI: 0.08-0.43, p < 0.001), dementia severity (OR = 0.15, 95% CI: 0.03-0.79, p = 0.03), QoL (OR = 0.88, 95% CI: 0.79-0.98, p = 0.017), and institutionalization. At three months, a higher overall rate of rehospitalization (F = 12.21; p < 0.001) and rehospitalization for behavioral and psychological symptoms of dementia (F = 6.76; p = 0.006) were observed for patients staying at home after CBU discharge. CONCLUSION: Our study allows for a better understanding of the institutionalization risk factors of the patients hospitalized in CBUs. Identification of these factors could help clinicians to better support patients and to help the transition to be smoother. Moreover, our results suggest that prognosis of institutionalized patients is not unfavorable when compared with patients staying at home.

Prion Protein Interactome: Identifying Novel Targets in Slowly and Rapidly Progressive Forms of Alzheimer's Disease. - Zafar, Saima; Shafiq, Mohsin; Younas, Neelam; Schmitz, Matthias; Ferrer, Isidre; Zerr, Inga (J Alzheimers Dis, 2017)
Rapidly progressive Alzheimer's disease (rpAD) is a variant of AD distinguished by a rapid decline in cognition and short disease duration from onset to death. While attempts to identify rpAD based on biomarker profile classifications have been initiated, the mechanisms which contribute to the rapid decline and prion mimicking heterogeneity in clinical signs are still largely unknown. In this study, we characterized prion protein (PrP) expression, localization, and interactome in rpAD, slow progressive AD, and in non-dementia controls. PrP along with its interacting proteins were affinity purified with magnetic Dynabeads Protein-G, and were identified using Q-TOF-ESI/MS analysis. Our data demonstrated a significant 1.2-fold decrease in di-glycosylated PrP isoforms specifically in rpAD patients. Fifteen proteins appeared to interact with PrP and only two proteins3/4histone H2B-type1-B and zinc alpha-2 protein3/4were specifically bound with PrP isoform isolated from rpAD cases. Our data suggest distinct PrP involvement in association with the altered PrP interacting protein in rpAD, though the pathophysiological significance of these interactions remains to be established.

Protein Expression of BACE1 is Downregulated by Donepezil in Alzheimer's Disease Platelets. - Sarno, Tamires Alves; Talib, Leda Leme; Joaquim, Helena Passarelli Giroud; Bram, Jessyka Maria de França; Gattaz, Wagner Farid; Forlenza, Orestes Vicente (J Alzheimers Dis, 2017)
BACKGROUND: Abnormal amyloid-β protein precursor (AβPP) metabolism is a key feature of Alzheimer's disease (AD). Platelets contain most of the enzymatic machinery required for AβPP processing, and correlates of intracerebral abnormalities have been demonstrated in platelets of patients with AD. Thus, AβPP-related molecules in platelets may be regarded as peripheral markers of AD. OBJECTIVE: We sought to determine the protein expression of the AβPP secretases (ADAM10, BACE1, and PSEN1) and AβPP ratio in platelets of patients with mild or moderate AD compared to healthy controls. We further determined whether the protein expression of these markers might be modified by chronic treatment with donepezil. METHODS: Platelet samples were obtained from patients and controls at baseline and after 3 and 6 months of continuous treatment with therapeutic doses of donepezil. The protein expression of platelet markers was determined by western blotting. RESULTS: AD patients had a significant decrease in AβPP ratio, ADAM10, and PSEN1 compared to controls at baseline, but these differences were not modified by the treatment. Nonetheless, a significant reduction in the protein expression of BACE1 was observed in patients treated with donepezil for 6 months. CONCLUSION: Our results corroborate previous findings from our group and others of decreased AβPP ratio and protein expression of ADAM10 in AD. We further show that PSEN1 is decreased in AD platelets, and that the protein expression of BACE1 is downregulated by chronic treatment with donepezil. This effect may be interpreted as evidence of disease modification.

Psychosocial Risk and Protective Factors and Incident Mild Cognitive Impairment and Dementia in Community Dwelling Elderly: Findings from the Singapore Longitudinal Ageing Study. - Rawtaer, Iris; Gao, Qi; Nyunt, Ma Shwe Zin; Feng, Lei; Chong, Mei Sian; Lim, Wee Shiong; Lee, Tih-Shih; Yap, Philip; Yap, Keng Bee; Ng, Tze Pin (J Alzheimers Dis, 2017)
BACKGROUND: Indicators of social isolation or support such as living alone, loneliness, being married, and life satisfaction are possible psychosocial risk and protective factors for dementia. OBJECTIVE: We investigate the associations of these overlapping psychosocial factors with incident MCI-dementia (neurocognitive disorder) in a population cohort. METHODS: Using data from 1601 participants of the Singapore Longitudinal Ageing Study (SLAS) who were free of MCI or dementia at baseline and followed up to 8 years, we estimated hazards ratio (HR) of association of living alone, loneliness, being married, and high life satisfaction with incident MCI-dementia. RESULTS: In univariate analyses, individual HRs of association with incident MCI-dementia for living alone was 1.86 [1.18 - 2.95], (p = 0.008), loneliness was 1.26 [0.86 - 1.84], (p = 0.23), being married was 0.54 [0.39 - 0.75] (p < 0.0001), and being very satisfied with life was 0.59 [0.38-0.91]), (p = 0.017). Adjusted mutually for other psychosocial variables, and for age, sex, education, ethnicity, smoking, alcohol, dyslipidemia, hypertension, diabetes, central obesity, history of stroke or heart disease, APOE-ɛ4, depression, physical, social, and productive activities, only being married (0.68 [0.47-0.99], p = 0.044), and being very satisfied with life (0.61 [0.39 - 0.96], p = 0.034) remained significant variables associated with lower risks of developing MCI-dementia. CONCLUSION: Individuals who were married and those who were very satisfied with life are protected against the risk of developing MCI and dementia. Controlling for the adverse effects of being without spousal support and low life satisfaction, living alone or a feeling of loneliness were not associated with increased risk of MCI-dementia.

Psychotic Symptoms Associated with Poor Renal Function in Mild Cognitive Impairment and Dementias. - Kunschmann, Ralf; Busse, Stefan; Frodl, Thomas; Busse, Mandy (J Alzheimers Dis, 2017)
Patients suffering from cognitive decline such as mild cognitive impairment or neurodegenerative disorders including Alzheimer's dementia, vascular dementia, frontotemporal dementia, and Lewy body dementia are often accompanied by symptoms like psychosis, depression, agitation, and apathy. Aging increases not only the prevalence of dementia but also the development of kidney disorders, which had emerged as possible risk factor of cognitive impairment and dementia. However, a contribution of renal dysfunction to psychosis associated with cognitive decline remains to be investigated. We addressed the question whether patients diagnosed with mild cognitive impairment or dementia and co-symptoms show alterations in serum parameters. Analyzing 309 patients in total, we detected a positive correlation between the occurrence of psychotic symptoms and increased retention parameters in serum, including creatinine and urea levels and the estimated glomerular filtration rates. This was in particular detected in female patients. In male patients, psychotic symptoms were associated with an increased number of leukocytes in blood. We propose that clinicians should be aware of psychotic symptoms in patients with reduced cognitive functions that could be associated with changes in the retention parameters.

Pupillary Responses as a Biomarker of Early Risk for Alzheimer's Disease. - Granholm, Eric L; Panizzon, Matthew S; Elman, Jeremy A; Jak, Amy J; Hauger, Richard L; Bondi, Mark W; Lyons, Michael J; Franz, Carol E; Kremen, William S (J Alzheimers Dis, 2017)
Task-evoked pupillary responses may be a psychophysiological biomarker of early risk for mild cognitive impairment (MCI) and Alzheimer's disease (AD). Pupil dilation during cognitive tasks reflects cognitive effort until compensatory capacity is surpassed and performance declines are manifest, and reflects activation in the locus coeruleus, where degenerative changes have been found in the earliest stages of AD. We recorded pupillary responses during digit span recall in 918 participants ages 56-66. Despite normal performance, amnestic single-domain MCI (S-MCI) participants showed greater pupil dilation than non-amnestic S-MCI and cognitively normal (CN) participants at lower cognitive loads. Multi-domain MCI (M-MCI) participants failed to modulate effort across cognitive loads and showed poorer performance. Pupillary responses differentiated MCI and CN groups. Amnestic S-MCI participants required compensatory effort to maintain performance, consistent with increased risk for decline. Greater effort in CN individuals might indicate risk for MCI. Results are consistent with dysfunction in locus coeruleus-linked brain systems. This brief task shows promise as a biomarker for early MCI and AD risk prediction.

Quantitative Comparison of Dense-Core Amyloid Plaque Accumulation in Amyloid-β Protein Precursor Transgenic Mice. - Liu, Peng; Reichl, John H; Rao, Eshaan R; McNellis, Brittany M; Huang, Eric S; Hemmy, Laura S; Forster, Colleen L; Kuskowski, Michael A; Borchelt, David R; Vassar, Robert; Ashe, Karen H; Zahs, Kathleen R (J Alzheimers Dis, 2017)
There exist several dozen lines of transgenic mice that express human amyloid-β protein precursor (AβPP) with Alzheimer's disease (AD)-linked mutations. AβPP transgenic mouse lines differ in the types and amounts of Aβ that they generate and in their spatiotemporal patterns of expression of Aβ assemblies, providing a toolkit to study Aβ amyloidosis and the influence of Aβ aggregation on brain function. More complete quantitative descriptions of the types of Aβ assemblies present in transgenic mice and in humans during disease progression should add to our understanding of how Aβ toxicity in mice relates to the pathogenesis of AD. Here, we provide a direct quantitative comparison of amyloid plaque burdens and plaque sizes in four lines of AβPP transgenic mice. We measured the fraction of cortex and hippocampus occupied by dense-core plaques, visualized by staining with Thioflavin S, in mice from young adulthood through advanced age. We found that the plaque burdens among the transgenic lines varied by an order of magnitude: at 15 months of age, the oldest age studied, the median cortical plaque burden in 5XFAD mice was already ∼4.5 times that of 21-month-old Tg2576 mice and ∼15 times that of 21-24-month-old rTg9191 mice. Plaque-size distributions changed across the lifespan in a line- and region-dependent manner. We also compared the dense-core plaque burdens in the mice to those measured in a set of pathologically-confirmed AD cases from the Nun Study. Cortical plaque burdens in Tg2576, APPSwePS1ΔE9, and 5XFAD mice eventually far exceeded those measured in the human cohort.

Reduced Cerebral Blood Flow in Mild Cognitive Impairment Assessed Using Phase-Contrast MRI. - de Eulate, Reyes García; Goñi, Irene; Galiano, Alvaro; Vidorreta, Marta; Recio, Miriam; Riverol, Mario; Zubieta, José L; Fernández-Seara, María A (J Alzheimers Dis, 2017)
There is increasing evidence of a vascular contribution to Alzheimer's disease (AD). In some cases, prior work suggests that chronic brain hypoperfusion could play a prime pathogenic role contributing to the accumulation of amyloid-β,while other studies favor the hypothesis that vascular dysfunction and amyloid pathology are independent, although synergistic, mechanisms contributing to cognitive impairment. Vascular dysfunction can be evaluated by assessing cerebral blood flow impairment. Phase contrast velocity mapping by MRI offers a non-invasive means of quantifying the total inflow of blood to the brain. This quantitative parameter could be a sensitive indicator of vascular disease at early stages of AD. In this work, phase contrast MRI was used to evaluate cerebral hemodynamics in patients with subjective memory complaints, amnestic mild cognitive impairment, and mild to moderate AD, and compare them with control subjects. Results showed that blood flow and velocity were decreased in the patients with cognitive dysfunction and the decrease correlated with the degree of cognitive impairment as assessed by means of neuropsychological tests. Total cerebral blood flow measurements were clearly reduced in AD patients, but more importantly appeared to be sensitive enough to distinguish between healthy subjects and those with mild cognitive impairment. A quantitative measurement of total brain blood flow could potentially predict vascular dysfunction and compromised brain perfusion in early stages of AD.

Reduction of RPT6/S8 (a Proteasome Component) and Proteasome Activity in the Cortex is associated with Cognitive Impairment in Lewy Body Dementia. - Alghamdi, Amani; Vallortigara, Julie; Howlett, David R; Broadstock, Martin; Hortobágyi, Tibor; Ballard, Clive; Thomas, Alan J; O'Brien, John T; Aarsland, Dag; Attems, Johannes; Francis, Paul T; Whitfield, David R (J Alzheimers Dis, 2017)
Lewy body dementia is the second most common neurodegenerative dementia and is pathologically characterized by α-synuclein positive cytoplasmic inclusions, with varying amounts of amyloid-β (Aβ) and hyperphosphorylated tau (tau) aggregates in addition to synaptic loss. A dysfunctional ubiquitin proteasome system (UPS), the major proteolytic pathway responsible for the clearance of short lived proteins, may be a mediating factor of disease progression and of the development of α-synuclein aggregates. In the present study, protein expression of a key component of the UPS, the RPT6 subunit of the 19S regulatory complex was determined. Furthermore, the main proteolytic-like (chymotrypsin- and PGPH-) activities have also been analyzed. The middle frontal (Brodmann, BA9), inferior parietal (BA40), and anterior cingulate (BA24) gyrus' cortex were selected as regions of interest from Parkinson's disease dementia (PDD, n = 31), dementia with Lewy bodies (DLB, n = 44), Alzheimer's disease (AD, n = 16), and control (n = 24) brains. Clinical and pathological data available included the MMSE score. DLB, PDD, and AD were characterized by significant reductions of RPT6 (one-way ANOVA, p < 0.001; Bonferroni post hoc test) in prefrontal cortex and parietal cortex compared with controls. Strong associations were observed between RPT6 levels in prefrontal, parietal cortex, and anterior cingulate gyrus and cognitive impairment (p = 0.001, p = 0.001, and p = 0.008, respectively). These findings highlight the involvement of the UPS in Lewy body dementia and indicate that targeting the UPS may have the potential to slow down or reduce the progression of cognitive impairment in DLB and PDD.

Retrograde Amnesia for Episodic and Semantic Memories in Amnestic Mild Cognitive Impairment. - De Simone, Maria Stefania; Fadda, Lucia; Perri, Roberta; De Tollis, Massimo; Aloisi, Marta; Caltagirone, Carlo; Carlesimo, Giovanni Augusto (J Alzheimers Dis, 2017)
Retrograde amnesia (RA), which includes loss of memory for past personal events (autobiographical RA) and for acquired knowledge (semantic RA), has been largely documented in patients with amnestic mild cognitive impairment (aMCI). However, previous studies have produced controversial results particularly concerning the temporal extent of memory impairment. Here we investigated whether, with the onset of hippocampal pathology, age of memory acquisition and retrieval frequency play different roles in modulating the progressive loss of semantic and episodic contents of retrograde memory respectively. For this purpose, aMCI patients and healthy controls were tested for the ability to recall semantic and autobiographical information related to famous public events as a function of both age of acquisition and retrieval frequency. In aMCI patients, we found that the impairment in recollecting past personal incidents was modulated by the combined action of memory age and retrieval frequency, because older and more frequently retrieved episodes are less susceptible to loss than more recent and less frequently retrieved ones. On the other side, we found that the loss of semantic information depended only on memory age, because the remoteness of the trace allows for better preservation of the memory. Our results provide evidence that the loss of the two components of retrograde memory is regulated by different mechanisms. This supports the view that diverse neural mechanisms are involved in episodic and semantic memory trace storage and retrieval, as postulated by the Multiple Trace Theory.

Risk Factors and Pathological Substrates Associated with Agitation/Aggression in Alzheimer's Disease: A Preliminary Study using NACC Data. - Sennik, Simrin; Schweizer, Tom A; Fischer, Corinne E; Munoz, David G (J Alzheimers Dis, 2017)
BACKGROUND: Neuropsychiatric symptoms are common manifestations of Alzheimer's disease (AD). A number of studies have targeted psychosis, i.e., hallucinations and delusions in AD, but few have assessed agitation/aggression in AD. OBJECTIVE: To investigate the risk factors and pathological substrates associated with presence [A(+)] and absence [A(-)] of agitation/aggression (A) in autopsy-confirmed AD. METHODS: Data was collected from the UDS data as of 2015 on the NACC database. Patients were stratified as intermediate (IAD) or high (HAD) pathological load of AD. Clinical diagnoses were not considered; additional pathological diagnoses were treated as variables. Analysis of data did not include a control group or corrections for multiple comparisons. RESULTS: 1,716 patients met the eligibility criteria; 31.2% of the IAD and 47.8% of the HAD patients were A(+), indicating an association with severity of pathology (p = 0.001). Risk factors for A(+) included: age at initial visit, age at death, years of education, smoking (in females), recent cardiac events (in males), and clinical history of traumatic brain injury (TBI) (in males). A history of hypertension was not related to A(+). In terms of comorbidity, clinical diagnosis of Lewy body dementia syndrome was associated with A(+) but the association was not confirmed when pathological diagnosis based on demonstration of Lewy bodies was used as the criterion. The additional presence of phosphorylated TDP-43, but not tau pathologies, was associated with A(+)HAD. Vascular lesions, including lacunes, large arterial infarcts, and severity of atherosclerosis were negatively associated with A(+). Associated symptoms included delusions, hallucinations, and depression, but not irritability, aberrant motor behavior, sleep and night time behavioral changes, or changes in appetite and eating habits. CONCLUSIONS: Smoking, TBI, and phosphorylated TDP-43 are associated with A(+)AD in specific groups, respectively. A(+) is directly associated with AD pathology load and inversely with vascular lesions.

The Road Less Traveled: Alternative Pathways for Action-Verb Processing in Parkinson's Disease. - Abrevaya, Sofía; Sedeño, Lucas; Fitipaldi, Sol; Pineda, David; Lopera, Francisco; Buritica, Omar; Villegas, Andrés; Bustamante, Catalina; Gomez, Diana; Trujillo, Natalia; Pautassi, Ricardo; Ibáñez, Agustín; et al. (J Alzheimers Dis, 2017)
Action verbs are critically embodied in motor brain networks. In Parkinson's disease (PD), damage to the latter compromises access to such words. However, patients are not fully incapable of processing them, as their performance is far from floor level. Here we tested the hypothesis that action-verb processing in PD may rely on alternative disembodied semantic circuits. Seventeen PD patients and 15 healthy controls listened to action verbs and nouns during functional MRI scanning. Using cluster-mass analysis with a permutation test, we assessed task-related functional connectivity considering seeds differentially engaged by action and non-action words (namely, putamen and M1 versus posterior superior temporal lobe, respectively). The putamen seed showed reduced connectivity within the basal ganglia in patients for both lexical categories. However, only action verbs recruited different cortical networks in each group. Specifically, the M1 seed exhibited more anterior connectivity for controls and more posterior connectivity for patients, with no differences in the temporal seed. Moreover, the patients' level of basal ganglia atrophy positively correlated with their reliance on M1-posterior connectivity during action-verb processing. PD patients seem to have processed action verbs via non-motor cortical networks subserving amodal semantics. Such circuits may afford alternative pathways to process words when default embodied mechanisms are disturbed. Moreover, the greater the level of basal ganglia atrophy, the greater the patients' reliance on this alternative route. Our findings offer new insights into differential neurofunctional mechanisms recruited to process action semantics in PD.

The Role of Cerebrovascular Disease on Cognitive and Functional Status and Psychosis in Severe Alzheimer's Disease. - Kim, Julia; Schweizer, Tom A; Fischer, Corinne E; Munoz, David G (J Alzheimers Dis, 2017)
BACKGROUND: The pathophysiology behind psychosis in patients with Alzheimer's disease (AD) remains unknown. Vascular risk factors have been recognized as an important modifier of the clinical presentation of AD. OBJECTIVE: The purpose of our study is to investigate the mechanism through which vascular risk factors mediate psychosis and whether or not it involves cerebrovascular lesions. METHODS: Data was provided by the National Alzheimer's Coordinating Centre. The Uniform Data Set was used to collect information on subject-reported history of vascular risk factors, clinician-reported state of cognitive performance, and presence of psychosis based on the Neuropsychiatric Inventory Questionnaire (NPI-Q). The Neuropathology Data Set was used to evaluate the presence of vascular lesions and the severity of AD pathology. Subjects with high probability of AD based on the NIA/AA Reagan criteria were included in the analysis. RESULTS: We identified 1,459 patients with high probability of AD and corresponding NPI-Q scores. We confirmed the association between hypertension and diabetes on psychosis, specifically in delusions and the co-occurrence of delusions and hallucinations. Furthermore, the presence of white matter rarefaction based on pathological evaluation was associated with hallucinations. A history of vascular risk factors was positively associated with vascular lesions. However, vascular lesions in the presence of vascular risk factors did not increase the likelihood of psychosis. Furthermore, vascular lesions were not associated with greater cognitive or functional impairments in this group with severe AD pathology. CONCLUSION: Vascular risk factors and vascular lesions are independently associated with psychosis in patients with severe AD. However, vascular lesions are not the mechanism through which vascular risk factors mediate psychosis.

Role of Niemann-Pick Type C Disease Mutations in Dementia. - Cupidi, Chiara; Frangipane, Francesca; Gallo, Maura; Clodomiro, Alessandra; Colao, Rosanna; Bernardi, Livia; Anfossi, Maria; Conidi, Maria Elena; Vasso, Franca; Curcio, Sabrina Anna Maria; Mirabelli, Maria; Smirne, Nicoletta; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Several neurological and systemic diseases can cause dementia, beyond Alzheimer's disease. Rare genetic causes are often responsible for dementia with atypical features. Recently, mutations causative for Niemann-Pick type C disease (NPC) have also been implicated in neurodegenerative diseases. NPC is an autosomal recessive lipid storage disorder caused by mutations in NPC1 and NPC2 genes. In adults, clinical presentation mimicking other neurodegenerative diseases makes diagnosis difficult. Recent evidence suggests that heterozygous mutations in NPC genes may take on etiological significance. OBJECTIVE: To investigate the presence of NPC1 and NPC2 mutations in adults affected by neurodegenerative dementia plus. METHODS: We performed a genetic screening on 50 patients using a wide clinical and biochemical approach to characterize the phenotype of mutated patients. RESULTS: Sequencing analysis revealed four different and known heterozygous mutations in NPC1 and NPC2 genes. Patient 1 carried the p. F284LfsX26 in NPC1 and was affected by progressive supranuclear palsy-like syndrome. The remaining three patients showed a corticobasal syndrome and harbored the c.441+1G>A variant of NPC2 (patient 2), the missense p.N222 S mutation associated with the c.1947+8G>C variant in the splice region of intron 12 in NPC1 (patient 3), and the p.V30M mutation in NPC2 (patient 4), respectively. Filipin staining was abnormal in patients 1 and 2. mRNA analysis revealed an altered splicing of the NPC2 gene in patient 2. CONCLUSIONS: Heterozygous mutations of NPC1 and NPC2 genes could contribute to dementia plus, at least in a subset of patients. We highlight the occurrence of NPC1 and NPC2 heterozygous variants in dementia-plus as pathological event.

Role of Suppressor of Cytokine Signaling 3 (SOCS3) in Altering Activated Microglia Phenotype in APPswe/PS1dE9 Mice. - Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Fujikura, Mai; Manabe, Tatsuo; Suzuki, Hiromi; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2017)
In response to changes of the central nervous system environment, microglia are capable of acquiring diverse phenotypes for cytotoxic or immune regulation and resolution of injury. Alzheimer's disease (AD) pathology also induces several microglial activations, resulting in production of pro-inflammatory cytokines and reactive oxygen species or clearance of amyloid-β (Aβ) through phagocytosis. We previously demonstrated that microglial activation and increase in oxidative stress started from the middle age in APPswe/PS1dE9 mice, and hypothesized that M1 activation occurs in middle-aged AD mice by Aβ stimulation. In the present study, we analyzed in vivo expressions of pro-inflammatory cytokines (M1 microglial markers), M2 microglial markers, and suppressor of cytokine signaling (SOCS) family, and examined the microglial phenotypic profile in APPswe/PS1dE9 mice. Then we compared the in vitro gene expression patterns of Aβ- and lipopolysaccharide (LPS)-stimulated primary-cultured microglia. Microglia in APPswe/PS1dE9 mice exhibited an M1-like phenotype, expressing tumor necrosis factor α (TNFα) but not interleukin 6 (IL6). Aβ-stimulated primary-cultured microglia also expressed TNFα but not IL6, whereas LPS-stimulated primary-cultured microglia expressed both pro-inflammatory cytokines. Furthermore, both microglia in APPswe/PS1dE9 mice and Aβ-stimulated primary-cultured microglia expressed SOCS3. Reduction of SOCS3 expression in Aβ-challenged primary-cultured microglia resulted in upregulation of IL6 expression. Our findings indicate that SOCS3 suppresses complete polarization to M1 phenotype through blocking IL6 production, and Aβ-challenged primary-cultured microglia replicate the in vivo gene expression pattern of microglia in APPswe/PS1dE9 mice. Aβ may induce the M1-like phenotype through blocking of IL6 by SOCS3.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Brain; Cells, Cultured; Disease Models, Animal; Female; Humans; Interleukin-6; Lipopolysaccharides; Male; Mice, Inbred C57BL; Mice, Transgenic; Microglia; Neurons; Presenilin-1; Suppressor of Cytokine Signaling 3 Protein; Tumor Necrosis Factor-alpha

S-Adenosylmethionine Attenuates Oxidative Stress and Neuroinflammation Induced by Amyloid-β Through Modulation of Glutathione Metabolism. - Li, Qian; Cui, Jing; Fang, Chen; Liu, Min; Min, Guowen; Li, Liang (J Alzheimers Dis, 2017)
Oxidative stress and neuroinflammation are mainly involved in the pathogenic mechanisms of Alzheimer's disease (AD). Amyloid-β (Aβ), the main component of senile plaques, is a kind of strong inducer of oxidative stress. Glutathione is an endogenous antioxidant protecting cells from oxidative injury. S-adenosylmethionine (SAM) produced in the methionine cycle is the primary methyl donor and the precursor of glutathione. In this study, the Aβ intrahippocampal injection rat model and cultured SH-SY5Y cells were used to explore the neuroprotective effect of SAM. We found that SAM could protect cells against Aβ-induced cellular injury by inhibition of oxidative stress and neuroinflammation. SAM administration could increase the endogenous antioxidant glutathione and potentiate the antioxidant enzymes activities. SAM might act as an antioxidant and be a potential candidate therapy for AD patients.

Sample Size Estimation for Alzheimer's Disease Trials from Japanese ADNI Serial Magnetic Resonance Imaging. - Fujishima, Motonobu; Kawaguchi, Atsushi; Maikusa, Norihide; Kuwano, Ryozo; Iwatsubo, Takeshi; Matsuda, Hiroshi (J Alzheimers Dis, 2017)
BACKGROUND: Little is known about the sample sizes required for clinical trials of Alzheimer's disease (AD)-modifying treatments using atrophy measures from serial brain magnetic resonance imaging (MRI) in the Japanese population. OBJECTIVE: The primary objective of the present study was to estimate how large a sample size would be needed for future clinical trials for AD-modifying treatments in Japan using atrophy measures of the brain as a surrogate biomarker. METHODS: Sample sizes were estimated from the rates of change of the whole brain and hippocampus by the k-means normalized boundary shift integral (KN-BSI) and cognitive measures using the data of 537 Japanese Alzheimer's Neuroimaging Initiative (J-ADNI) participants with a linear mixed-effects model. We also examined the potential use of ApoE status as a trial enrichment strategy. RESULTS: The hippocampal atrophy rate required smaller sample sizes than cognitive measures of AD and mild cognitive impairment (MCI). Inclusion of ApoE status reduced sample sizes for AD and MCI patients in the atrophy measures. CONCLUSION: These results show the potential use of longitudinal hippocampal atrophy measurement using automated image analysis as a progression biomarker and ApoE status as a trial enrichment strategy in a clinical trial of AD-modifying treatment in Japanese people.

Screening for Alzheimer's Disease: Cognitive Impairment in Self-Referred and Memory Clinic-Referred Patients. - Kirsebom, Bjørn-Eivind; Espenes, Ragna; Waterloo, Knut; Hessen, Erik; Johnsen, Stein Harald; Bråthen, Geir; Aarsland, Dag; Fladby, Tormod (J Alzheimers Dis, 2017)
BACKGROUND: Cognitive assessment is essential in tracking disease progression in AD. Presently, cohorts including preclinical at-risk participants are recruited by different means, which may bias cognitive and clinical features. We compared recruitment strategies to levels of cognitive functioning. OBJECTIVE: We investigate recruitment source biases in self-referred and memory clinic-referred patient cohorts to reveal potential differences in cognitive performance and demographics among at-risk participants. METHODS: We included 431 participants 40-80 years old. Participants were classified as controls (n = 132) or symptom group (n = 299). The symptom group comprised of subjective cognitive decline (SCD, n = 163) and mild cognitive impairment (MCI, n = 136). We compared cognitive performance and demographics in memory clinic-referrals (n = 86) to self-referred participants responding to advertisements and news bulletins (n = 179). Participants recruited by other means were excluded from analysis (n = 34). RESULTS: At symptom group level, we found significant reductions in cognitive performance in memory clinic-referrals compared to self-referrals. However, here reductions were only found within the MCI group. We found no differences in cognitive performance due to recruitment within the SCD group. The MCI group was significantly impaired compared to controls on all measures. Significant reductions in learning, and executive functions were also found for the SCD group. CONCLUSION: Regardless of recruitment method, both the SCD and MCI groups showed reductions in cognitive performance compared to controls. We found differences in cognitive impairment for memory clinic-referrals compared to self-referrals only within the MCI group, SCD-cases being equally affected irrespective of referral type.

Selenium Levels in Serum, Red Blood Cells, and Cerebrospinal Fluid of Alzheimer's Disease Patients: A Report from the Australian Imaging, Biomarker & Lifestyle Flagship Study of Ageing (AIBL). - Cardoso, Bárbara R; Hare, Dominic J; Bush, Ashley I; Li, Qiao-Xin; Fowler, Christopher J; Masters, Colin L; Martins, Ralph N; Ganio, Katherine; Lothian, Amber; Mukherjee, Soumya; Kapp, Eugene A; Roberts, Blaine R (J Alzheimers Dis, 2017)
Selenium (Se) protects cells against oxidative stress damage through a range of bioactive selenoproteins. Increased oxidative stress is a prominent feature of Alzheimer's disease (AD), and previous studies have shown that Se deficiency is associated with age-related cognitive decline. In this study, we assessed Se status in different biofluids from a subgroup of participants in the Australian Imaging, Biomarkers and Lifestyle Flagship Study of Ageing. As Se in humans can either be an active component of selenoproteins or inactive via non-specific incorporation into other proteins, we used both size exclusion chromatography-inductively coupled plasma-mass spectrometry (SEC-ICP-MS) and tandem mass spectrometry to characterize selenoproteins in serum. We observed no differences in total Se concentration in serum or cerebrospinal fluid of AD subjects compared to mildly cognitively impairment patients and healthy controls. However, Se levels in erythrocytes were decreased in AD compared to controls. SEC-ICP-MS analysis revealed a dominant Se-containing fraction. This fraction was subjected to standard protein purification and a bottom-up proteomics approach to confirm that the abundant Se in the fraction was due, in part, to selenoprotein P. The lack of change in the Se level is at odds with our previous observations in a Brazilian population deficient in Se, and we attribute this to the Australian cohort being Se-replete.

Self-Consciousness Deficits in Alzheimer's Disease and Frontotemporal Dementia. - Arroyo-Anlló, Eva Ma; Bouston, Adèle Turpin; Fargeau, Marie-Noëlle; Orgaz Baz, Begõna; Gil, Roger (J Alzheimers Dis, 2017)
Self-consciousness (SC) is multifaceted and considered to be the consciousness of one's own mental states. The main aim of this paper is to compare SC in patients with Alzheimer's disease (AD) and behavioral variant frontotemporal dementia (bvFTD). Three groups (control and patient groups) of 23 subjects each were assessed using an SC questionnaire. Both types of dementia clearly induce an alteration of SC. The bvFTD group showed a greater impairment in SC than the AD and control groups. The SC score was strongly associated with frontal functions. The most significantly impaired SC aspects in the bvFTD group were Anosognosia, Introspection, and Moral Judgments. For the AD group, the significantly impaired aspects of SC were Anosognosia and Prospective Memory. The differences in SC between the AD and bvFTD groups were essentially centered on the Anosognosia, Moral Judgments, and Introspection aspects, which were highly impaired in the bvFTD patients. This suggests that SC is related to orbito-frontal functioning and thus, to the default mode network.

Sembragiline in Moderate Alzheimer's Disease: Results of a Randomized, Double-Blind, Placebo-Controlled Phase II Trial (MAyflOwer RoAD). - Nave, Stephane; Doody, Rachelle S; Boada, Merce; Grimmer, Timo; Savola, Juha-Matti; Delmar, Paul; Pauly-Evers, Meike; Nikolcheva, Tania; Czech, Christian; Borroni, Edilio; Ricci, Benedicte; Dukart, Juergen; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sembragiline is a potent, selective, long-acting, and reversible MAO-B inhibitor developed as a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To evaluate the safety, tolerability, and efficacy of sembragiline in patients with moderate AD. METHODS: In this Phase II study (NCT01677754), 542 patients with moderate dementia (MMSE 13-20) on background acetylcholinesterase inhibitors with/without memantine were randomized (1:1:1) to sembragiline 1 mg, 5 mg, or placebo once daily orally for 52 weeks. RESULTS: No differences between treated groups and placebo in adverse events or in study completion. The primary endpoint, change from baseline in ADAS-Cog11, was not met. At Week 52, the difference between sembragiline and placebo in ADAS-Cog11 change from baseline was - 0.15 (p = 0.865) and 0.90 (p = 0.312) for 1 and 5 mg groups, respectively. Relative to placebo at Week 52 (but not at prior assessment times), the 1 mg and 5 mg sembragiline groups showed differences in ADCS-ADL of 2.64 (p = 0.051) and 1.89 (p = 0.160), respectively. A treatment effect in neuropsychiatric symptoms (as assessed by the difference between sembragiline and placebo on BEHAVE-AD-FW) was also seen at Week 52 only: - 2.80 (p = 0.014; 1 mg) and - 2.64 (p = 0.019; 5 mg), respectively. A post hoc subgroup analysis revealed greater treatment effects on behavior and functioning in patients with more severe baseline behavioral symptoms (above the median). CONCLUSIONS: This study showed that sembragiline was well-tolerated in patients with moderate AD. The study missed its primary and secondary endpoints. Post hoc analyses suggested potential effect on neuropsychiatric symptoms and functioning in more behaviorally impaired study population at baseline.

Severity of Depression Impacts Imminent Conversion from Mild Cognitive Impairment to Alzheimer's Disease. - Defrancesco, Michaela; Marksteiner, Josef; Kemmler, Georg; Fleischhacker, Walter Wolfgang; Blasko, Imrich; Deisenhammer, Eberhard A (J Alzheimers Dis, 2017)
BACKGROUND: Mild cognitive impairment (MCI) has been suggested to represent a prodromal stage of dementia and to confer a high risk for conversion to dementia Alzheimer's type (DAT). OBJECTIVES: In this study, we examined the predictive value of depressive symptoms and neuropsychological variables on conversion of MCI to DAT. METHODS: Neuropsychological and clinical follow-up data of 260 MCI patients seen at the Psychiatric Memory Clinic of the Medical University of Innsbruck between 2005 and 2015 were analyzed retrospectively. Depression was assessed using the Geriatric Depression Scale (GDS). Potential predictors of conversion from MCI to DAT were analyzed by logistic regression analyses and additional survival-analytic methods. RESULTS: Of the 260 patients (mean age 71.5±7.7 years), 83 (32%) converted to DAT within a mean follow-up time of 3.2±2.2 years and estimated one-year conversion rate of 10.1%. The univariate analysis showed with few exceptions (gender, use of antidepressants, low GDS score) group differences at baseline in patients converted to DAT compared to stable MCI patients. Logistic regression analysis as well as survival analysis revealed moderate to severe depression together with higher age and specific cognitive deficits as predictors of conversion from MCI to DAT. CONCLUSION: Our results support the predictive value of different neuropsychological measures on the progression of DAT. In addition, we found a strong negative influence of depression on conversion to DAT in MCI patients. These results emphasize the importance of assessing depressive symptoms in the early stages of DAT when evaluating the conversion from MCI to DAT.

Sex-Dependent Associations of Serum Uric Acid with Brain Function During Aging. - Kueider, Alexandra M; An, Yang; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Studenski, Stephanie; Ferrucci, Luigi; Thambisetty, Madhav (J Alzheimers Dis, 2017)
Serum uric acid (SUA) is an abundant natural antioxidant capable of reducing cellular oxidation, a major cause of neurodegenerative disease. In line with this, SUA levels are lower in Alzheimer's disease; however, the association between SUA and cognition remains unclear. Results from studies examining the effects of SUA on cognition may be difficult to interpret in the context of normal versus pathological aging. This study examined sex-specific associations of baseline SUA with cognition during aging. Data from dementia-free participants initially aged 26-99 (N = 1,451) recruited for the Baltimore Longitudinal Study of Aging (BLSA), were used in the current analyses. SUA was assessed using blood samples collected during research visits. Cognition was measured using five composite scores (verbal memory, attention, executive function, language, and visuospatial ability). At the first study visit, compared with women, men were older, more likely to be White, had more years of education, higher baseline SUA levels, and higher cardiovascular risk scores. Higher baseline SUA was associated with attenuated declines in attention (β= 0.006; p = 0.03) and visuospatial abilities (β= 0.007; p = 0.01) in men. There was a trend to suggest higher baseline SUA in men was associated with attenuated declines in language, but this finding did not reach statistical significance (p = 0.09). There were no significant findings with SUA and cognition in women. In this sample of cognitively healthy, community-dwelling adults, we found that higher SUA levels at baseline were associated with attenuated declines in attention and visuospatial abilities in men. SUA was not associated with cognition or change in cognition over time in women.

Sleep Apnea, Cognitive Profile, and Vascular Changes: An Intriguing Relationship. - Buratti, Laura; Viticchi, Giovanna; Baldinelli, Sara; Falsetti, Lorenzo; Luzzi, Simona; Pulcini, Alessandra; Petrelli, Cristina; Provinciali, Leandro; Silvestrini, Mauro (J Alzheimers Dis, 2017)
BACKGROUND: Sleep breathing disorders can affect cognitive performances through complex brain anatomical and functional changes. OBJECTIVE: Our aim was to evaluate the correlations between cognitive performances and obstructive sleep apnea syndrome (OSAS), as well as the possible influence of vascular factors. METHODS: Thirty-four non-demented OSAS patients and 34 controls were submitted to a neuropsychological evaluation and to a vascular screening including the study of cerebrovascular reactivity by means of the breath-holding index (BHI) calculation. After 6 months, polisomnographic, neuropsychologic, and hemodynamics assessment was repeated in patients. RESULTS: At baseline, some cognitive performances involved in executive and memory functions were significantly lower in patients with respect to controls. Significantly lower values in mean BHI were also detected in patients with respect to controls (p < 0.0001). At the 6-month evaluation, 18 patients had a reduction in OSAS severity (group 1) and 16 remained stable (group 2). Group 1 patients had a significant improvement in left and mean BHI (p < 0.001) and in short-term (p = 0.02) and long-term Rey Auditory Verbal Learning Test (p < 0.001). No change in cerebrovascular reactivity and cognitive profile was detected in group 2 patients. CONCLUSIONS: Patients with OSAS may experience a reduced cognitive efficiency. Improvement of OSAS was associated to favorable hemodynamic changes and increased level of performances in verbal memory tasks so suggesting an involvement of vascular underlying mechanisms in sustaining cognitive dysfunctions in OSAS. Our preliminary data suggest the need for further studies to deepen the knowledge about the relationships between OSAS, cerebral hemodynamic compromise, and cognitive impairment risk.

Sleep-Wake Profile in Dementia with Lewy Bodies, Alzheimer's Disease, and Normal Aging. - Cagnin, Annachiara; Fragiacomo, Federica; Camporese, Giulia; Turco, Matteo; Bussè, Cinzia; Ermani, Mario; Montagnese, Sara (J Alzheimers Dis, 2017)
BACKGROUND: Alterations of the sleep-wake cycle are common features of neurodegenerative dementia. OBJECTIVES: To study differences in sleep-wake profiles in dementia with Lewy bodies (DLB), Alzheimer's disease (AD), and healthy controls. METHODS: 30 DLB and 32 AD patients, and 33 healthy elderly participants were studied. Patients were evaluated for global cognitive impairment, extrapyramidal signs, fluctuations of attention, and behavioral disorders. A comprehensive sleep-wake profile was obtained including a set of questionnaires [Pittsburgh Sleep Quality Index (PSQI), REM Sleep Behavior Disorder Single-Question screen (RBD1Q), Epworth Sleepiness Scale (ESS)] and 12-day sleep diaries. RESULTS: Patients were matched for age, gender, and disease severity. DLB patients showed more severe daytime somnolence/dysfunction due to somnolence, and a higher proportion of RBD-like symptoms (70%) compared to AD and controls (p < 0.001), regardless of the presence of psychoactive drug treatment. As for sleep timing, DLB patients had a greater number of daytime naps and longer night sleep, with the latter being associated with use of clonazepam. The severity of fluctuations was associated with the presence of RBD (Clinician Assessment of Fluctuation score = RBD+: 5.2±3.7; RBD-: 2.1±3.2, p = 0.04). AD patients reported the best sleep-wake profile, while healthy controls declared the poorest sleep quality, although sleep timing and the quality of wakefulness were comparable between AD and controls. DISCUSSION: RBD and daytime fluctuations of attention may coexist in DLB and even reciprocally potentiate each other. Self-reports of sleep quality may lead to an underestimation of sleep disturbances in AD, possibly influenced by anosognosia, compared to normal elderly individuals who complain mainly of insomnia.

Soluble Oligomers Require a Ganglioside to Trigger Neuronal Calcium Overload. - Cascella, Roberta; Evangelisti, Elisa; Bigi, Alessandra; Becatti, Matteo; Fiorillo, Claudia; Stefani, Massimo; Chiti, Fabrizio; Cecchi, Cristina (J Alzheimers Dis, 2017)
An altered distribution of membrane gangliosides (GM), including GM1, has recently been reported in the brains of Alzheimer's disease (AD) patients. Moreover, amyloid-positive synaptosomes obtained from AD brains were found to contain high-density GM1 clusters, suggesting a pathological significance of GM1 increase at presynaptic neuritic terminals in AD. Here, we show that membrane GM1 specifically recruits small soluble oligomers of the 42-residue form of amyloid-β peptide (Aβ42), with intracellular flux of Ca2+ ions in primary rat hippocampal neurons and in human neuroblastoma cells. Specific membrane proteins appear to be involved in the early and transient influx of Ca2+ ions induced by Aβ42 oligomers with high solvent-exposed hydrophobicity (A+), but not in the sustained late influx of the same oligomers and in that induced by Aβ42 oligomers with low solvent-exposed hydrophobicity (A-) in GM1-enriched cells. In addition, A+ oligomers accumulate in proximity of membrane NMDA and AMPA receptors, inducing the early and transient Ca2+ influx, although FRET shows that the interaction is not direct. These results suggest that age-dependent clustering of GM1 within neuronal membranes could induce neurodegeneration in elderly people as a consequence of an increased ability of the lipid bilayers to recruit membrane-permeabilizing oligomers. We also show that both lipid and protein components of the plasma membrane can contribute to neuronal dysfunction, thus expanding the molecular targets for therapeutic intervention in AD.

Specific Verbal Memory Measures May Distinguish Alzheimer's Disease from Dementia with Lewy Bodies. - Bussè, Cinzia; Anselmi, Pasquale; Pompanin, Sara; Zorzi, Giovanni; Fragiacomo, Federica; Camporese, Giulia; Di Bernardo, Gian Antonio; Semenza, Carlo; Caffarra, Paolo; Cagnin, Annachiara (J Alzheimers Dis, 2017)
BACKGROUND: Standard measures of commonly used memory tests may not be appropriate to distinguish different neurodegenerative diseases affecting memory. OBJECTIVE: To study whether specific measures of verbal memory obtained with the Rey Auditory Verbal Learning test (RAVLT) could help distinguish dementia with Lewy bodies (DLB) from Alzheimer's disease (AD). METHODS: Twenty-nine DLB and 32 AD patients participated in the study and were followed longitudinally for 3 years until the diagnosis was confirmed according to standard clinical criteria. Twenty-eight healthy elderly subjects served as controls. The following verbal memory measures were evaluated: verbal learning (VL), verbal forgetting (VF), percentage of verbal forgetting (VF%), and serial position effects of the immediate recall performance. RESULTS: DLB and AD groups have comparable performances at the RAVLT immediate and delayed recall tasks. However, VL was higher in DLB than AD while VF% was greater in AD. With a VF% cut-off ≥75%, AD and DLB patients were differently distributed, with 58% of AD versus 21% of DLB above this cut-off. The recency effect was significant higher in AD than DLB. DISCUSSION: DLB patients had a better performance in VL than AD, but worse VF and recency effect. These specific measures of verbal memory could be used as cognitive markers in the differential diagnosis between these two conditions.

Synaptic Compensation as a Probable Cause of Prolonged Mild Cognitive Impairment in Alzheimer's Disease: Implications from a Transgenic Mouse Model of the Disease. - Baazaoui, Narjes; Flory, Michael; Iqbal, Khalid (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) is a slow, progressive neurodegenerative disease in which cognitive decline takes place over a period of several years with a very variable period of mild cognitive impairment (MCI) and, in some cases, relatively long period before progression to dementia. The cognitive deficit during MCI is probably due to neuronal loss, an intermediate level of amyloid-β (Aβ) plaques and neurofibrillary tangles (NFT) and synaptosis, which is interrupted with a transient compensatory increase. We found impairment in reference memory accompanied by a decrease in the expression of synaptophysin, β-III tubulin, and MAP2 and a trend for GluR1, at 12 weeks of age in 3xTg-AD mice (hAPPSwe, P301L tau, PS1 [M146V] knock-in), a widely used transgenic model of AD. Past 12 weeks, the cross-sectional analysis of different age groups showed a compensatory increase in synaptic markers relative to that in wild type animals in a topographic and time-dependent manner. When studied across time we found that in 3xTg-AD mice, the compensatory phenomenon occurred in parallel in different regions of the brain. However, this attempt of the brain to repair itself was able to only partially rescue cognitive impairment. These findings for the first time raise the intriguing possibility that AD causing mutated transgenes may initially cause an increase in synaptic and dendritic markers as a compensatory mechanism for synaptic deficit, and this phenomenon, though transient, could be the biological basis of the period of MCI seen in AD.

Tau Platelets Correlate with Regional Brain Atrophy in Patients with Alzheimer's Disease. - Slachevsky, Andrea; Guzmán-Martínez, Leonardo; Delgado, Carolina; Reyes, Pablo; Farías, Gonzalo A; Muñoz-Neira, Carlos; Bravo, Eduardo; Farías, Mauricio; Flores, Patricia; Garrido, Cristian; Becker, James T; Lopez, Oscar L; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Intracellular neurofibrillary tangles are part of the core pathology of Alzheimer's disease (AD), which are mainly composed of hyperphosphorylated tau protein. OBJECTIVES: The purpose of this study is to determine whether high molecular weight (HMW) or low molecular weight (LMW) tau protein levels, as well as the ratio HMW/LMW, present in platelets correlates with brain magnetic resonance imaging (MRI) structural changes in normal and cognitively impaired subjects. METHODS: We examined 53 AD patients and 37 cognitively normal subjects recruited from two Memory Clinics at the Universidad de Chile. Tau levels in platelets were determined by immunoreactivity and the MRI scans were analyzed using voxel-based morphometry in 41 AD patients. RESULTS: The HMW/LMW tau ratio was statistically different between controls and AD patients, and no associations were noted between HMW or LMW tau and MRI structures. In a multivariate analysis controlled for age and education level, the HMW/LMW tau ratio was associated with reduced volume in the left medial and right anterior cingulate gyri, right cerebellum, right thalamus (pulvinar), left frontal cortex, and right parahippocampal region. CONCLUSIONS: This exploratory study showed that HMW/LMW tau ratio is significantly higher in AD patients than control subjects, and that it is associated with specific brain regions atrophy. Determination of peripheral markers of AD pathology can help understanding the pathophysiology of neurodegeneration in AD.

Trehalose Improves Cognition in the Transgenic Tg2576 Mouse Model of Alzheimer's Disease. - Portbury, Stuart D; Hare, Dominic J; Sgambelloni, Charlotte; Perronnes, Kali; Portbury, Ashley J; Finkelstein, David I; Adlard, Paul A (J Alzheimers Dis, 2017)
This study assessed the therapeutic utility of the autophagy enhancing stable disaccharide trehalose in the Tg2576 transgenic mouse model of Alzheimer's disease (AD) via an oral gavage of a 2% trehalose solution for 31 days. Furthermore, as AD is a neurodegenerative condition in which the transition metals, iron, copper, and zinc, are understood to be intricately involved in the cellular cascades leading to the defining pathologies of the disease, we sought to determine any parallel impact of trehalose treatment on metal levels. Trehalose treatment significantly improved performance in the Morris water maze, consistent with enhanced learning and memory. The improvement was not associated with significant modulation of full length amyloid-β protein precursor or other amyloid-β fragments. Trehalose had no effect on autophagy as assessed by western blot of the LC3-1 to LC3-2 protein ratio, and no alteration in biometals that might account for the improved cognition was observed. Biochemical analysis revealed a significant increase in the hippocampus of both synaptophysin, a synaptic vesicle protein and surrogate marker of synapses, and doublecortin, a reliable marker of neurogenesis. The growth factor progranulin was also significantly increased in the hippocampus and cortex with trehalose treatment. This study suggests that trehalose might invoke a suite of neuroprotective mechanisms that can contribute to improved cognitive performance in AD that are independent of more classical trehalose-mediated pathways, such as Aβ reduction and activation of autophagy. Thus, trehalose may have utility as a potential AD therapeutic, with conceivable implications for the treatment of other neurodegenerative disorders.

Upregulated Expression of Heparanase and Heparanase 2 in the Brains of Alzheimer's Disease. - Garcia, Beatriz; Martin, Carla; Garcia-Suarez, Olivia; Muniz-Alonso, Barbara; Ordiales, Helena; Fernandez-Menendez, Santiago; Santos-Juanes, Jorge; Lorente-Gea, Laura; Castanon, Sonia; Vicente-Etxenausia, Ikerne; Pina Batista, Kelvin Manuel; Ruiz-Diaz, Irune; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Heparan sulfate proteoglycans (HSPGs) promote amyloid-β peptide and tau fibrillization in Alzheimer's disease (AD) and provide resistance against proteolytic breakdown. Heparanase (HPSE) is the only enzyme that cleaves heparan sulfate (HS). Heparanase 2 (HPSE2) lacks HS-degrading activity, although it is able to interact with HS with high affinity. OBJECTIVE: To analyze HPSE and HPSE2 expressions at different stages of AD. METHODS: RT-PCR was used to analyze transcription levels of both heparanases at different stages of AD, and immunohistochemistry was performed to localize each one in different parts of the brain. RESULTS: Both proteins appeared overexpressed at different stages of AD. Immunohistochemistry indicated that the presence of the heparanases was related to AD pathology, with intracellular deposits found in degenerated neurons. At the extracellular level, HPSE was observed only in neuritic plaques with a fragmented core, while HPSE2 appeared in those with compact cores as well. CONCLUSION: Given the involvement of HSPGs in AD pathology, there would seem to be a relationship between the regulation of heparanase expression, the features of the disease, and a possible therapeutic alternative.

The Utility of the Cognitive Function Instrument (CFI) to Detect Cognitive Decline in Non-Demented Older Adults. - Li, Clara; Neugroschl, Judith; Luo, Xiaodong; Zhu, Carolyn; Aisen, Paul; Ferris, Steven; Sano, Mary (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive complaint is a sensitive marker of decline. OBJECTIVE: This study aimed to (1) examine reliability of subjective cognitive complaint using the Cognitive Function Instrument (CFI), and (2) assess the utility of the CFI to detect cognitive decline in non-demented elders. METHODS: Data from a four-year longitudinal study at multiple Alzheimer's Disease Cooperative Study (ADCS) sites were extracted (n = 644). Of these, 497 had Clinical Dementia Rating (CDR) global scores of 0 and 147 had a CDR of 0.5. Mean age and education were 79.5±3.6 and 15.0±3.1 years, respectively. All participants and their study partners completed the subject and study partner CFI yearly. Modified Mini-Mental State Exam (mMMSE) and Free and Cued Selective Reminding Test (FCSRT) were administered. Scores below the predetermined cut-off scores on either measure at annual visit were triggers for a full diagnostic evaluation. Cognitive decline was defined by the absence/presence of the trigger. RESULTS: Three-month test retest reliability showed that inter-class coefficients for subject and study partner CFI were 0.76 and 0.78, respectively. Generalized estimating equation method revealed that both subject and study partner CFI change scores and scores from previous year were sensitive to cognitive decline in the CDR 0 group (p < 0.05). In the CDR 0.5 group, only the study partner CFI change score predicted cognitive decline (p < 0.05). CONCLUSION: Cognitive decline was predicted differentially by CDR level with subject CFI scores providing the best prediction for those with CDR 0 while study partner CFI predicted best for those at CDR 0.5.

Validation of the Spanish Version of the LASSI-L for Diagnosing Mild Cognitive Impairment and Alzheimer's Disease. - Matías-Guiu, Jordi A; Curiel, Rosie E; Rognoni, Teresa; Valles-Salgado, María; Fernández-Matarrubia, Marta; Hariramani, Roshan; Fernández-Castro, Alejandro; Moreno-Ramos, Teresa; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2017)
BACKGROUND: The Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L) is a novel cognitive test that measures recovery from proactive semantic interference, which may be an early cognitive marker of Alzheimer's disease (AD). OBJECTIVE: To generate normative data for a Spaniard population and to validate the LASSI-L for the diagnosis of amnestic mild cognitive impairment (aMCI) and mild AD. METHODS: We performed a cross-sectional study in which 97 healthy participants, 34 with aMCI, and 33 with mild AD were studied with LASSI-L and a comprehensive neuropsychological protocol. The overlapping strategy analysis was used to maximize the sample size and to provide age- and education-adjusted normative data using a logistic regression analysis. RESULTS: Internal consistency was 0.932. Convergent validity with the Free and Cued Selective Reminding Test was moderate. LASSI-L raw scores were correlated with age and years of education, but not gender. The area under the curve for discriminating between healthy controls and aMCI was 0.909, and between healthy controls and mild AD was 0.986. LASSI-L sub-scores representing maximum storage capacity, recovery from proactive interference, and delayed recall yielded the highest diagnostic accuracy. CONCLUSIONS: The LASSI-L is a reliable and valid test for the diagnosis of aMCI and mild AD. The age and education influences on the performance of the test and normative data are provided. LASSI-L merits further studies to evaluate its ability to detect preclinical AD and predict progression to aMCI and early dementia.

Violation of Laws in Frontotemporal Dementia: A Multicenter Study in Japan. - Shinagawa, Shunichiro; Shigenobu, Kazue; Tagai, Kenji; Fukuhara, Ryuji; Kamimura, Naoto; Mori, Takaaki; Yoshiyama, Kenji; Kazui, Hiroaki; Nakayama, Kazuhiko; Ikeda, Manabu (J Alzheimers Dis, 2017)
Although violations of laws, such as shoplifting, are considered to be common in frontotemporal dementia (FTD) patients, there have been few studies on this subject and the frequencies and types of such violations have not been clarified. The objective of this study was to conduct a retrospective investigation of FTD patients in the psychiatry departments of multiple institutions to determine the types and frequencies of any law violations and compare them with those of AD patients. All patients were examined between January 2011 and December 2015 at the specialized dementia outpatient clinics of 10 facilities (5 psychiatry departments of university hospitals, 5 psychiatric hospitals). According to diagnostic criteria, 73 behavior variant FTD (bvFTD) patients, 84 semantic variant of primary progressive aphasia (svPPA) patients, and 255 age- and sex-matched AD subjects as the control group were selected. The findings revealed a higher rate of law violations in the bvFTD and svPPA patients before the initial consultation as compared to the AD group (bvFTD: 33%, svPPA: 21%, AD: 6%) and that many patients had been referred due to such violations. Laws had been broken 4 times or 5 or more times in several cases in the FTD group before the initial consultation. Regarding rates for different types of violation, in bvFTD subjects, the highest rate was for theft, followed by nuisance acts and hit and run. In svPPA, theft had the highest rate, followed by ignoring road signs. There was no gender difference in law violations but they were more frequent when the disease was severe at the initial consultation in the FTD group. As the rates of law violations after the initial consultation were lower than before it, interventions were considered to have been effective. These findings may be useful for future prevention as well as to the legal system.

Visuospatial Functioning in Cerebral Amyloid Angiopathy: A Pilot Study. - Valenti, Raffaella; Charidimou, Andreas; Xiong, Li; Boulouis, Gregoire; Fotiadis, Panagiotis; Ayres, Alison; Riley, Grace; Kuijf, Hugo J; Reijmer, Yael D; Pantoni, Leonardo; Gurol, M Edip; Davidsdottir, Sigurros; et al. (J Alzheimers Dis, 2017)
Cerebral amyloid angiopathy (CAA) is a contributor to cognitive impairment in the elderly. We hypothesized that the posterior cortical predilection of CAA would cause visual-processing impairment. We systematically evaluated visuospatial abilities in 22 non-demented CAA patients. Neurocognitive evaluation demonstrated visuoperceptual impairment (23% on Benton Facial Recognition Test [BFRT] and 13.6% on Benton Judgment of Line Orientation Test [BJLO]). BFRT was inversely correlated with white matter hyperintensities volume and BJLO with parietal cerebral microbleeds. This pilot study highlights the presence of visual-processing deficits in CAA. The impairment could be related to global disease severity in addition to local brain injury.

Voluptuary Habits and Risk of Frontotemporal Dementia: A Case Control Retrospective Study. - Tremolizzo, Lucio; Bianchi, Elisa; Susani, Emanuela; Pupillo, Elisabetta; Messina, Paolo; Aliprandi, Angelo; Salmaggi, Andrea; Cosseddu, Maura; Pilotto, Andrea; Borroni, Barbara; Padovani, Alessandro; Bonomini, Cristina; et al. (J Alzheimers Dis, 2017)
Alcohol, coffee, and tobacco consumption was assessed on 151 FTD outpatients and 151 matched controls in a multicenter retrospective case-control design. No association was found for smoking and coffee intake. The risk of FTD was decreased by alcohol consumption (adj. OR 0.30, 95% CI 0.14-0.63); risk reduction was significant in current alcohol consumers (adj. OR 0.22, 95% CI 0.10-0.51). The risk of FTD inversely correlated with the duration of exposure (adj. OR 0.88, 95% CI 0.81-0.95, for every 5 years of exposure increase). Retrospective information and the unknown amount of consumed alcohol are limits of the present work.

When Patient Engagement and Research Ethics Collide: Lessons from a Dementia Forum. - Robillard, Julie M; Feng, Tanya L (J Alzheimers Dis, 2017)
The importance of patient engagement in research has been gaining recognition since the turn of the 21st century. However, little is known about the perspectives of people with dementia on the process of discovery. To fill this gap and to inform priorities in patient engagement in the context of dementia research, the Clinic for Alzheimer Disease and Related Disorders at the University of British Columbia hosted an interactive session for members of the patient community and of the general public to share their views on various ethical aspects of the research process. Results from the session indicate that several current research ethics policies and norms in dementia research are not in line with participants' preferences. Here we discuss the importance of bridging the gap between researchers and patients and call for reforms in current standards of dementia research.

White Matter Hyperintensities Potentiate Hippocampal Volume Reduction in Non-Demented Older Individuals with Abnormal Amyloid-β. - Freeze, Whitney M; Jacobs, Heidi I L; Gronenschild, Ed H; Jansen, Jacobus F A; Burgmans, Saartje; Aalten, Pauline; Clerx, Lies; Vos, Stephanie J; van Buchem, Mark A; Barkhof, Frederik; van der Flier, Wiesje M; Verbeek, Marcel M; et al. (J Alzheimers Dis, 2017)
Cerebral small vessel disease (cSVD) and amyloid-β (Aβ) deposition often co-exist in (prodromal) dementia, and both types of pathology have been associated with neurodegeneration. We examined whether cSVD and Aβ have independent or interactive effects on hippocampal volume (HV) in a memory clinic population. We included 87 individuals with clinical diagnoses of Alzheimer's disease (AD) (n = 24), mild cognitive impairment (MCI) (n = 26), and subjective cognitive complaints (SCC) (n = 37). cSVD magnetic resonance imaging markers included white matter hyperintensity (WMH) volume, lacunar infarct presence, and microbleed presence. Aβ pathology was assessed as cerebrospinal fluid-derived Aβ1 - 42 levels and dichotomized into normal or abnormal, and HV was determined by manual volumetric measurements. A linear hierarchical regression approach was applied for the detection of additive or interaction effects between cSVD and Aβ on HV in the total participant group (n = 87) and in the non-demented group (including SCC and MCI individuals only, n = 63). The results revealed that abnormal Aβ and lacunar infarct presence were independently associated with lower HV in the non-demented individuals. Interestingly, Aβ and WMH pathology interacted in the non-demented individuals, such that WMH had a negative effect on HV in individuals with abnormal CSF Aβ42 levels, but not in individuals with normal CSF Aβ42 levels. These associations were not present when individuals with AD were included in the analyses. Our observations suggest that relatively early on in the disease process older individuals with abnormal Aβ levels are at an increased risk of accelerated disease progression when concomitant cSVD is present.

ABCA7 Mediates Phagocytic Clearance of Amyloid-β in the Brain. - Fu, YuHong; Hsiao, Jen-Hsiang T; Paxinos, George; Halliday, Glenda M; Kim, Woojin Scott (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by dementia and abnormal deposits of aggregated amyloid-β in the brain. Recent genome-wide association studies have revealed that ABCA7 is strongly associated with AD. In vitro evidence suggests that the role of ABCA7 is related to phagocytic activity. Deletion of ABCA7 in a mouse model of AD exacerbates cerebral amyloid-β plaque load. However, the biological role of ABCA7 in AD brain pathogenesis is unknown. We show that ABCA7 is highly expressed in microglia and when monocytes are differentiated into macrophages. We hypothesized that ABCA7 plays a protective role in the brain that is related to phagocytic clearance of amyloid-β. We isolated microglia and macrophages from Abca7-/- and wild type mice and tested them for their capacity to phagocytose amyloid-β oligomers. We found that the phagocytic clearance of amyloid-β was substantially reduced in both microglia and macrophages from Abca7-/- mice compared to wild type mice. Consistent with these results, in vivo phagocytic clearance of amyloid-β oligomers in the hippocampus was reduced in Abca7-/- mice. Furthermore, ABCA7 transcription was upregulated in AD brains and in amyloidogenic mouse brains specifically in the hippocampus as a response to the amyloid-β pathogenic state. Together these results indicate that ABCA7 mediates phagocytic clearance of amyloid-β in the brain, and reveal a mechanism by which loss of function of ABCA7 increases the susceptibility to AD.

Adenosine Type A2A Receptor in Peripheral Cell from Patients with Alzheimer's Disease, Vascular Dementia, and Idiopathic Normal Pressure Hydrocephalus: A New/Old Potential Target. - Arosio, Beatrice; Casati, Martina; Gussago, Cristina; Ferri, Evelyn; Abbate, Carlo; Scortichini, Valeria; Colombo, Elena; Rossi, Paolo Dionigi; Mari, Daniela (J Alzheimers Dis, 2016)
As the European population gets older, the incidence of neurological disorders increases with significant impact on social costs. Despite differences in disease etiology, several brain disorders in the elderly (e.g., Alzheimer's disease, vascular dementia, normal pressure hydrocephalus) share dementia as a common clinical feature. The current treatment for the majority of these diseases is merely symptomatic and does not modify the course of the illness. Symptoms of normal pressure hydrocephalus are the only ones that can be modified if they are recognized in time and treated appropriately. Therefore, an important clinical strategy may be disclosed by pathogenic pathways that can be modified and to find drugs that can slow down or even arrest disease progression. Possibly a way to answer this question could be by re-examining all the molecules which have so far succeeded in improving many aspects of cognitive deterioration in some neurodegenerative conditions, that were not considered because of controversial opinions. The main purpose of this summary is to further substantiate the hypothesis that the pathway of adenosine type A2A receptor could be used as a potential target to develop new/old therapeutic strategies.

Age-Dependent Regulation of the Blood-Brain Barrier Influx/Efflux Equilibrium of Amyloid-β Peptide in a Mouse Model of Alzheimer's Disease (3xTg-AD). - Do, Tuan Minh; Dodacki, Agnès; Alata, Wael; Calon, Frederic; Nicolic, Sophie; Scherrmann, Jean-Michel; Farinotti, Robert; Bourasset, Fanchon (J Alzheimers Dis, 2016)
The involvement of transporters located at the blood-brain barrier (BBB) has been suggested in the control of cerebral Aβ levels, and thereby in Alzheimer's disease (AD). However, little is known about the regulation of these transporters at the BBB in animal models of AD. In this study, we investigated the BBB expression of Aβ influx (Rage) and efflux (Abcb1-Abcg2-Abcg4-Lrp-1) transporters and cholesterol transporter (Abca1) in 3-18-month-old 3xTg-AD and control mice. The age-dependent effect of BBB transporters regulation on the brain uptake clearance (Clup) of [3H]cholesterol and [3H]Aβ1 - 40 was then evaluated in these mice, using the in situ brain perfusion technique. Our data suggest that transgenes expression led to the BBB increase in Aβ influx receptor (Rage) and decrease in efflux receptor (Lrp-1). Our data also indicate that mice have mechanisms counteracting this increased net influx. Indeed, Abcg4 and Abca1 are up regulated in 3- and 3/6-month-old 3xTg-AD mice, respectively. Our data show that the balance between the BBB influx and efflux of Aβ is maintained in 3 and 6-month-old 3xTg-AD mice, suggesting that Abcg4 and Abca1 control the efflux of Aβ through the BBB by a direct (Abcg4) or indirect (Abca1) mechanism. At 18 months, the BBB Aβ efflux is significantly increased in 3xTg-AD mice compared to controls. This could result from the significant up-regulation of both Abcg2 and Abcb1 in 3xTg-AD mice compared to control mice. Thus, age-dependent regulation of several Aβ and cholesterol transporters at the BBB could ultimately limit the brain accumulation of Aβ.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP Binding Cassette Transporter, Sub-Family G, Member 1; ATP Binding Cassette Transporter, Sub-Family G, Member 2; ATP-Binding Cassette Transporters; Biological Transport; Blood-Brain Barrier; Brain; Carbon Isotopes; Cholesterol; Disease Models, Animal; Humans; Lipoproteins; Mice; Mice, Transgenic; P-Glycoproteins; Peptide Fragments; Receptors, LDL; Sucrose; Tritium; Tumor Suppressor Proteins

Age-Related Effects of the Apolipoprotein E Gene on Brain Function. - Matura, Silke; Prvulovic, David; Hartmann, Daniel; Scheibe, Monika; Sepanski, Beate; Butz, Marius; Oertel-Knöchel, Viola; Knöchel, Christian; Karakaya, Tarik; Fußer, Fabian; Hattingen, Elke; Pantel, Johannes (J Alzheimers Dis, 2016)
The apolipoprotein E (ApoE) ɛ4 allele is a well-established genetic risk factor for sporadic Alzheimer's disease. Some evidence suggests a negative role of the ApoE ɛ4 allele for cognitive performance in late life, while beneficial effects on cognition have been shown in young age. We investigated age-related effects of the ApoE gene on brain function by assessing cognitive performance, as well as functional activation patterns during retrieval of Face-Name pairs in a group of young (n = 50; age 26.4±4.6 years, 25 ɛ4 carriers) and old (n = 40; age 66.1±7.0 years, 20 ɛ4 carriers) participants. A cross-sectional factorial design was used to examine the effects of age, ApoE genotype, and their interaction on both cognitive performance and the blood oxygenation level dependent (BOLD) brain response during retrieval of Face-Name pairs. While there were no genotype-related differences in cognitive performance, we found a significant interaction of age and ApoE genotype on task-related activation bilaterally in anterior cingulate gyrus and superior frontal gyrus, as well as left and right insula. Old age was associated with increased activity in ɛ4 carriers. The increased BOLD response in old ɛ4 carriers during retrieval could indicate a neurocognitive disadvantage associated with the ɛ4 allele with increasing age. Furthermore, recruitment of neuronal resources resulted in enhanced memory performance in young ɛ4 carriers, pointing to a better neurofunctional capacity associated with the ApoE4 genotype in young age.

All Is Not Lost: Positive Behaviors in Alzheimer's Disease and Behavioral-Variant Frontotemporal Dementia with Disease Severity. - Midorikawa, Akira; Leyton, Cristian E; Foxe, David; Landin-Romero, Ramon; Hodges, John R; Piguet, Olivier (J Alzheimers Dis, 2016)
BACKGROUND: Anecdotal evidence indicates that some patients with dementia exhibit novel or increased positive behaviors, such as painting or singing, after the disease onset. Due to the lack of objective measures, however, the frequency and nature of these changes has not been formally investigated. OBJECTIVE: This study aimed to systematically identify changes in these behaviors in the two most common younger-onset dementia syndromes: Alzheimer's disease (AD) and behavioral-variant frontotemporal dementia (bvFTD). METHODS: Sixty-three caregivers of patients with dementia (32 caregivers of AD patients and 31 caregivers of bvFTD patients) participated in the study. Caregivers rated the presence and frequency of positive and negative behavior changes after the onset of dementia using the Hypersensory and Social/Emotional Scale (HSS) questionnaire, focusing on three domains: sensory processing, cognitive skills, and social/emotional processing. Six composites scores were obtained reflecting these three domains (two composite scores for each domain). Differences across scores and ratios of increased and decreased behaviors were analyzed between AD and bvFTD, at different disease severity levels. RESULTS: After disease onset, significant changes in the sensory processing domain were observed across disease severity levels, particularly in AD. Composite scores of the other domains did not change significantly. Importantly, however, some novel or increased positive behaviors were present in between 10% (Music activities) and 70% (Hypersensitivity) of AD and bvFTD patients, regardless of disease severity. CONCLUSIONS: We provide the first systematic investigation of positive behaviors in AD and bvFTD. The newly developed HSS questionnaire is a valid measure to characterize changes and progression of positive behaviors in patients with dementia.

Alterations in the Levels of Amyloid-β, Phospholipid Hydroperoxide, and Plasmalogen in the Blood of Patients with Alzheimer's Disease: Possible Interactions between Amyloid-β and These Lipids. - Yamashita, Shinji; Kiko, Takehiro; Fujiwara, Hironori; Hashimoto, Michio; Nakagawa, Kiyotaka; Kinoshita, Mikio; Furukawa, Katsutoshi; Arai, Hiroyuki; Miyazawa, Teruo (J Alzheimers Dis, 2016)
Aside from accumulation of amyloid-β (Aβ) peptide in the brain, Alzheimer's disease (AD) has been reported as being associated with peroxidation of major phospholipids (e.g., phosphatidylcholine (PtdCho)) and degradation of antioxidative phospholipids (e.g., ethanolamine plasmalogen (PlsEtn)). In addition to its presence in the brain, Aβ is also found in blood; however, there is still little information about the levels of PtdCho hydroperoxide (PCOOH) and PlsEtn in the blood of patients with AD. In this study, by assuming a possible interaction among Aβ, PCOOH, and PlsEtn in blood circulation, we evaluated the levels of these molecules and correlations in blood samples that had been obtained from our former AD study for PCOOH measurement (Kiko et al., J Alzheimers Dis28, 593-600, 2012). We found that when compared to controls, plasma from patients with AD showed lower concentrations of PlsEtn species, especially PlsEtn bearing the docosahexaenoic acid (DHA) moiety. In addition, lower PlsEtn and higher PCOOH levels were observed in red blood cells (RBCs) of patients with AD. In both AD and control blood samples, RBC PCOOH levels tended to correlate with plasma levels of Aβ40, and each PlsEtn species showed different correlations with plasma Aβ. These results, together with in vitro data suggesting Aβ aggregation due to a decrease in levels of PlsEtn having DHA, led us to deduce that Aβ is involved in alterations in levels of PCOOH and PlsEtn species observed in the blood of patients with AD.
Keywords: Aged; Amyloid beta-Peptides; Female; Humans; Hydrogen Peroxide; Male; Phosphatidylcholines; Plasmalogens

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Antioxidants Rescue Mitochondrial Transport in Differentiated Alzheimer's Disease Trans-Mitochondrial Cybrid Cells. - Yu, Qing; Fang, Du; Swerdlow, Russell Howard; Yu, Haiyang; Chen, John Xi; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Mitochondrial dysfunction and axonal degeneration are early pathological features of Alzheimer's disease (AD)-affected brains. The underlying mechanisms and strategies to rescue it have not been well elucidated. Here, we evaluated axonal mitochondrial transport and function in AD subject-derived mitochondria. We analyzed mitochondrial transport and kinetics in human trans-mitochondrial "cybrid" (cytoplasmic hybrid) neuronal cells whose mitochondria were derived from platelets of patients with sporadic AD and compared these AD cybrid cell lines with cybrid cell lines whose mitochondria were derived from age-matched, cognitively normal subjects. Human AD cybrid cell lines, when induced to differentiate, developed stunted projections. Mitochondrial transport and function within neuronal processes/axons was altered in AD-derived mitochondria. Antioxidants reversed deficits in axonal mitochondrial transport and function. These findings suggest that antioxidants may be able to mitigate the consequences of AD-associated mitochondrial dysfunction. The present study provides evidence of the cause/effect of AD specific mitochondrial defects, which significantly enhances our understanding of the AD pathogenesis and exploring the effective therapeutic strategy for AD.

The Anti-Prion Antibody 15B3 Detects Toxic Amyloid-β Oligomers. - Stravalaci, Matteo; Tapella, Laura; Beeg, Marten; Rossi, Alessandro; Joshi, Pooja; Pizzi, Erika; Mazzanti, Michele; Balducci, Claudia; Forloni, Gianluigi; Biasini, Emiliano; Salmona, Mario; Diomede, Luisa; et al. (J Alzheimers Dis, 2016)
15B3 is a monoclonal IgM antibody that selectively detects pathological aggregates of the prion protein (PrP). We report the unexpected finding that 15B3 also recognizes oligomeric but not monomeric forms of amyloid-β (Aβ)42, an aggregating peptide implicated in the pathogenesis of Alzheimer's disease (AD). The 15B3 antibody: i) inhibits the binding of synthetic Aβ42 oligomers to recombinant PrP and neuronal membranes; ii) prevents oligomer-induced membrane depolarization; iii) antagonizes the inhibitory effects of oligomers on the physiological pharyngeal contractions of the nematode Caenorhabditis elegans; and iv) counteracts the memory deficits induced by intracerebroventricular injection of Aβ42 oligomers in mice. Thus this antibody binds to pathologically relevant forms of Aβ, and offers a potential research, diagnostic, and therapeutic tool for AD.

Anti-Viral Properties of Amyloid-β Peptides. - Bourgade, Karine; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) peptides generated by the amyloidogenic pathway of amyloid-β protein precursor processing contribute significantly to neurodegeneration characteristic of Alzheimer's disease (AD). The involvement of Aβ peptides in the etiology of AD remains a subject of debate. Data published in the last 6 years by three different groups have added a new twist by revealing that Aβ peptides could act as antimicrobial peptides (AMP) in in vitro assays against some common and clinically relevant microorganisms, inhibit replication of seasonal and pandemic strains of influenza A and HSV-1 virus. These observations are of significance with respect to the notion that pathogens may be important contributors to the development of AD, particularly in the case of herpes simplex virus (HSV) infection, which often resides in the same cerebral sites where AD arises. Here, we review the data that support the interpretation that Aβ peptides behave as AMP, with an emphasis on studies concerning HSV-1 and a putative molecular mechanism that suggests that interactions between Aβ peptides and the HSV-1 fusogenic protein gB lead to impairment of HSV-1 infectivity by preventing the virus from fusing with the plasma membrane. A number of avenues for future research are suggested.

Assessment and Reporting of Driving Fitness in Patients with Dementia in Clinical Practice: Data from SveDem, the Swedish Dementia Registry. - Lovas, Joel; Fereshtehnejad, Seyed-Mohammad; Cermakova, Pavla; Lundberg, Catarina; Johansson, Björn; Johansson, Kurt; Winblad, Bengt; Eriksdotter, Maria; Religa, Dorota (J Alzheimers Dis, 2016)
BACKGROUND: Driving constitutes a very important aspect of daily life and is dependent on cognitive functions such as attention, visuo-spatial skills and memory, which are often compromised in dementia. Therefore, the driving fitness of patients with dementia needs to be addressed by physicians and those that are deemed unfit should not be allowed to continue driving. OBJECTIVE: We aimed at investigating to what extent physicians assess driving fitness in dementia patients and determinant factors for revoking of their licenses. METHODS: This study includes 15113 patients with newly diagnosed dementia and driver's license registered in the Swedish Dementia Registry (SveDem). The main outcomes were reporting to the licensing authority and making an agreement about driving eligibility with the patients. RESULTS: Physicians had not taken any action in 16% of dementia patients, whereas 9% were reported to the authority to have their licenses revoked. Males (OR = 3.04), those with an MMSE score between 20-24 (OR = 1.35) and 10-19 (OR = 1.50), patients with frontotemporal (OR = 3.09) and vascular dementia (OR = 1.26) were more likely to be reported to the authority. CONCLUSION: For the majority of patients with dementia, driving fitness was assessed. Nevertheless, physicians did not address the issue in a sizeable proportion of dementia patients. Type of dementia, cognitive status, age, sex and burden of comorbidities are independent factors associated with the assessment of driving fitness in patients with dementia. Increased knowledge on how these factors relate to road safety may pave the way for more specific guidelines addressing the issue of driving in patients with dementia.

Association between Cerebrospinal Fluid Biomarkers for Alzheimer's Disease, APOE Genotypes and Auditory Verbal Learning Task in Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Mandecka, Monika; Budziszewska, Magdalena; Barczak, Anna; Pepłońska, Beata; Chodakowska-Żebrowska, Małgorzata; Filipek-Gliszczyńska, Anna; Nesteruk, Marta; Styczyńska, Maria; Barcikowska, Maria; Gabryelewicz, Tomasz (J Alzheimers Dis, 2016)
In the course of Alzheimer's disease (AD), early pathological changes in the brain start decades before any clinical manifestation. The concentration levels of AD cerebrospinal fluid (CSF) biomarkers, such as amyloid-β1-42 (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau), may reflect a cerebral pathology facilitating an early diagnosis of the disease and predicting a cognitive deterioration. The aim of this study was to estimate the prevalence of AD CSF biomarkers in those individuals with a subjective cognitive decline (SCD), a mild cognitive impairment (MCI), and Alzheimer's dementia (AD-D), together with the relationships between the biomarkers, an APOE ɛ4 presence, and a verbal episodic memory performance. We included 252 patients from the memory clinic with a diagnosis of SCD (n = 85), MCI (n = 87), and AD-D (n = 80). A verbal episodic memory performance level was assessed and was based on a delayed recall trial from the 10-word list of an auditory verbal learning task (AVLT). We found that the patients with more severe cognitive impairments had significantly lower levels of Aβ1-42 and higher levels of T-tau and P-tau. This pattern was also typical for the APOE ɛ4 carriers, who had lower levels of Aβ1-42 than the noncarriers in the AD-D and MCI groups. The levels of T-tau and P-tau were significantly higher in the APOE ɛ4 carriers than in the noncarriers, but only in the MCI patients. The AVLT performance in the whole study samples was predicted by age, Aβ1-42, and the T-tau CSF biomarkers, but not by the APOE genotyping.

The Association Between Plasma Ceramides and Sphingomyelins and Risk of Alzheimer's Disease Differs by Sex and APOE in the Baltimore Longitudinal Study of Aging. - Mielke, Michelle M; Haughey, Norman J; Han, Dingfen; An, Yang; Bandaru, Veera Venkata Ratnam; Lyketsos, Constantine G; Ferrucci, Luigi; Resnick, Susan M (J Alzheimers Dis, 2016)
BACKGROUND: Cellular and animal studies demonstrated relationships between sphingolipid metabolism and Alzheimer's disease (AD) pathology. High blood ceramide levels have been shown to predict cognitive impairment and AD, but these studies had small sample sizes and did not assess differences in risk by sex or APOE genotype. OBJECTIVE: To determine whether plasma ceramides and sphingomyelins were associated with risk of AD, and whether the association varied by sex and APOE genotype. METHODS: Participants included 626 men and 366 women, aged 55 years and older, enrolled in the Baltimore Longitudinal Study of Aging. Plasma ceramides and sphingomyelins were determined using quantitative analyses performed on a high-performance liquid chromatography coupled electrospray ionization tandem mass spectrometer. Cox proportional hazards models, stratified by sex, were used to examine the relationship of plasma ceramides and sphingomyelins with risk of AD over a mean (SD) follow-up of 15.0 (7.0) years for men and 13.1 (5.9) years for women. RESULTS: Among men, the highest tertile of most ceramides and sphingomyelins were associated with an increased risk of AD. Among women, there were no associations between any of the ceramides and risk of AD. In contrast, women in the highest tertile of most sphingomyelins had a reduced risk of AD, which was most pronounced among APOE ɛ4 carriers. CONCLUSION: These results provide further evidence for the role of sphingolipid metabolism in AD and highlight the importance of considering sex and APOE genotype in assessing this relationship.

Association of Platelet Serotonin Levels in Alzheimer's Disease with Clinical and Cerebrospinal Fluid Markers. - Tajeddinn, Walid; Fereshtehnejad, Seyed-Mohammad; Seed Ahmed, Mohammed; Yoshitake, Takashi; Kehr, Jan; Shahnaz, Tasmin; Milovanovic, Micha; Behbahani, Homira; Höglund, Kina; Winblad, Bengt; Cedazo-Minguez, Angel; Jelic, Vesna; et al. (J Alzheimers Dis, 2016)
INTRODUCTION: Serotonin (5-HT) is involved in the pathology of Alzheimer's disease (AD). OBJECTIVE: We aimed to measure 5-HT level in platelets in AD and explore its association with cerebrospinal fluid (CSF), AD biomarkers (amyloid-β 1-42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau)), and clinical symptoms. METHODS: 15 patients with AD and 20 patients with subjective cognitive impairment (SCI) were included. 5-HT metabolites were measured, in a specific fraction, using high performance liquid chromatography with electrochemical detection (HPLC-ECD). RESULTS: Significantly lower 5-HT concentrations were observed in AD patients compared to SCI patients both after normalization against total protein (p = 0.008) or platelet count (p = 0.019). SCI patients with lower 5-HT level have higher AD CSF biomarkers, total tau (p = 0.026) and tau/Aβ42 ratio (p = 0.001), compared to those with high 5-HT levels. CONCLUSION: AD patients have reduced platelet 5-HT levels. In SCI, lower 5-HT content was associated with a higher AD-CSF biomarker burden.

Associations between Neuropsychiatric Symptoms and Cerebral Amyloid Deposition in Cognitively Impaired Elderly People. - Bensamoun, David; Guignard, Renaud; Furst, Ansgar J; Derreumaux, Alexandre; Manera, Valeria; Darcourt, Jacques; Benoit, Michel; Robert, Philippe H; David, Renaud (J Alzheimers Dis, 2016)
BACKGROUND: Neuropsychiatric symptoms, also known as behavioral and psychological symptoms of dementia (BPSD), affect the majority of patients with dementia, and result in a greater cognitive and functional impairment. OBJECTIVE: To investigate associations between BPSD and amyloid cerebral deposition as measured by 18F-Florbetapir-PET quantitative uptake in elderly subjects with and without cognitive impairment. METHODS: Participants with cognitive impairment [mild cognitive impairment (MCI) or Alzheimer's disease (AD)] and healthy controls (HC) from the ADNI cohort (Alzheimer Disease Neuroimaging Initiative) who underwent an 18F-florbetapir PET scan between May 2010 and March 2014 were included. Clinical assessments included the Clinical Dementia Rating, the Mini-Mental State Examination (MMSE), and the Neuropsychiatric Inventory. Freesurfer software was used to extract PET counts based on T1-based structural ROI (frontal, cingulate, parietal, and temporal). Spearman's partial correlation scores between BPSD severity and regional amyloid uptake were calculated. RESULTS: Data for 657 participants [age = 72.6 (7.19); MMSE = 27.4 (2.67)] were analyzed, including 230 HC [age = 73.1 (6.02); MMSE = 29 (1.21)], 308 MCI [age = 71.5 (7.44); MMSE = 28.0 (1.75)], and 119 AD subjects [age = 74.7 (8.05); MMSE = 23.1 (2.08)]. Considering all diagnostic groups together, positive significant correlations were found between anxiety and 18F-florbetapir uptake in the frontal (r = 0.102; p = 0.009), cingulate (r = 0.083; p = 0.034), and global cerebral uptake (r = 0.099; p = 0.011); between irritability and frontal (r = 0.089; p = 0.023), cingulate (r = 0.085; p = 0.030), parietal (r = 0.087; p = 0.025), and global cerebral uptake (r = 0.093; p = 0.017); in the MCI subgroup, between anxiety and frontal (r = 0.126; p = 0.03) and global uptake (r = 0.14; p = 0.013); in the AD subgroup, between irritability and parietal uptake (r = 0.201; p = 0.03). CONCLUSION: Anxiety and irritability are associated with greater amyloid deposition in the neurodegenerative process leading to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidogenic Proteins; Cerebral Cortex; Cognition Disorders; Cohort Studies; Female; Fluorodeoxyglucose F18; Humans; Male; Mental Status Schedule; Mood Disorders; Neuropsychological Tests; Positron-Emission Tomography

Astrocytic GluN2A and GluN2B Oppose the Synaptotoxic Effects of Amyloid-β1-40 in Hippocampal Cells. - Li, Yan; Chang, Lirong; Song, Yizhi; Gao, Xianghong; Roselli, Francesco; Liu, Jinping; Zhou, Wei; Fang, Yuan; Ling, Wei; Li, Hui; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Early-stage Alzheimer's disease (AD) is characterized by synaptic dysfunction, a phenomenon in which soluble oligomers of amyloid-beta (Aβ) and N-methyl-D-aspartate receptor (NMDAR) are implicated. Here, we demonstrated that astrocytes express NMDARs and therefore have the potential to modulate the synaptotoxic actions of Aβ. We found that specific pharmacological antagonism of two of the major NMDAR subunits, GluN2A and GluN2B, exacerbates Aβ-induced synaptotoxicity suggesting, for the first time, that astrocytic GluN2A and GluN2B mediate synaptoprotection. From the perspective of the pathogenic mechanisms of Alzheimer's disease, in which Aβ and NMDAR play significant roles, these observations are striking since neuronal GluN2A and GluN2B are well known modulators of neurodegeneration. We did initial studies to understand the basis for the differential effects of astrocytic and neuronal GluN2A and GluN2B in the promotion of synapse survival, and identified a neurotrophin produced by astrocytes, nerve growth factor β (β-NGF), as a likely mediator of the synaptoprotective effects of astrocytic GluN2A and GluN2B activation. The results presented suggest that astrocytes may be suitable druggable targets for the prevention and/or delay of the synaptic loss that occurs during early stages of AD.

AZD3293: A Novel, Orally Active BACE1 Inhibitor with High Potency and Permeability and Markedly Slow Off-Rate Kinetics. - Eketjäll, Susanna; Janson, Juliette; Kaspersson, Karin; Bogstedt, Anna; Jeppsson, Fredrik; Fälting, Johanna; Haeberlein, Samantha Budd; Kugler, Alan R; Alexander, Robert C; Cebers, Gvido (J Alzheimers Dis, 2016)
A growing body of pathological, biomarker, genetic, and mechanistic data suggests that amyloid accumulation, as a result of changes in production, processing, and/or clearance of brain amyloid-β peptide (Aβ) concentrations, plays a key role in the pathogenesis of Alzheimer's disease (AD). Beta-secretase 1 (BACE1) mediates the first step in the processing of amyloid-β protein precursor (AβPP) to Aβ peptides, with the soluble N terminal fragment of AβPP (sAβPPβ) as a direct product, and BACE1 inhibition is an attractive target for therapeutic intervention to reduce the production of Aβ. Here, we report the in vitro and in vivo pharmacological profile of AZD3293, a potent, highly permeable, orally active, blood-brain barrier (BBB) penetrating, BACE1 inhibitor with unique slow off-rate kinetics. The in vitro potency of AZD3293 was demonstrated in several cellular models, including primary cortical neurons. In vivo in mice, guinea pigs, and dogs, AZD3293 displayed significant dose- and time-dependent reductions in plasma, cerebrospinal fluid, and brain concentrations of Aβ40, Aβ42, and sAβPPβ. The in vitro potency of AZD3293 in mouse and guinea pig primary cortical neuronal cells was correlated to the in vivo potency expressed as free AZD3293 concentrations in mouse and guinea pig brains. In mice and dogs, the slow off-rate from BACE1 may have translated into a prolongation of the observed effect beyond the turnover rate of Aβ. The preclinical data strongly support the clinical development of AZD3293, and patients with AD are currently being recruited into a combined Phase 2/3 study to test the disease-modifying properties of AZD3293.
Keywords: Administration, Oral; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Blood Chemical Analysis; Blood-Brain Barrier; Brain; Dogs; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Enzyme Inhibitors; Female; Guinea Pigs; Humans; Imidazoles; Kinetics; Male; Mice, Inbred C57BL; Peptide Fragments; Spiro Compounds

AβPP/PS1 Transgenic Mice Show Sex Differences in the Cerebellum Associated with Aging. - Ordoñez-Gutierrez, Lara; Fernandez-Perez, Ivan; Herrera, Jose Luis; Anton, Marta; Benito-Cuesta, Irene; Wandosell, Francisco (J Alzheimers Dis, 2016)
Cerebellar pathology has been related to presenilin 1 mutations in certain pedigrees of familial Alzheimer's disease. However, cerebellum tissue has not been intensively analyzed in transgenic models of mutant presenilins. Furthermore, the effect of the sex of the mice was not systematically analyzed, despite the fact that important gender differences in the evolution of the disease in the human population have been described. We analyzed whether the progression of amyloidosis in a double transgenic mouse, AβPP/PS1, is susceptible to aging and differentially affects males and females. The accumulation of amyloid in the cerebellum differentially affects males and females of the AβPP/PS1 transgenic line, which was found to be ten-fold higher in 15-month-old females. Amyloid-β accumulation was more evident in the molecular layer of the cerebellum, but glia reaction was only observed in the granular layer of the older mice. The sex divergence was also observed in other neuronal, survival, and autophagic markers. The cerebellum plays an important role in the evolution of the pathology in this transgenic mouse model. Sex differences could be crucial for a complete understanding of this disease. We propose that the human population could be studied in this way. Sex-specific treatment strategies in human populations could show a differential response to the therapeutic approach.

Behavioral and Electrophysiological Correlates of Memory Binding Deficits in Patients at Different Risk Levels for Alzheimer's Disease. - Pietto, Marcos; Parra, Mario A; Trujillo, Natalia; Flores, Facundo; García, Adolfo M; Bustin, Julian; Richly, Pablo; Manes, Facundo; Lopera, Francisco; Ibáñez, Agustín; Baez, Sandra (J Alzheimers Dis, 2016)
Deficits in visual short-term memory (VSTM) binding have been proposed as an early and specific marker for Alzheimer's disease (AD). However, no studies have explored the neural correlates of this domain in clinical categories involving prodromal stages with different risk levels of conversion to AD. We assessed underlying electrophysiological modulations in patients with mild cognitive impairment (MCI), patients in the MCI stages of familial AD carrying the mutation E280A of the presenilin-1 gene (MCI-FAD), and healthy controls. Moreover, we compared the behavioral performance and neural correlates of both patient groups. Participants completed a change-detection VSTM task assessing recognition of changes between shapes or shape-color bindings, presented in two consecutive arrays (i.e., study and test) while event related potentials (ERPs) were recorded. Changes always occurred in the test array and consisted of new features replacing studied features (shape-only) or features swapping across items (shape-color binding). Both MCI and MCI-FAD patients performed worse than controls in the shape-color binding condition. Early electrophysiological activity (100-250 ms) was significantly reduced in both clinical groups, particularly over fronto-central and parieto-occipital regions. However, shape-color binding performance and their reduced neural correlates were similar between MCI and MCI-FAD. Our results support the validity of the VSTM binding test and their neural correlates in the early detection of AD and highlight the importance of studies comparing samples at different risk for AD conversion. The combined analysis of behavioral and ERP data gleaned with the VSTM binding task can offer a valuable memory biomarker for AD.

Bioenergetic Impairment in Animal and Cellular Models of Alzheimer's Disease: PARP-1 Inhibition Rescues Metabolic Dysfunctions. - Martire, Sara; Fuso, Andrea; Mosca, Luciana; Forte, Elena; Correani, Virginia; Fontana, Mario; Scarpa, Sigfrido; Maras, Bruno; d'Erme, Maria (J Alzheimers Dis, 2016)
Amyloid-beta peptide accumulation in the brain is one of the main hallmarks of Alzheimer's disease. The amyloid aggregation process is associated with the generation of free radical species responsible for mitochondrial impairment and DNA damage that in turn activates poly(ADP-ribose)polymerase 1 (PARP-1). PARP-1 catalyzes the poly(ADP-ribosylation), a post-translational modification of proteins, cleaving the substrate NAD+ and transferring the ADP-ribose moieties to the enzyme itself or to an acceptor protein to form branched polymers of ADP-ribose. In this paper, we demonstrate that a mitochondrial dysfunction occurs in Alzheimer's transgenic mice TgCRND8, in SH-SY5Y treated with amyloid-beta and in 7PA2 cells. Moreover, PARP-1 activation contributes to the functional energetic decline affecting cytochrome oxidase IV protein levels, oxygen consumption rates, and membrane potential, resulting in cellular bioenergetic deficit. We also observed, for the first time, an increase of pyruvate kinase 2 expression, suggesting a modulation of the glycolytic pathway by PARP-1. PARP-1 inhibitors are able to restore both mitochondrial impairment and pyruvate kinase 2 expression. The overall data here presented indicate a pivotal role for this enzyme in the bioenergetic network of neuronal cells and open new perspectives for investigating molecular mechanisms underlying energy charge decline in Alzheimer's disease. In this scenario, PARP-1 inhibitors might represent a novel therapeutic intervention to rescue cellular energetic metabolism.

Blockade of the Interaction of Calcineurin with FOXO in Astrocytes Protects Against Amyloid-β-Induced Neuronal Death. - Fernandez, Ana M; Hervas, Ruben; Dominguez-Fraile, Manuel; Garrido, Victoria Navarro; Gomez-Gutierrez, Patricia; Vega, Miguel; Vitorica, Javier; Perez, Juan J; Torres Aleman, Ignacio (J Alzheimers Dis, 2016)
Astrocytes actively participate in neuro-inflammatory processes associated to Alzheimer's disease (AD), and other brain pathologies. We recently showed that an astrocyte-specific intracellular signaling pathway involving an interaction of the phosphatase calcineurin with the transcription factor FOXO3 is a major driver in AD-associated pathological inflammation, suggesting a potential new druggable target for this devastating disease. We have now developed decoy molecules to interfere with calcineurin/FOXO3 interactions, and tested them in astrocytes and neuronal co-cultures exposed to amyloid-β (Aβ) toxicity. We observed that interference of calcineurin/FOXO3 interactions exerts a protective action against Aβ-induced neuronal death and favors the production of a set of growth factors that we hypothesize form part of a cytoprotective pathway to resolve inflammation. Furthermore, interference of the Aβ-induced interaction of calcineurin with FOXO3 by decoy compounds significantly decreased amyloid-β protein precursor (AβPP) synthesis, reduced the AβPP amyloidogenic pathway, resulting in lower Aβ levels, and blocked the expression of pro-inflammatory cytokines TNFα and IL-6 in astrocytes. Collectively, these data indicate that interrupting pro-inflammatory calcineurin/FOXO3 interactions in astrocytes triggered by Aβ accumulation in brain may constitute an effective new therapeutic approach in AD. Future studies with intranasal delivery, or brain barrier permeable decoy compounds, are warranted.

Cannabinoid Receptor 2 Participates in Amyloid-β Processing in a Mouse Model of Alzheimer's Disease but Plays a Minor Role in the Therapeutic Properties of a Cannabis-Based Medicine. - Aso, Ester; Andrés-Benito, Pol; Carmona, Margarita; Maldonado, Rafael; Ferrer, Isidre (J Alzheimers Dis, 2016)
The endogenous cannabinoid system represents a promising therapeutic target to modify neurodegenerative pathways linked to Alzheimer's disease (AD). The aim of the present study was to evaluate the specific contribution of CB2 receptor to the progression of AD-like pathology and its role in the positive effect of a cannabis-based medicine (1:1 combination of Δ9-tetrahidrocannabinol and cannabidiol) previously demonstrated to be beneficial in the AβPP/PS1 transgenic model of the disease. A new mouse strain was generated by crossing AβPP/PS1 transgenic mice with CB2 knockout mice. Results show that lack of CB2 exacerbates cortical Aβ deposition and increases the levels of soluble Aβ40. However, CB2 receptor deficiency does not affect the viability of AβPP/PS1 mice, does not accelerate their memory impairment, does not modify tau hyperphosphorylation in dystrophic neurites associated to Aβ plaques, and does not attenuate the positive cognitive effect induced by the cannabis-based medicine in these animals. These findings suggest a minor role for the CB2 receptor in the therapeutic effect of the cannabis-based medicine in AβPP/PS1 mice, but also constitute evidence of a link between CB2 receptor and Aβ processing.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cannabidiol; Cognition; Disease Models, Animal; Dronabinol; Humans; Male; Medical Marijuana; Memory; Mice, Inbred C57BL; Mice, Transgenic; Nootropic Agents; Presenilin-1; Random Allocation; Receptor, Cannabinoid, CB2; tau Proteins; Treatment Outcome

Cerebral Glucose Metabolism is Associated with Verbal but not Visual Memory Performance in Community-Dwelling Older Adults. - Gardener, Samantha L; Sohrabi, Hamid R; Shen, Kai-Kai; Rainey-Smith, Stephanie R; Weinborn, Michael; Bates, Kristyn A; Shah, Tejal; Foster, Jonathan K; Lenzo, Nat; Salvado, Olivier; Laske, Christoph; Laws, Simon M; et al. (J Alzheimers Dis, 2016)
Increasing evidence suggests that Alzheimer's disease (AD) sufferers show region-specific reductions in cerebral glucose metabolism, as measured by [18F]-fluoro-2-deoxyglucose positron emission tomography (18F-FDG PET). We investigated preclinical disease stage by cross-sectionally examining the association between global cognition, verbal and visual memory, and 18F-FDG PET standardized uptake value ratio (SUVR) in 43 healthy control individuals, subsequently focusing on differences between subjective memory complainers and non-memory complainers. The 18F-FDG PET regions of interest investigated include the hippocampus, amygdala, posterior cingulate, superior parietal, entorhinal cortices, frontal cortex, temporal cortex, and inferior parietal region. In the cohort as a whole, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in both the left hippocampus and right amygdala. There were no associations observed between global cognition, delayed recall in logical memory, or visual reproduction and 18F-FDG PET SUVR. Following stratification of the cohort into subjective memory complainers and non-complainers, verbal logical memory immediate recall was positively associated with 18F-FDG PET SUVR in the right amygdala in those with subjective memory complaints. There were no significant associations observed in non-memory complainers between 18F-FDG PET SUVR in regions of interest and cognitive performance. We observed subjective memory complaint-specific associations between 18F-FDG PET SUVR and immediate verbal memory performance in our cohort, however found no associations between delayed recall of verbal memory performance or visual memory performance. It is here argued that the neural mechanisms underlying verbal and visual memory performance may in fact differ in their pathways, and the characteristic reduction of 18F-FDG PET SUVR observed in this and previous studies likely reflects the pathophysiological changes in specific brain regions that occur in preclinical AD.

Cerebral Microbleeds and Cerebrovascular Reactivity in the General Population: The EDAN Study. - Akoudad, Saloua; Gurol, M Edip; Fotiadis, Panagiotis; Koudstaal, Peter J; Hofman, Albert; Ikram, M Arfan; Greenberg, Steven M; Vernooij, Meike W (J Alzheimers Dis, 2016)
BACKGROUND: In patients with symptomatic cerebral amyloid angiopathy (CAA), cerebrovascular reactivity to visual stimuli is reduced. Lobar microbleeds are a diagnostic hallmark of CAA, but are also highly prevalent in asymptomatic individuals. Recent data suggest that the latter group might have CAA. OBJECTIVE: We investigated whether cerebrovascular reactivity is impaired in asymptomatic individuals with lobar microbleeds. METHODS: From the population-based Rotterdam Study, we invited 35 participants with lobar microbleeds and 15 age-matched controls (all≥55 years) for functional MRI (fMRI) as part of the Early Detection of Angiopathy Network (EDAN) Study. Cerebrovascular reactivity parameters (i.e., amplitude and time to peak responses) were assessed in response to visual stimulation using fMRI. Student's t-test and linear regression were used to compare fMRI parameters in participants with and without microbleeds. RESULTS: Amplitude and time to peak responses did not differ between participants with and without microbleeds (respectively, p = 0.179 and p = 0.555). Participants with microbleeds had slightly higher amplitude responses compared to participants without microbleeds. After excluding individuals with mixed microbleeds (i.e., lobar and non-lobar microbleeds), we found no significant difference in cerebrovascular reactivity for persons with a single microbleed or multiple microbleeds compared to persons without microbleeds. CONCLUSIONS: In the general population, lobar microbleeds may not relate to impaired cerebrovascular reactivity. In asymptomatic individuals, lobar microbleeds may either reflect less advanced CAA pathology insufficient to cause functional vascular impairment, or reflect vascular pathology other than CAA.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers Across the Spectrum of Lewy Body Diseases: Results from a Large Multicenter Cohort. - van Steenoven, Inger; Aarsland, Dag; Weintraub, Daniel; Londos, Elisabet; Blanc, Frédéric; van der Flier, Wiesje M; Teunissen, Charlotte E; Mollenhauer, Brit; Fladby, Tormod; Kramberger, Milica G; Bonanni, Laura; Lemstra, Afina W (J Alzheimers Dis, 2016)
BACKGROUND: Concomitant Alzheimer's disease (AD) pathology is observed in Lewy body diseases (LBD), but the clinical impact is unknown. Only a few biomarker studies in LBD exist and have included small cohorts from single centers. OBJECTIVE: We aimed to evaluate the prevalence of abnormal cerebrospinal fluid (CSF) AD biomarkers across the spectrum of LBD in a large multicenter cohort and to assess whether an AD biomarker profile was associated with demographic and clinical differences in dementia with Lewy bodies (DLB). METHODS: We included 375 DLB patients, 164 Parkinson's disease (PD) patients without dementia, and 55 PD patients with dementia (PDD) from 10 centers. CSF amyloid-beta42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) values were dichotomized as abnormal or normal according to locally available cut-off values. A CSF AD profile was defined as abnormal Aβ42 combined with abnormal t-tau and/or p-tau. RESULTS: A substantial proportion of DLB patients had abnormal values for CSF Aβ42, t-tau, and p-tau, while abnormal values were uncommon in PD without dementia. Patients with PDD had values in between. A CSF AD profile was observed in 25% of DLB patients, compared with only 9% of PDD and 3% of PD without dementia. Within DLB, patients with a CSF AD profile were older, more often female, performed worse on the Mini-Mental State Examination, and had shorter disease duration compared with patients with normal CSF. CONCLUSION: A CSF AD profile is more common in DLB compared with PDD and PD, and is associated with more severe cognitive impairment in DLB.

Cerebrospinal Fluid Alzheimer's Disease Biomarkers in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Wacongne, Anne; Ayrignac, Xavier; Charif, Mahmoud; Fourcade, Genevieve; Azakri, Souhayla; Le Floch, Anne; Bouly, Stephane; Marelli, Cecilia; Arquizan, Caroline; Hirtz, Christophe; Gabelle, Audrey; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Decreased cerebrospinal fluid (CSF) amyloid-β 1-40 (Aβ40) and amyloid-β 1-42 (Aβ42) and increased total and phosphorylated tau (t-tau, p-tau) concentrations have been described in cerebral amyloid angiopathy (CAA). OBJECTIVE: Our aim was to analyze these biomarkers in patients with CAA-related inflammation (CAA-I). METHODS: We prospectively recruited nine patients with acute phase CAA-I fulfilling Chung criteria. CSF was analyzed for t-tau, p-tau, Aβ42, and Aβ40. Data were compared to controls (n = 14), patients with Alzheimer's disease (AD, n = 42), CAA (n = 10), and primary angiitis of the central nervous system (PACNS, n = 3). RESULTS: For the CAA-I group, statistically significant differences were: lower Aβ42 (p = 0.00053) compared to the control group; lower t-tau (p = 0.018), p-tau (p <  0.001), and Aβ40 (p <  0.001) compared to AD; lower Aβ42 (p = 0.027) compared to CAA; lower Aβ42 (p = 0.012) compared to PACNS. Nearly significantly lower Aβ40 (p = 0.051) and higher t-tau (p = 0.051) were seen in CAA-I compared to controls. CONCLUSION: CSF biomarkers profile similar to that of CAA was observed in CAA-I (with even lower levels of Aβ42 compared to CAA). Based on our findings, high p-tau seems more specific for AD, whereas low Aβ42 differentiates CAA-I from CAA, PACNS, and controls, and low Aβ40 differentiates CAA-I from AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Retrospective Studies; tau Proteins

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Cerebrospinal Fluid Biomarkers and Reserve Variables as Predictors of Future "Non-Cognitive" Outcomes of Alzheimer's Disease. - Ingber, Adam P; Hassenstab, Jason; Fagan, Anne M; Benzinger, Tammie L S; Grant, Elizabeth A; Holtzman, David M; Morris, John C; Roe, Catherine M (J Alzheimers Dis, 2016)
BACKGROUND: The influence of reserve variables and Alzheimer's disease (AD) biomarkers on cognitive test performance has been fairly well-characterized. However, less is known about the influence of these factors on "non-cognitive" outcomes, including functional abilities and mood. OBJECTIVE: We examined whether cognitive and brain reserve variables mediate how AD biomarker levels in cognitively normal persons predict future changes in function, mood, and neuropsychiatric behavior. METHODS: Non-cognitive outcomes were examined in 328 individuals 50 years and older enrolled in ongoing studies of aging and dementia at the Knight Alzheimer Disease Research Center (ADRC). All participants were cognitively normal at baseline (Clinical Dementia Rating [CDR] 0), completed cerebrospinal fluid (CSF) and structural neuroimaging studies within one year of baseline, and were followed for an average of 4.6 annual visits. Linear mixed effects models explored how cognitive reserve and brain reserve variables mediate the relationships between AD biomarker levels and changes in function, mood, and neuropsychiatric behavior in cognitively normal participants. RESULTS: Education levels did not have a significant effect on predicting non-cognitive decline. However, participants with smaller brain volumes exhibited the worst outcomes on measures of mood, functional abilities, and behavioral disturbance. This effect was most pronounced in individuals who also had abnormal CSF biomarkers. CONCLUSIONS: The findings suggest that brain reserve plays a stronger, or earlier, role than cognitive reserve in protecting against non-cognitive impairment in AD.

The Cerebrospinal Fluid Neurogranin/BACE1 Ratio is a Potential Correlate of Cognitive Decline in Alzheimer's Disease. - De Vos, Ann; Struyfs, Hanne; Jacobs, Dirk; Fransen, Erik; Klewansky, Tom; De Roeck, Ellen; Robberecht, Caroline; Van Broeckhoven, Christine; Duyckaerts, Charles; Engelborghs, Sebastiaan; Vanmechelen, Eugeen (J Alzheimers Dis, 2016)
BACKGROUND: In diagnosing Alzheimer's disease (AD), ratios of cerebrospinal fluid (CSF) biomarkers, such as CSF Aβ1-42/tau, have an improved diagnostic performance compared to the single analytes, yet, still a limited value to predict cognitive decline. Since synaptic dysfunction/loss is closely linked to cognitive impairment, synaptic proteins are investigated as candidate CSF AD progression markers. OBJECTIVE: We studied CSF levels of the postsynaptic protein neurogranin and protein BACE1, predominantly localized presynaptically, and their relation to CSF total-tau, Aβ1-42, Aβ1-40, and Aβ1-38. All six analytes were considered as single parameters as well as ratios. METHODS: Every ELISA involved was based on monoclonal antibodies, including the BACE1 and neurogranin immunoassay. The latter specifically targets neurogranin C-terminally truncated at P75, a more abundant species of the protein in CSF. We studied patients with MCI due to AD (n = 38) and 50 dementia due to AD patients, as well as age-matched cognitively healthy elderly (n = 20). A significant subset of the patients was followed up by clinical and neuropsychological (MMSE) examinations for at least one year. RESULTS: The single analytes showed statistically significant differences between the clinical groups, but the ratios of analytes indeed had a higher diagnostic performance. Furthermore, only the ratio of CSF neurogranin trunc P75/BACE1 was significantly correlated with the yearly decline in MMSE scores in patients with MCI and dementia due to AD, pointing toward the prognostic value of the ratio. CONCLUSION: This is the first study demonstrating that the CSF neurogranin trunc P75/BACE1 ratio, reflecting postsynaptic/presynaptic integrity, is related to cognitive decline.

Changes in Brain Volume with Bapineuzumab in Mild to Moderate Alzheimer's Disease. - Novak, Gerald; Fox, Nick; Clegg, Shona; Nielsen, Casper; Einstein, Steven; Lu, Yuan; Tudor, Iulia Cristina; Gregg, Keith; Di, Jianing; Collins, Peter; Wyman, Bradley T; Yuen, Eric; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Bapineuzumab, an anti-amyloid-β monoclonal antibody, was evaluated in two placebo-controlled trials in APOE*ɛ4 carriers and noncarriers, respectively, with Alzheimer's disease. OBJECTIVES: A volumetric magnetic resonance imaging substudy was performed to determine if bapineuzumab altered brain volume rate of change. METHODS: Bapineuzumab dosages included 0.5 mg/kg in carriers and 0.5 or 1.0 mg/kg in noncarriers, every 13 weeks for 78 weeks. Volumetric outcomes included annualized brain, ventricular, and mean hippocampal boundary shift integrals (BBSI; VBSI; HBSI) up to Week 71. Treatment differences were estimated using mixed models for repeated measures. RESULTS: For BBSI and HBSI, there were no significant treatment-related differences within either study, but, compared to pooled carriers and noncarriers receiving placebo, noncarriers receiving1.0 mg/kg bapineuzumab had greater increases in these measures. Bapineuzumab-treated patients showed significantly greater VBSI rates compared with placebo for 0.5 mg/kg in carriers and 1.0 mg/kg (but not 0.5 mg/kg) in noncarriers. CONCLUSIONS: Bapineuzumab produced an increase in ventricular volume compared with placebo. Etiology for this increase is unclear but may be related to amyloid-β clearance or its consequences.
Keywords: Aged; Alzheimer Disease; Antibodies, Monoclonal, Humanized; Apolipoprotein E4; Brain; Double-Blind Method; Female; Heterozygote; Humans; Least-Squares Analysis; Magnetic Resonance Imaging; Male; Nootropic Agents; Organ Size; Severity of Illness Index; Treatment Outcome

Characterization of Amyloid-β Deposits in Bovine Brains. - Vallino Costassa, Elena; Fiorini, Michele; Zanusso, Gianluigi; Peletto, Simone; Acutis, Pierluigi; Baioni, Elisa; Maurella, Cristiana; Tagliavini, Fabrizio; Catania, Marcella; Gallo, Marina; Faro, Monica Lo; Chieppa, Maria Novella; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) deposits are seen in aged individuals of many mammalian species that possess the same aminoacid sequence as humans. This study describes Aβ deposition in 102 clinically characterized cattle brains from animals aged 0 to 20 years. Extracellular and intracellular Aβ deposition was detected with 4G8 antibody in the cortex, hippocampus, and cerebellum. X-34 staining failed to stain Aβ deposits, indicating the non β-pleated nature of these deposits. Western blot analysis and surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry revealed in Tris, Triton, and formic acid fractions the presence of different Aβ peptides, characterized mainly by C-terminally truncated forms. Exploration of the genetic variability of APOE, PSEN1, and PSEN2 genes involved in Alzheimer's disease pathogenesis revealed several previously unreported polymorphisms. This study demonstrates certain similarities between Aβ deposition patterns exhibited in cattle brains and those in the human brain in early stages of aging. Furthermore, the identification of the same Aβ peptides reported in humans, but unable to form aggregates, supports the hypothesis that cattle may be protected against amyloid plaque formation.
Keywords: Aging; Amyloid beta-Peptides; Animals; Apolipoproteins E; Blotting, Western; Brain; Cattle; Extracellular Space; Gene Frequency; Genotyping Techniques; Glial Fibrillary Acidic Protein; Immunohistochemistry; Intracellular Space; Neuroglia; Neurons; Polymorphism, Genetic; Presenilin-1; Presenilin-2; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

CHRNA7 Gene and Response to Cholinesterase Inhibitors in an Italian Cohort of Alzheimer's Disease Patients. - Clarelli, Ferdinando; Mascia, Elisabetta; Santangelo, Roberto; Mazzeo, Salvatore; Giacalone, Giacomo; Galimberti, Daniela; Fusco, Federica; Zuffi, Marta; Fenoglio, Chiara; Franceschi, Massimo; Scarpini, Elio; Forloni, Gianluigi; et al. (J Alzheimers Dis, 2016)
Previous studies suggest that genetic variants in CHRNA7, which encodes for the major subunit of the acetylcholine receptor (α7-nAChR), are associated with the clinical response to cholinesterase inhibitors (ChEI) in Alzheimer's disease (AD) patients. We sought to replicate the association of two SNPs in the CHRNA7 gene, rs6494223 and rs8024987, with response to ChEI treatment in an Italian cohort of 169 AD patients, further extending the study to gene-level analysis. None of the tested variants was associated with clinical response. However, rs6494223 showed a consistent effect direction (OR = 1.4; p = 0.17), which after meta-analysis with previous study yielded a significant result (OR = 1.57, p = 0.02, I2 = 0%).

Chronic Cerebral Hypoperfusion Accelerates Alzheimer's Disease Pathology with Cerebrovascular Remodeling in a Novel Mouse Model. - Zhai, Yun; Yamashita, Toru; Nakano, Yumiko; Sun, Zhuoran; Shang, Jingwei; Feng, Tian; Morihara, Ryuta; Fukui, Yusuke; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
Recently, aging societies have been showing an increasingly strong relationship between Alzheimer's disease (AD) and chronic cerebral hypoperfusion (HP). In the present study, we created a new mouse model for AD with HP, and investigated its clinical and pathological characteristics. Alzheimer's disease transgenic mice (APP23) were subjected to bilateral common carotid arteries stenosis with ameroid constrictors for slowly progressive cerebral HP. In contrast to simple APP23 mice, cerebral HP exacerbated motor and cognitive dysfunctions with white matter lesions and meningo-parenchymal amyloid-β (Aβ) burdens. Strong cerebrovascular inflammation and severe amyloid angiopathy with cerebrovascular remodeling were also observed in APP23 + HP mouse brains. An acetylcholinesterase inhibitor galantamine improved such clinical dysfunctions, retrieved above neuropathological characteristics, and enhanced nicotinic acetylcholine receptor (nAChR)-binding activity. The present study demonstrates that chronic cerebral HP enhanced cognitive/motor dysfunctions with parenchymal/cerebrovascular Aβ accumulation and cerebrovascular remodeling. These neuropathological abnormalities were greatly ameliorated by galantamine treatment associated with nAChR-mediated neuroprotection by allosterically potentiating ligand action.

Chronic Obstructive Pulmonary Disease as a Risk Factor for Cognitive Dysfunction: A Meta-Analysis of Current Studies. - Zhang, Ximeng; Cai, Xiaoying; Shi, Xiaolei; Zheng, Zhenyang; Zhang, Aiwu; Guo, Junliang; Fang, Yannan (J Alzheimers Dis, 2016)
Cognitive dysfunction has been shown to be associated with many risk factors, such as smoking, diabetes, and body mass index. Chronic obstructive pulmonary disease (COPD), a common disease within the elderly population, has also been found to be related to cognitive decline. However, whether COPD is a risk factor of cognitive dysfunction is not well established. The purpose of this meta-analysis is to investigate the role COPD plays in cognitive dysfunction. PubMed, Cochrane library and Web of Science databases were searched. Three cohort studies and eleven cross-sectional studies were found to be eligible. According to our results, COPD patients had a higher risk of cognitive dysfunction than controls (OR [odds ratio]: 1.72; 95% CI, 1.12-2.65; p = 0.01). The exacerbation of COPD was strongly correlated with cognitive decline. COPD patients performed worse than controls on the Mini- Mental State Examination test, but the results were not statistically significant (OR: -0.79; 95% CI, [-1.78, 0.19]; p = 0.11). Thus, more attention should be given to the occurrence of cognitive decline in COPD patients. The prevention and control of COPD exacerbation are critical.
Keywords: Cognitive Dysfunction; Humans; Pulmonary Disease, Chronic Obstructive; Risk Factors

Chronic Traumatic Encephalopathy Presenting as Alzheimer's Disease in a Retired Soccer Player. - Grinberg, Lea T; Anghinah, Renato; Nascimento, Camila Fernandes; Amaro, Edson; Leite, Renata P; Martin, Maria da Graça M; Naslavsky, Michel S; Takada, Leonel T; Filho, Wilson Jacob; Pasqualucci, Carlos A; Nitrini, Ricardo (J Alzheimers Dis, 2016)
The relationship between soccer and chronic traumatic encephalopathy (CTE) is not well established. We report clinicopathological correlations in an 83-year-old retired center-back soccer player, with no history of concussion, manifesting typical Alzheimer-type dementia. Examination revealed mixed pathology including widespread CTE, moderate Alzheimer's disease, hippocampal sclerosis, and TDP-43 proteinopathy. This case adds to a few CTE cases described in soccer players. Furthermore, it corroborates that CTE may present clinically as typical Alzheimer-type dementia. Further studies investigating the extent to which soccer is a risk for CTE are needed.

Clinical Impact of a Second FDG-PET in Atypical/Unclear Dementia Syndromes. - Bergeron, David; Beauregard, Jean-Mathieu; Guimond, Jean; Fortin, Marie-Pierre; Houde, Michèle; Poulin, Stéphane; Verret, Louis; Bouchard, Rémi W; Laforce, Robert (J Alzheimers Dis, 2016)
Diagnosis of atypical/unclear dementia is often difficult and this delays treatment initiation. Several authors have shown that beyond standard dementia workup, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reduces the number of unclear diagnoses, leads to earlier treatment, and has a beneficial impact on families. However, it is not uncommon that the FDG-PET findings are equivocal in this setting. For those cases, a repeat FDG-PET may clarify the diagnosis and prevent treatment delay. We retrospectively assessed the clinical impact of a repeat FDG-PET in 59 patients with atypical/unclear dementia syndromes and inconclusive initial FDG-PET. Changes in primary diagnosis, diagnostic confidence, and management following the second FDG-PET were examined. Conducting a second FDG-PET reduced the number of unclear diagnoses from 80% to 34% , led to diagnostic change in 24% of cases, and treatment modification in 22% of patients. Overall, the clinical impact was higher when initial diagnostic confidence was low and the second FDG-PET repeated ≥12 months after the first one. In tertiary care memory clinic settings, when diagnostic incertitude persists despite extensive evaluation and an equivocal FDG-PET, repeating the FDG-PET 12 months later can greatly clarify the diagnosis and improve management.
Keywords: Adult; Brain; Dementia; Diagnosis, Differential; Female; Fluorodeoxyglucose F18; Humans; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; Retrospective Studies

Clinical Utility of Amyloid PET Imaging in the Differential Diagnosis of Atypical Dementias and Its Impact on Caregivers. - Bensaïdane, Mohamed Reda; Beauregard, Jean-Mathieu; Poulin, Stéphane; Buteau, François-Alexandre; Guimond, Jean; Bergeron, David; Verret, Louis; Fortin, Marie-Pierre; Houde, Michèle; Bouchard, Rémi W; Soucy, Jean-Paul; Laforce, Robert (J Alzheimers Dis, 2016)
Recent studies have supported a role for amyloid positron emission tomography (PET) imaging in distinguishing Alzheimer's disease (AD) pathology from other pathological protein accumulations leading to dementia. We investigated the clinical utility of amyloid PET in the differential diagnosis of atypical dementia cases and its impact on caregivers. Using the amyloid tracer 18F-NAV4694, we prospectively scanned 28 patients (mean age 59.3 y, s.d. 5.8; mean MMSE 21.4, s.d. 6.0) with an atypical dementia syndrome. Following a comprehensive diagnostic workup (i.e., history taking, neurological examination, blood tests, neuropsychological evaluation, MRI, and FDG-PET), no certain diagnosis could be arrived at. Amyloid PET was then conducted and classified as positive or negative. Attending physicians were asked to evaluate whether this result led to a change in diagnosis or altered management. They also reported their degree of confidence in the diagnosis. Caregivers were met after disclosure of amyloid PET results and completed a questionnaire/interview to assess the impact of the scan. Our cohort was evenly divided between positive (14/28) and negative (14/28) 18F-NAV4694 cases. Amyloid PET resulted in a diagnostic change in 9/28 cases (32.1%: 17.8% changed from AD to non-AD, 14.3% from non-AD to AD). There was a 44% increase in diagnostic confidence. Altered management occurred in 71.4% (20/28) of cases. Knowledge of amyloid status improved caregivers' outcomes in all domains (anxiety, depression, disease perception, future anticipation, and quality of life). This study suggests a useful additive role for amyloid PET in atypical cases with an unclear diagnosis beyond the extensive workup of a tertiary memory clinic. Amyloid PET increased diagnostic confidence and led to clinically significant alterations in management. The information gained from that test was well received by caregivers and encouraged spending quality time with their loved ones.

The Cognitive Change Index as a Measure of Self and Informant Perception of Cognitive Decline: Relation to Neuropsychological Tests. - Rattanabannakit, Chatchawan; Risacher, Shannon L; Gao, Sujuan; Lane, Kathleen A; Brown, Steven A; McDonald, Brenna C; Unverzagt, Frederick W; Apostolova, Liana G; Saykin, Andrew J; Farlow, Martin R (J Alzheimers Dis, 2016)
BACKGROUND: The perception of cognitive decline by individuals and those who know them well ("informants") has been inconsistently associated with objective cognitive performance, but strongly associated with depressive symptoms. OBJECTIVE: We investigated associations of self-report, informant-report, and discrepancy between self- and informant-report of cognitive decline obtained from the Cognitive Change Index (CCI) with cognitive test performance and self-reported depressive symptoms. METHODS: 267 participants with normal cognition, mild cognitive impairment (MCI), or mild dementia were included from a cohort study and memory clinic. Association of test performance and self-rated depression (Geriatric Depression Scale, GDS) with CCI scores obtained from subjects (CCI-S), their informants (CCI-I), and discrepancy scores between subjects and informants (CCI-D; CCI-S minus CCI-I) were analyzed using correlation and analysis of covariance (ANCOVA) models. RESULTS: CCI-S and CCI-I scores showed high internal consistency (Cronbach alpha 0.96 and 0.98, respectively). Higher scores on CCI-S and CCI-I, and lower scores on the CCI-D, were associated with lower performance on various cognitive tests in both univariate and in ANCOVA models adjusted for age, gender, and education. Adjustment for GDS slightly weakened the relationships between CCI and test performance but most remained significant. CONCLUSION: Self- and informant-report of cognitive decline, as measured by the CCI, show moderately strong relationships with objective test performance independent of age, gender, education, and depressive symptoms. The CCI appears to be a valid cross-sectional measure of self and informant perception of cognitive decline across the continuum of functioning. Studies are needed to address the relationship of CCI scores to longitudinal outcome.
Keywords: Adult; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Perception; Self Report

Cognitive Profile and its Association with Neuroimaging Markers of Non-Demented Cerebral Amyloid Angiopathy Patients in a Stroke Unit. - Xiong, Li; Davidsdottir, Sigurros; Reijmer, Yael D; Shoamanesh, Ashkan; Roongpiboonsopit, Duangnapa; Thanprasertsuk, Sekh; Martinez-Ramirez, Sergi; Charidimou, Andreas; Ayres, Alison M; Fotiadis, Panagiotis; Gurol, Edip; Blacker, Deborah L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Cerebral amyloid angiopathy (CAA) is increasingly recognized as a cause of cognitive impairment in the elderly, but the cognitive profile in patients with the disease has not been well characterized. OBJECTIVE: To characterize the neuropsychological profile of CAA patients without dementia and to determine the association between cognitive performance in different domains and neuroimaging lesions characteristic of CAA. METHODS: Fifty-eight non-demented CAA patients were compared to 138 cognitively normal subjects using a standard neuropsychological test battery. Total brain volume (TBV), white matter hyperintensities, number of lobar cerebral microbleeds, hippocampal volume, and cortical superficial siderosis in all CAA patients were assessed. The association between these neuroimaging markers and neuropsychological performance in different cognitive domains in the CAA group were analyzed. RESULTS: Patients with CAA had significantly worse performance on all individual neuropsychological domains tested, when compared to the cognitive normal group. The cognitive decline of CAA patients was most noticeable in tests for processing speed with a Z score of -1.92±1.56 (mean±SD), then followed by executive function (-0.93±1.01), episodic memory (-0.87±1.29), semantic fluency (-0.73±1.06), and attention (-0.42±0.98). TBV of the CAA patients was correlated with processing speed (β= 0.335, p = 0.03) and executive function (β= 0.394, p = 0.01). CONCLUSIONS: Non-demented patients with CAA had cognitive deficits in multiple areas. Lower TBV was related to slower processing speed and worse executive function.
Keywords: Aged; Atrophy; Brain; Cerebral Amyloid Angiopathy; Cognition; Cognition Disorders; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Stroke

Cognitive Stimulation for People with Dementia in Long-Term Care Facilities: Baseline Cognitive Level Predicts Cognitive Gains, Moderated by Depression. - Middelstädt, Jennifer; Folkerts, Ann-Kristin; Blawath, Sabrina; Kalbe, Elke (J Alzheimers Dis, 2016)
BACKGROUND: Increasing evidence demonstrates the efficacy of cognitive stimulation (CS) in individuals with dementia. However, conducting studies in nursing homes engenders specific challenges that have limited the data gathered on this topic so far. OBJECTIVE: The aim of this randomized controlled trial was to investigate the effects of CS on cognition, quality of life (QoL), behavioral symptoms, and activities of daily life in persons with dementia living in nursing homes. We further aimed to identify predictors of the intervention's benefits. METHODS: Seventy-one persons with mild to moderate dementia were randomly allocated to the experimental group (EG; n = 36) that visited a CS program twice weekly for eight weeks or to the control group (CG; n = 35) that was receiving usual care. Neuropsychological tests were conducted before and after the intervention period and at six-week follow-up. RESULTS: There were no significant interaction effects Time×Group for the outcome measures. However, regression analysis revealed that a low cognitive baseline level predicted cognitive improvements. Furthermore, a low baseline level of QoL predicted a QoL benefit. For both findings, depression was a significant moderator, meaning that persons with fewer depressive symptoms had a higher probability of showing improvements. CONCLUSION: This study provides data on profiles of patients who are most likely to profit from CS intervention in nursing-home settings and demonstrates that treatment of depression is of the utmost relevance for a positive outcome of CS. Living conditions will have to be considered more thoroughly in future research.

Cognitive Stimulation Modulates Platelet Total Phospholipases A2 Activity in Subjects with Mild Cognitive Impairment. - Balietti, Marta; Giuli, Cinzia; Fattoretti, Patrizia; Fabbietti, Paolo; Postacchini, Demetrio; Conti, Fiorenzo (J Alzheimers Dis, 2016)
We evaluated the effect of cognitive stimulation (CS) on platelet total phospholipases A2 activity (tPLA2A) in patients with mild cognitive impairment (MCI_P). At baseline, tPLA2A negatively correlated with Mini-Mental State Examination score (MMSE_s): patients with MMSE_s <26 (Subgroup 1) had significantly higher activity than those with MMSE_s ≥26 (Subgroup 2), who had values similar to the healthy elderly. Regarding CS effect, Subgroup 1 had a significant tPLA2A reduction, whereas Subgroup 2 did not significantly changes after training. Our results showed for the first time that tPLA2A correlates with the cognitive conditions of MCI_P, and that CS acts selectively on subjects with a dysregulated tPLA2A.
Keywords: Blood Platelets; Cognition; Cognitive Dysfunction; Cognitive Therapy; Cohort Studies; Humans; Mental Status Schedule; Neuropsychological Tests; Phospholipases A2; Treatment Outcome

Combination of Structural MRI and FDG-PET of the Brain Improves Diagnostic Accuracy in Newly Manifested Cognitive Impairment in Geriatric Inpatients. - Ritter, Kerstin; Lange, Catharina; Weygandt, Martin; Mäurer, Anja; Roberts, Anna; Estrella, Melanie; Suppa, Per; Spies, Lothar; Prasad, Vikas; Steffen, Ingo; Apostolova, Ivayla; Bittner, Daniel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The cause of cognitive impairment in acutely hospitalized geriatric patients is often unclear. The diagnostic process is challenging but important in order to treat potentially life-threatening etiologies or identify underlying neurodegenerative disease. OBJECTIVE: To evaluate the add-on diagnostic value of structural and metabolic neuroimaging in newly manifested cognitive impairment in elderly geriatric inpatients. METHODS: Eighty-one inpatients (55 females, 81.6±5.5 y) without history of cognitive complaints prior to hospitalization were recruited in 10 acute geriatrics clinics. Primary inclusion criterion was a clinical hypothesis of Alzheimer's disease (AD), cerebrovascular disease (CVD), or mixed AD+CVD etiology (MD), which remained uncertain after standard diagnostic workup. Additional procedures performed after enrollment included detailed neuropsychological testing and structural MRI and FDG-PET of the brain. An interdisciplinary expert team established the most probable etiologic diagnosis (non-neurodegenerative, AD, CVD, or MD) integrating all available data. Automatic multimodal classification based on Random Undersampling Boosting was used for rater-independent assessment of the complementary contribution of the additional diagnostic procedures to the etiologic diagnosis. RESULTS: Automatic 4-class classification based on all diagnostic routine standard procedures combined reproduced the etiologic expert diagnosis in 31% of the patients (p = 0.100, chance level 25%). Highest accuracy by a single modality was achieved by MRI or FDG-PET (both 45%, p≤0.001). Integration of all modalities resulted in 76% accuracy (p≤0.001). CONCLUSION: These results indicate substantial improvement of diagnostic accuracy in uncertain de novo cognitive impairment in acutely hospitalized geriatric patients with the integration of structural MRI and brain FDG-PET into the diagnostic process.

Combining Cerebrospinal Fluid Biomarkers and Neuropsychological Assessment: A Simple and Cost-Effective Algorithm to Predict the Progression from Mild Cognitive Impairment to Alzheimer's Disease Dementia. - Mazzeo, Salvatore; Santangelo, Roberto; Bernasconi, Maria Paola; Cecchetti, Giordano; Fiorino, Agnese; Pinto, Patrizia; Passerini, Gabriella; Falautano, Monica; Comi, Giancarlo; Magnani, Giuseppe (J Alzheimers Dis, 2016)
BACKGROUND: Correctly diagnosing Alzheimer's disease (AD) in prodromal phases would allow the adoption of experimental therapeutic strategies that could selectively interrupt the pathogenetic process before neuronal damage becomes irreversible. Therefore, great efforts have been aimed at finding early reliable disease markers. OBJECTIVE: The aim of this study was to identify a simple, cost effective, and reliable diagnostic algorithm to predict conversion from mild cognitive impairment (MCI) to AD. METHODS: 96 consecutive MCI patients admitted to the Neurology department of San Raffaele Hospital in Milan between January 2009 and January 2015 were included. All patients underwent neuropsychological assessment and lumbar puncture with CSF analysis of amyloid-β 42 (Aβ42), total tau (t-tau), and phosphorylated tau (p-tau) levels. Each patient underwent clinical and neuropsychological follow-up, in order to identify a possible progression from MCI to AD. The mean follow up time was 36.73 months. RESULTS: 37 out of 96 MCI converted to AD during follow up. CSF analysis and neuropsychological assessment reliably detected MCI patients who developed AD. In a subsample of 43 subjects, a Composite Cognitive Score (CCS) was calculated including episodic memory, executive function, and verbal fluency tests. Combining together CSF biomarkers and CCS increased the accuracy of the single predictors, correctly classifying 86% of patients with a specificity of 96% and a Positive Predictive Value of 93%. DISCUSSION: Even if preliminary, our data seem to suggest that CSF analysis and neuropsychological assessment could detect MCI patients who will convert to AD with high confidence. Their relative low cost and availability could make them worldwide essential tools in future clinical trials.

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Complementary and Alternative Medicine in the Context of Earlier Diagnoses of Alzheimer's Disease: Opening the Conversation to Prepare Ethical Responses. - Racine, Eric; Forlini, Cynthia; Aspler, John; Chandler, Jennifer (J Alzheimers Dis, 2016)
Preclinical Alzheimer's disease (AD), a newly proposed, actively researched, and hotly debated research-only diagnostic category, raises the prospect of an ethical dilemma: whether, and possibly how, to treat a disorder with no target symptoms. This proposed category rests on the detection of a number of biomarkers thought to provide evidence of AD pathophysiology years before any behavioral symptoms manifest. Faced with limited treatment options, patients and their relatives may come to consider complementary and alternative medicine (CAM) a viable option, albeit one with minimal supporting evidence. Accordingly, the hopes and needs of some preclinical patients and their relatives could further fuel market-oriented entrepreneurship for CAM. In this ethics review, we provide background and reflect on some ethical questions related to the roles of key stakeholders arising from the potential for CAM use in the context of a possible preclinical AD diagnosis.
Keywords: Alzheimer Disease; Complementary Therapies; Early Diagnosis; Ethical Analysis; Humans

Decreased Levels of VAMP2 and Monomeric Alpha-Synuclein Correlate with Duration of Dementia. - Vallortigara, Julie; Whitfield, David; Quelch, William; Alghamdi, Amani; Howlett, David; Hortobágyi, Tibor; Johnson, Mary; Attems, Johannes; O'Brien, John T; Thomas, Alan; Ballard, Clive G; Aarsland, Dag; et al. (J Alzheimers Dis, 2016)
Alpha-synuclein (α-syn) aggregations are the key pathological hallmark of dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), but are also frequently present in Alzheimer's disease (AD). Much remains unknown about the role of α-syn in the synapse and the wider role of synaptic dysfunction in these dementias. Changes in concentrations of key 'SNAP (Soluble N-ethylmaleimide Sensitive Factor Attachment Protein) Receptor' (SNARE) proteins as a consequence of alterations in the aggregation state of α-syn may contribute to synaptic dysfunction in patients with DLB, PDD, and AD and result in impaired cognition. We have studied a large cohort (n = 130) of autopsy confirmed DLB, PDD, AD, and control brains. Using semi-quantitative western blotting, we have demonstrated significant changes across the diagnostic groups of DLB, PDD, and AD in the SNARE and vesicle proteins syntaxin, Munc18, VAMP2, and monomeric α-syn in the prefrontal cortex, with a significant reduction of Munc18 in AD patients (p <  0.001). This correlated to the final MMSE score before death (p = 0.016). We also identified a significant negative correlation between the duration of dementia and the levels of the binding partners VAMP2 (p = 0.0004) and monomeric α-syn (p = 0.0002). Our findings may indicate that an upregulation of SNARE complex related proteins occurs in the early stages of disease as an attempt at compensating for failing synapses, prior to widespread deposition of pathological α-syn.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Amyloid beta-Peptides; Analysis of Variance; Cognition Disorders; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Regression Analysis; Synaptophysin; tau Proteins; Vesicle-Associated Membrane Protein 2

Delineating the Efficacy of a Cannabis-Based Medicine at Advanced Stages of Dementia in a Murine Model. - Aso, Ester; Andrés-Benito, Pol; Ferrer, Isidro (J Alzheimers Dis, 2016)
Previous reports have demonstrated that the combination of Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) botanical extracts, which are the components of an already approved cannabis-based medicine, reduce the Alzheimer-like phenotype of AβPP/PS1 transgenic mice when chronically administered during the early symptomatic stage. Here, we provide evidence that such natural cannabinoids are still effective in reducing memory impairment in AβPP/PS1 mice at advanced stages of the disease but are not effective in modifying the Aβ processing or in reducing the glial reactivity associated with aberrant Aβ deposition as occurs when administered at early stages of the disease. The present study also demonstrates that natural cannabinoids do not affect cognitive impairment associated with healthy aging in wild-type mice. The positive effects induced by Δ9-THC and CBD in aged AβPP/PS1 mice are associated with reduced GluR2/3 and increased levels of GABA-A Rα1 in cannabinoid-treated animals when compared with animals treated with vehicle alone.

Dementia and Rapid Mortality: Who is at Risk? - Staekenborg, Salka S; Pijnenburg, Yolande A L; Lemstra, Afina W; Scheltens, Philip; Vd Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is typically known for its insidious onset and slowly progressive course, but a subgroup deteriorates fast and dies within years or even months. OBJECTIVE: The purpose of this study was to characterize dementia patients with a rapidly progressive course to death and evaluate their cause of death. METHODS: We retrospectively included all patients from the Amsterdam Dementia Cohort who died within two years after diagnosis. We evaluated the characteristics of these rapid progressors and compared them to patients known to be alive two years after diagnosis ('non-rapid mortality'). RESULTS: We included 129 dementia patients (13% of our total cohort with known follow-up) with rapid mortality (age 72±10 y [29%  <65 y], 70[55%]M, MMSE 20±5). Mean(SD) survival was 12±7 months. Compared to non-rapid mortality patients (n = 892; age 68±9, 503(56%)M, MMSE 22±5), patients with rapid mortality were slightly older at time of diagnosis, had lower MMSE scores, more depressive symptoms and higher prevalence of a cardiovascular history (all p < 0.05). Alzheimer's disease (AD, 43%) was most frequent in patients with rapid mortality, but the occurrence was much lower compared to non-rapid mortality patients (71%), while all other dementia diagnoses, especially Creutzfeldt-Jakob disease (CJD), vascular dementia (VaD), and frontotemporal dementia (FTD), were more frequent (p < 0.001). There were no specific characteristics for AD patients with rapid versus non-rapid mortality, especially APOE genotypes and CSF-profiles were comparable (p > 0.70). Cause of death was highly variable without a clear relation to dementia diagnosis, with exception of dementia itself in CJD, intracerebral hematoma in VaD, and motor neuron disease in FTD. CONCLUSIONS: Short survival is relatively common (∼13% in our cohort) and occurs in all different types of dementia, with overrepresentation of non-AD dementias like CJD, VaD, and FTD.

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

Development of a Proxy-Free Objective Assessment Tool of Instrumental Activities of Daily Living in Mild Cognitive Impairment Using Smart Home Technologies. - Jekel, Katrin; Damian, Marinella; Storf, Holger; Hausner, Lucrezia; Frölich, Lutz (J Alzheimers Dis, 2016)
BACKGROUND: The assessment of activities of daily living (ADL) is essential for dementia diagnostics. Even in mild cognitive impairment (MCI), subtle deficits in instrumental ADL (IADL) may occur and signal a higher risk of conversion to dementia. Thus, sensitive and reliable ADL assessment tools are important. Smart homes equipped with sensor technology and video cameras may provide a proxy-free assessment tool for the detection of IADL deficits. OBJECTIVE: The aim of this paper is to investigate the potential of a smart home environment for the assessment of IADL in MCI. METHOD: The smart home consisted of a two-room flat equipped with activity sensors and video cameras. Participants with either MCI or healthy controls (HC) had to solve a standardized set of six tasks, e.g., meal preparation, telephone use, and finding objects in the flat. RESULTS: MCI participants needed more time (1384 versus 938 seconds, p <  0.001) and scored less total points (48 versus 57 points, p <  0.001) while solving the tasks than HC. Analyzing the subtasks, intergroup differences were observed for making a phone call, operating the television, and retrieving objects. MCI participants showed more searching and task-irrelevant behavior than HC. Task performance was correlated with cognitive status and IADL questionnaires but not with participants' age. CONCLUSION: This pilot study showed that smart home technologies offer the chance for an objective and ecologically valid assessment of IADL. It can be analyzed not only whether a task is successfully completed but also how it is completed. Future studies should concentrate on the development of automated detection of IADL deficits.

Diagnosing Dementia in the Clinical Setting: Can Amyloid PET Provide Additional Value Over Cerebrospinal Fluid? - Weston, Philip S J; Paterson, Ross W; Dickson, John; Barnes, Anna; Bomanji, Jamshed B; Kayani, Irfan; Lunn, Michael P; Mummery, Catherine J; Warren, Jason D; Rossor, Martin N; Fox, Nick C; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of amyloid and tau are the first-line Alzheimer's disease biomarkers in many clinical centers. We assessed if and when the addition of amyloid PET following CSF measurements provides added diagnostic value. Twenty patients from a cognitive clinic, who had undergone detailed assessment including CSF measures, went on to have amyloid PET. The treating neurologist's working diagnosis, and degree of diagnostic certainty, was assessed both before and after the PET. Amyloid PET changed the diagnosis in 7/20 cases. Amyloid PET can provide added diagnostic value, particularly in young-onset, atypical dementias, where CSF results are borderline and diagnostic uncertainty remains.

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer's Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies. - Barthélemy, Nicolas R; Gabelle, Audrey; Hirtz, Christophe; Fenaille, François; Sergeant, Nicolas; Schraen-Maschke, Susanna; Vialaret, Jérôme; Buée, Luc; Junot, Christophe; Becher, François; Lehmann, Sylvain (J Alzheimers Dis, 2016)
Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, specificity, sensitivity, and capturing property of the available antibodies. Mass spectrometry (MS) has recently allowed protein quantification in complex biological fluids using isotope-labeled recombinant standard for absolute quantification (PSAQ). To study Tau proteins, which are found at very low concentrations within the cerebrospinal fluid (CSF), we relied on an innovative two-step pre-fractionation strategy, which was not dependent on immuno-enrichment. We then developed a sensitive multiplex peptide detection capability using targeted high-resolution MS to quantify Tau-specific peptides covering its entire sequence. This approach was used on a clinical cohort of patients with AD, progressive supranuclear palsy (PSP), and dementia with Lewy body (DLB) and with control non-neurodegenerative disorders. We uncovered a common CSF Tau molecular profile characterized by a predominance of central core expression and 1N/3R isoform detection. While PSP and DLB tau profiles showed minimal changes, AD was characterized by a unique pattern with specific modifications of peptide distribution. Taken together these results provide important information on Tau biology for future therapeutic interventions, and improved molecular diagnosis of tauopathies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analysis of Variance; Chromatography, Liquid; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Peptide Fragments; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Statistics as Topic; Supranuclear Palsy, Progressive; tau Proteins

Differential Risk of Incident Alzheimer's Disease Dementia in Stable Versus Unstable Patterns of Subjective Cognitive Decline. - Wolfsgruber, Steffen; Kleineidam, Luca; Wagner, Michael; Mösch, Edelgard; Bickel, Horst; Lϋhmann, Dagmar; Ernst, Annette; Wiese, Birgitt; Steinmann, Susanne; König, Hans-Helmut; Brettschneider, Christian; Luck, Tobias; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer's disease (AD) dementia. OBJECTIVE: We tested the modifying role of temporal stability of the SCD report on AD dementia risk in cognitively normal elderly individuals. METHODS: We analyzed data of 1,990 cognitively normal participants from the longitudinal AgeCoDe Study. We assessed SCD with/without associated worries both at baseline and first follow-up 18 months later. Participants were then classified either as (a) Controls (CO, with no SCD at both baseline and follow-up 1, n = 613), (b) inconsistent SCD (with SCD reported only at baseline or at follow-up 1, n = 637), (c) consistent SCD but without/or with inconsistent worries (n = 610) or (d) consistent SCD with worries (n = 130). We estimated incident AD dementia risk over up to 6 years for each group with Cox-Proportional Hazard Regression analyses adjusted for age, gender, education, ApoE4 status, and depression. RESULTS: Compared to CO, inconsistent SCD was not associated with increased risk of incident AD dementia. In contrast, risk was doubled in the group of consistent SCD without/ with inconsistent worries, and almost 4-fold in the group of consistent SCD with worries. These results could be replicated when using follow-up 1 to follow-up 2 response patterns for group definition. CONCLUSION: These findings suggest that longitudinal stability versus instability is an important modifying factor of the association between SCD and AD dementia risk. Worrisome SCD that is also consistently reported over time is associated with greatly increased risk of AD dementia.

Dihydropyridine Derivatives Modulate Heat Shock Responses and have a Neuroprotective Effect in a Transgenic Mouse Model of Alzheimer's Disease. - Kasza, Ágnes; Hunya, Ákos; Frank, Zsuzsa; Fülöp, Ferenc; Török, Zsolt; Balogh, Gábor; Sántha, Miklós; Bálind, Árpád; Bernáth, Sándor; Blundell, Katie L I M; Prodromou, Chrisostomos; Horváth, Ibolya; et al. (J Alzheimers Dis, 2016)
Heat shock proteins (Hsps) have chaperone activity and play a pivotal role in the homeostasis of proteins by preventing misfolding, by clearing aggregated and damaged proteins from cells, and by maintaining proteins in an active state. Alzheimer's disease (AD) is thought to be caused by amyloid-β peptide that triggers tau hyperphosphorylation, which is neurotoxic. Although proteostasis capacity declines with age and facilitates the manifestation of neurodegenerative diseases such as AD, the upregulation of chaperones improves prognosis. Our research goal is to identify potent Hsp co-inducers that enhance protein homeostasis for the treatment of AD, especially 1,4-dihydropyridine derivatives optimized for their ability to modulate cellular stress responses. Based on favorable toxicological data and Hsp co-inducing activity, LA1011 was selected for the in vivo analysis of its neuroprotective effect in the APPxPS1 mouse model of AD. Here, we report that 6 months of LA1011 administration effectively improved the spatial learning and memory functions in wild type mice and eliminated neurodegeneration in double mutant mice. Furthermore, Hsp co-inducer therapy preserves the number of neurons, increases dendritic spine density, and reduces tau pathology and amyloid plaque formation in transgenic AD mice. In conclusion, the Hsp co-inducer LA1011 is neuroprotective and therefore is a potential pharmaceutical candidate for the therapy of neurodegenerative diseases, particularly AD.

Discrepancy in Expression of β-Secretase and Amyloid-β Protein Precursor in Alzheimer-Related Genes in the Rat Medial Temporal Lobe Cortex Following Transient Global Brain Ischemia. - Pluta, Ryszard; Kocki, Janusz; Ułamek-Kozioł, Marzena; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Brzozowska, Judyta; Furmaga-Jabłońska, Wanda; Bogucka-Kocka, Anna; Czuczwar, Stanisław J (J Alzheimers Dis, 2016)
Brain ischemia may be causally related with Alzheimer's disease. Presumably, β-secretase and amyloid-β protein precursor gene expression changes may be associated with Alzheimer's disease neuropathology. Consequently, we have examined quantitative changes in both β-secretase and amyloid-β protein precursor genes in the medial temporal lobe cortex with the use of quantitative rtPCR analysis following 10-min global brain ischemia in rats with survival of 2, 7, and 30 days. The greatest significant overexpression of β-secretase gene was noted on the 2nd day, while on days 7-30 the expression of this gene was only modestly downregulated. Amyloid-β protein precursor gene was downregulated on the 2nd day, but on days 7-30 postischemia, there was a significant reverse tendency. Thus, the demonstrated alterations indicate that the considerable changes of expression of β-secretase and amyloid-β protein precursor genes may be connected with a response of neurons in medial temporal lobe cortex to transient global brain ischemia. Finally, the ischemia-induced gene changes may play a key role in a late and slow onset of Alzheimer-type pathology.
Keywords: Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Brain Ischemia; Disease Models, Animal; Down-Regulation; Female; Rats; Rats, Wistar; Temporal Lobe; Time Factors

Disruption of White Matter Integrity by Chronic Cerebral Hypoperfusion in Alzheimer's Disease Mouse Model. - Zhai, Yun; Yamashita, Toru; Nakano, Yumiko; Sun, Zhuoran; Morihara, Ryuta; Fukui, Yusuke; Ohta, Yasuyuki; Hishikawa, Nozomi; Abe, Koji (J Alzheimers Dis, 2016)
A rapidly progressing aging society has raised attention to white matter lesions in Alzheimer's disease. In the present study, we applied an AD plus cerebral hypoperfusion (HP) mouse model and investigated the alternation of key protein molecules in the nodal, paranodal, and intermodal sites in the white matter as well as the efficacy of galantamine. Cerebral HP was induced in APP23 mice by bilateral common carotid arteries stenosis with ameroid constrictors. Compared with the wild type and simple APP23 mice, APP23 + HP mice showed a progressive loss of MAG and NF186 from 6 to 12 months, broken misdistribution of MBP, and extended relocation of Nav1.6 and AnkG beyond the primary nodal region in the corpus callosum. Such abnormal neuropathological processes were retrieved with galantamine treatment. The present study demonstrated that cerebral HP strongly disrupted white matter integrity (WMI) at intermodal, paranodal, and Ranvier's nodal sites which may be associated with cognitive decline. Galantamine treatment significantly protected such WMI probably by allosterically potentiating ligand action.

Distinct Patterns of Cognitive Aging Modified by Education Level and Gender among Adults with Limited or No Formal Education: A Normative Study of the Mini-Mental State Examination. - Xie, Haiqun; Zhang, Chengguo; Wang, Yukai; Huang, Shuyun; Cui, Wei; Yang, Wenbin; Koski, Lisa; Xu, Xiping; Li, Youbao; Zheng, Meili; He, Mingli; Fu, Jia; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is increasingly prevalent due to rapid aging of the population, but under-recognized among people with low education levels. This is partly due to a lack of appropriate and precise normative data, which underestimates cognitive aging in the use of screening tools for dementia. OBJECTIVE: We aimed to improve the precision of screening for cognitive impairment, by characterizing the patterns of cognitive aging and derived normative data of the Mini-Mental State Examination (MMSE) for illiterate and low-educated populations. METHODS: This community-based study included data from 2,280 individuals aged 40 years or older from two rural areas. Multiple linear modeling examined the effect of aging on cognition reflected by the MMSE, stratified by education level and gender. Threshold effect of age on cognition was performed using a smoothing function. RESULTS: The majority of participants (60.4%) were illiterate or had attended only primary school (24.6%). The effect of aging on cognition varied by gender and education. Primary-school educated females and males remained cognitively stable up to 62 and 71 years of age, respectively, with MMSE score declining 0.4 and 0.8 points/year in females and males thereafter. Illiterates females scored 2.3 points lower than illiterate males, and scores for both declined 0.2 points/year. According to these results, normative data stratified by age, education and gender was generated. CONCLUSION: This study suggests gender and educational differences exist in cognitive aging among adults with limited or no formal education. To improve screening precision for cognitive impairment with the use of MMSE in low-educated population, age, gender, and education level should be considered.
Keywords: Adult; Aged; Aged, 80 and over; China; Cognition Disorders; Cognitive Aging; Educational Status; Female; Humans; Male; Mental Status Schedule; Middle Aged; Reference Values; Rural Population; Sex Characteristics

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Does Microglial Activation Influence Hippocampal Volume and Neuronal Function in Alzheimer's Disease and Parkinson's Disease Dementia? - Femminella, Grazia D; Ninan, Siddharth; Atkinson, Rebecca; Fan, Zhen; Brooks, David J; Edison, Paul (J Alzheimers Dis, 2016)
BACKGROUND: The influence of neuroinflammation on neuronal function and hippocampal atrophy in Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) is still unclear. OBJECTIVES: Here we investigated whether microglial activation measured by [11C]PK11195 PET is associated with neuronal function measured by cerebral glucose metabolic rate (rCMRGlc) using FDG-PET and hippocampal volume measurements. METHODS: We enrolled 25 subjects (9 PDD, 8 AD, and 8 controls) who underwent PET scans with [11C](R)PK11195, [18F]FDG, and volumetric MRI scanning. RESULTS: SPM correlation analysis in AD and PDD showed a negative correlation between hippocampal volume and microglial activation within hippocampus or parahippocampus and with cortical and subcortical areas of projections from hippocampus, while there was a positive correlation between rCMRGlc in cortical and subcortical areas of projections from hippocampus and hippocampal volume. Hippocampal volume was significantly reduced in AD compared to controls but not in PDD. CONCLUSIONS: These findings indicate that microglial activation inversely correlated with hippocampal volume and hippocampal rCMRGlc in neurodegenerative diseases with dementia, providing further evidence for the central role of microglial activation in neurodegenerative diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antineoplastic Agents; Brain Mapping; Cognition; Female; Fluorodeoxyglucose F18; Hippocampus; Humans; Isoquinolines; Magnetic Resonance Imaging; Male; Microglia; Middle Aged; Neurons; Neuropsychological Tests; Parkinson Disease; Positron-Emission Tomography; Psychiatric Status Rating Scales; Supranuclear Palsy, Progressive

Dysregulation of Autophagy, Mitophagy, and Apoptotic Genes in the Medial Temporal Lobe Cortex in an Ischemic Model of Alzheimer's Disease. - Ułamek-Kozioł, Marzena; Kocki, Janusz; Bogucka-Kocka, Anna; Petniak, Alicja; Gil-Kulik, Paulina; Januszewski, Sławomir; Bogucki, Jacek; Jabłoński, Mirosław; Furmaga-Jabłońska, Wanda; Brzozowska, Judyta; Czuczwar, Stanisław J; Pluta, Ryszard (J Alzheimers Dis, 2016)
Ischemic brain damage is a pathological incident that is often linked with medial temporal lobe cortex injury and finally its atrophy. Post-ischemic brain injury associates with poor prognosis since neurons of selectively vulnerable ischemic brain areas are disappearing by apoptotic program of neuronal death. Autophagy has been considered, after brain ischemia, as a guardian against neurodegeneration. Consequently, we have examined changes in autophagy (BECN 1), mitophagy (BNIP 3), and apoptotic (caspase 3) genes in the medial temporal lobe cortex with the use of quantitative reverse-transcriptase PCR following transient 10-min global brain ischemia in rats with survival 2, 7, and 30 days. The intense significant overexpression of BECN 1 gene was noted on the 2nd day, while on days 7-30 the expression of this gene was still upregulated. BNIP 3 gene was downregulated on the 2nd day, but on days 7-30 post-ischemia, there was a significant reverse tendency. Caspase 3 gene, associated with apoptotic neuronal death, was induced in the same way as BNIP 3 gene after brain ischemia. Thus, the demonstrated changes indicate that the considerable dysregulation of expression of BECN 1, BNIP 3, and caspase 3 genes may be connected with a response of neuronal cells in medial temporal lobe cortex to transient complete brain ischemia.

Early Cognitive Deficits in Type 2 Diabetes: A Population-Based Study. - Marseglia, Anna; Fratiglioni, Laura; Laukka, Erika J; Santoni, Giola; Pedersen, Nancy L; Bäckman, Lars; Xu, Weili (J Alzheimers Dis, 2016)
Evidence links type 2 diabetes to dementia risk. However, our knowledge on the initial cognitive deficits in diabetic individuals and the factors that might promote such deficits is still limited. This study aimed to identify the cognitive domains initially impaired by diabetes and the factors that play a role in this first stage. Within the population-based Swedish National Study on Aging and Care-Kungsholmen, 2305 cognitively intact participants aged ≥60 y were identified. Attention/working memory, perceptual speed, category fluency, letter fluency, semantic memory, and episodic memory were assessed. Diabetes (controlled and uncontrolled) and prediabetes were ascertained by clinicians, who also collected information on vascular disorders (hypertension, heart diseases, and stroke) and vascular risk factors (VRFs, including smoking and overweight/obesity). Data were analyzed with linear regression models. Overall, 196 participants (8.5%) had diabetes, of which 144 (73.5%) had elevated glycaemia (uncontrolled diabetes); 571 (24.8%) persons had prediabetes. In addition, diabetes, mainly uncontrolled, was related to lower performance in perceptual speed (β - 1.10 [95% CI - 1.98, - 0.23]), category fluency (β - 1.27 [95% CI - 2.52, - 0.03]), and digit span forward (β - 0.35 [95% CI - 0.54, - 0.17]). Critically, these associations were present only among APOEɛ4 non-carriers. The associations of diabetes with perceptual speed and category fluency were present only among participants with VRFs or vascular disorders. Diabetes, especially uncontrolled diabetes, is associated with poorer performance in perceptual speed, category fluency, and attention/primary memory. VRFs, vascular disorders, and APOE status play a role in these associations.

Early in vivo Effects of the Human Mutant Amyloid-β Protein Precursor (hAβPPSwInd) on the Mouse Olfactory Bulb. - Rusznák, Zoltán; Kim, Woojin Scott; Hsiao, Jen-Hsiang T; Halliday, Glenda M; Paxinos, George; Fu, YuHong (J Alzheimers Dis, 2016)
The amyloid-β protein precursor (AβPP) has long been linked to Alzheimer's disease (AD). Using J20 mice, which express human AβPP with Swedish and Indiana mutations, we studied early pathological changes in the olfactory bulb. The presence of AβPP/amyloid-β (Aβ) was examined in mice aged 3 months (before the onset of hippocampal Aβ deposition) and over 5 months (when hippocampal Aβ deposits are present). The number of neurons, non-neurons, and proliferating cells was assessed using the isotropic fractionator method. Our results demonstrate that although AβPP is overexpressed in some of the mitral cells, widespread Aβ deposition and microglia aggregates are not prevalent in the olfactory bulb. The olfactory bulbs of the younger J20 group harbored significantly fewer neurons than those of the age-matched wild-type mice (5.57±0.13 million versus 6.59±0.36 million neurons; p = 0.011). In contrast, the number of proliferating cells was higher in the young J20 than in the wild-type group (i.e., 6617±425 versus 4455±623 cells; p = 0.011). A significant increase in neurogenic activity was also observed in the younger J20 olfactory bulb. In conclusion, our results indicate that (1) neurons participating in the mouse olfactory function overexpress AβPP; (2) the cellular composition of the young J20 olfactory bulb is different from that of wild-type littermates; (3) these differences may reflect altered neurogenic activity and/or delayed development of the J20 olfactory system; and (4) AβPP/Aβ-associated pathological changes that take place in the J20 hippocampus and olfactory bulb are not identical.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cell Proliferation; Disease Models, Animal; Gene Expression Regulation; Humans; Ki-67 Antigen; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurogenesis; Neurons; Olfactory Bulb; Piriform Cortex

Early Postmenopausal Transdermal 17β-Estradiol Therapy and Amyloid-β Deposition. - Kantarci, Kejal; Lowe, Val J; Lesnick, Timothy G; Tosakulwong, Nirubol; Bailey, Kent R; Fields, Julie A; Shuster, Lynne T; Zuk, Samantha M; Senjem, Matthew L; Mielke, Michelle M; Gleason, Carey; Jack, Clifford R; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It remains controversial whether hormone therapy in recently postmenopausal women modifies the risk of Alzheimer's disease (AD). OBJECTIVE: To investigate the effects of hormone therapy on amyloid-β deposition in recently postmenopausal women. METHODS: Participants within 5-36 months past menopause in the Kronos Early Estrogen Prevention Study, a randomized, double blinded placebo-controlled clinical trial, were randomized to: 1) 0.45 mg/day oral conjugated equine estrogens (CEE); 2) 50μg/day transdermal 17β-estradiol; or 3) placebo pills and patch for four years. Oral progesterone (200 mg/day) was given to active treatment groups for 12 days each month. 11C Pittsburgh compound B (PiB) PET imaging was performed in 68 of the 118 participants at Mayo Clinic approximately seven years post randomization and three years after stopping randomized treatment. PiB Standard unit value ratio (SUVR) was calculated. RESULTS: Women (age = 52-65) randomized to transdermal 17β-estradiol (n = 21) had lower PiB SUVR compared to placebo (n = 30) after adjusting for age [odds ratio (95% CI) = 0.31(0.11-0.83)]. In the APOEɛ4 carriers, transdermal 17β-estradiol treated women (n = 10) had lower PiB SUVR compared to either placebo (n = 5) [odds ratio (95% CI) = 0.04(0.004-0.44)], or the oral CEE treated group (n = 3) [odds ratio (95% CI) = 0.01(0.0006-0.23)] after adjusting for age. Hormone therapy was not associated with PiB SUVR in the APOEɛ4 non-carriers. CONCLUSION: In this pilot study, transdermal 17β-estradiol therapy in recently postmenopausal women was associated with a reduced amyloid-β deposition, particularly in APOEɛ4 carriers. This finding may have important implications for the prevention of AD in postmenopausal women, and needs to be confirmed in a larger sample.

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

EEG Markers of Dementia with Lewy Bodies: A Multicenter Cohort Study. - Bonanni, Laura; Franciotti, Raffaella; Nobili, Flavio; Kramberger, Milica G; Taylor, John-Paul; Garcia-Ptacek, Sara; Falasca, N Walter; Famá, Francesco; Cromarty, Ruth; Onofrj, Marco; Aarsland, Dag (J Alzheimers Dis, 2016)
Quantitative EEG (QEEG) has demonstrated good discriminative capacity for dementia with Lewy bodies (DLB) diagnosis as compared to Alzheimer's disease (AD) with a predictive value of 100% in a single cohort study. EEG in DLB was characterized by a dominant frequency (DF) in pre-alpha (5.5-7.5 Hz), theta, or delta bands and DF variability (DFV) >1.2 Hz, frequency prevalence (FP) pre-alpha in >40% and FP alpha in <32% of the epochs. To validate the aforementioned QEEG findings in independent cohorts of clinically diagnosed DLB versus AD patients, we analyzed EEG traces of 79 DLB and 133 AD patients (MMSE >20) collected from four European Centers. EEG traces from 19 scalp derivations were acquired as at least 10 min continuous signals and epoched in off-setting as series of 2-second-long epochs, subsequently processed by Fast Fourier Transform (frequency resolution 0.5 Hz). DLB patients showed EEG specific abnormalities in posterior derivations characterized by DF <8 Hz FP pre-alpha >50%, FP alpha <25%. DFV was >0.5 Hz. AD patients displayed stable alpha DF, DFV <0.5 Hz, FP pre-alpha <30%, and FP alpha >55%. DLB and AD differed for DF (p < 10-6), DFV (p < 0.05), FP pre-alpha (p < 10-12) and FP alpha (p < 10-12). Discriminant analysis detected specific cut-offs for every EEG mathematical descriptor; DF = 8, DFV = 2.2 Hz, FP pre-alpha=33%, FP alpha = 41% for posterior derivations. If at least one of the cut-off values was met, the percentage of DLB and AD patients correctly classified was 90% and 64%, respectively. The findings in this multicenter study support the validity of QEEG analysis as a tool for diagnosis in DLB patients.

The Effect of Propofol Versus Isoflurane Anesthesia on Human Cerebrospinal Fluid Markers of Alzheimer's Disease: Results of a Randomized Trial. - Berger, Miles; Nadler, Jacob W; Friedman, Allan; McDonagh, David L; Bennett, Ellen R; Cooter, Mary; Qi, Wenjing; Laskowitz, Daniel T; Ponnusamy, Vikram; Newman, Mark F; Shaw, Leslie M; Warner, David S; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Preclinical studies have found differential effects of isoflurane and propofol on the Alzheimer's disease (AD)-associated markers tau, phosphorylated tau (p-tau) and amyloid-β (Aβ). OBJECTIVE: We asked whether isoflurane and propofol have differential effects on the tau/Aβ ratio (the primary outcome), and individual AD biomarkers. We also examined whether genetic/intraoperative factors influenced perioperative changes in AD biomarkers. METHODS: Patients undergoing neurosurgical/otolaryngology procedures requiring lumbar cerebrospinal fluid (CSF) drain placement were prospectively randomized to receive isoflurane (n = 21) or propofol (n = 18) for anesthetic maintenance. We measured perioperative CSF sample AD markers, performed genotyping assays, and examined intraoperative data from the electronic anesthesia record. A repeated measures ANOVA was used to examine changes in AD markers by anesthetic type over time. RESULTS: The CSF tau/Aβ ratio did not differ between isoflurane- versus propofol-treated patients (p = 1.000). CSF tau/Aβ ratio and tau levels increased 10 and 24 h after drain placement (p = 2.002×10-6 and p = 1.985×10-6, respectively), mean CSF p-tau levels decreased (p = 0.005), and Aβ levels did not change (p = 0.152). There was no interaction between anesthetic treatment and time for any of these biomarkers. None of the examined genetic polymorphisms, including ApoE4, were associated with tau increase (n = 9 polymorphisms, p > 0.05 for all associations). CONCLUSION: Neurosurgery/otolaryngology procedures are associated with an increase in the CSF tau/Aβ ratio, and this increase was not influenced by anesthetic type. The increased CSF tau/Aβ ratio was largely driven by increases in tau levels. Future work should determine the functional/prognostic significance of these perioperative CSF tau elevations.

Effectiveness of Supporting Informal Caregivers of People with Dementia: A Systematic Review of Randomized and Non-Randomized Controlled Trials. - Vandepitte, Sophie; Van Den Noortgate, Nele; Putman, Koen; Verhaeghe, Sofie; Faes, Kristof; Annemans, Lieven (J Alzheimers Dis, 2016)
BACKGROUND: Dementia is known as a major public health problem affecting both patients and caregivers, and placing a high financial strain upon society. In community-dwelling patients, it is important to support informal caregivers in order to help them sustain their demanding role. Previous reviews about effectiveness of such supporting strategies often included a small number of studies, focused only on particular supportive types, particular outcomes, or solely on caregivers. OBJECTIVE: A general systematic review was conducted investigating effectiveness of different supportive strategies on at least the well-being of the caregiver or the care-recipient. METHODS: A systematic literature search was conducted in Web of Science and PubMed. An adapted version of the Downs and Black (1998) checklist was used to assess methodological quality. A new classification was developed to group different types of caregiver support. RESULTS: Fifty-three papers met the inclusion criteria. Although 87% of the interventions were to some extent effective, methods and findings were rather inconsistent. Psychoeducational interventions generally lead to positive outcomes for caregivers, and delay permanent institutionalization of care-recipients. Cognitive behavioral therapy decreases dysfunctional thoughts among caregivers. Occupational therapy decreases behavioral problems among patients and improves self-efficacy of caregivers. In general, those interventions tailored on individual level generate better outcomes. Comparative research on respite care was very rare. CONCLUSIONS: Despite methodological inconsistency, supporting caregivers appears to be an effective strategy often improving well-being of caregiver or care-recipient and resulting in additional benefits for society. However, there is a need for more research on the (cost)-effectiveness of respite care.

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Elevated mRNA Expression and Low Methylation of SNCA in Japanese Alzheimer's Disease Subjects. - Yoshino, Yuta; Mori, Takaaki; Yoshida, Taku; Yamazaki, Kiyohiro; Ozaki, Yuki; Sao, Tomoko; Funahashi, Yu; Iga, Jun-Ichi; Ueno, Shu-Ichi (J Alzheimers Dis, 2016)
Despite the continuing debate about the amyloid hypothesis in Alzheimer's disease (AD), the precise pathogenesis is still unclear. Mixed pathology is common and multiple different protein aggregates are seen in human postmortem brains. Aggregates consisting of the alpha-synuclein protein encoded by the Synuclein Alpha gene (SCNA) are common in both dementia with Lewy bodies and AD. We examined SNCA mRNA expression and methylation rates of the CpG island at intron 1 of SNCA in peripheral leukocytes in 50 AD and age- and sex-matched control subjects to verify whether alpha-synuclein pathology affects the AD pathogenesis. SNCA mRNA expression in AD subjects was significantly higher than that in control subjects (1.62±0.73 versus 0.98±0.50, p < 0.001). We found significant differences between AD and control subjects at seven CpG sites (average rate; 8.8±2.7 versus 9.5±2.5, respectively: p = 0.027). The methylation rates tended to be lower in AD subjects at all CpG sites. We conclude that mRNA expression and methylation of SNCA intron 1 are altered in AD, which may be caused by Lewy body pathology in AD.

Evaluation of a Genetic Risk Score to Improve Risk Prediction for Alzheimer's Disease. - Chouraki, Vincent; Reitz, Christiane; Maury, Fleur; Bis, Joshua C; Bellenguez, Celine; Yu, Lei; Jakobsdottir, Johanna; Mukherjee, Shubhabrata; Adams, Hieab H; Choi, Seung Hoan; Larson, Eric B; Fitzpatrick, Annette; et al. (J Alzheimers Dis, 2016)
Effective prevention of Alzheimer's disease (AD) requires the development of risk prediction tools permitting preclinical intervention. We constructed a genetic risk score (GRS) comprising common genetic variants associated with AD, evaluated its association with incident AD and assessed its capacity to improve risk prediction over traditional models based on age, sex, education, and APOEɛ4. In eight prospective cohorts included in the International Genomics of Alzheimer's Project (IGAP), we derived weighted sum of risk alleles from the 19 top SNPs reported by the IGAP GWAS in participants aged 65 and older without prevalent dementia. Hazard ratios (HR) of incident AD were estimated in Cox models. Improvement in risk prediction was measured by the difference in C-index (Δ-C), the integrated discrimination improvement (IDI) and continuous net reclassification improvement (NRI>0). Overall, 19,687 participants at risk were included, of whom 2,782 developed AD. The GRS was associated with a 17% increase in AD risk (pooled HR = 1.17; 95% CI =   [1.13-1.21] per standard deviation increase in GRS; p-value =  2.86×10-16). This association was stronger among persons with at least one APOEɛ4 allele (HRGRS = 1.24; 95% CI =   [1.15-1.34]) than in others (HRGRS = 1.13; 95% CI =   [1.08-1.18]; pinteraction = 3.45×10-2). Risk prediction after seven years of follow-up showed a small improvement when adding the GRS to age, sex, APOEɛ4, and education (Δ-Cindex =  0.0043 [0.0019-0.0067]). Similar patterns were observed for IDI and NRI>0. In conclusion, a risk score incorporating common genetic variation outside the APOEɛ4 locus improved AD risk prediction and may facilitate risk stratification for prevention trials.

Evaluation of Neuropathological Effects of a High-Fat Diet in a Presymptomatic Alzheimer's Disease Stage in APP/PS1 Mice. - Ettcheto, Miren; Petrov, Dmitry; Pedrós, Ignacio; Alva, Norma; Carbonell, Teresa; Beas-Zarate, Carlos; Pallas, Merce; Auladell, Carme; Folch, Jaume; Camins, Antoni (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is currently an incurable aging-related neurodegenerative disorder. Recent studies give support to the hypotheses that AD should be considered as a metabolic disease. The present study aimed to explore the relationship between hippocampal neuropathological amyloid-β (Aβ) plaque formation and obesity at an early presymptomatic disease stage (3 months of age). For this purpose, we used APPswe/PS1dE9 (APP/PS1) transgenic mice, fed with a high-fat diet (HFD) in order to investigate the potential molecular mechanisms involved in both disorders. The results showed that the hippocampus from APP/PS1 mice fed with a HFD had an early significant decrease in Aβ signaling pathway specifically in the insulin degrading enzyme protein levels, an enzyme involved in (Aβ) metabolism, and α-secretase. These changes were accompanied by a significant increase in the occurrence of plaques in the hippocampus of these mice. Furthermore, APP/PS1 mice showed a significant hippocampal decrease in PGC-1α levels, a cofactor involved in mitochondrial biogenesis. However, HFD does not provoke changes in neither insulin receptors gene expression nor enzymes involved in the signaling pathway. Moreover, there are no changes in any enzymes (kinases) involved in tau phosphorylation, such as CDK5, and neither in brain oxidative stress production. These results suggest that early changes in brains of APP/PS1 mice fed with a HFD are mediated by an increase in Aβ1 ‒ 42, which induces a decrease in PKA levels and alterations in the p-CREB/ NMDA2B /PGC1-α pathway, favoring early AD neuropathology in mice.

The Evolution of Caregiver Burden in Frontotemporal Dementia with and without Amyotrophic Lateral Sclerosis. - Hsieh, Sharpley; Leyton, Cristian E; Caga, Jashelle; Flanagan, Emma; Kaizik, Cassandra; O'Connor, Claire M; Kiernan, Matthew C; Hodges, John R; Piguet, Olivier; Mioshi, Eneida (J Alzheimers Dis, 2016)
BACKGROUND AND AIMS: Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) represent a disease spectrum. Caregiver burden in subtypes of FTD has not yet been directly compared with those patients who have co-existent FTD and ALS (ALSFTD). METHOD: Perceived caregiver burden was evaluated using the short Zarit Burden Interview (ZBI) in patients with behavioral-variant FTD (bvFTD, n = 21), semantic dementia (SD, n = 18), and ALSFTD (n = 15) at the initial clinical presentation and follow-up assessments. The Mini-Addenbrooke's Cognitive Examination (M-ACE) and the Motor Neuron Disease Behaviour Scale (MiND-B) were also used. Linear mixed effects models examined longitudinal changes on the ZBI, M-ACE, and MiND-B across groups. RESULTS: Burden at baseline was highest for the bvFTD group. Longitudinally, perceived burden increased for the SD and ALSFTD groups whereas in bvFTD, the level of burden which was high at baseline and remained high with disease progression. The severity of abnormal behaviors at baseline, as assessed by the MiND-B, correlated with baseline levels of caregiver burden and further accounted for 23% of the variance in caregiver burden at clinical follow-up. CONCLUSIONS: The trajectory of perceived burden differs across the FTD-ALS spectrum, with SD and ALSFTD caregivers demonstrating an increased burden that develops over time, compared to a persistently high level for bvFTD caregivers, evident throughout the disease course. The evolution of burden in these three syndromes likely reflects the initial presentation and clinical characterization that develops with time. Psycho-education programs for caregivers, which provide better coping strategies for challenging behaviors, may reduce levels of burden experienced with disease progression.
Keywords: Adaptation, Psychological; Aged; Amyotrophic Lateral Sclerosis; Analysis of Variance; Caregivers; Case-Control Studies; Cost of Illness; Disease Progression; Female; Frontotemporal Dementia; Humans; Interviews as Topic; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Surveys and Questionnaires

Evolution of the Antidepressant Prescribing in Alzheimer's Disease and Related Disorders Between 2010 and 2014: Results from the French National Database on Alzheimer's Disease (BNA). - David, Renaud; Manera, Valeria; Fabre, Roxane; Pradier, Christian; Robert, Philippe; Tifratene, Karim (J Alzheimers Dis, 2016)
BACKGROUND: Safety warnings from health authorities are currently intended to limit the use of psychotropic agents in dementia-related conditions. Evidence concerning the use of antidepressants in dementia is, however, scarce and contradictory. OBJECTIVE: To evaluate antidepressant use among individuals with Alzheimer's disease (AD) and related disorders in the French population between 2010 and 2014. METHOD: Antidepressant prescriptions in individuals with AD, mixed dementia (MD), and vascular dementia (VaD) in the French National Alzheimer Database between 2010 and 2014 were analyzed (N = 199,544). RESULTS: Multivariate analysis showed an annual significant increase (p < 0.001) in the prescription rate of antidepressants from 26% (2010) to 31% (2014), and identified female gender, younger age, higher education, living in long-term facilities, more severe cognitive decline, and presence of vascular signs (VaD and MD) as associated factors for antidepressant prescribing. CONCLUSION: The annual increase of antidepressant prescribing among individuals with AD, MD, and VaD in French specialized settings may be partially related to the lack of current valuable medications for dementia-related behavioral symptoms.

Expression of the Alzheimer's Disease Mutations AβPP695sw and PSEN1M146I in Double-Transgenic Göttingen Minipigs. - Jakobsen, Jannik E; Johansen, Marianne G; Schmidt, Mette; Liu, Ying; Li, Rong; Callesen, Henrik; Melnikova, Margarita; Habekost, Mette; Matrone, Carmela; Bouter, Yvonne; Bayer, Thomas A; Nielsen, Anders Lade; et al. (J Alzheimers Dis, 2016)
Mutations in the amyloid-β protein precursor gene (AβPP), the presenilin 1 gene (PSEN1) or the presenilin 2 gene (PSEN2) that increase production of the AβPP-derived peptide Aβ42 cause early-onset Alzheimer's disease. Rodent models of the disease show that further increase in Aβ42 production and earlier brain pathology can be obtained by coexpressing AβPP and PSEN1 mutations. To generate such elevated Aβ42 level in a large animal model, we produced Göttingen minipigs carrying in their genome one copy of a human PSEN1 cDNA with the Met146Ile (PSEN1M146I) mutation and three copies of a human AβPP695 cDNA with the Lys670Asn/Met671Leu (AβPPsw) double-mutation. Both transgenes were expressed in fibroblasts and in the brain, and their respective proteins were processed normally. Immunohistochemical staining with Aβ42-specific antibodies detected intraneuronal accumulation of Aβ42 in brains from a 10- and an 18-month-old pig. Such accumulation may represent an early event in the pathogenesis of Alzheimer's disease.

Fibrillar Amyloid-β Accumulation Triggers an Inflammatory Mechanism Leading to Hyperphosphorylation of the Carboxyl-Terminal End of Tau Polypeptide in the Hippocampal Formation of the 3×Tg-AD Transgenic Mouse. - Ontiveros-Torres, Miguel Ángel; Labra-Barrios, María Luisa; Díaz-Cintra, Sofía; Aguilar-Vázquez, Azucena Ruth; Moreno-Campuzano, Samadhi; Flores-Rodríguez, Paola; Luna-Herrera, Claudia; Mena, Raúl; Perry, George; Florán-Garduño, Benjamín; Luna-Muñoz, José; Luna-Arias, Juan Pedro (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a degenerative and irreversible disorder whose progressiveness is dependent on age. It is histopathologically characterized by the massive accumulation of insoluble forms of tau and amyloid-β (Aβ) asneurofibrillary tangles and neuritic plaques, respectively. Many studies have documented that these two polypeptides suffer several posttranslational modifications employing postmortem tissue sections from brains of patients with AD. In order to elucidate the molecular mechanisms underlying the posttranslational modifications of key players in this disease, including Aβ and tau, several transgenic mouse models have been developed. One of these models is the 3×Tg-AD transgenic mouse, carrying three transgenes encoding APPSWE, S1M146V, and TauP301L proteins. To further characterize this transgenicmouse, we determined the accumulation of fibrillar Aβ as a function of age in relation to the hyperphosphorylation patterns of TauP301L at both its N- and C-terminus in the hippocampal formation by immunofluorescence and confocal microscopy. Moreover, we searched for the expression of activated protein kinases and mediators of inflammation by western blot of wholeprotein extracts from hippocampal tissue sections since 3 to 28 months as well. Our results indicate that the presence of fibrillar Aβ deposits correlates with a significant activation of astrocytes and microglia in subiculum and CA1 regions of hippocampus. Accordingly, we also observed a significant increase in the expression of TNF-α associated to neuritic plaques and glial cells. Importantly, there is an overexpression of the stress activated protein kinases SAPK/JNK and Cdk-5 in pyramidal neurons, which might phosphorylate several residues at the C-terminus of TauP301L. Therefore, the accumulation of Aβ oligomers results in an inflammatory environment that upregulates kinases involved in hyperphosphorylation of TauP301L polypeptide.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Hippocampus; Humans; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroglia; Phosphorylation; Plaque, Amyloid; Presenilin-1; Pyramidal Cells; tau Proteins

FOXP2 Expression in Frontotemporal Lobar Degeneration-Tau. - López-González, Irene; Palmeira, Andre; Aso, Ester; Carmona, Margarita; Fernandez, Liana; Ferrer, Isidro (J Alzheimers Dis, 2016)
FOXP2 is altered in a variety of language disorders. We found reduced mRNA and protein expression of FOXP2 in frontal cortex area 8 in Pick's disease, and frontotemporal lobar degeneration-tau linked to P301L mutation presenting with language impairment in comparison with age-matched controls and cases with parkinsonian variant progressive supranuclear palsy. Foxp2 mRNA and protein are also reduced with disease progression in the somatosensory cortex in transgenic mice bearing the P301S mutation in MAPT when compared with wild-type littermates. Our findings support the presence of FOXP2 expression abnormalities in sporadic and familial frontotemporal degeneration tauopathies.

Gene Expression of Quaking in Sporadic Alzheimer's Disease Patients is Both Upregulated and Related to Expression Levels of Genes Involved in Amyloid Plaque and Neurofibrillary Tangle Formation. - Farnsworth, Bryn; Peuckert, Christiane; Zimmermann, Bettina; Jazin, Elena; Kettunen, Petronella; Emilsson, Lina Sors (J Alzheimers Dis, 2016)
Quaking (QKI) is a gene exclusively expressed within glial cells. QKI has previously been implicated in various neurological disorders and diseases, including Alzheimer's disease (AD), a condition for which increasing evidence suggests a central role of glia cells. The objective of the present study was to investigate the expression levels of QKI and three QKI isoforms (QKI5, QKI6, and QKI7) in AD. Genes that have previously been related to the ontogeny and progression of AD, specifically APP, PSEN1, PSEN2, and MAPT, were also investigated. A real-time PCR assay of 123 samples from human postmortem sporadic AD patients and control brains was performed. The expression values were analyzed with an analysis of covariance model and subsequent multiple regressions to explore the possibility of related expression values between QKI, QKI isoforms, and AD-related genes. Further, the sequences of AD-related genes were analyzed for the presence of QKI binding domains. QKI and all measured QKI isoforms were found to be significantly upregulated in AD samples, relative to control samples. However, APP, PSEN1, PSEN2, and MAPT were not found to be significantly different. QKI and QKI isoforms were found to be predictive for the variance of APP, PSEN1, PSEN2, and MAPT, and putative QKI binding sites suggests an interaction with QKI. Overall, these results implicate a possible role of QKI in AD, although the exact mechanism by which this occurs remains to be uncovered.

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

Higher Fasting Plasma Glucose Levels, within the Normal Range, are Associated with Decreased Processing Speed in High Functioning Young Elderly. - Raizes, Meytal; Elkana, Odelia; Franko, Motty; Ravona Springer, Ramit; Segev, Shlomo; Beeri, Michal Schnaider (J Alzheimers Dis, 2016)
We explored the association of plasma glucose levels within the normal range with processing speed in high functioning young elderly, free of type 2 diabetes mellitus (T2DM). A sample of 41 participants (mean age = 64.7, SD = 10; glucose 94.5 mg/dL, SD = 9.3), were examined with a computerized cognitive battery. Hierarchical linear regression analysis showed that higher plasma glucose levels, albeit within the normal range (<110 mg/dL), were associated with longer reaction times (p <  0.01). These findings suggest that even in the subclinical range and in the absence of T2DM, monitoring plasma glucose levels may have an impact on cognitive function.
Keywords: Aged; Blood Glucose; Cognition; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Linear Models; Male; Middle Aged; Neuropsychological Tests; Psychomotor Performance; Reaction Time; Reference Values

Hippocampal Lipid Homeostasis in APP/PS1 Mice is Modulated by a Complex Interplay Between Dietary DHA and Estrogens: Relevance for Alzheimer's Disease. - Díaz, Mario; Fabelo, Noemí; Casañas-Sánchez, Verónica; Marin, Raquel; Gómez, Tomás; Quinto-Alemany, David; Pérez, José A (J Alzheimers Dis, 2016)
Current evidence suggests that lipid homeostasis in the hippocampus is affected by different genetic, dietary, and hormonal factors, and that its deregulation may be associated with the onset and progression of Alzheimer's disease (AD). However, the precise levels of influence of each of these factors and their potential interactions remain largely unknown, particularly during neurodegenerative processes. In the present study, we have performed multifactorial analyses of the combined effects of diets containing different doses of docosahexaenoic acid (DHA), estrogen status (ovariectomized animals receiving vehicle or 17β-estradiol), and genotype (wild-type or transgenic APP/PS1 mice) in hippocampal lipid profiles. We have observed that the three factors affect lipid classes and fatty acid composition to different extents, and that strong interactions between these factors exist. The most aberrant lipid profiles were observed in APP/PS1 animals receiving DHA-poor diets and deprived of estrogens. Conversely, wild-type animals under a high-DHA diet and receiving estradiol exhibited a lipid profile that closely resembled that of the hippocampus of control animals. Interestingly, though the lipid signatures of APP/PS1 hippocampi markedly differed from wild-type, administration of a high-DHA diet in the presence of estrogens gave rise to a lipid profile that approached that of control animals. Paralleling changes in lipid composition, patterns of gene expression of enzymes involved in lipid biosynthesis were also altered and affected by combination of experimental factors. Overall, these results indicate that hippocampal lipid homeostasis is strongly affected by hormonal and dietary conditions, and that manipulation of these factors might be incorporated in AD therapeutics.
Keywords: Acyl Coenzyme A; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Disease Models, Animal; Docosahexaenoic Acids; Dose-Response Relationship, Drug; Estrogens; Gene Expression Regulation; Hippocampus; Homeostasis; Humans; Lipid Metabolism; Mice; Mice, Transgenic; Mutation; Presenilin-1; RNA, Messenger

Homotaurine Effects on Hippocampal Volume Loss and Episodic Memory in Amnestic Mild Cognitive Impairment. - Spalletta, Gianfranco; Cravello, Luca; Gianni, Walter; Piras, Federica; Iorio, Mariangela; Cacciari, Claudia; Casini, Anna Rosa; Chiapponi, Chiara; Sancesario, Giuseppe; Fratangeli, Claudia; Orfei, Maria Donata; Caltagirone, Carlo; et al. (J Alzheimers Dis, 2016)
Homotaurine supplementation may have a positive effect on early Alzheimer's disease. Here, we investigated its potential neuroprotective effect on the hippocampus structure and episodic memory performances in amnestic mild cognitive impairment (aMCI). Neuropsychological, clinical, and neuroimaging assessment in 11 treated and 22 untreated patients were performed at baseline and after 1 year. Magnetic resonance data were analyzed using voxel-based morphometry to explore significant differences (Family Wise Error corrected) between the two groups over time. Patients treated with homotaurine showed decreased volume loss in the left and right hippocampal tail, left and right fusiform gyrus, and right inferior temporal cortex which was associated with improved short-term episodic memory performance as measured by the recency effect of the Rey 15-word list learning test immediate recall. Thus, homotaurine supplementation in individuals with aMCI has a positive effect on hippocampus atrophy and episodic memory loss. Future studies should further clarify the mechanisms of its effects on brain morphometry.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Chi-Square Distribution; Cognitive Dysfunction; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Status Schedule; Middle Aged; Neuroprotective Agents; Neuropsychological Tests; Taurine

Human Truncated Tau Induces Mature Neurofibrillary Pathology in a Mouse Model of Human Tauopathy. - Zimova, Ivana; Brezovakova, Veronika; Hromadka, Tomas; Weisova, Petronela; Cubinkova, Veronika; Valachova, Bernadeta; Filipcik, Peter; Jadhav, Santosh; Smolek, Tomas; Novak, Michal; Zilka, Norbert (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) represents the most common neurodegenerative disorder. Several animal models have been developed in order to test pathophysiological mechanisms of the disease and to predict effects of pharmacological interventions. Here we examine the molecular and behavioral features of R3m/4 transgenic mice expressing human non-mutated truncated tau protein (3R tau, aa151-391) that were previously used for efficacy testing of passive tau vaccine. The mouse model reliably recapitulated crucial histopathological features of human AD, such as pre-tangles, neurofibrillary tangles, and neuropil threads. The pathology was predominantly located in the brain stem. Transgenic mice developed mature sarkosyl insoluble tau complexes consisting of mouse endogenous and human truncated and hyperphosphorylated forms of tau protein. The histopathological and biochemical features were accompanied by significant sensorimotor impairment and reduced lifespan. The sensorimotor impairment was monitored by a highly sensitive, fully-automated tool that allowed us to assess early deficit in gait and locomotion. We suggest that the novel transgenic mouse model can serve as a valuable tool for analysis of the therapeutic efficacy of tau vaccines for AD therapy.

Impact of Omega-3 Fatty Acid Supplementation on Memory Functions in Healthy Older Adults. - Külzow, Nadine; Witte, A Veronica; Kerti, Lucia; Grittner, Ulrike; Schuchardt, Jan Philipp; Hahn, Andreas; Flöel, Agnes (J Alzheimers Dis, 2016)
As the process of Alzheimer's disease (AD) begins years before disease onset, searching for prevention strategies is of major medical and economic importance. Nutritional supplementation with long-chain polyunsaturated omega-3 fatty acids (LC-n3-FA) may exert beneficial effects on brain structure and function. However, experimental evidence in older adults without clinical dementia is inconsistent, possibly due to low sensitivity of previously employed test batteries for detecting subtle improvements in cognition in healthy individuals. Here we used LOCATO, recently described as a robust and sensitive tool for assessing object-location memory (OLM) in older adults, to evaluate the impact of LC-n3-FA supplementation on learning and memory formation. In a double-blind placebo-controlled proof-of-concept study, 44 (20 female) cognitively healthy individuals aged 50-75 years received either LC-n3-FA (2,200 mg/day, n = 22) or placebo (n = 22) for 26 weeks. Before and after intervention, memory performance in the OLM-task (primary) was tested. As secondary outcome parameters, performance in Rey Auditory Verbal Learning Test (AVLT), dietary habits, omega-3-index, and other blood-derived parameters were assessed. Omega-3 index increased significantly in the LC-n3-FA group compared with the placebo group. Moreover, recall of object locations was significantly better after LC-n3-FA supplementation compared with placebo. Performance in the AVLT was not significantly affected by LC-n3-FA. This double-blind placebo-controlled proof-of-concept study provides further experimental evidence that LC-n3-FA exert positive effects on memory functions in healthy older adults. Our findings suggest novel strategies to maintain cognitive functions into old age.
Keywords: Aged; Apolipoproteins E; Auditory Perception; Blood Chemical Analysis; Cognitive Aging; Dietary Supplements; Double-Blind Method; Fatty Acids, Omega-3; Feeding Behavior; Female; Humans; Learning; Male; Memory; Middle Aged; Neuropsychological Tests; Nootropic Agents; Treatment Outcome

Impaired Autophagy in APOE4 Astrocytes. - Simonovitch, Shira; Schmukler, Eran; Bespalko, Alina; Iram, Tal; Frenkel, Dan; Holtzman, David M; Masliah, Eliezer; Michaelson, Danny M; Pinkas-Kramarski, Ronit (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most prevalent form of dementia in elderly. Genetic studies revealed allelic segregation of the apolipoprotein E (ApoE) gene in sporadic AD and in families with higher risk of AD. The mechanisms underlying the pathological effects of ApoE4 are not yet entirely clear. Several studies indicate that autophagy, which plays an important role in degradation pathways of proteins, organelles and protein aggregates, may be impaired in AD. In the present study, we investigated the effects of ApoE4 versus the ApoE3 isoform on the process of autophagy in mouse-derived astrocytes. The results obtained reveal that under several autophagy-inducing conditions, astrocytes expressing ApoE4 exhibit lower autophagic flux compared to astrocytes expressing ApoE3. Using an in situ model, we examined the role of autophagy and the effects thereon of ApoE4 in the elimination of Aβ plaques from isolated brain sections of transgenic 5xFAD mice. This revealed that ApoE4 astrocytes eliminate Aβ plaques less effectively than the corresponding ApoE3 astrocytes. Additional experiments showed that the autophagy inducer, rapamycin, enhances Aβ plaque degradation by ApoE4 astrocytes whereas the autophagy inhibitor, chloroquine, blocks Aβ plaque degradation by ApoE3 astrocytes. Taken together, these findings show that ApoE4 impairs autophagy in astrocyte cultures and that this effect is associated with reduced capacity to clear Aβ plaques. This suggests that impaired autophagy may play a role in mediating the pathological effects of ApoE4 in AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoprotein E3; Apolipoprotein E4; Astrocytes; Autophagy; Brain; Cells, Cultured; Central Nervous System Agents; Chloroquine; Disease Models, Animal; Humans; Mice, Transgenic; Plaque, Amyloid; Sirolimus; Time Factors

Increase of α-Secretase ADAM10 in Platelets Along Cognitively Healthy Aging. - Schuck, Florian; Wolf, Dominik; Fellgiebel, Andreas; Endres, Kristina (J Alzheimers Dis, 2016)
ADAM10 is one of the key players in ectodomain-shedding of the amyloid-β protein precursor (AβPP). Previous research with postmortem tissue has shown reduced expression and activity of ADAM10 within the central nervous system (CNS) of Alzheimer's disease (AD) patients. Determination of cerebral ADAM10 in living humans is hampered by its transmembrane property; only the physiological AβPP cleavage product generated by ADAM10, sAβPPα, can be assessed in cerebrospinal fluid. Establishment of surrogate markers in easily accessible material therefore is crucial. It has been demonstrated that ADAM10 is expressed in platelets and that platelet amount is decreased in AD patients. Just recently it has been shown that platelet ADAM10 and cognitive performance of AD patients positively correlate. In contrast to AD patients, to our knowledge almost no information has been published regarding ADAM10 expression during normal aging. We investigated ADAM10 amount and activity in platelets of cognitively healthy individuals from three different age groups ranging from 22-85 years. Interestingly, we observed an age-dependent increase in ADAM10 levels and activity in platelets.
Keywords: ADAM Proteins; ADAM10 Protein; Adult; Age Factors; Aged; Aged, 80 and over; Aging; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Apolipoprotein E4; Cognition; Female; Healthy Volunteers; Humans; Integrin beta3; Male; Membrane Proteins; Middle Aged; Neuropsychological Tests; Young Adult

Increased Electron Paramagnetic Resonance Signal Correlates with Mitochondrial Dysfunction and Oxidative Stress in an Alzheimer's disease Mouse Brain. - Fang, Du; Zhang, Zhihua; Li, Hang; Yu, Qing; Douglas, Justin T; Bratasz, Anna; Kuppusamy, Periannan; Yan, Shirley ShiDu (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized clinically by cognitive decline and memory loss. The pathological features are amyloid-β peptide (Aβ) plaques and intracellular neurofibrillary tangles. Many studies have suggested that oxidative damage induced by reactive oxygen species (ROS) is an important mechanism for AD progression. Our recent study demonstrated that oxidative stress could further impair mitochondrial function. In the present study, we adopted a transgenic mouse model of AD (mAPP, overexpressing AβPP/Aβ in neurons) and performed redox measurements using in vivo electron paramagnetic resonance (EPR) imaging with methoxycarbamyl-proxyl (MCP) as a redox-sensitive probe for studying oxidative stress in an early stage of pathology in a transgenic AD mouse model. Through assessing oxidative stress, mitochondrial function and cognitive behaviors of mAPP mice at the age of 8-9 months, we found that oxidative stress and mitochondrial dysfunction appeared in the early onset of AD. Increased ROS levels were associated with defects of mitochondrial and cognitive dysfunction. Notably, the in vivo EPR method offers a unique way of assessing tissue oxidative stress in living animals under noninvasive conditions, and thus holds a potential for early diagnosis and monitoring the progression of AD.
Keywords: Adenosine Triphosphate; Age of Onset; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition; Disease Models, Animal; Electron Spin Resonance Spectroscopy; Electron Transport Complex IV; Female; Humans; Male; Maze Learning; Mice, Transgenic; Mitochondria; Oxidative Stress; Reactive Oxygen Species; Spatial Memory

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Influence of Incipient Dementia on Hospitalization for Primary Care Sensitive Conditions: A Population-Based Cohort Study. - Pimouguet, Clément; Rizzuto, Debora; Fastbom, Johan; Lagergren, Mårten; Fratiglioni, Laura; Xu, Weili (J Alzheimers Dis, 2016)
BACKGROUND: Studies have reported that moderate/severe stages of dementia are linked to increased hospitalization rates, but little is known about the influence of incipient dementia on hospitalizations for primary care sensitive conditions (PCSCs). OBJECTIVE: To examine the associations between incipient dementia and hospitalization outcomes, including all-cause and PCSC hospitalization. METHODS: A total of 2,268 dementia-free participants in the Swedish National study on Aging and Care-Kungsholmen were interviewed and clinically examined at baseline. Participants aged ≥78 years were followed for 3 years, and those aged 60-72 years, for 6 years. Number of hospitalizations was retrieved from the National Patient Register. Dementia was diagnosed in accordance with Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Hospitalization outcomes were compared in participants who did and did not develop dementia. Zero-inflated Poisson regressions and logistic regressions were used in data analysis. RESULTS: During the follow-up, 175 participants developed dementia. The unadjusted PCSC admission rate was 88.2 per 1000 person-years in those who developed dementia and 25.6 per 1000 person-years in those who did not. In the fully adjusted logistic regression model, incipient dementia was associated with an increased risk of hospitalization for PCSCs (OR = 2.3, 95% CI 1.3-3.9) but not with the number of hospitalizations or with all-cause hospitalization. Risks for hospitalization for diabetes, congestive heart failure, and pyelonephritis were higher in those who developed dementia than in those who did not. About 10% participants had a PCSC hospitalization attributable to incipient dementia. CONCLUSION: People with incipient dementia are more prone to hospitalization for PCSCs but not to all-cause hospitalization.
Keywords: Acute Disease; Age Factors; Aged; Aged, 80 and over; Chronic Disease; Dementia; Female; Follow-Up Studies; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Primary Health Care; Registries; Risk; Sensitivity and Specificity; Socioeconomic Factors; Sweden

Interaction Between Midlife Blood Glucose and APOE Genotype Predicts Later Alzheimer's Disease Pathology. - Bangen, Katherine J; Himali, Jayandra J; Beiser, Alexa S; Nation, Daniel A; Libon, David J; Fox, Caroline S; Seshadri, Sudha; Wolf, Philip A; McKee, Ann C; Au, Rhoda; Delano-Wood, Lisa (J Alzheimers Dis, 2016)
Elevated blood glucose and the apolipoprotein (APOE) ɛ4 allele have both been associated with increased dementia risk; however, the neuropathological mechanisms underlying these associations remain unclear. We examined the impact of APOE genotype and midlife blood glucose on post-mortem vascular and Alzheimer's disease (AD) neuropathology. Ninety-four participants from the Framingham Heart Study without diagnosed diabetes underwent health examination at midlife and brain autopsy at death. Histopathological measures of vascular and AD neuropathology were obtained and analyzed. Results demonstrated that, among APOE ɛ4 carriers, elevated blood glucose was associated with more severe AD pathology. There was no such relationship with vascular pathology. In a relatively healthy sample with low vascular risk burden, midlife elevated blood glucose was associated with greater AD pathology among APOE ɛ4 carriers. A better understanding of interactive effects of APOE genotype and vascular risk on neuropathology has implications for identification of individuals at risk for decline and long-term preventive treatment.

Iron Regulates Apolipoprotein E Expression and Secretion in Neurons and Astrocytes. - Xu, He; Perreau, Victoria M; Dent, Krista A; Bush, Ashley I; Finkelstein, David I; Adlard, Paul A (J Alzheimers Dis, 2016)
BACKGROUND: There is strong evidence that iron homeostasis is impaired in the aging and Alzheimer's disease (AD) brain and that this contributes to neurodegeneration. Apolipoprotein E (APOE) has been identified as the strongest genetic risk factor for AD. However, the interaction between the two has yet to be fully explored. OBJECTIVE: This study aimed to investigate the relationship between exogenous iron levels and ApoE in neurons and astrocytes. METHODS: Our study used primary cultured cortical neurons and astrocytes to investigate the changes in ApoE caused by iron. Western blot and RT-PCR were used to measure ApoE. RESULTS: We observed that iron upregulated intracellular ApoE levels in both neurons and astrocytes at the post-transcriptional and transcriptional level, respectively. However, there was less full-length ApoE secreted by neurons and astrocytes after iron treatment. We speculate that this might impair brain lipid metabolism and amyloid-β clearance. In terms of ApoE receptors, we observed that neuronal LRP-1 levels were increased by the addition of exogenous iron, which could contribute to AβPP endocytosis in neurons. However, there were no significant changes in neuronal LDLR, astrocyte LDLR, or astrocyte LRP-1. CONCLUSION: Our study reveals that iron may contribute to the pathogenesis of AD by affecting ApoE and its receptors and supports the notion that iron chelation should be investigated as a therapeutic strategy for AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Blotting, Western; Cell Survival; Cells, Cultured; Cerebral Cortex; Copper; Ferritins; Immunohistochemistry; Iron; Mice, Inbred C57BL; Neurons; Polymerase Chain Reaction; Reactive Oxygen Species; Receptors, LDL; RNA, Messenger; Tumor Suppressor Proteins; Zinc

Late-Life Depressive Symptoms and Lifetime History of Major Depression: Cognitive Deficits are Largely Due to Incipient Dementia rather than Depression. - Heser, Kathrin; Bleckwenn, Markus; Wiese, Birgitt; Mamone, Silke; Riedel-Heller, Steffi G; Stein, Janine; Lühmann, Dagmar; Posselt, Tina; Fuchs, Angela; Pentzek, Michael; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Late-life depression is frequently accompanied by cognitive impairments. OBJECTIVE: Whether these impairments indicate a prodromal state of dementia, or are a symptomatic expression of depression per se is not well-studied. METHODS: In a cohort of very old initially non-demented primary care patients (n = 2,709, mean age = 81.1 y), cognitive performance was compared between groups of participants with or without elevated depressive symptoms and with or without subsequent dementia using ANCOVA (adjusted for age, sex, and education). Logistic regression analyses were computed to predict subsequent dementia over up to six years of follow-up. The same analytical approach was performed for lifetime major depression. RESULTS: Participants with elevated depressive symptoms without subsequent dementia showed only small to medium cognitive deficits. In contrast, participants with depressive symptoms with subsequent dementia showed medium to very large cognitive deficits. In adjusted logistic regression models, learning and memory deficits predicted the risk for subsequent dementia in participants with depressive symptoms. Participants with a lifetime history of major depression without subsequent dementia showed no cognitive deficits. However, in adjusted logistic regression models, learning and orientation deficits predicted the risk for subsequent dementia also in participants with lifetime major depression. CONCLUSION: Marked cognitive impairments in old age depression should not be dismissed as "depressive pseudodementia", but require clinical attention as a possible sign of incipient dementia. Non-depressed elderly with a lifetime history of major depression, who remained free of dementia during follow-up, had largely normal cognitive performance.

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

The Level of NMDA Receptor in the Membrane Modulates Amyloid-β Association and Perforation. - Peters, Christian; Sepúlveda, Fernando J; Fernández-Pérez, Eduardo J; Peoples, Robert W; Aguayo, Luis G (J Alzheimers Dis, 2016)
Alzheimer's disease is a neurodegenerative disorder that affects mostly the elderly. The main histopathological markers are the senile plaques formed by amyloid-β peptide (Aβ) aggregates that can perforate the plasma membrane of cells, increasing the intracellular calcium levels and releasing synaptic vesicles that finally lead to a delayed synaptic failure. Several membrane proteins and lipids interact with Aβ affecting its toxicity in neurons. Here, we focus on NMDA receptors (NMDARs) as proteins that could be modulating the association and neurotoxic perforation induced by Aβ on the plasma membrane. In fact, our results showed that decreasing NMDARs, using enzymatic or siRNA approaches, increased the association of Aβ to the neurons. Furthermore, overexpression of NMDARs also resulted in an enhanced association between NMDA and Aβ. Functionally, the reduction in membrane NMDARs augmented the process of membrane perforation. On the other hand, overexpressing NMDARs had a protective effect because Aβ was now unable to cause membrane perforation, suggesting a complex relationship between Aβ and NMDARs. Because previous studies have recognized that Aβ oligomers are able to increase membrane permeability and produce amyloid pores, the present study supports the conclusion that NMDARs play a critical protective role on Aβ actions in hippocampal neurons. These results could explain the lack of correlation between brain Aβ burden and clinically observed dementia.

Lewy Bodies, Vascular Risk Factors, and Subcortical Arteriosclerotic Leukoencephalopathy, but not Alzheimer Pathology, are Associated with Development of Psychosis in Alzheimer's Disease. - Fischer, Corinne E; Qian, Winnie; Schweizer, Tom A; Millikin, Colleen P; Ismail, Zahinoor; Smith, Eric E; Lix, Lisa M; Shelton, Paul; Munoz, David G (J Alzheimers Dis, 2016)
BACKGROUND: The neuropathological correlates of psychosis in Alzheimer's disease (AD) is unclear, with some studies reporting a correlation between psychosis and increased AD pathology while others have found no association. OBJECTIVE: To determine the demographic, clinical, and neuropathological features associated with psychotic symptoms in clinically attributed and neuropathologically proven AD. METHOD: We separately reviewed two overlapping groups of clinically diagnosed (cAD) AD patients with neuropathology data and neuropathologically definite (npAD) cases (regardless of clinical diagnosis) from the NACC database, and explored the relationships between psychosis and clinical variables, neuropathologic correlates, and vascular risk factors. Delusions and hallucinations, defined according to the NPI-Q, were analyzed separately. RESULTS: 1,073 subjects in the database fulfilled our criteria (890 cAD and 728 npAD patients). 34% of cAD and 37% of npAD had psychotic symptoms during their illness. Hallucinations were associated with greater cognitive and functional impairments on the MMSE and CDR, while delusional patients showed less impairment on CDR, consistent across cAD and npAD groups. Burden of AD pathology appears to relate to presence of psychotic symptoms in the clinical AD group, but this result is not confirmed in the neuropathologically confirmed group suggesting the findings in the clinical group were due to misdiagnosis of AD. Lewy body pathology, subcortical arteriosclerotic leukoencephalopathy, and vascular risk factors, including a history of hypertension and diabetes, were associated with the development of psychosis. METHOD: Vascular and Lewy body pathologies and vascular risk factors are important modifiers of the risk of psychosis in AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Databases, Factual; Dementia, Vascular; Female; Hemorrhage; Humans; Lewy Bodies; Male; Middle Aged; Psychiatric Status Rating Scales; Psychotic Disorders; Retrospective Studies; Risk Factors; Severity of Illness Index; Surveys and Questionnaires

Linguistic Features Identify Alzheimer's Disease in Narrative Speech. - Fraser, Kathleen C; Meltzer, Jed A; Rudzicz, Frank (J Alzheimers Dis, 2016)
BACKGROUND: Although memory impairment is the main symptom of Alzheimer's disease (AD), language impairment can be an important marker. Relatively few studies of language in AD quantify the impairments in connected speech using computational techniques. OBJECTIVE: We aim to demonstrate state-of-the-art accuracy in automatically identifying Alzheimer's disease from short narrative samples elicited with a picture description task, and to uncover the salient linguistic factors with a statistical factor analysis. METHODS: Data are derived from the DementiaBank corpus, from which 167 patients diagnosed with "possible" or "probable" AD provide 240 narrative samples, and 97 controls provide an additional 233. We compute a number of linguistic variables from the transcripts, and acoustic variables from the associated audio files, and use these variables to train a machine learning classifier to distinguish between participants with AD and healthy controls. To examine the degree of heterogeneity of linguistic impairments in AD, we follow an exploratory factor analysis on these measures of speech and language with an oblique promax rotation, and provide interpretation for the resulting factors. RESULTS: We obtain state-of-the-art classification accuracies of over 81% in distinguishing individuals with AD from those without based on short samples of their language on a picture description task. Four clear factors emerge: semantic impairment, acoustic abnormality, syntactic impairment, and information impairment. CONCLUSION: Modern machine learning and linguistic analysis will be increasingly useful in assessment and clustering of suspected AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Diagnosis, Computer-Assisted; Factor Analysis, Statistical; Female; Humans; Language Disorders; Linguistics; Logistic Models; Machine Learning; Male; Mental Status Schedule; Middle Aged; Narration; Photic Stimulation; Speech; Verbal Behavior

Longitudinal Study of Impaired Intra- and Inter-Network Brain Connectivity in Subjects at High Risk for Alzheimer's Disease. - Zhan, Yafeng; Ma, Jianhua; Alexander-Bloch, Aaron F; Xu, Kaibin; Cui, Yue; Feng, Qianjin; Jiang, Tianzi; Liu, Yong (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is associated with abnormal resting-state network (RSN) architecture of the default mode network (DMN), the dorsal attention network (DAN), the executive control network (CON), the salience network (SAL), and the sensory-motor network (SMN). However, little is known about the disrupted intra- and inter-network architecture in mild cognitive impairment (MCI). Here, we employed a priori defined regions of interest to investigate the intra- and inter-network functional connectivity profiles of these RSNs in longitudinal participants, including normal controls (n = 23), participants with early MCI (n = 26), and participants with late MCI (n = 19). We found longitudinal alterations of functional connectivity within the DMN, where they were correlated with variation in cognitive ability. The SAL as well as the interaction between the DMN and the SAL were disrupted in MCI. Furthermore, our results demonstrate that longitudinal alterations of functional connectivity are more profound in earlier stages as opposed to later stages of the disease. The increased severity of cognitive impairment is associated with increasingly altered RSN connectivity patterns, suggesting that disruptions in functional connectivity may contribute to cognitive dysfunction and may represent a potential biomarker of impaired cognitive ability in MCI. Earlier prevention and treatment may help to delay disease progression to AD.

Low Plasma Cholinesterase Activities are Associated with Deficits in Spatial Orientation, Reduced Ability to Perform Basic Activities of Daily Living, and Low Body Mass Index in Patients with Progressed Alzheimer's Disease. - Dingova, Dominika; Fazekas, Tomas; Okuliarova, Petra; Strbova, Jaroslava; Kucera, Matej; Hrabovska, Anna (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a progressive and irreversible neurodegenerative disorder characterized by a central cholinergic deficit. Non-neuronal cholinergic changes are, however, described as well. Here we focused on possible changes in the activity of the plasma cholinesterases, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), in hospitalized AD patients. We analyzed plasma AChE and BChE activities with regards to age, gender, body mass index (BMI), cognitive functions, and ability to perform activities of daily living in AD patients in comparison to healthy subjects. We observed lower AChE activity and trend toward lower BChE activity in AD patients, which both correlated with low BMI. AD patients unable to perform basic activities of daily living (feeding, bathing, dressing, and grooming) showed reduced plasma AChE activities, while worse spatial orientation was linked to lower BChE activities. Three out of four AD patients with the lowest BChE activities died within one year. In conclusion, progressed AD was accompanied by lower plasma AChE activity and trend toward lower BChE activity, which correlated with BMI and deficits in different components of the AD.
Keywords: Acetylcholinesterase; Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Blood Chemical Analysis; Body Mass Index; Butyrylcholinesterase; Female; Hospitalization; Humans; Male; Middle Aged; Orientation, Spatial

Low Serum Insulin-Like Growth Factor-I Predicts Cognitive Decline in Alzheimer's Disease. - Vidal, Jean-Sébastien; Hanon, Olivier; Funalot, Benoît; Brunel, Nadège; Viollet, Cécile; Rigaud, Anne-Sophie; Seux, Marie-Laure; le-Bouc, Yves; Epelbaum, Jacques; Duron, Emmanuelle (J Alzheimers Dis, 2016)
BACKGROUND: The relationship between the insulin-like growth factor-I (IGF-I) system and Alzheimer's disease (AD) is mostly based on transversal studies. It remains, however, to demonstrate whether IGF-I is associated with cognitive decline over time in AD. OBJECTIVE: The objective of the study was to analyze the course of cognitive decline of AD subjects over a 24-month period in relation to serum IGF-I and insulin-like growth factor binding protein-3 (IGFBP-3) measured at baseline. METHODS: Data are from the SIGAL follow-up study. IGF-I and IGFBP-3 were measured in AD subjects who performed a Mini-Mental State Examination (MMSE) every 6 months for 2 years. MMSE course was analyzed using a mixed model with random intercept and slope function. RESULTS: Among the 200 AD participants, 146 (mean age = 81.1 (standard deviation (SD) = 5.9) years, 62.6% of women) had at least one follow-up visit. Mean IGF-I at baseline was 147.8 (74.2) ng/mL. Hundred forty-six participants (62.6%) had at least one follow-up visit. Mean MMSE was 21.7 (4.7)/30 and dropped on average by 2.28 points per year. MMSE decline was steeper among participants with lower IGF-I. For each decrease of 1 SD of IGF-I, subjects lost an additional 0.63 points per year in MMSE, e.g., participants with IGF-I level of 74 ng/mL lost 2.91 MMSE points per year whereas participants with IGF-I of 222 ng/mL lost 1.65 MMSE points per year. There was no association between IGFBP-3 and cognitive decline. CONCLUSION: Lower baseline serum IGF-I was associated with faster cognitive decline in AD over a 2-year period.

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Measurement Error, Reliability, and Minimum Detectable Change in the Mini-Mental State Examination, Montreal Cognitive Assessment, and Color Trails Test among Community Living Middle-Aged and Older Adults. - Feeney, Joanne; Savva, George M; O'Regan, Claire; King-Kallimanis, Bellinda; Cronin, Hilary; Kenny, Rose Anne (J Alzheimers Dis, 2016)
BACKGROUND: Knowing the reliability of cognitive tests, particularly those commonly used in clinical practice, is important in order to interpret the clinical significance of a change in performance or a low score on a single test. OBJECTIVE: To report the intra-class correlation (ICC), standard error of measurement (SEM) and minimum detectable change (MDC) for the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Color Trails Test (CTT) among community dwelling older adults. METHODS: 130 participants aged 55 and older without severe cognitive impairment underwent two cognitive assessments between two and four months apart. Half the group changed rater between assessments and half changed time of day. RESULTS: Mean (standard deviation) MMSE was 28.1 (2.1) at baseline and 28.4 (2.1) at repeat. Mean (SD) MoCA increased from 24.8 (3.6) to 25.2 (3.6). There was a rater effect on CTT, but not on the MMSE or MoCA. The SEM of the MMSE was 1.0, leading to an MDC (based on a 95% confidence interval) of 3 points. The SEM of the MoCA was 1.5, implying an MDC95 of 4 points. MoCA (ICC = 0.81) was more reliable than MMSE (ICC = 0.75), but all tests examined showed substantial within-patient variation. CONCLUSION: An individual's score would have to change by greater than or equal to 3 points on the MMSE and 4 points on the MoCA for the rater to be confident that the change was not due to measurement error. This has important implications for epidemiologists and clinicians in dementia screening and diagnosis.

The Memory Binding Test: Development of Two Alternate Forms into Spanish and Catalan. - Gramunt, Nina; Sánchez-Benavides, Gonzalo; Buschke, Herman; Diéguez-Vide, Faustino; Peña-Casanova, Jordi; Masramon, Xavier; Fauria, Karine; Gispert, Juan D; Molinuevo, José L (J Alzheimers Dis, 2016)
BACKGROUND: The Memory Binding Test (MBT) is emerging as a promising tool for the detection of subtle memory impairment suggestive of Alzheimer's disease (AD). For such a test to be widely accessed and used, the availability of both alternate forms and language adaptations is required. OBJECTIVES: To develop a thorough methodology for obtaining alternate forms (A and B) of the MBT in Spanish and Catalan and to assess their equivalence. METHOD: According to the original development of the test, frequency was taken as the lexical variable of reference for the Spanish and Catalan adaptations. A crossed design protocol by form and language was used to compare the MBT results in a sample of 290 cognitively normal middle-aged participants. Pairwise Intraclass Correlation Coefficients (ICCs) were calculated among the six possible combinations. RESULTS: The Spanish and Catalan lists of words for the MBT A and B resulting from the adaptation process as well as the original lists in English are presented. ICC indices for the comparisons between forms and languages ranged from 0.56 to 0.82. CONCLUSION: The MBT A and B in Spanish and Catalan showed similar outcomes and can be considered equivalent. Moreover, the thorough methodology presented here for the transcultural adaptation and equivalence study, could serve as a model for future adaptations of the MBT and other verbal tests.

Methods for the Specific Detection and Quantitation of Amyloid-β Oligomers in Cerebrospinal Fluid. - Schuster, Judith; Funke, Susanne Aileen (J Alzheimers Dis, 2016)
Protein misfolding and aggregation are fundamental features of the majority of neurodegenerative diseases, like Alzheimer's disease (AD), Parkinson's disease, frontotemporal dementia, and prion diseases. Proteinaceous deposits in the brain of the patient, e.g., amyloid plaques consisting of the amyloid-β (Aβ) peptide and tangles composed of tau protein, are the hallmarks of AD. Soluble oligomers of Aβ and tau play a fundamental role in disease progression, and specific detection and quantification of the respective oligomeric proteins in cerebrospinal fluid may provide presymptomatically detectable biomarkers, paving the way for early diagnosis or even prognosis. Several studies on the development of techniques for the specific detection of Aβ oligomers were published, but some of the existing tools do not yet seem to be satisfactory, and the study results are contradicting. The detection of oligomers is challenging due to their polymorphous and unstable nature, their low concentration, and the presence of competing proteins and Aβ monomers in body fluids. Here, we present an overview of the current state of the development of methods for Aβ oligomer specific detection and quantitation. The methods are divided in the three subgroups: (i) enzyme linked immunosorbent assays (ELISA), (ii) methods for single oligomer detection, and (iii) others, which are mainly biosensor based methods.

A Mitochondrial Role of SV2a Protein in Aging and Alzheimer's Disease: Studies with Levetiracetam. - Stockburger, Carola; Miano, Davide; Baeumlisberger, Marion; Pallas, Thea; Arrey, Tabiwang N; Karas, Michael; Friedland, Kristina; Müller, Walter E (J Alzheimers Dis, 2016)
Aberrant neuronal network activity associated with neuronal hyperexcitability seems to be an important cause of cognitive decline in aging and Alzheimer's disease (AD). Out of many antiepileptics, only levetiracetam improved cognitive dysfunction in AD patients and AD animal models by reducing hyperexcitability. As impaired inhibitory interneuronal function, rather than overactive neurons, seems to be the underlying cause, improving impaired neuronal function rather than quieting overactive neurons might be relevant in explaining the lack of activity of the other antiepileptics. Interestingly, improvement of cognitive deficits by levetiracetam caused by small levels of soluble Aβ was accompanied by improvement of synaptic function and plasticity. As the negative effects of Aβ on synaptic plasticity strongly correlate with mitochondrial dysfunction, wehypothesized that the effect of levetiracetam on synaptic activity might be raised by an improved mitochondrial function. Accordingly, we investigated possible effects of levetiracetam on neuronal deficits associated with mitochondrial dysfunction linked to aging and AD. Levetiracetam improved several aspects of mitochondrial dysfunction including alterations of fission and fusion balance in a cell model for aging and early late-onset AD. We demonstrate for the first time, using immunohistochemistry and proteomics, that the synaptic vesicle protein 2A (SV2a), the molecular target of levetiracetam, is expressed in mitochondria. In addition, levetiracetam shows significant effect on the opening of the mitochondrial permeability transition pore. Importantly, the effects of levetiracetam were significantly abolished when SV2a was knockdown using siRNA. In conclusion, interfering with the SV2a protein at the mitochondrial level and thereby improving mitochondrial function might represent an additional therapeutic effect of levetiracetam to improve symptoms of late-onset AD.
Keywords: Adenosine Triphosphate; Aging; Alzheimer Disease; Animals; Brain; Cell Line; Cognition Disorders; Female; GAP-43 Protein; Gene Expression Regulation; Humans; Male; Membrane Glycoproteins; Mitochondria; Mitochondrial Membrane Transport Proteins; Nerve Tissue Proteins; Nitroprusside; Nootropic Agents; Piracetam; Proteomics; Rats; RNA, Small Interfering

Moderate-to-High Intensity Physical Exercise in Patients with Alzheimer's Disease: A Randomized Controlled Trial. - Hoffmann, Kristine; Sobol, Nanna A; Frederiksen, Kristian S; Beyer, Nina; Vogel, Asmus; Vestergaard, Karsten; Brændgaard, Hans; Gottrup, Hanne; Lolk, Annette; Wermuth, Lene; Jacobsen, Søren; Laugesen, Lars P; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Studies of physical exercise in patients with Alzheimer's disease (AD) are few and results have been inconsistent. OBJECTIVE: To assess the effects of a moderate-to-high intensity aerobic exercise program in patients with mild AD. METHODS: In a randomized controlled trial, we recruited 200 patients with mild AD to a supervised exercise group (60-min sessions three times a week for 16 weeks) or to a control group. Primary outcome was changed from baseline in cognitive performance estimated by Symbol Digit Modalities Test (SDMT) in the intention-to-treat (ITT) group. Secondary outcomes included changes in quality of life, ability to perform activities of daily living, and in neuropsychiatric and depressive symptoms. RESULTS: The ITT analysis showed no significant differences between intervention and control groups in change from baseline of SDMT, other cognitive tests, quality of life, or activities of daily living. The change from baseline in Neuropsychiatric Inventory differed significantly in favor of the intervention group (mean: -3.5, 95% confidence interval (CI) -5.8 to -1.3, p = 0.002). In subjects who adhered to the protocol, we found a significant effect on change from baseline in SDMT as compared with the control group (mean: 4.2, 95% CI 0.5 to 7.9, p = 0.028), suggesting a dose-response relationship between exercise and cognition. CONCLUSIONS: This is the first randomized controlled trial with supervised moderate-to-high intensity exercise in patients with mild AD. Exercise reduced neuropsychiatric symptoms in patients with mild AD, with possible additional benefits of preserved cognition in a subgroup of patients exercising with high attendance and intensity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Depression; Exercise; Exercise Therapy; Female; Humans; Male; Middle Aged; Quality of Life; Treatment Outcome

Motoric Cognitive Risk Syndrome and Falls Risk: A Multi-Center Study. - Callisaya, Michele L; Ayers, Emmeline; Barzilai, Nir; Ferrucci, Luigi; Guralnik, Jack M; Lipton, Richard B; Otahal, Petr; Srikanth, Velandai K; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The Motoric Cognitive Risk Syndrome (MCR) is characterized by slow gait speed and cognitive complaints. OBJECTIVES: The objective of this study was to determine if the presence of MCR increases the risk of falls in older people. METHODS: Individual participant data (n = 6,204) from five longitudinal studies from three countries were used for this analysis. MCR diagnosis was defined as both the presence of objectively measured slow gait speed and subjective cognitive complaints in those without dementia or mobility disability. Falls were prospectively ascertained using phone calls or questionnaires. Log binomial regression was performed to determine if MCR increased the risk of falls separately in each cohort. Random effects meta-analysis was used to pool results from all cohorts. RESULTS: The mean age of participants was 74.9 (SD 6.8) years and 44% (n = 2728) were male. Overall 33.9% (n = 2104) reported a fall over follow-up. Pooled relative risk of MCR with any falls was RR 1.44 95% CI 1.16, 1.79. The components of MCR, slow gait (RR 1.30 95% CI 1.14, 1.47) and cognitive complaint (RR 1.25, 95% CI 1.07, 1.46) were also associated with an increased risk of any falls. In sub-analyses MCR was associated with any fall independent of previous falls (RR 1.29 95% CI 1.09, 1.53) and with multiple falls (RR 1.77, 95% CI 1.25, 2.51). CONCLUSION: MCR is associated with an increased risk of falls. The increase in risk was higher than for its individual components. The simplicity of the MCR makes it an attractive falls risk screening tool for the clinic.

Music and Memory in Alzheimer's Disease and The Potential Underlying Mechanisms. - Peck, Katlyn J; Girard, Todd A; Russo, Frank A; Fiocco, Alexandra J (J Alzheimers Dis, 2016)
With population aging and a projected exponential expansion of persons diagnosed with Alzheimer's disease (AD), the development of treatment and prevention programs has become a fervent area of research and discovery. A growing body of evidence suggests that music exposure can enhance memory and emotional function in persons with AD. However, there is a paucity of research that aims to identify specific underlying neural mechanisms associated with music's beneficial effects in this particular population. As such, this paper reviews existing anecdotal and empirical evidence related to the enhancing effects of music exposure on cognitive function and further provides a discussion on the potential underlying mechanisms that may explain music's beneficial effect. Specifically, this paper will outline the potential role of the dopaminergic system, the autonomic nervous system, and the default network in explaining how music may enhance memory function in persons with AD.
Keywords: Alzheimer Disease; Auditory Perception; Autonomic Nervous System; Dopamine; Humans; Memory Disorders; Music Therapy

Naphthoquinone-Tryptophan Hybrid Inhibits Aggregation of the Tau-Derived Peptide PHF6 and Reduces Neurotoxicity. - Frenkel-Pinter, Moran; Tal, Sharon; Scherzer-Attali, Roni; Abu-Hussien, Malak; Alyagor, Idan; Eisenbaum, Tal; Gazit, Ehud; Segal, Daniel (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD), are a group of disorders characterized neuropathologically by intracellular toxic accumulations of abnormal protein aggregates formed by misfolding of the microtubule-associated protein tau. Since protein self-assembly appears to be an initial key step in the pathology of this group of diseases, intervening in this process can be both a prophylactic measure and a means for modifying the course of the disease for therapeutic purposes. We and others have shown that aromatic small molecules can be effective inhibitors of aggregation of various protein assemblies, by binding to the aromatic core in aggregation-prone motifs and preventing their self-assembly. Specifically, we have designed a series of small aromatic naphthoquinone-tryptophan hybrid molecules as candidate aggregation inhibitors of β -sheet based assembly and demonstrated their efficacy toward inhibiting aggregation of the amyloid-β peptide, another culprit of AD, as well as of various other aggregative proteins involved in other protein misfolding diseases. Here we tested whether a leading naphthoquinone-tryptophan hybrid molecule, namely NQTrp, can be repurposed as an inhibitor of the aggregation of the tau protein in vitro and in vivo. We show that the molecule inhibits the in vitro assembly of PHF6, the aggregation-prone fragment of tau protein, reduces hyperphosphorylated tau deposits and ameliorates tauopathy-related behavioral defect in an established transgenic Drosophila model expressing human tau. We suggest that NQTrp, or optimized versions of it, could act as novel disease modifying drugs for AD and other tauopathies.
Keywords: Animals; Carrier Proteins; Disease Models, Animal; Drosophila; Drosophila Proteins; Eye; Female; Humans; Immunoprecipitation; In Vitro Techniques; Larva; Locomotion; Mice, Transgenic; Microscopy, Electron, Scanning; Naphthoquinones; Neurotoxicity Syndromes; Protein Aggregates; Retinal Pigments; tau Proteins; Tryptophan

Neurophysiological assessment of Alzheimer's disease individuals by a single electroencephalographic marker. - Lizio, Roberta; Del Percio, Claudio; Marzano, Nicola; Soricelli, Andrea; Yener, Görsev G; Başar, Erol; Mundi, Ciro; De Rosa, Salvatore; Triggiani, Antonio Ivano; Ferri, Raffaele; Arnaldi, Dario; Nobili, Flavio Mariano; et al. (J Alzheimers Dis, 2016)
Here we presented a single electroencephalographic (EEG) marker for a neurophysiological assessment of Alzheimer's disease (AD) patients already diagnosed by current guidelines. The ability of the EEG marker to classify 127 AD individuals and 121 matched cognitively intact normal elderly (Nold) individuals was tested. Furthermore, its relationship to AD patients' cognitive status and structural brain integrity was examined. Low-resolution brain electromagnetic tomography (LORETA) freeware estimated cortical sources of resting state eyes-closed EEG rhythms. The EEG marker was defined as the ratio between the activity of parieto-occipital cortical sources of delta (2-4 Hz) and low-frequency alpha (8-10.5 Hz) rhythms. Results showed 77.2% of sensitivity in the recognition of the AD individuals; 65% of specificity in the recognition of the Nold individuals; and 0.75 of area under the receiver-operating characteristic curve. Compared to the AD subgroup with the EEG maker within one standard deviation of the Nold mean (EEG-), the AD subgroup with EEG+ showed lower global cognitive status, as revealed by Mini-Mental State Evaluation score, and more abnormal values of white-matter and cerebrospinal fluid normalized volumes, as revealed by structural magnetic resonance imaging. We posit that cognitive and functional status being equal, AD patients with EEG+ should receive special clinical attention due to a neurophysiological "frailty". EEG+ label can be also used in clinical trials (i) to form homogeneous groups of AD patients diagnosed by current guidelines and (ii) as end-point to evaluate intervention effects.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain Mapping; Case-Control Studies; Cognition Disorders; Electroencephalography; Female; Humans; Italy; Magnetic Resonance Imaging; Male; Middle Aged; Occipital Lobe; Rest; ROC Curve; Turkey

Non Fluent Variant of Primary Progressive Aphasia Due to the Novel GRN g.9543delA(IVS3-2delA) Mutation. - Cioffi, Sara M G; Galimberti, Daniela; Barocco, Federica; Spallazzi, Marco; Fenoglio, Chiara; Serpente, Maria; Arcaro, Marina; Gardini, Simona; Scarpini, Elio; Caffarra, Paolo (J Alzheimers Dis, 2016)
Mutations in progranulin gene (GRN) are a common cause of autosomal dominant frontotemporal lobar degeneration syndromes and are associated with a wide phenotypic heterogeneity. The majority of genetic defects in GRN consists of loss-of-function mutations, causing haploinsufficiency, and is associated with extremely low plasma progranulin levels. Herein, we describe a patient who developed language dysfunctions and memory disturbances at 63 years of age. Considering the early onset and the positive family history (sister aged 50 with non-fluent/agrammatic variant of primary progressive aphasia, father with behavioral disturbances in his sixties), a genetic analysis was carried out, showing the presence of a novel mutation [g.9543delA (IVS3-2delA)] in a predicted splicing site of GRN. Her progranulin plasma levels were under the reference threshold, as in her sister, thus supporting the causative role of the new variant. The same genetic mutation was confirmed by sequencing in her sister. Results described enlarge current knowledge on genetic causes of the disease and clinical characteristics of carriers.

Non-Verbal Episodic Memory Deficits in Primary Progressive Aphasias are Highly Predictive of Underlying Amyloid Pathology. - Ramanan, Siddharth; Flanagan, Emma; Leyton, Cristian E; Villemagne, Victor L; Rowe, Christopher C; Hodges, John R; Hornberger, Michael (J Alzheimers Dis, 2016)
Diagnostic distinction of primary progressive aphasias (PPA) remains challenging, in particular for the logopenic (lvPPA) and nonfluent/agrammatic (naPPA) variants. Recent findings highlight that episodic memory deficits appear to discriminate these PPA variants from each other, as only lvPPA perform poorly on these tasks while having underlying amyloid pathology similar to that seen in amnestic dementias like Alzheimer's disease (AD). Most memory tests are, however, language based and thus potentially confounded by the prevalent language deficits in PPA. The current study investigated this issue across PPA variants by contrasting verbal and non-verbal episodic memory measures while controlling for their performance on a language subtest of a general cognitive screen. A total of 203 participants were included (25 lvPPA; 29 naPPA; 59 AD; 90 controls) and underwent extensive verbal and non-verbal episodic memory testing, with a subset of patients (n = 45) with confirmed amyloid profiles as assessed by Pittsburgh Compound B and PET. The most powerful discriminator between naPPA and lvPPA patients was a non-verbal recall measure (Rey Complex Figure delayed recall), with 81% of PPA patients classified correctly at presentation. Importantly, AD and lvPPA patients performed comparably on this measure, further highlighting the importance of underlying amyloid pathology in episodic memory profiles. The findings demonstrate that non-verbal recall emerges as the best discriminator of lvPPA and naPPA when controlling for language deficits in high load amyloid PPA cases.
Keywords: Aged; Alzheimer Disease; Amyloid; Aniline Compounds; Aphasia, Primary Progressive; Brain; Diagnosis, Differential; Female; Humans; Logistic Models; Male; Memory, Episodic; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Speech Perception; Thiazoles

Novel Selective Calpain 1 Inhibitors as Potential Therapeutics in Alzheimer's Disease. - Fà, Mauro; Zhang, Hong; Staniszewski, Agnieszka; Saeed, Faisal; Shen, Li W; Schiefer, Isaac T; Siklos, Marton I; Tapadar, Subhasish; Litosh, Vladislav A; Libien, Jenny; Petukhov, Pavel A; Teich, Andrew F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease, one of the most important brain pathologies associated with neurodegenerative processes, is related to overactivation of calpain-mediated proteolysis. Previous data showed a compelling efficacy of calpain inhibition against abnormal synaptic plasticity and memory produced by the excess of amyloid-β, a distinctive marker of the disease. Moreover, a beneficial effect of calpain inhibitors in Alzheimer's disease is predictable by the occurrence of calpain hyperactivation leading to impairment of memory-related pathways following abnormal calcium influxes that might ensue independently of amyloid-β elevation. However, molecules currently available as effective calpain inhibitors lack adequate selectivity. This work is aimed at characterizing the efficacy of a novel class of epoxide-based inhibitors, synthesized to display improved selectivity and potency towards calpain 1 compared to the prototype epoxide-based generic calpain inhibitor E64. Both functional and preliminary toxicological investigations proved the efficacy, potency, and safety of the novel and selective calpain inhibitors NYC438 and NYC488 as possible therapeutics against the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cysteine Proteinase Inhibitors; Disease Models, Animal; Dose-Response Relationship, Drug; Fear; Glycoproteins; Hippocampus; Humans; In Vitro Techniques; Long-Term Potentiation; Maze Learning; Memory; Mice; Mice, Inbred ICR; Mice, Transgenic; Mutation; Patch-Clamp Techniques; Peptide Fragments; Presenilin-1; Spectrin

A Novel Small Molecule Modulator of Amyloid Pathology. - Lovell, Mark A; Lynn, Bert C; Fister, Shuling; Bradley-Whitman, Melissa; Murphy, M Paul; Beckett, Tina L; Norris, Christopher M (J Alzheimers Dis, 2016)
Because traditional approaches to drug development for Alzheimer's disease are becoming increasingly expensive and in many cases disappointingly unsuccessful, alternative approaches are required to shift the paradigm. Following leads from investigations of dihydropyridine calcium channel blockers, we observed unique properties from a class of functionalized naphthyridines and sought to develop these as novel therapeutics that minimize amyloid pathology without the adverse effects associated with current therapeutics. Our data show methyl 2,4-dimethyl-5-oxo-5,6-dihydrobenzo[c][2,7]naphthyridine-1-carboxylate (BNC-1) significantly decreases amyloid burden in a well-established mouse model of amyloid pathology through a unique mechanism mediated by Elk-1, a transcriptional repressor of presenilin-1. Additionally, BNC-1 treatment leads to increased levels of synaptophysin and synapsin, markers of synaptic integrity, but does not adversely impact presenilin-2 or processing of Notch-1, thus avoiding negative off target effects associated with pan-gamma secretase inhibition. Overall, our data show BNC-1 significantly decreases amyloid burden and improves markers of synaptic integrity in a well-established mouse model of amyloid deposition by promoting phosphorylation and activation of Elk-1, a transcriptional repressor of presenilin-1 but not presenilin-2. These data suggest BNC-1 might be a novel, disease-modifying therapeutic that will alter the pathogenesis of Alzheimer's disease.

Oculodentodigital dysplasia with massive brain calcification and a new mutation of GJA1 gene. - Tumminelli, Gemma; Di Donato, Ilaria; Guida, Valentina; Rufa, Alessandra; De Luca, Alessandro; Federico, Antonio (J Alzheimers Dis, 2016)
Oculodentodigital dysplasia (ODDD) [MIM 164200] is a rare disorder caused by mutations in the gap junction alpha 1 (GJA1) gene encoding for connexin 43 (Cx43). Typical signs include type III syndactyly, microphtalmia, microdontia, and neurological disturbances. We report a 59-year-old man having clinical symptoms and signs suggestive of ODDD, with some rarely reported features, that is the presence of gross calcifications of basal ganglia and cerebellar nuclei. Mutation analysis of GJA1 gene identified an unreported heterozygous missense mutation [NM_000165.3:c.124 G>C;p.(Glu42Gln)], which may be thought to alter the brain microvessels leading to massive calcifications, as in primary familial brain calcification.
Keywords: Basal Ganglia; Calcinosis; Connexin 43; Craniofacial Abnormalities; DNA Mutational Analysis; Eye Abnormalities; Fingers; Foot Deformities, Congenital; Humans; Male; Middle Aged; Mutation, Missense; Syndactyly; Tomography, X-Ray Computed; Tooth Abnormalities

Optimization of Statistical Single Subject Analysis of Brain FDG PET for the Prognosis of Mild Cognitive Impairment-to-Alzheimer's Disease Conversion. - Lange, Catharina; Suppa, Per; Frings, Lars; Brenner, Winfried; Spies, Lothar; Buchert, Ralph (J Alzheimers Dis, 2016)
BACKGROUND: Positron emission tomography (PET) with the glucose analog F-18-fluorodeoxyglucose (FDG) is widely used in the diagnosis of neurodegenerative diseases. Guidelines recommend voxel-based statistical testing to support visual evaluation of the PET images. However, the performance of voxel-based testing strongly depends on each single preprocessing step involved. OBJECTIVE: To optimize the processing pipeline of voxel-based testing for the prognosis of dementia in subjects with amnestic mild cognitive impairment (MCI). METHODS: The study included 108 ADNI MCI subjects grouped as 'stable MCI' (n = 77) or 'MCI-to-AD converter' according to their diagnostic trajectory over 3 years. Thirty-two ADNI normals served as controls. Voxel-based testing was performed with the statistical parametric mapping software (SPM8) starting with default settings. The following modifications were added step-by-step: (i) motion correction, (ii) custom-made FDG template, (iii) different reference regions for intensity scaling, and (iv) smoothing was varied between 8 and 18 mm. The t-sum score for hypometabolism within a predefined AD mask was compared between the different settings using receiver operating characteristic (ROC) analysis with respect to differentiation between 'stable MCI' and 'MCI-to-AD converter'. The area (AUC) under the ROC curve was used as performance measure. RESULTS: The default setting provided an AUC of 0.728. The modifications of the processing pipeline improved the AUC up to 0.832 (p = 0.046). Improvement of the AUC was confirmed in an independent validation sample of 241 ADNI MCI subjects (p = 0.048). CONCLUSION: The prognostic value of voxel-based single subject analysis of brain FDG PET in MCI subjects can be improved considerably by optimizing the processing pipeline.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Glucose; Humans; Image Interpretation, Computer-Assisted; Male; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve

Oral Infections and Cytokine Levels in Patients with Alzheimer's Disease and Mild Cognitive Impairment Compared with Controls. - Cestari, José Augusto Ferrari; Fabri, Gisele Maria Campos; Kalil, Jorge; Nitrini, Ricardo; Jacob-Filho, Wilson; de Siqueira, José Tadeu Tesseroli; Siqueira, Silvia Regina D T (J Alzheimers Dis, 2016)
BACKGROUND: Oral infections are prevalent in the adult population. Their impact includes the implication as a risk factor for Alzheimer's disease (AD), altering its progression. One of the potential mechanisms involves immune mediators such as circulating cytokines. OBJECTIVE: The goal of the present study was to investigate the prevalence of oral infections and blood levels of IL-1β, TNF-α, and IL-6 in patients with AD, mild cognitive impairment (MCI), and controls. METHODS: Sixty-five elderly were evaluated (25 AD, 19 MCI, and 21 controls) by the following methods: Mini Mental State Exam, Questionnaire of Functional Activities, periodontal and oral evaluation, and blood concentrations of IL-1β, TNF-α and IL-6. RESULTS: Patients with AD had high serum IL-6 levels (p = 0.029), and patients with periodontitis had high serum TNF-α levels (p = 0.005). There was an association between IL-6 and TNF-α in patients with AD/MCI and periodontitis (p = 0.023). CONCLUSION: The increased levels of TNF-α and IL-6 in this study suggests their implication in the overlapping mechanisms between oral infections and AD. Longitudinal studies are necessary for further investigation.

Outstanding Phenotypic Differences in the Profile of Amyloid-β between Tg2576 and APPswe/PS1dE9 Transgenic Mouse Models of Alzheimer's Disease. - Allué, José Antonio; Sarasa, Leticia; Izco, María; Pérez-Grijalba, Virginia; Fandos, Noelia; Pascual-Lucas, María; Ogueta, Samuel; Pesini, Pedro; Sarasa, Manuel (J Alzheimers Dis, 2016)
APPswe/PS1dE9 and Tg2576 are very common transgenic mouse models of Alzheimer's disease (AD), used in many laboratories as tools to research the mechanistic process leading to the disease. In order to augment our knowledge about the amyloid-β (Aβ) isoforms present in both transgenic mouse models, we have developed two chromatographic methods, one acidic and the other basic, for the characterization of the Aβ species produced in the brains of the two transgenic mouse models. After immunoprecipitation and micro-liquid chromatography-electrospray ionization mass spectrometry/mass spectrometry, 10 species of Aβ, surprisingly all of human origin, were detected in the brain of Tg2576 mouse, whereas 39 species, of both murine and human origin, were detected in the brain of the APP/PS1 mouse. To the best of our knowledge, this is the first study showing the identification of such a high number of Aβ species in the brain of the APP/PS1 transgenic mouse, whereas, in contrast, a much lower number of Aβ species were identified in the Tg2576 mouse. Therefore, this study brings to light a relevant phenotypic difference between these two popular mice models of AD.

Paired Studies Comparing Clinical Profiles of Lewy Body Dementia with Alzheimer's and Parkinson's Diseases. - Scharre, Douglas W; Chang, Shu-Ing; Nagaraja, Haikady N; Park, Ariane; Adeli, Anahita; Agrawal, Punit; Kloos, Anne; Kegelmeyer, Deb; Linder, Shannon; Fritz, Nora; Kostyk, Sandra K; Kataki, Maria (J Alzheimers Dis, 2016)
Limited data compares clinical profiles of Lewy Body Dementia (LBD) with Alzheimer's disease (AD) and Parkinson's disease (PD). Twenty-one mildly demented ambulatory LBD subjects were individually matched by MMSE score with 21 AD subjects and by UPDRS motor score with 21 PD subjects. Matched by age, gender, education, and race, pairs were compared using cognitive, functional, behavioral, and motor measures. LBD group performed worse than PD on axial motor, gait, and balance measures. AD had more amnesia and orientation impairments, but less executive and visuospatial deficits than LBD subjects. LBD group had more sleepiness, cognitive/behavioral fluctuations, hallucinations, and sleep apnea than AD or PD. Axial motor, gait, and balance disturbances correlated with executive, visuospatial, and global cognition deficits. LBD is differentiated from AD and PD by retrieval memory, visuospatial, and executive deficits; axial motor, gait and balance impairments; sleepiness, cognitive/behavioral fluctuations, hallucinations, and sleep apnea.

Patients with Mild Alzheimer's Disease Fail When Using Their Working Memory: Evidence from the Eye Tracking Technique. - Fernández, Gerardo; Manes, Facundo; Politi, Luis E; Orozco, David; Schumacher, Marcela; Castro, Liliana; Agamennoni, Osvaldo; Rotstein, Nora P (J Alzheimers Dis, 2016)
Patients with Alzheimer's disease (AD) develop progressive language, visuoperceptual, attentional, and oculomotor changes that can have an impact on their reading comprehension. However, few studies have examined reading behavior in AD, and none have examined the contribution of predictive cueing in reading performance. For this purpose we analyzed the eye movement behavior of 35 healthy readers (Controls) and 35 patients with probable AD during reading of regular and high-predictable sentences. The cloze predictability of words N - 1, and N + 1 exerted an influence on the reader's gaze duration. The predictabilities of preceding words in high-predictable sentences served as task-appropriate cues that were used by Control readers. In contrast, these effects were not present in AD patients. In Controls, changes in predictability significantly affected fixation duration along the sentence; noteworthy, these changes did not affect fixation durations in AD patients. Hence, only in healthy readers did predictability of upcoming words influence fixation durations via memory retrieval. Our results suggest that Controls used stored information of familiar texts for enhancing their reading performance and imply that contextual-word predictability, whose processing is proposed to require memory retrieval, only affected reading behavior in healthy subjects. In AD patients, this loss reveals impairments in brain areas such as those corresponding to working memory and memory retrieval. These findings might be relevant for expanding the options for the early detection and monitoring in the early stages of AD. Furthermore, evaluation of eye movements during reading could provide a new tool for measuring drug impact on patients' behavior.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Eye Movements; Female; Humans; Linear Models; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Mental Status Schedule; Predictive Value of Tests; Semantics; Verbal Learning

PDE5 Exists in Human Neurons and is a Viable Therapeutic Target for Neurologic Disease. - Teich, Andrew F; Sakurai, Mikako; Patel, Mitesh; Holman, Cameron; Saeed, Faisal; Fiorito, Jole; Arancio, Ottavio (J Alzheimers Dis, 2016)
Phosphodiesterase 5 (PDE5) is a critical component of the cGMP-PKG axis of cellular signaling in neurons, and inhibition of PDE5 has been shown to be therapeutic in a wide range of neurologic conditions in animal models. However, enthusiasm for PDE5 inhibitors in humans is limited by data suggesting that PDE5 may not exist in human neurons. Here, we first show that past attempts to quantify PDE5 mRNA were flawed due to the use of incorrect primers, and that when correct primers are used, PDE5 mRNA is detectable in human brain tissue. We then show that PDE5 protein exists in human brain by western blot and ELISA. Most importantly, we performed immunohistochemistry and demonstrate that PDE5 is present in human neurons. We hope that this work will trigger a renewed interest in the development of PDE5 inhibitors for neurologic disease.
Keywords: Blotting, Western; Brain; Cyclic Nucleotide Phosphodiesterases, Type 5; DNA Primers; Enzyme-Linked Immunosorbent Assay; Humans; Immunohistochemistry; Nervous System Diseases; Neurons; Phosphodiesterase 5 Inhibitors; Polymerase Chain Reaction; RNA, Messenger

Performance Evaluation of an Automated ELISA System for Alzheimer's Disease Detection in Clinical Routine. - Chiasserini, Davide; Biscetti, Leonardo; Farotti, Lucia; Eusebi, Paolo; Salvadori, Nicola; Lisetti, Viviana; Baschieri, Francesca; Chipi, Elena; Frattini, Giulia; Stoops, Erik; Vanderstichele, Hugo; Calabresi, Paolo; et al. (J Alzheimers Dis, 2016)
The variability of Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers undermines their full-fledged introduction into routine diagnostics and clinical trials. Automation may help to increase precision and decrease operator errors, eventually improving the diagnostic performance. Here we evaluated three new CSF immunoassays, EUROIMMUNtrademark amyloid-β 1-40 (Aβ1-40), amyloid-β 1-42 (Aβ1-42), and total tau (t-tau), in combination with automated analysis of the samples. The CSF biomarkers were measured in a cohort consisting of AD patients (n = 28), mild cognitive impairment (MCI, n = 77), and neurological controls (OND, n = 35). MCI patients were evaluated yearly and cognitive functions were assessed by Mini-Mental State Examination. The patients clinically diagnosed with AD and MCI were classified according to the CSF biomarkers profile following NIA-AA criteria and the Erlangen score. Technical evaluation of the immunoassays was performed together with the calculation of their diagnostic performance. Furthermore, the results for EUROIMMUN Aβ1-42 and t-tau were compared to standard immunoassay methods (INNOTESTtrademark). EUROIMMUN assays for Aβ1-42 and t-tau correlated with INNOTEST (r = 0.83, p < 0.001 for both) and allowed a similar interpretation of the CSF profiles. The Aβ1-42/Aβ1-40 ratio measured with EUROIMMUN was the best parameter for AD detection and improved the diagnostic accuracy of Aβ1-42 (area under the curve = 0.93). In MCI patients, the Aβ1-42/Aβ1-40 ratio was associated with cognitive decline and clinical progression to AD.The diagnostic performance of the EUROIMMUN assays with automation is comparable to other currently used methods. The variability of the method and the value of the Aβ1-42/Aβ1-40 ratio in AD diagnosis need to be validated in large multi-center studies.

Performance of Hippocampus Volumetry with FSL-FIRST for Prediction of Alzheimer's Disease Dementia in at Risk Subjects with Amnestic Mild Cognitive Impairment. - Suppa, Per; Hampel, Harald; Kepp, Timo; Lange, Catharina; Spies, Lothar; Fiebach, Jochen B; Dubois, Bruno; Buchert, Ralph (J Alzheimers Dis, 2016)
MRI-based hippocampus volume, a core feasible biomarker of Alzheimer's disease (AD), is not yet widely used in clinical patient care, partly due to lack of validation of software tools for hippocampal volumetry that are compatible with routine workflow. Here, we evaluate fully-automated and computationally efficient hippocampal volumetry with FSL-FIRST for prediction of AD dementia (ADD) in subjects with amnestic mild cognitive impairment (aMCI) from phase 1 of the Alzheimer's Disease Neuroimaging Initiative. Receiver operating characteristic analysis of FSL-FIRST hippocampal volume (corrected for head size and age) revealed an area under the curve of 0.79, 0.70, and 0.70 for prediction of aMCI-to-ADD conversion within 12, 24, or 36 months, respectively. Thus, FSL-FIRST provides about the same power for prediction of progression to ADD in aMCI as other volumetry methods.
Keywords: Aged; Aging; Alzheimer Disease; Area Under Curve; Cognitive Dysfunction; Databases, Factual; Disease Progression; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Organ Size; Pattern Recognition, Automated; Prognosis; Reproducibility of Results; Risk; ROC Curve; Sensitivity and Specificity; Time Factors

Peripheral Administration of GSK-3β Antisense Oligonucleotide Improves Learning and Memory in SAMP8 and Tg2576 Mouse Models of Alzheimer's Disease. - Farr, Susan A; Sandoval, Karin E; Niehoff, Michael L; Witt, Ken A; Kumar, Vijaya B; Morley, John E (J Alzheimers Dis, 2016)
Glycogen synthase kinase (GSK)-3β is a multifunctional protein that has been implicated in the pathological characteristics of Alzheimer's disease (AD), including the heightened levels of neurofibrillary tangles, amyloid-beta (Aβ), and neurodegeneration. We have previously shown that an antisense oligonucleotide directed at the Tyr 216 site on GSK-3β (GAO) when injected centrally can decrease GSK-3β levels, improve learning and memory, and decrease oxidative stress. In addition, we showed that GAO can cross the blood-brain barrier. Herein the impact of peripherally administered GAO in both the non-transgenic SAMP8 and transgenic Tg2576 (APPswe) models of AD were examined respective to learning and memory. Brain tissues were then evaluated for expression changes in the phosphorylated-Tyr 216 residue, which leads to GSK-3β activation, and the phosphorylated-Ser9 residue, which reduces GSK-3β activity. SAMP8 GAO-treated mice showed improved acquisition and retention using aversive T-maze, and improved declarative memory as measured by the novel object recognition (NOR) test. Expression of the phosphorylated-Tyr 216 was decreased and the phosphorylated-Ser9 was increased in GAO-treated SAMP8 mice. Tg2576 GAO-treated mice improved acquisition and retention in both the T-maze and NOR tests, with an increased phosphorylated-Ser9 GSK-3β expression. Results demonstrate that peripheral administration of GAO improves learning and memory, corresponding with alterations in GSK-3β phosphorylation state. This study supports peripherally administered GAO as a viable means to mediate GSK-3β activity within the brain and a possible treatment for AD.

Pharmacological Modulations of the Serotonergic System in a Cell-Model of Familial Alzheimer's Disease. - Tajeddinn, Walid; Persson, Torbjörn; Calvo-Garrido, Javier; Seed Ahmed, Mohammed; Maioli, Silvia; Vijayaraghavan, Swetha; Kazokoglu, Mehmet Selim; Parrado-Fernández, Cristina; Yoshitake, Takashi; Kehr, Jan; Francis, Paul; Winblad, Bengt; et al. (J Alzheimers Dis, 2016)
Serotonin (5-HT) plays a central role in the integrity of different brain functions. The 5-HT homeostasis is regulated by many factors, including serotonin transporter (SERT), monoamine oxidase enzyme (MAO), and several 5-HT receptors, including the 5-HT1B. There is little knowledge how the dynamics of this system is affected by the amyloid-β (Aβ) burden of Alzheimer's disease (AD) pathology. SH-SY5Y neuroblastoma cells transfected with the amyloid precursor protein (APP) gene containing the Swedish mutations causing familial AD (APPswe), were used as a model to explore the effect of Aβ pathology on 5-HT1B and related molecules including the receptor adaptor protein (p11), SERT and MAOA gene expression, and MAOA activity after treatment with selective serotonin reuptake inhibitor (SSRI) (sertraline), and a 5-HT1B receptor antagonist. Sertraline led more than 70 fold increase of 5-HT1B gene expression (p < 0.001), an increased serotonin turnover in both APPswe and control cells and reduced intracellular serotonin levels by 75% in APPswe cells but not in controls (p > 0.05). Treatment with the 5-HT1B receptor antagonist increased SERT gene-expression in control cells but not in the APPswe cells. 5-HT and 5-HT1B antagonist treatment resulted in different p11 expression patterns in APPswe cells compared to controls. Although MAOA gene expression was not changed by APPswe overexpression, adding 5-HT lead to a significant increase in MAOA gene expression in APPswe but not control cells. These findings suggest that the sensitivity of the 5-HT1B receptor and related systems is affected by APPswe overexpression, with potential relevance for pharmacologic intervention in AD. This may at least partly explain the lack of effect of SSRIs in patients with AD and depression.

A Phase II Study of Fornix Deep Brain Stimulation in Mild Alzheimer's Disease. - Lozano, Andres M; Fosdick, Lisa; Chakravarty, M Mallar; Leoutsakos, Jeannie-Marie; Munro, Cynthia; Oh, Esther; Drake, Kristen E; Lyman, Christopher H; Rosenberg, Paul B; Anderson, William S; Tang-Wai, David F; Pendergrass, Jo Cara; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Deep brain stimulation (DBS) is used to modulate the activity of dysfunctional brain circuits. The safety and efficacy of DBS in dementia is unknown. OBJECTIVE: To assess DBS of memory circuits as a treatment for patients with mild Alzheimer's disease (AD). METHODS: We evaluated active "on" versus sham "off" bilateral DBS directed at the fornix-a major fiber bundle in the brain's memory circuit-in a randomized, double-blind trial (ClinicalTrials.gov NCT01608061) in 42 patients with mild AD. We measured cognitive function and cerebral glucose metabolism up to 12 months post-implantation. RESULTS: Surgery and electrical stimulation were safe and well tolerated. There were no significant differences in the primary cognitive outcomes (ADAS-Cog 13, CDR-SB) in the "on" versus "off" stimulation group at 12 months for the whole cohort. Patients receiving stimulation showed increased metabolism at 6 months but this was not significant at 12 months. On post-hoc analysis, there was a significant interaction between age and treatment outcome: in contrast to patients  CONCLUSION: DBS for AD was safe and associated with increased cerebral glucose metabolism. There were no differences in cognitive outcomes for participants as a whole, but participants aged≥65 years may have derived benefit while there was possible worsening in patients below age 65 years with stimulation.

Physical and Cognitive Stimulation Using an Exergame in Subjects with Normal Aging, Mild and Moderate Cognitive Impairment. - Ben-Sadoun, Grégory; Sacco, Guillaume; Manera, Valeria; Bourgeois, Jérémy; König, Alexandra; Foulon, Pierre; Fosty, Baptiste; Bremond, François; d'Arripe-Longueville, Fabienne; Robert, Philippe (J Alzheimers Dis, 2016)
BACKGROUND: The use of Serious exerGames (SeG) as enriched environments (EE), which promotes cognitive simulation with physical activity in a positive emotional context, has been proposed to represent a powerful method to slow down the decline due to neurodegenerative diseases (ND), such as Alzheimer's disease (AD). However, so far, no SeG targeting EE has been tested in ND subjects. OBJECTIVE: This study aimed at evaluating the usability and short-term training effects of X-Torp, an action SeG designed for elderly ND subjects with mild cognitive impairment (MCI) and AD. METHODS: X-Torp is a SeG played using the Microsoft® Kinect™. 10 ND subjects and 8 healthy elderly controls (HEC) were enrolled in a 1-month program with three training sessions per week. Usability was evaluated through game time, game performance, the aerobic intensity level reached, perceived emotions, and perceived usability. RESULTS: All participants successfully completed the training program. ND subjects played less and had a lower game performance compared to HEC. During the sessions, ND subjects maintained a light intensity of aerobic activity, while HEC maintained a moderate intensity. Both groups experienced only positive emotions, and reported a 'moderate' to 'high' perceived competence, a 'moderate' game difficulty, and a 'high' interest in the game. CONCLUSION: Usability results suggest that X-Torp represents a usable EE for healthy subjects and persons with MCI and AD. However, in order to reach moderate or high intensity of aerobic activity, X-Torp control modes should be adapted to become more physically stimulating.

Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study. - Chatterjee, Pratishtha; Lim, Wei L F; Shui, Guanghou; Gupta, Veer B; James, Ian; Fagan, Anne M; Xiong, Chengjie; Sohrabi, Hamid R; Taddei, Kevin; Brown, Belinda M; Benzinger, Tammie; Masters, Colin; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). METHODS: Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. RESULTS: One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p <  0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p <  0.05). CONCLUSION: These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.
Keywords: Adult; Alzheimer Disease; Apolipoproteins E; Female; Humans; Linear Models; Male; Middle Aged; Mutation; Phospholipids; Pilot Projects; Presenilin-1; Sphingolipids

Plasma Screening for Progranulin Mutations in Patients with Progressive Supranuclear Palsy and Corticobasal Syndromes. - Galimberti, Daniela; Bertram, Kelly; Formica, Alessandra; Fenoglio, Chiara; Cioffi, Sara M G; Arighi, Andrea; Scarpini, Elio; Colosimo, Carlo (J Alzheimers Dis, 2016)
Progranulin gene (GRN) mutations are characterized by heterogeneous presentations. Corticobasal syndrome (CBS) is often associated with GRN mutations, whereas association with progressive supranuclear palsy syndrome (PSPS) is rare. Plasma progranulin levels were evaluated in 34 patients, including 19 with PSPS, 12 with CBS, and 3 with mixed signs, with the purpose to screen for the presence of causal mutations, associated with low levels. We found undetectable levels in a patient with CBS. Sequencing confirmed the presence of the Thr272fs deletion. Progranulin mutation screening is suggested in cases of CBS, even in the absence of positive family history for dementia and/or movement disorders.

Platelet Membrane β-Secretase Activity in Mild Cognitive Impairment and Conversion to Dementia: a Longitudinal Study. - McGuinness, Bernadette; Fuchs, Marc; Barrett, Suzanne L; Passmore, A Peter; Johnston, Janet A (J Alzheimers Dis, 2016)
A blood-based biomarker to complement the clinical and neuropsychological assessments used to evaluate the risk of individuals with mild cognitive impairment (MCI) developing Alzheimer's disease (AD) would be invaluable. Previous pilot studies by our group identified elevated platelet membrane β-secretase activity in patients with AD and MCI, as compared to controls, and this activity was influenced by membrane cholesterol levels. The present study investigated baseline platelet membrane β-secretase activity and cholesterol levels in 97 MCI participants and 85 controls and explored whether these parameters differed in individuals with stable MCI, as compared to those who subsequently developed AD. To evaluate signal specificity, β-secretase activity assays were conducted in the presence and absence of beta-site amyloid-β protein precursor-cleaving enzyme (BACE) inhibitors. Baseline platelet membrane β-secretase activity did not differ significantly in MCI participants, as compared to controls, and platelet membrane cholesterol levels were significantly lower in the MCI group. The longitudinal study indicated that the activities inhibited by two different BACE inhibitors did not predict conversion to AD; however, the activity that was not affected by BACE inhibitors was significantly (40%) higher in individuals with stable MCI, as compared with those who subsequently developed AD. These findings indicated that further research into the source of this activity could contribute to a measure facilitating prediction of the risk of conversion from MCI to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Biomarkers; Blood Platelets; Cholesterol; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Neuropsychological Tests; Sensitivity and Specificity

Prediction of Alzheimer's Disease in Amnestic Mild Cognitive Impairment Subtypes: Stratification Based on Imaging Biomarkers. - Ota, Kenichi; Oishi, Naoya; Ito, Kengo; Fukuyama, Hidenao (J Alzheimers Dis, 2016)
BACKGROUND: Prediction of progression to Alzheimer's disease (AD) in amnestic mild cognitive impairment (MCI) is challenging because of its heterogeneity. OBJECTIVE: To evaluate a stratification method on different cohorts and to investigate whether stratification in amnestic MCI could improve prediction accuracy. METHODS: We identified 80 and 79 patients with amnestic MCI from different cohorts, respectively. They underwent baseline magnetic resonance imaging (MRI) and 18F-fluorodeoxyglucose (FDG) positron emission tomography (PET) scans. We performed hierarchical clustering with three imaging biomarkers: Brain volume on MRI, left hippocampus grey matter loss on MRI, and left inferior temporal gyrus glucose hypometabolism on FDG-PET. Regions-of-interest for biomarkers were defined by the Automated Anatomical Labeling atlas. We performed voxel-wise statistical parametric mapping to explore differences between clusters in patterns of grey matter loss and glucose hypometabolism. We compared time to progression using an interval-censored parametric model. We evaluated predictive performance using logistic regression. RESULTS: Similar clusters were found in different cohorts. MCI1 had the healthiest biomarker profile of cognitive performance and imaging biomarkers. MCI2 had cognitive performance and MRI measures intermediate between those of nonconverters and converters. MCI3 showed the severest reduction in brain volume and left hippocampal atrophy. MCI4 showed remarkable glucose hypometabolism in the left inferior temporal gyrus, and also demonstrated significant decreases in most cognitive scores, including non-memory functions. MCI4 showed the highest risk for progression. The prediction of progression of MCI2 especially benefited from the stratification. CONCLUSION: Stratification with imaging biomarkers in amnestic MCI can be a good approach for improving predictive performance.

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy. - Stern, Robert A; Tripodis, Yorghos; Baugh, Christine M; Fritts, Nathan G; Martin, Brett M; Chaisson, Christine; Cantu, Robert C; Joyce, James A; Shah, Sahil; Ikezu, Tsuneya; Zhang, Jing; Gercel-Taylor, Cicek; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's disease, there is a need for methods to diagnose CTE during life through objective biomarkers. OBJECTIVE: The aim of this study was to examine tau-positive exosomes in plasma as a potential CTE biomarker. METHODS: Subjects were 78 former National Football League (NFL) players and 16 controls. Extracellular vesicles were isolated from plasma. Fluorescent nanoparticle tracking analysis was used to determine the number of vesicles staining positive for tau. RESULTS: The NFL group had higher exosomal tau than the control group (p <  0.0001). Exosomal tau discriminated between the groups, with 82% sensitivity, 100% specificity, 100% positive predictive value, and 53% negative predictive value. Within the NFL group, higher exosomal tau was associated with worse performance on tests of memory (p = 0.0126) and psychomotor speed (p = 0.0093). CONCLUSION: These preliminary findings suggest that exosomal tau in plasma may be an accurate, noninvasive CTE biomarker.
Keywords: Adult; Aged; Analysis of Variance; Case-Control Studies; Chronic Traumatic Encephalopathy; Extracellular Vesicles; Humans; Male; Middle Aged; Plasma; tau Proteins

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Protective Effect of Amyloid-β Peptides Against Herpes Simplex Virus-1 Infection in a Neuronal Cell Culture Model. - Bourgade, Karine; Le Page, Aurélie; Bocti, Christian; Witkowski, Jacek M; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Senile amyloid plaques are one of the main hallmarks of Alzheimer's disease (AD). They correspond to insoluble deposits of amyloid-β peptides (Aβ) and are responsible for the inflammatory response and neurodegeneration that lead to loss of memory. Recent data suggest that Aβ possess antimicrobial and anti-viral activity in vitro. Here, we have used cocultures of neuroglioma (H4) and glioblastoma (U118-MG) cells as a minimal in vitro model to investigate whether Aβ is produced by neuroglioma cells and whether this could result in protective anti-viral activity against HSV-1 infection. Results showed that H4 cells secreted Aβ42 in response to HSV-1 challenge and that U118-MG cells could rapidly internalize Aβ42. Production of pro-inflammatory cytokines TNFα and IL-1β by H4 and U118-MG cells occurred under basal conditions but infection of the cells with HSV-1 did not significantly upregulate production. Both cell lines produced low levels of IFNα. However, extraneous Aβ42 induced strong production of these cytokines. A combination of Aβ42 and HSV-1 induced production of pro-inflammatory cytokines TNFα and IL-1β, and IFNα in the cell lines. The reported anti-viral protection of Aβ42 was revealed in transfer experiments involving conditioned medium (CM) of HSV-1-infected H4 cells. CM conferred Aβ-dependent protection against HSV-1 replication in de novo cultures of H4 cells challenged with HSV-1. Type 1 interferons did not play a role in these assays. Our data established that H4 neuroglioma cells produced Aβ42 in response to HSV-1 infection thus inhibiting secondary replication. This mechanism may play a role in the etiology of AD.
Keywords: Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Cell Line, Tumor; Coculture Techniques; Culture Media, Conditioned; Herpes Simplex; Herpesvirus 1, Human; Humans; Interferon-alpha; Interleukin-1beta; Neuroglia; Neurons; Peptide Fragments; Tumor Necrosis Factor-alpha; Virus Replication

Psychometric Properties of the Memory Binding Test: Test-Retest Reliability and Convergent Validity. - Gramunt, Nina; Sánchez-Benavides, Gonzalo; Buschke, Herman; Lipton, Richard B; Masramon, Xavier; Gispert, Juan D; Peña-Casanova, Jordi; Fauria, Karine; Molinuevo, José L (J Alzheimers Dis, 2016)
BACKGROUND: Episodic memory testing is fundamental for the diagnosis of Alzheimer's disease (AD). Although the Free and Cued Selective Reminding Test (FCSRT) is widely used for this purpose, it may not be sensitive enough for early detection of subtle decline in preclinical AD. The Memory Binding Test (MBT) intends to overcome this limitation. OBJECTIVES: To analyze the test-retest reliability of the MBT and its convergent validity with the FCRST. METHODS: 36 cognitively healthy participants of the ALFA Study, aged 45 to 65, were included for the test-retest study and 69 for the convergent analysis. They were visited twice in a period of 6 ± 2 weeks. Test-retest reliability was determined by the calculation of the intra-class correlation coefficient (ICC). Score differences were studied by computing the mean percentage of score variation between visits and visualized by Bland-Altman plots. Convergent validity was determined by Pearson's correlations. RESULTS: ICC values in the test-retest reliability analysis of the MBT direct scores ranged from 0.64 to 0.76. Subjects showed consistent practice effects, with mean amounts of score increasing between 10% and 26%. Pearson correlation between MBT and FCSRT direct scores showed r values between 0.40 and 0.53. The FCSRT displayed ceiling effects not observed in the MBT. CONCLUSIONS: The MBT shows adequate test-retest reliability and overall moderate convergent validity with the FCSRT. Unlike the FCSRT, the MBT does not have ceiling effects and it may therefore be especially useful in longitudinal studies, facilitating the measurement of subtle memory performance decline and the detection of very early AD.
Keywords: Aged; Alzheimer Disease; Female; Humans; Male; Memory; Middle Aged; Psychological Tests; Psychometrics; Reproducibility of Results

Reduction of Amyloid-β Plasma Levels by Hemodialysis: An Anti-Amyloid Treatment Strategy? - Tholen, Susanne; Schmaderer, Christoph; Chmielewski, Stefan; Förstl, Hans; Heemann, Uwe; Baumann, Marcus; Steubl, Dominik; Grimmer, Timo (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment in hemodialysis patients is common, but the underlying pathogenesis remains unclear. Alzheimer's disease is the most common cause of dementia in the general elderly population. Histopathological hallmarks are, among others, senile plaques, which consist of amyloid-β (Aβ). OBJECTIVE: To measure plasma levels of Aβ42 and Aβ40 during hemodialysis and to examine potential associations with cognitive performance in cognitively impaired hemodialysis patients. METHODS: Plasma samples of 26 hemodialysis patients were collected shortly before, after 50% of dialysis time, and at the end of a dialysis session. Aβ42 and Aβ40 levels were measured by a high-sensitivity ELISA for human amyloid-β. Cognition was tested under standardized conditions using the Montreal Cognitive Assessment (MoCA) as proposed previously. RESULTS: Clearance rates of both peptides during one dialysis session were 22% and 35% for Aβ42 and Aβ40, respectively. Aβ42 but not Aβ40 baseline levels were significantly associated with MoCA test results (r = 0.654, p = 0.001). CONCLUSION: In cognitively impaired hemodialysis patients plasma Aβ42 levels were associated with cognitive performance and both Aβ42 and Aβ40 plasma levels could be effectively reduced by dialysis. By inducing peripheral Aβ sink, hemodialysis may be considered as an anti-amyloid treatment strategy.
Keywords: Adult; Aged; Aged, 80 and over; Amyloid beta-Peptides; Cognition Disorders; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Renal Dialysis

Reduction of Blood Amyloid-β Oligomers in Alzheimer's Disease Transgenic Mice by c-Abl Kinase Inhibition. - Estrada, Lisbell D; Chamorro, David; Yañez, María José; Gonzalez, Marcelo; Leal, Nancy; von Bernhardi, Rommy; Dulcey, Andrés E; Marugan, Juan; Ferrer, Marc; Soto, Claudio; Zanlungo, Silvana; Inestrosa, Nibaldo C; et al. (J Alzheimers Dis, 2016)
One of the pathological hallmarks of Alzheimer's disease (AD) is the presence of amyloid plaques, which are deposits of misfolded and aggregated amyloid-beta peptide (Aβ). The role of the c-Abl tyrosine kinase in Aβ-mediated neurodegeneration has been previously reported. Here, we investigated the therapeutic potential of inhibiting c-Abl using imatinib. We developed a novel method, based on a technique used to detect prions (PMCA), to measure minute amounts of misfolded-Aβ in the blood of AD transgenic mice. We found that imatinib reduces Aβ-oligomers in plasma, which correlates with a reduction of AD brain features such as plaques and oligomers accumulation, neuroinflammation, and cognitive deficits. Cells exposed to imatinib and c-Abl KO mice display decreased levels of β-CTF fragments, suggesting that an altered processing of the amyloid-beta protein precursor is the most probable mechanism behind imatinib effects. Our findings support the role of c-Abl in Aβ accumulation and AD, and propose AD-PMCA as a new tool to evaluate AD progression and screening for drug candidates.

Regular Benzodiazepine and Z-Substance Use and Risk of Dementia: An Analysis of German Claims Data. - Gomm, Willy; von Holt, Klaus; Thomé, Friederike; Broich, Karl; Maier, Wolfgang; Weckbecker, Klaus; Fink, Anne; Doblhammer, Gabriele; Haenisch, Britta (J Alzheimers Dis, 2016)
BACKGROUND: While acute detrimental effects of benzodiazepine (BDZ), and BDZ and related z-substance (BDZR) use on cognition and memory are known, the association of BDZR use and risk of dementia in the elderly is controversially discussed. Previous studies on cohort or claims data mostly show an increased risk for dementia with the use of BDZs or BDZRs. For Germany, analyses on large population-based data sets are missing. OBJECTIVE: To evaluate the association between regular BDZR use and incident any dementia in a large German claims data set. METHODS: Using longitudinal German public health insurance data from 2004 to 2011 we analyzed the association between regular BDZR use (versus no BDZR use) and incident dementia in a case-control design. We examined patient samples aged≥60 years that were free of dementia at baseline. To address potential protopathic bias we introduced a lag time between BDZR prescription and dementia diagnosis. Odds ratios were calculated applying conditional logistic regression, adjusted for potential confounding factors such as comorbidities and polypharmacy. RESULTS: The regular use of BDZRs was associated with a significant increased risk of incident dementia for patients aged≥60 years (adjusted odds ratio [OR] 1.21, 95% confidence interval [CI] 1.13-1.29). The association was slightly stronger for long-acting substances than for short-acting ones. A trend for increased risk for dementia with higher exposure was observed. CONCLUSION: The restricted use of BDZRs may contribute to dementia prevention in the elderly.

Reliability and Validity of a Novel Internet-Based Battery to Assess Mood and Cognitive Function in the Elderly. - Myers, Candice A; Keller, Jeffrey N; Allen, H Raymond; Brouillette, Robert M; Foil, Heather; Davis, Allison B; Greenway, Frank L; Johnson, William D; Martin, Corby K (J Alzheimers Dis, 2016)
Dementia is a chronic condition in the elderly and depression is often a concurrent symptom. As populations continue to age, accessible and useful tools to screen for cognitive function and its associated symptoms in elderly populations are needed. The aim of this study was to test the reliability and validity of a new internet-based assessment battery for screening mood and cognitive function in an elderly population. Specifically, the Helping Hand Technology (HHT) assessments for depression (HHT-D) and global cognitive function (HHT-G) were evaluated in a sample of 57 elderly participants (22 male, 35 female) aged 59-85 years. The study sample was categorized into three groups: 1) dementia (n = 8; Mini-Mental State Exam (MMSE) score 10-24), 2) mild cognitive impairment (n = 24; MMSE score 25-28), and 3) control (n = 25; MMSE score 29-30). Test-retest reliability (Pearson correlation coefficient, r) and internal consistency reliability (Cronbach's alpha, α) of the HHT-D and HHT-G were assessed. Validity of the HHT-D and HHT-G was tested via comparison (Pearson r) to commonly used pencil-and-paper based assessments: HHT-D versus the Geriatric Depression Scale (GDS) and HHT-G versus the MMSE. Good test-retest (r = 0.80; p < 0.0001) and acceptable internal consistency reliability (α= 0.73) of the HHT-D were established. Moderate support for the validity of the HHT-D was obtained (r = 0.60 between the HHT-D and GDS; p < 0.0001). Results indicated good test-retest (r = 0.87; p < 0.0001) and acceptable internal consistency reliability (α= 0.70) of the HHT-G. Validity of the HHT-G was supported (r = 0.71 between the HHT-G and MMSE; p < 0.0001). In summary, the HHT-D and HHT-G were found to be reliable and valid computerized assessments to screen for depression and cognitive status, respectively, in an elderly sample.

Risk of dementia in patients with celiac disease: a population-based cohort study. - Lebwohl, Benjamin; Luchsinger, Jose A; Freedberg, Daniel E; Green, Peter H R; Ludvigsson, Jonas F (J Alzheimers Dis, 2016)
BACKGROUND: Patients with celiac disease (CD) frequently report cognitive symptoms when they are exposed to gluten, and cognitive deficits have been quantified in patients with newly diagnosed CD. OBJECTIVE: To determine whether patients with CD have an increased risk of dementia. METHODS: Using a population-based database of older adults (age ≥50 years) with histologically proven CD (duodenal/jejunal villous atrophy) from all 28 pathology departments in Sweden, we compared the incidence of a subsequent dementia diagnosis to those of age- and gender-matched controls. RESULTS: Among patients with CD (n = 8,846) and controls (n = 43,474), the median age was 63 years and 56% were female. During a median follow-up time of 8.4 years, dementia was diagnosed in 4.3% of CD patients and 4.4% of controls (HR 1.07; 95% CI 0.95-1.20). Although there was an increased risk of dementia in the first year following a diagnosis of CD (HR 1.73; 95% CI 1.15-2.61), this risk was not present in the whole observation period. Among those subjects with a dementia subtype specified, the increased risk was restricted to vascular dementia (HR 1.28; 95% CI 1.00-1.64) and was not present for Alzheimer's dementia (HR 1.12; 95% CI 0.91-1.37). CONCLUSIONS: Patients with CD are not at increased risk for dementia overall, though subgroup analysis suggests that they may be at increased risk for vascular dementia.
Keywords: Aged; Celiac Disease; Cohort Studies; Databases, Factual; Dementia; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sweden

Searching for Primary Predictors of Conversion from Mild Cognitive Impairment to Alzheimer's Disease: A Multivariate Follow-Up Study. - López, María Eugenia; Turrero, Agustín; Cuesta, Pablo; López-Sanz, David; Bruña, Ricardo; Marcos, Alberto; Gil, Pedro; Yus, Miguel; Barabash, Ana; Cabranes, José Antonio; Maestú, Fernando; Fernández, Alberto (J Alzheimers Dis, 2016)
Recent proposals of diagnostic criteria within the healthy aging-Alzheimer's disease (AD) continuum stressed the role of biomarker information. More importantly, such information might be critical to predict those mild cognitive impairment (MCI) patients at a higher risk of conversion to AD. Usually, follow-up studies utilize a reduced number of potential markers although the conversion phenomenon may be deemed as multifactorial in essence. In addition, not only biological but also cognitive markers may play an important role. Considering this background, we investigated the role of cognitive reserve, cognitive performance in neuropsychological testing, hippocampal volumes, APOE genotype, and magnetoencephalography power sources to predict the conversion to AD in a sample of 33 MCI patients. MCIs were followed up during a 2-year period and divided into two subgroups according to their outcome: The "stable" MCI group (sMCI, 21 subjects) and the "progressive" MCI group (pMCI, 12 subjects). Baseline multifactorial information was submitted to a hierarchical logistic regression analysis to build a predictive model of conversion to AD. Results indicated that the combination of left hippocampal volume, occipital cortex theta power, and clock drawing copy subtest scores predicted conversion to AD with a 100% of sensitivity and 94.7% of specificity. According to these results it might be suggested that anatomical, cognitive, and neurophysiological markers may be considered as "first order" predictors of progression to AD, while APOE or cognitive reserve proxies might play a more secondary role.

Self-Consciousness in Patients with Behavioral Variant Frontotemporal Dementia. - Arroyo-Anlló, Eva M; Bouston, Adèle Turpin; Fargeau, Marie-Noëlle; Orgaz Baz, Begõna; Gil, Roger (J Alzheimers Dis, 2016)
Self-consciousness (SC) is multifaceted and considered to be the consciousness of one's own mental states. The medial prefrontal cortex may play a critical role in SC. The main aim of this paper was to examine SC in patients with behavioral variant frontotemporal dementia, who are characterized more by changes in personal, social, and emotional conduct and loss of insight than by cognitive disturbances. Control and patient groups of 21 subjects each, matched by age, educational level, gender, and nationality were assessed using a SC questionnaire. It measures several aspects: Personal identity, Anosognosia, Affective state, Body representation, Prospective memory, Introspection, and Moral judgments. The most disturbed ones in patients were Anosognosia, Affective state, and Moral judgments, and the least disturbed aspects were awareness of identity and of body representation. No significant correlations were found between the SC score and any clinical or demographical characteristics. The core deficiency of SC in patients was related to behavioral SC aspects, which are more dependent on orbito-frontal functioning.
Keywords: Aged; Brain; Educational Status; Female; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Psychological Tests; Self Concept

Serotonin 2A Receptor Inverse Agonist as a Treatment for Parkinson's Disease Psychosis: A Systematic Review and Meta-analysis of Serotonin 2A Receptor Negative Modulators. - Yasue, Ichiro; Matsunaga, Shinji; Kishi, Taro; Fujita, Kiyoshi; Iwata, Nakao (J Alzheimers Dis, 2016)
BACKGROUND: There is uncertainty about the efficacy and tolerability of serotonin 2A (5-HT2A) receptor negative modulators for Parkinson's disease psychosis (PDP). OBJECTIVE: This is the first meta-analysis of randomized placebo-controlled trials (RCTs) testing negative modulators of the 5-HT2A receptor as a treatment for PDP. METHODS: The primary outcome was the Scale for Assessment of Positive Symptoms (SAPS)-hallucinations (H) and -delusions (D) scores (SAPS-H+D). Other outcome measures were SAPS-H, SAPS-D, the Unified Parkinson's Disease Rating Scale Part II and III (UPDRS-II+III), discontinuation rates, and individual adverse events. RESULTS: Four RCTs were identified that met inclusion criteria, all assessing the 5-HT2A inverse agonist pimavanserin (including 417 drug-treated and 263 placebo-treated PDP patients). Pimavanserin significantly decreased SAPS-H+D scores compared to placebo [weighted mean differences (WMD) = -2.26, 95% confidence interval (95% CI) = -3.86 to -0.67, p = 0.005, I2 = 30% , N = 4 studies, n = 502 patients]. Moreover, pimavanserin was superior to placebo for reducing SAPS-H (WMD = -2.15, 95% CI = -3.45 to -0.86, p = 0.001, I2 = 0% , N = 2, n = 237) and SAPS-D scores (WMD = -1.32, 95% CI = -2.32 to -0.32, p = 0.010, I2 = 0% , N = 2, n = 237). Pimavanserin was associated with less orthostatic hypotension than placebo (risk ratio = 0.33, 95% CI = 0.15-0.75, p = 0.008, I2 = 0% , number needed to harm = 17, p = 0.01, N = 3, n = 476). There were no significant differences in rates of all-cause discontinuation, adverse events, and death, UPDRS-II+III scores, and incidences of individual adverse events (other than orthostatic hypotension) between pimavanserin and placebo groups. CONCLUSIONS: Pooled RCT results suggest that pimavanserin is beneficial for the treatment of PDP and is well tolerated. We did not identify other negative modulators of the 5-HT2A receptor for the treatment of PDP.
Keywords: Antiparkinson Agents; Humans; Parkinson Disease; Randomized Controlled Trials as Topic; Receptor, Serotonin, 5-HT2A; Serotonin 5-HT2 Receptor Agonists

Serum Uric Acid and Its Association with Longitudinal Cognitive Change Among Urban Adults. - Beydoun, May A; Canas, Jose-Atilio; Dore, Gregory A; Beydoun, Hind A; Rostant, Ola S; Fanelli-Kuczmarski, Marie T; Evans, Michele K; Zonderman, Alan B (J Alzheimers Dis, 2016)
Uric acid, a waste metabolite among humans, was linked to various cognitive outcomes. We describe sex and age-group specific associations of baseline serum uric acid (SUAbase) and significant change in SUA (ΔSUA: 1 versus 0 = decrease versus no change; 2 versus 0 = increase versus no change) with longitudinal annual rate of cognitive change among a large sample of urban adults. Data from the Healthy Aging in Neighborhoods of Diversity across the Life Span study, 2004-2009 (visit 1) and 2009-2013 (visit 2) were used. Of 3,720 adults selected at baseline (age range: 30-64 y), complete data were available for N = 1,487-1,602 with a mean repeat of 1.5-1.7 visits/participant. Cognitive test domains spanned attention, processing speed, learning/memory, executive function, visuo-spatial/visuo-construction ability, language/verbal, and global cognitive function. SUA was measured at both visits. Multiple mixed-effects regression analyses were conducted. In the total population, a higher SUAbase was associated with a faster annual rate of decline on a measure of visual memory/visuo-construction ability (the Benton Visual Retention Test) by γ= 0.07 with a standard error of 0.02, p < 0.001. Among older men, a significant increase in SUA was associated with slower decline on a test of attention/processing speed, namely Trailmaking test, Part A, measured in seconds to completion (γ= -6.91 ± 1.73, p < 0.001). In sum, a higher SUAbase was associated with faster cognitive decline over-time in a visual memory/visuo-construction ability test. ΔSUA had particular beneficial effects of an increasing ΔSUA on the domain of attention/processing speed among older men. More longitudinal studies are needed to examine cognitive domain-specific effects of over-time change in SUA within sex and age groups.

Severe Brain Metabolic Decreases Associated with REM Sleep Behavior Disorder in Dementia with Lewy Bodies. - Iaccarino, Leonardo; Marelli, Sara; Iannaccone, Sandro; Magnani, Giuseppe; Ferini-Strambi, Luigi; Perani, Daniela (J Alzheimers Dis, 2016)
BACKGROUND/OBJECTIVE: To evaluate the prevalence of REM sleep behavior disorder (RBD) in a sample of Dementia with Lewy Bodies (DLB) and Alzheimer's Disease (AD) patients and compare the patterns of brain glucose metabolism in DLB patients with or without the sleep disturbances. METHODS: In this retrospective study, the presence of probable RBD was ascertained for 27 clinically diagnosed DLB patients and 11 AD patients by a self-administered RBD Single-Question Screen (RBD1Q), followed by a sleep structured interview by experts in sleep disorders blinded to clinical information. For 18F-FDG-PET metabolic comparisons, we considered an additional 13 DLB patients with negative history for sleep disturbance. We performed DLB within-group comparisons covarying for age and disease duration. RESULTS: The RBD1Q questionnaire identified 20 out of 27 DLB RBD+ and 7 out of 27 DLB RBD-. None of the AD patients was positive to RBD1Q test. 18F-FDG-PET hypometabolism at the single- and group-level tested by means of an optimized SPM approach revealed the typical DLB metabolic pattern. Each DLB patient showed a predominant occipital hypometabolism. The SPM voxel-based comparisons revealed significant brain metabolic differences, namely a more severe metabolic decrease in DLB RBD+ in the dorsolateral and medial frontal regions, left precuneus, bilateral superior parietal lobule and rolandic operculum, and amygdala. DISCUSSION: We found a high prevalence of RBD in DLB and none in AD, as identified by the RBD1Q questionnaire, indicating its utility in clinical practice. DLB patients with or without RBD show different hypometabolism patterns that might reflect differences in underlying pathology.

Short-Term Effects of Rhythmic Sensory Stimulation in Alzheimer's Disease: An Exploratory Pilot Study. - Clements-Cortes, Amy; Ahonen, Heidi; Evans, Michael; Freedman, Morris; Bartel, Lee (J Alzheimers Dis, 2016)
This study assessed the effect of stimulating the somatosensory system of Alzheimer's disease (AD) patients at three stages of their illness with 40 Hz sound. In this AB cross-over study design, 18 participants (6 mild, 6 moderate, 6 severe) each participated in 13 sessions: one intake and 12 treatment. Treatment A consisted of 40 Hz sound stimulation and Treatment B consisted of visual stimulation using DVDs, each provided twice a week over 6 weeks for a total of 6 times per treatment. Outcome measures included: St. Louis University Mental Status Test (SLUMS), Observed Emotion Rating Scale, and behavioral observation by the researcher. Data were submitted to regression analysis for the series of 6 SLUMS scores in treatment A and 6 scores in B with comparison by group. The slopes for the full sample and subgroups in the 40 Hz treatment were all significant beyond alpha = 0.05, while those for the DVD were not. A thematic analysis of qualitative observations supported the statistical findings. 40 Hz treatment appeared to have the strongest impact on persons with mild and moderate AD. Results are promising in terms of a potential new treatment for persons with AD, and further research is needed.

Sideritis spp. Extracts Enhance Memory and Learning in Alzheimer's β-Amyloidosis Mouse Models and Aged C57Bl/6 Mice. - Hofrichter, Jacqueline; Krohn, Markus; Schumacher, Toni; Lange, Cathleen; Feistel, Bjöorn; Walbroel, Bernd; Pahnke, Jens (J Alzheimers Dis, 2016)
Nowadays, Alzheimer's disease is the most prevalent epiphenomenon of the aging population. Although soluble amyloid-β (Aβ) species (monomers, oligomers) are recognized triggers of the disease, no therapeutic approach is able to stop it. Herbal medicines are used to treat different diseases in many regions of the world. On the Balkan Peninsula, at the eastern Mediterranean Sea, and adjacent regions, Sideritis species are used as traditional medicine to prevent age-related problems in elderly. To evaluate this traditional knowledge in controlled experiments, we tested extracts of two commonly used Sideritis species, Sideritis euboea and Sideritis scardica, with regard to their effects on cognition in APP-transgenic and aged, non-transgenic C57Bl/6 mice. Additionally, histomorphological and biochemical changes associated with Aβ deposition and treatment were assessed. We found that daily oral treatment with Sideritis spp. extracts highly enhanced cognition in aged, non-transgenic as well as in APP-transgenic mice, an effect that was even more pronounced when extracts of both species were applied in combination. The treatment strongly reduced Aβ42 load in APP-transgenic mice, accompanied by increased phagocytic activity of microglia, and increased expression of the α-secretase ADAM10. Moreover, the treatment was able to fully rescue neuronal loss of APP-transgenic mice to normal levels as seen in non-transgenic controls. Having the traditional knowledge in mind, our results imply that treatment with Sideritis spp. extracts might be a potent, well-tolerated option for treating symptoms of cognitive impairment in elderly and with regard to Alzheimer's disease by affecting its most prominent hallmarks: Aβ pathology and cognitive decline.

Sirtuin 2 Inhibition Improves Cognitive Performance and Acts on Amyloid-β Protein Precursor Processing in Two Alzheimer's Disease Mouse Models. - Biella, Gloria; Fusco, Federica; Nardo, Emanuele; Bernocchi, Ottavia; Colombo, Alessio; Lichtenthaler, Stefan F; Forloni, Gianluigi; Albani, Diego (J Alzheimers Dis, 2016)
The neuropathological hallmarks of Alzheimer's disease (AD) are extracellular plaques built up by the accumulation of the amyloid-β protein precursor (AβPP)-derived peptide β (Aβ), and intracellular tangles of hyperphosphorylated tau protein. Sirtuin 2 (SIRT2) is a member of the sirtuin family, featuring conserved enzymes with deacetylase activity and involved in several cell molecular pathways. We investigated the importance of SIRT2 inhibition in AD. We inhibited SIRT2 by small molecules (AGK-2, AK-7) and examined AβPP metabolism in H4-SW neuroglioma cells overexpressing AβPP and two AD transgenic mouse models (3xTg-AD and APP23). The in vitro studies suggested that the inhibition of SIRT2 reduced Aβ production; in vivo data showed an improvement of cognitive performance in the novel object recognition test, and an effect on AβPP proteolytic processing leading to a reduction of soluble β-AβPP and an increase of soluble α-AβPP protein. In 3xTg-AD mice, we noticed that total tau protein level rose. Overall, our pre-clinical data support a role for SIRT2 inhibition in the improvement of cognitive performance and the modulation of molecular mechanisms relevant for AD, thus deserving attention as possible therapeutic strategy.

So Close Yet So Far: Executive Contribution to Memory Processing in Behavioral Variant Frontotemporal Dementia. - Bertoux, Maxime; Ramanan, Siddharth; Slachevsky, Andrea; Wong, Stephanie; Henriquez, Fernando; Musa, Gada; Delgado, Carolina; Flanagan, Emma; Bottlaender, Michel; Sarazin, Marie; Hornberger, Michael; Dubois, Bruno (J Alzheimers Dis, 2016)
BACKGROUND: Memory impairment in behavioral variant frontotemporal dementia (bvFTD) is traditionally considered to be mild and attributed to prefrontal cortex dysfunction. Recent studies, however, indicated that some patients can present with a memory impairment of the hippocampal type, showing storage and consolidation deficits in addition to the more executive/prefrontal related encoding and strategic difficulties. OBJECTIVE: This study aimed to study the relationship between executive functions (EF) and memory processes in bvFTD via a data-driven approach. METHOD: Participants consisted of 71 bvFTD (among which 60.6% had a lumbar puncture showing non-Alzheimer biomarker profile) and 60 controls (among which 45% had amyloid imaging showing a normal profile). EF were assessed by the Frontal Assessment Battery, semantic/lexical verbal fluency tests, and forward/backward digit spans. Patients were split into amnestic (n = 33) and non-amnestic (n = 38) subgroups based on normative data (total recall score) from the Free and Cued Selective Reminding Test (FCSRT). Relationships between FCSRT subscores and EF measures were explored through hierarchical clustering analysis, partial correlation analysis with an EF component, and automated linear modeling. RESULTS: Convergent findings across the statistical approaches show that, overall, memory performance was independent from EF in bvFTD whereas the relationship was stronger in controls. Indeed, in bvFTD, memory performance did not cluster with EF, was not correlated with the EF component, and was only partially (4% - 12.7%) predicted by EF. DISCUSSION: These findings show that executive dysfunctions cannot solely explain the memory deficits occurring in bvFTD. Indeed, some patients present with a genuine amnesia affecting storage and consolidation abilities, which are independent from executive dysfunctions. On the clinical level, this study highlights the importance of revising the neuropsychological diagnosis criteria for bvFTD.

Spatial Navigation in Preclinical Alzheimer's Disease. - Allison, Samantha L; Fagan, Anne M; Morris, John C; Head, Denise (J Alzheimers Dis, 2016)
Although several previous studies have demonstrated navigational deficits in early-stage symptomatic Alzheimer's disease (AD), navigational abilities in preclinical AD have not been examined. The present investigation examined the effects of preclinical AD and early-stage symptomatic AD on spatial navigation performance. Performance on tasks of wayfinding and route learning in a virtual reality environment were examined. Comparisons were made across the following three groups: Clinically normal without preclinical AD (n = 42), clinically normal with preclinical AD (n = 13), and early-stage symptomatic AD (n = 16) groups. Preclinical AD was defined based on cerebrospinal fluid Aβ42 levels below 500 pg/ml. Preclinical AD was associated with deficits in the use of a wayfinding strategy, but not a route learning strategy. Moreover, post-hoc analyses indicated that wayfinding performance had moderate sensitivity and specificity. Results also confirmed early-stage symptomatic AD-related deficits in the use of both wayfinding and route learning strategies. The results of this study suggest that aspects of spatial navigation may be particularly sensitive at detecting the earliest cognitive deficits of AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Educational Status; Female; Humans; Learning; Male; Neuropsychological Tests; Prodromal Symptoms; Psychomotor Performance; ROC Curve; Spatial Navigation; tau Proteins; User-Computer Interface

Specific Features of Subjective Cognitive Decline Predict Faster Conversion to Mild Cognitive Impairment. - Fernández-Blázquez, Miguel A; Ávila-Villanueva, Marina; Maestú, Fernando; Medina, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a silent disorder that needs the earliest possible intervention in order to reduce its high economic and social impact. It has been recently suggested that subjective cognitive decline (SCD) appears at preclinical stages many years before the onset of AD. Therefore, SCD could become an ideal target for early therapeutic intervention. OBJECTIVE: The goal of this study was to evaluate the clinical significance of SCD on the conversion from a cognitively healthy stage to a mild cognitive impairment (MCI) in one-year follow-up. METHODS: A total of 608 cognitively intact individuals from the Vallecas Project's cohort, a community-based prospective study to identify early markers of AD, were enrolled in this study. Participants were classified in three groups: i) No Complaints (NCg), ii) Subjects with complaints in one or more cognitive domains (SCDg), and iii) Subjects who, besides complaints, fulfilled the features of SCD Plus proposed by the International Working Group of SCD (SCD-Pg). RESULTS: Individuals were followed up for a mean of 13.1 months (range 10.7-22.4). During this time, 41 volunteers developed MCI (6.7% of total sample). The conversion rate for SCD-Pg (18.9%) was significantly higher than SCDg (5.6%) and NCg (4.9%). CONCLUSION: Specific features associated with SCD may help to identify individuals at high risk of fast conversion to MCI. These results highlight the importance of a close follow-up of subjects with SCD-P and include them in early intervention programs because of their increased risk for the development of MCI.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Genotyping Techniques; Humans; Kaplan-Meier Estimate; Male; Neuropsychological Tests; Perception; Prodromal Symptoms; Prognosis; Prospective Studies; Time Factors

Specific Triazine Herbicides Induce Amyloid-β42 Production. - Portelius, Erik; Durieu, Emilie; Bodin, Marion; Cam, Morgane; Pannee, Josef; Leuxe, Charlotte; Mabondzo, Aloϊse; Oumata, Nassima; Galons, Hervé; Lee, Jung Yeol; Chang, Young-Tae; Stϋber, Kathrin; et al. (J Alzheimers Dis, 2016)
Proteolytic cleavage of the amyloid-β protein precursor (AβPP) by secretases leads to extracellular release of amyloid-β (Aβ) peptides. Increased production of Aβ42 over Aβ40 and aggregation into oligomers and plaques constitute an Alzheimer's disease (AD) hallmark. Identifying products of the 'human chemical exposome' (HCE) able to induce Aβ42 production may be a key to understanding some of the initiating causes of AD and to generate non-genetic, chemically-induced AD animal models. A cell model was used to screen HCE libraries for Aβ42 inducers. Out of 3500+ compounds, six triazine herbicides were found that induced a β- and γ-secretases-dependent, 2-10 fold increase in the production of extracellular Aβ42 in various cell lines, primary neuronal cells, and neurons differentiated from human-induced pluripotent stem cells (iPSCs). Immunoprecipitation/mass spectrometry analyses show enhanced production of Aβ peptides cleaved at positions 42/43, and reduced production of peptides cleaved at positions 38 and lower, a characteristic of AD. Neurons derived from iPSCs obtained from a familial AD (FAD) patient (AβPP K724N) produced more Aβ42 versus Aβ40 than neurons derived from healthy controls iPSCs (AβPP WT). Triazines enhanced Aβ42 production in both control and AD iPSCs-derived neurons. Triazines also shifted the cleavage pattern of alcadeinα, another γ-secretase substrate, suggesting a direct effect of triazines on γ-secretase activity. In conclusion, several widely used triazines enhance the production of toxic, aggregation prone Aβ42/Aβ43 amyloids, suggesting the possible existence of environmental "Alzheimerogens" which may contribute to the initiation and propagation of the amyloidogenic process in late-onset AD.

Standardized Uptake Value Ratio-Independent Evaluation of Brain Amyloidosis. - Chincarini, Andrea; Sensi, Francesco; Rei, Luca; Bossert, Irene; Morbelli, Silvia; Guerra, Ugo Paolo; Frisoni, Giovanni; Padovani, Alessandro; Nobili, Flavio (J Alzheimers Dis, 2016)
The assessment of in vivo18F images targeting amyloid deposition is currently carried on by visual rating with an optional quantification based on standardized uptake value ratio (SUVr) measurements. We target the difficulties of image reading and possible shortcomings of the SUVr methods by validating a new semi-quantitative approach named ELBA. ELBA involves a minimal image preprocessing and does not rely on small, specific regions of interest (ROIs). It evaluates the whole brain and delivers a geometrical/intensity score to be used for ranking and dichotomic assessment. The method was applied to adniimages 18F-florbetapir images from the ADNI database. Five expert readers provided visual assessment in blind and open sessions. The longitudinal trend and the comparison to SUVr measurements were also evaluated. ELBA performed with area under the roc curve (AUC) = 0.997 versus the visual assessment. The score was significantly correlated to the SUVr values (r = 0.86, p < 10-4). The longitudinal analysis estimated a test/retest error of ≃2.3%. Cohort and longitudinal analysis suggests that the ELBA method accurately ranks the brain amyloid burden. The expert readers confirmed its relevance in aiding the visual assessment in a significant number (85) of difficult cases. Despite the good performance, poor and uneven image quality constitutes the major limitation.

Strong Impact of Chronic Cerebral Hypoperfusion on Neurovascular Unit, Cerebrovascular Remodeling, and Neurovascular Trophic Coupling in Alzheimer's Disease Model Mouse. - Shang, Jingwei; Yamashita, Toru; Zhai, Yun; Nakano, Yumiko; Morihara, Ryuta; Fukui, Yusuke; Hishikawa, Nozomi; Ohta, Yasuyuki; Abe, Koji (J Alzheimers Dis, 2016)
Although chronic cerebral hypoperfusion (CCH) may affect Alzheimer's disease (AD) pathogenesis, the mechanism remains elusive. In the present study, we investigated the role of CCH on an AD mouse model in neurovascular unit, cerebrovascular remodeling, and neurovascular trophic coupling. Moreover, examined protective effect of galantamine. Alzheimer's disease transgenic mice (APP23) were subjected to bilateral common carotid arteries stenosis with ameroid constrictors for slowly progressive cerebral hypoperfusion. CCH exacerbated neuronal loss and decrease of α7 subunit of nicotinic acetylcholine receptors (α7-nAChRs) expression in hippocampus and thalamus at 12 months. Meanwhile, CCH greatly induced advanced glycation end products expression, and blood-brain barrier leakage through observing IgG and MMP9 expressions. Furthermore, a significant number of dramatic enlarged cerebral vessels with remodeling, BDNF/TrkB decreased in neurovascular trophic coupling. The present study demonstrated that CCH strongly enhanced primary AD pathology including neurodegeneration, neurovascular unit disruption, cerebrovascular remodeling and neurovascular trophic coupling damage in AD mice, and that galantamine treatment greatly ameliorated such neuropathologic abnormalities.

A Systematic Review and Meta-Analysis of On-Road Simulator and Cognitive Driving Assessment in Alzheimer's Disease and Mild Cognitive Impairment. - Hird, Megan A; Egeto, Peter; Fischer, Corinne E; Naglie, Gary; Schweizer, Tom A (J Alzheimers Dis, 2016)
BACKGROUND: Many individuals with Alzheimer's disease (AD) and mild cognitive impairment (MCI) are at an increased risk of driving impairment. There is a need for tools with sufficient validity to help clinicians assess driving ability. OBJECTIVE: Provide a systematic review and meta-analysis of the primary driving assessment methods (on-road, cognitive, driving simulation assessments) in patients with MCI and AD. METHODS: We investigated (1) the predictive utility of cognitive tests and domains, and (2) the areas and degree of driving impairment in patients with MCI and AD. Effect sizes were derived and analyzed in a random effects model. RESULTS: Thirty-two articles (including 1,293 AD patients, 92 MCI patients, 2,040 healthy older controls) met inclusion criteria. Driving outcomes included: On-road test scores, pass/fail classifications, errors; caregiver reports; real world crash involvement; and driving simulator collisions/risky behavior. Executive function (ES [95% CI]; 0.61 [0.41, 0.81]), attention (0.55 [0.33, 0.77]), visuospatial function (0.50 [0.34, 0.65]), and global cognition (0.61 [0.39, 0.83]) emerged as significant predictors of driving performance. Trail Making Test Part B (TMT-B, 0.61 [0.28, 0.94]), TMT-A (0.65 [0.08, 1.21]), and Maze test (0.88 [0.60, 1.15]) emerged as the best single predictors of driving performance. Patients with very mild AD (CDR = 0.5) mild AD (CDR = 1) were more likely to fail an on-road test than healthy control drivers (CDR = 0), with failure rates of 13.6%, 33.3% and 1.6%, respectively. CONCLUSION: The driving ability of patients with MCI and AD appears to be related to degree of cognitive impairment. Across studies, there are inconsistent cognitive predictors and reported driving outcomes in MCI and AD patients. Future large-scale studies should investigate the driving performance and associated neural networks of subgroups of AD (very mild, mild, moderate) and MCI (amnestic, non-amnestic, single-domain, multiple-domain).

A TgCRND8 Mouse Model of Alzheimer's Disease Exhibits Sexual Dimorphisms in Behavioral Indices of Cognitive Reserve. - Granger, Matthew W; Franko, Bettina; Taylor, Matthew W; Messier, Claude; George-Hyslop, Peter St; Bennett, Steffany A L (J Alzheimers Dis, 2016)
Cognitive decline is sexually dimorphic in Alzheimer's disease (AD). Men show higher incidences of amnestic mild cognitive impairment yet women disproportionally phenoconvert to AD. It is hypothesized that men maintain greater cognitive reserve than women under comparable amyloid-β (Aβ) challenge. One behavioral aspect of cognitive reserve in mice is the capacity to cope with Aβ-associated stereotypies by switching to increasingly effective navigational search strategies in the Morris water maze. To explore inherent sex differences in this paradigm, however, we require an AβPP mouse model wherein behavioral flexibility is impaired earlier in females than males despite equivalent Aβ load. Here, we show that when F1 C57Bl/6×C3H/HeJ TgCRND8 mice are placed on C57Bl/6 background, N5 Tg males and females exhibit equivalent Aβ pathologies at 2, 4, 6, and 8 months of age yet females display learning and memory deficits earlier than males. We further show that this N5 line does not carry the autosomal recessive pde6brd1 mutation that impairs visual acuity and that the estrous cycle is not disrupted on this genetic background. At 5.5 months of age, Tg males, but not females, compensate for Aβ-associated stereotypic behaviors (i.e., hyperactive tight circling) by alternating navigational search strategies and adopting increasingly productive spatial search strategies. Females fail to overcome Aβ-associated stereotypies and do not efficiently switch from systematic to spatial learning strategies. Together, these data identify a novel AβPP mouse model that can be used for preclinical testing of interventions targeting sexual dimorphisms in behavioral indices of cognitive reserve.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognitive Reserve; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid; Psychomotor Performance; Sex Characteristics; Spatial Memory; Spatial Navigation; Survival Analysis

Thyroid-Stimulating Hormone and Mild Cognitive Impairment: Results of the Heinz Nixdorf Recall Study. - Winkler, Angela; Weimar, Christian; Jöckel, Karl-Heinz; Erbel, Raimund; Dragano, Nico; Broecker-Preuss, Martina; Moebus, Susanne; Führer-Sakel, Dagmar; Dlugaj, Martha (J Alzheimers Dis, 2016)
BACKGROUND: Although some studies reported on the association of serum thyroid-stimulating hormone (TSH) concentration and cognition, only one population-based study investigated the association of TSH concentration and mild cognitive impairment (MCI). OBJECTIVE: To investigate the gender-specific association of low- and high-normal TSH concentrations with MCI in euthyroid participants. METHODS: Analysis sample 1 included 2,563 euthyroid participants (aged 50-80 years) from the second examination of the population-based Heinz Nixdorf Recall study. Gender-specific TSH quintiles (Q1 low, Q2-Q4 middle, Q5 high TSH concentration) were determined and group comparisons of age- and education-adjusted mean scores were performed for all cognitive subtests. Analysis sample 2 included 378 participants with MCI and 931 cognitively normal participants. MCI was diagnosed according to previously published MCI criteria. Multivariate logistic regression models were performed using TSH quintiles (Q2-Q4 as reference) to assess the association of low- and high-normal TSH concentration with MCI. Models were performed unadjusted and adjusted for sociodemographic and cardiovascular risk factors. RESULTS: Group comparisons showed significant differences only in the immediate recall of the verbal memory task in women. Only women showed a strong association of high-normal TSH concentration with MCI (unadjusted: odds ratio 2.09, 95% confidence interval 1.29-3.37, full adjusted: 1.86, 1.06-3.27). There was no association with low-normal TSH concentration in women and no association of either low- or high-normal TSH concentration with MCI in men. CONCLUSIONS: These results suggest that women with high-normal TSH concentration might be at higher risk of cognitive decline. This needs to be confirmed in the longitudinal analysis.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Case-Control Studies; Cognitive Dysfunction; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Risk Factors; Sex Characteristics; Statistics, Nonparametric; Thyrotropin

Towards a Pathway Inventory of the Human Brain for Modeling Disease Mechanisms Underlying Neurodegeneration. - Iyappan, Anandhi; Gündel, Michaela; Shahid, Mohammad; Wang, Jiali; Li, Hui; Mevissen, Heinz-Theodor; Müller, Bernd; Fluck, Juliane; Jirsa, Viktor; Domide, Lia; Younesi, Erfan; Hofmann-Apitius, Martin (J Alzheimers Dis, 2016)
Molecular signaling pathways have been long used to demonstrate interactions among upstream causal molecules and downstream biological effects. They show the signal flow between cell compartments, the majority of which are represented as cartoons. These are often drawn manually by scanning through the literature, which is time-consuming, static, and non-interoperable. Moreover, these pathways are often devoid of context (condition and tissue) and biased toward certain disease conditions. Mining the scientific literature creates new possibilities to retrieve pathway information at higher contextual resolution and specificity. To address this challenge, we have created a pathway terminology system by combining signaling pathways and biological events to ensure a broad coverage of the entire pathway knowledge domain. This terminology was applied to mining biomedical papers and patents about neurodegenerative diseases with focus on Alzheimer's disease. We demonstrate the power of our approach by mapping literature-derived signaling pathways onto their corresponding anatomical regions in the human brain under healthy and Alzheimer's disease states. We demonstrate how this knowledge resource can be used to identify a putative mechanism explaining the mode-of-action of the approved drug Rasagiline, and show how this resource can be used for fingerprinting patents to support the discovery of pathway knowledge for Alzheimer's disease. Finally, we propose that based on next-generation cause-and-effect pathway models, a dedicated inventory of computer-processable pathway models specific to neurodegenerative diseases can be established, which hopefully accelerates context-specific enrichment analysis of experimental data with higher resolution and richer annotations.

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

Usefulness of an Integrated Analysis of Different Memory Tasks to Predict the Progression from Mild Cognitive Impairment to Alzheimer's Disease: The Episodic Memory Score (EMS). - Marra, Camillo; Gainotti, Guido; Fadda, Lucia; Perri, Roberta; Lacidogna, Giordano; Scaricamazza, Eugenia; Piccininni, Chiara; Quaranta, Davide (J Alzheimers Dis, 2016)
Taking into the account both the severity and the consistency of performances obtained on memory tests by patients with amnestic mild cognitive impairment (aMCI) could improve the power to predict their progression to Alzheimer's disease. For this purpose, we constructed the Episodic Memory Score (EMS), which is obtained by subdividing in tertiles performances obtained at baseline in verbal (RAVLT) and visual episodic memory (Rey-Osterrieth Figure-delayed recall) and giving a score ranging from 1 (worst result) to 3 (best result) to results falling within each tertile. The EMS was computed for each patient by summing the tertile score obtained on each memory task, so that the total score ranged from 4 (worst performance) to 12 (best performance). The aMCI sample consisted of 198 subjects who completed the two-year follow-up, at the end of which 55 subjects had converted to dementia. The mean EMS score obtained by aMCI converters was significantly lower than that of aMCI-stable patients. In detecting conversion to dementia, the comparison between EMS and individual memory scores obtained at baseline was made by computing ROC curves, and estimating the respective area under the curve (AUC). The EMS had a larger AUC than the individual memory scores. At baseline aMCI converters performed worse than non-converters not only on memory tasks, but also on executive functions tasks. However, in a multiple variables logistic regression analysis in which all scores showing statistically significant differences between aMCI-converters and aMCI-stable were entered, the EMS was the only reliable predictor of progression from aMCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Memory, Episodic; Mental Recall; Neuropsychological Tests; ROC Curve

Validation of Immunoassay-Based Tools for the Comprehensive Quantification of Aβ40 and Aβ42 Peptides in Plasma. - Pérez-Grijalba, Virginia; Fandos, Noelia; Canudas, Jesús; Insua, Daniel; Casabona, Diego; Lacosta, Ana M; Montañés, María; Pesini, Pedro; Sarasa, Manuel (J Alzheimers Dis, 2016)
Recent advances in neuroimaging and cerebrospinal fluid (CSF) biomarker assays have provided evidence of a long preclinical stage of Alzheimer's disease (AD). This period is being increasingly targeted for secondary prevention trials of new therapies. In this context, the interest of a noninvasive, cost-effective amyloid-β (Aβ) blood-based test does not need to be overstated. Nevertheless, a thorough validation of these bioanalytical methods should be performed as a prerequisite for confident interpretation of clinical results. The aim of this study was to validate ELISA sandwich colorimetric ABtest40 and ABtest42 for the quantification of Aβ40 and Aβ42 in human plasma. The validation parameters assessed included precision, accuracy, sensitivity, specificity, recovery, and dilution linearity. ABtest40 and ABtest42 proved to be specific for their target peptide using Aβ peptides with sequence similar to the target. Mean relative error in the quantification was found to be below 7.5% for both assays, with high intra-assay, inter-assay, and inter-batch precision (CV <9.0% on average). Sensitivity was assessed by determination of the limit of quantification fulfilling precision and accuracy criteria; it was established at 7.60 pg/ml and 3.60 pg/ml for ABtest40 and ABtest42, respectively. Plasma dilution linearity was demonstrated in PBS; however, dilution in a proprietary formulated buffer significantly increased the recovery of both Aβ40 and Aβ42 masked by matrix interactions, allowing a more comprehensive assessment of the free and total peptide levels in the plasma. In conclusion, both assays were successfully validated as tools for the quantification Aβ40 and Aβ42 in plasma.

Validation of microRNAs in Cerebrospinal Fluid as Biomarkers for Different Forms of Dementia in a Multicenter Study. - Müller, Mareike; Kuiperij, H Bea; Versleijen, Alexandra A M; Chiasserini, Davide; Farotti, Lucia; Baschieri, Francesca; Parnetti, Lucilla; Struyfs, Hanne; De Roeck, Naomi; Luyckx, Jill; Engelborghs, Sebastiaan; Claassen, Jurgen A; et al. (J Alzheimers Dis, 2016)
MicroRNAs (miRNAs) regulate translational inhibition of proteins, but are also detected in body fluids, including cerebrospinal fluid (CSF), where they may serve as disease-specific biomarkers. Previously, we showed differential expression of miR-146a, miR-29a, and miR-125b in the CSF of Alzheimer's disease (AD) patients versus controls. In this study, we aim to confirm these findings by using larger, independent sample cohorts of AD patients and controls from three different centers. Furthermore, we aim to identify confounding factors that possibly arise using such a multicenter approach. The study was extended by including patients diagnosed with mild cognitive impairment due to AD, frontotemporal dementia and dementia with Lewy bodies. Previous results of decreased miR-146a levels in AD patients compared to controls were confirmed in one center. When samples from all three centers were combined, several confounding factors were identified. After controlling for these factors, we did not identify differences in miRNA levels between the different groups. However, we provide suggestions to circumvent various pitfalls when measuring miRNAs in CSF to improve future studies.

Validation of the Spanish version of the Baylor Profound Mental Status Examination. - Salmerón, Sergio; Huedo, Isabel; López-Utiel, Melisa; Soler-Moratalla, Isabel; Flores-Ruano, Teresa; Fernández-Sánchez, Miguel; Noguerón, Alicia; Doody, Rachelle S; Abizanda, Pedro (J Alzheimers Dis, 2016)
BACKGROUND: There are no short valid instruments to evaluate cognitive status in severe Alzheimer's disease (AD) patients in the Spanish language. OBJECTIVE: To validate the Spanish version of the Baylor Profound Mental Status Examination (BPMSE-Sp). METHODS: The Baylor Profound Mental Status Examination (BPMSE) was translated to Spanish and back translated. Validation was conducted in 100 patients with severe probable AD with a Mini-Mental State Examination (MMSE) <12. We assessed internal consistency (Cronbach's alpha), concurrent validity (Pearson's correlations) with the MMSE, Severe Impairment Battery (SIB), Neuropsychiatric Inventory Short Form (NPI-Q) and the Functional Assessment Staging and reliability. RESULTS: The mean age of patients was 84.9; 74% were female; 64% were institutionalized. The mean MMSE was 5.6; the mean BPMSE-Sp was 13.6; the mean BPMSE-Sp behavior was 1.2; the mean SIB was 42.2; and the mean NPI-Q was 4.7. BPMSE-Sp presented good internal consistency (Cronbach α= 0.84). There were significant correlations between the BPMSE-Sp and MMSE (r = 0.86, p <  0.001), and between the BPMSE-Sp and SIB (r = 0.92, p <  0.001). Inter-rater and test-retest reliability were in both cases excellent, ranging between 0.96 and 0.99 (p <  0.001). BPMSE-Sp had fewer floor and ceiling effects than the MMSE. CONCLUSIONS: The BPMSE-Sp is a valid tool for use in daily practice and research in the evaluation of cognitive function of patients with severe AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognition Disorders; Female; Humans; Language; Male; Mental Status Schedule; Neuropsychological Tests; Reproducibility of Results; Severity of Illness Index; Spain

Vascular Risk Factors and Cognition in Parkinson's Disease. - Pilotto, Andrea; Turrone, Rosanna; Liepelt-Scarfone, Inga; Bianchi, Marta; Poli, Loris; Borroni, Barbara; Alberici, Antonella; Premi, Enrico; Formenti, Anna; Bigni, Barbara; Cosseddu, Maura; Cottini, Elisabetta; et al. (J Alzheimers Dis, 2016)
Vascular risk factors have been associated with cognitive deficits and incident dementia in the general population, but their role on cognitive dysfunction in Parkinson's disease (PD) is still unclear. The present study addresses the single and cumulative effect of vascular risk factors on cognition in PD patients, taking clinical confounders into account. Standardized neuropsychological assessment was performed in 238 consecutive PD patients. We evaluated the association of single and cumulative vascular risk factors (smoking, diabetes, hypercholesterolemia, hypertension, and heart disease), with the diagnosis of PD normal cognition (PDNC, n = 94), mild cognitive impairment (PD-MCI, n = 111), and dementia (PDD, n = 33). The association between single neuropsychological tests and vascular risk factors was evaluated with covariance analyses adjusted for age at onset, educational levels, gender, disease duration, and motor performance. Age, educational levels, disease duration, and motor function were significantly different between PDNC, PD-MCI, and PDD. Heart disease was the only vascular factor significantly more prevalent in PDD compared with PDNC in adjusted analyses. Performance of tests assessing executive and attention functions were significantly worse in patients with hypertension, heart disease, and/or diabetes (p <  0.05). Heart disease is associated with dementia in PD, suggesting a potential window of intervention. Vascular risk factors act especially on attention and executive functions in PD. Vascular risk stratification may be useful in order to identify PD patients with a greater risk of developing dementia. These findings need to be verified in longitudinal studies.
Keywords: Age of Onset; Aged; Attention; Disability Evaluation; Educational Status; Executive Function; Female; Humans; Male; Motor Activity; Neuropsychological Tests; Parkinson Disease; Prevalence; Risk Factors; Sex Factors; Time Factors; Vascular Diseases

Vitamin D, Cognition and Alzheimer's Disease: The Therapeutic Benefit is in the D-Tails. - Landel, Véréna; Annweiler, Cedric; Millet, Pascal; Morello, Maria; Féron, François (J Alzheimers Dis, 2016)
Since its discovery during the epidemic of rickets in the early 1920s, the physiological effects of vitamin D on calcium/phosphorus homeostasis have been thoroughly studied. Along with the understanding of its actions on skeletal diseases and advances in cellular and molecular biology, this misnamed vitamin has gained attention as a potential player in a growing number of physiological processes and a variety of diseases. During the last 25 years, vitamin D has emerged as a serious candidate in nervous system development and function and a therapeutic tool in a number of neurological pathologies. More recently, experimental and pre-clinical data suggest a link between vitamin D status and cognitive function. Human studies strongly support a correlation between low levels of circulating 25-hydroxyvitamin D (25(OH)D) and cognitive impairment or dementia in aging populations. In parallel, animal studies show that supplementation with vitamin D is protective against biological processes associated with Alzheimer's disease (AD) and enhances learning and memory performance in various animal models of aging and AD. These experimental observations support multiple mechanisms by which vitamin D can act against neurodegenerative processes. However, clinical interventional studies are disappointing and fail to associate increased 25(OH)D levels with improved cognitive outcomes. This review collects the current available data from both animal and human studies and discusses the considerations that future studies examining the effects of vitamin D status on neurocognitive function might consider.

Volumetric and shape analysis of the thalamus and striatum in amnestic mild cognitive impairment. - Leh, Sandra E; Kälin, Andrea M; Schroeder, Clemens; Park, Min Tae M; Chakravarty, M Mallar; Freund, Patrick; Gietl, Anton F; Riese, Florian; Kollias, Spyros; Hock, Christoph; Michels, Lars (J Alzheimers Dis, 2016)
Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and shape analysis, which we believe to be complimentary to volumetric measures. We were able to replicate "classical" cortical thickness alterations in aMCI in the hippocampus, amygdala, putamen, insula, and inferior temporal regions. Additionally, aMCI showed significant thalamic and striatal shape differences. We observed higher global amyloid deposition in aMCI, a significant correlation between striatal displacement and global amyloid, and an inverse correlation between executive function and right-hemispheric thalamic displacement. In contrast, no volumetric differences were detected in thalamic, striatal, and hippocampal regions. Our results provide new evidence for early subcortical neuroanatomical changes in patients with aMCI, which are linked to cognitive abilities and amyloid deposition. Hence, shape analysis may aid in the identification of structural biomarkers for identifying individuals at highest risk of conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Corpus Striatum; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Thalamus

White Matter Abnormalities Track Disease Progression in PSEN1 Autosomal Dominant Alzheimer's Disease. - Sánchez-Valle, Raquel; Monté, Gemma C; Sala-Llonch, Roser; Bosch, Beatriz; Fortea, Juan; Lladó, Albert; Antonell, Anna; Balasa, Mircea; Bargalló, Nuria; Molinuevo, José Luis (J Alzheimers Dis, 2016)
PSEN1 mutations are the most frequent cause of autosomal dominant Alzheimer's disease (ADAD), and show nearly full penetrance. There is presently increasing interest in the study of biomarkers that track disease progression in order to test therapeutic interventions in ADAD. We used white mater (WM) volumetric characteristics and diffusion tensor imaging (DTI) metrics to investigate correlations with the normalized time to expected symptoms onset (relative age ratio) and group differences in a cohort of 36 subjects from PSEN1 ADAD families: 22 mutation carriers, 10 symptomatic (SMC) and 12 asymptomatic (AMC), and 14 non-carriers (NC). Subjects underwent a 3T MRI. WM morphometric data and DTI metrics were analyzed. We found that PSEN1 MC showed significant negative correlation between fractional anisotropy (FA) and the relative age ratio in the genus and body of corpus callosum and corona radiate (p <  0.05 Family-wise error correction (FWE) at cluster level) and positive correlation with mean diffusivity (MD), axial diffusivity (AxD), and radial diffusivity (RD) in the splenium of corpus callosum. SMC presented WM volume loss, reduced FA and increased MD, AxD, and RD in the anterior and posterior corona radiate, corpus callosum (p <  0.05 FWE) compared with NC. No significant differences were observed between AMC and NC in WM volume or DTI measures. These findings suggest that the integrity of the WM deteriorates linearly in PSEN1 ADAD from the early phases of the disease; thus DTI metrics might be useful to monitor the disease progression. However, the lack of significant alterations at the preclinical stages suggests that these indexes might not be good candidates for early markers of the disease.
Keywords: Adult; Aging; Alzheimer Disease; Brain; Cohort Studies; Diffusion Tensor Imaging; Disease Progression; Family; Female; Heterozygote; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Mutation; Neuropsychological Tests; Organ Size; Presenilin-1; White Matter

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Alzheimer's Disease Normative Cerebrospinal Fluid Biomarkers Validated in PET Amyloid-β Characterized Subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study. - Li, Qiao-Xin; Villemagne, Victor L; Doecke, James D; Rembach, Alan; Sarros, Shannon; Varghese, Shiji; McGlade, Amelia; Laughton, Katrina M; Pertile, Kelly K; Fowler, Christopher J; Rumble, Rebecca L; Trounson, Brett O; et al. (J Alzheimers Dis, 2015)
BACKGROUND: The cerebrospinal fluid (CSF) amyloid-β (Aβ)1-42, total-tau (T-tau), and phosphorylated-tau (P-tau181P) profile has been established as a valuable biomarker for Alzheimer's disease (AD). OBJECTIVE: The current study aimed to determine CSF biomarker cut-points using positron emission tomography (PET) Aβ imaging screened subjects from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging, as well as correlate CSF analyte cut-points across a range of PET Aβ amyloid ligands. METHODS: Aβ pathology was determined by PET imaging, utilizing 11C-Pittsburgh Compound B, 18F-flutemetamol, or 18F-florbetapir, in 157 AIBL participants who also underwent CSF collection. Using an INNOTEST assay, cut-points were established (Aβ1-42 >544 ng/L, T-tau <407 ng/L, and P-tau181P <78 ng/L) employing a rank based method to define a "positive" CSF in the sub-cohort of amyloid-PET negative healthy participants (n = 97), and compared with the presence of PET demonstrated AD pathology. RESULTS: CSF Aβ1-42 was the strongest individual biomarker, detecting cognitively impaired PET positive mild cognitive impairment (MCI)/AD with 85% sensitivity and 91% specificity. The ratio of P-tau181P or T-tau to Aβ1-42 provided greater accuracy, predicting MCI/AD with Aβ pathology with ≥92% sensitivity and specificity. Cross-validated accuracy, using all three biomarkers or the ratio of P-tau or T-tau to Aβ1-42 to predict MCI/AD, reached ≥92% sensitivity and specificity. CONCLUSIONS: CSF Aβ1-42 levels and analyte combination ratios demonstrated very high correlation with PET Aβ imaging. Our study offers additional support for CSF biomarkers in the early and accurate detection of AD pathology, including enrichment of patient cohorts for treatment trials even at the pre-symptomatic stage.

Amyloid-β and Tau Dynamics in Human Brain Interstitial Fluid in Patients with Suspected Normal Pressure Hydrocephalus. - Herukka, Sanna-Kaisa; Rummukainen, Jaana; Ihalainen, Jouni; von Und Zu Fraunberg, Mikael; Koivisto, Anne M; Nerg, Ossi; Puli, Lakshman K; Seppälä, Toni T; Zetterberg, Henrik; Pyykkö, Okko T; Helisalmi, Seppo; Tanila, Heikki; et al. (J Alzheimers Dis, 2015)
Background: Amyloid-β (Aβ1-42), total tau (T-tau), and phosphorylated tau (P-tau181) in the cerebrospinal fluid (CSF) are the most promising biomarkers of Alzheimer's disease (AD). Still, little is known about the dynamics of these molecules in the living brain. In a transgenic mouse brain, soluble Aβ decreases with increasing age and advanced Aβ pathology as seen similarly in CSF. Objective: To assess the relationship between AD-related pathological changes in human brain tissue, ventricular and lumbar CSF, and brain interstitial fluid (ISF). Methods: Altogether 11 patients with suspected idiopathic normal pressure hydrocephalus underwent frontal cortical brain biopsy, 24-h intraventricular pressure monitoring, and a microdialysis procedure. AD-related biomarkers were analyzed from brain tissue, CSF, and ISF. Results: ISF T-tau levels decreased strongly within the first 12 h, then plateauing until the end of the experiment. Aβ1-42 and P-tau181 remained stable during the experiment (n = 3). T-tau and P-tau were higher in the ISF than in ventricular or lumbar CSF, while Aβ1-42 levels were within similar range in both CSF and ISF samples. ISF P-tau correlated with the ventricular CSF T-tau (r = 0.70, p = 0.017) and P-tau181 (r = 0.64, p = 0.034). Five patients with amyloid pathology in the brain biopsy tended to reveal lower ISF Aβ1-42 levels than those six without amyloid pathology. Conclusions: This is the first study to report ISF Aβ and tau levels in the human brain without significant brain injury. The set-up used enables sampling from the brain ISF for at least 24 h without causing adverse effects due to the microdialysis procedure to follow the dynamics of the key molecules in AD pathogenesis in the living brain at various stages of the disease.

The APOE Gene is Differentially Methylated in Alzheimer's Disease. - Foraker, Jessica; Millard, Steven P; Leong, Lesley; Thomson, Zachary; Chen, Sunny; Keene, C Dirk; Bekris, Lynn M; Yu, Chang-En (J Alzheimers Dis, 2015)
The ɛ4 allele of the human apolipoprotein E gene (APOE) is a well-proven genetic risk factor for the late onset form of Alzheimer's disease (AD). However, the biological mechanisms through which the ɛ4 allele contributes to disease pathophysiology are incompletely understood. The three common alleles of APOE, ɛ2, ɛ3 and ɛ4, are defined by two single nucleotide polymorphisms (SNPs) that reside in the coding region of exon 4, which overlaps with a well-defined CpG island (CGI). Both SNPs change not only the protein codon but also the quantity of CpG dinucleotides, primary sites for DNA methylation. Thus, we hypothesize that the presence of an ɛ4 allele changes the DNA methylation landscape of the APOE CGI and that such epigenetic alteration contributes to AD susceptibility. To explore the relationship between APOE genotype, AD risk, and DNA methylation of the APOE CGI, we applied bisulfite pyrosequencing and evaluated methylation profiles of postmortem brain from 15 AD and 10 control subjects. We observed a tissue-specific decrease in DNA methylation with AD and identified two AD-specific differentially methylated regions (DMRs), which were also associated with APOE genotype. We further demonstrated that one DMR was completely un-methylated in a sub-population of genomes, possibly due to a subset of brain cells carrying deviated APOE methylation profiles. These data suggest that the APOE CGI is differentially methylated in AD brain in a tissue- and APOE-genotype-specific manner. Such epigenetic alteration might contribute to neural cell dysfunction in AD brain.

A Blood-Based, 7-Metabolite Signature for the Early Diagnosis of Alzheimer's Disease. - Olazarán, Javier; Gil-de-Gómez, Luis; Rodríguez-Martín, Andrés; Valentí-Soler, Meritxell; Frades-Payo, Belén; Marín-Muñoz, Juan; Antúnez, Carmen; Frank-García, Ana; Jiménez, Carmen Acedo; Gracia, Lorenzo Morlén; Torregrossa, Roberto Petidier; Guisasola, María Concepción; et al. (J Alzheimers Dis, 2015)
Accurate blood-based biomarkers of Alzheimer's disease (AD) could constitute simple, inexpensive, and non-invasive tools for the early diagnosis and treatment of this devastating neurodegenerative disease. We sought to develop a robust AD biomarker panel by identifying alterations in plasma metabolites that persist throughout the continuum of AD pathophysiology. Using a multicenter, cross-sectional study design, we based our analysis on metabolites whose levels were altered both in AD patients and in patients with amnestic mild cognitive impairment (aMCI), the earliest identifiable stage of AD. UPLC coupled to mass spectrometry was used to independently compare the levels of 495 plasma metabolites in aMCI (n = 58) and AD (n = 100) patients with those of normal cognition controls (NC, n = 93). Metabolite alterations common to both aMCI and AD patients were used to generate a logistic regression model that accurately distinguished AD from NC patients. The final panel consisted of seven metabolites: three amino acids (glutamic acid, alanine, and aspartic acid), one non-esterified fatty acid (22:6n-3, DHA), one bile acid (deoxycholic acid), one phosphatidylethanolamine [PE(36:4)], and one sphingomyelin [SM(39:1)]. Detailed analysis ruled out the influence of potential confounding variables, including comorbidities and treatments, on each of the seven biomarkers. The final model accurately distinguished AD from NC patients (AUC, 0.918). Importantly, the model also distinguished aMCI from NC patients (AUC, 0.826), indicating its potential diagnostic utility in early disease stages. These findings describe a sensitive biomarker panel that may facilitate the specific detection of early-stage AD through the analysis of plasma samples.

Buccal Cell Cytokeratin 14 Correlates with Multiple Blood Biomarkers of Alzheimer's Disease Risk. - Leifert, Wayne R; Nguyen, Tori; Rembach, Alan; Martins, Ralph; Rainey-Smith, Stephanie; Masters, Colin L; Ames, David; Rowe, Christopher C; Macaulay, S Lance; François, Maxime; Fenech, Michael F (J Alzheimers Dis, 2015)
Mild cognitive impairment (MCI) may reflect early stages of neurodegenerative disorders such as Alzheimer's disease (AD). Our hypothesis was that cytokeratin 14 (CK14) expression could be used with blood-based biomarkers such as homocysteine, vitamin B12, and folate to identify individuals with MCI or AD from the Australian Imaging, Biomarkers and Lifestyle (AIBL) flagship study of aging. Buccal cells from 54 individuals were analyzed by a newly developed method that is rapid, automated, and quantitative for buccal cell CK14 expression levels. CK14 was negatively correlated with plasma Mg2 + and LDL, while positively correlated with vitamin B12, red cell hematocrit/volume, and basophils in the MCI group and positively correlated with insulin and vitamin B12 in the AD group. The combined biomarker panel (CK14 expression, plasma vitamin B12, and homocysteine) was significantly lower in the MCI (p = 0.003) and AD (p = 0.0001) groups compared with controls. Receiver-operating characteristic curves yielded area under the curve (AUC) values of 0.829 for the MCI (p = 0.002) group and 0.856 for the AD (p = 0.0003) group. These complex associations of multiple related parameters highlight the differences between the MCI and AD cohorts and possibly an underlying metabolic pathology associated with the development of early memory impairment. The changes in buccal cell CK14 expression observed in this pilot study supports previous results suggesting the peripheral biomarkers and metabolic changes are not restricted to brain pathology alone in MCI and AD and could prove useful as a potential biomarker in identifying individuals with an increased risk of developing MCI and eventually AD.

Cognitive Effects of Soy Isoflavones in Patients with Alzheimer's Disease. - Gleason, Carey E; Fischer, Barbara L; Dowling, N Maritza; Setchell, Kenneth D R; Atwood, Craig S; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2015)
BACKGROUND: In a previous trial, treatment with soy isoflavones was associated with improved nonverbal memory, construction abilities, verbal fluency, and speeded dexterity compared to treatment with placebo in cognitively healthy older adults. OBJECTIVE: The current trial aimed to examine the potential cognitive benefits of soy isoflavones in patients with Alzheimer's disease. METHODS: Sixty-five men and women over the age of 60 were treated with 100 mg/day soy isoflavones, or matching placebo capsules for six months. APOE genotype was determined for all participants. Cognitive outcomes and plasma isoflavone levels were measured at baseline, and at two additional time points: three and six months after baseline. RESULTS: Of the sixty-five participants enrolled, thirty-four (52.3% ) were women, and 31 (47.7% ) were APOEɛ4 positive. Average age was 76.3 (SD = 7.2) years. Fifty-nine (90.8% ) subjects completed all study visits. Plasma isoflavone levels increased in subjects treated with soy isoflavones compared to baseline and to placebo, although intersubject variability in plasma levels was large. No significant differences in treatment effects for cognition emerged between treatment groups or genders. Exploratory analyses of associations between changes in cognition and plasma isoflavone levels revealed an association between equol levels, and speeded dexterity and verbal fluency. CONCLUSIONS: Six months of 100 mg/day treatment with soy isoflavones did not benefit cognition in older men and women with Alzheimer's disease. However, our results suggest the need to examine the role of isoflavone metabolism, i.e., the ability to effectively metabolize soy isoflavones by converting daidzen to equol when attempting to fully clarify the cognitive effects of isoflavones.

Comprehensive Gene- and Pathway-Based Analysis of Depressive Symptoms in Older Adults. - Nho, Kwangsik; Ramanan, Vijay K; Horgusluoglu, Emrin; Kim, Sungeun; Inlow, Mark H; Risacher, Shannon L; McDonald, Brenna C; Farlow, Martin R; Foroud, Tatiana M; Gao, Sujuan; Callahan, Christopher M; Hendrie, Hugh C; et al. (J Alzheimers Dis, 2015)
Depressive symptoms are common in older adults and are particularly prevalent in those with or at elevated risk for dementia. Although the heritability of depression is estimated to be substantial, single nucleotide polymorphism-based genome-wide association studies of depressive symptoms have had limited success. In this study, we PERFORMED genome-wide gene- and pathway-based analyses of depressive symptom burden. Study participants included non-Hispanic Caucasian subjects (n = 6,884) from three independent cohorts, the Alzheimer's Disease Neuroimaging Initiative (ADNI), the Health and Retirement Study (HRS), and the Indiana Memory and Aging Study (IMAS). Gene-based meta-analysis identified genome-wide significant associations (ANGPT4 and FAM110A, q-value = 0.026; GRM7-AS3 and LRFN5, q-value = 0.042). Pathway analysis revealed enrichment of association in 105 pathways, including multiple pathways related to ERK/MAPK signaling, GSK3 signaling in bipolar disorder, cell development, and immune activation and inflammation. GRM7, ANGPT4, and LRFN5 have been previously implicated in psychiatric disorders, including the GRM7 region displaying association with major depressive disorder. The ERK/MAPK signaling pathway is a known target of antidepressant drugs and has important roles in neuronal plasticity, and GSK3 signaling has been previously implicated in Alzheimer's disease and as a promising therapeutic target for depression. Our results warrant further investigation in independent and larger cohorts and add to the growing understanding of the genetics and pathobiology of depressive symptoms in aging and neurodegenerative disorders. In particular, the genes and pathways demonstrating association with depressive symptoms may be potential therapeutic targets for these symptoms in older adults.

The Continuing Failure of Bexarotene in Alzheimer's Disease Mice. - Balducci, Claudia; Paladini, Alessandra; Micotti, Edoardo; Tolomeo, Daniele; La Vitola, Pietro; Grigoli, Emanuele; Richardson, Jill C; Forloni, Gianluigi (J Alzheimers Dis, 2015)
Alzheimer's disease (AD) is the most common form of dementia characterized by synaptic dysfunction, memory loss, neuroinflammation, and neuronal cell death. Amyloid-β (Aβ), recognized as the main culprit of AD, aggregates and accumulates in the extracellular compartment as neuritic plaques, after deregulation of its production or clearance. Apolipoprotein E (ApoE) plays a major role in Aβ clearance and its expression is transcriptionally regulated by the liver X receptor and retinoid X receptors (RXRs) system. Bexarotene (BEXA), an RXR agonist, that increases ApoE expression and microglia phagocytosis and has been proposed as a promising therapy for AD, resolving both the amyloid pathology and memory loss. Despite the first compelling report, however, multiple failures have been documented, raising concern about whether BEXA could in fact become a novel disease-modifying strategy for AD. To help clarify this, we investigated the effect of BEXA in vivo at multiple levels in TASTPM transgenic mice. Seven-day oral administration of BEXA to these mice did not achieve any significant memory improvement, plaque reduction, or enhancement of microglial cell activation. No differences were found when specifically investigating the microglial phagocytic state in vivo. In addition, a brain structural analysis with magnetic resonance did not detect any BEXA-mediated change in the volume reduction of the main affected brain areas in our mice. These results suggest that BEXA has no beneficial effect on the multi-factorial pathologic phenotype of AD mice.

Depression and Suicidal Ideation During Two Psychosocial Treatments in Older Adults with Major Depression and Dementia. - Kiosses, Dimitris N; Rosenberg, Paul B; McGovern, Amanda; Fonzetti, Pasquale; Zaydens, Hana; Alexopoulos, George S (J Alzheimers Dis, 2015)
BACKGROUND: Depression is prevalent in dementia and contributes to poor outcomes for patients and their families. Antidepressants have limited efficacy in older adults with major depression and dementia, and psychosocial interventions are under-investigated. OBJECTIVE: To examine the course, predictors and moderators of depression and suicidal ideation during 12 weeks of home-delivered Problem Adaptation Therapy (PATH) versus Supportive Therapy for Cognitively Impaired Older Adults (ST-CI) in 39 older adults with major depression and dementia. METHODS: Thirty-nine older adults with major depression, mild or moderate dementia, and disability participated in a randomized controlled trial that compared the efficacy of PATH versus ST-CI. Depression and suicidal ideation were assessed with Cornell Scale for Depression in Dementia Total Score and Suicide Item. RESULTS: PATH participants had significantly greater reduction in depression than ST-CI participants over 12 weeks of treatment. PATH participants with high social support had the greatest reduction in depression. Both treatments had comparable reduction in suicidal ideation. CONCLUSION: PATH is more effective in reducing depression in older adults with major depression and dementia compared to ST-CI. These results are clinically significant as antidepressants have limited efficacy in this population. Home-delivered psychosocial treatments may reduce suicidal ideation in this population.

The GLP-1 Receptor Agonist Liraglutide Improves Memory Function and Increases Hippocampal CA1 Neuronal Numbers in a Senescence-Accelerated Mouse Model of Alzheimer's Disease. - Hansen, Henrik H; Fabricius, Katrine; Barkholt, Pernille; Niehoff, Michael L; Morley, John E; Jelsing, Jacob; Pyke, Charles; Bjerre Knudsen, Lotte; Farr, Susan A; Vrang, Niels (J Alzheimers Dis, 2015)
Recent studies indicate that glucagon-like peptide 1 (GLP-1) receptor agonists, currently used in the management of type 2 diabetes, exhibit neurotrophic and neuroprotective effects in amyloid-β (Aβ) toxicity models of Alzheimer's disease (AD). We investigated the potential pro-cognitive and neuroprotective effects of the once-daily GLP-1 receptor agonist liraglutide in senescence-accelerated mouse prone 8 (SAMP8) mice, a model of age-related sporadic AD not dominated by Aβ plaques. Six-month-old SAMP8 mice received liraglutide (100 or 500 μg/kg/day, s.c.) or vehicle once daily for 4 months. Vehicle-dosed age-matched 50% back-crossed as well as untreated young (4-month-old) SAMP8 mice were used as control groups for normal memory function. Vehicle-dosed 10-month-old SAMP8 mice showed significant learning and memory retention deficits in an active-avoidance T-maze, as compared to both control groups. Also, 10-month-old SAMP8 mice displayed no immunohistological signatures of Aβ plaques or hyperphosphorylated tau, indicating the onset of cognitive deficits prior to deposition of amyloid plaques and neurofibrillary tangles in this AD model. Liraglutide significantly increased memory retention and total hippocampal CA1 pyramidal neuron numbers in SAMP8 mice, as compared to age-matched vehicle-dosed SAMP8 mice. In conclusion, liraglutide delayed or partially halted the progressive decline in memory function associated with hippocampal neuronal loss in a mouse model of pathological aging with characteristics of neurobehavioral and neuropathological impairments observed in early-stage sporadic AD.

Mapping the Progression of Atrophy in Early- and Late-Onset Alzheimer's Disease. - Migliaccio, Raffaella; Agosta, Federica; Possin, Katherine L; Canu, Elisa; Filippi, Massimo; Rabinovici, Gil D; Rosen, Howard J; Miller, Bruce L; Gorno-Tempini, Maria Luisa (J Alzheimers Dis, 2015)
The term early-onset Alzheimer's disease (EOAD) identifies patients who meet criteria for AD, but show onset of symptoms before the age of 65. We map progression of gray matter atrophy in EOAD patients compared to late-onset AD (LOAD). T1-weighted MRI scans were obtained at diagnosis and one-year follow-up from 15 EOAD, 10 LOAD, and 38 age-matched controls. Voxel-based and tensor-based morphometry were used, respectively, to assess the baseline and progression of atrophy. At baseline, EOAD patients already showed a widespread atrophy in temporal, parietal, occipital, and frontal cortices. After one year, EOAD had atrophy progression in medial temporal and medial parietal cortices. At baseline, LOAD patients showed atrophy in the medial temporal regions only, and, after one year, an extensive pattern of atrophy progression in the same neocortical cortices of EOAD. Although atrophy mainly involved different lateral neocortical or medial temporal hubs at baseline, it eventually progressed along the same brain default-network regions in both groups. The cortical region showing a significant progression in both groups was the medial precuneus/posterior cingulate.

A Phase II Randomized Clinical Trial of a Nutritional Formulation for Cognition and Mood in Alzheimer's Disease. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Doshanjh, Laura; Fishman, Paul; Luo, Yuan; Smyers, Kathleen; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2015)
Background: Increasing evidence points toward the efficacy of nutritional modifications in delaying cognitive decline and mood/behavioral difficulties in Alzheimer's disease (AD). Nutritional supplementation with individual agents has shown varied results suggesting the need for combinatorial intervention. Objective: We set out to determine whether nutritional intervention could positively impact cognitive performance and behavioral difficulties for individuals diagnosed with AD. Methods: A double-blind, multi-site, phase II study (ClinicalTrials.gov NCT01320527; Alzheimer's Association Trialmatch) was conducted in which 106 individuals with AD were randomized to a nutraceutical formulation (NF; folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) or placebo for 3 or 6 months, followed by an open-label extension where participants received NF for 6 additional months. Results: The NF cohort improved versus the placebo cohort within 3 months (Clox-1 p = 0.0083, 95%CI [0.4481, 2.9343]; Dementia Rating Scale p = 0.0266, 95%CI [0.1722, 2.7171]). Caregivers reported non-significant improvements in Neuropsychiatric Inventory. Both cohorts improved or maintained baseline performance during open-label extensions. Activities of Daily Living did not change for either cohort. Conclusions: These findings extend phase I studies where NF maintained or improved cognitive performance and mood/behavior.

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

Phase 3 trials of solanezumab for mild-to-moderate Alzheimer's disease. - Doody, Rachelle S; Thomas, Ronald G; Farlow, Martin; Iwatsubo, Takeshi; Vellas, Bruno; Joffe, Steven; Kieburtz, Karl; Raman, Rema; Sun, Xiaoying; Aisen, Paul S; Siemers, Eric; Liu-Seifert, Hong; et al. (N Engl J Med, 2014)
BACKGROUND: Alzheimer's disease is characterized by amyloid-beta plaques, neurofibrillary tangles, gliosis, and neuronal loss. Solanezumab, a humanized monoclonal antibody, preferentially binds soluble forms of amyloid and in preclinical studies promoted its clearance from the brain. METHODS: In two phase 3, double-blind trials (EXPEDITION 1 and EXPEDITION 2), we randomly assigned 1012 and 1040 patients, respectively, with mild-to-moderate Alzheimer's disease to receive placebo or solanezumab (administered intravenously at a dose of 400 mg) every 4 weeks for 18 months. The primary outcomes were the changes from baseline to week 80 in scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11; range, 0 to 70, with higher scores indicating greater cognitive impairment) and the Alzheimer's Disease Cooperative Study-Activities of Daily Living scale (ADCS-ADL; range, 0 to 78, with lower scores indicating worse functioning). After analysis of data from EXPEDITION 1, the primary outcome for EXPEDITION 2 was revised to the change in scores on the 14-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog14; range, 0 to 90, with higher scores indicating greater impairment), in patients with mild Alzheimer's disease. RESULTS: Neither study showed significant improvement in the primary outcomes. The modeled difference between groups (solanezumab group minus placebo group) in the change from baseline was -0.8 points for the ADAS-cog11 score (95% confidence interval [CI], -2.1 to 0.5; P=0.24) and -0.4 points for the ADCS-ADL score (95% CI, -2.3 to 1.4; P=0.64) in EXPEDITION 1 and -1.3 points (95% CI, -2.5 to 0.3; P=0.06) and 1.6 points (95% CI, -0.2 to 3.3; P=0.08), respectively, in EXPEDITION 2. Between-group differences in the changes in the ADAS-cog14 score were -1.7 points in patients with mild Alzheimer's disease (95% CI, -3.5 to 0.1; P=0.06) and -1.5 in patients with moderate Alzheimer's disease (95% CI, -4.1 to 1.1; P=0.26). In the combined safety data set, the incidence of amyloid-related imaging abnormalities with edema or hemorrhage was 0.9% with solanezumab and 0.4% with placebo for edema (P=0.27) and 4.9% and 5.6%, respectively, for hemorrhage (P=0.49). CONCLUSIONS: Solanezumab, a humanized monoclonal antibody that binds amyloid, failed to improve cognition or functional ability. (Funded by Eli Lilly; EXPEDITION 1 and 2 ClinicalTrials.gov numbers, NCT00905372 and NCT00904683.).
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Cognition; Double-Blind Method; Female; Humans; Intention to Treat Analysis; Male; Neuropsychological Tests; Severity of Illness Index; tau Proteins; Treatment Failure

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Integrated systems approach identifies genetic nodes and networks in late-onset Alzheimer's disease. - Zhang, Bin; Gaiteri, Chris; Bodea, Liviu-Gabriel; Wang, Zhi; McElwee, Joshua; Podtelezhnikov, Alexei A; Zhang, Chunsheng; Xie, Tao; Tran, Linh; Dobrin, Radu; Fluder, Eugene; Clurman, Bruce; et al. (Cell, 2013)
The genetics of complex disease produce alterations in the molecular interactions of cellular pathways whose collective effect may become clear through the organized structure of molecular networks. To characterize molecular systems associated with late-onset Alzheimer's disease (LOAD), we constructed gene-regulatory networks in 1,647 postmortem brain tissues from LOAD patients and nondemented subjects, and we demonstrate that LOAD reconfigures specific portions of the molecular interaction structure. Through an integrative network-based approach, we rank-ordered these network structures for relevance to LOAD pathology, highlighting an immune- and microglia-specific module that is dominated by genes involved in pathogen phagocytosis, contains TYROBP as a key regulator, and is upregulated in LOAD. Mouse microglia cells overexpressing intact or truncated TYROBP revealed expression changes that significantly overlapped the human brain TYROBP network. Thus the causal network structure is a useful predictor of response to gene perturbations and presents a framework to test models of disease mechanisms underlying LOAD.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Animals; Bayes Theorem; Brain; Gene Regulatory Networks; Humans; Membrane Proteins; Mice; Microglia

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

Exercise Engagement as a Moderator of the Effects of APOE Genotype on Amyloid Deposition. - Head, Denise; Bugg, Julie M; Goate, Alison M; Fagan, Anne M; Mintun, Mark A; Benzinger, Tammie; Holtzman, David M; Morris, John C (Arch Neurol, 2012)
OBJECTIVE: APOE ε4 status has been associated with greater cortical amyloid deposition, whereas exercise has been associated with less in cognitively normal adults. The primary objective here was to examine whether physical exercise moderates the association between APOE genotype and amyloid deposition in cognitively normal adults. DESIGN: APOE genotyping data and answers to a questionnaire on physical exercise engagement over the last decade were obtained in conjunction with cerebrospinal fluid (CSF) samples and amyloid imaging with carbon 11-labeled Pittsburgh Compound B ([(11)C]PiB) positron emission tomography. Participants were classified as either low or high exercisers based on exercise guidelines of the American Heart Association. SETTING: Knight Alzheimer's Disease Research Center at Washington University, St Louis, Missouri. PARTICIPANTS: A total of 201 cognitively normal adults (135 of whom were women) aged 45 to 88 years were recruited from the Knight Alzheimer's Disease Research Center. Samples of CSF were collected from 165 participants. Amyloid imaging was performed for 163 participants. RESULTS: APOE ε4 carriers evidenced higher [(11)C]PiB binding (P<.001) and lower CSF Aβ42 levels (P<.001) than did noncarriers. Our previous findings of higher [(11)C]PiB binding (P=.005) and lower CSF Aβ42 levels (P=.009) in more sedentary individuals were replicated. Most importantly, we observed a novel interaction between APOE status and exercise engagement for [(11)C]PiB binding (P=.008) such that a more sedentary lifestyle was significantly associated with higher [(11)C]PiB binding for ε4 carriers (P=.013) but not for noncarriers (P=.20). All findings remained significant after controlling for age; sex; educational level; body mass index; the presence or history of hypertension, diabetes mellitus, heart problems, or depression; and the interval between assessments. CONCLUSION: Collectively, these results suggest that cognitively normal sedentary APOE ε4-positive individuals may be at augmented risk for cerebral amyloid deposition.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Brain; Cognition; Cohort Studies; Exercise; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Positron-Emission Tomography; Regression Analysis; Surveys and Questionnaires; Thiazoles

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

18F-THK523: a novel in vivo tau imaging ligand for Alzheimer's disease. - Fodero-Tavoletti, Michelle T; Okamura, Nobuyuki; Furumoto, Shozo; Mulligan, Rachel S; Connor, Andrea R; McLean, Catriona A; Cao, Diana; Rigopoulos, Angela; Cartwright, Glenn A; O'Keefe, Graeme; Gong, Sylvia; Adlard, Paul A; et al. (Brain, 2011)
While considerable effort has focused on developing positron emission tomography β-amyloid imaging radiotracers for the early diagnosis of Alzheimer's disease, no radiotracer is available for the non-invasive quantification of tau. In this study, we detail the characterization of (18)F-THK523 as a novel tau imaging radiotracer. In vitro binding studies demonstrated that (18)F-THK523 binds with higher affinity to a greater number of binding sites on recombinant tau (K18Δ280K) compared with β-amyloid(1-42) fibrils. Autoradiographic and histofluorescence analysis of human hippocampal serial sections with Alzheimer's disease exhibited positive THK523 binding that co-localized with immunoreactive tau pathology, but failed to highlight β-amyloid plaques. Micro-positron emission tomography analysis demonstrated significantly higher retention of (18)F-THK523 (48%; P < 0.007) in tau transgenic mice brains compared with their wild-type littermates or APP/PS1 mice. The preclinical examination of THK523 has demonstrated its high affinity and selectivity for tau pathology both in vitro and in vivo, indicating that (18)F-THK523 fulfils ligand criteria for human imaging trials.
Keywords: Alzheimer Disease; Analysis of Variance; Aniline Compounds; Animals; Autoradiography; Binding Sites; Brain; Female; Fluorodeoxyglucose F18; Humans; Immunohistochemistry; Male; Mice; Quinolines; Radiopharmaceuticals; tau Proteins

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Directed conversion of Alzheimer's disease patient skin fibroblasts into functional neurons. - Qiang, Liang; Fujita, Ryousuke; Yamashita, Toru; Angulo, Sergio; Rhinn, Herve; Rhee, David; Doege, Claudia; Chau, Lily; Aubry, Laetitia; Vanti, William B; Moreno, Herman; Abeliovich, Asa (Cell, 2011)
Directed conversion of mature human cells, as from fibroblasts to neurons, is of potential clinical utility for neurological disease modeling as well as cell therapeutics. Here, we describe the efficient generation of human-induced neuronal (hiN) cells from adult skin fibroblasts of unaffected individuals and Alzheimer's patients, using virally transduced transcription regulators and extrinsic support factors. hiN cells from unaffected individuals display morphological, electrophysiological, and gene expression profiles that typify glutamatergic forebrain neurons and are competent to integrate functionally into the rodent CNS. hiN cells from familial Alzheimer disease (FAD) patients with presenilin-1 or -2 mutations exhibit altered processing and localization of amyloid precursor protein (APP) and increased production of Aβ, relative to the source patient fibroblasts or hiN cells from unaffected individuals. Together, our findings demonstrate directed conversion of human fibroblasts to a neuronal phenotype and reveal cell type-selective pathology in hiN cells derived from FAD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Cell Transdifferentiation; Cells, Cultured; Fibroblasts; Humans; Neurons; Presenilin-1; Presenilin-2; Regenerative Medicine; Skin

Human apoE isoforms differentially regulate brain amyloid-β peptide clearance. - Castellano, Joseph M; Kim, Jungsu; Stewart, Floy R; Jiang, Hong; DeMattos, Ronald B; Patterson, Bruce W; Fagan, Anne M; Morris, John C; Mawuenyega, Kwasi G; Cruchaga, Carlos; Goate, Alison M; Bales, Kelly R; et al. (Sci Transl Med, 2011)
The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late-onset, sporadic Alzheimer's disease (AD). The APOE ε4 allele markedly increases AD risk and decreases age of onset, likely through its strong effect on the accumulation of amyloid-β (Aβ) peptide. In contrast, the APOE ε2 allele appears to decrease AD risk. Most rare, early-onset forms of familial AD are caused by autosomal dominant mutations that often lead to overproduction of Aβ(42) peptide. However, the mechanism by which APOE alleles differentially modulate Aβ accumulation in sporadic, late-onset AD is less clear. In a cohort of cognitively normal individuals, we report that reliable molecular and neuroimaging biomarkers of cerebral Aβ deposition vary in an apoE isoform-dependent manner. We hypothesized that human apoE isoforms differentially affect Aβ clearance or synthesis in vivo, resulting in an apoE isoform-dependent pattern of Aβ accumulation later in life. Performing in vivo microdialysis in a mouse model of Aβ-amyloidosis expressing human apoE isoforms (PDAPP/TRE), we find that the concentration and clearance of soluble Aβ in the brain interstitial fluid depends on the isoform of apoE expressed. This pattern parallels the extent of Aβ deposition observed in aged PDAPP/TRE mice. ApoE isoform-dependent differences in soluble Aβ metabolism are observed not only in aged but also in young PDAPP/TRE mice well before the onset of Aβ deposition in amyloid plaques in the brain. Additionally, amyloidogenic processing of amyloid precursor protein and Aβ synthesis, as assessed by in vivo stable isotopic labeling kinetics, do not vary according to apoE isoform in young PDAPP/TRE mice. Our results suggest that APOE alleles contribute to AD risk by differentially regulating clearance of Aβ from the brain, suggesting that Aβ clearance pathways may be useful therapeutic targets for AD prevention.
Keywords: Adult; Aged; Alleles; Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoprotein E4; Biomarkers; Brain; Female; Genotype; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Middle Aged; Protein Isoforms

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric

APOE predicts amyloid-beta but not tau Alzheimer pathology in cognitively normal aging. - Morris, John C; Roe, Catherine M; Xiong, Chengjie; Fagan, Anne M; Goate, Alison M; Holtzman, David M; Mintun, Mark A (Ann Neurol, 2010)
OBJECTIVE: To examine interactions of apolipoprotein E (APOE) genotype with age and with in vivo measures of preclinical Alzheimer disease (AD) in cognitively normal aging. METHODS: Two hundred forty-one cognitively normal individuals, aged 45-88 years, had cerebral amyloid imaging studies with Pittsburgh Compound-B (PIB). Of the 241 individuals, 168 (70%) also had cerebrospinal fluid (CSF) assays of amyloid-beta(42) (Abeta(42)), tau, and phosphorylated tau (ptau(181)). All individuals were genotyped for APOE. RESULTS: The frequency of individuals with elevated mean cortical binding potential (MCBP) for PIB rose in an age-dependent manner from 0% at ages 45-49 years to 30.3% at 80-88 years. Reduced levels of CSF Abeta(42) appeared to begin earlier (18.2% of those aged 45-49 years) and increase with age in higher frequencies (50% at age 80-88 years) than elevations of MCBP. There was a gene dose effect for the APOE4 genotype, with greater MCBP increases and greater reductions in CSF Abeta(42) with increased numbers of APOE4 alleles. Individuals with an APOE2 allele had no increase in MCBP with age and had higher CSF Abeta(42) levels than individuals without an APOE2 allele. There was no APOE4 or APOE2 effect on CSF tau or ptau(181). INTERPRETATION: Increasing cerebral Abeta deposition with age is the pathobiological phenotype of APOE4. The biomarker sequence that detects Abeta deposition may first be lowered CSF Abeta(42), followed by elevated MCBP for PIB. A substantial proportion of cognitively normal individuals have presumptive preclinical AD.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; Brain; Female; Follow-Up Studies; Genotype; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins; Thiazoles

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide